The aging and dying processes and the health of older adults. - Diehr, Paula; Williamson, Jeff; Burke, Gregory L; Psaty, Bruce M (J Clin Epidemiol, 2002)
It is difficult to distinguish changes in health due to aging from those related to dying, because the two processes are highly related. Some potentially treatable conditions may mistakenly be dismissed as due to old age. The goal of this article was to examine the relationships of aging and of dying to changes in 10 health-related variables: self-rated health, depression, ADLs, IADLs, minimental state examination, body mass index, blocks walked per week, bed days, hospitalization, and walking speed (all coded so that higher values were better). We used longitudinal data from the Cardiovascular Health Study to estimate the changes in the variables associated with 5 years of aging and also in the 5 years before death, controlling for years from death and for age, respectively. All 10 health variables declined as death approached, and most of them also declined with age. The "effect" of the dying process was usually significantly larger than the effect of aging. Large declines in these health measures are probably not due to aging, and should be taken seriously by patients and their providers.
Keywords: Aged; Aging; Death; Female; Health Status Indicators; Humans; Linear Models; Longitudinal Studies; Male; Muscular Atrophy

Angiotensin II type 1 receptor polymorphisms in the cardiovascular health study: relation to blood pressure, ethnicity, and cardiovascular events. - Hindorff, Lucia A; Heckbert, Susan R; Tracy, Russell; Tang, Zhonghua; Psaty, Bruce M; Edwards, Karen L; Siscovick, David S; Kronmal, Richard A; Nazar-Stewart, Valle (Am J Hypertens, 2002)
BACKGROUND: The angiotensin II type 1 receptor A1166C polymorphism has been associated with increased risks of hypertension and myocardial infarction in several small studies. We examined the association between this polymorphism and new-onset hypertension, blood pressure (BP) control, and incident cardiovascular events in a large population-based cohort of older adults. METHODS: Eight hundred self-identified African Americans and 1,371 randomly selected white participants in the Cardiovascular Health Study were genotyped. The median duration of follow-up was 8.1 years. RESULTS: The A1166C polymorphism was not associated with new-onset hypertension, with BP control, or with incident cardiovascular events in the overall population. In white participants, the CC genotype was associated with higher baseline systolic BP and pulse pressure, compared to the AC or AA genotype. In whites with treated hypertension at baseline, compared to the AA genotype, the CC genotype was associated with increased risks of incident congestive heart failure (hazard ratio = 2.5, 95% confidence interval [CI] 1.3-4.9) and incident ischemic stroke (hazard ratio = 2.6, 95% CI 1.1-6.0). These associations were not observed among white participants without treated hypertension, but the interaction of genotype with treated hypertension on ischemic stroke and heart failure was only marginally significant. CONCLUSIONS: On the whole, in this large cohort of older adults, the A1166C polymorphism was not associated with BP control or incident cardiovascular events. The subgroup findings in treated hypertensives need to be confirmed in additional studies.
Keywords: African Continental Ancestry Group; Aged; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Gene Frequency; Humans; Hypertension; Male; Polymorphism, Genetic; Receptor, Angiotensin, Type 1; Receptors, Angiotensin; United States

Calcium channel blocker use and gastrointestinal tract bleeding among older adults. - Kaplan, Robert C; Heckbert, Susan R; Koepsell, Thomas D; Rosendaal, Frits R; Furberg, Curt D; Cooper, Lawton S; Psaty, Bruce M (Age Ageing, 2002)
Keywords: Aged; Antihypertensive Agents; Calcium Channel Blockers; Gastrointestinal Hemorrhage; Geriatric Assessment; Health Services for the Aged; Humans; Hypertension; Prospective Studies; Risk Factors

Cardiovascular disease risk status in elderly persons with renal insufficiency. - Shlipak, Michael G; Fried, Linda F; Crump, Casey; Bleyer, Anthony J; Manolio, Teri A; Tracy, Russell P; Furberg, Curt D; Psaty, Bruce M (Kidney Int, 2002)
BACKGROUND: Renal insufficiency has been independently associated with incident cardiovascular disease events in some, but not all, prospective studies. We determined the prevalence of elevated cardiovascular disease risk status among elderly persons with renal insufficiency. METHODS: This study is a cross-sectional analysis using data collected at the baseline visit of the Cardiovascular Health Study, which enrolled 5888 community dwelling adults aged 65 years or older from four clinical centers in the United States. Renal insufficiency was defined as a serum creatinine level > or =1.3 mg/dL in women and > or =1.5 mg/dL in men. The outcomes of this study included prevalent cardiovascular disease [prior coronary heart disease (CHD) or stroke], subclinical cardiovascular disease (abnormal values of ankle-arm index, carotid ultrasound, and echocardiography) and elevated cardiovascular risk based upon a diagnosis of diabetes and the Framingham equations. The association between renal insufficiency and cardiovascular risk status was estimated with and without adjustment for other cardiovascular predictors. RESULTS: Among the 5808 participants with creatinine levels measured at entry, 15.9% of men (N = 394), and 7.6% of women (N = 254) had renal insufficiency. The prevalence of either clinical or subclinical cardiovascular disease was 64% in persons with renal insufficiency compared with 43% in those without it [odds ratio (OR) 2.34; 95% confidence interval (95% CI), 1.96, 2.80]. After adjustment for other cardiovascular risk factors, renal insufficiency remained significantly associated with clinical and subclinical cardiovascular disease (adjusted OR 1.43; 95% CI, 1.18, 1.75), but the magnitude of association was substantially reduced. After combining clinical and subclinical cardiovascular disease, diabetes, and an estimated risk>20% by the Framingham equations, 78% of men and 61% of women with renal insufficiency had elevated cardiovascular risk status. CONCLUSIONS: Renal insufficiency is a marker for elevated cardiovascular disease risk in community dwelling elderly adults.
Keywords: Age Distribution; Aged; Cholesterol, HDL; Cholesterol, LDL; Coronary Disease; Creatinine; Cross-Sectional Studies; Female; Humans; Kidney Failure, Chronic; Male; Prevalence; Prospective Studies; Risk Factors

Fasting and 2-hour postchallenge serum glucose measures and risk of incident cardiovascular events in the elderly: the Cardiovascular Health Study. - Smith, Nicholas L; Barzilay, Joshua I; Shaffer, Douglas; Savage, Peter J; Heckbert, Susan R; Kuller, Lewis H; Kronmal, Richard A; Resnick, Helaine E; Psaty, Bruce M (Arch Intern Med, 2002)
BACKGROUND: The contributions of fasting and 2-hour postchallenge glucose level to cardiovascular events remain ill-defined, especially for nondiabetic adults. This study examined the relative predictive power of fasting and 2-hour glucose level on cardiovascular event risk. METHODS: A total of 4014 community-dwelling adults 65 years or older who participated in the baseline visit of the Cardiovascular Health Study and who were without treated diabetes or previous myocardial infarction or stroke were eligible for analyses. Participants with treated diabetes at baseline were excluded. Incident myocardial infarction or stroke, or coronary death, was the outcome of interest. Age-, sex-, and race-adjusted proportional hazards regression models described individual and joint associations between baseline measures of fasting and 2-hour postchallenge glucose level and event risk. RESULTS: There were 764 incident cardiovascular events during 8.5 years of follow-up. Fasting glucose level of 115 mg/dL (6.4 mmol/L) or more was associated with an increased cardiovascular risk (hazard ratio [HR], 1.66 [95% confidence interval (CI), 1.39-1.98]) in adjusted analyses compared with fasting glucose level less than 115 mg/dL. Two-hour glucose level was associated with a linear risk (HR, 1.02 [95% CI, 1.00-1.04] per 10 mg/dL [0.6 mmol/L]) that included an additional increase in risk for 2-hour glucose level of 154 mg/dL (8.5 mmol/L) or more (HR, 1.29 [95% CI, 1.04-1.59]) in adjusted analyses. In joint fasting and 2-hour glucose models, only 2-hour glucose level remained predictive of event risk. CONCLUSIONS: Two-hour glucose level was better than fasting glucose level alone at identifying older adults at increased risk of major incident cardiovascular events.
Keywords: Aged; Blood Glucose; Cardiovascular Diseases; Fasting; Female; Glucose Tolerance Test; Humans; Male; Myocardial Infarction; Predictive Value of Tests; Proportional Hazards Models; Risk Assessment; Stroke

Glucose, blood pressure, and lipid control in older people with and without diabetes mellitus: the Cardiovascular Health Study. - Smith, Nicholas L; Savage, Peter J; Heckbert, Susan R; Barzilay, Joshua I; Bittner, Vera A; Kuller, Lewis H; Psaty, Bruce M (J Am Geriatr Soc, 2002)
OBJECTIVES: To determine the prevalence of cardiovascular risk-factor treatment and control in older adults with normal fasting glucose, impaired fasting glucose, and diabetes mellitus and whether those with diabetes mellitus had better risk factor control than older adults with normal fasting glucose. DESIGN: Secondary analysis of data from population-based, prospective cohort study of risk factors for cardio-vascular and cerebrovascular disease in older people (Cardiovascular Health Study). SETTING: Community-based. PARTICIPANTS: Community-dwelling adults aged 65 and older. MEASUREMENTS: Fasting plasma glucose, serum cholesterol and its subfractions, systolic and diastolic blood pressures, and body mass index. RESULTS: There were 579 (18%) cohort members with diabetes mellitus (77% receiving antidiabetic medication, 23% with fasting glucose > or =126 mg/dL and no treatment), 213 (6%) with impaired fasting glucose, and 2,582 (77%)with normal fasting glucose. Of diabetic participants, 12% had recommended fasting glucose levels of less than 110 mg/dL. Of participants with hypertension, a larger proportion of diabetic participants than nondiabetic participants (89% versus 75%, P < .01) was treated with antihypertensive agents, but a smaller proportion of diabetic participants had recommended blood pressure levels of 129/85 mmHg or lower than nondiabetic participants had recommended blood pressure levels of 139/89 mmHg or lower (27% vs 48%, P < .01). Diabetic dyslipidemic participants were treated less often with lipid-lowering therapy (26% versus 55%, P < .01) and achieved recommended low-density lipoprotein goals less often (8%versus 54%, P < .01) than nondiabetic dyslipidemic participants. CONCLUSIONS: Overall, treatment and control of cardiovascular risk factors were suboptimal in this older population, especially among those with diabetes mellitus. Optimizing risk-factor control can improve health outcomes in older adults with and without diabetes mellitus.
Keywords: Age Factors; Aged; Blood Glucose; Blood Pressure; Cardiovascular Diseases; Cholesterol, LDL; Cross-Sectional Studies; Diabetes Complications; Diabetes Mellitus; Female; Humans; Male; Prevalence; Prospective Studies; Risk Factors

A regression model for longitudinal change in the presence of measurement error. - Yanez, N David; Kronmal, Richard A; Shemanski, Lynn R; Psaty, Bruce M (Ann Epidemiol, 2002)
PURPOSE: The analysis of change in measured variables has become quite popular in studies where data are collected repeatedly over time. The authors describe some of the potential pitfalls in the analysis of change when the variable for change is measured with error. They show that regression analysis is often biased, possibly leading to erroneous results. METHODS: A simple method to correct for measurement error bias in regression models that model change is presented. RESULTS AND CONCLUSIONS: The two examples illustrate how measurement error can adversely affect an analysis. The bias-corrected approach yields valid results.
Keywords: Aged; Bias; Coronary Disease; Humans; Lipoproteins; Models, Statistical; Regression Analysis; Risk Factors

Therapy with hydroxymethylglutaryl coenzyme a reductase inhibitors (statins) and associated risk of incident cardiovascular events in older adults: evidence from the Cardiovascular Health Study. - Lemaitre, Rozenn N; Psaty, Bruce M; Heckbert, Susan R; Kronmal, Richard A; Newman, Anne B; Burke, Gregory L (Arch Intern Med, 2002)
BACKGROUND: Recommendations to treat older adults with hydroxymethylglutaryl coenzyme A reductase inhibitors (statins) for the primary prevention of coronary heart disease events are supported by a single clinical trial restricted to adults 73 years or younger with low levels of high-density lipoprotein cholesterol. METHODS: We investigated the association of statin use with incident cardiovascular disease and all-cause mortality during up to 7.3 years' follow-up of 1250 women and 664 men from the Cardiovascular Health Study. Study participants were 65 years and older and free of cardiovascular disease at baseline. They received drug therapy to lower cholesterol levels at baseline or no treatment with a recommendation for therapy according to the National Cholesterol Education Program guidelines. Use of these drugs was assessed annually. We used proportional-hazards models to calculate hazard ratios (HRs) and 95% confidence intervals (CIs), adjusted for confounding variables. RESULTS: We found 382 incident cardiovascular events (159 myocardial infarctions, 159 strokes, and 64 deaths due to coronary heart disease) and 362 total deaths from June 1, 1989, to May 31, 1997. Compared with no use of drugs to lower cholesterol levels, statin use was associated with decreased risk of cardiovascular events (multivariate HR, 0.44; 95% CI, 0.27-0.71) and all-cause mortality (HR, 0.56; 95% CI, 0.36-0.88). Similar associations were observed among participants 74 years or older at baseline. CONCLUSIONS: Use of statins was associated with decreased risk of incident cardiovascular events among elderly adults. These findings lend support to the National Cholesterol Education Program guidelines, which recommend therapy for the lowering of cholesterol levels for older adults with hypercholesterolemia.
Keywords: Aged; Cholesterol, LDL; Coronary Disease; Female; Follow-Up Studies; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hypercholesterolemia; Hypolipidemic Agents; Incidence; Male; Multivariate Analysis; Proportional Hazards Models; Risk Factors; United States

Time trends in high blood pressure control and the use of antihypertensive medications in older adults: the Cardiovascular Health Study. - Psaty, Bruce M; Manolio, Teri A; Smith, Nicholas L; Heckbert, Susan R; Gottdiener, John S; Burke, Gregory L; Weissfeld, Joel; Enright, Paul; Lumley, Thomas; Powe, Neil; Furberg, Curt D (Arch Intern Med, 2002)
BACKGROUND: Control of high blood pressure (BP) in older adults is an important part of public health efforts at prevention. OBJECTIVE: To assess recent time trends in the awareness, treatment, and control of high BP and in the use of medications to treat high BP. METHODS: In the Cardiovascular Health Study, 5888 adults 65 years and older were recruited from 4 US centers. At baseline, participants underwent an extensive examination that included the measurement of BP, use of medications, and other risk factors. Participants were followed up with annual visits that assessed BP and medication use from baseline in 1989-1990 through the examination in 1998-1999. The primary outcome measures were control of BP to levels lower than than 140/90 mm Hg and the prevalence of use of various classes of antihypertensive medications. RESULTS: The awareness, treatment, and control of high BP improved during the 1990s. The proportions aware and treated were higher among blacks than whites, though control prevalences were similar. For both groups combined, the control of high BP to lower than 140/90 mm Hg increased from 37% at baseline to 49% in 1999. The 51% whose BP was not controlled generally had isolated mild to moderate elevations in systolic BP. Among treated persons, the improvement in control was achieved in part by a mean increase of 0.2 antihypertensive medications per person over the course of 9 years. Improved control was also achieved by increasing the proportion of the entire Cardiovascular Health Study population that was treated for hypertension, from 34.5% in 1990 to 51.1% in 1999. Time trends in antihypertensive drug use were pronounced. Among those without coronary disease, the use of low-dose diuretics and beta-blockers decreased, while the use of newer agents, such as calcium channel blockers, angiotensin-converting enzyme inhibitors, and alpha-blockers increased. CONCLUSIONS: While control of high BP improved in the 1990s, about half the participants with hypertension had uncontrolled BP, primarily mild to moderate elevations in systolic BP. Low-dose diuretics and beta-blockers--the preferred agents since 1993 according to the recommendations of the Joint National Committee on the Detection, Evaluation and Treatment of High Blood Pressure--remained underused. More widespread use of these agents will be an important intervention to prevent the devastating complications of hypertension, including stroke, myocardial infarction, and heart failure.
Keywords: Age Factors; Aged; Antihypertensive Agents; Awareness; Cohort Studies; Drug Therapy; Female; Health Knowledge, Attitudes, Practice; Humans; Hypertension; Male; Prospective Studies; Time Factors

The association between time since last meal and blood pressure in older adults: the cardiovascular health study. - Smith, Nicholas L; Psaty, Bruce M; Rutan, Gale H; Lumley, Thomas; Yanez, David; Chaves, Paulo H M; Kronmal, Richard A (J Am Geriatr Soc, 2003)
OBJECTIVES: To demonstrate a postprandial hypotensive (PPH) phenomenon in older adults. DESIGN: Observational, prospective cohort study composed of baseline and nine follow-up visits. SETTING: Cardiovascular Health Study, an epidemiological study of risk factors for cardiovascular disease in older adults. PARTICIPANTS: Five thousand eight hundred eighty-eight community-dwelling adults aged 65 and older. MEASUREMENTS: Blood pressure and time since last meal were recorded synchronously at baseline and at follow-up clinic visits. Generalized estimating equations were used to estimate associations between time since last meal and blood pressure and to adjust variance estimates to account for repeated blood pressure measures within subjects across fasting times. RESULTS: Mean systolic and diastolic blood pressures were lower in the first hour after the last meal and were progressively higher through the fourth hour after the last meal than blood pressures measured immediately after the last meal (0 hour: 133.7/68.8 mmHg; 1st hour: 130.1/66.6 mmHg; 4th hour: 136.5/71.1 mmHg). Changes were significant for systolic and diastolic measures (P <.001 for both). Exploratory analyses suggested that the systolic PPH association was more pronounced in women. Little evidence was found that the degree of systolic or diastolic PPH varied by age, race, prevalent cardiovascular disease, heart rate, ejection fraction, treated hypertension or diabetes mellitus, or body mass index. CONCLUSION: These data support previous observations that there is a significant drop in blood pressure within 1 hour after a meal in older adults. Time since last meal may be an important factor to consider when measuring blood pressure in older adults, and perhaps national standards need to be set.
Keywords: Aged; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Eating; Female; Humans; Hypotension; Male; Postprandial Period; Prospective Studies; Risk Factors; Time Factors

Beta2-adrenergic receptor polymorphisms and risk of incident cardiovascular events in the elderly. - Heckbert, Susan R; Hindorff, Lucia A; Edwards, Karen L; Psaty, Bruce M; Lumley, Thomas; Siscovick, David S; Tang, Zhonghua; Durda, J Peter; Kronmal, Richard A; Tracy, Russell P (Circulation, 2003)
BACKGROUND: Genetic polymorphisms at codons 16 and 27 of the beta2-adrenergic receptor have been associated with altered response to sympathetic stimulation. We examined these polymorphisms in relation to cardiovascular event risk in the Cardiovascular Health Study. METHODS AND RESULTS: A total of 808 black and 4441 white participants (mean age, 73 years) were genotyped for the Arg16Gly and Gln27Glu polymorphisms of the beta2-adrenergic receptor. There were 702 incident coronary events, 438 ischemic strokes, and 1136 combined cardiovascular events during 7 to 10 years of follow-up. Allele frequencies differed by race but not by age or hypertension status. Glu27 carriers had a lower risk of coronary events than Gln27 homozygotes (hazard ratio, 0.82; 95% CI, 0.70 to 0.95), and there was a suggestion of decreased risk among Gly16 carriers compared with Arg16 homozygotes (hazard ratio, 0.88; 95% CI, 0.72 to 1.07). There was no association of beta2-adrenergic receptor genotype with ischemic stroke or combined cardiovascular events. CONCLUSIONS: The Glu27 allele of the beta2-adrenergic receptor was associated with a lower risk of incident coronary events in this elderly population.
Keywords: African Continental Ancestry Group; Aged; Alleles; Brain Ischemia; Cardiovascular Diseases; Cohort Studies; Comorbidity; Coronary Disease; European Continental Ancestry Group; Follow-Up Studies; Gene Frequency; Humans; Incidence; Linkage Disequilibrium; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Risk Assessment; Stroke; United States

C-reactive protein, carotid intima-media thickness, and incidence of ischemic stroke in the elderly: the Cardiovascular Health Study. - Cao, Jie J; Thach, Chau; Manolio, Teri A; Psaty, Bruce M; Kuller, Lewis H; Chaves, Paulo H M; Polak, Joseph F; Sutton-Tyrrell, Kim; Herrington, David M; Price, Thomas R; Cushman, Mary (Circulation, 2003)
BACKGROUND: Increased carotid artery intima-media thickness (IMT) and elevated C-reactive protein (CRP) are both associated with the occurrence of stroke. We investigated whether elevated CRP is a risk factor for ischemic stroke independent of carotid IMT and studied the interaction between CRP and IMT. METHODS AND RESULTS: We studied 5417 participants aged 65 years or older without preexisting stroke or chronic atrial fibrillation who were participants in the Cardiovascular Health Study. The hazard ratio of incident ischemic stroke was estimated by Cox proportional hazards regression. During 10.2 years of follow-up, 469 incident ischemic strokes occurred. The adjusted hazard ratios for ischemic stroke in the 2nd to 4th quartiles of baseline CRP, relative to the 1st quartile, were 1.19 (95% CI 0.92 to 1.53), 1.05 (95% CI 0.81 to 1.37), and 1.60 (95% CI 1.23 to 2.08), respectively. With additional adjustment for carotid IMT, there was little confounding. The association of CRP with stroke was significantly different depending on IMT (P<0.02), with no association of CRP with stroke among those in the lowest IMT tertile and a significant association among those with higher levels of IMT. CONCLUSIONS: We conclude that elevated CRP is a risk factor for ischemic stroke, independent of atherosclerosis severity as measured by carotid IMT. The association of CRP with stroke is more apparent in the presence of a higher carotid IMT. CRP and carotid IMT may each be independent integrals in determining the risk of ischemic stroke.
Keywords: Aged; Brain Ischemia; C-Reactive Protein; California; Carotid Arteries; Cohort Studies; Comorbidity; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Maryland; North Carolina; Odds Ratio; Pennsylvania; Proportional Hazards Models; Risk Assessment; Risk Factors; Stroke; Tunica Intima; Tunica Media; Ultrasonography

Elevations of inflammatory and procoagulant biomarkers in elderly persons with renal insufficiency. - Shlipak, Michael G; Fried, Linda F; Crump, Casey; Bleyer, Anthony J; Manolio, Teri A; Tracy, Russell P; Furberg, Curt D; Psaty, Bruce M (Circulation, 2003)
BACKGROUND: Renal insufficiency has been associated with cardiovascular disease events and mortality in several prospective studies, but the mechanisms for the elevated risk are not clear. Little is known about the association of renal insufficiency with inflammatory and procoagulant markers, which are potential mediators for the cardiovascular risk of kidney disease. METHODS AND RESULTS: The cross-sectional association of renal insufficiency with 8 inflammatory and procoagulant factors was evaluated using baseline data from the Cardiovascular Health Study, a population-based cohort study of 5888 subjects aged > or =65 years. C-reactive protein, fibrinogen, factor VIIc, and factor VIIIc levels were measured in nearly all participants; interleukin-6, intercellular adhesion molecule-1, plasmin-antiplasmin complex, and D-dimer levels were measured in nearly half of participants. Renal insufficiency was defined as a serum creatinine level > or =1.3 mg/dL in women and > or =1.5 mg/dL in men. Multivariate linear regression was used to compare adjusted mean levels of each biomarker in persons with and without renal insufficiency after adjustment for other baseline characteristics. Renal insufficiency was present in 647 (11%) of Cardiovascular Health Study participants. After adjustment for baseline differences, levels of C-reactive protein, fibrinogen, interleukin-6, factor VIIc, factor VIIIc, plasmin-antiplasmin complex, and D-dimer were significantly greater among persons with renal insufficiency (P<0.001). In participants with clinical, subclinical, and no cardiovascular disease at baseline, the positive associations of renal insufficiency with these inflammatory and procoagulant markers were similar. CONCLUSION: Renal insufficiency was independently associated with elevations in inflammatory and procoagulant biomarkers. These pathways may be important mediators leading to the increased cardiovascular risk of persons with kidney disease.
Keywords: Aged; alpha-2-Antiplasmin; Biomarkers; Blood Coagulation Factors; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Creatinine; Cross-Sectional Studies; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Fibrinolysin; Humans; Inflammation; Interleukin-6; Male; Prospective Studies; Renal Insufficiency; Risk Factors

Hormone replacement therapy and the risk of incident congestive heart failure: the Cardiovascular Health Study. - Rea, Thomas D; Psaty, Bruce M; Heckbert, Susan R; Cushman, Mary; Meilahn, Elaine; Olson, Jean L; Lemaitre, Rozenn N; Smith, Nicholas L; Sotoodehnia, Nona; Chaves, Paulo H M (J Womens Health (Larchmt), 2003)
BACKGROUND: The development of congestive heart failure (CHF) in older persons is related to a variety of mechanisms. Hormone replacement therapy (HRT) affects several of the pathways that may be important in the development of CHF. We hypothesized that HRT would be associated with a decreased risk of incident CHF. METHODS: Using Cox proportional-hazards regression, we assessed the risk of incident CHF (n = 304) associated with time-dependent past and current use of HRT compared to never use. The Cardiovascular Health Study is a prospective cohort study of community-dwelling adults aged 65 years and older. This analysis included female participants without a history of CHF at baseline (n = 3223). RESULTS: At baseline, 62% were never users, 26% were past users, and 12% were current users of HRT. Compared with never users, the multivariable relative risk (RR) of CHF was 1.01 (95% confidence interval [95% CI] 0.76,1.34) for past users and 1.34 (0.93,1.94) for current users. Results were similar among most treatment and clinical subgroups, except that the association of current HRT with CHF appeared to depend on body mass index (BMI) or osteoporosis status. The RR was 0.82 (0.43,1.60) for normal weight women, 1.65 (0.95,2.88) for overweight women, and 2.22 (1.06,4.67) for obese women (p = 0.01 for interaction). Similarly, the RR was 0.15 (0.04,0.65) for women with osteoporosis and 1.82 (1.25,2.65) for women without osteoporosis (p = 0.001 for interaction). CONCLUSIONS: Overall, HRT was not associated with the risk of incident CHF, although BMI and osteoporosis appeared to modify the association of HRT with CHF. The risk of CHF was lower in patients with lower BMI or osteoporosis.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Estrogen Replacement Therapy; Female; Heart Failure; Humans; Incidence; Life Style; Middle Aged; Multivariate Analysis; Obesity; Osteoporosis, Postmenopausal; Proportional Hazards Models; Prospective Studies; Risk; Risk Factors; United States; Women's Health

Inflammation as a risk factor for atrial fibrillation. - Aviles, Ronnier J; Martin, David O; Apperson-Hansen, Carolyn; Houghtaling, Penny L; Rautaharju, Pentti; Kronmal, Richard A; Tracy, Russell P; Van Wagoner, David R; Psaty, Bruce M; Lauer, Michael S; Chung, Mina K (Circulation, 2003)
BACKGROUND: The presence of systemic inflammation determined by elevations in C-reactive protein (CRP) has been associated with persistence of atrial fibrillation (AF). The relationship between CRP and prediction of AF has not been studied in a large population-based cohort. METHODS AND RESULTS: CRP measurement and cardiovascular assessment were performed at baseline in 5806 subjects enrolled in the Cardiovascular Health Study. Patients were followed up for a mean of 6.9+/-1.6 (median 7.8) years. AF was identified by self-reported history and ECGs at baseline and by ECGs and hospital discharge diagnoses at follow-up. Univariate and multivariate analyses were used to assess CRP as a predictor of baseline and future development of AF. At baseline, 315 subjects (5%) had AF. Compared with subjects in the first CRP quartile (<0.97 mg/L), subjects in the fourth quartile (>3.41 mg/L) had more AF (7.4% versus 3.7%, adjusted OR 1.8, 95% CI 1.2 to 2.5; P=0.002). Of 5491 subjects without AF at baseline, 897 (16%) developed AF during follow-up. Baseline CRP predicted higher risk for developing future AF (fourth versus first quartile adjusted hazard ratio 1.31, 95% CI 1.08 to 1.58; P=0.005). When treated as a continuous variable, elevated CRP predicted increased risk for developing future AF (adjusted hazard ratio for 1-SD increase, 1.24; 95% CI 1.11 to 1.40; P<0.001). CONCLUSIONS: CRP is not only associated with the presence of AF but may also predict patients at increased risk for future development of AF.
Keywords: Aged; Atrial Fibrillation; C-Reactive Protein; Cross-Sectional Studies; Female; Humans; Inflammation; Longitudinal Studies; Male; Risk Factors

Serum homocysteine, thermolabile variant of methylene tetrahydrofolate reductase (MTHFR), and venous thromboembolism: Longitudinal Investigation of Thromboembolism Etiology (LITE). - Tsai, Albert W; Cushman, Mary; Tsai, Michael Y; Heckbert, Susan R; Rosamond, Wayne D; Aleksic, Nena; Yanez, N David; Psaty, Bruce M; Folsom, Aaron R (Am J Hematol, 2003)
We sought to examine prospectively the association of serum homocysteine and the methylene tetrahydrofolate reductase (MTHFR) C677T gene polymorphism with risk of venous thromboembolism (VTE). We studied these relationships in a nested case-control study of 303 VTE cases and 635 matched controls from a population-based cohort of 21,680 adults from six U.S. communities. The highest quintile of serum homocysteine carried a non-statistically significant adjusted odds ratio of 1.55 (95% CI, 0.93-2.58) compared to the lowest quintile in the overall cohort but a significant association among adults aged 45-64 years (OR = 2.05, 95% CI, 1.10-3.83) and an inverse association in those > or = 65 years of age. Carriers of the MTHFR C677T polymorphism were not at higher risk for VTE than those with normal genotype (OR = 0.74, 95% CI = 0.56-0.98). Our prospective data showed, at most, a weak relationship between homocysteine and VTE risk, with associations larger among younger participants. MTHFR C677T was not a risk factor for VTE.
Keywords: Aged; Aging; Animals; Case-Control Studies; Cohort Studies; Factor V; Female; Genotype; Homocysteine; Humans; Longitudinal Studies; Male; Methylenetetrahydrofolate Reductase (NADPH2); Middle Aged; Odds Ratio; Oxidoreductases Acting on CH-NH Group Donors; Polymorphism, Genetic; Prospective Studies; Risk Factors; Venous Thrombosis

The association between lipid levels and the risks of incident myocardial infarction, stroke, and total mortality: The Cardiovascular Health Study. - Psaty, Bruce M; Anderson, Melissa; Kronmal, Richard A; Tracy, Russell P; Orchard, Trevor; Fried, Linda P; Lumley, Thomas; Robbins, John; Burke, Greg; Newman, Anne B; Furberg, Curt D (J Am Geriatr Soc, 2004)
OBJECTIVES: To assess the association between lipid levels and cardiovascular events in older adults. DESIGN: A prospective population-based study. SETTING: Four field centers in U.S. communities. PARTICIPANTS: A total of 5,201 adults aged 65 and older living in U.S. communities, plus a recruitment of 687 African Americans 3 years later. MEASUREMENTS: Fasting lipid measures included low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol, and triglycerides. RESULTS: At baseline, 1,954 men and 2,931 women were at risk for an incident myocardial infarction (MI) or stroke. During an average 7.5-year follow-up, 436 subjects had a coronary event, 332 had an ischemic stroke, 104 a hemorrhagic stroke, and 1,096 died. After adjustment, lipid measures were not major predictors of the outcomes of MI, ischemic stroke, hemorrhagic stroke, and total mortality. For total cholesterol and LDL-C, the associations with MI and ischemic stroke were only marginally significant. HDL-C was inversely associated with MI risk (hazard ratio=0.85 per standard deviation of 15.7 mg/dL, 95% confidence interval=0.76-0.96). For the outcome of ischemic stroke, high levels of HDL-C were associated with a decreased risk in men but not women. Lipid measures were generally only weakly associated with the risks of hemorrhagic stroke or total mortality. CONCLUSION: In this population-based study of older adults, most lipid measures were weakly associated with cardiovascular events. The association between low HDL-C and increased MI risk was nonetheless strong and consistent.
Keywords: African Americans; African Continental Ancestry Group; Aged; Female; Health Surveys; Humans; Incidence; Lipids; Male; Mortality; Myocardial Infarction; Population Surveillance; Prospective Studies; Risk Factors; Stroke; United States

Fish intake and risk of incident atrial fibrillation. - Mozaffarian, Dariush; Psaty, Bruce M; Rimm, Eric B; Lemaitre, Rozenn N; Burke, Gregory L; Lyles, Mary F; Lefkowitz, David; Siscovick, David S (Circulation, 2004)
BACKGROUND: Atrial fibrillation (AF) is the most common arrhythmia in clinical practice and is particularly common in the elderly. Although effects of fish intake, including potential antiarrhythmic effects, may favorably influence risk of AF, relationships between fish intake and AF incidence have not been evaluated. METHODS AND RESULTS: In a prospective, population-based cohort of 4815 adults > or =age 65 years, usual dietary intake was assessed at baseline in 1989 and 1990. Consumption of tuna and other broiled or baked fish correlated with plasma phospholipid long-chain n-3 fatty acids, whereas consumption of fried fish or fish sandwiches (fish burgers) did not. AF incidence was prospectively ascertained on the basis of hospital discharge records and annual electrocardiograms. During 12 years' follow-up, 980 cases of incident AF were diagnosed. In multivariate analyses, consumption of tuna or other broiled or baked fish was inversely associated with incidence of AF, with 28% lower risk with intake 1 to 4 times per week (HR=0.72, 95% CI=0.58 to 0.91, P=0.005), and 31% lower risk with intake > or =5 times per week (HR=0.69, 95% CI=0.52 to 0.91, P=0.008), compared with <1 time per month (P trend=0.004). Results were not materially different after adjustment for preceding myocardial infarction or congestive heart failure. In similar analyses, fried fish/fish sandwich consumption was not associated with lower risk of AF. CONCLUSIONS: Among elderly adults, consumption of tuna or other broiled or baked fish, but not fried fish or fish sandwiches, is associated with lower incidence of AF. Fish intake may influence risk of this common cardiac arrhythmia.
Keywords: Aged; Animals; Atrial Fibrillation; Cardiotonic Agents; Cohort Studies; Cooking; Diet; Dietary Fats; Fatty Acids, Omega-3; Fish Oils; Fishes; Follow-Up Studies; Humans; Incidence; Massachusetts; Proportional Hazards Models; Prospective Studies; Risk; Seafood; Tuna

Medications and cardiovascular health in older adults: room for improvement in prevention and treatment. - Rhoads, Caroline S; Psaty, Bruce M; Olson, Jean L; Furberg, Curt D (Am J Geriatr Cardiol, 2004)
Keywords: Aged; Antihypertensive Agents; Atrial Fibrillation; Cardiovascular Diseases; Diabetes Mellitus; Health Knowledge, Attitudes, Practice; Heart Failure; Humans; Hyperlipidemias; Hypertension; Hypolipidemic Agents; Risk Factors

The presence of frailty in elderly persons with chronic renal insufficiency. - Shlipak, Michael G; Stehman-Breen, Catherine; Fried, Linda F; Song, Xiao; Siscovick, David; Fried, Linda P; Psaty, Bruce M; Newman, Anne B (Am J Kidney Dis, 2004)
BACKGROUND: Frailty has been defined as a tool to define individuals who lack functional reserve and are at risk for functional decline. We hypothesized that chronic renal insufficiency (CRI) would be associated with a greater prevalence of frailty and disability in the elderly. METHODS: This cross-sectional analysis used baseline data collected from the Cardiovascular Health Study, which enrolled 5,888 community-dwelling adults aged 65 years or older from 4 clinical centers in the United States. Renal insufficiency is defined as a serum creatinine level of 1.3 mg/dL or greater (> or =115 micromol/L) in women and 1.5 mg/dL or greater (> or =133 micromol/L) in men. Frailty is defined by the presence of 3 of the following abnormalities: unintentional weight loss, self-reported exhaustion, measured weakness, slow walking speed, and low physical activity. Disability is defined as any self-reported difficulty with activities of daily living. RESULTS: Among 5,808 participants with creatinine levels measured at entry, 15.9% of men (n = 394) and 7.6% of women (n = 254) had CRI. Prevalences of frailty (15% versus 6%; P < 0.001) and disability (12% versus 7%; P = 0.001) were greater in participants with CRI compared with those with normal renal function. After multivariate adjustment for comorbidity, CRI remained significantly associated with frailty (odds ratio, 1.76; 95% confidence interval, 1.28 to 2.41), but not disability (odds ratio, 1.26; 95% confidence interval, 0.94 to 1.69). CONCLUSION: Elderly persons with CRI have a high prevalence of frailty, which may signal their risk for progression to adverse health outcomes. If confirmed in other studies, identification of frailty in patients with CRI may warrant special interventions to preserve their independence, quality of life, and survival.
Keywords: Activities of Daily Living; Aged; Cross-Sectional Studies; Female; Frail Elderly; Humans; Kidney Failure, Chronic; Male; United States

Risk of congestive heart failure in an elderly population treated with peripheral alpha-1 antagonists. - Bryson, Chris L; Smith, Nicholas L; Kuller, Lewis H; Chaves, Paulo H M; Manolio, Teri A; Lewis, William; Boyko, Edward J; Furberg, Curt D; Psaty, Bruce M (J Am Geriatr Soc, 2004)
OBJECTIVES: To compare the risk of congestive heart failure (CHF) in elderly individuals treated with any peripheral alpha-1 antagonist for hypertension with any thiazide, test whether the risk persists in subjects without cardiovascular disease (CVD) at baseline, and examine CHF risk in normotensive men with prostatism treated with alpha antagonists. DESIGN: Prospective cohort study. SETTING: Four U.S. sites: Washington County, Maryland; Allegheny County, Pennsylvania; Sacramento County, California; and Forsyth County, North Carolina. PARTICIPANTS: A total of 5,888 community-dwelling subjects aged 65 and older. MEASUREMENTS: Adjudicated incident CHF. RESULTS: The 3,105 participants with treated hypertension were at risk for CHF; 22% of men and 8% of women took alpha antagonists during follow-up. The age-adjusted risk of CHF in those receiving monotherapy treated with alpha antagonists was 1.90 (95% confidence interval=1.03-3.50) compared with thiazides. In subjects without CVD at baseline receiving monotherapy, women taking an alpha antagonist had a 3.6 times greater age-adjusted risk of CHF, whereas men had no difference in risk. Adjustment for systolic blood pressure attenuated statistical differences in risk. There were 930 men without hypertension at risk for CHF; 5% used alpha antagonists during follow-up, with no observed increase in CHF risk. CONCLUSION: Subjects receiving alpha antagonist monotherapy for hypertension had a two to three times greater risk of incident CHF, also seen in lower-risk subjects, but differences in blood pressure control partly explained this.
Keywords: Adrenergic alpha-Antagonists; Aged; Antihypertensive Agents; Benzothiadiazines; Blood Pressure; Cohort Studies; Diuretics; Female; Heart Failure; Humans; Hypertension; Male; Risk Factors; Sodium Chloride Symporter Inhibitors; United States

Survival associated with two sets of diagnostic criteria for congestive heart failure. - Schellenbaum, Gina D; Rea, Thomas D; Heckbert, Susan R; Smith, Nicholas L; Lumley, Thomas; Roger, Veronique L; Kitzman, Dalane W; Taylor, Herman A; Levy, Daniel; Psaty, Bruce M (Am J Epidemiol, 2004)
Congestive heart failure (CHF) definitions vary across epidemiologic studies. The Framingham Heart Study criteria include CHF signs and symptoms assessed by a physician panel. In the Cardiovascular Health Study, a committee of physicians adjudicated CHF diagnoses, confirmed by signs, symptoms, clinical tests, and/or medical therapy. The authors used data from the Cardiovascular Health Study, a population-based cohort study of 5,888 elderly US adults, to compare CHF incidence and survival patterns following onset of CHF as defined by Framingham and/or Cardiovascular Health Study criteria. They constructed an inception cohort of nonfatal, hospitalized CHF patients. Of 875 participants who had qualifying CHF hospitalizations between 1989 and 2000, 54% experienced a first CHF event that fulfilled both sets of diagnostic criteria (concordant), 31% fulfilled only the Framingham criteria (Framingham only), and 15% fulfilled only the Cardiovascular Health Study criteria (Cardiovascular Health Study only). No significant survival difference was found between the Framingham-only group (hazard ratio = 0.87, 95% confidence interval: 0.71, 1.07) or the Cardiovascular Health Study-only group (hazard ratio = 0.89, 95% confidence interval: 0.68, 1.15) and the concordant group (referent). Compared with Cardiovascular Health Study central adjudication, Framingham criteria for CHF identified a larger group of participants with incident CHF, but all-cause mortality rates were similar across these diagnostic classifications.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Diagnosis, Differential; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Prognosis; Severity of Illness Index; Survival Analysis

Time trends in the use of beta-blockers and other pharmacotherapies in older adults with congestive heart failure. - Smith, Nicholas L; Chan, Jeannie D; Rea, Thomas D; Wiggins, Kerri L; Gottdiener, John S; Lumley, Thomas; Psaty, Bruce M (Am Heart J, 2004)
BACKGROUND: Evidence supporting pharmacotherapy of congestive heart failure (CHF) has grown substantially over the past decade and includes large, placebo-controlled trials with mortality end points. We describe beta-blocker and other medication temporal treatment trends of CHF in the Cardiovascular Health Study, a community-based cohort study of 5888 adults > or =65 years of age. METHODS: Prescription medication data were collected from hospital discharge summaries for incident CHF events and at in-study annual clinic visits for prevalent CHF cases from 1989 to 2000. Change in use of agents over time was estimated by using generalized estimating equations while adjusting for potential confounding factors of age, sex, race, and cardiovascular and pulmonary comorbidities. RESULTS: Among 1033 incident CHF events, beta-blocker use after diagnosis increased an average of 2.4 percentage points annually (95% CI, 1.5 to 3.4 points) from 1989 to 2000. The increasing trend was consistent throughout follow-up. Among participants with coronary disease and/or hypertension and among those with low ejection fractions (<45%), beta-blocker use remained flat from 1989 to 1994 and increased 4.7 points annually (2.5 to 6.9) and 10.0 points annually (6.1 to 13.8), respectively, from 1995 to 2000. Among participants without coronary disease or hypertension, there was no overall increase in use. Use of renin-angiotensin system inhibitors increased 2.3 points annually (1.0 to 3.5), digoxin use decreased 2.4 points annually (-3.6 to -1.1), and loop diuretic use remained flat between 1989 and 2000. In general, treatment trends were similar for prevalent CHF. CONCLUSIONS: Treatment of CHF has changed gradually in the 1990s and may in part reflect the influence of CHF clinical trial evidence.
Keywords: Adrenergic beta-Antagonists; Aged; Angiotensin II Type 1 Receptor Blockers; Angiotensin-Converting Enzyme Inhibitors; Cohort Studies; Drug Therapy; Drug Therapy, Combination; Female; Heart Failure; Humans; Male; Multivariate Analysis; Prevalence

Association of beta-blocker use with mortality among patients with congestive heart failure in the Cardiovascular Health Study (CHS). - Chan, Jeannie D; Rea, Thomas D; Smith, Nicholas L; Siscovick, David; Heckbert, Susan R; Lumley, Thomas; Chaves, Paulo; Furberg, Curt D; Kuller, Lewis; Psaty, Bruce M (Am Heart J, 2005)
BACKGROUND: In clinical trials, beta-blocker therapy reduces all-cause mortality among people with congestive heart failure (CHF) characterized by depressed systolic function, but few trials included large numbers of elderly participants. This study assessed the association between beta-blocker therapy and mortality among community-dwelling older adults with CHF. METHODS: The Cardiovascular Health Study (CHS) is a longitudinal, population-based study of adults aged > or = 65 years. Recruitment began in 1989 with follow-up extending through June 2000 or death. Cox proportional hazard regression models were used to assess the association between beta-blocker therapy and all-cause mortality among 950 participants who developed new-onset CHF. RESULTS: beta-Blocker users (n = 157) were more likely than nonusers (n = 793) to have treated hypertension, clinical coronary artery disease, and valvular disease at the time of CHF diagnosis. Death occurred in 67 users and 446 nonusers during a median follow-up of 2.3 years. Compared with nonuse, use of beta-blockers was associated with a multivariable adjusted hazard ratio (HR) of 0.74 (95% CI 0.56-0.98) for all-cause mortality. Among the 520 participants who had left ventricular ejection fraction assessed within 90 days after CHF diagnosis, the risk for all cause mortality associated with beta-blocker use did not differ significantly between those with ejection fraction of < 40% and those with ejection fraction of > or = 40% (HR 0.56, 95% CI 0.27-1.13; HR 0.82, 95% CI 0.56-1.22, respectively; interaction P = .34). CONCLUSIONS: This observational study suggests that beta-blocker treatment is associated with a reduced risk of all-cause mortality among community-dwelling older adults with CHF.
Keywords: Adrenergic beta-Antagonists; Age Factors; Aged; Aged, 80 and over; Female; Follow-Up Studies; Heart Failure; Humans; Male

beta(2)-Adrenergic receptor polymorphisms and determinants of cardiovascular risk: the Cardiovascular Health Study. - Hindorff, Lucia A; Heckbert, Susan R; Psaty, Bruce M; Lumley, Thomas; Siscovick, David S; Herrington, David M; Edwards, Karen L; Tracy, Russell P (Am J Hypertens, 2005)
BACKGROUND: Common Arg16Gly and Gln27Glu polymorphisms of the beta(2)-adrenergic receptor (beta(2)AR) have been associated with hypertension and coronary disease. This analysis of older adults in the Cardiovascular Health Study examined whether these polymorphisms were associated with blood pressure (BP), subclinical atherosclerosis, and, among treated hypertensive individuals, differences in coronary disease risk according to antihypertensive drug class. METHODS: Altogether, 5249 participants (4441 white and 808 African American, median follow-up time 10.2 years) were genotyped for both polymorphisms. Ankle-arm index (AAI), carotid intima-media thickness (IMT), and brachial flow-mediated dilation were measured cross-sectionally. All estimates were adjusted for ethnicity. RESULTS: Relative to Gln27 homozygotes, carrying the Glu27 allele was not associated with new-onset hypertension (hazard ratio [HR] = 1.01, 95% confidence interval [CI] = 0.87 to 1.16), BP control (odds ratio [OR] = 0.97, 95% CI = 0.89 to 1.06), AAI (mean difference 0.0042 +/- 0.0052), carotid IMT (mean difference 0.0044 +/- 0.02 mm), or brachial flow-mediated dilation (mean difference in baseline diameter -0.028 +/- 0.036 mm; the most marked of three measures). Among treated hypertensive individuals, coronary disease risk was similar in Glu27 carriers relative to Gln27 homozygotes in subgroups defined by use of beta-blockers (HR = 1.09, 95% CI = 0.64 to 1.87) or other antihypertensive medications (HR = 1.00, 95% CI = 0.78 to 1.28). Results were similar for the Arg16Gly polymorphism. CONCLUSIONS: The association of beta(2)AR genotype with coronary disease previously reported in this older adult population is not likely to be explained by BP levels, subclinical atherosclerosis, or antihypertensive treatment. Other measures of vascular response, gene-gene or gene-environment interactions, or characteristics developing earlier in life may mediate the association between beta(2)AR genotype and coronary disease and merit further research.
Keywords: African Americans; Antihypertensive Agents; Arteriosclerosis; Coronary Artery Disease; European Continental Ancestry Group; Female; Genotype; Homozygote; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Risk Factors

Common promoter polymorphisms of inflammation and thrombosis genes and longevity in older adults: the cardiovascular health study. - Reiner, Alexander P; Diehr, Paula; Browner, Warren S; Humphries, Stephen E; Jenny, Nancy S; Cushman, Mary; Tracy, Russell P; Walston, Jeremy; Lumley, Thomas; Newman, Anne B; Kuller, Lewis H; Psaty, Bruce M (Atherosclerosis, 2005)
Inflammatory response genes may influence life span or quality at advanced ages. Using data from the population-based cardiovascular health study (CHS) cohort, we examined the associations between promoter polymorphisms of several inflammation and thrombosis genes with longevity. We ascertained genotypes for interleukin (IL)-6 -174 G/C, beta-fibrinogen -455 G/A, plasminogen activator inhibitor (PAI)-1 -675 4G/5G, and thrombin-activatable fibrinolysis inhibitor (TAFI) -438 G/A in 2224 men and women > or = 65 years old at baseline. During 10 years of follow-up, men with the TAFI -438 A/A genotype had decreased mortality due to all causes, and lived, on average, 0.9 more years of life, or 1.1 more years of healthy life, than men with the -438 G allele. The effects of TAFI -438 G/A in women were smaller and not statistically significant. PAI-1 4G/4G genotype appeared to be associated with lower non-cardiovascular mortality in men, but with greater cardiovascular mortality in women. In exploratory analyses, we observed a possible interaction among anti-inflammatory drugs, interleukin-6 -174 C/C genotype, and longevity. These findings suggest that modulators of fibrinolytic activity may have a generalized influence on aging, and merit further investigation in studies of genetic determinants of human longevity.
Keywords: Aged; Aging; Carboxypeptidase B2; Cause of Death; Cohort Studies; Female; Genotype; Health Status; Humans; Inflammation; Longevity; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Prospective Studies; Risk Factors; Thrombosis

C-reactive protein and the 10-year incidence of coronary heart disease in older men and women: the cardiovascular health study. - Cushman, Mary; Arnold, Alice M; Psaty, Bruce M; Manolio, Teri A; Kuller, Lewis H; Burke, Gregory L; Polak, Joseph F; Tracy, Russell P (Circulation, 2005)
BACKGROUND: High C-reactive protein (CRP) is associated with increased coronary heart disease risk. Few long-term data in the elderly are available. METHODS AND RESULTS: Baseline CRP was measured in 3971 men and women > or =65 years of age without prior vascular diseases; 26% had elevated concentrations (>3 mg/L). With 10 years of follow-up, 547 participants developed coronary heart disease (CHD; defined as myocardial infarction or coronary death). With elevated CRP, the 10-year cumulative CHD incidences were 33% in men and 17% in women. The age-, ethnicity-, and sex-adjusted relative risk of CHD for CRP >3 mg/L compared with <1 mg/L was 1.82 (95% CI, 1.46 to 2.28). Adjusting for conventional risk factors reduced the relative risk to 1.45 (95% CI, 1.14 to 1.86). The population-attributable risk of CHD for elevated CRP was 11%. Risk relationships did not differ in subgroups defined by baseline risk factors. We assessed whether CRP improved prediction by the Framingham Risk Score. Among men with a 10-year Framingham-predicted risk of 10% to 20%, the observed CHD incidence was 32% for elevated CRP. Among women, CRP discriminated best among those with a 10-year predicted risk >20%; the incidences were 31% and 10% for elevated and normal CRP levels, respectively. CONCLUSIONS: In older men and women, elevated CRP was associated with increased 10-year risk of CHD, regardless of the presence or absence of cardiac risk factors. A single CRP measurement provided information beyond conventional risk assessment, especially in intermediate-Framingham-risk men and high-Framingham-risk women.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Coronary Disease; Female; Humans; Incidence; Inflammation; Male; Myocardial Infarction; Predictive Value of Tests; Risk Factors

Cystatin C concentration as a risk factor for heart failure in older adults. - Sarnak, Mark J; Katz, Ronit; Stehman-Breen, Catherine O; Fried, Linda F; Jenny, Nancy Swords; Psaty, Bruce M; Newman, Anne B; Siscovick, David; Shlipak, Michael G (Ann Intern Med, 2005)
BACKGROUND: Previous studies that evaluated the association of kidney function with incident heart failure may be limited by the insensitivity of serum creatinine concentration for detecting abnormal kidney function. OBJECTIVE: To compare serum concentrations of cystatin C (a novel marker of kidney function) and creatinine as predictors of incident heart failure. DESIGN: Observational study based on measurement of serum cystatin C from frozen sera obtained at the 1992-1993 visit of the Cardiovascular Health Study. Follow-up occurred every 6 months. SETTING: Adults 65 years of age or older from 4 communities in the United States. PARTICIPANTS: 4384 persons without previous heart failure who had measurements of serum cystatin C and serum creatinine. MEASUREMENTS: Incident heart failure. RESULTS: The mean (+/-SD) serum concentrations of cystatin C and creatinine were 82 +/- 25 nmol/L (1.10 +/- 0.33 mg/L) and 89 +/- 34 micromol/L (1.01 +/- 0.39 mg/dL), respectively. During a median follow-up of 8.3 years (maximum, 9.1 years), 763 (17%) participants developed heart failure. After adjustment for demographic factors, traditional and novel cardiovascular risk factors, cardiovascular disease status, and medication use, sequential quintiles of cystatin C concentration were associated with a stepwise increased risk for heart failure in Cox proportional hazards models (hazard ratios, 1.0 [reference], 1.30 [95% CI, 0.96 to 1.75], 1.44 [CI, 1.07 to 1.94], 1.58 [CI, 1.18 to 2.12], and 2.16 [CI, 1.61 to 2.91]). In contrast, quintiles of serum creatinine concentration were not associated with risk for heart failure in adjusted analysis (hazard ratios, 1.0 [reference], 0.77 [CI, 0.59 to 1.01], 0.85 [CI, 0.64 to 1.13], 0.97 [CI, 0.72 to 1.29], and 1.14 [CI, 0.87 to 1.49]). LIMITATIONS: The mechanism by which cystatin C concentration predicts risk for heart failure remains unclear. CONCLUSIONS: The cystatin C concentration is an independent risk factor for heart failure in older adults and appears to provide a better measure of risk assessment than the serum creatinine concentration. *For a full list of participating Cardiovascular Health Study investigators and institutions, see http://www.chs-nhlbi.org.
Keywords: Aged; Biomarkers; Creatinine; Cystatin C; Cystatins; Female; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Incidence; Kidney; Kidney Function Tests; Male; Risk Factors; United States

Cystatin-C and inflammatory markers in the ambulatory elderly. - Shlipak, Michael G; Katz, Ronit; Cushman, Mary; Sarnak, Mark J; Stehman-Breen, Catherine; Psaty, Bruce M; Siscovick, David; Tracy, Russell P; Newman, Anne; Fried, Linda (Am J Med, 2005)
PURPOSE: Inflammatory factors are elevated in persons with severe renal dysfunction, but their association across all levels of renal function is unclear. We compared cystatin-C, a novel marker of renal function, with creatinine and estimated glomerular filtration rate (eGFR) as predictors of C-reactive protein and fibrinogen levels. METHODS: This study is a cross-sectional analysis to evaluate cystatin-C, creatinine, and eGFR as predictors of the inflammatory markers C-reactive protein and fibrinogen. Participants included 4637 ambulatory elderly patients from the Cardiovascular Health Study. Multivariate linear regression was used to determine the independent associations of each renal function measurement with the inflammatory marker outcomes. RESULTS: After adjustment for confounding factors, cystatin-C was correlated with both C-reactive protein (coefficient = 0.13; 95% confidence interval: 0.10-1.16, P <.0001) and fibrinogen levels (0.15; 0.13-0.18, P <.0001). Associations were larger than those for creatinine and C-reactive protein (0.05; 0.02-0.07, P = .003) or fibrinogen (0.07; 0.04-0.10, P <.0001). Adjusted levels of C-reactive protein increased incrementally across quintiles of cystatin-C, from a median of 2.2 mg/L in quintile 1 to 3.7 mg/L in quintile 5. In contrast, both C-reactive protein and fibrinogen had U-shaped associations with quintiles of creatinine and eGFR, because the inflammatory markers were equivalently elevated in quintiles 1 and 5. CONCLUSIONS: The finding of a significant linear association of cystatin-C and inflammation markers suggests that even small reductions in renal function may be associated with adverse pathophysiologic consequences.
Keywords: Age Factors; Aged; Biomarkers; C-Reactive Protein; Cross-Sectional Studies; Cystatin C; Cystatins; Female; Fibrinogen; Glomerular Filtration Rate; Humans; Kidney Diseases; Male; Predictive Value of Tests; Sensitivity and Specificity

Cystatin-C and mortality in elderly persons with heart failure. - Shlipak, Michael G; Katz, Ronit; Fried, Linda F; Jenny, Nancy Swords; Stehman-Breen, Catherine O; Newman, Anne B; Siscovick, David; Psaty, Bruce M; Sarnak, Mark J (J Am Coll Cardiol, 2005)
OBJECTIVES: We sought to evaluate cystatin-C, a novel measure of renal function, as a predictor of mortality in elderly persons with heart failure (HF) and to compare it with creatinine. BACKGROUND: Renal function is an important prognostic factor in patients with HF, but creatinine levels, which partly reflect muscle mass, may be insensitive for detecting renal insufficiency. METHODS: A total of 279 Cardiovascular Health Study participants with prevalent HF and measures of serum cystatin-C and creatinine were followed for mortality outcomes over a median of 6.5 years. RESULTS: Median creatinine and cystatin-C levels were 1.05 mg/dl and 1.26 mg/l. Each standard deviation increase in cystatin-C (0.35 mg/l) was associated with a 31% greater adjusted mortality risk (95% confidence interval [CI] 20% to 43%, p < 0.001), whereas each standard deviation increase in creatinine (0.39 mg/dl) was associated with a 17% greater adjusted mortality risk (95% CI 1% to 36%, p = 0.04). When both measures were combined in a single adjusted model, cystatin-C remained associated with elevated mortality risk (hazard ratio 1.60, 95% CI 1.32 to 1.94), whereas creatinine levels appeared associated with lower risk (hazard ratio 0.73, 95% CI 0.57 to 0.95). CONCLUSIONS: Cystatin-C is a stronger predictor of mortality than creatinine in elderly persons with HF. If confirmed in future studies, this new marker of renal function could improve risk stratification in patients with HF.
Keywords: Age Factors; Aged; Aged, 80 and over; Creatinine; Cystatin C; Cystatins; Female; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Male; Pilot Projects; Predictive Value of Tests; Risk Assessment; Survival Analysis

Incidence of cardiovascular disease in older Americans: the cardiovascular health study. - Arnold, Alice M; Psaty, Bruce M; Kuller, Lewis H; Burke, Gregory L; Manolio, Teri A; Fried, Linda P; Robbins, John A; Kronmal, Richard A (J Am Geriatr Soc, 2005)
OBJECTIVES: To estimate incidence rates of major cardiovascular disease (CVD) in older Americans. DESIGN: Longitudinal cohort study using prospectively collected data on cardiovascular events. SETTING: Four U.S. communities in the Cardiovascular Health Study (CHS). PARTICIPANTS: Five thousand eight hundred eighty-eight participants in CHS, aged 65 or older at enrollment, including 3,393 women (581 African American) and 2,495 men (343 African American). MEASUREMENTS: At semiannual contacts, participants reported any occurrence of clinical CVD. Medical records were obtained and adjudicated to confirm diagnosis of CVD. RESULTS: During 10 years of follow-up, incidence of coronary heart disease (CHD) per 1,000 person-years was 39.6 (95% confidence interval (CI)=36.4-43.1) in men and 22.3 (95% CI=20.4-24.2) in women. Cumulative event rates for CHD and myocardial infarction for women aged 75 and older at baseline were similar to those for men aged 65 to 74. The overall incidence of stroke was similar for men and women (14.7 (95% CI=13.0-16.6) and 13.7 (95% CI=12.4-15.1) per 1,000 person-years, respectively), but the risk of stroke increased with age more rapidly in women, resulting in a greater cumulative event rate for stroke in women than in men aged 75 and older. The incidence of congestive heart failure increased 9% with each year of age over 65 and was greater than 6% per year in Caucasian men and women aged 85 and older at baseline. Rates were similar in African Americans and Caucasians. CONCLUSION: The occurrence of new CVD in older Americans is high, indicating that preventive efforts need to be maintained into older ages.
Keywords: African Americans; Age Distribution; Aged; Aged, 80 and over; Cardiovascular Diseases; European Continental Ancestry Group; Female; Geriatric Assessment; Humans; Incidence; Longitudinal Studies; Male; Sex Distribution; Survival Rate; United States

Population structure, admixture, and aging-related phenotypes in African American adults: the Cardiovascular Health Study. - Reiner, Alexander P; Ziv, Elad; Lind, Denise L; Nievergelt, Caroline M; Schork, Nicholas J; Cummings, Steven R; Phong, Angie; Burchard, Esteban González; Harris, Tamara B; Psaty, Bruce M; Kwok, Pui-Yan (Am J Hum Genet, 2005)
U.S. populations are genetically admixed, but surprisingly little empirical data exists documenting the impact of such heterogeneity on type I and type II error in genetic-association studies of unrelated individuals. By applying several complementary analytical techniques, we characterize genetic background heterogeneity among 810 self-identified African American subjects sampled as part of a multisite cohort study of cardiovascular disease in older adults. On the basis of the typing of 24 ancestry-informative biallelic single-nucleotide-polymorphism markers, there was evidence of substantial population substructure and admixture. We used an allele-sharing-based clustering algorithm to infer evidence for four genetically distinct subpopulations. Using multivariable regression models, we demonstrate the complex interplay of genetic and socioeconomic factors on quantitative phenotypes related to cardiovascular disease and aging. Blood glucose level correlated with individual African ancestry, whereas body mass index was associated more strongly with genetic similarity. Blood pressure, HDL cholesterol level, C-reactive protein level, and carotid wall thickness were not associated with genetic background. Blood pressure and HDL cholesterol level varied by geographic site, whereas C-reactive protein level differed by occupation. Both ancestry and genetic similarity predicted the number and quality of years lived during follow-up, but socioeconomic factors largely accounted for these associations. When the 24 genetic markers were tested individually, there were an excess number of marker-trait associations, most of which were attenuated by adjustment for genetic ancestry. We conclude that the genetic demography underlying older individuals who self identify as African American is complex, and that controlling for both genetic admixture and socioeconomic characteristics will be required in assessing genetic associations with chronic-disease-related traits in African Americans. Complementary methods that identify discrete subgroups on the basis of genetic similarity may help to further characterize the complex biodemographic structure of human populations.
Keywords: African Americans; Aged; Aging; Algorithms; Cardiovascular Diseases; Cohort Studies; Female; Genetics, Population; Genotype; Humans; Male; Models, Genetic; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Socioeconomic Factors

Statin use and the risk of incident dementia: the Cardiovascular Health Study. - Rea, Thomas D; Breitner, John C; Psaty, Bruce M; Fitzpatrick, Annette L; Lopez, Oscar L; Newman, Anne B; Hazzard, William R; Zandi, Peter P; Burke, Gregory L; Lyketsos, Constantine G; Bernick, Charles; Kuller, Lewis H (Arch Neurol, 2005)
BACKGROUND: Statins (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) reduce cardiovascular risk through mechanisms that might affect the development of dementia. OBJECTIVE: To evaluate whether statin use is associated with a lower risk of dementia compared with never use of lipid-lowering agents (LLAs). DESIGN: Cohort study of community-dwelling adults 65 years and older. The analysis included 2798 participants free of dementia at baseline. MAIN OUTCOME MEASURES: Using Cox proportional hazards regression analysis, we estimated the risk of incident all-cause and type-specific dementia associated with time-dependent statin therapy compared with never use of LLAs. The primary analyses incorporated a 1-year lag between exposure and outcome. Secondary analyses included the final year of exposure and modeled statin use as current use vs nonuse to simulate a case-control approach. RESULTS: Compared with never use of LLAs, ever use of statins was not associated with the risk of all-cause dementia (multivariable-adjusted hazard ratio [HR], 1.08; 95% confidence interval [CI], 0.77-1.52), Alzheimer disease alone (HR, 1.21; 95% CI, 0.76-1.91), mixed Alzheimer disease and vascular dementia (HR, 0.87; 95% CI, 0.44-1.72), or vascular dementia alone (HR, 1.36; 95% CI, 0.61-3.06). In contrast, in secondary analyses, current use of statins compared with nonuse of LLAs was associated with HRs of 0.69 (95% CI, 0.46-1.02) for all-cause dementia and 0.56 (95% CI, 0.35-0.92) for any Alzheimer disease. CONCLUSIONS: In this cohort study, statin therapy was not associated with a decreased risk of dementia. Methodological differences may explain why results of this cohort investigation differ from those of prior case-control studies. Additional investigation is needed to determine whether and for whom statin use may affect dementia risk.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Dementia; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hyperlipidemias; Male

Weight loss, muscle strength, and angiotensin-converting enzyme inhibitors in older adults with congestive heart failure or hypertension. - Schellenbaum, Gina D; Smith, Nicholas L; Heckbert, Susan R; Lumley, Thomas; Rea, Thomas D; Furberg, Curt D; Lyles, Mary F; Psaty, Bruce M (J Am Geriatr Soc, 2005)
OBJECTIVES: To determine whether angiotensin-converting enzyme (ACE) inhibitor use may be associated with weight maintenance and sustained muscle strength (measured by grip strength) in older adults. DESIGN: Data from the Cardiovascular Health Study (CHS), a community-based prospective cohort study of 5,888 older adults, were used. SETTING: Subjects were recruited from four U.S. sites beginning in 1989; this analysis included data through 2001. PARTICIPANTS: CHS participants with congestive heart failure (CHF) or treated hypertension. MEASUREMENTS: The exposure, current ACE inhibitor use, was ascertained by medication inventory at annual clinic visits; the outcomes were weight change and grip-strength change during the following year. Multivariate linear regression was used, accounting for correlations between observations on the same participant over time. RESULTS: The average annual weight change was -0.38 kg in 2,834 participants (14,443 person-years) with treated hypertension and -0.62 kg in 342 participants (980 person-years) with CHF. ACE inhibitor use was associated with less annual weight loss after adjustment for potential confounders: a difference of 0.17 kg (95% confidence interval (CI)=0.05-0.29) in those with treated hypertension and 0.29 kg (95% CI=-0.25-0.83) in those with CHF. There was no evidence of association between ACE inhibitor use and grip-strength change. CONCLUSION: ACE inhibitor use may be associated with weight maintenance, but not maintenance of muscle strength, in older adults with treated hypertension.
Keywords: Aged; Aged, 80 and over; Angiotensin-Converting Enzyme Inhibitors; Female; Hand Strength; Heart Failure; Humans; Hypertension; Male; Multivariate Analysis; Outcome Assessment, Health Care; Prospective Studies; Statistics as Topic; United States; Weight Loss

10-year follow-up of subclinical cardiovascular disease and risk of coronary heart disease in the Cardiovascular Health Study. - Kuller, Lewis H; Arnold, Alice M; Psaty, Bruce M; Robbins, John A; O'Leary, Daniel H; Tracy, Russell P; Burke, Gregory L; Manolio, Teri A; Chaves, Paolo H M (Arch Intern Med, 2006)
BACKGROUND: The incidence of coronary heart disease (CHD) is very high among individuals 65 years or older. METHODS: We evaluated the relationships between measurements of subclinical disease at baseline (1989-1990) and at the third-year follow-up examination (1992-1993) and subsequent incidence of cardiovascular disease and total mortality as of June 2001. Approximately 61% of the participants without clinical cardiovascular disease at baseline had subclinical disease based on our previously described criteria from the Cardiovascular Health Study. RESULTS: The incidence of CHD was substantially increased for participants with subclinical disease compared with those who had no subclinical disease: 30.5 per 1000 person-years with and 16.3 per 1000 person-years without for white individuals, and 31.2 per 1000 person-years with and 12.5 per 1000 person-years without for black individuals. The risk persisted over the entire follow-up period. Incidence rates were higher for men than for women with or without subclinical disease, but there was little difference in rates for black individuals and white individuals. CONCLUSIONS: In multivariable models, subclinical disease at baseline remained a significant predictor of CHD in both men and women; the hazard ratios (95% confidence intervals) of their relative risks were 1.64 (1.30-2.06) and 1.49 (1.21-1.84), respectively. The presence of subclinical disease substantially increased the risk of subsequent CHD for participants with hypertension, diabetes mellitus, or elevated C-reactive protein. In summary, subclinical disease is very prevalent among older individuals, is independently associated with risk of CHD even over a 10-year follow-up period, and substantially increases the risk of CHD among participants with hypertension or diabetes mellitus.
Keywords: African Continental Ancestry Group; Aged; Blood Chemical Analysis; Cardiovascular Diseases; Comorbidity; Coronary Disease; Echocardiography; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Multivariate Analysis; Prevalence; Proportional Hazards Models; Regression Analysis; Risk Factors; Sex Distribution; United States

Alcohol consumption and risk of coronary heart disease in older adults: the Cardiovascular Health Study. - Mukamal, Kenneth J; Chung, Hyoju; Jenny, Nancy S; Kuller, Lewis H; Longstreth, W T; Mittleman, Murray A; Burke, Gregory L; Cushman, Mary; Psaty, Bruce M; Siscovick, David S (J Am Geriatr Soc, 2006)
OBJECTIVES: To evaluate several aspects of the relationship between alcohol use and coronary heart disease in older adults, including beverage type, mediating factors, and type of outcome. DESIGN: Prospective cohort study. SETTING: Four U.S. communities. PARTICIPANTS: Four thousand four hundred ten adults aged 65 and older free of cardiovascular disease at baseline. MEASUREMENTS: Risk of incident myocardial infarction or coronary death according to self-reported consumption of beer, wine, and spirits ascertained yearly. RESULTS: During an average follow-up period of 9.2 years, 675 cases of incident myocardial infarction or coronary death occurred. Compared with long-term abstainers, multivariate relative risks of 0.90 (95% confidence interval (CI)=0.71-1.14), 0.93 (95% CI=0.73-1.20), 0.76 (95% CI=0.53-1.10), and 0.58 (95% CI=0.39-0.86) were found in consumers of less than one, one to six, seven to 13, and 14 or more drinks per week, respectively (P for trend=.007). Associations were similar for secondary coronary outcomes, including nonfatal and fatal events. No strong mediators of the association were identified, although fibrinogen appeared to account for 9% to 10% of the relationship. The associations were statistically similar for intake of wine, beer, and liquor and generally similar in subgroups, including those with and without an apolipoprotein E4 allele. CONCLUSION: In this population, consumption of 14 or more drinks per week was associated with the lowest risk of coronary heart disease, although clinicians should not recommend moderate drinking to prevent coronary heart disease based on this evidence alone, because current National Institute on Alcohol Abuse and Alcoholism guidelines suggest that older adults limit alcohol intake to one drink per day.
Keywords: Aged; Alcohol Drinking; Apolipoproteins E; Beer; Cohort Studies; Coronary Disease; Female; Genotype; Health Behavior; Humans; Incidence; Male; Residence Characteristics; Risk Assessment; Socioeconomic Factors; United States; Wine

The association of microalbuminuria with clinical cardiovascular disease and subclinical atherosclerosis in the elderly: the Cardiovascular Health Study. - Cao, Jie J; Barzilay, Joshua I; Peterson, Do; Manolio, Teri A; Psaty, Bruce M; Kuller, Lewis; Wexler, Jason; Bleyer, Anthony J; Cushman, Mary (Atherosclerosis, 2006)
PURPOSE: Microalbuminuria (MA) is a risk factor for cardiovascular disease (CVD). It is not known whether this association is due to the effect of MA on the development of subclinical atherosclerosis or whether MA destabilizes subclinical atherosclerosis, leading to clinical events. METHODS: In a cross-sectional analysis we evaluated 3312 Cardiovascular Health Study participants, age >or=65 years, who had MA testing. Participants were divided into three groups: those without diabetes or hypertension (33%), those with hypertension (52%) and those with diabetes, with or without hypertension (15%). Clinical CVD was defined as presence of coronary heart disease (angina, MI, CABG, PTCA), cerebrovascular disease (stroke, TIA) and peripheral arterial disease (requiring intervention). Among those without clinical disease, subclinical atherosclerosis was defined as increased carotid artery intima-media thickness, decreased ankle arm index or increased left ventricular mass. RESULTS: In each of the three groups of participants, the adjusted odds of prevalent clinical CVD in the presence of MA was 1.70-1.80-fold increased, independent of other risk factors. MA was not associated with risk of subclinical atherosclerosis in those without hypertension or diabetes (OR 1.14 [95% CI 0.59, 2.23]), whereas it was associated with subclinical atherosclerosis in those with hypertension (OR 1.58 [95% CI 1.08, 2.30]) or diabetes (OR 2.51 [95% CI 1.27, 4.94]). CONCLUSION: In the absence of hypertension or diabetes, MA was associated with clinical CVD but not with subclinical atherosclerosis. Thus, a hypothesis may be made that the mechanism of association of MA with clinical vascular disease involves destabilization of the vasculature, leading to clinical disease.
Keywords: Aged; Aged, 80 and over; Albuminuria; Atherosclerosis; Cardiovascular Diseases; Coronary Disease; Diabetes Mellitus; Female; Humans; Hypertension; Male; Peripheral Vascular Diseases; Prevalence; Risk Factors; Stroke; United States

Association of polymorphisms in the CRP gene with circulating C-reactive protein levels and cardiovascular events. - Lange, Leslie A; Carlson, Christopher S; Hindorff, Lucia A; Lange, Ethan M; Walston, Jeremy; Durda, J Peter; Cushman, Mary; Bis, Joshua C; Zeng, Donglin; Lin, Danyu; Kuller, Lewis H; Nickerson, Deborah A; et al. (JAMA, 2006)
CONTEXT: C-reactive protein (CRP) is an inflammation protein that may play a role in the pathogenesis of cardiovascular disease (CVD). OBJECTIVE: To assess whether polymorphisms in the CRP gene are associated with plasma CRP, carotid intima-media thickness (CIMT), and CVD events. DESIGN, SETTING, AND PARTICIPANTS: In the prospective, population-based Cardiovascular Health Study, 4 tag single-nucleotide polymorphisms (SNPs) (1919A/T, 2667G/C, 3872G/A, 5237A/G) were genotyped in 3941 white (European American) participants and 5 tag SNPs (addition of 790A/T) were genotyped in 700 black (African American) participants, aged 65 years or older, all of whom were without myocardial infarction (MI) or stroke before study entry. Median follow-up was 13 years (1989-2003). MAIN OUTCOME MEASURES: Baseline CIMT; occurrence of MI, stroke, and CVD mortality during follow-up. RESULTS: In white participants, 461 incident MIs, 491 incident strokes, and 490 CVD-related deaths occurred; in black participants, 67 incident MIs, 78 incident strokes, and 75 CVD-related deaths occurred. The 1919T and 790T alleles were associated with higher CRP levels in white and black participants, respectively. The 3872A allele was associated with lower CRP levels in both populations, and the 2667C allele was associated with lower CRP levels in white participants only. There was no association between CIMT and any CRP gene polymorphism in either population. In white participants, the 1919T allele was associated with increased risk of stroke for TT vs AA (hazard ratio [HR], 1.40; 95% confidence interval [CI], 1.06-1.87) and for CVD mortality (HR, 1.40; 95% CI, 1.10-1.90). In black participants, homozygosity for the 790T allele was associated with a 4-fold increased risk of MI compared with homozygosity for the 790A allele (95% CI, 1.58-10.53). The minor alleles of the 2 SNPs associated with lower plasma CRP concentration in white participants (2667C and 3872A) were associated with decreased risk of CVD mortality. CONCLUSIONS: Genetic variation in the CRP gene is associated with plasma CRP levels and CVD risk in older adults.
Keywords: African Continental Ancestry Group; Aged; C-Reactive Protein; Cardiovascular Diseases; Carotid Arteries; European Continental Ancestry Group; Female; Genotype; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk; Stroke; Tunica Intima

Beta2-adrenergic receptor genetic variants and risk of sudden cardiac death. - Sotoodehnia, Nona; Siscovick, David S; Vatta, Matteo; Psaty, Bruce M; Tracy, Russell P; Towbin, Jeffrey A; Lemaitre, Rozenn N; Rea, Thomas D; Durda, J Peter; Chang, Joel M; Lumley, Thomas S; Kuller, Lewis H; et al. (Circulation, 2006)
BACKGROUND: Sympathetic activation influences the risk of ventricular arrhythmias and sudden cardiac death (SCD), mediated in part by the beta2-adrenergic receptor (B2AR). We investigated whether variation in the B2AR gene is associated with SCD risk. METHODS AND RESULTS: In this study, 4441 white and 808 black Cardiovascular Health Study (CHS) participants were followed up prospectively for SCD and genotyped for B2AR Gly16Arg and Gln27Glu polymorphisms. The study was replicated in 155 case and 144 control white subjects in a population-based case-control study of SCD, the Cardiac Arrest Blood Study (CABS). In CHS, Gly16 and Gln27 allele frequencies were 62.4% and 57.1% among white and 50.1% and 81.4% among black participants. Over a median follow-up of 11.1 years, 156 and 39 SCD events occurred in white and black participants, respectively. The Gln27Glu variant was associated with SCD risk (P=0.008 for general model). SCD risk was higher in Gln27 homozygous participants than in Glu27 carriers (ethnicity-adjusted hazard ratio [HR], 1.56; 95% confidence interval [CI], 1.17 to 2.09; P=0.003). The increased risk did not differ significantly between white (HR, 1.62; 95% CI, 1.18 to 2.23) and black (HR, 1.23; 95% CI, 0.61 to 2.48) participants, although the confidence interval was wide in blacks. In the CABS replication study, Gln27 homozygous participants similarly had higher SCD risk than Glu27 carriers (odds ratio, 1.64; 95% CI, 1.02 to 2.63; P=0.040). Gly16Arg was not associated with SCD risk in either study. CONCLUSIONS: Gln27 homozygous individuals have an increased risk of SCD in 2 study populations. Our findings suggest that B2AR plays a role in SCD in humans. Study of genetic variation within the B2AR gene may help identify those at increased SCD risk.
Keywords: African Continental Ancestry Group; Aged; Case-Control Studies; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Glutamine; Haplotypes; Homozygote; Humans; Male; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-2; Reproducibility of Results

Blood pressure level and outcomes in adults aged 65 and older with prior ischemic stroke. - Kaplan, Robert C; Tirschwell, David L; Longstreth, W T; Manolio, Teri A; Heckbert, Susan R; LeValley, Aaron J; Lefkowitz, David; El-Saed, Aiman; Psaty, Bruce M (J Am Geriatr Soc, 2006)
OBJECTIVES: To examine the association between blood pressure (BP) levels and long-term stroke outcomes in elderly stroke survivors. DESIGN: Observational study. SETTING: The Cardiovascular Health Study (CHS) of 5,888 community-dwelling adults. PARTICIPANTS: Two hundred fifty-four adults aged 65 and older (mean age 78.6) who sustained a nonfatal first ischemic stroke. MEASUREMENTS: BP levels assessed at prestroke and poststroke CHS visits were examined as predictors of stroke recurrence, coronary heart disease (CHD), combined vascular events (CVEs), and mortality. RESULTS: Higher poststroke BP level, assessed 261.6 days (mean) after stroke, was associated with higher risk of stroke recurrence over 5.4 years (mean) of follow-up. The multivariate-adjusted hazard ratio for stroke recurrence was 1.42 (95% confidence interval (CI) = 1.03-1.99) per standard deviation (SD) of systolic BP (P = .04) and 1.39 (95% CI = 1.01-1.91) per SD of diastolic BP (P = .04). Mortality was significantly greater in patients with low or high poststroke BP than in those with intermediate BP. Poststroke BP was not associated with risk of CHD or CVE, although further analyses suggested that high systolic BP predicted CHD and CVE in younger but not older subjects. Prestroke BP did not predict poststroke outcomes. CONCLUSION: In this observational study of adults aged 65 and older assessed approximately 8 months after stroke, low BP was associated with favorable risk of recurrent stroke, although high and low poststroke BP levels were associated with greater mortality. Long-term antihypertensive trials in older stroke survivors would increase knowledge about the benefits of lowering BP in this population.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Brain Ischemia; Female; Follow-Up Studies; Humans; Male; Outcome Assessment, Health Care; Prospective Studies; Recurrence; Stroke; Survival Rate

Characteristics and baseline clinical predictors of future fatal versus nonfatal coronary heart disease events in older adults: the Cardiovascular Health Study. - Pearte, Camille A; Furberg, Curt D; O'Meara, Ellen S; Psaty, Bruce M; Kuller, Lewis; Powe, Neil R; Manolio, Teri (Circulation, 2006)
BACKGROUND: Although >80% of annual coronary heart disease (CHD) deaths occur in adults aged >65 years and the population is aging rapidly, CHD event fatality and its predictors in the elderly have not been well described. METHODS AND RESULTS: The first myocardial infarction (MI) or CHD death among the 5888 adults aged > or =65 years occurring during enrollment in the Cardiovascular Health Study during 1989-2001 was identified and adjudicated. Characteristics measured at examinations before the event were examined for associations with case fatality (death before hospitalization or hospital discharge) and for differences in predictors by demographics or clinical history. During a median follow-up of 8.2 years, 985 CHD events occurred, of which 30% were fatal. Case fatality decreased slightly over time, ranging from 28% to 30% per year in the early 1990s versus 23% by 2000-2001; with adjustment for age at MI and gender, there was a 6% lower odds of fatality with each successive year (odds ratio [OR], 0.94; 95% confidence interval [CI], 0.90 to 0.98). Case fatality was similar by race and gender but higher with age and prior CHD (MI, angina, or revascularization). When considered alone, many subclinical disease measures, such as common carotid intima-media thickness, ankle-arm index, left ventricular mass by ECG, and a major ECG abnormality, and traditional risk factors, such as diabetes and hypertension, were associated with fatality. In multivariable analysis, independent predictors of fatality were prior congestive heart failure (OR, 3.20; 95% CI, 2.32 to 4.41), prior CHD rather than only history of MI (OR, 2.51; 95% CI, 1.84 to 3.43), diabetes (OR, 1.66; 95% CI, 1.10 to 2.31), and age (OR, 1.21 per 5 years; 95% CI, 1.07 to 1.37), adjusted for gender and each other. Prior congestive heart failure, regardless of left ventricular systolic function, age, gender, or prior CHD, conferred a > or =3-fold increased risk of fatality in almost all subgroups. CONCLUSIONS: Among community-dwelling older adults, CHD case fatality remains substantial, with easily identifiable risk factors that may be different from those that predict incident disease. In the elderly in whom the risk/benefit of therapies may be influenced by multiple competing comorbidities and care needs, risk stratification possibly may be improved further by focusing more aggressive care on specific patients, especially those with a history of congestive heart failure or prior CHD.
Keywords: Age Factors; Aged; Aged, 80 and over; Carotid Artery, Common; Cohort Studies; Comorbidity; Coronary Disease; Diabetes Mellitus; Electrocardiography; Female; Follow-Up Studies; Forecasting; Heart Failure; Heart Ventricles; Hospitalization; Humans; Hyperlipidemias; Hypertension; Male; Multivariate Analysis; Myocardial Infarction; Organ Size; Predictive Value of Tests; Risk Factors; Sampling Studies; Tunica Intima; Tunica Media; United States

Comparison of mortality risk for electrocardiographic abnormalities in men and women with and without coronary heart disease (from the Cardiovascular Health Study). - Rautaharju, Pentti M; Ge, Sijian; Nelson, Jennifer C; Marino Larsen, Emily K; Psaty, Bruce M; Furberg, Curt D; Zhang, Zhu-Ming; Robbins, John; Gottdiener, John S; Chaves, Paulo H M (Am J Cardiol, 2006)
Mortality risk associated with electrocardiographic (ECG) abnormalities has been commonly reported to be lower in women than in men. We compared coronary heart disease (CHD) and all-cause mortality risk for ECG variables during a mean 9.1-year follow-up in 4,912 participants in the Cardiovascular Health Study who were > or = 65 years of age. The hypothesis was that mortality risk for ECG abnormalities is not lower in women than in men. Five ECG variables were significant mortality predictors in Cox regression models that were adjusted for demographic, clinical, and medication variables. Gender differences were significant and mortality risk was higher in women for ECG estimates of left ventricular mass for both end points and for nondipolar QRS voltage for all-cause mortality. When evaluated simultaneously in multiple ECG variable risk models in subgroups that were stratified by baseline CHD status, no gender difference was significant. In the latter models, ST depression was a strong predictor of CHD mortality in groups with and without previous CHD. Other significant ECG predictors were previous myocardial infarction in the previous CHD group and nondipolar QRS voltage in the CHD-free group. Four ECG abnormalities were significant predictors of all-cause mortality in the CHD-free group, with risk increases of 18% to 50%. The risk of all-cause mortality in the previous CHD group was significantly increased for ST depression (by 64%), the ECG estimate of left ventricular mass (by 48%), and previous myocardial infarction (by 34%). In conclusion, we found no evidence that the relative risk of mortality for ECG abnormalities is lower in women than in men.
Keywords: Aged; Coronary Disease; Electrocardiography; Female; Humans; Male; Risk

Congestive heart failure incidence and prognosis: case identification using central adjudication versus hospital discharge diagnoses. - Schellenbaum, Gina D; Heckbert, Susan R; Smith, Nicholas L; Rea, Thomas D; Lumley, Thomas; Kitzman, Dalane W; Roger, Veronique L; Taylor, Herman A; Psaty, Bruce M (Ann Epidemiol, 2006)
PURPOSE: We compared hospitalized congestive heart failure (CHF) incidence and prognosis estimates using hospital discharge diagnoses or central adjudication. METHODS: We used the Cardiovascular Health Study (CHS), a population-based cohort study of 5888 elderly adults. A physician committee adjudicated potential CHF events, confirmed by signs, symptoms, clinical tests, and/or medical therapy. A CHF discharge diagnosis included any of these ICD-9 codes in any position: 428, 425, 398.91, 402.01, 402.11, 402.91, and 997.1. We constructed an inception cohort of 1209 hospitalized, nonfatal, incident CHF cases, identified by discharge diagnosis, adjudication, or both. RESULTS: Incidence rates for hospitalized CHF were 24.6 per 1000 person-years using discharge diagnoses and 17.1 per 1000 person-years using central adjudication. Compared to the group identified as having CHF by both methods, the group with only a discharge diagnosis (hazard ratio=0.77, 95% confidence interval=0.65-0.91) and the group with central adjudication only (hazard ratio=0.72, 95% confidence interval=0.55-0.94) had lower mortality rates. CONCLUSIONS: In the elderly, studies using only discharge diagnoses, as compared to central adjudication, may estimate higher rates of incident hospitalized CHF. Mortality following CHF onset may be similar for these methods and higher if both methods are used together.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Heart Failure; Humans; Incidence; Male; Patient Discharge; Prognosis

Mortality in pharmacologically treated older adults with diabetes: the Cardiovascular Health Study, 1989-2001. - Kronmal, Richard A; Barzilay, Joshua I; Smith, Nicholas L; Psaty, Bruce M; Kuller, Lewis H; Burke, Gregory L; Furberg, Curt (PLoS Med, 2006)
BACKGROUND: Diabetes mellitus (DM) confers an increased risk of mortality in young and middle-aged individuals and in women. It is uncertain, however, whether excess DM mortality continues beyond age 75 years, is related to type of hypoglycemic therapy, and whether women continue to be disproportionately affected by DM into older age. METHODS AND FINDINGS: From the Cardiovascular Health Study, a prospective study of 5,888 adults, we examined 5,372 participants aged 65 y or above without DM (91.2%), 322 with DM treated with oral hypoglycemic agents (OHGAs) (5.5%), and 194 with DM treated with insulin (3.3%). Participants were followed (1989-2001) for total, cardiovascular disease (CVD), coronary heart disease (CHD), and non-CVD/noncancer mortality. Compared with non-DM participants, those treated with OHGAs or insulin had adjusted hazard ratios (HRs) for total mortality of 1.33 (95% confidence interval [CI], 1.10 to 1.62) and 2.04 (95% CI, 1.62 to 2.57); CVD mortality, 1.99 (95% CI, 1.54 to 2.57) and 2.16 (95% CI, 1.54 to 3.03); CHD mortality, 2.47 (95% CI, 1.89 to 3.24) and 2.75 (95% CI, 1.95 to 3.87); and infectious and renal mortality, 1.35 (95% CI, 0.70 to 2.59) and 6.55 (95% CI, 4.18 to 10.26), respectively. The interaction of age (65-74 y versus > or =75 y) with DM was not significant. Women treated with OHGAs had a similar HR for total mortality to men, but a higher HR when treated with insulin. CONCLUSIONS: DM mortality risk remains high among older adults in the current era of medical care. Mortality risk and type of mortality differ between OHGA and insulin treatment. Women treated with insulin therapy have an especially high mortality risk. Given the high absolute CVD mortality in older people, those with DM warrant aggressive CVD risk factor reduction.
Keywords: Administration, Oral; Aged; Cardiovascular Diseases; Coronary Disease; Diabetes Mellitus; Female; Humans; Hypoglycemic Agents; Insulin; Male; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Distribution

New-onset diabetes and risk of all-cause and cardiovascular mortality: the Cardiovascular Health Study. - Smith, Nicholas L; Barzilay, Joshua I; Kronmal, Richard; Lumley, Thomas; Enquobahrie, Daniel; Psaty, Bruce M (Diabetes Care, 2006)
OBJECTIVE: Cardiovascular risk associated with new-onset diabetes is not well characterized. We hypothesized that risk of all-cause and cardiovascular mortality would be similar among participants with and without new-onset diabetes in the first years of follow-up and rise over time for new-onset diabetes. RESEARCH DESIGN AND METHODS: The Cardiovascular Health Study (CHS) is a longitudinal study of cardiovascular risk factors in adults aged > or =65 years. We used CHS participants to define a cohort (n = 282) with new-onset diabetes during 11 years of follow-up. New-onset diabetes was defined by initiation of antidiabetes medication or by fasting plasma glucose >125 mg/dl among CHS participants without diabetes at study entry. Three CHS participants without diabetes were matched for age, sex, and race to each participant with new-onset diabetes at the time of diabetes identification (n = 837). Survival analysis provided adjusted hazard ratios (HRs) for all-cause and cardiovascular mortality. RESULTS: During a median of 5.9 years of follow-up, there were 352 deaths, of which 41% were cardiovascular. In adjusted analyses, new-onset diabetes was associated with an HR of 1.9 (95% CI 1.4-2.5) for all-cause and 2.2 (1.4-3.4) for cardiovascular mortality compared with no diabetes. Mortality risks were elevated within 2 years of onset, especially cardiovascular risk (4.3 [95% CI 1.7-10.8]), and did not increase over time. CONCLUSIONS: Our findings indicate that there may be a mortality differential soon after diabetes onset in older adults and suggest that long-term macrovascular damage from atherosclerosis may not be primarily responsible for increased risk.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Blood Glucose; Cardiovascular Diseases; Diabetes Complications; Diabetes Mellitus; Follow-Up Studies; Humans; Kaplan-Meier Estimate; Risk Factors; Survival Rate; Time Factors

Alcohol consumption and risk and prognosis of atrial fibrillation among older adults: the Cardiovascular Health Study. - Mukamal, Kenneth J; Psaty, Bruce M; Rautaharju, Pentti M; Furberg, Curt D; Kuller, Lewis H; Mittleman, Murray A; Gottdiener, John S; Siscovick, David S (Am Heart J, 2007)
BACKGROUND: The relationship of alcohol consumption with risk of atrial fibrillation (AF) is inconsistent in previous studies, and its relationship with prognosis of AF is undetermined. METHODS: As part of the Cardiovascular Health Study, a population-based cohort of adults 65 years and older from 4 US communities, 5609 participants reported their use of beer, wine, and spirits yearly. We identified cases of AF with routine study electrocardiograms and validated discharge diagnoses from hospitalizations. RESULTS: A total of 1232 cases of AF were documented during a mean of 9.1 years of follow-up. Compared with long-term abstainers, the multivariable-adjusted hazard ratios were 1.25 (95% CI, 1.02-1.54) among former drinkers, 1.09 (95% CI, 0.94-1.28) among consumers of less than 1 drink per week, 1.00 (95% CI, 0.84-1.19) among consumers of 1 to 6 drinks per week, 1.06 (95% CI, 0.82-1.37) among consumers of 7 to 13 drinks per week, and 1.09 (95% CI, 0.88-1.37) among consumers of 14 or more drinks per week (P trend = 0.64). In analyses of mortality among participants with AF, the hazard ratios were 1.27 (95% CI, 1.06-1.52) among former drinkers, 0.94 (95% CI, 0.76-1.18) among consumers of less than 1 drink per week, 0.98 (95% CI, 0.78-1.23) among consumers of 1 to 6 drinks per week, 0.73 (95% CI, 0.51-1.03) among consumers of 7 to 13 drinks per week, and 0.81 (95% CI, 0.59-1.11) among consumers of 14 or more drinks per week (P trend = 0.12). CONCLUSIONS: Current moderate alcohol consumption is not associated with risk of AF or with risk of death after diagnosis of AF, but former drinking identifies individuals at higher risk.
Keywords: Aged; Alcohol Drinking; Atrial Fibrillation; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Prognosis; Risk Factors

Association of carotid artery intima-media thickness, plaques, and C-reactive protein with future cardiovascular disease and all-cause mortality: the Cardiovascular Health Study. - Cao, Jie J; Arnold, Alice M; Manolio, Teri A; Polak, Joseph F; Psaty, Bruce M; Hirsch, Calvin H; Kuller, Lewis H; Cushman, Mary (Circulation, 2007)
BACKGROUND: Carotid atherosclerosis, measured as carotid intima-media thickness or as characteristics of plaques, has been linked to cardiovascular disease (CVD) and to C-reactive protein (CRP) levels. We investigated the relationship between carotid atherosclerosis and CRP and their joint roles in CVD prediction. METHODS AND RESULTS: Of 5888 participants in the Cardiovascular Health Study, an observational study of adults aged > or = 65 years, 5020 without baseline CVD were included in the analysis. They were followed up for as long as 12 years for CVD incidence and all-cause mortality after baseline ultrasound and CRP measurement. When CRP was elevated (> 3 mg/L) among those with detectable atherosclerosis on ultrasound, there was a 72% (95% CI, 1.46 to 2.01) increased risk for CVD death and a 52% (95% CI, 1.37 to 1.68) increased risk for all-cause mortality. Elevated CRP in the absence of atherosclerosis did not increase CVD or all-cause mortality risk. The proportion of excess risk attributable to the interaction of high CRP and atherosclerosis was 54% for CVD death and 79% for all-cause mortality. Addition of CRP or carotid atherosclerosis to conventional risk factors modestly increased in the ability to predict CVD, as measured by the c statistic. CONCLUSIONS: In older adults, elevated CRP was associated with increased risk for CVD and all-cause mortality only in those with detectable atherosclerosis based on carotid ultrasound. Despite the significant associations of CRP and carotid atherosclerosis with CVD, these measures modestly improve the prediction of CVD outcomes after one accounts for the conventional risk factors.
Keywords: African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Carotid Artery Diseases; Cohort Studies; Comorbidity; Diabetes Mellitus; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Hyperlipidemias; Hypertension; Incidence; Inflammation; Kaplan-Meier Estimate; Male; Mass Screening; Mortality; Myocardial Infarction; Obesity; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; ROC Curve; Smoking; Stroke; Survival Analysis; Tunica Intima; Tunica Media; Ultrasonography; United States

Association of total insulin-like growth factor-I, insulin-like growth factor binding protein-1 (IGFBP-1), and IGFBP-3 levels with incident coronary events and ischemic stroke. - Kaplan, Robert C; McGinn, Aileen P; Pollak, Michael N; Kuller, Lewis H; Strickler, Howard D; Rohan, Tom E; Cappola, Anne R; Xue, XiaoNan; Psaty, Bruce M (J Clin Endocrinol Metab, 2007)
CONTEXT: Prior observational studies have demonstrated that the GH/IGF axis is associated with cardiovascular disease. However, this association has not been extensively studied among older adults. OBJECTIVE: The objective of this study was to assess the association between levels of total IGF-I and IGF binding proteins (IGFBP-1, IGFBP-3) and risk of incident coronary events and ischemic stroke. DESIGN AND PARTICIPANTS: A case-cohort analysis was conducted among adults 65 yr and older in the Cardiovascular Health Study. MAIN OUTCOME MEASURES: A total of 534 coronary events [316 nonfatal myocardial infarctions (MIs), 48 fatal MIs, and 170 fatal coronary heart disease events] and 370 ischemic strokes were identified on follow-up. Comparison subjects were 1122 randomly selected participants from the Cardiovascular Health Study. RESULTS: Mean follow-up time was 6.7 yr for coronary events, 5.6 yr for strokes, and 9.3 yr for comparison subjects. Hazard ratios (95% confidence intervals) associated with baseline levels of total IGF-I and IGFBPs were estimated using multivariate adjusted Cox proportional hazards models. Neither IGF-I nor IGFBP-1 levels predicted risk of incident coronary events or stroke. IGFBP-3 had an inverse association with risk of coronary events [adjusted hazard ratio per sd=0.88 (0.78-1.00), P=0.05] but was not associated with stroke. Exploratory analyses suggested that low IGF-I and low IGFBP-3 levels were significantly associated with higher risk of nonfatal MI (P<0.05) but not with risk of fatal MI or fatal coronary heart disease. CONCLUSION: Circulating levels of total IGF-I or IGFBP-1 were not associated with risk of total coronary events or ischemic stroke among older adults, whereas low IGFBP-3 level was associated with increased risk of incident coronary events.
Keywords: Aged; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; Coronary Disease; Female; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Multivariate Analysis; Risk Factors; Stroke

Clinical factors, but not C-reactive protein, predict progression of calcific aortic-valve disease: the Cardiovascular Health Study. - Novaro, Gian M; Katz, Ronit; Aviles, Ronnier J; Gottdiener, John S; Cushman, Mary; Psaty, Bruce M; Otto, Catherine M; Griffin, Brian P (J Am Coll Cardiol, 2007)
OBJECTIVES: The purpose of this study was to examine the relationship between C-reactive protein (CRP) and calcific aortic valve disease in a large, randomly selected, population-based cohort. BACKGROUND: The pathobiology of calcific aortic stenosis involves an active inflammatory, atheromatous, osteogenic process. Elevations in CRP, a measure of systemic inflammation, have been associated with aortic stenosis. METHODS: Two-dimensional and Doppler echocardiography and CRP measurement were performed at baseline in 5,621 participants in the Cardiovascular Health Study. Multivariable analysis was used to identify CRP as a predictor of baseline and incident aortic stenosis. RESULTS: At a mean echocardiographic follow-up of 5 years, 9% of subjects with aortic sclerosis progressed to some degree of aortic stenosis. Increasing age (odds ratio [OR] 1.13, 95% confidence interval [CI] 1.09 to 1.16; p < 0.001) and male gender (OR 3.05, 95% CI 1.76 to 5.27; p < 0.001) were related to risk of incident aortic stenosis, whereas increasing height (OR 0.96, 95% CI 0.94 to 0.99; p = 0.013) and African-American ethnicity conveyed a lower risk (OR 0.49, 95% CI 0.25 to 0.95; p = 0.035). C-reactive protein, treated as a continuous variable, was not associated with baseline aortic stenosis, progression to aortic sclerosis (adjusted OR 0.93, 95% CI 0.85 to 1.02; p = 0.107), or progression to aortic stenosis (adjusted OR 0.85, 95% CI 0.70 to 1.03; p = 0.092). CONCLUSIONS: In this large population-based cohort, approximately 9% of subjects with aortic sclerosis progressed to aortic stenosis over a 5-year follow-up period. There was no association between CRP levels and the presence of calcific aortic-valve disease or incident aortic stenosis. C-reactive protein appears to be a poor predictor of subclinical calcific aortic-valve disease.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; C-Reactive Protein; Calcinosis; Cardiovascular Diseases; Cohort Studies; Disease Progression; Female; Follow-Up Studies; Heart Valve Diseases; Humans; Male; Risk Factors

Inflammation biomarkers and near-term death in older men. - Jenny, Nancy Swords; Yanez, N David; Psaty, Bruce M; Kuller, Lewis H; Hirsch, Calvin H; Tracy, Russell P (Am J Epidemiol, 2007)
Associations of C-reactive protein (CRP) and fibrinogen with death may weaken over time. Combining both markers may improve prediction of death in older adults. In 5,828 Cardiovascular Health Study participants (United States, 1989-2000), 383 deaths (183 cardiovascular disease (CVD)) in years 1-3 (early) and 914 deaths (396 CVD) in years 4-8 (late) occurred. For men, when comparing highest to lowest quartiles, hazard ratios for early death were 4.1 (95% confidence interval (CI): 2.7, 6.3) for CRP and 4.1 (95% CI: 2.7, 6.4) for fibrinogen in models adjusted for CVD risk. For early CVD death, hazard ratios were 4.3 (95% CI: 2.2, 8.4) and 3.4 (95% CI: 1.8, 6.3), respectively. When comparing men in the highest quartiles of both biomarkers with those in the lowest, hazard ratios were 9.6 (95% CI: 4.3, 21.1) for early death and 13.5 (95% CI: 3.2, 56.5) for early CVD death. Associations were weaker for late deaths. For women, CRP (hazard ratio = 2.3, 95% CI: 1.4, 3.9), but not fibrinogen (hazard ratio = 1.3, 95% CI: 0.8, 2.2), was associated with early death. Results were similar for CVD death. Neither was associated with late deaths. CRP and fibrinogen were more strongly associated with death in older men than women and more strongly associated with early than late death. Combining both markers may identify older men at greatest risk of near-term death.
Keywords: Age Distribution; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Diabetes Complications; Epidemiologic Studies; Female; Fibrinogen; Follow-Up Studies; Humans; Hypercholesterolemia; Hypertension; Inflammation; Male; Middle Aged; Obesity; Population Surveillance; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Factors; Sex Distribution; Smoking; Time Factors; United States

Leukocyte telomere length and cardiovascular disease in the cardiovascular health study. - Fitzpatrick, Annette L; Kronmal, Richard A; Gardner, Jeffrey P; Psaty, Bruce M; Jenny, Nancy S; Tracy, Russell P; Walston, Jeremy; Kimura, Masyuki; Aviv, Abraham (Am J Epidemiol, 2007)
The telomere length of replicating somatic cells is inversely correlated with age and has been reported to be associated cross-sectionally with cardiovascular disease (CVD). Leukocyte telomere length, as expressed by mean terminal restriction fragment (TRF) length, was measured in 419 randomly selected participants from the Cardiovascular Health Study, comprising a community-dwelling cohort recruited in four US communities. The authors investigated associations between TRF length and selected measures of subclinical CVD/risk factors for CVD (data were collected at the 1992/1993 clinic visit) and incident CVD (ascertained through June 2002). In these participants (average age = 74.2 years (standard deviation, 5.2)), mean TRF length was 6.3 kilobase pairs (standard deviation, 0.62). Significant or borderline inverse associations were found between TRF length and diabetes, glucose, insulin, diastolic blood pressure, carotid intima-media thickness, and interleukin-6. Associations with body size and C-reactive protein were modified by gender and age, occurring only in men and in participants aged 73 years or younger. In younger (but not older) participants, each shortened kilobase pair of TRF corresponded with a threefold increased risk of myocardial infarction (hazard ratio = 3.08, 95% confidence interval: 1.22, 7.73) and stroke (hazard ratio = 3.22, 95% confidence interval: 1.29, 8.02). These results support the hypotheses that telomere attrition may be related to diseases of aging through mechanisms involving oxidative stress, inflammation, and progression to CVD.
Keywords: Aged; Cardiovascular Diseases; DNA; Female; Humans; Inflammation; Leukocytes; Male; Myocardial Infarction; Oxidative Stress; Pilot Projects; Polymorphism, Restriction Fragment Length; Risk; Risk Assessment; Risk Factors; Telomere

Serum amyloid P and cardiovascular disease in older men and women: results from the Cardiovascular Health Study. - Jenny, Nancy Swords; Arnold, Alice M; Kuller, Lewis H; Tracy, Russell P; Psaty, Bruce M (Arterioscler Thromb Vasc Biol, 2007)
OBJECTIVE: Serum amyloid P (SAP), a pentraxin like C-reactive protein (CRP), functions in innate immunity. However, associations of SAP with cardiovascular disease (CVD) are unknown. METHODS AND RESULTS: We examined these associations in the Cardiovascular Health Study using a case-cohort design. Nonexclusive case groups were incident angina (n=523), myocardial infarction (MI; n=308), stroke (n=323), and CVD death (n=288). 786 participants had no events. SAP was correlated with CRP, CVD risk factors (obesity, blood pressure, lipids), common and internal carotid wall thickness, and ankle-brachial index (all P<0.02). In Cox regression models adjusted for age, sex, and ethnicity, a standard deviation increase in SAP (9.8 mg/L) was associated with angina (hazard ratio; 95% confidence interval 1.3; 1.2 to 1.5) and MI (1.3; 1.1 to 1.5), but not stroke (1.1; 0.9 to 1.3) or CVD death (1.1; 0.9 to 1.3). Adding CRP to the models had no significant effect on associations. Adjusting for CVD risk factors slightly attenuated SAP associations with CVD events; however, associations with angina and MI remained significant. CONCLUSIONS: Although both are pentraxins, SAP and CRP may represent different facets of inflammation. The association of SAP with CVD in these older adults further supports the role of innate immunity in atherosclerosis.
Keywords: Aged; Aged, 80 and over; Aging; Angina, Unstable; Atherosclerosis; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Humans; Hypertension; Immunity, Innate; Male; Myocardial Infarction; Obesity; Prevalence; Proportional Hazards Models; Risk Factors; Serum Amyloid P-Component

Association of gene variants with incident myocardial infarction in the Cardiovascular Health Study. - Shiffman, Dov; O'Meara, Ellen S; Bare, Lance A; Rowland, Charles M; Louie, Judy Z; Arellano, Andre R; Lumley, Thomas; Rice, Kenneth; Iakoubova, Olga; Luke, May M; Young, Bradford A; Malloy, Mary J; et al. (Arterioscler Thromb Vasc Biol, 2008)
OBJECTIVE: We asked whether single nucleotide polymorphisms (SNPs) that had been nominally associated with cardiovascular disease in antecedent studies were also associated with cardiovascular disease in a population-based prospective study of 4522 individuals aged 65 or older. METHODS AND RESULTS: Based on antecedent studies, we prespecified a risk allele and an inheritance model for each of 74 SNPs. We then tested the association of these SNPs with myocardial infarction (MI) in the Cardiovascular Health Study (CHS). The prespecified risk alleles of 8 SNPs were nominally associated (1-sided P<0.05) with increased risk of MI in White CHS participants. The false discovery rate for these 8 was 0.43, suggesting that about 4 of these 8 are likely to be true positives. The 4 of these 8 SNPs that had the strongest evidence for association with cardiovascular disease before testing in CHS (association in 3 antecedent studies) were in KIF6 (CHS HR=1.29; 90%CI 1.1 to 1.52), VAMP8 (HR=1.2; 90%CI 1.02 to 1.41), TAS2R50 (HR=1.13; 90%CI 1 to 1.27), and LPA (HR=1.62; 90%CI 1.09 to 2.42). CONCLUSIONS: Although most of the SNPs investigated were not associated with MI in CHS, evidence from this investigation combined with previous studies suggests that 4 of these SNPs are likely associated with MI.
Keywords: African Americans; Aged; Aged, 80 and over; Coronary Disease; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Proportional Hazards Models; United States

Biomarkers of Inflammation and MRI-Defined Small Vessel Disease of the Brain: The Cardiovascular Health Study. - Fornage, Myriam; Chiang, Y Aron; O'Meara, Ellen S; Psaty, Bruce M; Reiner, Alexander P; Siscovick, David S; Tracy, Russell P; Longstreth, W T (Stroke, 2008)
BACKGROUND AND PURPOSE: To clarify the role of inflammation in the pathogenesis of small vessel disease of the brain, we investigated the association between common variation in the C-reactive protein (CRP) and interleukin (IL)-6 genes, plasma CRP and IL6 levels, and presence of MRI-defined white matter lesions (WML) and brain infarcts (BI) in elderly participants of the Cardiovascular Health Study. METHODS: Tag single nucleotide polymorphisms (SNPs) in the CRP and IL6 genes were selected from the SeattleSNPs database. In cross-sectional analyses, logistic regression models adjusting for known cardiovascular disease risk factors were constructed to assess the associations of plasma CRP and IL6 levels and common CRP and IL6 gene haplotypes with presence of WML or BI in Blacks (n=532) and Whites (n=2905). RESULTS: Plasma IL6 and CRP levels were associated with presence of WML and BI in both races. In Whites, common haplotypes of the IL6 gene were significantly associated with WML and BI. The common haplotype tagged by the -174G/C promoter polymorphism was associated with an increased risk of WML (OR=1.14; 95% CI: [1.02; 1.28]). The common haplotype tagged by the -572G/C promoter polymorphism was associated with an increased risk of BI (OR=1.57; 95% CI: [1.15; 2.14]). Significant associations were lacking for WML or BI with IL6 gene variation in Blacks, or with CRP gene variation in either race. CONCLUSIONS: This study provides evidence of a genetic basis underlying the relationship between plasma biomarkers of inflammation and small vessel disease of the brain. Further studies to elucidate the specific role of IL6 in disease pathogenesis are warranted.
Keywords: African Continental Ancestry Group; Aged; Biomarkers; Brain Infarction; C-Reactive Protein; Cohort Studies; European Continental Ancestry Group; Female; Haplotypes; Humans; Inflammation; Interleukin-6; Magnetic Resonance Imaging; Male; Polymorphism, Single Nucleotide

Cardiovascular and mortality risk prediction and stratification using urinary albumin excretion in older adults ages 68-102: the Cardiovascular Health Study. - Cao, Jie J; Biggs, Mary L; Barzilay, Joshua; Konen, Joseph; Psaty, Bruce M; Kuller, Lewis; Bleyer, Anthony J; Olson, Jean; Wexler, Jason; Summerson, John; Cushman, Mary (Atherosclerosis, 2008)
BACKGROUND: Elevated urinary albumin excretion (UAE) is associated with the risk of cardiovascular disease (CVD) and all-cause mortality. We tested the hypothesis that elevated UAE improves cardiovascular risk stratification in an elderly cohort aged 68-102 years. METHODS: We evaluated UAE in 3112 participants of the Cardiovascular Health Study who attended the 1996-1997 examination and had median follow up of 5.4 years. Elevated UAE was defined as urinary albumin to creatinine ratio > or =30 microg/mg. Microalbuminuria and macroalbuminuria were defined as urinary albumin to creatinine ratio 30-300 microg/mg and >300 microg/mg, respectively. Outcomes included CVD (myocardial infarction, stroke, cardiovascular death) and all-cause mortality. Cox proportional hazards models were used to assess the risk of outcomes associated with elevated UAE. RESULTS: The prevalence of elevated UAE was 14.3%, 17.1% and 26.9% in those aged 68-74, 75-84 and 85-102 years, respectively. CVD incidence and all-cause mortality were doubled (7.2% and 8.1% per year) in those with microalbuminuria and tripled (11.1% and 12.3% per year) in those with macroalbuminuria compared to those with normal UAE (3.3% and 3.8% per year). The increased CVD and mortality risks were observed in all age groups after adjustment for conventional risk factors. The adjusted population attributable risk percent of CVD and all-cause mortality for elevated UAE was 11% and 12%, respectively. When participants were cross-classified by UAE and Framingham Risk Score categories, the 5-year cumulative incidence of coronary heart disease among participants with elevated UAE and a 5-year predicted risk of 5-10% was 20%, substantially higher than 6.3% in those with UAE <30m microg/mg. CONCLUSION: Elevated UAE was associated with an increased risk of CVD and all-cause mortality in all age groups from 68 to 102 years. Combining elevated UAE with the Framingham risk scores may improve risk stratification for CVD in the elderly.
Keywords: Aged; Aged, 80 and over; Albuminuria; Biomarkers; Cohort Studies; Coronary Disease; Cross-Sectional Studies; Female; Health Surveys; Humans; Male; Predictive Value of Tests; Risk

Cardiovascular risk factors and incident acute renal failure in older adults: the cardiovascular health study. - Mittalhenkle, Anuja; Stehman-Breen, Catherine O; Shlipak, Michael G; Fried, Linda F; Katz, Ronit; Young, Bessie A; Seliger, Stephen; Gillen, Daniel; Newman, Anne B; Psaty, Bruce M; Siscovick, David (Clin J Am Soc Nephrol, 2008)
BACKGROUND AND OBJECTIVES: Although the elderly are at increased risk for acute renal failure, few prospective studies have identified risk factors for acute renal failure in the elderly. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: The associations of cardiovascular disease risk factors, subclinical cardiovascular disease, and clinical coronary heart disease with the risk for development of acute renal failure were examined in older adults in the Cardiovascular Health Study, a prospective cohort study of community-dwelling older adults. Incident hospitalized cases of acute renal failure were identified through hospital discharge International Classification of Diseases, Ninth Revision codes and confirmed through physician diagnoses of acute renal failure in discharge summaries. RESULTS: Acute renal failure developed in 225 (3.9%) of the 5731 patients during a median follow-up period of 10.2 yr. In multivariate analyses, diabetes, current smoking, hypertension, C-reactive protein, and fibrinogen were associated with acute renal failure. Prevalent coronary heart disease was associated with incident acute renal failure, and among patients without prevalent coronary heart disease, subclinical vascular disease measures were also associated with acute renal failure: Low ankle-arm index (< or =0.9), common carotid intima-media thickness, and internal carotid intima-media thickness. CONCLUSIONS: In this large, population-based, prospective cohort study, cardiovascular risk factors and both subclinical and clinical vascular disease were associated with incident acute renal failure in the elderly.
Keywords: Acute Kidney Injury; Aged; Cardiovascular Diseases; Female; Follow-Up Studies; Humans; Male; Prospective Studies; Risk Factors

Common variants in the CRP gene in relation to longevity and cause-specific mortality in older adults: the Cardiovascular Health Study. - Hindorff, Lucia A; Rice, Kenneth M; Lange, Leslie A; Diehr, Paula; Halder, Indrani; Walston, Jeremy; Kwok, Pui; Ziv, Elad; Nievergelt, Caroline; Cummings, Steven R; Newman, Anne B; Tracy, Russell P; et al. (Atherosclerosis, 2008)
Common polymorphisms in the CRP gene are associated with plasma CRP levels in population-based studies, but associations with age-related events are uncertain. A previous study of CRP haplotypes in older adults was broadened to include longevity and cause-specific mortality (all-cause, noncardiovascular (non-CV), and cardiovascular (CV)). Common haplotypes were inferred from four tagSNPs in 4512 whites and five tagSNPs in 812 blacks from the Cardiovascular Health Study, a longitudinal cohort of adults over age 65. Exploratory analyses addressed early versus late mortality. CRP haplotypes were not associated with all-cause mortality or longevity overall in either population, but associations with all-cause mortality differed during early and late periods. In blacks, the haplotype tagged by 3872A (rs1205) was associated with increased risk of non-CV mortality, relative to other haplotypes (adjusted hazard ratio for each additional copy: 1.42, 95% CI: 1.07, 1.87). Relative to other haplotypes, this haplotype was associated with decreased risk of early but not decreased risk of late CV mortality in blacks; among whites, a haplotype tagged by 2667C (rs1800947) gave similar but nonsignificant findings. If confirmed, CRP genetic variants may be weakly associated with CV and non-CV mortality in older adults, particularly in self-identified blacks.
Keywords: African Americans; Aged; C-Reactive Protein; Cardiovascular Diseases; Cause of Death; Cohort Studies; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Linear Models; Longevity; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; United States

Distribution and correlates of lipoprotein-associated phospholipase A2 in an elderly cohort: the Cardiovascular Health Study. - Furberg, Curt D; Nelson, Jeanenne J; Solomon, Cam; Cushman, Mary; Jenny, Nancy Swords; Psaty, Bruce M (J Am Geriatr Soc, 2008)
OBJECTIVES: To determine whether high levels of lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) are associated with prevalent cardiovascular disease (CVD) and to evaluate factors most influencing Lp-PLA(2) levels in a community-based cohort of older adults. DESIGN: Cross-sectional. SETTING: The Cardiovascular Health Study (CHS), a population-based cohort study of men and women aged 65 and older. PARTICIPANTS: Five thousand five hundred thirty-one CHS participants. MEASUREMENTS: Levels of Lp-PLA(2) activity were determined using stored blood samples from the baseline examination. RESULTS: Mean Lp-PLA(2) was higher in participants with electrocardiographically determined ventricular conduction defect and major Q-wave abnormality and was positively correlated with left ventricular (LV) mass. It was high in those with echocardiographically determined abnormal LV ejection fraction, which persisted after adjustment. Mean Lp-PLA(2) was also higher in participants with mild renal insufficiency and kidney disease. After multivariable adjustment, there was a modest but significant 27% greater risk of prevalent CHF per standard deviation increment of Lp-PLA(2) and a modest but significant 12% greater risk of prevalent myocardial infarction. Lp-PLA(2) was weakly but mainly most strongly correlated with cholesterol and lipoproteins, but those correlations were not especially strong. Lp-PLA(2) was weakly positively correlated with soluble intercellular adhesion molecule-1 but not interleukin-6. In total, all factors considered could explain only 29% of Lp-PLA(2) activity. CONCLUSION: Novel findings in the study are the associations, in those aged 65 and older, between Lp-PLA(2) activity and LV dysfunction, CHF, and renal disease. CVD risk factors only minimally explain levels of Lp-PLA(2).
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Atherosclerosis; Body Mass Index; Cardiac Output, Low; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Cross-Sectional Studies; Electrocardiography; Female; Heart Failure; Humans; Hypertrophy, Left Ventricular; Long QT Syndrome; Male; Reference Values; Renal Insufficiency; Risk Factors; Statistics as Topic; Triglycerides

High insulinlike growth factor binding protein 1 level predicts incident congestive heart failure in the elderly. - Kaplan, Robert C; McGinn, Aileen P; Pollak, Michael N; Kuller, Lewis; Strickler, Howard D; Rohan, Thomas E; Cappola, Anne R; Xue, XiaoNan; Psaty, Bruce M (Am Heart J, 2008)
BACKGROUND: Low levels of insulinlike growth factor 1 (IGF-I) may influence the development of age-related cardiovascular diseases including congestive heart failure (CHF). Insulinlike growth factor binding protein 1 (IGFBP-1), which increases during catabolic states and inhibits anabolic IGF-I effects, is increased in patients with CHF and has been associated prospectively with increased mortality among older adults and survivors of myocardial infarction. We investigated the association between fasting plasma levels of IGF-I, IGFBP-1, IGFBP-3, and insulin and risk of incident CHF in the prospective Cardiovascular Health Study. METHODS: From among 5,888 adults 65 years old and older in the Cardiovascular Health Study, we studied 566 incident CHF cases and 1,072 comparison subjects after exclusion of underweight individuals (body mass index <18.5 kg/m(2)) and insulin users. Hazard ratios (HRs) with 95% CIs for CHF were estimated after adjustment for age, race, sex, hypertension, systolic blood pressure, lipid levels, left ventricular hypertrophy, coronary disease, C-reactive protein, health status, diabetes, and body mass index. RESULTS: High baseline IGFBP-1 level was a significant predictor of CHF, independent of established CHF risk factors and inflammation markers. The HR per SD of IGFBP-1 was 1.22 (95% CI 1.07-1.39, P < .01). Relative to the lowest IGFBP-1 tertile, the HR was 1.29 (95% CI 0.96-1.74, P = .09) for the second IGFBP-1 tertile and 1.47 (95% CI 1.06-2.04; P = .02) for the highest IGFBP-1 tertile (tertile cut points 19.5 and 35.8 ng/mL). Total IGF-I, IGFBP-3, or insulin levels had no association with CHF after adjustment for CHF risk factors. CONCLUSIONS: High circulating IGFBP-1 level may be a CHF risk factor among older adults.
Keywords: Aged; Aged, 80 and over; Female; Heart Failure; Humans; Incidence; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Predictive Value of Tests; Prospective Studies; Risk Factors

Insulin-like growth factor-(IGF)-axis, inflammation, and glucose intolerance among older adults. - Rajpathak, Swapnil N; McGinn, Aileen P; Strickler, Howard D; Rohan, Thomas E; Pollak, Michael; Cappola, Anne R; Kuller, Lewis; Xue, XiaoNan; Newman, Anne B; Strotmeyer, Elsa S; Psaty, Bruce M; Kaplan, Robert C (Growth Horm IGF Res, 2008)
Increasing evidence suggests that the insulin-like growth factor (IGF)-axis may play a role in glucose metabolism and may also be associated with systemic inflammation. The aim of this study was to evaluate the association of insulin-like growth factor-1 (IGF-I) and its binding proteins, IGFBP-1 and IGFBP-3, with glucose intolerance and inflammation among older adults. We conducted a cross-sectional analysis in a in a random subsample (n=922) of the Cardiovascular Health Study (CHS), a prospective cohort of men and women > or = 65 years. Mean IGFBP-1 levels were significantly lower in older adults with impaired glucose tolerance (IGT), impaired fasting glucose (IFG) and diabetes compared to those with normal fasting and post-load glucose. High IGFBP-1 was associated with a reduced prevalence of IGT and IFG; the multivariable OR between extreme quartiles of IGFBP-1 was 0.60 (95% CI: 0.37, 0.95; p-trend: 0.03) for IGT and 0.41 (95% CI: 0.26, 0.64; p-trend: <0.01) for IFG. We did not find any significant association between IGF-I and glucose intolerance in this study and the association for IGFBP-3 was less clear. However, low levels of IGF-I and IGFBP-3 were associated with increased levels of markers of inflammation including C-reactive protein and interleukin-6 levels. We conclude that among adults > or = 65 years, low IGFBP-1 levels are associated with increased prevalence of glucose intolerance. We did not confirm prior associations of low IGF-I with glucose intolerance in this cohort of older individuals.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Cross-Sectional Studies; Female; Glucose Intolerance; Humans; Inflammation; Insulin-Like Growth Factor Binding Proteins; Male; Signal Transduction; Somatomedins

Lipoprotein-associated phospholipase A2 and risk of venous thrombosis in older adults. - Olson, Nels; O'Meara, Ellen S; Jenny, Nancy S; Folsom, Aaron R; Bovill, Edwin G; Furberg, Curt D; Heckbert, Susan R; Psaty, Bruce M; Cushman, Mary (Am J Hematol, 2008)
Lipoprotein-associated phospholipase A2 (Lp-PLA2) is an enzyme involved in inflammation and platelet function. Inherited deficiency and elevated levels are associated with atherosclerosis. Given potential common etiologies of atherosclerosis and venous thrombosis (VT), we hypothesized that low and high Lp-PLA2 would be associated with VT risk. Lp-PLA(2) mass and activity were measured in baseline samples of Cardiovascular Health Study participants (5,888 men and women age > or =65), excluding 354 reporting pre-baseline VT. The study endpoint was VT unrelated to cancer after 11.6 years follow-up. Hazard ratios were estimated using Cox proportional hazard models, adjusting for age, race, sex, and body-mass index. With 129 cases of VT, there was no association of Lp-PLA2 activity with risk. Adjusted hazard ratios were 1.19 (CI 0.62, 2.29) and 0.87 (CI 0.43, 1.76) for the lowest and highest decile, respectively, compared to the 10-25th percentile. Corresponding hazard ratios for Lp-PLA2 mass were 1.63 (CI 0.79, 3.34) and 1.33 (CI 0.61, 2.87). Results were robust to several definitions of low or high Lp-PLA2. While the association of Lp-PLA(2) levels with arterial disease events implies a role for this enzyme in atherogenesis, our findings suggest that it is not prothrombotic.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Female; Humans; Male; Risk Factors; Venous Thrombosis

Physical activity and incidence of atrial fibrillation in older adults: the cardiovascular health study. - Mozaffarian, Dariush; Furberg, Curt D; Psaty, Bruce M; Siscovick, David (Circulation, 2008)
BACKGROUND: Vigorous exertion and endurance training have been reported to increase atrial fibrillation (AF). Associations of habitual light or moderate activity with AF incidence have not been evaluated. METHODS AND RESULTS: We prospectively investigated associations of leisure-time activity, exercise intensity, and walking habits, assessed at baseline and updated during follow-up visits, with incident AF, diagnosed by annual 12-lead ECGs and hospital discharge records, from 1989 to 2001 among 5446 adults > or =65 years of age in the Cardiovascular Health Study. During 47 280 person-years of follow-up, 1061 new AF cases occurred (incidence 22.4/1000 person-years). In multivariable-adjusted analyses, leisure-time activity was associated with lower AF incidence in a graded manner, with 25% (hazard ratio [HR] 0.75, 95% confidence interval [CI] 0.61 to 0.90), 22% (HR 0.78, 95% CI 0.65 to 0.95), and 36% (HR 0.64, 95% CI 0.52 to 0.79) lower risk in quintiles 3, 4, and 5 versus quintile 1 (P for trend <0.001). Exercise intensity had a U-shaped relationship with AF (quadratic P=0.02): Versus no exercise, AF incidence was lower with moderate-intensity exercise (HR 0.72, 95% CI 0.58 to 0.89) but not with high-intensity exercise (HR 0.87, 95% CI 0.64 to 1.19). Walking distance and pace were each associated with lower AF risk in a graded manner (P for trend <0.001); when we assessed the combined effects of distance and pace, individuals in quartiles 2, 3, and 4 had 25% (HR 0.75, 95% CI 0.56 to 0.99), 32% (HR 0.68, 95% CI 0.50 to 0.92), and 44% (HR 0.56, 95% CI 0.38 to 0.82) lower AF incidence than individuals in quartile 1. Findings appeared unrelated to confounding by comorbidity or indication. After evaluation of cut points of moderate leisure-time activity (approximately 600 kcal/week), walking distance (12 blocks per week), and pace (2 mph), 26% of all new AF cases (95% CI 7% to 43%) appeared attributable to absence of these activities. CONCLUSIONS: Light to moderate physical activities, particularly leisure-time activity and walking, are associated with significantly lower AF incidence in older adults.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Exercise; Female; Humans; Incidence; Leisure Activities; Male; Motor Activity; Prospective Studies; Walking

Prevalence, prognosis, and implications of isolated minor nonspecific ST-segment and T-wave abnormalities in older adults: Cardiovascular Health Study. - Kumar, Anita; Prineas, Ronald J; Arnold, Alice M; Psaty, Bruce M; Furberg, Curt D; Robbins, John; Lloyd-Jones, Donald M (Circulation, 2008)
BACKGROUND: The prevalence and prognostic significance of isolated minor nonspecific ST-segment and T-wave abnormalities (NSSTTAs) in older adults are poorly understood. METHODS AND RESULTS: Cardiovascular Health Study participants free of both clinical cardiovascular disease and major ECG abnormalities were included. We examined the prospective association of isolated minor NSSTTAs (defined by Minnesota Codes 4-3, 4-4, 5-3, and 5-4) with total, cardiovascular, and coronary mortality and incident nonfatal myocardial infarction. Among 3224 participants (61.9% women; mean age, 72 years), 233 (7.2%) had isolated NSSTTAs at baseline. Covariates associated with isolated NSSTTAs included older age, nonwhite race (20.5% of blacks versus 4.8% of whites; P<0.001), diabetes, and higher blood pressure and body mass index but not the presence of subclinical cardiovascular disease. After 39 518 person-years of follow-up, the presence of isolated NSSTTAs was associated with significantly increased risk for coronary heart disease mortality (multivariable-adjusted hazards ratio, 1.76; 95% CI, 1.18 to 2.61) but not with incident nonfatal myocardial infarction (multivariable-adjusted hazards ratio, 0.71; 95% CI, 0.43 to 1.17). The association of isolated NSSTTAs with coronary death was independent of subclinical atherosclerosis and left ventricular mass measures. In secondary analyses, among those with cardiac death, there was a significantly higher rate of primary arrhythmic death (32.3% versus 15.4%; P=0.02) in participants with isolated NSSTTAs versus those without NSSTTAs. CONCLUSIONS: Isolated NSSTTAs are common in older Americans and are associated with significantly increased risk for coronary death. However, isolated NSSTTAs are not associated with incident nonfatal myocardial infarction, suggesting that they are associated particularly with increased risk for primary arrhythmic death.
Keywords: Age Factors; Aged; Arrhythmias, Cardiac; Cardiovascular Diseases; Cohort Studies; Electrocardiography; Female; Health Status; Humans; Male; Middle Aged; Prevalence; Prognosis; Prospective Studies

The relationship between exercise and risk of venous thrombosis in elderly people. - van Stralen, Karlijn J; Doggen, Carine J M; Lumley, Thomas; Cushman, Mary; Folsom, Aaron R; Psaty, Bruce M; Siscovick, David; Rosendaal, Frits R; Heckbert, Susan R (J Am Geriatr Soc, 2008)
OBJECTIVES: To study whether exercise is associated with the risk of venous thrombosis in elderly people. DESIGN: Observational study with a median follow-up of 11.6 years. SETTING: The Cardiovascular Health Study in four U.S. communities. PARTICIPANTS: People aged 65 and older without prior venous thrombosis (deep venous thrombosis or pulmonary embolism). MEASUREMENTS: Self-reported exercise was measured two or three times during follow-up and was defined as expending more than 500 kcal/wk on exercise, including walking for exercise. Venous thrombosis cases were verified using medical record review. RESULTS: Of 5,534 participants, 171 developed a first venous thrombosis. Self-reported exercise at baseline was not related to the risk of venous thrombosis after adjustment for sex, age, race, self-reported health, and body mass index (adjusted hazard ratio (HR(adj))=1.16, 95% confidence interval (CI)=0.84-1.61), although with exercise modeled as a time-varying exposure, overall results were in the direction of greater risk of venous thrombosis (HR(adj)=1.38, 95% CI=0.99-1.91). For mild-intensity exercise, such as walking, there was a nonsignificant finding in the direction of benefit (HR(adj)=0.75, 95% CI=0.49-1.16), but strenuous exercise, such as jogging, was associated with greater risk of venous thrombosis (HR(adj)=1.75, 95% CI=1.08-2.83) than no exercise at all. CONCLUSION: In elderly people, strenuous exercise was associated with a higher risk of venous thrombosis than no exercise at all. Future studies are needed to explain this unexpected higher risk.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cohort Studies; Energy Metabolism; Exercise; Female; Humans; Male; Prevalence; Risk Factors; United States; Venous Thrombosis

Total insulinlike growth factor 1 and insulinlike growth factor binding protein levels, functional status, and mortality in older adults. - Kaplan, Robert C; McGinn, Aileen P; Pollak, Michael N; Kuller, Lewis; Strickler, Howard D; Rohan, Thomas E; Xue, XiaoNan; Kritchevsky, Stephen B; Newman, Anne B; Psaty, Bruce M (J Am Geriatr Soc, 2008)
OBJECTIVES: To assess the association between total insulinlike growth factor (IGF)-1, IGF binding protein-1 (IGFBP-1), and IGFBP-3 levels and functioning and mortality in older adults. DESIGN: Cohort study. SETTING/PARTICIPANTS: One thousand one hundred twenty-two individuals aged 65 and older without prior cardiovascular disease events participating in the Cardiovascular Health Study. MEASUREMENTS: Baseline fasting plasma levels of IGF-1, IGFBP-1, and IGFBP-3 (defined as tertiles, T1-T3) were examined in relationship to handgrip strength, time to walk 15 feet, development of new difficulties with activities of daily living (ADLs), and mortality. RESULTS: Higher IGFBP-1 predicted worse handgrip strength (P-trend(T1-T3)<.01) and slower walking speed (P-trend(T1-T3)=.03), lower IGF-1 had a borderline significant association with worse handgrip strength (P-trend(T1-T3)=.06), and better grip strength was observed in the middle IGFBP-3 tertile than in the low or high tertiles (P=.03). Adjusted for age, sex, and race, high IGFBP-1 predicted greater mortality (P-trend(T1-T3)<.001, hazard ratio (HR)(T3vsT1)=1.48, 95% confidence interval (CI)=1.15-1.90); this association was borderline significant after additional confounder adjustment (P-trend(T1-T3)=.05, HR(T3vsT1)=1.35, 95% CI=0.98-1.87). High IGFBP-1 was associated with greater risk of incident ADL difficulties after adjustment for age, sex, race, and other confounders (P-trend(T1-T3)=.04, HR(T3vsT1)=1.40, CI=1.01-1.94). Neither IGF-1 nor IGFBP-3 level predicted mortality or incident ADL difficulties. CONCLUSION: In adults aged 65 and older, high IGFBP-1 levels were associated with greater risk of mortality and poorer functional ability, whereas IGF-1 and IGFBP-3 had little association with these outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Enzyme-Linked Immunosorbent Assay; Fasting; Female; Follow-Up Studies; Hand Strength; Humans; Incidence; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Middle Aged; Prognosis; Prospective Studies; Risk Factors; Survival Rate; United States; Walking

Agreement between nosologist and cardiovascular health study review of deaths: implications of coding differences. - Ives, Diane G; Samuel, Paulraj; Psaty, Bruce M; Kuller, Lewis H (J Am Geriatr Soc, 2009)
OBJECTIVES: To compare nosologist coding of underlying cause of death according to the death certificate with adjudicated cause of death for subjects aged 65 and older in the Cardiovascular Health Study (CHS). DESIGN: Observational. SETTING: Four communities: Forsyth County, North Carolina (Wake Forest University); Sacramento County, California (University of California at Davis); Washington County, Maryland (Johns Hopkins University); and Pittsburgh, Pennsylvania (University of Pittsburgh). PARTICIPANTS: Men and women aged 65 and older participating in CHS, a longitudinal study of coronary heart disease and stroke, who died through June 2004. MEASUREMENTS: The CHS centrally adjudicated underlying cause of death for 3,194 fatal events from June 1989 to June 2004 using medical records, death certificates, proxy interviews, and autopsies, and results were compared with underlying cause of death assigned by a trained nosologist based on death certificate only. RESULTS: Comparison of 3,194 CHS versus nosologist underlying cause of death revealed moderate agreement except for cancer (kappa=0.91, 95% confidence interval (CI)=0.89-0.93). kappas varied according to category (coronary heart disease, kappa=0.61, 95% CI=0.58-0.64; stroke, kappa=0.59, 95% CI=0.54-0.64; chronic obstructive pulmonary disease, kappa=0.58, 95% CI=0.51-0.65; dementia, kappa=0.40, 95% CI=0.34-0.45; and pneumonia, kappa=0.35, 95% CI=0.29-0.42). Differences between CHS and nosologist coding of dementia were found especially in older ages in the sex and race categories. CHS attributed 340 (10.6%) deaths due to dementia, whereas nosologist coding attributed only 113 (3.5%) to dementia as the underlying cause. CONCLUSION: Studies that use only death certificates to determine cause of death may result in misclassification and potential bias. Changing trends in cause-specific mortality in older individuals may be a function of classification process rather than incidence and case fatality.
Keywords: Aged; Aged, 80 and over; Cause of Death; Coronary Disease; Death Certificates; Female; Forms and Records Control; Humans; Longitudinal Studies; Male; Stroke

Association of common genetic variation in the insulin/IGF1 signaling pathway with human longevity. - Pawlikowska, Ludmila; Hu, Donglei; Huntsman, Scott; Sung, Andrew; Chu, Catherine; Chen, Justin; Joyner, Alexander H; Schork, Nicholas J; Hsueh, Wen-Chi; Reiner, Alexander P; Psaty, Bruce M; Atzmon, Gil; et al. (Aging Cell, 2009)
The insulin/IGF1 signaling pathways affect lifespan in several model organisms, including worms, flies and mice. To investigate whether common genetic variation in this pathway influences lifespan in humans, we genotyped 291 common variants in 30 genes encoding proteins in the insulin/IGF1 signaling pathway in a cohort of elderly Caucasian women selected from the Study of Osteoporotic Fractures (SOF). The cohort included 293 long-lived cases (lifespan > or = 92 years (y), mean +/- standard deviation (SD) = 95.3 +/- 2.2y) and 603 average-lifespan controls (lifespan < or = 79y, mean = 75.7 +/- 2.6y). Variants were selected for genotyping using a haplotype-tagging approach. We found a modest excess of variants nominally associated with longevity. Nominally significant variants were then replicated in two additional Caucasian cohorts including both males and females: the Cardiovascular Health Study and Ashkenazi Jewish Centenarians. An intronic single nucleotide polymorphism in AKT1, rs3803304, was significantly associated with lifespan in a meta-analysis across the three cohorts (OR = 0.78 95%CI = 0.68-0.89, adjusted P = 0.043); two intronic single nucleotide polymorphisms in FOXO3A demonstrated a significant lifespan association among women only (rs1935949, OR = 1.35, 95%CI = 1.15-1.57, adjusted P = 0.0093). These results demonstrate that common variants in several genes in the insulin/IGF1 pathway are associated with human lifespan.
Keywords: Aged; Aged, 80 and over; Female; Follow-Up Studies; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome, Human; Genotype; Humans; Insulin; Insulin-Like Growth Factor I; Longevity; Male; Osteoporosis; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins c-akt; Signal Transduction

Association of novel genetic Loci with circulating fibrinogen levels: a genome-wide association study in 6 population-based cohorts. - Dehghan, Abbas; Yang, Qiong; Peters, Annette; Basu, Saonli; Bis, Joshua C; Rudnicka, Alicja R; Kavousi, Maryam; Chen, Ming-Huei; Baumert, Jens; Lowe, Gordon D O; McKnight, Barbara; Tang, Weihong; et al. (Circ Cardiovasc Genet, 2009)
BACKGROUND: Fibrinogen is both central to blood coagulation and an acute-phase reactant. We aimed to identify common variants influencing circulation fibrinogen levels. METHODS AND RESULTS: We conducted a genome-wide association analysis on 6 population-based studies, the Rotterdam Study, the Framingham Heart Study, the Cardiovascular Health Study, the Atherosclerosis Risk in Communities Study, the Monitoring of Trends and Determinants in Cardiovascular Disease/KORA Augsburg Study, and the British 1958 Birth Cohort Study, including 22 096 participants of European ancestry. Four loci were marked by 1 or more single-nucleotide polymorphisms that demonstrated genome-wide significance (P<5.0 x 10(-8)). These included a single-nucleotide polymorphism located in the fibrinogen beta chain (FGB) gene and 3 single-nucleotide polymorphisms representing newly identified loci. The high-signal single-nucleotide polymorphisms were rs1800789 in exon 7 of FGB (P=1.8 x 10(-30)), rs2522056 downstream from the interferon regulatory factor 1 (IRF1) gene (P=1.3 x 10(-15)), rs511154 within intron 1 of the propionyl coenzyme A carboxylase (PCCB) gene (P=5.9 x 10(-10)), and rs1539019 on the NLR family pyrin domain containing 3 isoforms (NLRP3) gene (P=1.04 x 10(-8)). CONCLUSIONS: Our findings highlight biological pathways that may be important in regulation of inflammation underlying cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Associations of pentraxin 3 with cardiovascular disease and all-cause death: the Cardiovascular Health Study. - Jenny, Nancy Swords; Arnold, Alice M; Kuller, Lewis H; Tracy, Russell P; Psaty, Bruce M (Arterioscler Thromb Vasc Biol, 2009)
OBJECTIVE: We examined associations of pentraxin 3 (PTX3), a vascular inflammation marker, with incident cardiovascular disease (CVD) and all-cause death. METHODS AND RESULTS: 1583 Cardiovascular Health Study participants free of prevalent CVD were included. Nonexclusive case groups were angina (n=476), myocardial infarction (MI; n=237), stroke (n=310), CVD death (n=282), and all-cause death (n=772). 535 participants had no events. PTX3 levels were higher in those with subclinical CVD (1.90+/-1.89 ng/mL) than those without (1.71+/-1.88 ng/mL; P=0.001). Using Cox regression adjusted for age, sex, and ethnicity, a standard deviation increase in PTX3 (1.89 ng/mL) was associated with CVD death (hazard ratio 1.11; 95% confidence interval 1.02 to 1.21) and all-cause death (1.08; 1.02 to 1.15). PTX3 was not associated with angina (1.09; 0.98 to 1.20), MI (0.96; 0.81 to 1.12), or stroke (1.06; 0.95 to 1.18). Adding C-reactive protein (CRP) or CVD risk factors to the models had no significant effects on associations. CONCLUSIONS: In these older adults, PTX3 was associated with CVD and all-cause death independent of CRP and CVD risk factors. PTX3 likely reflects different aspects of inflammation than CRP and may provide insight into vascular health in aging and chronic diseases of aging that lead to death.
Keywords: Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Health Surveys; Humans; Inflammation Mediators; Linear Models; Male; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Serum Amyloid P-Component; Time Factors; United States; Up-Regulation

Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium: Design of prospective meta-analyses of genome-wide association studies from 5 cohorts. - Psaty, Bruce M; O'Donnell, Christopher J; Gudnason, Vilmundur; Lunetta, Kathryn L; Folsom, Aaron R; Rotter, Jerome I; Uitterlinden, André G; Harris, Tamara B; Witteman, Jacqueline C M; Boerwinkle, Eric (Circ Cardiovasc Genet, 2009)
BACKGROUND: The primary aim of genome-wide association studies is to identify novel genetic loci associated with interindividual variation in the levels of risk factors, the degree of subclinical disease, or the risk of clinical disease. The requirement for large sample sizes and the importance of replication have served as powerful incentives for scientific collaboration. Methods- The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium was formed to facilitate genome-wide association studies meta-analyses and replication opportunities among multiple large population-based cohort studies, which collect data in a standardized fashion and represent the preferred method for estimating disease incidence. The design of the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium includes 5 prospective cohort studies from the United States and Europe: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. With genome-wide data on a total of about 38 000 individuals, these cohort studies have a large number of health-related phenotypes measured in similar ways. For each harmonized trait, within-cohort genome-wide association study analyses are combined by meta-analysis. A prospective meta-analysis of data from all 5 cohorts, with a properly selected level of genome-wide statistical significance, is a powerful approach to finding genuine phenotypic associations with novel genetic loci. CONCLUSIONS: The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and collaborating non-member studies or consortia provide an excellent framework for the identification of the genetic determinants of risk factors, subclinical-disease measures, and clinical events.
Keywords: Adult; Aged; Aging; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Diseases; Humans; Male; Meta-Analysis as Topic; Middle Aged; Phenotype; Research Design; Risk Factors

Common variants at ten loci influence QT interval duration in the QTGEN Study. - Newton-Cheh, Christopher; Eijgelsheim, Mark; Rice, Kenneth M; de Bakker, Paul I W; Yin, Xiaoyan; Estrada, Karol; Bis, Joshua C; Marciante, Kristin; Rivadeneira, Fernando; Noseworthy, Peter A; Sotoodehnia, Nona; Smith, Nicholas L; et al. (Nat Genet, 2009)
QT interval duration, reflecting myocardial repolarization on the electrocardiogram, is a heritable risk factor for sudden cardiac death and drug-induced arrhythmias. We conducted a meta-analysis of three genome-wide association studies in 13,685 individuals of European ancestry from the Framingham Heart Study, the Rotterdam Study and the Cardiovascular Health Study, as part of the QTGEN consortium. We observed associations at P < 5 x 10(-8) with variants in NOS1AP, KCNQ1, KCNE1, KCNH2 and SCN5A, known to be involved in myocardial repolarization and mendelian long-QT syndromes. Associations were found at five newly identified loci, including 16q21 near NDRG4 and GINS3, 6q22 near PLN, 1p36 near RNF207, 16p13 near LITAF and 17q12 near LIG3 and RFFL. Collectively, the 14 independent variants at these 10 loci explain 5.4-6.5% of the variation in QT interval. These results, together with an accompanying paper, offer insights into myocardial repolarization and suggest candidate genes that could predispose to sudden cardiac death and drug-induced arrhythmias.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Aged; Arrhythmias, Cardiac; Chromosome Mapping; Death, Sudden, Cardiac; Electroencephalography; ERG1 Potassium Channel; Ether-A-Go-Go Potassium Channels; European Continental Ancestry Group; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Humans; KCNQ1 Potassium Channel; Meta-Analysis as Topic; Muscle Proteins; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Potassium Channels, Voltage-Gated; Risk Factors; Sodium Channels

Gene variants associated with ischemic stroke: the cardiovascular health study. - Luke, May M; O'Meara, Ellen S; Rowland, Charles M; Shiffman, Dov; Bare, Lance A; Arellano, Andre R; Longstreth, W T; Lumley, Thomas; Rice, Kenneth; Tracy, Russell P; Devlin, James J; Psaty, Bruce M (Stroke, 2009)
BACKGROUND AND PURPOSE: The purpose of this study was to determine whether 74 single nucleotide polymorphisms (SNPs), which had been associated with coronary heart disease, are associated with incident ischemic stroke. METHODS: Based on antecedent studies of coronary heart disease, we prespecified the risk allele for each of the 74 SNPs. We used Cox proportional hazards models that adjusted for traditional risk factors to estimate the associations of these SNPs with incident ischemic stroke during 14 years of follow-up in a population-based study of older adults: the Cardiovascular Health Study (CHS). RESULTS: In white CHS participants, the prespecified risk alleles of 7 of the 74 SNPs (in HPS1, ITGAE, ABCG2, MYH15, FSTL4, CALM1, and BAT2) were nominally associated with increased risk of stroke (one-sided P<0.05, false discovery rate=0.42). In black participants, the prespecified risk alleles of 5 SNPs (in KRT4, LY6G5B, EDG1, DMXL2, and ABCG2) were nominally associated with stroke (one-sided P<0.05, false discovery rate=0.55). The Val12Met SNP in ABCG2 was associated with stroke in both white (hazard ratio, 1.46; 90% CI, 1.05 to 2.03) and black (hazard ratio, 3.59; 90% CI, 1.11 to 11.6) participants of CHS. Kaplan-Meier estimates of the 10-year cumulative incidence of stroke were greater among Val allele homozygotes than among Met allele carriers in both white (10% versus 6%) and black (12% versus 3%) participants of CHS. CONCLUSIONS: The Val12Met SNP in ABCG2 (encoding a transporter of sterols and xenobiotics) was associated with incident ischemic stroke in white and black participants of CHS.
Keywords: African Continental Ancestry Group; Aged; Alleles; Brain Ischemia; Cardiovascular Diseases; Coronary Disease; Ethnic Groups; European Continental Ancestry Group; Female; Gene Frequency; Genetic Variation; Humans; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Stroke; United States

Genetic variants associated with cardiac structure and function: a meta-analysis and replication of genome-wide association data. - Vasan, Ramachandran S; Glazer, Nicole L; Felix, Janine F; Lieb, Wolfgang; Wild, Philipp S; Felix, Stephan B; Watzinger, Norbert; Larson, Martin G; Smith, Nicholas L; Dehghan, Abbas; Grosshennig, Anika; Schillert, Arne; et al. (JAMA, 2009)
CONTEXT: Echocardiographic measures of left ventricular (LV) structure and function are heritable phenotypes of cardiovascular disease. OBJECTIVE: To identify common genetic variants associated with cardiac structure and function by conducting a meta-analysis of genome-wide association data in 5 population-based cohort studies (stage 1) with replication (stage 2) in 2 other community-based samples. DESIGN, SETTING, AND PARTICIPANTS: Within each of 5 community-based cohorts comprising the EchoGen consortium (stage 1; n = 12 612 individuals of European ancestry; 55% women, aged 26-95 years; examinations between 1978-2008), we estimated the association between approximately 2.5 million single-nucleotide polymorphisms (SNPs; imputed to the HapMap CEU panel) and echocardiographic traits. In stage 2, SNPs significantly associated with traits in stage 1 were tested for association in 2 other cohorts (n = 4094 people of European ancestry). Using a prespecified P value threshold of 5 x 10(-7) to indicate genome-wide significance, we performed an inverse variance-weighted fixed-effects meta-analysis of genome-wide association data from each cohort. MAIN OUTCOME MEASURES: Echocardiographic traits: LV mass, internal dimensions, wall thickness, systolic dysfunction, aortic root, and left atrial size. RESULTS: In stage 1, 16 genetic loci were associated with 5 echocardiographic traits: 1 each with LV internal dimensions and systolic dysfunction, 3 each with LV mass and wall thickness, and 8 with aortic root size. In stage 2, 5 loci replicated (6q22 locus associated with LV diastolic dimensions, explaining <1% of trait variance; 5q23, 12p12, 12q14, and 17p13 associated with aortic root size, explaining 1%-3% of trait variance). CONCLUSIONS: We identified 5 genetic loci harboring common variants that were associated with variation in LV diastolic dimensions and aortic root size, but such findings explained a very small proportion of variance. Further studies are required to replicate these findings, identify the causal variants at or near these loci, characterize their functional significance, and determine whether they are related to overt cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Aorta; Cardiovascular Diseases; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Atria; Heart Ventricles; Humans; Male; Middle Aged; Organ Size; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Ventricular Dysfunction, Left; Ventricular Function, Left

Genetic variations in nitric oxide synthase 1 adaptor protein are associated with sudden cardiac death in US white community-based populations. - Kao, W H Linda; Arking, Dan E; Post, Wendy; Rea, Thomas D; Sotoodehnia, Nona; Prineas, Ronald J; Bishe, Bryan; Doan, Betty Q; Boerwinkle, Eric; Psaty, Bruce M; Tomaselli, Gordon F; Coresh, Josef; et al. (Circulation, 2009)
BACKGROUND: The ECG QT interval is associated with risk of sudden cardiac death (SCD). A previous genome-wide association study demonstrated that allelic variants (rs10494366 and rs4657139) in the nitric oxide synthase 1 adaptor protein (NOS1AP), which encodes a carboxy-terminal PDZ ligand of neuronal nitric oxide synthase, are associated with the QT interval in white adults. The present analysis was conducted to validate the association between NOS1AP variants and the QT interval and to examine the association with SCD in a combined population of 19 295 black and white adults from the Atherosclerosis Risk In Communities Study and the Cardiovascular Health Study. METHODS AND RESULTS: We examined 19 tagging single-nucleotide polymorphisms in the genomic blocks containing rs10494366 and rs4657139 in NOS1AP. SCD was defined as a sudden pulseless condition of cardiac origin in a previously stable individual. General linear models and Cox proportional hazards regression models were used. Multiple single-nucleotide polymorphisms in NOS1AP, including rs10494366, rs4657139, and rs16847548, were significantly associated with adjusted QT interval in whites (P<0.0001). In whites, after adjustment for age, sex, and study, the relative hazard of SCD associated with each C allele at rs16847548 was 1.31 (95% confidence interval 1.10 to 1.56, P=0.002), assuming an additive model. In addition, a downstream neighboring single-nucleotide polymorphism, rs12567209, which was not correlated with rs16847548 or QT interval, was also independently associated with SCD in whites (relative hazard 0.57, 95% confidence interval 0.39 to 0.83, P=0.003). Adjustment for QT interval and coronary heart disease risk factors attenuated but did not eliminate the association between rs16847548 and SCD, and such adjustment had no effect on the association between rs12567209 and SCD. No significant associations between tagging single-nucleotide polymorphisms in NOS1AP and either QT interval or SCD were observed in blacks. CONCLUSIONS: In a combined analysis of 2 population-based prospective cohort studies, sequence variations in NOS1AP were associated with baseline QT interval and the risk of SCD in white US adults.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Death, Sudden, Cardiac; Electrocardiography; European Continental Ancestry Group; Genotype; Humans; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomewide association studies of stroke. - Ikram, M Arfan; Seshadri, Sudha; Bis, Joshua C; Fornage, Myriam; DeStefano, Anita L; Aulchenko, Yurii S; Debette, Stephanie; Lumley, Thomas; Folsom, Aaron R; van den Herik, Evita G; Bos, Michiel J; Beiser, Alexa; et al. (N Engl J Med, 2009)
BACKGROUND: The genes underlying the risk of stroke in the general population remain undetermined. METHODS: We carried out an analysis of genomewide association data generated from four large cohorts composing the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, including 19,602 white persons (mean [+/-SD] age, 63+/-8 years) in whom 1544 incident strokes (1164 ischemic strokes) developed over an average follow-up of 11 years. We tested the markers most strongly associated with stroke in a replication cohort of 2430 black persons with 215 incident strokes (191 ischemic strokes), another cohort of 574 black persons with 85 incident strokes (68 ischemic strokes), and 652 Dutch persons with ischemic stroke and 3613 unaffected persons. RESULTS: Two intergenic single-nucleotide polymorphisms on chromosome 12p13 and within 11 kb of the gene NINJ2 were associated with stroke (P<5x10(-8)). NINJ2 encodes an adhesion molecule expressed in glia and shows increased expression after nerve injury. Direct genotyping showed that rs12425791 was associated with an increased risk of total (i.e., all types) and ischemic stroke, with hazard ratios of 1.30 (95% confidence interval [CI], 1.19 to 1.42) and 1.33 (95% CI, 1.21 to 1.47), respectively, yielding population attributable risks of 11% and 12% in the discovery cohorts. Corresponding hazard ratios were 1.35 (95% CI, 1.01 to 1.79; P=0.04) and 1.42 (95% CI, 1.06 to 1.91; P=0.02) in the large cohort of black persons and 1.17 (95% CI, 1.01 to 1.37; P=0.03) and 1.19 (95% CI, 1.01 to 1.41; P=0.04) in the Dutch sample; the results of an underpowered analysis of the smaller black cohort were nonsignificant. CONCLUSIONS: A genetic locus on chromosome 12p13 is associated with an increased risk of stroke.
Keywords: African Continental Ancestry Group; Aged; Chromosomes, Human, Pair 12; Cohort Studies; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors; Stroke

Genome-wide association study of blood pressure and hypertension. - Levy, Daniel; Ehret, Georg B; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Dehghan, Abbas; Glazer, Nicole L; Morrison, Alanna C; Johnson, Andrew D; Aspelund, Thor; Aulchenko, Yurii; Lumley, Thomas; et al. (Nat Genet, 2009)
Blood pressure is a major cardiovascular disease risk factor. To date, few variants associated with interindividual blood pressure variation have been identified and replicated. Here we report results of a genome-wide association study of systolic (SBP) and diastolic (DBP) blood pressure and hypertension in the CHARGE Consortium (n = 29,136), identifying 13 SNPs for SBP, 20 for DBP and 10 for hypertension at P < 4 × 10(-7). The top ten loci for SBP and DBP were incorporated into a risk score; mean BP and prevalence of hypertension increased in relation to the number of risk alleles carried. When ten CHARGE SNPs for each trait were included in a joint meta-analysis with the Global BPgen Consortium (n = 34,433), four CHARGE loci attained genome-wide significance (P < 5 × 10(-8)) for SBP (ATP2B1, CYP17A1, PLEKHA7, SH2B3), six for DBP (ATP2B1, CACNB2, CSK-ULK3, SH2B3, TBX3-TBX5, ULK4) and one for hypertension (ATP2B1). Identifying genes associated with blood pressure advances our understanding of blood pressure regulation and highlights potential drug targets for the prevention or treatment of hypertension.
Keywords: Blood Pressure; Cell Line; Chromosome Mapping; Chromosomes, Human; Diastole; Gene Expression Regulation; Genetic Association Studies; Genome-Wide Association Study; Humans; Hypertension; Liver; Lymphocytes; Meta-Analysis as Topic; Odds Ratio; Phenotype; Prevalence; Risk Assessment; Systole

Insulin-like growth factors and leukocyte telomere length: the cardiovascular health study. - Kaplan, Robert C; Fitzpatrick, Annette L; Pollak, Michael N; Gardner, Jeffrey P; Jenny, Nancy S; McGinn, Aileen P; Kuller, Lewis H; Strickler, Howard D; Kimura, Masayuki; Psaty, Bruce M; Aviv, Abraham (J Gerontol A Biol Sci Med Sci, 2009)
The insulin-like growth factor (IGF) axis may affect immune cell replicative potential and telomere dynamics. Among 551 adults 65 years and older, leukocyte telomere length (LTL), insulin-like growth factor-1 (IGF-1), and insulin-like growth factor-binding proteins 1 and 3 (IGFBP-1, IGFBP-3) were measured. Multivariate linear regression was used to model the association of LTL with IGF-1 and IGFBPs, while controlling for confounding and increasing precision by adjusting for covariates. We observed a significant association between higher IGF-1 and longer LTL after adjustment for age, sex, race, smoking status, body mass index, hypertension, diabetes, and serum lipids. The results suggested an increase of .08 kb in LTL for each standard deviation increase of IGF-1 (p = .04). IGFBP-1 and IGFBP-3 were not significantly associated with LTL. High IGF-1 may be an independent predictor of longer LTL, consistent with prior evidence suggesting a role for IGF-1 in mechanisms relating to telomere maintenance.
Keywords: Aged; Aging; Cross-Sectional Studies; Female; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor Binding Proteins; Insulin-Like Growth Factor I; Leukocytes; Linear Models; Male; Sex Characteristics; Telomere

Lipoprotein-associated phospholipase A(2) and risk of congestive heart failure in older adults: the Cardiovascular Health Study. - Suzuki, Takeki; Solomon, Cam; Jenny, Nancy Swords; Tracy, Russell; Nelson, Jeanenne J; Psaty, Bruce M; Furberg, Curt; Cushman, Mary (Circ Heart Fail, 2009)
BACKGROUND: Inflammation may be a causative factor in congestive heart failure (CHF). Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) is an inflammation marker associated with vascular risk. One previous study showed an association of Lp-PLA(2) activity with CHF risk, but there were only 94 CHF cases and Lp-PLA(2) antigen, which is available clinically in the United States, was not measured. METHODS AND RESULTS: We measured baseline Lp-PLA(2) antigen and activity in 3991 men and women without baseline CHF or cardiovascular disease who were participating in the Cardiovascular Health Study, a prospective observational study of adults 65 years or older. Cox proportional hazards models adjusted for age, sex, clinic site, race, low-density and high-density lipoprotein cholesterol, body mass index, systolic and diastolic blood pressure, hypertension, smoking status, pack-years, and diabetes were used to calculate hazard ratios and 95% CIs for incident CHF. Further models adjusted for coronary disease events during follow-up and C-reactive protein. Eight hundred twenty-nine participants developed CHF during 12.1 years. Adjusted hazard ratios for CHF with Lp-PLA(2) in the fourth compared with the first quartile were 1.44 (95% CI, 1.16 to 1.79) for Lp-PLA(2) antigen and 1.06 (95% CI, 0.84 to 1.32) for activity. Adjustment for incident coronary disease attenuated the hazard ratio for Lp-PLA(2) antigen to 1.26 (95% CI, 1.02 to 1.57), adjustment for C-reactive protein had minimal impact. CONCLUSIONS: Lp-PLA(2) antigen was associated with risk of future CHF in older people, independent of CHF and coronary risk factors, and partly mediated by coronary disease events. Further clinical and basic research is needed to better understand the role of Lp-PLA(2) in CHF.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Biomarkers; C-Reactive Protein; Female; Fibrinogen; Heart Failure; Humans; Incidence; Inflammation Mediators; Interleukin-6; Kaplan-Meier Estimate; Male; Population Surveillance; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Multiple loci influence erythrocyte phenotypes in the CHARGE Consortium. - Ganesh, Santhi K; Zakai, Neil A; van Rooij, Frank J A; Soranzo, Nicole; Smith, Albert V; Nalls, Michael A; Chen, Ming-Huei; Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Kuhnel, Brigitte; Aspelund, Thor; et al. (Nat Genet, 2009)
Measurements of erythrocytes within the blood are important clinical traits and can indicate various hematological disorders. We report here genome-wide association studies (GWAS) for six erythrocyte traits, including hemoglobin concentration (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red blood cell count (RBC). We performed an initial GWAS in cohorts of the CHARGE Consortium totaling 24,167 individuals of European ancestry and replication in additional independent cohorts of the HaemGen Consortium totaling 9,456 individuals. We identified 23 loci significantly associated with these traits in a meta-analysis of the discovery and replication cohorts (combined P values ranging from 5 x 10(-8) to 7 x 10(-86)). Our findings include loci previously associated with these traits (HBS1L-MYB, HFE, TMPRSS6, TFR2, SPTA1) as well as new associations (EPO, TFRC, SH2B3 and 15 other loci). This study has identified new determinants of erythrocyte traits, offering insight into common variants underlying variation in erythrocyte measures.
Keywords: Blood Pressure; Cell Line; Cohort Studies; Endothelial Cells; Erythrocytes; Gene Expression; Genome, Human; Genome-Wide Association Study; Humans; Hypertension; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

NRXN3 is a novel locus for waist circumference: a genome-wide association study from the CHARGE Consortium. - Heard-Costa, Nancy L; Zillikens, M Carola; Monda, Keri L; Johansson, Asa; Harris, Tamara B; Fu, Mao; Haritunians, Talin; Feitosa, Mary F; Aspelund, Thor; Eiriksdottir, Gudny; Garcia, Melissa; Launer, Lenore J; et al. (PLoS Genet, 2009)
Central abdominal fat is a strong risk factor for diabetes and cardiovascular disease. To identify common variants influencing central abdominal fat, we conducted a two-stage genome-wide association analysis for waist circumference (WC). In total, three loci reached genome-wide significance. In stage 1, 31,373 individuals of Caucasian descent from eight cohort studies confirmed the role of FTO and MC4R and identified one novel locus associated with WC in the neurexin 3 gene [NRXN3 (rs10146997, p = 6.4x10(-7))]. The association with NRXN3 was confirmed in stage 2 by combining stage 1 results with those from 38,641 participants in the GIANT consortium (p = 0.009 in GIANT only, p = 5.3x10(-8) for combined analysis, n = 70,014). Mean WC increase per copy of the G allele was 0.0498 z-score units (0.65 cm). This SNP was also associated with body mass index (BMI) [p = 7.4x10(-6), 0.024 z-score units (0.10 kg/m(2)) per copy of the G allele] and the risk of obesity (odds ratio 1.13, 95% CI 1.07-1.19; p = 3.2x10(-5) per copy of the G allele). The NRXN3 gene has been previously implicated in addiction and reward behavior, lending further evidence that common forms of obesity may be a central nervous system-mediated disorder. Our findings establish that common variants in NRXN3 are associated with WC, BMI, and obesity.
Keywords: Aged; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Obesity; Polymorphism, Single Nucleotide; Waist Circumference

Total and cause-specific mortality in the cardiovascular health study. - Newman, Anne B; Sachs, Michael C; Arnold, Alice M; Fried, Linda P; Kronmal, Richard; Cushman, Mary; Psaty, Bruce M; Harris, Tamara B; Robbins, John A; Burke, Gregory L; Kuller, Lewis H; Lumley, Thomas (J Gerontol A Biol Sci Med Sci, 2009)
BACKGROUND: Few cohort studies have adequate numbers of carefully reviewed deaths to allow an analysis of unique and shared risk factors for cause-specific mortality. Shared risk factors could be targeted for prevention of premature death and the study of longevity. METHODS: A total of 5,888 community-dwelling persons aged 65 years or older living in four communities in the United States participated in the Cardiovascular Health Study cohort. Participants were initially recruited from 1989 to 1990; an additional 687 black participants were recruited in 1992-1993. The average length of follow-up was 16 years. Total and cause-specific mortality, including cardiovascular disease, stroke, cancer, dementia, pulmonary disease, infection, and other cause, were examined as outcomes. Variables previously associated with total mortality were examined for each cause of death using Cox proportional hazard models. RESULTS: Multiple risk factors were related to total mortality. When examining specific causes, many factors were related to cardiovascular death, whereas fewer were related to other causes. For most causes, risk factors were specific for that cause. For example, apolipoprotein E epsilon4 was strongly associated for dementia death and forced vital capacity with pulmonary death. Age, male sex, markers of inflammation, and cognitive function were related to multiple causes of death. CONCLUSIONS: In these older adults, associations of risk factors with a given cause of death were related to specific deficits in that same organ system. Inflammation may represent a common pathway to all causes of death.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cause of Death; Chronic Disease; Cohort Studies; Female; Geriatric Assessment; Health Surveys; Humans; Kaplan-Meier Estimate; Male; Probability; Proportional Hazards Models; Retrospective Studies; Risk Assessment; Severity of Illness Index; Sex Factors; Survival Analysis; United States

Usefulness of myeloperoxidase levels in healthy elderly subjects to predict risk of developing heart failure. - Tang, W H Wilson; Katz, Ronit; Brennan, Marie-Luise; Aviles, Ronnier J; Tracy, Russell P; Psaty, Bruce M; Hazen, Stanley L (Am J Cardiol, 2009)
Increased systemic myeloperoxidase (MPO) has been associated with both the presence and severity of heart failure (HF). This study tested the hypothesis that increased systemic MPO in apparently healthy elderly subjects may predict increased risk of developing HF. Systemic MPO was measured in all available samples from the 1992 to 1993 visit of the Cardiovascular Health Study (CHS). After excluding subjects without available blood samples or with a history of prevalent HF, myocardial infarction (MI), or stroke, 3,733 subjects were included. A total of 569 subjects developed incident HF during 7.2 +/- 2.3 years of follow-up. Patients in the highest MPO quartile (>432 pmol/L) showed higher risk of developing incident HF after adjusting for MI, age, gender, systolic blood pressure, smoking, low-density lipoprotein cholesterol, diabetes mellitus, and any subclinical cardiovascular disease (hazard ratio 1.34, 95% confidence interval 1.06 to 1.72, p = 0.013). However, the relation was more apparent after censoring subjects with incident MI before incident HF, even when adjusted for C-reactive protein and cystatin C (hazard ratio 1.46, 95% confidence interval 1.08 to 1.97, p = 0.02). Interestingly, stratified analyses showed that the relation between increased MPO and HF risk was stronger in subjects without traditional cardiovascular risk factors (<or=75 years old, systolic blood pressure <or=136 mm Hg, no subclinical cardiovascular disease, and no diabetes mellitus). In conclusion, an independent association between increased MPO and the development of HF in apparently healthy elderly subjects was observed, particularly beyond MI and traditional cardiac risk factors.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; Disease Progression; Female; Geriatric Assessment; Heart Failure; Humans; Longitudinal Studies; Male; Peroxidase; Predictive Value of Tests; Probability; Prognosis; Risk Assessment; Sensitivity and Specificity; Severity of Illness Index; Sex Factors

Variants in ZFHX3 are associated with atrial fibrillation in individuals of European ancestry. - Benjamin, Emelia J; Rice, Kenneth M; Arking, Dan E; Pfeufer, Arne; van Noord, Charlotte; Smith, Albert V; Schnabel, Renate B; Bis, Joshua C; Boerwinkle, Eric; Sinner, Moritz F; Dehghan, Abbas; Lubitz, Steven A; et al. (Nat Genet, 2009)
We conducted meta-analyses of genome-wide association studies for atrial fibrillation (AF) in participants from five community-based cohorts. Meta-analyses of 896 prevalent (15,768 referents) and 2,517 incident (21,337 referents) AF cases identified a new locus for AF (ZFHX3, rs2106261, risk ratio RR = 1.19; P = 2.3 x 10(-7)). We replicated this association in an independent cohort from the German AF Network (odds ratio = 1.44; P = 1.6 x 10(-11); combined RR = 1.25; combined P = 1.8 x 10(-15)).
Keywords: Atrial Fibrillation; Chromosomes, Human, Pair 16; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeodomain Proteins; Humans; Meta-Analysis as Topic; Mutation; Polymorphism, Single Nucleotide; Reproducibility of Results

Association of genome-wide variation with the risk of incident heart failure in adults of European and African ancestry: a prospective meta-analysis from the cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Smith, Nicholas L; Felix, Janine F; Morrison, Alanna C; Demissie, Serkalem; Glazer, Nicole L; Loehr, Laura R; Cupples, L Adrienne; Dehghan, Abbas; Lumley, Thomas; Rosamond, Wayne D; Lieb, Wolfgang; Rivadeneira, Fernando; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Although genetic factors contribute to the onset of heart failure (HF), no large-scale genome-wide investigation of HF risk has been published to date. We have investigated the association of 2,478,304 single-nucleotide polymorphisms with incident HF by meta-analyzing data from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Eligible participants for these analyses were of European or African ancestry and free of clinical HF at baseline. Each study independently conducted genome-wide scans and imputed data to the approximately 2.5 million single-nucleotide polymorphisms in HapMap. Within each study, Cox proportional hazards regression models provided age- and sex-adjusted estimates of the association between each variant and time to incident HF. Fixed-effect meta-analyses combined results for each single-nucleotide polymorphism from the 4 cohorts to produce an overall association estimate and P value. A genome-wide significance P value threshold was set a priori at 5.0x10(-7). During a mean follow-up of 11.5 years, 2526 incident HF events (12%) occurred in 20 926 European-ancestry participants. The meta-analysis identified a genome-wide significant locus at chromosomal position 15q22 (1.4x10(-8)), which was 58.8 kb from USP3. Among 2895 African-ancestry participants, 466 incident HF events (16%) occurred during a mean follow-up of 13.7 years. One genome-wide significant locus was identified at 12q14 (6.7x10(-8)), which was 6.3 kb from LRIG3. CONCLUSIONS: We identified 2 loci that were associated with incident HF and exceeded genome-wide significance. The findings merit replication in other community-based settings of incident HF.
Keywords: African Americans; Aged; Aged, 80 and over; Cohort Studies; Endopeptidases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Heart Failure; Humans; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk; Ubiquitin-Specific Proteases

Biological, clinical and population relevance of 95 loci for blood lipids. - Teslovich, Tanya M; Musunuru, Kiran; Smith, Albert V; Edmondson, Andrew C; Stylianou, Ioannis M; Koseki, Masahiro; Pirruccello, James P; Ripatti, Samuli; Chasman, Daniel I; Willer, Cristen J; Johansen, Christopher T; Fouchier, Sigrid W; et al. (Nature, 2010)
Plasma concentrations of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with plasma lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 x 10(-8)), with 59 showing genome-wide significant association with lipid traits for the first time. The newly reported associations include single nucleotide polymorphisms (SNPs) near known lipid regulators (for example, CYP7A1, NPC1L1 and SCARB1) as well as in scores of loci not previously implicated in lipoprotein metabolism. The 95 loci contribute not only to normal variation in lipid traits but also to extreme lipid phenotypes and have an impact on lipid traits in three non-European populations (East Asians, South Asians and African Americans). Our results identify several novel loci associated with plasma lipids that are also associated with CAD. Finally, we validated three of the novel genes-GALNT2, PPP1R3B and TTC39B-with experiments in mouse models. Taken together, our findings provide the foundation to develop a broader biological understanding of lipoprotein metabolism and to identify new therapeutic opportunities for the prevention of CAD.
Keywords: African Americans; Animals; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Europe; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Lipid Metabolism; Lipids; Liver; Male; Mice; N-Acetylgalactosaminyltransferases; Phenotype; Polymorphism, Single Nucleotide; Protein Phosphatase 1; Reproducibility of Results; Triglycerides

Candidate gene association resource (CARe): design, methods, and proof of concept. - Musunuru, Kiran; Lettre, Guillaume; Young, Taylor; Farlow, Deborah N; Pirruccello, James P; Ejebe, Kenechi G; Keating, Brendan J; Yang, Qiong; Chen, Ming-Huei; Lapchyk, Nina; Crenshaw, Andrew; Ziaugra, Liuda; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: The National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe), a planned cross-cohort analysis of genetic variation in cardiovascular, pulmonary, hematologic, and sleep-related traits, comprises >40,000 participants representing 4 ethnic groups in 9 community-based cohorts. The goals of CARe include the discovery of new variants associated with traits using a candidate gene approach and the discovery of new variants using the genome-wide association mapping approach specifically in African Americans. METHODS AND RESULTS: CARe has assembled DNA samples for >40,000 individuals self-identified as European American, African American, Hispanic, or Chinese American, with accompanying data on hundreds of phenotypes that have been standardized and deposited in the CARe Phenotype Database. All participants were genotyped for 7 single-nucleotide polymorphisms (SNPs) selected based on prior association evidence. We performed association analyses relating each of these SNPs to lipid traits, stratified by sex and ethnicity, and adjusted for age and age squared. In at least 2 of the ethnic groups, SNPs near CETP, LIPC, and LPL strongly replicated for association with high-density lipoprotein cholesterol concentrations, PCSK9 with low-density lipoprotein cholesterol levels, and LPL and APOA5 with serum triglycerides. Notably, some SNPs showed varying effect sizes and significance of association in different ethnic groups. CONCLUSIONS: The CARe Pilot Study validates the operational framework for phenotype collection, SNP genotyping, and analytic pipeline of the CARe project and validates the planned candidate gene study of approximately 2000 biological candidate loci in all participants and genome-wide association study in approximately 8000 African American participants. CARe will serve as a valuable resource for the scientific community.
Keywords: African Americans; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Databases, Genetic; European Continental Ancestry Group; Genetic Association Studies; Genotype; Humans; Phenotype; Pilot Projects; Polymorphism, Single Nucleotide; Research Design; Triglycerides

Combined association of lipids and blood pressure in relation to incident cardiovascular disease in the elderly: the cardiovascular health study. - Wong, Nathan D; Lopez, Victor A; Roberts, Craig S; Solomon, Henry A; Burke, Gregory L; Kuller, Lewis; Tracy, Russell; Yanez, David; Psaty, Bruce M (Am J Hypertens, 2010)
BACKGROUND: Hypertension and dyslipidemia are highly prevalent in the elderly. We studied the combined impact of both conditions on cardiovascular disease (CVD) events. METHODS: We studied 4,311 participants aged 65-98 (61.2% female) from the Cardiovascular Health Study (CHS), a longitudinal epidemiologic study, with no prior CVD. We evaluated the relation of low-density lipoprotein (LDL), high-density lipoprotein (HDL), or non-HDL-cholesterol combined with blood pressure (BP) categories to incident CVD-including coronary heart disease (CHD) (angina, myocardial infarction (MI), angioplasty, coronary bypass surgery, or CHD death), stroke, claudication, and CVD death over 15 years. RESULTS: CVD incidence (per 1,000 person years) ranged from 38.4 when BP <120/80 mm Hg and LDL-C <100 mg/dl to 94.8 when BP >or=160/100 mm Hg and LDL-C >or=160 mg/dl, and from 28.9 when BP <120/80 mm Hg and HDL >60 mg/dl to 87.1 for a BP >or=160/100 and HDL-C <40 mg/dl. Compared with those with BP <120/80 mm Hg with either LDL-C <100 mg/dl or HDL-C >60 mg/dl, hazard ratios (HRs) for CVD events were 2.1 when BP >or=160/100 mm Hg and LDL-C >or=160 mg/dl and 2.1 when BP >or=160/100 and HDL-C <40 mg/dl (all P < 0.01), with similar results for non-HDL-C. Elevated BP was associated with increased risk across all lipid levels. Increased LDL-C added risk mainly when BP <140/90 mm Hg, but lower HDL-C also predicted CVD in those with higher BP. CONCLUSION: Increased BP confers increased risks for CVD in elderly persons across all lipid levels. Although increased LDL-C added risk mainly when BP <140/90 mm Hg, low HDL-C added risk also in those with hypertension. These results document the importance of combined hypertension and dyslipidemia.
Keywords: Age Factors; Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus; Female; Health Surveys; Humans; Likelihood Functions; Lipids; Male; Proportional Hazards Models; Sex Factors; Smoking; Socioeconomic Factors; United States

Common genetic determinants of vitamin D insufficiency: a genome-wide association study. - Wang, Thomas J; Zhang, Feng; Richards, J Brent; Kestenbaum, Bryan; van Meurs, Joyce B; Berry, Diane; Kiel, Douglas P; Streeten, Elizabeth A; Ohlsson, Claes; Koller, Daniel L; Peltonen, Leena; Cooper, Jason D; et al. (Lancet, 2010)
BACKGROUND: Vitamin D is crucial for maintenance of musculoskeletal health, and might also have a role in extraskeletal tissues. Determinants of circulating 25-hydroxyvitamin D concentrations include sun exposure and diet, but high heritability suggests that genetic factors could also play a part. We aimed to identify common genetic variants affecting vitamin D concentrations and risk of insufficiency. METHODS: We undertook a genome-wide association study of 25-hydroxyvitamin D concentrations in 33 996 individuals of European descent from 15 cohorts. Five epidemiological cohorts were designated as discovery cohorts (n=16 125), five as in-silico replication cohorts (n=9367), and five as de-novo replication cohorts (n=8504). 25-hydroxyvitamin D concentrations were measured by radioimmunoassay, chemiluminescent assay, ELISA, or mass spectrometry. Vitamin D insufficiency was defined as concentrations lower than 75 nmol/L or 50 nmol/L. We combined results of genome-wide analyses across cohorts using Z-score-weighted meta-analysis. Genotype scores were constructed for confirmed variants. FINDINGS: Variants at three loci reached genome-wide significance in discovery cohorts for association with 25-hydroxyvitamin D concentrations, and were confirmed in replication cohorts: 4p12 (overall p=1.9x10(-109) for rs2282679, in GC); 11q12 (p=2.1x10(-27) for rs12785878, near DHCR7); and 11p15 (p=3.3x10(-20) for rs10741657, near CYP2R1). Variants at an additional locus (20q13, CYP24A1) were genome-wide significant in the pooled sample (p=6.0x10(-10) for rs6013897). Participants with a genotype score (combining the three confirmed variants) in the highest quartile were at increased risk of having 25-hydroxyvitamin D concentrations lower than 75 nmol/L (OR 2.47, 95% CI 2.20-2.78, p=2.3x10(-48)) or lower than 50 nmol/L (1.92, 1.70-2.16, p=1.0x10(-26)) compared with those in the lowest quartile. INTERPRETATION: Variants near genes involved in cholesterol synthesis, hydroxylation, and vitamin D transport affect vitamin D status. Genetic variation at these loci identifies individuals who have substantially raised risk of vitamin D insufficiency. FUNDING: Full funding sources listed at end of paper (see Acknowledgments).
Keywords: Canada; Chromosomes, Human, Pair 11; Chromosomes, Human, Pair 4; Cohort Studies; Dietary Supplements; Europe; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Immunoassay; International Cooperation; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Seasons; United States; Vitamin D; Vitamin D Deficiency

Common genetic variants associate with serum phosphorus concentration. - Kestenbaum, Bryan; Glazer, Nicole L; Köttgen, Anna; Felix, Janine F; Hwang, Shih-Jen; Liu, Yongmei; Lohman, Kurt; Kritchevsky, Stephen B; Hausman, Dorothy B; Petersen, Ann-Kristin; Gieger, Christian; Ried, Janina S; et al. (J Am Soc Nephrol, 2010)
Phosphorus is an essential mineral that maintains cellular energy and mineralizes the skeleton. Because complex actions of ion transporters and regulatory hormones regulate serum phosphorus concentrations, genetic variation may determine interindividual variation in phosphorus metabolism. Here, we report a comprehensive genome-wide association study of serum phosphorus concentration. We evaluated 16,264 participants of European ancestry from the Cardiovascular Heath Study, Atherosclerosis Risk in Communities Study, Framingham Offspring Study, and the Rotterdam Study. We excluded participants with an estimated GFR <45 ml/min per 1.73 m(2) to focus on phosphorus metabolism under normal conditions. We imputed genotypes to approximately 2.5 million single-nucleotide polymorphisms in the HapMap and combined study-specific findings using meta-analysis. We tested top polymorphisms from discovery cohorts in a 5444-person replication sample. Polymorphisms in seven loci with minor allele frequencies 0.08 to 0.49 associate with serum phosphorus concentration (P = 3.5 x 10(-16) to 3.6 x 10(-7)). Three loci were near genes encoding the kidney-specific type IIa sodium phosphate co-transporter (SLC34A1), the calcium-sensing receptor (CASR), and fibroblast growth factor 23 (FGF23), proteins that contribute to phosphorus metabolism. We also identified genes encoding phosphatases, kinases, and phosphodiesterases that have yet-undetermined roles in phosphorus homeostasis. In the replication sample, five of seven top polymorphisms associate with serum phosphorous concentrations (P < 0.05 for each). In conclusion, common genetic variants associate with serum phosphorus in the general population. Further study of the loci identified in this study may help elucidate mechanisms of phosphorus regulation.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Fibroblast Growth Factors; Gene Frequency; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Male; Middle Aged; Phosphorus; Polymorphism, Single Nucleotide; Receptors, Calcium-Sensing; Sex Factors; Sodium-Phosphate Cotransporter Proteins, Type IIa

Common variants in 22 loci are associated with QRS duration and cardiac ventricular conduction. - Sotoodehnia, Nona; Isaacs, Aaron; de Bakker, Paul I W; Dörr, Marcus; Newton-Cheh, Christopher; Nolte, Ilja M; van der Harst, Pim; Müller, Martina; Eijgelsheim, Mark; Alonso, Alvaro; Hicks, Andrew A; Padmanabhan, Sandosh; et al. (Nat Genet, 2010)
The QRS interval, from the beginning of the Q wave to the end of the S wave on an electrocardiogram, reflects ventricular depolarization and conduction time and is a risk factor for mortality, sudden death and heart failure. We performed a genome-wide association meta-analysis in 40,407 individuals of European descent from 14 studies, with further genotyping in 7,170 additional Europeans, and we identified 22 loci associated with QRS duration (P < 5 × 10(-8)). These loci map in or near genes in pathways with established roles in ventricular conduction such as sodium channels, transcription factors and calcium-handling proteins, but also point to previously unidentified biologic processes, such as kinase inhibitors and genes related to tumorigenesis. We demonstrate that SCN10A, a candidate gene at the most significantly associated locus in this study, is expressed in the mouse ventricular conduction system, and treatment with a selective SCN10A blocker prolongs QRS duration. These findings extend our current knowledge of ventricular depolarization and conduction.
Keywords: Animals; Animals, Newborn; Chromosomes, Human; Computational Biology; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Mice; Mice, Transgenic; Models, Animal; Myocytes, Cardiac; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sodium Channels

Common variants in KCNN3 are associated with lone atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Glazer, Nicole L; Pfeufer, Arne; Alonso, Alvaro; Chung, Mina K; Sinner, Moritz F; de Bakker, Paul I W; Mueller, Martina; Lubitz, Steven A; Fox, Ervin; Darbar, Dawood; et al. (Nat Genet, 2010)
Atrial fibrillation (AF) is the most common sustained arrhythmia. Previous studies have identified several genetic loci associated with typical AF. We sought to identify common genetic variants underlying lone AF. This condition affects a subset of individuals without overt heart disease and with an increased heritability of AF. We report a meta-analysis of genome-wide association studies conducted using 1,335 individuals with lone AF (cases) and 12,844 unaffected individuals (referents). Cases were obtained from the German AF Network, Heart and Vascular Health Study, the Atherosclerosis Risk in Communities Study, the Cleveland Clinic and Massachusetts General Hospital. We identified an association on chromosome 1q21 to lone AF (rs13376333, adjusted odds ratio = 1.56; P = 6.3 x 10(-12)), and we replicated this association in two independent cohorts with lone AF (overall combined odds ratio = 1.52, 95% CI 1.40-1.64; P = 1.83 x 10(-21)). rs13376333 is intronic to KCNN3, which encodes a potassium channel protein involved in atrial repolarization.
Keywords: Adolescent; Adult; Aged; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Introns; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Small-Conductance Calcium-Activated Potassium Channels; Young Adult

Common variants in the calcium-sensing receptor gene are associated with total serum calcium levels. - O'Seaghdha, Conall M; Yang, Qiong; Glazer, Nicole L; Leak, Tennille S; Dehghan, Abbas; Smith, Albert V; Kao, W H Linda; Lohman, Kurt; Hwang, Shih-Jen; Johnson, Andrew D; Hofman, Albert; Uitterlinden, André G; et al. (Hum Mol Genet, 2010)
Serum calcium levels are tightly regulated. We performed genome-wide association studies (GWAS) in population-based studies participating in the CHARGE Consortium to uncover common genetic variations associated with total serum calcium levels. GWAS of serum calcium concentrations was performed in 20 611 individuals of European ancestry for ∼2.5 million genotyped and imputed single-nucleotide polymorphisms (SNPs). The SNP with the lowest P-value was rs17251221 (P = 2.4 * 10(-22), minor allele frequency 14%) in the calcium-sensing receptor gene (CASR). This lead SNP was associated with higher serum calcium levels [0.06 mg/dl (0.015 mmol/l) per copy of the minor G allele] and accounted for 0.54% of the variance in serum calcium concentrations. The identification of variation in CASR that influences serum calcium concentration confirms the results of earlier candidate gene studies. The G allele of rs17251221 was also associated with higher serum magnesium levels (P = 1.2 * 10(-3)), lower serum phosphate levels (P = 2.8 * 10(-7)) and lower bone mineral density at the lumbar spine (P = 0.038), but not the femoral neck. No additional genomic loci contained SNPs associated at genome-wide significance (P < 5 * 10(-8)). These associations resemble clinical characteristics of patients with familial hypocalciuric hypercalcemia, an autosomal-dominant disease arising from rare inactivating mutations in the CASR gene. We conclude that common genetic variation in the CASR gene is associated with similar but milder features in the general population.
Keywords: Adult; Calcium; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Calcium-Sensing

CRP gene variation and risk of community-acquired pneumonia. - Mukamal, Kenneth J; Pai, Jennifer K; O'Meara, Ellen S; Tracy, Russell P; Psaty, Bruce M; Kuller, Lewis H; Newman, Anne B; Yende, Sachin; Curhan, Gary C; Siscovick, David S; Rimm, Eric B (Respirology, 2010)
BACKGROUND AND OBJECTIVE: CRP has several potentially antibacterial effects, and variation in the CRP gene is known to influence CRP levels. Whether this variation influences risk of infection, and hence whether CRP has anti-infective activity in humans, is uncertain. METHODS: We evaluated a series of haplotype-tagging single nucleotide polymorphisms among 5374 individuals in the Cardiovascular Health Study, a cohort of older adults from four communities, who were followed for community-acquired pneumonia for 12-13 years. Secondarily, we evaluated whether these polymorphisms varied among men in the Health Professionals Follow-up Study who self-reported pneumonia on biennial questionnaires. RESULTS: There were 581 (507 white and 74 black) Cardiovascular Health Study participants with incident hospitalizations for pneumonia. No single nucleotide polymorphism or haplotypes were associated with risk among white Cardiovascular Health Study participants. Among black participants, the haplotype tagged by A790T was associated with lower risk of incident pneumonia (hazard ratio 0.5; 95% confidence interval: 0.3-0.9) and with higher CRP levels. In Health Professionals Follow-up Study, a separate haplotype was associated with less frequent self-reported pneumonia but not with circulating CRP levels. CONCLUSIONS: Some genetic variants in CRP may be associated with risk of pneumonia, but haplotypes associated with risk are variably associated with baseline CRP levels. If CRP is a relevant component of innate immunity in humans, the inducibility or tissue-specificity of expression may be at least as important as chronic circulating levels.
Keywords: African Americans; Aged; Aged, 80 and over; Body Mass Index; C-Reactive Protein; Cohort Studies; Community-Acquired Infections; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Pneumonia; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Smoking

Cystatin C and sudden cardiac death risk in the elderly. - Deo, Rajat; Sotoodehnia, Nona; Katz, Ronit; Sarnak, Mark J; Fried, Linda F; Chonchol, Michel; Kestenbaum, Bryan; Psaty, Bruce M; Siscovick, David S; Shlipak, Michael G (Circ Cardiovasc Qual Outcomes, 2010)
BACKGROUND: Recent studies have demonstrated an association between moderate kidney dysfunction and sudden cardiac death in people with cardiovascular disease. METHODS AND RESULTS: The study was a longitudinal analysis among 4465 participants from the Cardiovascular Health Study without prevalent cardiovascular disease at baseline. Cystatin C and creatinine were measured from baseline sera. Sudden cardiac death (SCD) was defined as a sudden pulseless condition from a cardiac origin in a previously stable individual that occurred out of the hospital or in the emergency room. The association between cystatin C tertiles and SCD was determined with multivariate Cox proportional hazards. A similar analysis compared SCD incidence across creatinine-based estimated glomerular filtration rate (eGFR) tertiles. Over a median follow-up of 11.2 years, 91 adjudicated SCD events occurred. The annual incidence of SCD events increased across cystatin C tertiles: 10 events per 10 000 person years in tertile 1, 25 events per 10 000 person years in tertile 2, and 32 events per 10 000 person-years in the highest cystatin C tertile. These associations persisted after multivariate adjustment: hazards ratio=2.72; 95% confidence interval, 1.44 to 5.16 in tertile 2 and hazards ratio=2.67; 95% confidence interval, 1.33 to 5.35 in tertile 3. After multivariate adjustment, the rate of SCD also increased in a linear distribution across creatinine-based eGFR tertiles: 15 events per 10 000 person-years in tertile 1, 22 events per 10 000 person-years in tertile 2, and 27 events per 10 000 person-years in tertile 3. No significant associations, however, remained between creatinine-based eGFR and SCD after multivariable adjustment. CONCLUSIONS: Impaired kidney function, as measured by cystatin C, has an independent association with SCD risk among elderly persons without clinical cardiovascular disease.
Keywords: Age Factors; Aged; Biomarkers; Chi-Square Distribution; Creatinine; Cystatin C; Death, Sudden, Cardiac; Female; Glomerular Filtration Rate; Humans; Incidence; Kidney Diseases; Longitudinal Studies; Male; Proportional Hazards Models; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

Four novel Loci (19q13, 6q24, 12q24, and 5q14) influence the microcirculation in vivo. - Ikram, M Kamran; Sim, Xueling; Xueling, Sim; Jensen, Richard A; Cotch, Mary Frances; Hewitt, Alex W; Ikram, M Arfan; Wang, Jie Jin; Klein, Ronald; Klein, Barbara E K; Breteler, Monique M B; Cheung, Ning; et al. (PLoS Genet, 2010)
There is increasing evidence that the microcirculation plays an important role in the pathogenesis of cardiovascular diseases. Changes in retinal vascular caliber reflect early microvascular disease and predict incident cardiovascular events. We performed a genome-wide association study to identify genetic variants associated with retinal vascular caliber. We analyzed data from four population-based discovery cohorts with 15,358 unrelated Caucasian individuals, who are members of the Cohort for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and replicated findings in four independent Caucasian cohorts (n  =  6,652). All participants had retinal photography and retinal arteriolar and venular caliber measured from computer software. In the discovery cohorts, 179 single nucleotide polymorphisms (SNP) spread across five loci were significantly associated (p<5.0×10(-8)) with retinal venular caliber, but none showed association with arteriolar caliber. Collectively, these five loci explain 1.0%-3.2% of the variation in retinal venular caliber. Four out of these five loci were confirmed in independent replication samples. In the combined analyses, the top SNPs at each locus were: rs2287921 (19q13; p  =  1.61×10(-25), within the RASIP1 locus), rs225717 (6q24; p = 1.25×10(-16), adjacent to the VTA1 and NMBR loci), rs10774625 (12q24; p  =  2.15×10(-13), in the region of ATXN2,SH2B3 and PTPN11 loci), and rs17421627 (5q14; p = 7.32×10(-16), adjacent to the MEF2C locus). In two independent samples, locus 12q24 was also associated with coronary heart disease and hypertension. Our population-based genome-wide association study demonstrates four novel loci associated with retinal venular caliber, an endophenotype of the microcirculation associated with clinical cardiovascular disease. These data provide further insights into the contribution and biological mechanisms of microcirculatory changes that underlie cardiovascular disease.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Child; Child, Preschool; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; Cohort Studies; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Microcirculation; Middle Aged; Polymorphism, Single Nucleotide; Retinal Vessels; Young Adult

Genetic predictors of medically refractory ulcerative colitis. - Haritunians, Talin; Taylor, Kent D; Targan, Stephan R; Dubinsky, Marla; Ippoliti, Andrew; Kwon, Soonil; Guo, Xiuqing; Melmed, Gil Y; Berel, Dror; Mengesha, Emebet; Psaty, Bruce M; Glazer, Nicole L; et al. (Inflamm Bowel Dis, 2010)
BACKGROUND: Acute severe ulcerative colitis (UC) remains a significant clinical challenge and the ability to predict, at an early stage, those individuals at risk of colectomy for medically refractory UC (MR-UC) would be a major clinical advance. The aim of this study was to use a genome-wide association study (GWAS) in a well-characterized cohort of UC patients to identify genetic variation that contributes to MR-UC. METHODS: A GWAS comparing 324 MR-UC patients with 537 non-MR-UC patients was analyzed using logistic regression and Cox proportional hazards methods. In addition, the MR-UC patients were compared with 2601 healthy controls. RESULTS: MR-UC was associated with more extensive disease (P = 2.7 × 10(-6)) and a positive family history of UC (P = 0.004). A risk score based on the combination of 46 single nucleotide polymorphisms (SNPs) associated with MR-UC explained 48% of the variance for colectomy risk in our cohort. Risk scores divided into quarters showed the risk of colectomy to be 0%, 17%, 74%, and 100% in the four groups. Comparison of the MR-UC subjects with healthy controls confirmed the contribution of the major histocompatibility complex to severe UC (peak association: rs17207986, P = 1.4 × 10(-16)) and provided genome-wide suggestive association at the TNFSF15 (TL1A) locus (peak association: rs11554257, P = 1.4 × 10(-6)). CONCLUSIONS: A SNP-based risk scoring system, identified here by GWAS analyses, may provide a useful adjunct to clinical parameters for predicting the natural history of UC. Furthermore, discovery of genetic processes underlying disease severity may help to identify pathways for novel therapeutic intervention in severe UC.
Keywords: Acute Disease; Adolescent; Adult; Cohort Studies; Colectomy; Colitis, Ulcerative; Female; Genetic Loci; Genome-Wide Association Study; Humans; Major Histocompatibility Complex; Male; Polymorphism, Single Nucleotide; Risk Factors; Severity of Illness Index; Tumor Necrosis Factor Ligand Superfamily Member 15; Young Adult

Genome-wide analysis of genetic loci associated with Alzheimer disease. - Seshadri, Sudha; Fitzpatrick, Annette L; Ikram, M Arfan; DeStefano, Anita L; Gudnason, Vilmundur; Boada, Merce; Bis, Joshua C; Smith, Albert V; Carassquillo, Minerva M; Lambert, Jean Charles; Harold, Denise; Schrijvers, Elisabeth M C; et al. (JAMA, 2010)
CONTEXT: Genome-wide association studies (GWAS) have recently identified CLU, PICALM, and CR1 as novel genes for late-onset Alzheimer disease (AD). OBJECTIVES: To identify and strengthen additional loci associated with AD and confirm these in an independent sample and to examine the contribution of recently identified genes to AD risk prediction in a 3-stage analysis of new and previously published GWAS on more than 35,000 persons (8371 AD cases). DESIGN, SETTING, AND PARTICIPANTS: In stage 1, we identified strong genetic associations (P < 10(-3)) in a sample of 3006 AD cases and 14,642 controls by combining new data from the population-based Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (1367 AD cases [973 incident]) with previously reported results from the Translational Genomics Research Institute and the Mayo AD GWAS. We identified 2708 single-nucleotide polymorphisms (SNPs) with P < 10(-3). In stage 2, we pooled results for these SNPs with the European AD Initiative (2032 cases and 5328 controls) to identify 38 SNPs (10 loci) with P < 10(-5). In stage 3, we combined data for these 10 loci with data from the Genetic and Environmental Risk in AD consortium (3333 cases and 6995 controls) to identify 4 SNPs with P < 1.7x10(-8). These 4 SNPs were replicated in an independent Spanish sample (1140 AD cases and 1209 controls). Genome-wide association analyses were completed in 2007-2008 and the meta-analyses and replication in 2009. MAIN OUTCOME MEASURE: Presence of Alzheimer disease. RESULTS: Two loci were identified to have genome-wide significance for the first time: rs744373 near BIN1 (odds ratio [OR],1.13; 95% confidence interval [CI],1.06-1.21 per copy of the minor allele; P = 1.59x10(-11)) and rs597668 near EXOC3L2/BLOC1S3/MARK4 (OR, 1.18; 95% CI, 1.07-1.29; P = 6.45x10(-9)). Associations of these 2 loci plus the previously identified loci CLU and PICALM with AD were confirmed in the Spanish sample (P < .05). However, although CLU and PICALM were confirmed to be associated with AD in this independent sample, they did not improve the ability of a model that included age, sex, and APOE to predict incident AD (improvement in area under the receiver operating characteristic curve from 0.847 to 0.849 in the Rotterdam Study and 0.702 to 0.705 in the Cardiovascular Health Study). CONCLUSIONS: Two genetic loci for AD were found for the first time to reach genome-wide statistical significance. These findings were replicated in an independent population. Two recently reported associations were also confirmed. These loci did not improve AD risk prediction. While not clinically useful, they may implicate biological pathways useful for future research.
Keywords: Age of Onset; Aged; Alzheimer Disease; Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Odds Ratio; Polymorphism, Single Nucleotide

Genome-wide association analysis identifies multiple loci related to resting heart rate. - Eijgelsheim, Mark; Newton-Cheh, Christopher; Sotoodehnia, Nona; de Bakker, Paul I W; Müller, Martina; Morrison, Alanna C; Smith, Albert V; Isaacs, Aaron; Sanna, Serena; Dörr, Marcus; Navarro, Pau; Fuchsberger, Christian; et al. (Hum Mol Genet, 2010)
Higher resting heart rate is associated with increased cardiovascular disease and mortality risk. Though heritable factors play a substantial role in population variation, little is known about specific genetic determinants. This knowledge can impact clinical care by identifying novel factors that influence pathologic heart rate states, modulate heart rate through cardiac structure and function or by improving our understanding of the physiology of heart rate regulation. To identify common genetic variants associated with heart rate, we performed a meta-analysis of 15 genome-wide association studies (GWAS), including 38,991 subjects of European ancestry, estimating the association between age-, sex- and body mass-adjusted RR interval (inverse heart rate) and approximately 2.5 million markers. Results with P < 5 × 10(-8) were considered genome-wide significant. We constructed regression models with multiple markers to assess whether results at less stringent thresholds were likely to be truly associated with RR interval. We identified six novel associations with resting heart rate at six loci: 6q22 near GJA1; 14q12 near MYH7; 12p12 near SOX5, c12orf67, BCAT1, LRMP and CASC1; 6q22 near SLC35F1, PLN and c6orf204; 7q22 near SLC12A9 and UfSp1; and 11q12 near FADS1. Associations at 6q22 400 kb away from GJA1, at 14q12 MYH6 and at 1q32 near CD34 identified in previously published GWAS were confirmed. In aggregate, these variants explain approximately 0.7% of RR interval variance. A multivariant regression model including 20 variants with P < 10(-5) increased the explained variance to 1.6%, suggesting that some loci falling short of genome-wide significance are likely truly associated. Future research is warranted to elucidate underlying mechanisms that may impact clinical care.
Keywords: Adult; Aged; Base Pairing; Cohort Studies; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Heart Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Rest

Genome-wide association identifies OBFC1 as a locus involved in human leukocyte telomere biology. - Levy, Daniel; Neuhausen, Susan L; Hunt, Steven C; Kimura, Masayuki; Hwang, Shih-Jen; Chen, Wei; Bis, Joshua C; Fitzpatrick, Annette L; Smith, Erin; Johnson, Andrew D; Gardner, Jeffrey P; Srinivasan, Sathanur R; et al. (Proc Natl Acad Sci U S A, 2010)
Telomeres are engaged in a host of cellular functions, and their length is regulated by multiple genes. Telomere shortening, in the course of somatic cell replication, ultimately leads to replicative senescence. In humans, rare mutations in genes that regulate telomere length have been identified in monogenic diseases such as dyskeratosis congenita and idiopathic pulmonary fibrosis, which are associated with shortened leukocyte telomere length (LTL) and increased risk for aplastic anemia. Shortened LTL is observed in a host of aging-related complex genetic diseases and is associated with diminished survival in the elderly. We report results of a genome-wide association study of LTL in a consortium of four observational studies (n = 3,417 participants with LTL and genome-wide genotyping). SNPs in the regions of the oligonucleotide/oligosaccharide-binding folds containing one gene (OBFC1; rs4387287; P = 3.9 x 10(-9)) and chemokine (C-X-C motif) receptor 4 gene (CXCR4; rs4452212; P = 2.9 x 10(-8)) were associated with LTL at a genome-wide significance level (P < 5 x 10(-8)). We attempted replication of the top SNPs at these loci through de novo genotyping of 1,893 additional individuals and in silico lookup in another observational study (n = 2,876), and we confirmed the association findings for OBFC1 but not CXCR4. In addition, we confirmed the telomerase RNA component (TERC) as a gene associated with LTL (P = 1.1 x 10(-5)). The identification of OBFC1 through genome-wide association as a locus for interindividual variation in LTL in the general population advances the understanding of telomere biology in humans and may provide insights into aging-related disorders linked to altered LTL dynamics.
Keywords: Cohort Studies; Genome-Wide Association Study; Genotype; Humans; Leukocytes; Polymorphism, Single Nucleotide; Receptors, CXCR4; Telomere; Telomere-Binding Proteins

Genome-wide association studies of MRI-defined brain infarcts: meta-analysis from the CHARGE Consortium. - Debette, Stephanie; Bis, Joshua C; Fornage, Myriam; Schmidt, Helena; Ikram, M Arfan; Sigurdsson, Sigurdur; Heiss, Gerardo; Struchalin, Maksim; Smith, Albert V; van der Lugt, Aad; DeCarli, Charles; Lumley, Thomas; et al. (Stroke, 2010)
BACKGROUND AND PURPOSE: Previous studies examining genetic associations with MRI-defined brain infarct have yielded inconsistent findings. We investigated genetic variation underlying covert MRI infarct in persons without histories of transient ischemic attack or stroke. We performed meta-analysis of genome-wide association studies of white participants in 6 studies comprising the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Using 2.2 million genotyped and imputed single nucleotide polymorphisms, each study performed cross-sectional genome-wide association analysis of MRI infarct using age- and sex-adjusted logistic regression models. Study-specific findings were combined in an inverse-variance-weighted meta-analysis, including 9401 participants with mean age 69.7 (19.4% of whom had >or=1 MRI infarct). RESULTS: The most significant association was found with rs2208454 (minor allele frequency, 20%), located in intron 3 of MACRO domain containing 2 gene and in the downstream region of fibronectin leucine-rich transmembrane protein 3 gene. Each copy of the minor allele was associated with lower risk of MRI infarcts (odds ratio, 0.76; 95% confidence interval, 0.68-0.84; P=4.64x10(-7)). Highly suggestive associations (P<1.0x10(-5)) were also found for 22 other single nucleotide polymorphisms in linkage disequilibrium (r(2)>0.64) with rs2208454. The association with rs2208454 did not replicate in independent samples of 1822 white and 644 black participants, although 4 single nucleotide polymorphisms within 200 kb from rs2208454 were associated with MRI infarcts in the black population sample. CONCLUSIONS: This first community-based, genome-wide association study on covert MRI infarcts uncovered novel associations. Although replication of the association with top single nucleotide polymorphisms failed, possibly because of insufficient power, results in the black population sample are encouraging, and further efforts at replication are needed.
Keywords: African Americans; Aged; Brain; Brain Infarction; Cohort Studies; DNA Mutational Analysis; Female; Gene Frequency; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Magnetic Resonance Imaging; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Genome-wide association studies of serum magnesium, potassium, and sodium concentrations identify six Loci influencing serum magnesium levels. - Meyer, Tamra E; Verwoert, Germaine C; Hwang, Shih-Jen; Glazer, Nicole L; Smith, Albert V; van Rooij, Frank J A; Ehret, Georg B; Boerwinkle, Eric; Felix, Janine F; Leak, Tennille S; Harris, Tamara B; Yang, Qiong; et al. (PLoS Genet, 2010)
Magnesium, potassium, and sodium, cations commonly measured in serum, are involved in many physiological processes including energy metabolism, nerve and muscle function, signal transduction, and fluid and blood pressure regulation. To evaluate the contribution of common genetic variation to normal physiologic variation in serum concentrations of these cations, we conducted genome-wide association studies of serum magnesium, potassium, and sodium concentrations using approximately 2.5 million genotyped and imputed common single nucleotide polymorphisms (SNPs) in 15,366 participants of European descent from the international CHARGE Consortium. Study-specific results were combined using fixed-effects inverse-variance weighted meta-analysis. SNPs demonstrating genome-wide significant (p<5 x 10(-8)) or suggestive associations (p<4 x 10(-7)) were evaluated for replication in an additional 8,463 subjects of European descent. The association of common variants at six genomic regions (in or near MUC1, ATP2B1, DCDC5, TRPM6, SHROOM3, and MDS1) with serum magnesium levels was genome-wide significant when meta-analyzed with the replication dataset. All initially significant SNPs from the CHARGE Consortium showed nominal association with clinically defined hypomagnesemia, two showed association with kidney function, two with bone mineral density, and one of these also associated with fasting glucose levels. Common variants in CNNM2, a magnesium transporter studied only in model systems to date, as well as in CNNM3 and CNNM4, were also associated with magnesium concentrations in this study. We observed no associations with serum sodium or potassium levels exceeding p<4 x 10(-7). Follow-up studies of newly implicated genomic loci may provide additional insights into the regulation and homeostasis of human serum magnesium levels.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Magnesium; Male; Middle Aged; Polymorphism, Single Nucleotide; Potassium; Sodium

Genome-wide association study identifies GPC5 as a novel genetic locus protective against sudden cardiac arrest. - Arking, Dan E; Reinier, Kyndaron; Post, Wendy; Jui, Jonathan; Hilton, Gina; O'Connor, Ashley; Prineas, Ronald J; Boerwinkle, Eric; Psaty, Bruce M; Tomaselli, Gordon F; Rea, Thomas; Sotoodehnia, Nona; et al. (PLoS One, 2010)
BACKGROUND: Existing studies indicate a significant genetic component for sudden cardiac arrest (SCA) and genome-wide association studies (GWAS) provide an unbiased approach for identification of novel genes. We performed a GWAS to identify genetic determinants of SCA. METHODOLOGY/PRINCIPAL FINDINGS: We used a case-control design within the ongoing Oregon Sudden Unexpected Death Study (Oregon-SUDS). Cases (n = 424) were SCAs with coronary artery disease (CAD) among residents of Portland, OR (2002-07, population approximately 1,000,000) and controls (n = 226) were residents with CAD, but no history of SCA. All subjects were of White-European ancestry and GWAS was performed using Affymetrix 500K/5.0 and 6.0 arrays. High signal markers were genotyped in SCA cases (n = 521) identified from the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS) (combined n = 19,611). No SNPs reached genome-wide significance (p<5x10(-8)). SNPs at 6 loci were prioritized for follow-up primarily based on significance of p<10(-4) and proximity to a known gene (CSMD2, GPR37L1, LIN9, B4GALNT3, GPC5, and ZNF592). The minor allele of GPC5 (GLYPICAN 5, rs3864180) was associated with a lower risk of SCA in Oregon-SUDS, an effect that was also observed in ARIC/CHS whites (p<0.05) and blacks (p<0.04). In a combined Cox proportional hazards model analysis that adjusted for race, the minor allele exhibited a hazard ratio of 0.85 (95% CI 0.74 to 0.98; p<0.01). CONCLUSIONS/SIGNIFICANCE: A novel genetic locus for SCA, GPC5, was identified from Oregon-SUDS and successfully validated in the ARIC and CHS cohorts. Three other members of the Glypican family have been previously implicated in human disease, including cardiac conditions. The mechanism of this specific association requires further study.
Keywords: Aged; Alleles; Case-Control Studies; Cohort Studies; Death, Sudden, Cardiac; Ethnic Groups; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glypicans; Heart Diseases; Humans; Male; Middle Aged; Models, Genetic; Oligonucleotide Array Sequence Analysis; Oregon; Polymorphism, Single Nucleotide

Genome-wide association study of PR interval. - Pfeufer, Arne; van Noord, Charlotte; Marciante, Kristin D; Arking, Dan E; Larson, Martin G; Smith, Albert Vernon; Tarasov, Kirill V; Müller, Martina; Sotoodehnia, Nona; Sinner, Moritz F; Verwoert, Germaine C; Li, Man; et al. (Nat Genet, 2010)
The electrocardiographic PR interval (or PQ interval) reflects atrial and atrioventricular nodal conduction, disturbances of which increase risk of atrial fibrillation. We report a meta-analysis of genome-wide association studies for PR interval from seven population-based European studies in the CHARGE Consortium: AGES, ARIC, CHS, FHS, KORA, Rotterdam Study, and SardiNIA (N = 28,517). We identified nine loci associated with PR interval at P < 5 x 10(-8). At the 3p22.2 locus, we observed two independent associations in voltage-gated sodium channel genes, SCN10A and SCN5A. Six of the loci were near cardiac developmental genes, including CAV1-CAV2, NKX2-5 (CSX1), SOX5, WNT11, MEIS1, and TBX5-TBX3, providing pathophysiologically interesting candidate genes. Five of the loci, SCN5A, SCN10A, NKX2-5, CAV1-CAV2, and SOX5, were also associated with atrial fibrillation (N = 5,741 cases, P < 0.0056). This suggests a role for common variation in ion channel and developmental genes in atrial and atrioventricular conduction as well as in susceptibility to atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Meta-Analysis as Topic

Genomic variation associated with mortality among adults of European and African ancestry with heart failure: the cohorts for heart and aging research in genomic epidemiology consortium. - Morrison, Alanna C; Felix, Janine F; Cupples, L Adrienne; Glazer, Nicole L; Loehr, Laura R; Dehghan, Abbas; Demissie, Serkalem; Bis, Joshua C; Rosamond, Wayne D; Aulchenko, Yurii S; Wang, Ying A; Haritunians, Talin; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Prognosis and survival are significant concerns for individuals with heart failure (HF). To better understand the pathophysiology of HF prognosis, the association between 2,366,858 single-nucleotide polymorphisms (SNPs) and all-cause mortality was evaluated among individuals with incident HF from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Participants were 2526 individuals of European ancestry and 466 individuals of African ancestry who experienced an incident HF event during follow-up in the respective cohorts. Within each study, the association between genetic variants and time to mortality among individuals with HF was assessed by Cox proportional hazards models that included adjustment for sex and age at the time of the HF event. Prospective fixed-effect meta-analyses were conducted for the 4 study populations of European ancestry (N=1645 deaths) and for the 2 populations of African ancestry (N=281 deaths). Genome-wide significance was set at P=5.0x10(-7). Meta-analytic findings among individuals of European ancestry revealed 1 genome-wide significant locus on chromosome 3p22 in an intron of CKLF-like MARVEL transmembrane domain containing 7 (CMTM7, P=3.2x10(-7)). Eight additional loci in individuals of European ancestry and 4 loci in individuals of African ancestry were identified by high-signal SNPs (P<1.0x10(-5)) but did not meet genome-wide significance. CONCLUSIONS: This study identified a novel locus associated with all-cause mortality among individuals of European ancestry with HF. This finding warrants additional investigation, including replication, in other studies of HF.
Keywords: African Americans; Aged; Aged, 80 and over; Chemokines; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Failure; Humans; Introns; Male; MARVEL Domain-Containing Proteins; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Impaired kidney function and atrial fibrillation in elderly subjects. - Deo, Rajat; Katz, Ronit; Kestenbaum, Bryan; Fried, Linda; Sarnak, Mark J; Psaty, Bruce M; Siscovick, David S; Shlipak, Michael G (J Card Fail, 2010)
BACKGROUND: Impaired kidney function is associated with increased risk for cardiovascular events. We evaluated whether kidney function is associated with atrial fibrillation (AF) risk in elderly persons. METHODS AND RESULTS: Subjects were participants in the Cardiovascular Health Study (CHS), a population-based cohort of ambulatory elderly. Measures of kidney function were cystatin C and creatinine-based estimated glomerular filtration rate (eGFR). Among the 4663 participants, 342 (7%) had AF at baseline and 579 (13%) developed incident AF during follow-up (mean 7.4 years). In unadjusted analyses, cystatin C quartiles were strongly associated with prevalent AF with a nearly 3-fold odds in the highest quartile compared with the lowest (HR=1.19, 95% CI [0.80-1.76] in quartile 2; HR=2.00, 95% CI [1.38-2.88] in quartile 3; and HR=2.87, 95% CI [2.03-4.07] in quartile 4). This increased risk for prevalent AF remained significant after multivariate adjustment. The risk for incident AF increased across cystatin C quartiles in the unadjusted analysis (HR=1.37, 95% CI [1.07-1.75] in quartile 2; HR=1.43, 95% CI [1.11-1.84] in quartile 3; and HR=1.88, 95% CI [1.47-2.41] in quartile 4); however, after multivariate adjustment, these findings were no longer significant. An estimated GFR <60 mL.min.1.73m(2) was associated with prevalent and incident AF in unadjusted, but not multivariate analyses. CONCLUSIONS: Impaired kidney function, as measured by cystatin C, is an independent marker of prevalent AF; however, neither cystatin C nor eGFR are predictors of incident AF.
Keywords: Age Factors; Aged; Aged, 80 and over; Atrial Fibrillation; Cohort Studies; Cross-Sectional Studies; Female; Follow-Up Studies; Glomerular Filtration Rate; Humans; Kidney Diseases; Kidney Function Tests; Male

Intravenous tissue plasminogen activator and stroke in the elderly. - Longstreth, W T; Katz, Ronit; Tirschwell, David L; Cushman, Mary; Psaty, Bruce M (Am J Emerg Med, 2010)
OBJECTIVE: Since publication in 1995 of the National Institute of Neurological Disorders and Stroke (NINDS) trial of intravenous tissue plasminogen activator (IV tPA) for acute ischemic stroke, the benefit and frequency of use of IV tPA in the elderly have remained uncertain. METHODS: We obtained data from the NINDS trial to summarize outcomes for randomized subjects older than 80 years. We used data from the Cardiovascular Health Study, a cohort study of 5888 elderly participants from 4 US communities followed longitudinally for stroke since 1989 to estimate the use of and hospital outcome after IV tPA in older adults following publication of the trial in 1995. RESULTS: In the NINDS trial, 44 subjects older than 80 years were randomized, and their 3-month functional outcomes were not significantly improved with IV tPA. Of 25 randomized to IV tPA, 4 experienced symptomatic intracranial hemorrhages within 36 hours of treatment. Compared with younger patients, older patients were 2.87 times more likely to experience a symptomatic intracranial hemorrhage within 36 hours of IV tPA (95% confidence interval, 1.04-7.93). Of 227 Cardiovascular Health Study participants hospitalized for ischemic stroke between 1995 and 2002, seven, whose mean age was 84 years, were treated with IV tPA (3.1%; 95% confidence interval 1.2-6.2). Two had symptomatic intracranial hemorrhages, 3 failed to improve, and 2 of the 7 had good outcomes. CONCLUSIONS: These data highlight the need to clarify the risk-benefit profile of IV tPA in ischemic stroke victims who are older than 80 years.
Keywords: Aged, 80 and over; Female; Fibrinolytic Agents; Humans; Longitudinal Studies; Male; Placebos; Randomized Controlled Trials as Topic; Stroke; Tissue Plasminogen Activator; Treatment Outcome; United States

Large-scale genomic studies reveal central role of ABO in sP-selectin and sICAM-1 levels. - Barbalic, Maja; Dupuis, Josée; Dehghan, Abbas; Bis, Joshua C; Hoogeveen, Ron C; Schnabel, Renate B; Nambi, Vijay; Bretler, Monique; Smith, Nicholas L; Peters, Annette; Lu, Chen; Tracy, Russell P; et al. (Hum Mol Genet, 2010)
P-selectin and intercellular adhesion molecule-1 (ICAM-1) participate in inflammatory processes by promoting adhesion of leukocytes to vascular wall endothelium. Their soluble levels have been associated with adverse cardiovascular events. To identify loci affecting soluble levels of P-selectin (sP-selectin) and ICAM-1 (sICAM-1), we performed a genome-wide association study in a sample of 4115 (sP-selectin) and 9813 (sICAM-1) individuals of European ancestry as a part of The Cohorts for Heart and Aging Research in Genome Epidemiology consortium. The most significant SNP association for sP-selectin was within the SELP gene (rs6136, P = 4.05 x 10(-61)) and for sICAM-1 levels within the ICAM-1 gene (rs3093030, P = 3.53 x 10(-23)). Both sP-selectin and sICAM-1 were associated with ABO gene variants (rs579459, P = 1.86 x 10(-41) and rs649129, P = 1.22 x 10(-15), respectively) and in both cases the observed associations could be accounted for by the A1 allele of the ABO blood group. The absence of an association between ABO blood group and platelet-bound P-selectin levels in an independent subsample (N = 1088) from the ARIC study, suggests that the ABO blood group may influence cleavage of the P-selectin protein from the cell surface or clearance from the circulation, rather than its production and cellular presentation. These results provide new insights into adhesion molecule biology.
Keywords: ABO Blood-Group System; Blood Platelets; Enzyme-Linked Immunosorbent Assay; European Continental Ancestry Group; Fluorescence; Genome-Wide Association Study; Humans; Intercellular Adhesion Molecule-1; P-Selectin

Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) and risk of cardiovascular disease in older adults: results from the Cardiovascular Health Study. - Jenny, Nancy Swords; Solomon, Cam; Cushman, Mary; Tracy, Russell P; Nelson, Jeanenne J; Psaty, Bruce M; Furberg, Curt D (Atherosclerosis, 2010)
OBJECTIVE: To examine associations between lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) antigen level (mass) and enzymatic activity (activity) and cardiovascular disease (CVD) in older adults. METHODS: We examined associations of Lp-PLA(2) mass and activity with incident myocardial infarction (MI; n=508), stroke (n=565) and CVD death (n=665) using Cox regressions adjusted for age, sex, ethnicity and CVD risk factors in 3949 older adults, aged > or =65 years at baseline, from the Cardiovascular Health Study (CHS). RESULTS: Lp-PLA(2) was associated with incident CVD events in these older adults. Hazard ratios (95% confidence intervals) for highest versus lowest tertiles of Lp-PLA(2) mass were 1.49 (1.19-1.85) for MI, 1.21 (0.98-1.49) for stroke and 1.11 (0.92-1.33) for CVD death. The highest tertile of Lp-PLA(2) activity was associated with MI (1.36; 1.09-1.70) and CVD death (1.23; 1.02-1.50). Combined Lp-PLA(2) tertile 3 and CRP>3mg/l, compared to Lp-PLA(2) tertile 1 and CRP<1mg/l, was associated with MI (2.29; 1.49-3.52) for Lp-PLA(2) mass and MI (1.66; 1.10-2.51) and CVD death (1.57; 1.08-2.26) for activity. For MI, both mass and activity added excess risk to elevated CRP alone ( approximately 20% excess risk) and activity added excess risk for CVD death ( approximately 12%). CONCLUSION: Lp-PLA(2) mass and activity were associated with incident CVD events in older adults in CHS. Lp-PLA(2) and CRP were independent and additive in prediction of events. While associations were modest, these results support further exploration of Lp-PLA(2) to identify older individuals at risk for CVD.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; C-Reactive Protein; Cardiovascular Diseases; Female; Humans; Myocardial Infarction; Population Surveillance; Prospective Studies; Risk; Stroke

Meta-analyses of genome-wide association studies identify multiple loci associated with pulmonary function. - Hancock, Dana B; Eijgelsheim, Mark; Wilk, Jemma B; Gharib, Sina A; Loehr, Laura R; Marciante, Kristin D; Franceschini, Nora; van Durme, Yannick M T A; Chen, Ting-Hsu; Barr, R Graham; Schabath, Matthew B; Couper, David J; et al. (Nat Genet, 2010)
Spirometric measures of lung function are heritable traits that reflect respiratory health and predict morbidity and mortality. We meta-analyzed genome-wide association studies for two clinically important lung-function measures: forced expiratory volume in the first second (FEV(1)) and its ratio to forced vital capacity (FEV(1)/FVC), an indicator of airflow obstruction. This meta-analysis included 20,890 participants of European ancestry from four CHARGE Consortium studies: Atherosclerosis Risk in Communities, Cardiovascular Health Study, Framingham Heart Study and Rotterdam Study. We identified eight loci associated with FEV(1)/FVC (HHIP, GPR126, ADAM19, AGER-PPT2, FAM13A, PTCH1, PID1 and HTR4) and one locus associated with FEV(1) (INTS12-GSTCD-NPNT) at or near genome-wide significance (P < 5 x 10(-8)) in the CHARGE Consortium dataset. Our findings may offer insights into pulmonary function and pathogenesis of chronic lung disease.
Keywords: Databases, Genetic; Female; Forced Expiratory Volume; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung; Lung Diseases; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Spirometry; Vital Capacity

Meta-analysis identifies 13 new loci associated with waist-hip ratio and reveals sexual dimorphism in the genetic basis of fat distribution. - Heid, Iris M; Jackson, Anne U; Randall, Joshua C; Winkler, Thomas W; Qi, Lu; Steinthorsdottir, Valgerdur; Thorleifsson, Gudmar; Zillikens, M Carola; Speliotes, Elizabeth K; Mägi, Reedik; Workalemahu, Tsegaselassie; White, Charles C; et al. (Nat Genet, 2010)
Waist-hip ratio (WHR) is a measure of body fat distribution and a predictor of metabolic consequences independent of overall adiposity. WHR is heritable, but few genetic variants influencing this trait have been identified. We conducted a meta-analysis of 32 genome-wide association studies for WHR adjusted for body mass index (comprising up to 77,167 participants), following up 16 loci in an additional 29 studies (comprising up to 113,636 subjects). We identified 13 new loci in or near RSPO3, VEGFA, TBX15-WARS2, NFE2L3, GRB14, DNM3-PIGC, ITPR2-SSPN, LY86, HOXC13, ADAMTS9, ZNRF3-KREMEN1, NISCH-STAB1 and CPEB4 (P = 1.9 × 10⁻⁹ to P = 1.8 × 10⁻⁴⁰) and the known signal at LYPLAL1. Seven of these loci exhibited marked sexual dimorphism, all with a stronger effect on WHR in women than men (P for sex difference = 1.9 × 10⁻³ to P = 1.2 × 10⁻¹³). These findings provide evidence for multiple loci that modulate body fat distribution independent of overall adiposity and reveal strong gene-by-sex interactions.
Keywords: Adipose Tissue; Age Factors; Chromosome Mapping; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Sex Characteristics; Waist-Hip Ratio

A meta-analysis of four genome-wide association studies of survival to age 90 years or older: the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. - Newman, Anne B; Walter, Stefan; Lunetta, Kathryn L; Garcia, Melissa E; Slagboom, P Eline; Christensen, Kaare; Arnold, Alice M; Aspelund, Thor; Aulchenko, Yurii S; Benjamin, Emelia J; Christiansen, Lene; D'Agostino, Ralph B; et al. (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Genome-wide association studies (GWAS) may yield insights into longevity. METHODS: We performed a meta-analysis of GWAS in Caucasians from four prospective cohort studies: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Longevity was defined as survival to age 90 years or older (n = 1,836); the comparison group comprised cohort members who died between the ages of 55 and 80 years (n = 1,955). In a second discovery stage, additional genotyping was conducted in the Leiden Longevity Study cohort and the Danish 1905 cohort. RESULTS: There were 273 single-nucleotide polymorphism (SNP) associations with p < .0001, but none reached the prespecified significance level of 5 x 10(-8). Of the most significant SNPs, 24 were independent signals, and 16 of these SNPs were successfully genotyped in the second discovery stage, with one association for rs9664222, reaching 6.77 x 10(-7) for the combined meta-analysis of CHARGE and the stage 2 cohorts. The SNP lies in a region near MINPP1 (chromosome 10), a well-conserved gene involved in regulation of cellular proliferation. The minor allele was associated with lower odds of survival past age 90 (odds ratio = 0.82). Associations of interest in a homologue of the longevity assurance gene (LASS3) and PAPPA2 were not strengthened in the second stage. CONCLUSION: Survival studies of larger size or more extreme or specific phenotypes may support or refine these initial findings.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Cohort Studies; Confidence Intervals; Female; Genome-Wide Association Study; Genotype; Humans; Longevity; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide

Multiple genetic loci influence serum urate levels and their relationship with gout and cardiovascular disease risk factors. - Yang, Qiong; Köttgen, Anna; Dehghan, Abbas; Smith, Albert V; Glazer, Nicole L; Chen, Ming-Huei; Chasman, Daniel I; Aspelund, Thor; Eiriksdottir, Gudny; Harris, Tamara B; Launer, Lenore; Nalls, Michael; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Elevated serum urate levels can lead to gout and are associated with cardiovascular risk factors. We performed a genome-wide association study to search for genetic susceptibility loci for serum urate and gout and investigated the causal nature of the associations of serum urate with gout and selected cardiovascular risk factors and coronary heart disease (CHD). METHODS AND RESULTS: Meta-analyses of genome-wide association studies (GWAS) were performed in 5 population-based cohorts of the Cohorts for Heart and Aging Research in Genome Epidemiology consortium for serum urate and gout in 28 283 white participants. The effect of the most significant single-nucleotide polymorphism at all genome-wide significant loci on serum urate was added to create a genetic urate score. Findings were replicated in the Women's Genome Health Study (n=22 054). Single-nucleotide polymorphisms at 8 genetic loci achieved genome-wide significance with serum urate levels (P=4×10(-8) to 2×10(-242) in SLC22A11, GCKR, R3HDM2-INHBC region, RREB1, PDZK1, SLC2A9, ABCG2, and SLC17A1). Only 2 loci (SLC2A9, ABCG2) showed genome-wide significant association with gout. The genetic urate score was strongly associated with serum urate and gout (odds ratio, 12.4 per 100 μmol/L; P=3×10(-39)) but not with blood pressure, glucose, estimated glomerular filtration rate, chronic kidney disease, or CHD. The lack of association between the genetic score and the latter phenotypes also was observed in the Women's Genome Health Study. CONCLUSIONS: The genetic urate score analysis suggested a causal relationship between serum urate and gout but did not provide evidence for one between serum urate and cardiovascular risk factors and CHD.
Keywords: Cardiovascular Diseases; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Gout; Humans; Male; Risk Factors; Uric Acid

New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk. - Dupuis, Josée; Langenberg, Claudia; Prokopenko, Inga; Saxena, Richa; Soranzo, Nicole; Jackson, Anne U; Wheeler, Eleanor; Glazer, Nicole L; Bouatia-Naji, Nabila; Gloyn, Anna L; Lindgren, Cecilia M; Mägi, Reedik; et al. (Nat Genet, 2010)
Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5, MADD, ADRA2A, CRY2, FADS1, GLIS3, SLC2A2, PROX1 and C2CD4B) and one influencing fasting insulin and HOMA-IR (near IGF1). We also demonstrated association of ADCY5, PROX1, GCK, GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.
Keywords: Adolescent; Adult; Alleles; Blood Glucose; Child; Databases, Genetic; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Fasting; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeostasis; Humans; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Reproducibility of Results

New loci associated with kidney function and chronic kidney disease. - Köttgen, Anna; Pattaro, Cristian; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Glazer, Nicole L; Parsa, Afshin; Gao, Xiaoyi; Yang, Qiong; Smith, Albert V; O'Connell, Jeffrey R; Li, Man; et al. (Nat Genet, 2010)
Chronic kidney disease (CKD) is a significant public health problem, and recent genetic studies have identified common CKD susceptibility variants. The CKDGen consortium performed a meta-analysis of genome-wide association data in 67,093 individuals of European ancestry from 20 predominantly population-based studies in order to identify new susceptibility loci for reduced renal function as estimated by serum creatinine (eGFRcrea), serum cystatin c (eGFRcys) and CKD (eGFRcrea < 60 ml/min/1.73 m(2); n = 5,807 individuals with CKD (cases)). Follow-up of the 23 new genome-wide-significant loci (P < 5 x 10(-8)) in 22,982 replication samples identified 13 new loci affecting renal function and CKD (in or near LASS2, GCKR, ALMS1, TFDP2, DAB2, SLC34A1, VEGFA, PRKAG2, PIP5K1B, ATXN2, DACH1, UBE2Q2 and SLC7A9) and 7 loci suspected to affect creatinine production and secretion (CPS1, SLC22A2, TMEM60, WDR37, SLC6A13, WDR72 and BCAS3). These results further our understanding of the biologic mechanisms of kidney function by identifying loci that potentially influence nephrogenesis, podocyte function, angiogenesis, solute transport and metabolic functions of the kidney.
Keywords: Cohort Studies; Creatinine; Cystatin C; Diet; Europe; Genetic Markers; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Models, Genetic; Risk Factors

Novel associations of multiple genetic loci with plasma levels of factor VII, factor VIII, and von Willebrand factor: The CHARGE (Cohorts for Heart and Aging Research in Genome Epidemiology) Consortium. - Smith, Nicholas L; Chen, Ming-Huei; Dehghan, Abbas; Strachan, David P; Basu, Saonli; Soranzo, Nicole; Hayward, Caroline; Rudan, Igor; Sabater-Lleal, Maria; Bis, Joshua C; de Maat, Moniek P M; Rumley, Ann; et al. (Circulation, 2010)
BACKGROUND: Plasma levels of coagulation factors VII (FVII), VIII (FVIII), and von Willebrand factor (vWF) influence risk of hemorrhage and thrombosis. We conducted genome-wide association studies to identify new loci associated with plasma levels. METHODS AND RESULTS: The setting of the study included 5 community-based studies for discovery comprising 23 608 European-ancestry participants: Atherosclerosis Risk In Communities Study, Cardiovascular Health Study, British 1958 Birth Cohort, Framingham Heart Study, and Rotterdam Study. All subjects had genome-wide single-nucleotide polymorphism (SNP) scans and at least 1 phenotype measured: FVII activity/antigen, FVIII activity, and vWF antigen. Each study used its genotype data to impute to HapMap SNPs and independently conducted association analyses of hemostasis measures using an additive genetic model. Study findings were combined by meta-analysis. Replication was conducted in 7604 participants not in the discovery cohort. For FVII, 305 SNPs exceeded the genome-wide significance threshold of 5.0x10(-8) and comprised 5 loci on 5 chromosomes: 2p23 (smallest P value 6.2x10(-24)), 4q25 (3.6x10(-12)), 11q12 (2.0x10(-10)), 13q34 (9.0x10(-259)), and 20q11.2 (5.7x10(-37)). Loci were within or near genes, including 4 new candidate genes and F7 (13q34). For vWF, 400 SNPs exceeded the threshold and marked 8 loci on 6 chromosomes: 6q24 (1.2x10(-22)), 8p21 (1.3x10(-16)), 9q34 (<5.0x10(-324)), 12p13 (1.7x10(-32)), 12q23 (7.3x10(-10)), 12q24.3 (3.8x10(-11)), 14q32 (2.3x10(-10)), and 19p13.2 (1.3x10(-9)). All loci were within genes, including 6 new candidate genes, as well as ABO (9q34) and VWF (12p13). For FVIII, 5 loci were identified and overlapped vWF findings. Nine of the 10 new findings were replicated. CONCLUSIONS: New genetic associations were discovered outside previously known biological pathways and may point to novel prevention and treatment targets of hemostasis disorders.
Keywords: Adult; Factor VII; Factor VIII; Female; Genome-Wide Association Study; Hemostasis; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Thrombosis; von Willebrand Factor

Validation of an atrial fibrillation risk algorithm in whites and African Americans. - Schnabel, Renate B; Aspelund, Thor; Li, Guo; Sullivan, Lisa M; Suchy-Dicey, Astrid; Harris, Tamara B; Pencina, Michael J; D'Agostino, Ralph B; Levy, Daniel; Kannel, William B; Wang, Thomas J; Kronmal, Richard A; et al. (Arch Intern Med, 2010)
BACKGROUND: We sought to validate a recently published risk algorithm for incident atrial fibrillation (AF) in independent cohorts and other racial groups. METHODS: We evaluated the performance of a Framingham Heart Study (FHS)-derived risk algorithm modified for 5-year incidence of AF in the FHS (n = 4764 participants) and 2 geographically and racially diverse cohorts in the age range 45 to 95 years: AGES (the Age, Gene/Environment Susceptibility-Reykjavik Study) (n = 4238) and CHS (the Cardiovascular Health Study) (n = 5410, of whom 874 [16.2%] were African Americans). The risk algorithm included age, sex, body mass index, systolic blood pressure, electrocardiographic PR interval, hypertension treatment, and heart failure. RESULTS: We found 1359 incident AF events in 100 074 person-years of follow-up. Unadjusted 5-year event rates differed by cohort (AGES, 12.8 cases/1000 person-years; CHS whites, 22.7 cases/1000 person-years; and FHS, 4.5 cases/1000 person-years) and by race (CHS African Americans, 18.4 cases/1000 person-years). The strongest risk factors in all samples were age and heart failure. The relative risks for incident AF associated with risk factors were comparable across cohorts and race groups. After recalibration for baseline incidence and risk factor distribution, the Framingham algorithm, reported in C statistic, performed reasonably well in all samples: AGES, 0.67 (95% confidence interval [CI], 0.64-0.71); CHS whites, 0.68 (95% CI, 0.66-0.70); and CHS African Americans, 0.66 (95% CI, 0.61-0.71). Risk factors combined in the algorithm explained between 47.0% (AGES) and 63.6% (FHS) of the population-attributable risk. CONCLUSIONS: Risk of incident AF in community-dwelling whites and African Americans can be assessed reliably by routinely available and potentially modifiable clinical variables. Seven risk factors accounted for up to 64% of risk.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Algorithms; Atrial Fibrillation; Blood Pressure; Body Mass Index; Cohort Studies; Electrocardiography; Europe; European Continental Ancestry Group; Female; Follow-Up Studies; Heart Failure; Humans; Hypertension; Incidence; Kaplan-Meier Estimate; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Sex Factors; Systole; United States

Validation of the health ABC heart failure model for incident heart failure risk prediction: the Cardiovascular Health Study. - Kalogeropoulos, Andreas; Psaty, Bruce M; Vasan, Ramachandran S; Georgiopoulou, Vasiliki; Smith, Andrew L; Smith, Nicholas L; Kritchevsky, Stephen B; Wilson, Peter W F; Newman, Anne B; Harris, Tamara B; Butler, Javed (Circ Heart Fail, 2010)
BACKGROUND: The recently developed and internally validated Health ABC HF model uses 9 routinely available clinical variables to determine incident heart failure risk. In this study, we sought to externally validate the Health ABC HF model. METHODS AND RESULTS: Observed 5-year incidence of heart failure, defined as first hospitalization for new-onset heart failure, was compared with 5-year risk estimates derived from the Health ABC HF model among participants without heart failure at baseline in the Cardiovascular Health Study. During follow-up, 400 of 5335 (7.5%) participants developed heart failure over 5 years versus 364 (6.8%) predicted by the Health ABC HF model (predicted-to-observed ratio, 0.90). Observed versus predicted 5-year heart failure probabilities were 3.2% versus 2.8%, 9.0% versus 7.0%, 15.9% versus 13.7%, and 24.6% versus 30.8% for the <5%, 5% to 10%, 10% to 20%, and >20% 5-year risk categories, respectively. The Hosmer-Lemeshow chi(2) was 14.72 (degrees of freedom, 10; P=0.14), and the C index was 0.74 (95% CI, 0.72 to 0.76). Calibration and discrimination demonstrated adequate performance across sex and race overall; however, risk was underestimated in white men, especially in the 5% to 10% risk category. Model performance was optimal when participants with normal left ventricular function at baseline were assessed separately. Performance was consistent across age groups. Analyses with death as a competing risk yielded similar results. CONCLUSIONS: The Health ABC HF model adequately predicted 5-year heart failure risk in a large community-based study, providing support for the external validity of the model. This tool may be used to identify individuals to whom to target heart failure prevention efforts.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cause of Death; Cohort Studies; Confidence Intervals; Disease Progression; Echocardiography, Doppler; Female; Heart Failure; Humans; Incidence; Male; Models, Statistical; Predictive Value of Tests; Prognosis; Severity of Illness Index; Sex Distribution; Survival Analysis; United States

Antihypertensive medication use and change in kidney function in elderly adults: a marginal structural model analysis. - Odden, Michelle C; Tager, Ira B; van der Laan, Mark J; Delaney, Joseph A C; Peralta, Carmen A; Katz, Ronit; Sarnak, Mark J; Psaty, Bruce M; Shlipak, Michael G (Int J Biostat, 2011)
BACKGROUND: The evidence for the effectiveness of antihypertensive medication use for slowing decline in kidney function in older persons is sparse. We addressed this research question by the application of novel methods in a marginal structural model. METHODS: Change in kidney function was measured by two or more measures of cystatin C in 1,576 hypertensive participants in the Cardiovascular Health Study over 7 years of follow-up (1989-1997 in four U.S. communities). The exposure of interest was antihypertensive medication use. We used a novel estimator in a marginal structural model to account for bias due to confounding and informative censoring. RESULTS: The mean annual decline in eGFR was 2.41 ± 4.91 mL/min/1.73 m(2). In unadjusted analysis, antihypertensive medication use was not associated with annual change in kidney function. Traditional multivariable regression did not substantially change these estimates. Based on a marginal structural analysis, persons on antihypertensives had slower declines in kidney function; participants had an estimated 0.88 (0.13, 1.63) ml/min/1.73 m(2) per year slower decline in eGFR compared with persons on no treatment. In a model that also accounted for bias due to informative censoring, the estimate for the treatment effect was 2.23 (-0.13, 4.59) ml/min/1.73 m(2) per year slower decline in eGFR. CONCLUSION: In summary, estimates from a marginal structural model suggested that antihypertensive therapy was associated with preserved kidney function in hypertensive elderly adults. Confirmatory studies may provide power to determine the strength and validity of the findings.
Keywords: Aged; Antihypertensive Agents; Cystatin C; Data Interpretation, Statistical; Female; Glomerular Filtration Rate; Humans; Hypertension; Kidney; Longitudinal Studies; Male; Models, Statistical

Association of hypertension drug target genes with blood pressure and hypertension in 86,588 individuals. - Johnson, Andrew D; Newton-Cheh, Christopher; Chasman, Daniel I; Ehret, Georg B; Johnson, Toby; Rose, Lynda; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Gudnason, Vilmundur; Larson, Martin G; Chakravarti, Aravinda; et al. (Hypertension, 2011)
We previously conducted genome-wide association meta-analysis of systolic blood pressure, diastolic blood pressure, and hypertension in 29,136 people from 6 cohort studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Here we examine associations of these traits with 30 gene regions encoding known antihypertensive drug targets. We find nominal evidence of association of ADRB1, ADRB2, AGT, CACNA1A, CACNA1C, and SLC12A3 polymorphisms with 1 or more BP traits in the Cohorts for Heart and Aging Research in Genomic Epidemiology genome-wide association meta-analysis. We attempted replication of the top meta-analysis single nucleotide polymorphisms for these genes in the Global BPgen Consortium (n=34,433) and the Women's Genome Health Study (n=23,019) and found significant results for rs1801253 in ADRB1 (Arg389Gly), with the Gly allele associated with a lower mean systolic blood pressure (β: 0.57 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=4.7×10(-10)), diastolic blood pressure (β: 0.36 mm Hg; SE: 0.06 mm Hg; meta-analysis: P=9.5×10(-10)), and prevalence of hypertension (β: 0.06 mm Hg; SE: 0.02 mm Hg; meta-analysis: P=3.3×10(-4)). Variation in AGT (rs2004776) was associated with systolic blood pressure (β: 0.42 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=3.8×10(-6)), as well as diastolic blood pressure (P=5.0×10(-8)) and hypertension (P=3.7×10(-7)). A polymorphism in ACE (rs4305) showed modest replication of association with increased hypertension (β: 0.06 mm Hg; SE: 0.01 mm Hg; meta-analysis: P=3.0×10(-5)). Two loci, ADRB1 and AGT, contain single nucleotide polymorphisms that reached a genome-wide significance threshold in meta-analysis for the first time. Our findings suggest that these genes warrant further studies of their genetic effects on blood pressure, including pharmacogenetic interactions.
Keywords: Alleles; Angiotensinogen; Antihypertensive Agents; Blood Pressure; Female; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Male; Pharmacogenetics; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-1

A bivariate genome-wide approach to metabolic syndrome: STAMPEED consortium. - Kraja, Aldi T; Vaidya, Dhananjay; Pankow, James S; Goodarzi, Mark O; Assimes, Themistocles L; Kullo, Iftikhar J; Sovio, Ulla; Mathias, Rasika A; Sun, Yan V; Franceschini, Nora; Absher, Devin; Li, Guo; et al. (Diabetes, 2011)
OBJECTIVE The metabolic syndrome (MetS) is defined as concomitant disorders of lipid and glucose metabolism, central obesity, and high blood pressure, with an increased risk of type 2 diabetes and cardiovascular disease. This study tests whether common genetic variants with pleiotropic effects account for some of the correlated architecture among five metabolic phenotypes that define MetS. RESEARCH DESIGN AND METHODS Seven studies of the STAMPEED consortium, comprising 22,161 participants of European ancestry, underwent genome-wide association analyses of metabolic traits using a panel of ∼2.5 million imputed single nucleotide polymorphisms (SNPs). Phenotypes were defined by the National Cholesterol Education Program (NCEP) criteria for MetS in pairwise combinations. Individuals exceeding the NCEP thresholds for both traits of a pair were considered affected. RESULTS Twenty-nine common variants were associated with MetS or a pair of traits. Variants in the genes LPL, CETP, APOA5 (and its cluster), GCKR (and its cluster), LIPC, TRIB1, LOC100128354/MTNR1B, ABCB11, and LOC100129150 were further tested for their association with individual qualitative and quantitative traits. None of the 16 top SNPs (one per gene) associated simultaneously with more than two individual traits. Of them 11 variants showed nominal associations with MetS per se. The effects of 16 top SNPs on the quantitative traits were relatively small, together explaining from ∼9% of the variance in triglycerides, 5.8% of high-density lipoprotein cholesterol, 3.6% of fasting glucose, and 1.4% of systolic blood pressure. CONCLUSIONS Qualitative and quantitative pleiotropic tests on pairs of traits indicate that a small portion of the covariation in these traits can be explained by the reported common genetic variants.
Keywords: Adult; Aged; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Meta-Analysis as Topic; Metabolic Syndrome; Middle Aged; Phenotype; Polymorphism, Single Nucleotide

Carotid intima-media thickness, electrocardiographic left ventricular hypertrophy, and incidence of intracerebral hemorrhage. - Folsom, Aaron R; Yatsuya, Hiroshi; Psaty, Bruce M; Shahar, Eyal; Longstreth, W T (Stroke, 2011)
BACKGROUND AND PURPOSE: Carotid intima-media thickness and electrocardiographic left ventricular hypertrophy are 2 subclinical cardiovascular disease measures associated with increased risk of total and ischemic strokes. Increased intima-media thickness and electrocardiographic left ventricular hypertrophy also may reflect end-organ hypertensive effects. Information is scant on the associations of these subclinical measures with intracerebral hemorrhage (ICH). We hypothesized that greater carotid intima-media thickness and the presence of electrocardiographic left ventricular hypertrophy would be independently associated with increased ICH incidence. METHODS: Among 18,155 participants initially free of stroke in the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS), we assessed carotid intima-media thickness, carotid plaque, and electrocardiographic left ventricular hypertrophy. Over a median of 18 years of follow-up, 162 incident ICH events occurred. RESULTS: After adjustment for other ICH risk factors, carotid intima-media thickness was associated positively with incidence of ICH in both ARIC and CHS. The risk was lowest in study-specific Quartile 1, elevated 1.6- to 2.6-fold in Quartiles 2 to 3, and elevated 2.5 to 3.7-fold in Quartile 4 (P<0.05 for both studies). In CHS, having a carotid plaque was associated with a 2-fold (95% CI, 1.1-3.4) greater ICH risk than having no plaque, but only 1.2-fold (95% CI, 0.76-2.0) greater ICH risk in ARIC. Electrocardiographic left ventricular hypertrophy carried a hazard ratio of ICH of 1.7 (95% CI, 0.77-3.7) in CHS and 2.8 (95% CI, 1.2-6.4) in ARIC. CONCLUSIONS: Our data suggest that people with carotid atherosclerosis and possibly left ventricular hypertrophy are at increased risk not only of ischemic stroke, but also of ICH.
Keywords: Carotid Intima-Media Thickness; Cerebral Hemorrhage; Cohort Studies; Electrocardiography; Female; Follow-Up Studies; Humans; Hypertrophy, Left Ventricular; Incidence; Male; Middle Aged; Prospective Studies; Risk Factors

Cerivastatin, genetic variants, and the risk of rhabdomyolysis. - Marciante, Kristin D; Durda, Jon P; Heckbert, Susan R; Lumley, Thomas; Rice, Ken; McKnight, Barbara; Totah, Rheem A; Tamraz, Bani; Kroetz, Deanna L; Fukushima, Hisayo; Kaspera, Rüdiger; Bis, Joshua C; et al. (Pharmacogenet Genomics, 2011)
OBJECTIVE: The withdrawal of cerivastatin involved an uncommon but serious adverse reaction, rhabdomyolysis. The bimodal response, rhabdomyolysis in a small proportion of users, points to genetic factors as a potential cause. We conducted a case-control study to evaluate genetic markers for cerivastatin-associated rhabdomyolysis. METHODS: This study had two components: a candidate gene study to evaluate variants in CYP2C8, UGT1A1, UGT1A3, and SLCO1B1; and a genome-wide association study to identify risk factors in other regions of the genome. A total of 185 rhabdomyolysis cases were frequency matched to statin-using controls from the Cardiovascular Health Study (n=374) and the Heart and Vascular Health Study (n=358). Validation relied on functional studies. RESULTS: Permutation test results suggested an association between cerivastatin-associated rhabdomyolysis and variants in SLCO1B1 (P=0.002), but not variants in CYP2C8 (P=0.073) or UGTs (P=0.523). An additional copy of the minor allele of SLCO1B1 rs4149056 (p.Val174Ala) was associated with the risk of rhabdomyolysis (odds ratio: 1.89; 95% confidence interval: 1.40-2.56). In transfected cells, this variant reduced cerivastatin transport by 40% compared with the reference transporter (P<0.001). The genome-wide association study identified an intronic variant (rs2819742) in the ryanodine receptor 2 gene (RYR2) as significant (P=1.74E-07). An additional copy of the minor allele of the RYR2 variant was associated with a reduced risk of rhabdomyolysis (odds ratio: 0.48; 95% confidence interval: 0.36-0.63). CONCLUSION: We identified modest genetic risk factors for an extreme response to cerivastatin. Disabling genetic variants in the candidate genes were not responsible for the bimodal response to cerivastatin.
Keywords: Adult; Aged; Aged, 80 and over; Aryl Hydrocarbon Hydroxylases; Case-Control Studies; Cytochrome P-450 CYP2C8; Female; Genetic Variation; Genome-Wide Association Study; Glucuronosyltransferase; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Organic Anion Transporters; Polymorphism, Single Nucleotide; Pyridines; Rhabdomyolysis; Risk; Ryanodine Receptor Calcium Release Channel; Solute Carrier Organic Anion Transporter Family Member 1b1

The contribution of a 9p21.3 variant, a KIF6 variant, and C-reactive protein to predicting risk of myocardial infarction in a prospective study. - Shiffman, Dov; O'Meara, Ellen S; Rowland, Charles M; Louie, Judy Z; Cushman, Mary; Tracy, Russell P; Devlin, James J; Psaty, Bruce M (BMC Cardiovasc Disord, 2011)
BACKGROUND: Genetic risk factors might improve prediction of coronary events. Several variants at chromosome 9p21.3 have been widely reported to be associated with coronary heart disease (CHD) in prospective and case-control studies. A variant of KIF6 (719Arg) has also been reported to be associated with increased risk of CHD in large prospective studies, but not in case-control studies. We asked whether the addition of genetic information (the 9p21.3 or KIF6 variants) or a well-established non-genetic risk factor (C-reactive protein [CRP]) can improve risk prediction by the Framingham Risk Score (FRS) in the Cardiovascular Health Study (CHS)--a prospective observational study of risk factors for cardiovascular disease among > 5,000 participants aged 65 or older. METHODS: Improvement of risk prediction was assessed by change in the area under the receiver-operator characteristic curve (AUC) and by net reclassification improvement (NRI). RESULTS: Among white participants the FRS was improved by addition of KIF6 719Arg carrier status among men as assessed by the AUC (from 0.581 to 0.596, P = 0.03) but not by NRI (NRI = 0.027, P = 0.32). Adding both CRP and 719Arg carrier status to the FRS improved risk prediction by the AUC (0.608, P = 0.02) and NRI (0.093, P = 0.008) in men, but not women (P ≥ 0.24). CONCLUSIONS: While none of these risk markers individually or in combination improved risk prediction among women, a combination of KIF6 719Arg carrier status and CRP levels modestly improved risk prediction among white men; although this improvement is not significant after multiple-testing correction. These observations should be investigated in other prospective studies.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; C-Reactive Protein; Case-Control Studies; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Variation; Humans; Kinesin; Male; Myocardial Infarction; Predictive Value of Tests; Prospective Studies; Risk Factors

CUBN is a gene locus for albuminuria. - Böger, Carsten A; Chen, Ming-Huei; Tin, Adrienne; Olden, Matthias; Köttgen, Anna; de Boer, Ian H; Fuchsberger, Christian; O'Seaghdha, Conall M; Pattaro, Cristian; Teumer, Alexander; Liu, Ching-Ti; Glazer, Nicole L; et al. (J Am Soc Nephrol, 2011)
Identification of genetic risk factors for albuminuria may alter strategies for early prevention of CKD progression, particularly among patients with diabetes. Little is known about the influence of common genetic variants on albuminuria in both general and diabetic populations. We performed a meta-analysis of data from 63,153 individuals of European ancestry with genotype information from genome-wide association studies (CKDGen Consortium) and from a large candidate gene study (CARe Consortium) to identify susceptibility loci for the quantitative trait urinary albumin-to-creatinine ratio (UACR) and the clinical diagnosis microalbuminuria. We identified an association between a missense variant (I2984V) in the CUBN gene, which encodes cubilin, and both UACR (P = 1.1 × 10(-11)) and microalbuminuria (P = 0.001). We observed similar associations among 6981 African Americans in the CARe Consortium. The associations between this variant and both UACR and microalbuminuria were significant in individuals of European ancestry regardless of diabetes status. Finally, this variant associated with a 41% increased risk for the development of persistent microalbuminuria during 20 years of follow-up among 1304 participants with type 1 diabetes in the prospective DCCT/EDIC Study. In summary, we identified a missense CUBN variant that associates with levels of albuminuria in both the general population and in individuals with diabetes.
Keywords: African Continental Ancestry Group; Albuminuria; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Humans; Mutation, Missense; Receptors, Cell Surface

Electrocardiographic and clinical predictors separating atherosclerotic sudden cardiac death from incident coronary heart disease. - Soliman, Elsayed Z; Prineas, Ronald J; Case, L Douglas; Russell, Gregory; Rosamond, Wayne; Rea, Thomas; Sotoodehnia, Nona; Post, Wendy S; Siscovick, David; Psaty, Bruce M; Burke, Gregory L (Heart, 2011)
OBJECTIVE: To identify specific ECG and clinical predictors that separate atherosclerotic sudden cardiac death (SCD) from incident coronary heart disease (CHD) (non-fatal events and non-sudden death) in the combined cohorts of the Atherosclerosis Risk in Communities study and the Cardiovascular Health Study. METHODS: This analysis included 18,497 participants (58% females, 24% black individuals, mean age 58 years) who were initially free of clinical CHD. A competing risk analysis was conducted to examine the prognostic significance of baseline clinical characteristics and an extensive electronic database of ECG measurements for prediction of 229 cases of SCD as a first event versus 2297 incident CHD cases (2122 non-fatal events and 175 non-sudden death) that occurred during a median follow-up time of 13 years in the Cardiovascular Health Study and 14 years in the Atherosclerosis Risk in Communities study. RESULTS: After adjusting for common CHD risk factors, a number of clinical characteristics and ECG measurements were independently predictive of SCD and CHD. However, the risk of SCD versus incident CHD was significantly different for race/ethnicity, hypertension, body mass index (BMI), heart rate, QTc, abnormally inverted T wave in any ECG lead group and level of ST elevation in V2. Black race/ethnicity (compared to non-black) was predictive of high SCD risk but less risk of incident CHD (p value for differences in the risk (HR) for SCD versus CHD <0.0001). Hypertension, increased heart rate, prolongation of QTc and abnormally inverted T wave were stronger predictors of high SCD risk compared to CHD (p value=0.0460, 0.0398, 0.0158 and 0.0265, respectively). BMI was not predictive of incident CHD but was predictive of high SCD risk in a quadratic fashion (p value=0.0220). On the other hand, elevated ST height as measured at the J point and that measured at 60 ms after the J point in V2 were not predictive of SCD but were predictive of high incident CHD risk (p value=0.0251 and 0.0155, respectively). CONCLUSIONS: SCD and CHD have many risk factors in common. Hypertension, race/ethnicity, BMI, heart rate, QTc, abnormally inverted T wave in any ECG lead group and level of ST elevation in V2 have the potential to separate between the risks of SCD and CHD. These results need to be validated in another cohort.
Keywords: Adult; Aged; Aged, 80 and over; Body Mass Index; Continental Population Groups; Coronary Disease; Death, Sudden, Cardiac; Electrocardiography; Ethnic Groups; Female; Heart Rate; Humans; Hypertension; Male; Middle Aged; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Adjustment; Risk Factors; Time Factors; United States

Fasting and post-glucose load measures of insulin resistance and risk of ischemic stroke in older adults. - Thacker, Evan L; Psaty, Bruce M; McKnight, Barbara; Heckbert, Susan R; Longstreth, W T; Mukamal, Kenneth J; Meigs, James B; de Boer, Ian H; Boyko, Edward J; Carnethon, Mercedes R; Kizer, Jorge R; Tracy, Russell P; et al. (Stroke, 2011)
BACKGROUND AND PURPOSE: Few studies have assessed post-glucose load measures of insulin resistance and ischemic stroke risk, and data are sparse for older adults. We investigated whether fasting and post-glucose load measures of insulin resistance were related to incident ischemic stroke in nondiabetic, older adults. METHODS: Participants were men and women in the Cardiovascular Health Study, age 65+ years and without prevalent diabetes or stroke at baseline, followed for 17 years for incident ischemic stroke. The Gutt insulin sensitivity index was calculated from baseline body weight and from fasting and 2-hour postload insulin and glucose; a lower Gutt index indicates higher insulin resistance. RESULTS: Analyses included 3442 participants (42% men) with a mean age of 73 years. Incidence of ischemic stroke was 9.8 strokes per 1000 person-years. The relative risk (RR) for lowest quartile versus highest quartile of Gutt index was 1.64 (95% CI, 1.24-2.16), adjusted for demographics and prevalent cardiovascular and kidney disease. Similarly, the adjusted RR for highest quartile versus lowest quartile of 2-hour glucose was 1.84 (95% CI, 1.39-2.42). In contrast, the adjusted RR for highest quartile versus lowest quartile of fasting insulin was 1.10 (95% CI, 0.84-1.46). CONCLUSIONS: In nondiabetic, older adults, insulin resistance measured by Gutt index or 2-hour glucose, but not by fasting insulin, was associated with risk of incident ischemic stroke.
Keywords: Aged; Aged, 80 and over; Blood Glucose; Body Mass Index; Brain Ischemia; Fasting; Female; Humans; Incidence; Insulin Resistance; Male; Risk; Stroke

Gender differences between the Minnesota code and Novacode electrocardiographic prognostication of coronary heart disease in the cardiovascular health study. - Zhang, Zhu-Ming; Prineas, Ronald J; Case, Doug; Psaty, Bruce M; Suzuki, Takeki; Burke, Gregory L (Am J Cardiol, 2011)
The Minnesota Code (MC) and Novacode (Nova) are the most widely used electrocardiographic (ECG) classification systems. The comparative strengths of their classifications for Q- and ST-T-wave abnormalities in predicting coronary heart disease (CHD) events and total mortality have not been evaluated separately by gender. We studied standard 12-lead electrocardiograms at rest from 4,988 participants in the Cardiovascular Health Study. Average age at baseline was 73 years, 60% of participants were women 85% were white, and 22% had a history of cardiovascular disease or presence of ECG myocardial infarction by MC or Nova. Starting in 1989 with an average 17-year follow-up, 65% of participants died and 33% had incident CHD in a cohort free of cardiovascular disease at baseline. Of these, electrocardiograms with major Q-wave or major ST-T abnormalities by MC or Nova predicted increased risk for CHD events and total mortality with no significant differences in predictability between men and women. The study also found that women had fewer major Q-wave changes but more major ST-T abnormalities than men. However, there were no gender differences in predicting CHD events and total mortality. In conclusion, ECG classification systems for myocardial infarction/ischemia abnormalities by MC or Nova are valuable and useful for men and women in clinical trials and epidemiologic studies.
Keywords: Aged; Coronary Disease; Electrocardiography; Female; Humans; Incidence; Male; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Sex Factors; United States

Genetic loci associated with plasma phospholipid n-3 fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Lemaitre, Rozenn N; Tanaka, Toshiko; Tang, Weihong; Manichaikul, Ani; Foy, Millennia; Kabagambe, Edmond K; Nettleton, Jennifer A; King, Irena B; Weng, Lu-Chen; Bhattacharya, Sayanti; Bandinelli, Stefania; Bis, Joshua C; et al. (PLoS Genet, 2011)
Long-chain n-3 polyunsaturated fatty acids (PUFAs) can derive from diet or from α-linolenic acid (ALA) by elongation and desaturation. We investigated the association of common genetic variation with plasma phospholipid levels of the four major n-3 PUFAs by performing genome-wide association studies in five population-based cohorts comprising 8,866 subjects of European ancestry. Minor alleles of SNPs in FADS1 and FADS2 (desaturases) were associated with higher levels of ALA (p = 3 x 10⁻⁶⁴) and lower levels of eicosapentaenoic acid (EPA, p = 5 x 10⁻⁵⁸) and docosapentaenoic acid (DPA, p = 4 x 10⁻¹⁵⁴). Minor alleles of SNPs in ELOVL2 (elongase) were associated with higher EPA (p = 2 x 10⁻¹²) and DPA (p = 1 x 10⁻⁴³) and lower docosahexaenoic acid (DHA, p = 1 x 10⁻¹⁵). In addition to genes in the n-3 pathway, we identified a novel association of DPA with several SNPs in GCKR (glucokinase regulator, p = 1 x 10⁻⁸). We observed a weaker association between ALA and EPA among carriers of the minor allele of a representative SNP in FADS2 (rs1535), suggesting a lower rate of ALA-to-EPA conversion in these subjects. In samples of African, Chinese, and Hispanic ancestry, associations of n-3 PUFAs were similar with a representative SNP in FADS1 but less consistent with a representative SNP in ELOVL2. Our findings show that common variation in n-3 metabolic pathway genes and in GCKR influences plasma phospholipid levels of n-3 PUFAs in populations of European ancestry and, for FADS1, in other ancestries.
Keywords: Alleles; Continental Population Groups; Fatty Acids, Omega-3; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide

Genetic predictors of fibrin D-dimer levels in healthy adults. - Smith, Nicholas L; Huffman, Jennifer E; Strachan, David P; Huang, Jie; Dehghan, Abbas; Trompet, Stella; Lopez, Lorna M; Shin, So-Youn; Baumert, Jens; Vitart, Veronique; Bis, Joshua C; Wild, Sarah H; et al. (Circulation, 2011)
BACKGROUND: Fibrin fragment D-dimer, one of several peptides produced when crosslinked fibrin is degraded by plasmin, is the most widely used clinical marker of activated blood coagulation. To identity genetic loci influencing D-dimer levels, we performed the first large-scale, genome-wide association search. METHODS AND RESULTS: A genome-wide investigation of the genomic correlates of plasma D-dimer levels was conducted among 21 052 European-ancestry adults. Plasma levels of D-dimer were measured independently in each of 13 cohorts. Each study analyzed the association between ≈2.6 million genotyped and imputed variants across the 22 autosomal chromosomes and natural-log–transformed D-dimer levels using linear regression in additive genetic models adjusted for age and sex. Among all variants, 74 exceeded the genome-wide significance threshold and marked 3 regions. At 1p22, rs12029080 (P=6.4×10(-52)) was 46.0 kb upstream from F3, coagulation factor III (tissue factor). At 1q24, rs6687813 (P=2.4×10(-14)) was 79.7 kb downstream of F5, coagulation factor V. At 4q32, rs13109457 (P=2.9×10(-18)) was located between 2 fibrinogen genes: 10.4 kb downstream from FGG and 3.0 kb upstream from FGA. Variants were associated with a 0.099-, 0.096-, and 0.061-unit difference, respectively, in natural-log–transformed D-dimer and together accounted for 1.8% of the total variance. When adjusted for nonsynonymous substitutions in F5 and FGA loci known to be associated with D-dimer levels, there was no evidence of an additional association at either locus. CONCLUSIONS: Three genes were associated with fibrin D-dimer levels. Of these 3, the F3 association was the strongest, and has not been previously reported.
Keywords: Adult; Aged; Blood Coagulation; European Continental Ancestry Group; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Testing; Genome-Wide Association Study; Humans; Male; Middle Aged; Reference Values; Thromboplastin

Genetic variants in novel pathways influence blood pressure and cardiovascular disease risk. - Ehret, Georg B; Munroe, Patricia B; Rice, Kenneth M; Bochud, Murielle; Johnson, Andrew D; Chasman, Daniel I; Smith, Albert V; Tobin, Martin D; Verwoert, Germaine C; Hwang, Shih-Jen; Pihur, Vasyl; Vollenweider, Peter; et al. (Nature, 2011)
Blood pressure is a heritable trait influenced by several biological pathways and responsive to environmental stimuli. Over one billion people worldwide have hypertension (≥140 mm Hg systolic blood pressure or  ≥90 mm Hg diastolic blood pressure). Even small increments in blood pressure are associated with an increased risk of cardiovascular events. This genome-wide association study of systolic and diastolic blood pressure, which used a multi-stage design in 200,000 individuals of European descent, identified sixteen novel loci: six of these loci contain genes previously known or suspected to regulate blood pressure (GUCY1A3-GUCY1B3, NPR3-C5orf23, ADM, FURIN-FES, GOSR2, GNAS-EDN3); the other ten provide new clues to blood pressure physiology. A genetic risk score based on 29 genome-wide significant variants was associated with hypertension, left ventricular wall thickness, stroke and coronary artery disease, but not kidney disease or kidney function. We also observed associations with blood pressure in East Asian, South Asian and African ancestry individuals. Our findings provide new insights into the genetics and biology of blood pressure, and suggest potential novel therapeutic pathways for cardiovascular disease prevention.
Keywords: Africa; Asia; Blood Pressure; Cardiovascular Diseases; Coronary Artery Disease; Europe; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Kidney Diseases; Polymorphism, Single Nucleotide; Stroke

Genetic variation near IRS1 associates with reduced adiposity and an impaired metabolic profile. - Kilpeläinen, Tuomas O; Zillikens, M Carola; Stančáková, Alena; Finucane, Francis M; Ried, Janina S; Langenberg, Claudia; Zhang, Weihua; Beckmann, Jacques S; Luan, Jian'an; Vandenput, Liesbeth; Styrkarsdottir, Unnur; Zhou, Yanhua; et al. (Nat Genet, 2011)
Genome-wide association studies have identified 32 loci influencing body mass index, but this measure does not distinguish lean from fat mass. To identify adiposity loci, we meta-analyzed associations between ∼2.5 million SNPs and body fat percentage from 36,626 individuals and followed up the 14 most significant (P < 10(-6)) independent loci in 39,576 individuals. We confirmed a previously established adiposity locus in FTO (P = 3 × 10(-26)) and identified two new loci associated with body fat percentage, one near IRS1 (P = 4 × 10(-11)) and one near SPRY2 (P = 3 × 10(-8)). Both loci contain genes with potential links to adipocyte physiology. Notably, the body-fat-decreasing allele near IRS1 is associated with decreased IRS1 expression and with an impaired metabolic profile, including an increased visceral to subcutaneous fat ratio, insulin resistance, dyslipidemia, risk of diabetes and coronary artery disease and decreased adiponectin levels. Our findings provide new insights into adiposity and insulin resistance.
Keywords: Adiponectin; Adiposity; Alleles; Body Fat Distribution; Body Mass Index; Body Weight; Female; Genetic Variation; Genome-Wide Association Study; Humans; Insulin Receptor Substrate Proteins; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Meta-Analysis as Topic; Metabolome; Obesity; Polymorphism, Single Nucleotide; Subcutaneous Fat

Genome-wide association and large-scale follow up identifies 16 new loci influencing lung function. - Soler Artigas, Maria; Loth, Daan W; Wain, Louise V; Gharib, Sina A; Obeidat, Ma'en; Tang, Wenbo; Zhai, Guangju; Zhao, Jing Hua; Smith, Albert Vernon; Huffman, Jennifer E; Albrecht, Eva; Jackson, Catherine M; et al. (Nat Genet, 2011)
Pulmonary function measures reflect respiratory health and are used in the diagnosis of chronic obstructive pulmonary disease. We tested genome-wide association with forced expiratory volume in 1 second and the ratio of forced expiratory volume in 1 second to forced vital capacity in 48,201 individuals of European ancestry with follow up of the top associations in up to an additional 46,411 individuals. We identified new regions showing association (combined P < 5 × 10(-8)) with pulmonary function in or near MFAP2, TGFB2, HDAC4, RARB, MECOM (also known as EVI1), SPATA9, ARMC2, NCR3, ZKSCAN3, CDC123, C10orf11, LRP1, CCDC38, MMP15, CFDP1 and KCNE2. Identification of these 16 new loci may provide insight into the molecular mechanisms regulating pulmonary function and into molecular targets for future therapy to alleviate reduced lung function.
Keywords: Child; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger

A genome-wide association study identifies novel loci associated with circulating IGF-I and IGFBP-3. - Kaplan, Robert C; Petersen, Ann-Kristin; Chen, Ming-Huei; Teumer, Alexander; Glazer, Nicole L; Döring, Angela; Lam, Carolyn S P; Friedrich, Nele; Newman, Anne; Müller, Martina; Yang, Qiong; Homuth, Georg; et al. (Hum Mol Genet, 2011)
Insulin-like growth factor-I (IGF-I) and insulin-like growth factor-binding protein-3 (IGFBP-3) are involved in cell replication, proliferation, differentiation, protein synthesis, carbohydrate homeostasis and bone metabolism. Circulating IGF-I and IGFBP-3 concentrations predict anthropometric traits and risk of cancer and cardiovascular disease. In a genome-wide association study of 10 280 middle-aged and older men and women from four community-based cohort studies, we confirmed a known association of single nucleotide polymorphisms in the IGFBP3 gene region on chromosome 7p12.3 with IGFBP-3 concentrations using a significance threshold of P < 5 × 10(-8) (P = 3.3 × 10(-101)). Furthermore, the same IGFBP3 gene locus (e.g. rs11977526) that was associated with IGFBP-3 concentrations was also associated with the opposite direction of effect, with IGF-I concentration after adjustment for IGFBP-3 concentration (P = 1.9 × 10(-26)). A novel and independent locus on chromosome 7p12.3 (rs700752) had genome-wide significant associations with higher IGFBP-3 (P = 4.4 × 10(-21)) and higher IGF-I (P = 4.9 × 10(-9)) concentrations; when the two measurements were adjusted for one another, the IGF-I association was attenuated but the IGFBP-3 association was not. Two additional loci demonstrated genome-wide significant associations with IGFBP-3 concentration (rs1065656, chromosome 16p13.3, P = 1.2 × 10(-11), IGFALS, a confirmatory finding; and rs4234798, chromosome 4p16.1, P = 4.5 × 10(-10), SORCS2, a novel finding). Together, the four genome-wide significant loci explained 6.5% of the population variation in IGFBP-3 concentration. Furthermore, we observed a borderline statistically significant association between IGF-I concentration and FOXO3 (rs2153960, chromosome 6q21, P = 5.1 × 10(-7)), a locus associated with longevity. These genetic loci deserve further investigation to elucidate the biological basis for the observed associations and clarify their possible role in IGF-mediated regulation of cell growth and metabolism.
Keywords: Aged; Chromosomes, Human, Pair 7; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Polymorphism, Single Nucleotide

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

A genome-wide association study of aging. - Walter, Stefan; Atzmon, Gil; Demerath, Ellen W; Garcia, Melissa E; Kaplan, Robert C; Kumari, Meena; Lunetta, Kathryn L; Milaneschi, Yuri; Tanaka, Toshiko; Tranah, Gregory J; Völker, Uwe; Yu, Lei; et al. (Neurobiol Aging, 2011)
Human longevity and healthy aging show moderate heritability (20%-50%). We conducted a meta-analysis of genome-wide association studies from 9 studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium for 2 outcomes: (1) all-cause mortality, and (2) survival free of major disease or death. No single nucleotide polymorphism (SNP) was a genome-wide significant predictor of either outcome (p < 5 × 10(-8)). We found 14 independent SNPs that predicted risk of death, and 8 SNPs that predicted event-free survival (p < 10(-5)). These SNPs are in or near genes that are highly expressed in the brain (HECW2, HIP1, BIN2, GRIA1), genes involved in neural development and function (KCNQ4, LMO4, GRIA1, NETO1) and autophagy (ATG4C), and genes that are associated with risk of various diseases including cancer and Alzheimer's disease. In addition to considerable overlap between the traits, pathway and network analysis corroborated these findings. These findings indicate that variation in genes involved in neurological processes may be an important factor in regulating aging free of major disease and achieving longevity.
Keywords: Aging; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Longevity

Identification of a sudden cardiac death susceptibility locus at 2q24.2 through genome-wide association in European ancestry individuals. - Arking, Dan E; Junttila, M Juhani; Goyette, Philippe; Huertas-Vazquez, Adriana; Eijgelsheim, Mark; Blom, Marieke T; Newton-Cheh, Christopher; Reinier, Kyndaron; Teodorescu, Carmen; Uy-Evanado, Audrey; Carter-Monroe, Naima; Kaikkonen, Kari S; et al. (PLoS Genet, 2011)
Sudden cardiac death (SCD) continues to be one of the leading causes of mortality worldwide, with an annual incidence estimated at 250,000-300,000 in the United States and with the vast majority occurring in the setting of coronary disease. We performed a genome-wide association meta-analysis in 1,283 SCD cases and >20,000 control individuals of European ancestry from 5 studies, with follow-up genotyping in up to 3,119 SCD cases and 11,146 controls from 11 European ancestry studies, and identify the BAZ2B locus as associated with SCD (P = 1.8×10(-10)). The risk allele, while ancestral, has a frequency of ~1.4%, suggesting strong negative selection and increases risk for SCD by 1.92-fold per allele (95% CI 1.57-2.34). We also tested the role of 49 SNPs previously implicated in modulating electrocardiographic traits (QRS, QT, and RR intervals). Consistent with epidemiological studies showing increased risk of SCD with prolonged QRS/QT intervals, the interval-prolonging alleles are in aggregate associated with increased risk for SCD (P = 0.006).
Keywords: Adult; Aged; Alleles; Chromosomes, Human, Pair 2; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Contraction; Polymorphism, Single Nucleotide

Leukocyte telomere length and mortality in the Cardiovascular Health Study. - Fitzpatrick, Annette L; Kronmal, Richard A; Kimura, Masayuki; Gardner, Jeffrey P; Psaty, Bruce M; Jenny, Nancy S; Tracy, Russell P; Hardikar, Sheetal; Aviv, Abraham (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Leukocyte telomere length (LTL) is related to diseases of aging, but studies of mortality have been inconsistent. METHODS: We evaluated LTL in relation to total mortality and specific cause of death in 1,136 participants of the Cardiovascular Health Study who provided blood samples in 1992-1993 and survived through 1997-1998. LTL was measured by Southern blots of the terminal restriction fragments. Cause of death was classified by a committee of physicians reviewing death certificates, medical records, and informant interviews. RESULTS: A total of 468 (41.2%) deaths occurred over 6.1 years of follow-up in participants with mean age of 73.9 years (SD 4.7), 65.4% female, and 14.8% African American. Although increased age and male gender were associated with shorter LTLs, African Americans had significantly longer LTLs independent of age and sex (p < .001). Adjusted for age, sex, and race, persons with the shortest quartile of LTL were 60% more likely to die during follow-up than those within the longest quartile (hazard ratio: 1.61, 95% confidence interval: 1.22-2.12, p = .001). The association remained after adjustment for cardiovascular disease risk factors. Evaluations of cause of death found LTL to be related to deaths due to an infectious disease etiology (hazard ratio: 2.80, 95% confidence interval: 1.32-5.94, p = .007), whereas a borderline association was found for cardiac deaths (hazard ratio: 1.82, 95% confidence interval: 0.95-3.49, p = .07) in adjusted models. Risk estimates for deaths due to cancer, dementia, and ischemic stroke were not significant. CONCLUSION: These data weakly corroborate prior findings of associations between LTL and mortality in the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Body Mass Index; Cardiovascular Diseases; Cause of Death; Comorbidity; Coronary Disease; Diabetes Mellitus; Female; Humans; Hypertension; Leukocytes; Longitudinal Studies; Male; Prospective Studies; Smoking; Stroke; Telomere

Meta-analysis of genome-wide association studies from the CHARGE consortium identifies common variants associated with carotid intima media thickness and plaque. - Bis, Joshua C; Kavousi, Maryam; Franceschini, Nora; Isaacs, Aaron; Abecasis, Goncalo R; Schminke, Ulf; Post, Wendy S; Smith, Albert V; Cupples, L Adrienne; Markus, Hugh S; Schmidt, Reinhold; Huffman, Jennifer E; et al. (Nat Genet, 2011)
Carotid intima media thickness (cIMT) and plaque determined by ultrasonography are established measures of subclinical atherosclerosis that each predicts future cardiovascular disease events. We conducted a meta-analysis of genome-wide association data in 31,211 participants of European ancestry from nine large studies in the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. We then sought additional evidence to support our findings among 11,273 individuals using data from seven additional studies. In the combined meta-analysis, we identified three genomic regions associated with common carotid intima media thickness and two different regions associated with the presence of carotid plaque (P < 5 × 10(-8)). The associated SNPs mapped in or near genes related to cellular signaling, lipid metabolism and blood pressure homeostasis, and two of the regions were associated with coronary artery disease (P < 0.006) in the Coronary Artery Disease Genome-Wide Replication and Meta-Analysis (CARDIoGRAM) consortium. Our findings may provide new insight into pathways leading to subclinical atherosclerosis and subsequent cardiovascular events.
Keywords: Adult; Aged; Aging; Atherosclerosis; Carotid Intima-Media Thickness; Cohort Studies; Coronary Artery Disease; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Heart; Humans; Middle Aged; Phenotype; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Risk Factors

Meta-analysis of genome-wide association studies in >80 000 subjects identifies multiple loci for C-reactive protein levels. - Dehghan, Abbas; Dupuis, Josée; Barbalic, Maja; Bis, Joshua C; Eiriksdottir, Gudny; Lu, Chen; Pellikka, Niina; Wallaschofski, Henri; Kettunen, Johannes; Henneman, Peter; Baumert, Jens; Strachan, David P; et al. (Circulation, 2011)
BACKGROUND: C-reactive protein (CRP) is a heritable marker of chronic inflammation that is strongly associated with cardiovascular disease. We sought to identify genetic variants that are associated with CRP levels. METHODS AND RESULTS: We performed a genome-wide association analysis of CRP in 66 185 participants from 15 population-based studies. We sought replication for the genome-wide significant and suggestive loci in a replication panel comprising 16 540 individuals from 10 independent studies. We found 18 genome-wide significant loci, and we provided evidence of replication for 8 of them. Our results confirm 7 previously known loci and introduce 11 novel loci that are implicated in pathways related to the metabolic syndrome (APOC1, HNF1A, LEPR, GCKR, HNF4A, and PTPN2) or the immune system (CRP, IL6R, NLRP3, IL1F10, and IRF1) or that reside in regions previously not known to play a role in chronic inflammation (PPP1R3B, SALL1, PABPC4, ASCL1, RORA, and BCL7B). We found a significant interaction of body mass index with LEPR (P<2.9×10(-6)). A weighted genetic risk score that was developed to summarize the effect of risk alleles was strongly associated with CRP levels and explained ≈5% of the trait variance; however, there was no evidence for these genetic variants explaining the association of CRP with coronary heart disease. CONCLUSIONS: We identified 18 loci that were associated with CRP levels. Our study highlights immune response and metabolic regulatory pathways involved in the regulation of chronic inflammation.
Keywords: Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Vasculitis

New gene functions in megakaryopoiesis and platelet formation. - Gieger, Christian; Radhakrishnan, Aparna; Cvejic, Ana; Tang, Weihong; Porcu, Eleonora; Pistis, Giorgio; Serbanovic-Canic, Jovana; Elling, Ulrich; Goodall, Alison H; Labrune, Yann; Lopez, Lorna M; Mägi, Reedik; et al. (Nature, 2011)
Platelets are the second most abundant cell type in blood and are essential for maintaining haemostasis. Their count and volume are tightly controlled within narrow physiological ranges, but there is only limited understanding of the molecular processes controlling both traits. Here we carried out a high-powered meta-analysis of genome-wide association studies (GWAS) in up to 66,867 individuals of European ancestry, followed by extensive biological and functional assessment. We identified 68 genomic loci reliably associated with platelet count and volume mapping to established and putative novel regulators of megakaryopoiesis and platelet formation. These genes show megakaryocyte-specific gene expression patterns and extensive network connectivity. Using gene silencing in Danio rerio and Drosophila melanogaster, we identified 11 of the genes as novel regulators of blood cell formation. Taken together, our findings advance understanding of novel gene functions controlling fate-determining events during megakaryopoiesis and platelet formation, providing a new example of successful translation of GWAS to function.
Keywords: Animals; Blood Platelets; Cell Size; Drosophila melanogaster; Drosophila Proteins; Europe; Gene Expression Profiling; Gene Silencing; Genome, Human; Genome-Wide Association Study; Hematopoiesis; Humans; Megakaryocytes; Platelet Count; Protein Interaction Maps; Transcription, Genetic; Zebrafish; Zebrafish Proteins

A phenomics-based strategy identifies loci on APOC1, BRAP, and PLCG1 associated with metabolic syndrome phenotype domains. - Avery, Christy L; He, Qianchuan; North, Kari E; Ambite, José L; Boerwinkle, Eric; Fornage, Myriam; Hindorff, Lucia A; Kooperberg, Charles; Meigs, James B; Pankow, James S; Pendergrass, Sarah A; Psaty, Bruce M; et al. (PLoS Genet, 2011)
Despite evidence of the clustering of metabolic syndrome components, current approaches for identifying unifying genetic mechanisms typically evaluate clinical categories that do not provide adequate etiological information. Here, we used data from 19,486 European American and 6,287 African American Candidate Gene Association Resource Consortium participants to identify loci associated with the clustering of metabolic phenotypes. Six phenotype domains (atherogenic dyslipidemia, vascular dysfunction, vascular inflammation, pro-thrombotic state, central obesity, and elevated plasma glucose) encompassing 19 quantitative traits were examined. Principal components analysis was used to reduce the dimension of each domain such that >55% of the trait variance was represented within each domain. We then applied a statistically efficient and computational feasible multivariate approach that related eight principal components from the six domains to 250,000 imputed SNPs using an additive genetic model and including demographic covariates. In European Americans, we identified 606 genome-wide significant SNPs representing 19 loci. Many of these loci were associated with only one trait domain, were consistent with results in African Americans, and overlapped with published findings, for instance central obesity and FTO. However, our approach, which is applicable to any set of interval scale traits that is heritable and exhibits evidence of phenotypic clustering, identified three new loci in or near APOC1, BRAP, and PLCG1, which were associated with multiple phenotype domains. These pleiotropic loci may help characterize metabolic dysregulation and identify targets for intervention.
Keywords: African Americans; Apolipoprotein C-I; Blood Glucose; Dyslipidemias; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome, Human; Humans; Metabolic Syndrome; Obesity, Abdominal; Phenotype; Phospholipase C gamma; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Ubiquitin-Protein Ligases; Vascular Diseases

Seasonal variation in 25-hydroxyvitamin D concentrations in the cardiovascular health study. - Shoben, Abigail B; Kestenbaum, Bryan; Levin, Gregory; Hoofnagle, Andrew N; Psaty, Bruce M; Siscovick, David S; de Boer, Ian H (Am J Epidemiol, 2011)
Low circulating concentrations of 25-hydroxyvitamin D (25(OH)D) are associated with adverse health outcomes in diverse populations. However, 25(OH)D concentrations vary seasonally with varying exposure to sunlight, so single measurements may poorly reflect long-term 25(OH)D exposure. The authors investigated cyclical trends in average serum 25(OH)D concentrations among 2,298 individuals enrolled in the Cardiovascular Health Study of community-based older adults (1992-1993). A sinusoidal model closely approximated observed 25(OH)D concentrations and fit the data significantly better than did a mean model (P < 0.0001). The mean annual 25(OH)D concentration was 25.1 ng/mL (95% confidence interval: 24.7, 25.5), and the mean peak-trough difference was 9.6 ng/mL (95% confidence interval: 8.5, 10.7). Male sex, higher latitude of study site, and greater physical activity levels were associated with larger peak-trough difference in 25(OH)D concentration (each P < 0.05). Serum concentrations of intact parathyroid hormone and bone-specific alkaline phosphatase also varied in a sinusoidal fashion (P < 0.0001), inversely to 25(OH)D. In conclusion, serum 25(OH)D varies in a sinusoidal manner, with large seasonal differences relative to mean concentration and laboratory evidence of biologic sequelae. Single 25(OH)D measurements might not capture overall vitamin D status, and the extent of misclassification could vary by demographic and behavioral factors. Accounting for collection time may reduce bias in research studies and improve decision-making in clinical care.
Keywords: Aged; Biomarkers; Continental Population Groups; Exercise; Female; Humans; Male; Residence Characteristics; Seasons; Sex Factors; Vitamin D

Subclinical vascular disease burden and risk for death and cardiovascular events in older community dwellers. - Inzitari, Marco; Arnold, Alice M; Patel, Kushang V; Mercer, Laina D; Karlamangla, Arun; Ding, Jingzhong; Psaty, Bruce M; Williamson, Jeff D; Kuller, Lewis H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Individual measures and previous composite measures of subclinical vascular disease defined high risk for cardiovascular events, but did not detect low and modest risk. A different approach might better describe the spectrum from low to high risk. Methods and Results. In the Cardiovascular Health Study, 3,252 participants without history of clinical cardiovascular disease (M ± SD 74.3 years ± 5.1, 63% women, 17% African Americans) had noninvasive vascular assessments in 1992-1993. We assigned a score of 0, 1, or 2 (no, mild, or severe abnormalities) to ankle-arm index, electrocardiogram, and common carotid intima-media thickness, based on clinical cutoffs. A summary index (range 0-6, absent to severe disease) summed individual scores. Abdominal aortic ultrasound and brain magnetic resonance imaging were collected in a subsample. Mortality and incident cardiovascular events were identified through June 2008. Event and death rates increased across index grades. Comparing grades 1 to 5+ with absent disease, and adjusting for demographics, hazard ratios for cardiovascular events within 8 years ranged from 1.1 (95% confidence interval 0.8-1.6) to 4.7 (3.4-6.9) and, for mortality, from 1.5 (1.0-2.3) to 5.0 (3.3-7.7) (p for trend across grades <.001 for both outcomes). Adjustment for cardiovascular risk factors did not substantially change the associations. The index improved mortality risk classification over demographics and risk factors in participants who did not die during the follow-up. Including in the index the aortic ultrasound and the brain magnetic resonance imaging further improved risk classification. CONCLUSIONS: Older adults with minimal subclinical vascular disease had low cardiovascular events risk and mortality. This approach might more fully account for vascular burden.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cost of Illness; Female; Humans; Male; Risk; Vascular Diseases

Systolic blood pressure and incident heart failure in the elderly. The Cardiovascular Health Study and the Health, Ageing and Body Composition Study. - Butler, Javed; Kalogeropoulos, Andreas P; Georgiopoulou, Vasiliki V; Bibbins-Domingo, Kirsten; Najjar, Samer S; Sutton-Tyrrell, Kim C; Harris, Tamara B; Kritchevsky, Stephen B; Lloyd-Jones, Donald M; Newman, Anne B; Psaty, Bruce M (Heart, 2011)
BACKGROUND: The exact form of the association between systolic blood pressure (SBP) and heart failure (HF) risk in the elderly remains incompletely defined, especially in individuals not receiving antihypertensive drugs. OBJECTIVE: To examine the association between SBP and HF risk in the elderly. DESIGN: Competing-risks proportional hazards modelling of incident HF risk, using 10-year follow-up data from two NIH-sponsored cohort studies: the Cardiovascular Health Study (inception: 1989-90 and 1992-3) and the Health ABC Study (inception: 1997-8). SETTING: Community-based cohorts. PARTICIPANTS: 4408 participants (age, 72.8 (4.9) years; 53.1% women, 81.7% white; 18.3% black) without prevalent HF and not receiving antihypertensive drugs at baseline. MAIN OUTCOME MEASURES: Incident HF, defined as first adjudicated hospitalisation for HF. RESULTS: Over 10 years, 493 (11.2%) participants developed HF. Prehypertension (120-139 mm Hg), stage 1 (140-159 mm Hg), and stage 2 (≥160 mm Hg) hypertension were associated with escalating HF risk; HRs versus optimal SBP (<120 mm Hg) in competing-risks models controlling for clinical characteristics were 1.63 (95% CI 1.23 to 2.16; p=0.001), 2.21 (95% CI 1.65 to 2.96; p<0.001) and 2.60 (95% CI 1.85 to 3.64; p<0.001), respectively. Overall 255/493 (51.7%) HF events occurred in participants with SBP <140 mm Hg at baseline. Increasing SBP was associated with higher HF risk in women than in men; no race-SBP interaction was seen. In analyses with continuous SBP, HF risk had a continuous positive association with SBP to levels as low as 113 mm Hg in men and 112 mm Hg in women. CONCLUSIONS: There is a continuous positive association between SBP and HF risk in the elderly for levels of SBP as low as <115 mm Hg; over half of incident HF events occur in individuals with SBP <140 mm Hg.
Keywords: Aged; Aged, 80 and over; Aging; Blood Pressure; Body Composition; Epidemiologic Methods; Female; Heart Failure; Humans; Hypertension; Male; Myocardial Infarction; Sex Factors; Stroke; Stroke Volume

Vitamin D, parathyroid hormone, and sudden cardiac death: results from the Cardiovascular Health Study. - Deo, Rajat; Katz, Ronit; Shlipak, Michael G; Sotoodehnia, Nona; Psaty, Bruce M; Sarnak, Mark J; Fried, Linda F; Chonchol, Michel; de Boer, Ian H; Enquobahrie, Daniel; Siscovick, David; Kestenbaum, Bryan (Hypertension, 2011)
Recent studies have demonstrated greater risks of cardiovascular events and mortality among persons who have lower 25-hydroxyvitamin D (25-OHD) and higher parathyroid hormone (PTH) levels. We sought to evaluate the association between markers of mineral metabolism and sudden cardiac death (SCD) among the 2312 participants from the Cardiovascular Health Study who were free of clinical cardiovascular disease at baseline. We estimated associations of baseline 25-OHD and PTH concentrations individually and in combination with SCD using Cox proportional hazards models after adjustment for demographics, cardiovascular risk factors, and kidney function. During a median follow-up of 14 years, there were 73 adjudicated SCD events. The annual incidence of SCD was greater among subjects who had lower 25-OHD concentrations, 2 events per 1000 for 25-OHD ≥20 ng/mL and 4 events per 1000 for 25-OHD <20 ng/mL. Similarly, SCD incidence was greater among subjects who had higher PTH concentrations, 2 events per 1000 for PTH <65 pg/mL and 4 events per 1000 for PTH ≥65 pg/mL. Multivariate adjustment attenuated associations of 25-OHD and PTH with SCD. Finally, 267 participants (11.7% of the cohort) had high PTH and low 25-OHD concentrations. This combination was associated with a >2-fold risk of SCD after adjustment (hazard ratio: 2.19 [95% CI: 1.17-4.10]; P=0.017) compared with participants with normal levels of PTH and 25-OHD. The combination of lower 25-OHD and higher PTH concentrations appears to be associated independently with SCD risk among older adults without cardiovascular disease.
Keywords: Aged; Cardiovascular Diseases; Comorbidity; Death, Sudden, Cardiac; Diabetes Mellitus; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Kidney; Male; Middle Aged; Minerals; Parathyroid Hormone; Proportional Hazards Models; Risk Factors; Socioeconomic Factors; United States; Vitamin D

Assessment of gene-by-sex interaction effect on bone mineral density. - Liu, Ching-Ti; Estrada, Karol; Yerges-Armstrong, Laura M; Amin, Najaf; Evangelou, Evangelos; Li, Guo; Minster, Ryan L; Carless, Melanie A; Kammerer, Candace M; Oei, Ling; Zhou, Yanhua; Alonso, Nerea; et al. (J Bone Miner Res, 2012)
Sexual dimorphism in various bone phenotypes, including bone mineral density (BMD), is widely observed; however, the extent to which genes explain these sex differences is unclear. To identify variants with different effects by sex, we examined gene-by-sex autosomal interactions genome-wide, and performed expression quantitative trait loci (eQTL) analysis and bioinformatics network analysis. We conducted an autosomal genome-wide meta-analysis of gene-by-sex interaction on lumbar spine (LS) and femoral neck (FN) BMD in 25,353 individuals from 8 cohorts. In a second stage, we followed up the 12 top single-nucleotide polymorphisms (SNPs; p < 1 × 10(-5) ) in an additional set of 24,763 individuals. Gene-by-sex interaction and sex-specific effects were examined in these 12 SNPs. We detected one novel genome-wide significant interaction associated with LS-BMD at the Chr3p26.1-p25.1 locus, near the GRM7 gene (male effect = 0.02 and p = 3.0 × 10(-5) ; female effect = -0.007 and p = 3.3 × 10(-2) ), and 11 suggestive loci associated with either FN- or LS-BMD in discovery cohorts. However, there was no evidence for genome-wide significant (p < 5 × 10(-8) ) gene-by-sex interaction in the joint analysis of discovery and replication cohorts. Despite the large collaborative effort, no genome-wide significant evidence for gene-by-sex interaction was found to influence BMD variation in this screen of autosomal markers. If they exist, gene-by-sex interactions for BMD probably have weak effects, accounting for less than 0.08% of the variation in these traits per implicated SNP. © 2012 American Society for Bone and Mineral Research.
Keywords: Bone Density; Cohort Studies; Female; Genes; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Sex Characteristics

Association between chromosome 9p21 variants and the ankle-brachial index identified by a meta-analysis of 21 genome-wide association studies. - Murabito, Joanne M; White, Charles C; Kavousi, Maryam; Sun, Yan V; Feitosa, Mary F; Nambi, Vijay; Lamina, Claudia; Schillert, Arne; Coassin, Stefan; Bis, Joshua C; Broer, Linda; Crawford, Dana C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genetic determinants of peripheral arterial disease (PAD) remain largely unknown. To identify genetic variants associated with the ankle-brachial index (ABI), a noninvasive measure of PAD, we conducted a meta-analysis of genome-wide association study data from 21 population-based cohorts. METHODS AND RESULTS: Continuous ABI and PAD (ABI ≤0.9) phenotypes adjusted for age and sex were examined. Each study conducted genotyping and imputed data to the ≈2.5 million single nucleotide polymorphisms (SNPs) in HapMap. Linear and logistic regression models were used to test each SNP for association with ABI and PAD using additive genetic models. Study-specific data were combined using fixed effects inverse variance weighted meta-analyses. There were a total of 41 692 participants of European ancestry (≈60% women, mean ABI 1.02 to 1.19), including 3409 participants with PAD and with genome-wide association study data available. In the discovery meta-analysis, rs10757269 on chromosome 9 near CDKN2B had the strongest association with ABI (β=-0.006, P=2.46×10(-8)). We sought replication of the 6 strongest SNP associations in 5 population-based studies and 3 clinical samples (n=16 717). The association for rs10757269 strengthened in the combined discovery and replication analysis (P=2.65×10(-9)). No other SNP associations for ABI or PAD achieved genome-wide significance. However, 2 previously reported candidate genes for PAD and 1 SNP associated with coronary artery disease were associated with ABI: DAB21P (rs13290547, P=3.6×10(-5)), CYBA (rs3794624, P=6.3×10(-5)), and rs1122608 (LDLR, P=0.0026). CONCLUSIONS: Genome-wide association studies in more than 40 000 individuals identified 1 genome wide significant association on chromosome 9p21 with ABI. Two candidate genes for PAD and 1 SNP for coronary artery disease are associated with ABI.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Ankle Brachial Index; Chromosomes, Human, Pair 9; Cohort Studies; Cyclin-Dependent Kinase Inhibitor p15; Female; Genome-Wide Association Study; Genotype; HapMap Project; Humans; Logistic Models; Male; Middle Aged; Peripheral Vascular Diseases; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Sex Factors

Development and validation of a coronary risk prediction model for older U.S. and European persons in the Cardiovascular Health Study and the Rotterdam Study. - Koller, Michael T; Leening, Maarten J G; Wolbers, Marcel; Steyerberg, Ewout W; Hunink, M G Myriam; Schoop, Rotraut; Hofman, Albert; Bucher, Heiner C; Psaty, Bruce M; Lloyd-Jones, Donald M; Witteman, Jacqueline C M (Ann Intern Med, 2012)
BACKGROUND: Risk scores for prediction of coronary heart disease (CHD) in older adults are needed. OBJECTIVE: To develop a sex-specific CHD risk prediction model for older adults that accounts for competing risks for death. DESIGN: 2 observational cohort studies, using data from 4946 participants in the Cardiovascular Health Study (CHS) and 4303 participants in the Rotterdam Study (RS). SETTING: Community settings in the United States (CHS) and Rotterdam, the Netherlands (RS). PARTICIPANTS: Persons aged 65 years or older who were free of cardiovascular disease. MEASUREMENTS: A composite of nonfatal myocardial infarction and coronary death. RESULTS: During a median follow-up of 16.5 and 14.9 years, 1166 CHS and 698 RS participants had CHD events, respectively. Deaths from noncoronary causes largely exceeded the number of CHD events, complicating accurate CHD risk predictions. The prediction model had moderate ability to discriminate between events and nonevents (c-statistic, 0.63 in both U.S. and European men and 0.67 and 0.68 in U.S. and European women). The model was well-calibrated; predicted risks were in good agreement with observed risks. Compared with the Framingham point scores, the prediction model classified elderly U.S. persons into higher risk categories but elderly European persons into lower risk categories. Differences in classification accuracy were not consistent and depended on cohort and sex. Adding newer cardiovascular risk markers to the model did not substantially improve performance. LIMITATION: The model may be less applicable in nonwhite populations, and the comparison Framingham model was not designed for adults older than 79 years. CONCLUSION: A CHD risk prediction model that accounts for deaths from noncoronary causes among older adults provided well-calibrated risk estimates but was not substantially more accurate than Framingham point scores. Moreover, adding newer risk markers did not improve accuracy. These findings emphasize the difficulties of predicting CHD risk in elderly persons and the need to improve these predictions. PRIMARY FUNDING SOURCE: National Heart, Lung, and Blood Institute; National Institute of Neurological Disorders and Stroke; The Netherlands Organisation for Scientific Research; and the Netherlands Organisation for Health Research and Development.
Keywords: Aged; Aged, 80 and over; Algorithms; Cause of Death; Coronary Disease; European Continental Ancestry Group; Female; Humans; Incidence; Male; Models, Statistical; Multivariate Analysis; Netherlands; Prospective Studies; Risk Assessment; Risk Factors; United States

Eight genetic loci associated with variation in lipoprotein-associated phospholipase A2 mass and activity and coronary heart disease: meta-analysis of genome-wide association studies from five community-based studies. - Grallert, Harald; Dupuis, Josée; Bis, Joshua C; Dehghan, Abbas; Barbalic, Maja; Baumert, Jens; Lu, Chen; Smith, Nicholas L; Uitterlinden, André G; Roberts, Robert; Khuseyinova, Natalie; Schnabel, Renate B; et al. (Eur Heart J, 2012)
AIMS: Lipoprotein-associated phospholipase A2 (Lp-PLA2) generates proinflammatory and proatherogenic compounds in the arterial vascular wall and is a potential therapeutic target in coronary heart disease (CHD). We searched for genetic loci related to Lp-PLA2 mass or activity by a genome-wide association study as part of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. METHODS AND RESULTS: In meta-analyses of findings from five population-based studies, comprising 13 664 subjects, variants at two loci (PLA2G7, CETP) were associated with Lp-PLA2 mass. The strongest signal was at rs1805017 in PLA2G7 [P = 2.4 × 10(-23), log Lp-PLA2 difference per allele (beta): 0.043]. Variants at six loci were associated with Lp-PLA2 activity (PLA2G7, APOC1, CELSR2, LDL, ZNF259, SCARB1), among which the strongest signals were at rs4420638, near the APOE-APOC1-APOC4-APOC2 cluster [P = 4.9 × 10(-30); log Lp-PLA2 difference per allele (beta): -0.054]. There were no significant gene-environment interactions between these eight polymorphisms associated with Lp-PLA2 mass or activity and age, sex, body mass index, or smoking status. Four of the polymorphisms (in APOC1, CELSR2, SCARB1, ZNF259), but not PLA2G7, were significantly associated with CHD in a second study. CONCLUSION: Levels of Lp-PLA2 mass and activity were associated with PLA2G7, the gene coding for this protein. Lipoprotein-associated phospholipase A2 activity was also strongly associated with genetic variants related to low-density lipoprotein cholesterol levels.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Coronary Artery Disease; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Phospholipases A2; Polymorphism, Single Nucleotide

FTO genotype is associated with phenotypic variability of body mass index. - Yang, Jian; Loos, Ruth J F; Powell, Joseph E; Medland, Sarah E; Speliotes, Elizabeth K; Chasman, Daniel I; Rose, Lynda M; Thorleifsson, Gudmar; Steinthorsdottir, Valgerdur; Mägi, Reedik; Waite, Lindsay; Smith, Albert Vernon; et al. (Nature, 2012)
There is evidence across several species for genetic control of phenotypic variation of complex traits, such that the variance among phenotypes is genotype dependent. Understanding genetic control of variability is important in evolutionary biology, agricultural selection programmes and human medicine, yet for complex traits, no individual genetic variants associated with variance, as opposed to the mean, have been identified. Here we perform a meta-analysis of genome-wide association studies of phenotypic variation using ∼170,000 samples on height and body mass index (BMI) in human populations. We report evidence that the single nucleotide polymorphism (SNP) rs7202116 at the FTO gene locus, which is known to be associated with obesity (as measured by mean BMI for each rs7202116 genotype), is also associated with phenotypic variability. We show that the results are not due to scale effects or other artefacts, and find no other experiment-wise significant evidence for effects on variability, either at loci other than FTO for BMI or at any locus for height. The difference in variance for BMI among individuals with opposite homozygous genotypes at the FTO locus is approximately 7%, corresponding to a difference of ∼0.5 kilograms in the standard deviation of weight. Our results indicate that genetic variants can be discovered that are associated with variability, and that between-person variability in obesity can partly be explained by the genotype at the FTO locus. The results are consistent with reported FTO by environment interactions for BMI, possibly mediated by DNA methylation. Our BMI results for other SNPs and our height results for all SNPs suggest that most genetic variants, including those that influence mean height or mean BMI, are not associated with phenotypic variance, or that their effects on variability are too small to detect even with samples sizes greater than 100,000.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Height; Body Mass Index; Co-Repressor Proteins; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteins; Repressor Proteins

Genetic risk factors for ischaemic stroke and its subtypes (the METASTROKE collaboration): a meta-analysis of genome-wide association studies. - Traylor, Matthew; Farrall, Martin; Holliday, Elizabeth G; Sudlow, Cathie; Hopewell, Jemma C; Cheng, Yu-Ching; Fornage, Myriam; Ikram, M Arfan; Malik, Rainer; Bevan, Steve; Thorsteinsdottir, Unnur; Nalls, Mike A; et al. (Lancet Neurol, 2012)
BACKGROUND: Various genome-wide association studies (GWAS) have been done in ischaemic stroke, identifying a few loci associated with the disease, but sample sizes have been 3500 cases or less. We established the METASTROKE collaboration with the aim of validating associations from previous GWAS and identifying novel genetic associations through meta-analysis of GWAS datasets for ischaemic stroke and its subtypes. METHODS: We meta-analysed data from 15 ischaemic stroke cohorts with a total of 12 389 individuals with ischaemic stroke and 62 004 controls, all of European ancestry. For the associations reaching genome-wide significance in METASTROKE, we did a further analysis, conditioning on the lead single nucleotide polymorphism in every associated region. Replication of novel suggestive signals was done in 13 347 cases and 29 083 controls. FINDINGS: We verified previous associations for cardioembolic stroke near PITX2 (p=2·8×10(-16)) and ZFHX3 (p=2·28×10(-8)), and for large-vessel stroke at a 9p21 locus (p=3·32×10(-5)) and HDAC9 (p=2·03×10(-12)). Additionally, we verified that all associations were subtype specific. Conditional analysis in the three regions for which the associations reached genome-wide significance (PITX2, ZFHX3, and HDAC9) indicated that all the signal in each region could be attributed to one risk haplotype. We also identified 12 potentially novel loci at p<5×10(-6). However, we were unable to replicate any of these novel associations in the replication cohort. INTERPRETATION: Our results show that, although genetic variants can be detected in patients with ischaemic stroke when compared with controls, all associations we were able to confirm are specific to a stroke subtype. This finding has two implications. First, to maximise success of genetic studies in ischaemic stroke, detailed stroke subtyping is required. Second, different genetic pathophysiological mechanisms seem to be associated with different stroke subtypes. FUNDING: Wellcome Trust, UK Medical Research Council (MRC), Australian National and Medical Health Research Council, National Institutes of Health (NIH) including National Heart, Lung and Blood Institute (NHLBI), the National Institute on Aging (NIA), the National Human Genome Research Institute (NHGRI), and the National Institute of Neurological Disorders and Stroke (NINDS).
Keywords: Brain Ischemia; Databases, Genetic; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Stroke

Genetic variants and associations of 25-hydroxyvitamin D concentrations with major clinical outcomes. - Levin, Gregory P; Robinson-Cohen, Cassianne; de Boer, Ian H; Houston, Denise K; Lohman, Kurt; Liu, Yongmei; Kritchevsky, Stephen B; Cauley, Jane A; Tanaka, Toshiko; Ferrucci, Luigi; Bandinelli, Stefania; Patel, Kushang V; et al. (JAMA, 2012)
CONTEXT: Lower serum 25-hydroxyvitamin D concentrations are associated with greater risks of many chronic diseases across large, prospective community-based studies. Substrate 25-hydroxyvitamin D must be converted to 1,25-dihydroxyvitamin D for full biological activity, and complex metabolic pathways suggest that interindividual variability in vitamin D metabolism may alter the clinical consequences of measured serum 25-hydroxyvitamin D. OBJECTIVE: To investigate whether common variation within genes encoding the vitamin D-binding protein, megalin, cubilin, CYP27B1, CYP24A1, and the vitamin D receptor (VDR) modify associations of low 25-hydroxyvitamin D with major clinical outcomes. DESIGN, SETTING, AND PARTICIPANTS: Examination of 141 single-nucleotide polymorphisms in a discovery cohort of 1514 white participants (who were recruited from 4 US regions) from the community-based Cardiovascular Health Study. Participants had serum 25-hydroxyvitamin D measurements in 1992-1993 and were followed up for a median of 11 years (through 2006). Replication meta-analyses were conducted across the independent, community-based US Health, Aging, and Body Composition (n = 922; follow-up: 1998-1999 through 2005), Italian Invecchiare in Chianti (n = 835; follow-up: 1998-2000 through 2006), and Swedish Uppsala Longitudinal Study of Adult Men (n = 970; follow-up: 1991-1995 through 2008) cohort studies. MAIN OUTCOME MEASURE: Composite outcome of incident hip facture, myocardial infarction, cancer, and mortality over long-term follow-up. RESULTS: Interactions between 5 single-nucleotide polymorphisms and low 25-hydroxyvitamin D concentration were identified in the discovery phase and 1 involving a variant in the VDR gene replicated in independent meta-analysis. Among Cardiovascular Health Study participants, low 25-hydroxyvitamin D concentration was associated with hazard ratios for risk of the composite outcome of 1.40 (95% CI, 1.12-1.74) for those who had 1 minor allele at rs7968585 and 1.82 (95% CI, 1.31-2.54) for those with 2 minor alleles at rs7968585. In contrast, there was no evidence of an association (estimated hazard ratio, 0.93 [95% CI, 0.70-1.24]) among participants who had 0 minor alleles at this single-nucleotide polymorphism. CONCLUSION: Known associations of low 25-hydroxyvitamin D with major health outcomes may vary according to common genetic differences in the vitamin D receptor.
Keywords: 25-Hydroxyvitamin D3 1-alpha-Hydroxylase; Aged; Chronic Disease; Cohort Studies; Female; Genetic Variation; Genotype; Hip Fractures; Humans; Low Density Lipoprotein Receptor-Related Protein-2; Male; Meta-Analysis as Topic; Myocardial Infarction; Neoplasms; Polymorphism, Single Nucleotide; Receptors, Calcitriol; Receptors, Cell Surface; Risk; Steroid Hydroxylases; Vitamin D; Vitamin D3 24-Hydroxylase

Genome-wide association studies identify CHRNA5/3 and HTR4 in the development of airflow obstruction. - Wilk, Jemma B; Shrine, Nick R G; Loehr, Laura R; Zhao, Jing Hua; Manichaikul, Ani; Lopez, Lorna M; Smith, Albert Vernon; Heckbert, Susan R; Smolonska, Joanna; Tang, Wenbo; Loth, Daan W; Curjuric, Ivan; et al. (Am J Respir Crit Care Med, 2012)
RATIONALE: Genome-wide association studies (GWAS) have identified loci influencing lung function, but fewer genes influencing chronic obstructive pulmonary disease (COPD) are known. OBJECTIVES: Perform meta-analyses of GWAS for airflow obstruction, a key pathophysiologic characteristic of COPD assessed by spirometry, in population-based cohorts examining all participants, ever smokers, never smokers, asthma-free participants, and more severe cases. METHODS: Fifteen cohorts were studied for discovery (3,368 affected; 29,507 unaffected), and a population-based family study and a meta-analysis of case-control studies were used for replication and regional follow-up (3,837 cases; 4,479 control subjects). Airflow obstruction was defined as FEV(1) and its ratio to FVC (FEV(1)/FVC) both less than their respective lower limits of normal as determined by published reference equations. MEASUREMENTS AND MAIN RESULTS: The discovery meta-analyses identified one region on chromosome 15q25.1 meeting genome-wide significance in ever smokers that includes AGPHD1, IREB2, and CHRNA5/CHRNA3 genes. The region was also modestly associated among never smokers. Gene expression studies confirmed the presence of CHRNA5/3 in lung, airway smooth muscle, and bronchial epithelial cells. A single-nucleotide polymorphism in HTR4, a gene previously related to FEV(1)/FVC, achieved genome-wide statistical significance in combined meta-analysis. Top single-nucleotide polymorphisms in ADAM19, RARB, PPAP2B, and ADAMTS19 were nominally replicated in the COPD meta-analysis. CONCLUSIONS: These results suggest an important role for the CHRNA5/3 region as a genetic risk factor for airflow obstruction that may be independent of smoking and implicate the HTR4 gene in the etiology of airflow obstruction.
Keywords: Aged; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Receptors, Nicotinic; Receptors, Serotonin, 5-HT4; Smoking; Vital Capacity

Genome-wide association study for circulating levels of PAI-1 provides novel insights into its regulation. - Huang, Jie; Sabater-Lleal, Maria; Asselbergs, Folkert W; Tregouet, David; Shin, So-Youn; Ding, Jingzhong; Baumert, Jens; Oudot-Mellakh, Tiphaine; Folkersen, Lasse; Johnson, Andrew D; Smith, Nicholas L; Williams, Scott M; et al. (Blood, 2012)
We conducted a genome-wide association study to identify novel associations between genetic variants and circulating plasminogen activator inhibitor-1 (PAI-1) concentration, and examined functional implications of variants and genes that were discovered. A discovery meta-analysis was performed in 19 599 subjects, followed by replication analysis of genome-wide significant (P < 5 × 10(-8)) single nucleotide polymorphisms (SNPs) in 10 796 independent samples. We further examined associations with type 2 diabetes and coronary artery disease, assessed the functional significance of the SNPs for gene expression in human tissues, and conducted RNA-silencing experiments for one novel association. We confirmed the association of the 4G/5G proxy SNP rs2227631 in the promoter region of SERPINE1 (7q22.1) and discovered genome-wide significant associations at 3 additional loci: chromosome 7q22.1 close to SERPINE1 (rs6976053, discovery P = 3.4 × 10(-10)); chromosome 11p15.2 within ARNTL (rs6486122, discovery P = 3.0 × 10(-8)); and chromosome 3p25.2 within PPARG (rs11128603, discovery P = 2.9 × 10(-8)). Replication was achieved for the 7q22.1 and 11p15.2 loci. There was nominal association with type 2 diabetes and coronary artery disease at ARNTL (P < .05). Functional studies identified MUC3 as a candidate gene for the second association signal on 7q22.1. In summary, SNPs in SERPINE1 and ARNTL and an SNP associated with the expression of MUC3 were robustly associated with circulating levels of PAI-1.
Keywords: Adaptor Proteins, Signal Transducing; ARNTL Transcription Factors; ATPases Associated with Diverse Cellular Activities; Cell Line; Cell Line, Tumor; Cohort Studies; Coronary Artery Disease; Diabetes Mellitus, Type 2; Gene Expression Profiling; Gene Expression Regulation; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; LIM Domain Proteins; Meta-Analysis as Topic; Monocytes; Mucin-3; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; PPAR gamma; Proteasome Endopeptidase Complex; RNA Interference; Transcription Factors

Genome-wide joint meta-analysis of SNP and SNP-by-smoking interaction identifies novel loci for pulmonary function. - Hancock, Dana B; Soler Artigas, Maria; Gharib, Sina A; Henry, Amanda; Manichaikul, Ani; Ramasamy, Adaikalavan; Loth, Daan W; Imboden, Medea; Koch, Beate; McArdle, Wendy L; Smith, Albert V; Smolonska, Joanna; et al. (PLoS Genet, 2012)
Genome-wide association studies have identified numerous genetic loci for spirometic measures of pulmonary function, forced expiratory volume in one second (FEV(1)), and its ratio to forced vital capacity (FEV(1)/FVC). Given that cigarette smoking adversely affects pulmonary function, we conducted genome-wide joint meta-analyses (JMA) of single nucleotide polymorphism (SNP) and SNP-by-smoking (ever-smoking or pack-years) associations on FEV(1) and FEV(1)/FVC across 19 studies (total N = 50,047). We identified three novel loci not previously associated with pulmonary function. SNPs in or near DNER (smallest P(JMA = )5.00×10(-11)), HLA-DQB1 and HLA-DQA2 (smallest P(JMA = )4.35×10(-9)), and KCNJ2 and SOX9 (smallest P(JMA = )1.28×10(-8)) were associated with FEV(1)/FVC or FEV(1) in meta-analysis models including SNP main effects, smoking main effects, and SNP-by-smoking (ever-smoking or pack-years) interaction. The HLA region has been widely implicated for autoimmune and lung phenotypes, unlike the other novel loci, which have not been widely implicated. We evaluated DNER, KCNJ2, and SOX9 and found them to be expressed in human lung tissue. DNER and SOX9 further showed evidence of differential expression in human airway epithelium in smokers compared to non-smokers. Our findings demonstrated that joint testing of SNP and SNP-by-environment interaction identified novel loci associated with complex traits that are missed when considering only the genetic main effects.
Keywords: Forced Expiratory Volume; Gene Expression; Genome, Human; Genome-Wide Association Study; HLA-DQ Antigens; HLA-DQ beta-Chains; Humans; Lung; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels, Inwardly Rectifying; Pulmonary Disease, Chronic Obstructive; Receptors, Cell Surface; Smoking; SOX9 Transcription Factor; Vital Capacity

Genome-wide meta-analysis identifies 56 bone mineral density loci and reveals 14 loci associated with risk of fracture. - Estrada, Karol; Styrkarsdottir, Unnur; Evangelou, Evangelos; Hsu, Yi-Hsiang; Duncan, Emma L; Ntzani, Evangelia E; Oei, Ling; Albagha, Omar M E; Amin, Najaf; Kemp, John P; Koller, Daniel L; Li, Guo; et al. (Nat Genet, 2012)
Bone mineral density (BMD) is the most widely used predictor of fracture risk. We performed the largest meta-analysis to date on lumbar spine and femoral neck BMD, including 17 genome-wide association studies and 32,961 individuals of European and east Asian ancestry. We tested the top BMD-associated markers for replication in 50,933 independent subjects and for association with risk of low-trauma fracture in 31,016 individuals with a history of fracture (cases) and 102,444 controls. We identified 56 loci (32 new) associated with BMD at genome-wide significance (P < 5 × 10(-8)). Several of these factors cluster within the RANK-RANKL-OPG, mesenchymal stem cell differentiation, endochondral ossification and Wnt signaling pathways. However, we also discovered loci that were localized to genes not known to have a role in bone biology. Fourteen BMD-associated loci were also associated with fracture risk (P < 5 × 10(-4), Bonferroni corrected), of which six reached P < 5 × 10(-8), including at 18p11.21 (FAM210A), 7q21.3 (SLC25A13), 11q13.2 (LRP5), 4q22.1 (MEPE), 2p16.2 (SPTBN1) and 10q21.1 (DKK1). These findings shed light on the genetic architecture and pathophysiological mechanisms underlying BMD variation and fracture susceptibility.
Keywords: Bone Density; Computational Biology; European Continental Ancestry Group; Extracellular Matrix Proteins; Female; Femur Neck; Fractures, Bone; Gene Expression Profiling; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Glycoproteins; Humans; Intercellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-5; Lumbar Vertebrae; Male; Mitochondrial Membrane Transport Proteins; Osteoporosis; Phosphoproteins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Spectrin

Genome-wide meta-analysis points to CTC1 and ZNF676 as genes regulating telomere homeostasis in humans. - Mangino, Massimo; Hwang, Shih-Jen; Spector, Timothy D; Hunt, Steven C; Kimura, Masayuki; Fitzpatrick, Annette L; Christiansen, Lene; Petersen, Inge; Elbers, Clara C; Harris, Tamara; Chen, Wei; Srinivasan, Sathanur R; et al. (Hum Mol Genet, 2012)
Leukocyte telomere length (LTL) is associated with a number of common age-related diseases and is a heritable trait. Previous genome-wide association studies (GWASs) identified two loci on chromosomes 3q26.2 (TERC) and 10q24.33 (OBFC1) that are associated with the inter-individual LTL variation. We performed a meta-analysis of 9190 individuals from six independent GWAS and validated our findings in 2226 individuals from four additional studies. We confirmed previously reported associations with OBFC1 (rs9419958 P = 9.1 × 10(-11)) and with the telomerase RNA component TERC (rs1317082, P = 1.1 × 10(-8)). We also identified two novel genomic regions associated with LTL variation that map near a conserved telomere maintenance complex component 1 (CTC1; rs3027234, P = 3.6 × 10(-8)) on chromosome17p13.1 and zinc finger protein 676 (ZNF676; rs412658, P = 3.3 × 10(-8)) on 19p12. The minor allele of rs3027234 was associated with both shorter LTL and lower expression of CTC1. Our findings are consistent with the recent observations that point mutations in CTC1 cause short telomeres in both Arabidopsis and humans affected by a rare Mendelian syndrome. Overall, our results provide novel insights into the genetic architecture of inter-individual LTL variation in the general population.
Keywords: Genome-Wide Association Study; Humans; Kruppel-Like Transcription Factors; Telomere; Telomere Homeostasis; Telomere-Binding Proteins

Hemodynamic fluid shear stress response genes and carotid intima-media thickness: a candidate gene association analysis in the cardiovascular health study. - Suchy-Dicey, Astrid M; Enquobahrie, Daniel A; Heckbert, Susan R; Rotter, Jerome I; Psaty, Bruce M; McKnight, Barbara (Int J Mol Epidemiol Genet, 2012)
OBJECTIVE: This study examined whether carotid artery intimal-medial thickness (cIMT) is associated with genetic variations (SNPs) in a hemodynamics-responsive gene pathway. METHODS: Subjects were Cardiovascular Health Study participants free of cardiovascular events at baseline (N=3388). Genotype was measured using Illumina 370CNV HumanHap chip. Carotid IMT was measured using ultrasound. Estimated mean differences in cIMT per additional minor allele for 366 SNPs in MAP2K5, MAPK7, MEF2A/C, and KLF2 were adjusted for sex, age, clinic, and medication use. SNP-SNP interactions were examined using logic regression for 71 tagSNPs. RESULTS: None of the associations was significant after correction for multiple comparisons; smallest P-value=0.065 for MAP2K5 and common cIMT. The best-performing logic regression tree combined two SNPs in MAP2K5-rs745212 and rs12905175- and common cIMT; this association was not significant, corrected P-value=0.062. CONCLUSION: There was not strong evidence of association between genetic variants in a hemodynamics-responsive gene pathway and atherosclerosis among older adults.

Impact of ancestry and common genetic variants on QT interval in African Americans. - Smith, J Gustav; Avery, Christy L; Evans, Daniel S; Nalls, Michael A; Meng, Yan A; Smith, Erin N; Palmer, Cameron; Tanaka, Toshiko; Mehra, Reena; Butler, Anne M; Young, Taylor; Buxbaum, Sarah G; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Ethnic differences in cardiac arrhythmia incidence have been reported, with a particularly high incidence of sudden cardiac death and low incidence of atrial fibrillation in individuals of African ancestry. We tested the hypotheses that African ancestry and common genetic variants are associated with prolonged duration of cardiac repolarization, a central pathophysiological determinant of arrhythmia, as measured by the electrocardiographic QT interval. METHODS AND RESULTS: First, individual estimates of African and European ancestry were inferred from genome-wide single-nucleotide polymorphism (SNP) data in 7 population-based cohorts of African Americans (n=12,097) and regressed on measured QT interval from ECGs. Second, imputation was performed for 2.8 million SNPs, and a genome-wide association study of QT interval was performed in 10 cohorts (n=13,105). There was no evidence of association between genetic ancestry and QT interval (P=0.94). Genome-wide significant associations (P<2.5 × 10(-8)) were identified with SNPs at 2 loci, upstream of the genes NOS1AP (rs12143842, P=2 × 10(-15)) and ATP1B1 (rs1320976, P=2 × 10(-10)). The most significant SNP in NOS1AP was the same as the strongest SNP previously associated with QT interval in individuals of European ancestry. Low probability values (P<10(-5)) were observed for SNPs at several other loci previously identified in genome-wide association studies in individuals of European ancestry, including KCNQ1, KCNH2, LITAF, and PLN. CONCLUSIONS: We observed no difference in duration of cardiac repolarization with global genetic indices of African American ancestry. In addition, our genome-wide association study extends the association of polymorphisms at several loci associated with repolarization in individuals of European ancestry to include individuals of African ancestry.
Keywords: Adult; African Americans; Aged; Electrocardiography; European Continental Ancestry Group; Female; Genealogy and Heraldry; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Large-scale association analyses identify new loci influencing glycemic traits and provide insight into the underlying biological pathways. - Scott, Robert A; Lagou, Vasiliki; Welch, Ryan P; Wheeler, Eleanor; Montasser, May E; Luan, Jian'an; Mägi, Reedik; Strawbridge, Rona J; Rehnberg, Emil; Gustafsson, Stefan; Kanoni, Stavroula; Rasmussen-Torvik, Laura J; et al. (Nat Genet, 2012)
Through genome-wide association meta-analyses of up to 133,010 individuals of European ancestry without diabetes, including individuals newly genotyped using the Metabochip, we have increased the number of confirmed loci influencing glycemic traits to 53, of which 33 also increase type 2 diabetes risk (q < 0.05). Loci influencing fasting insulin concentration showed association with lipid levels and fat distribution, suggesting impact on insulin resistance. Gene-based analyses identified further biologically plausible loci, suggesting that additional loci beyond those reaching genome-wide significance are likely to represent real associations. This conclusion is supported by an excess of directionally consistent and nominally significant signals between discovery and follow-up studies. Functional analysis of these newly discovered loci will further improve our understanding of glycemic control.
Keywords: Adult; Animals; Blood Glucose; Fasting; Female; Gene Frequency; Genome-Wide Association Study; Humans; Insulin; Male; Metabolic Networks and Pathways; Mice; Osmolar Concentration; Quantitative Trait Loci

Lipid-related markers and cardiovascular disease prediction. - Di Angelantonio, Emanuele; Gao, Pei; Pennells, Lisa; Kaptoge, Stephen; Caslake, Muriel; Thompson, Alexander; Butterworth, Adam S; Sarwar, Nadeem; Wormser, David; Saleheen, Danish; Ballantyne, Christie M; Psaty, Bruce M; et al. (JAMA, 2012)
CONTEXT: The value of assessing various emerging lipid-related markers for prediction of first cardiovascular events is debated. OBJECTIVE: To determine whether adding information on apolipoprotein B and apolipoprotein A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 to total cholesterol and high-density lipoprotein cholesterol (HDL-C) improves cardiovascular disease (CVD) risk prediction. DESIGN, SETTING, AND PARTICIPANTS: Individual records were available for 165,544 participants without baseline CVD in 37 prospective cohorts (calendar years of recruitment: 1968-2007) with up to 15,126 incident fatal or nonfatal CVD outcomes (10,132 CHD and 4994 stroke outcomes) during a median follow-up of 10.4 years (interquartile range, 7.6-14 years). MAIN OUTCOME MEASURES: Discrimination of CVD outcomes and reclassification of participants across predicted 10-year risk categories of low (<10%), intermediate (10%-<20%), and high (≥20%) risk. RESULTS: The addition of information on various lipid-related markers to total cholesterol, HDL-C, and other conventional risk factors yielded improvement in the model's discrimination: C-index change, 0.0006 (95% CI, 0.0002-0.0009) for the combination of apolipoprotein B and A-I; 0.0016 (95% CI, 0.0009-0.0023) for lipoprotein(a); and 0.0018 (95% CI, 0.0010-0.0026) for lipoprotein-associated phospholipase A2 mass. Net reclassification improvements were less than 1% with the addition of each of these markers to risk scores containing conventional risk factors. We estimated that for 100,000 adults aged 40 years or older, 15,436 would be initially classified at intermediate risk using conventional risk factors alone. Additional testing with a combination of apolipoprotein B and A-I would reclassify 1.1%; lipoprotein(a), 4.1%; and lipoprotein-associated phospholipase A2 mass, 2.7% of people to a 20% or higher predicted CVD risk category and, therefore, in need of statin treatment under Adult Treatment Panel III guidelines. CONCLUSION: In a study of individuals without known CVD, the addition of information on the combination of apolipoprotein B and A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 mass to risk scores containing total cholesterol and HDL-C led to slight improvement in CVD prediction.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cholesterol, HDL; Cohort Studies; Female; Humans; Lipoproteins; Male; Middle Aged; Risk Assessment

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Polymerase gamma; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies six new susceptibility loci for atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Albert, Christine M; Glazer, Nicole L; Ritchie, Marylyn D; Smith, Albert V; Arking, Dan E; Müller-Nurasyid, Martina; Krijthe, Bouwe P; Lubitz, Steven A; Bis, Joshua C; Chung, Mina K; et al. (Nat Genet, 2012)
Atrial fibrillation is a highly prevalent arrhythmia and a major risk factor for stroke, heart failure and death. We conducted a genome-wide association study (GWAS) in individuals of European ancestry, including 6,707 with and 52,426 without atrial fibrillation. Six new atrial fibrillation susceptibility loci were identified and replicated in an additional sample of individuals of European ancestry, including 5,381 subjects with and 10,030 subjects without atrial fibrillation (P < 5 × 10(-8)). Four of the loci identified in Europeans were further replicated in silico in a GWAS of Japanese individuals, including 843 individuals with and 3,350 individuals without atrial fibrillation. The identified loci implicate candidate genes that encode transcription factors related to cardiopulmonary development, cardiac-expressed ion channels and cell signaling molecules.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Child; Child, Preschool; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Infant, Newborn; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Multi-ethnic analysis of lipid-associated loci: the NHLBI CARe project. - Musunuru, Kiran; Romaine, Simon P R; Lettre, Guillaume; Wilson, James G; Volcik, Kelly A; Tsai, Michael Y; Taylor, Herman A; Schreiner, Pamela J; Rotter, Jerome I; Rich, Stephen S; Redline, Susan; Psaty, Bruce M; et al. (PLoS One, 2012)
BACKGROUND: Whereas it is well established that plasma lipid levels have substantial heritability within populations, it remains unclear how many of the genetic determinants reported in previous studies (largely performed in European American cohorts) are relevant in different ethnicities. METHODOLOGY/PRINCIPAL FINDINGS: We tested a set of ∼50,000 polymorphisms from ∼2,000 candidate genes and genetic loci from genome-wide association studies (GWAS) for association with low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) in 25,000 European Americans and 9,000 African Americans in the National Heart, Lung, and Blood Institute (NHLBI) Candidate Gene Association Resource (CARe). We replicated associations for a number of genes in one or both ethnicities and identified a novel lipid-associated variant in a locus harboring ICAM1. We compared the architecture of genetic loci associated with lipids in both African Americans and European Americans and found that the same genes were relevant across ethnic groups but the specific associated variants at each gene often differed. CONCLUSIONS/SIGNIFICANCE: We identify or provide further evidence for a number of genetic determinants of plasma lipid levels through population association studies. In many loci the determinants appear to differ substantially between African Americans and European Americans.
Keywords: African Americans; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Genetic Association Studies; Genetic Loci; Humans; Polymorphism, Single Nucleotide; Triglycerides

Novel loci associated with PR interval in a genome-wide association study of 10 African American cohorts. - Butler, Anne M; Yin, Xiaoyan; Evans, Daniel S; Nalls, Michael A; Smith, Erin N; Tanaka, Toshiko; Li, Guo; Buxbaum, Sarah G; Whitsel, Eric A; Alonso, Alvaro; Arking, Dan E; Benjamin, Emelia J; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: The PR interval, as measured by the resting, standard 12-lead ECG, reflects the duration of atrial/atrioventricular nodal depolarization. Substantial evidence exists for a genetic contribution to PR, including genome-wide association studies that have identified common genetic variants at 9 loci influencing PR in populations of European and Asian descent. However, few studies have examined loci associated with PR in African Americans. METHODS AND RESULTS: We present results from the largest genome-wide association study to date of PR in 13 415 adults of African descent from 10 cohorts. We tested for association between PR (ms) and ≈2.8 million genotyped and imputed single-nucleotide polymorphisms. Imputation was performed using HapMap 2 YRI and CEU panels. Study-specific results, adjusted for global ancestry and clinical correlates of PR, were meta-analyzed using the inverse variance method. Variation in genome-wide test statistic distributions was noted within studies (λ range: 0.9-1.1), although not after genomic control correction was applied to the overall meta-analysis (λ: 1.008). In addition to generalizing previously reported associations with MEIS1, SCN5A, ARHGAP24, CAV1, and TBX5 to African American populations at the genome-wide significance level (P<5.0 × 10(-8)), we also identified a novel locus: ITGA9, located in a region previously implicated in SCN5A expression. The 3p21 region harboring SCN5A also contained 2 additional independent secondary signals influencing PR (P<5.0 × 10(-8)). CONCLUSIONS: This study demonstrates the ability to map novel loci in African Americans as well as the generalizability of loci associated with PR across populations of African, European, and Asian descent.
Keywords: Adult; African Americans; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide

Novel loci for adiponectin levels and their influence on type 2 diabetes and metabolic traits: a multi-ethnic meta-analysis of 45,891 individuals. - Dastani, Zari; Hivert, Marie-France; Timpson, Nicholas; Perry, John R B; Yuan, Xin; Scott, Robert A; Henneman, Peter; Heid, Iris M; Kizer, Jorge R; Lyytikäinen, Leo-Pekka; Fuchsberger, Christian; Tanaka, Toshiko; et al. (PLoS Genet, 2012)
Circulating levels of adiponectin, a hormone produced predominantly by adipocytes, are highly heritable and are inversely associated with type 2 diabetes mellitus (T2D) and other metabolic traits. We conducted a meta-analysis of genome-wide association studies in 39,883 individuals of European ancestry to identify genes associated with metabolic disease. We identified 8 novel loci associated with adiponectin levels and confirmed 2 previously reported loci (P = 4.5×10(-8)-1.2×10(-43)). Using a novel method to combine data across ethnicities (N = 4,232 African Americans, N = 1,776 Asians, and N = 29,347 Europeans), we identified two additional novel loci. Expression analyses of 436 human adipocyte samples revealed that mRNA levels of 18 genes at candidate regions were associated with adiponectin concentrations after accounting for multiple testing (p<3×10(-4)). We next developed a multi-SNP genotypic risk score to test the association of adiponectin decreasing risk alleles on metabolic traits and diseases using consortia-level meta-analytic data. This risk score was associated with increased risk of T2D (p = 4.3×10(-3), n = 22,044), increased triglycerides (p = 2.6×10(-14), n = 93,440), increased waist-to-hip ratio (p = 1.8×10(-5), n = 77,167), increased glucose two hours post oral glucose tolerance testing (p = 4.4×10(-3), n = 15,234), increased fasting insulin (p = 0.015, n = 48,238), but with lower in HDL-cholesterol concentrations (p = 4.5×10(-13), n = 96,748) and decreased BMI (p = 1.4×10(-4), n = 121,335). These findings identify novel genetic determinants of adiponectin levels, which, taken together, influence risk of T2D and markers of insulin resistance.
Keywords: Adiponectin; African Americans; Asian Continental Ancestry Group; Cholesterol, HDL; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Tolerance Test; Humans; Insulin Resistance; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Risk of intraparenchymal hemorrhage with magnetic resonance imaging-defined leukoaraiosis and brain infarcts. - Folsom, Aaron R; Yatsuya, Hiroshi; Mosley, Thomas H; Psaty, Bruce M; Longstreth, W T (Ann Neurol, 2012)
OBJECTIVE: To determine whether the burden of leukoaraiosis and the number of brain infarcts, defined by magnetic resonance imaging (MRI), are prospectively and independently associated with intraparenchymal hemorrhage (IPH) incidence in a pooled population-based study. METHODS: Among 4,872 participants initially free of clinical stroke in the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study, we assessed white matter grade (range, 0-9), reflecting increasing leukoaraiosis, and brain infarcts using MRI. Over a median of 13 years of follow-up, 71 incident, spontaneous IPH events occurred. RESULTS: After adjustment for other IPH risk factors, the hazard ratios (95% confidence intervals) across white matter grades 0 to 1, 2, 3, and 4 to 9 were 1.00, 1.68 (0.86-3.30), 3.52 (1.80-6.89), and 3.96 (1.90-8.27), respectively (p for trend <0.0001). These hazard ratios were weakened only modestly (p for trend = 0.0003) with adjustment for MRI-defined brain infarcts. The IPH hazard ratios for 0, 1, 2, or ≥3 MRI-defined brain infarcts were 1.00, 1.97 (1.10-3.54), 2.00 (0.83-4.78), and 3.12 (1.31-7.43) (p for trend = 0.002), but these were substantially attenuated when adjusted for white matter grade (p for trend = 0.049). INTERPRETATION: Greater MRI-defined burden of leukoaraiosis is a risk factor for spontaneous IPH. Spontaneous IPH should be added to the growing list of potential poor outcomes in people with leukoaraiosis.
Keywords: Cerebral Infarction; Cohort Studies; Female; Humans; Incidence; Intracranial Hemorrhages; Leukoaraiosis; Magnetic Resonance Imaging; Male; Middle Aged; Risk Factors

Telomere-associated polymorphisms correlate with cardiovascular disease mortality in Caucasian women: the Cardiovascular Health Study. - Burnett-Hartman, Andrea N; Fitzpatrick, Annette L; Kronmal, Richard A; Psaty, Bruce M; Jenny, Nancy S; Bis, Josh C; Tracy, Russ P; Kimura, Masayuki; Aviv, Abraham (Mech Ageing Dev, 2012)
Leukocyte telomere length (LTL) is linked to cardiovascular disease (CVD); however, it is unclear if LTL has an etiologic role in CVD. To gain insight into the LTL and CVD relationship, a cohort study of CVD mortality and single nucleotide polymorphisms (SNPs) in OBFC1 and TERC, genes related to LTL, was conducted among 3271 Caucasian participants ages ≥65 years enrolled 1989-1990 in the Cardiovascular Health Study. Leukocyte DNA was genotyped for SNPs in OBFC1 (rs4387287 and rs9419958) and TERC (rs3772190) that were previously associated with LTL through genome-wide association studies. Cox regression was used to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs). The OBFC1 SNPs were in linkage disequilibrium (r(2)=0.99), and both SNPs were similarly associated with CVD mortality in women. For women, there was a decreased risk of CVD death associated with the minor allele (rs4387287), HR=0.7; 95% CI: 0.5-0.9 (CC vs. AC) and HR=0.5; 95% CI: 0.20-1.4 (CC vs. AA) (P-trend <0.01). For men there was no association, HR=1.0; 95% CI: 0.7-1.3 (CC vs. AC) and HR=1.7; 95% CI: 0.8-3.6 (CC vs. AA) (P-trend=0.64). These findings support the hypothesis that telomere biology and associated genes may play a role in CVD-related death, particularly among women.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Humans; Leukocytes; Male; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Risk; RNA; Sex Factors; Telomerase; Telomere

Transforming growth factor beta-1 and incidence of heart failure in older adults: the Cardiovascular Health Study. - Glazer, Nicole L; Macy, Elizabeth M; Lumley, Thomas; Smith, Nicholas L; Reiner, Alex P; Psaty, Bruce M; King, George L; Tracy, Russell P; Siscovick, David S (Cytokine, 2012)
CONTEXT: Transforming growth factor-beta1 (TGF-B1) is a highly pleiotropic cytokine whose functions include a central role in the induction of fibrosis. OBJECTIVE: To investigate the hypothesis that elevated plasma levels of TGF-B1 are positively associated with incident heart failure (HF). PARTICIPANTS AND METHODS: The hypotheses were tested using a two-phase case-control study design, ancillary to the Cardiovascular Health Study - a longitudinal, population-based cohort study. Cases were defined as having an incident HF event after their 1992-1993 exam and controls were free of HF at follow-up. TGF-B1 was measured using plasma collected in 1992-1993 and data from 89 cases and 128 controls were used for analysis. The association between TGF-B1 and risk of HF was evaluated using the weighted likelihood method, and odds ratios (OR) for risk of HF were calculated for TGF-B1 as a continuous linear variable and across quartiles of TGF-B1. RESULTS: The OR for HF was 1.88 (95% confidence intervals [CI] 1.26-2.81) for each nanogram increase in TGF-B1, and the OR for the highest quartile (compared to the lowest) of TGF-B1 was 5.79 (95% CI 1.65-20.34), after adjustment for age, sex, C-reactive protein, platelet count and digoxin use. Further adjustment with other covariates did not change the results. CONCLUSIONS: Higher levels of plasma TGF-B1 were associated with an increased risk of incident heart failure among older adults. However, further study is needed in larger samples to confirm these findings.
Keywords: Aged; Case-Control Studies; Health; Heart Failure; Humans; Incidence; Transforming Growth Factor beta1; United States

Association of genome-wide variation with highly sensitive cardiac troponin-T levels in European Americans and Blacks: a meta-analysis from atherosclerosis risk in communities and cardiovascular health studies. - Yu, Bing; Barbalic, Maja; Brautbar, Ariel; Nambi, Vijay; Hoogeveen, Ron C; Tang, Weihong; Mosley, Thomas H; Rotter, Jerome I; deFilippi, Christopher R; O'Donnell, Christopher J; Kathiresan, Sekar; Rice, Ken; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: High levels of cardiac troponin T, measured by a highly sensitive assay (hs-cTnT), are strongly associated with incident coronary heart disease and heart failure. To date, no large-scale genome-wide association study of hs-cTnT has been reported. We sought to identify novel genetic variants that are associated with hs-cTnT levels. METHODS AND RESULTS: We performed a genome-wide association in 9491 European Americans and 2053 blacks free of coronary heart disease and heart failure from 2 prospective cohorts: the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Genome-wide association studies were conducted in each study and race stratum. Fixed-effect meta-analyses combined the results of linear regression from 2 cohorts within each race stratum and then across race strata to produce overall estimates and probability values. The meta-analysis identified a significant association at chromosome 8q13 (rs10091374; P=9.06×10(-9)) near the nuclear receptor coactivator 2 (NCOA2) gene. Overexpression of NCOA2 can be detected in myoblasts. An additional analysis using logistic regression and the clinically motivated 99th percentile cut point detected a significant association at 1q32 (rs12564445; P=4.73×10(-8)) in the gene TNNT2, which encodes the cardiac troponin T protein itself. The hs-cTnT-associated single-nucleotide polymorphisms were not associated with coronary heart disease in a large case-control study, but rs12564445 was significantly associated with incident heart failure in Atherosclerosis Risk in Communities Study European Americans (hazard ratio=1.16; P=0.004). CONCLUSIONS: We identified 2 loci, near NCOA2 and in the TNNT2 gene, at which variation was significantly associated with hs-cTnT levels. Further use of the new assay should enable replication of these results.
Keywords: African Continental Ancestry Group; Atherosclerosis; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Nuclear Receptor Coactivator 2; Polymorphism, Single Nucleotide; Prospective Studies; Residence Characteristics; Risk Factors; Troponin T

Associations of plasma phospholipid and dietary alpha linolenic acid with incident atrial fibrillation in older adults: the Cardiovascular Health Study. - Fretts, Amanda M; Mozaffarian, Dariush; Siscovick, David S; Heckbert, Susan R; McKnight, Barbara; King, Irena B; Rimm, Eric B; Psaty, Bruce M; Sacks, Frank M; Song, Xiaoling; Spiegelman, Donna; Lemaitre, Rozenn N (J Am Heart Assoc, 2013)
BACKGROUND: Few studies have examined the relationship of α-linolenic acid (ALA 18:3n-3), an intermediate-chain essential n-3 polyunsaturated fatty acid derived from plants and vegetable oils, with incident atrial fibrillation (AF). METHODS AND RESULTS: The study population included participants from the Cardiovascular Health Study, a community-based longitudinal cohort of adults aged 65 or older, free of prevalent coronary heart disease and atrial fibrillation. We assessed the associations of plasma phospholipid and dietary ALA with incident AF using Cox regression. The biomarker analysis comprised a total of 2899 participants, and the dietary analysis comprised 4337 participants. We found no association of plasma phospholipid ALA and incident AF. Comparing each of the second, third, and fourth quartiles to the lowest quartile, the hazard ratios for AF were 1.11 (95% CI, 0.90 to 1.37), 1.09 (95% CI, 0.88 to 1.35), and 0.92 (95% CI, 0.74 to 1.15), after adjustment for age, sex, race, clinic, education, smoking, alcohol, body mass index, waist circumference, diabetes, heart failure, stroke, treated hypertension, and physical activity (P trend=0.48). When dietary ALA was considered the exposure of interest, results were similar. CONCLUSIONS: Results from this prospective cohort study of older adults indicate no association of plasma phospholipid or dietary ALA and incident AF.
Keywords: Age Factors; Aged; Aged, 80 and over; alpha-Linolenic Acid; Atrial Fibrillation; Biomarkers; Diet; Female; Humans; Incidence; Linear Models; Longitudinal Studies; Male; Nutritional Status; Phospholipids; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Atrial ectopy as a predictor of incident atrial fibrillation: a cohort study. - Dewland, Thomas A; Vittinghoff, Eric; Mandyam, Mala C; Heckbert, Susan R; Siscovick, David S; Stein, Phyllis K; Psaty, Bruce M; Sotoodehnia, Nona; Gottdiener, John S; Marcus, Gregory M (Ann Intern Med, 2013)
BACKGROUND: Atrial fibrillation (AF) prediction models have unclear clinical utility given the absence of AF prevention therapies and the immutability of many risk factors. Premature atrial contractions (PACs) play a critical role in AF pathogenesis and may be modifiable. OBJECTIVE: To investigate whether PAC count improves model performance for AF risk. DESIGN: Prospective cohort study. SETTING: 4 U.S. communities. PATIENTS: A random subset of 1260 adults without prevalent AF enrolled in the Cardiovascular Health Study between 1989 and 1990. MEASUREMENTS: The PAC count was quantified by 24-hour electrocardiography. Participants were followed for the diagnosis of incident AF or death. The Framingham AF risk algorithm was used as the comparator prediction model. RESULTS: In adjusted analyses, doubling the hourly PAC count was associated with a significant increase in AF risk (hazard ratio, 1.17 [95% CI, 1.13 to 1.22]; P < 0.001) and overall mortality (hazard ratio, 1.06 [CI, 1.03 to 1.09]; P < 0.001). Compared with the Framingham model, PAC count alone resulted in similar AF risk discrimination at 5 and 10 years of follow-up and superior risk discrimination at 15 years. The addition of PAC count to the Framingham model resulted in significant 10-year AF risk discrimination improvement (c-statistic, 0.65 vs. 0.72; P < 0.001), net reclassification improvement (23.2% [CI, 12.8% to 33.6%]; P < 0.001), and integrated discrimination improvement (5.6% [CI, 4.2% to 7.0%]; P < 0.001). The specificity for predicting AF at 15 years exceeded 90% for PAC counts more than 32 beats/h. LIMITATION: This study does not establish a causal link between PACs and AF. CONCLUSION: The addition of PAC count to a validated AF risk algorithm provides superior AF risk discrimination and significantly improves risk reclassification. Further study is needed to determine whether PAC modification can prospectively reduce AF risk. PRIMARY FUNDING SOURCE: American Heart Association, Joseph Drown Foundation, and National Institutes of Health.
Keywords: Aged; Atrial Fibrillation; Atrial Function; Cause of Death; Electrocardiography; Female; Humans; Male; Models, Statistical; Myocardial Contraction; Prospective Studies; Risk Assessment

Atrial fibrillation and cognitive decline: a longitudinal cohort study. - Thacker, Evan L; McKnight, Barbara; Psaty, Bruce M; Longstreth, W T; Sitlani, Colleen M; Dublin, Sascha; Arnold, Alice M; Fitzpatrick, Annette L; Gottesman, Rebecca F; Heckbert, Susan R (Neurology, 2013)
OBJECTIVE: We sought to determine whether in the absence of clinical stroke, people with atrial fibrillation experience faster cognitive decline than people without atrial fibrillation. METHODS: We conducted a longitudinal analysis in the Cardiovascular Health Study, a community-based study of 5,888 men and women aged 65 years and older, enrolled in 1989/1990 or 1992/1993. Participants did not have atrial fibrillation or a history of stroke at baseline. Participants were censored when they experienced incident clinical stroke. Incident atrial fibrillation was identified by hospital discharge diagnosis codes and annual study ECGs. The main outcome was rate of decline in mean scores on the 100-point Modified Mini-Mental State Examination (3MSE), administered annually up to 9 times. RESULTS: Analyses included 5,150 participants, of whom 552 (10.7%) developed incident atrial fibrillation during a mean of 7 years of follow-up. Mean 3MSE scores declined faster after incident atrial fibrillation compared with no prior atrial fibrillation. For example, the predicted 5-year decline in mean 3MSE score from age 80 to age 85 was -6.4 points (95% confidence interval [CI]: -7.0, -5.9) for participants without a history of atrial fibrillation, but was -10.3 points (95% CI: -11.8, -8.9) for participants experiencing incident atrial fibrillation at age 80, a 5-year difference of -3.9 points (95% CI: -5.3, -2.5). CONCLUSIONS: In the absence of clinical stroke, people with incident atrial fibrillation are likely to reach thresholds of cognitive impairment or dementia at earlier ages than people with no history of atrial fibrillation.
Keywords: Age Factors; Aged; Aged, 80 and over; Atrial Fibrillation; Cognition Disorders; Comorbidity; Female; Humans; Incidence; Longitudinal Studies; Luria-Nebraska Neuropsychological Battery; Male; Predictive Value of Tests

Best practices and joint calling of the HumanExome BeadChip: the CHARGE Consortium. - Grove, Megan L; Yu, Bing; Cochran, Barbara J; Haritunians, Talin; Bis, Joshua C; Taylor, Kent D; Hansen, Mark; Borecki, Ingrid B; Cupples, L Adrienne; Fornage, Myriam; Gudnason, Vilmundur; Harris, Tamara B; et al. (PLoS One, 2013)
Genotyping arrays are a cost effective approach when typing previously-identified genetic polymorphisms in large numbers of samples. One limitation of genotyping arrays with rare variants (e.g., minor allele frequency [MAF] <0.01) is the difficulty that automated clustering algorithms have to accurately detect and assign genotype calls. Combining intensity data from large numbers of samples may increase the ability to accurately call the genotypes of rare variants. Approximately 62,000 ethnically diverse samples from eleven Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium cohorts were genotyped with the Illumina HumanExome BeadChip across seven genotyping centers. The raw data files for the samples were assembled into a single project for joint calling. To assess the quality of the joint calling, concordance of genotypes in a subset of individuals having both exome chip and exome sequence data was analyzed. After exclusion of low performing SNPs on the exome chip and non-overlap of SNPs derived from sequence data, genotypes of 185,119 variants (11,356 were monomorphic) were compared in 530 individuals that had whole exome sequence data. A total of 98,113,070 pairs of genotypes were tested and 99.77% were concordant, 0.14% had missing data, and 0.09% were discordant. We report that joint calling allows the ability to accurately genotype rare variation using array technology when large sample sizes are available and best practices are followed. The cluster file from this experiment is available at www.chargeconsortium.com/main/exomechip.
Keywords: Aging; Alleles; Cluster Analysis; Cohort Studies; Continental Population Groups; Exome; Female; Gene Frequency; Genomics; Genotype; Heart; Humans; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Sample Size; Self Report; Sequence Analysis, DNA

Blood pressure variability and the risk of all-cause mortality, incident myocardial infarction, and incident stroke in the cardiovascular health study. - Suchy-Dicey, Astrid M; Wallace, Erin R; Mitchell, S V Elkind; Aguilar, Maria; Gottesman, Rebecca F; Rice, Kenneth; Kronmal, Richard; Psaty, Bruce M; Longstreth, W T (Am J Hypertens, 2013)
BACKGROUND: Recent reports have linked variability in visit-to-visit systolic blood pressure (SBP) to risk of mortality and stroke, independent of the effect of mean SBP level. This study aimed to evaluate whether variability in SBP is associated with all-cause mortality, incident myocardial infarction (MI), and incident stroke, independent of mean SBP or trends in SBP levels over time. METHODS: The Cardiovascular Health Study is a longitudinal cohort study of vascular risk factors and disease in the elderly. Participants who attended their first 5 annual clinic visits and experienced no event before the 5th visit were eligible (n = 3,852). Primary analyses were restricted to participants not using antihypertensive medications throughout the first 5 clinic visits (n = 1,642). Intraindividual SBP variables were defined using each participant's 5-visit blood pressure measures. Cox proportional hazards models estimated adjusted hazard ratios (HRs) per SD increase in intraindividual SBP variability, adjusted for intraindividual SBP mean and change over time. RESULTS: Over a mean follow-up of 9.9 years, there were 844 deaths, 203 MIs, and 195 strokes. Intraindividual SBP variability was significantly associated with increased risk of mortality (HR = 1.13; 95% confidence interval (CI) = 1.05-1.21) and of incident MI (HR = 1.20; 95%CI = 1.06-1.36), independent of the effect from adjustment factors. Intraindividual SBP variability was not associated with risk of stroke (HR = 1.03; 95% CI = 0.89-1.21). CONCLUSIONS: Long-term visit-to-visit SBP variability was independently associated with a higher risk of subsequent mortality and MI but not stroke. More research is needed to determine the relationship of BP variability with cardiovascular risk and the clinical implications.
Keywords: Aged; Blood Pressure; Cohort Studies; Female; Humans; Incidence; Longitudinal Studies; Male; Mortality; Myocardial Infarction; Risk; Stroke; United States

The Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium as a model of collaborative science. - Psaty, Bruce M; Sitlani, Colleen (Epidemiology, 2013)
Keywords: Aging; Cohort Studies; Cooperative Behavior; Genome-Wide Association Study; Heart Failure; Humans; Incidence; Multicenter Studies as Topic; Myocardial Infarction; Research Support as Topic; Stroke; United States

Common FABP4 genetic variants and plasma levels of fatty acid binding protein 4 in older adults. - Mukamal, Kenneth J; Wilk, Jemma B; Biggs, Mary L; Jensen, Majken K; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Zieman, Susan J; Mozaffarian, Dariush; Psaty, Bruce M; Siscovick, David S; Djoussé, Luc (Lipids, 2013)
We examined common variants in the fatty acid binding protein 4 gene (FABP4) and plasma levels of FABP4 in adults aged 65 and older from the Cardiovascular Health Study. We genotyped rs16909187, rs1054135, rs16909192, rs10808846, rs7018409, rs2290201, and rs6992708 and measured circulating FABP4 levels among 3190 European Americans and 660 African Americans. Among European Americans, the minor alleles of six single nucleotide polymorphisms (SNP) were associated with lower FABP4 levels (all p ≤ 0.01). Among African Americans, the SNP with the lowest minor allele frequency was associated with lower FABP4 levels (p = 0.015). The C-A haplotype of rs16909192 and rs2290201 was associated with lower FABP4 levels in both European Americans (frequency = 16 %; p = 0.001) and African Americans (frequency = 8 %; p = 0.04). The haplotype combined a SNP in the first intron with one in the 3'untranslated region. However, the alleles associated with lower FABP4 levels were associated with higher fasting glucose in meta-analyses from the MAGIC consortium. These results demonstrate associations of common SNP and haplotypes in the FABP4 gene with lower plasma FABP4 but higher fasting glucose levels.
Keywords: African Americans; Aged; Aged, 80 and over; Blood Glucose; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Fatty Acid-Binding Proteins; Female; Gene Frequency; Genetic Association Studies; Haplotypes; Humans; Insulin; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide

Common genetic loci influencing plasma homocysteine concentrations and their effect on risk of coronary artery disease. - van Meurs, Joyce B J; Paré, Guillaume; Schwartz, Stephen M; Hazra, Aditi; Tanaka, Toshiko; Vermeulen, Sita H; Cotlarciuc, Ioana; Yuan, Xin; Mälarstig, Anders; Bandinelli, Stefania; Bis, Joshua C; Blom, Henk; et al. (Am J Clin Nutr, 2013)
BACKGROUND: The strong observational association between total homocysteine (tHcy) concentrations and risk of coronary artery disease (CAD) and the null associations in the homocysteine-lowering trials have prompted the need to identify genetic variants associated with homocysteine concentrations and risk of CAD. OBJECTIVE: We tested whether common genetic polymorphisms associated with variation in tHcy are also associated with CAD. DESIGN: We conducted a meta-analysis of genome-wide association studies (GWAS) on tHcy concentrations in 44,147 individuals of European descent. Polymorphisms associated with tHcy (P < 10(⁻⁸) were tested for association with CAD in 31,400 cases and 92,927 controls. RESULTS: Common variants at 13 loci, explaining 5.9% of the variation in tHcy, were associated with tHcy concentrations, including 6 novel loci in or near MMACHC (2.1 × 10⁻⁹), SLC17A3 (1.0 × 10⁻⁸), GTPB10 (1.7 × 10⁻⁸), CUBN (7.5 × 10⁻¹⁰), HNF1A (1.2 × 10⁻¹²)), and FUT2 (6.6 × 10⁻⁹), and variants previously reported at or near the MTHFR, MTR, CPS1, MUT, NOX4, DPEP1, and CBS genes. Individuals within the highest 10% of the genotype risk score (GRS) had 3-μmol/L higher mean tHcy concentrations than did those within the lowest 10% of the GRS (P = 1 × 10⁻³⁶). The GRS was not associated with risk of CAD (OR: 1.01; 95% CI: 0.98, 1.04; P = 0.49). CONCLUSIONS: We identified several novel loci that influence plasma tHcy concentrations. Overall, common genetic variants that influence plasma tHcy concentrations are not associated with risk of CAD in white populations, which further refutes the causal relevance of moderately elevated tHcy concentrations and tHcy-related pathways for CAD.
Keywords: Coronary Artery Disease; Genes; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homocysteine; Humans; Polymorphism, Genetic; Risk Factors

Common variants associated with plasma triglycerides and risk for coronary artery disease. - Do, Ron; Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Gao, Chi; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; et al. (Nat Genet, 2013)
Triglycerides are transported in plasma by specific triglyceride-rich lipoproteins; in epidemiological studies, increased triglyceride levels correlate with higher risk for coronary artery disease (CAD). However, it is unclear whether this association reflects causal processes. We used 185 common variants recently mapped for plasma lipids (P < 5 × 10(-8) for each) to examine the role of triglycerides in risk for CAD. First, we highlight loci associated with both low-density lipoprotein cholesterol (LDL-C) and triglyceride levels, and we show that the direction and magnitude of the associations with both traits are factors in determining CAD risk. Second, we consider loci with only a strong association with triglycerides and show that these loci are also associated with CAD. Finally, in a model accounting for effects on LDL-C and/or high-density lipoprotein cholesterol (HDL-C) levels, the strength of a polymorphism's effect on triglyceride levels is correlated with the magnitude of its effect on CAD risk. These results suggest that triglyceride-rich lipoproteins causally influence risk for CAD.
Keywords: Biological Transport; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors; Triglycerides

Discovery and refinement of loci associated with lipid levels. - Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; Beckmann, Jacques S; Bragg-Gresham, Jennifer L; et al. (Nat Genet, 2013)
Levels of low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides and total cholesterol are heritable, modifiable risk factors for coronary artery disease. To identify new loci and refine known loci influencing these lipids, we examined 188,577 individuals using genome-wide and custom genotyping arrays. We identify and annotate 157 loci associated with lipid levels at P < 5 × 10(-8), including 62 loci not previously associated with lipid levels in humans. Using dense genotyping in individuals of European, East Asian, South Asian and African ancestry, we narrow association signals in 12 loci. We find that loci associated with blood lipid levels are often associated with cardiovascular and metabolic traits, including coronary artery disease, type 2 diabetes, blood pressure, waist-hip ratio and body mass index. Our results demonstrate the value of using genetic data from individuals of diverse ancestry and provide insights into the biological mechanisms regulating blood lipids to guide future genetic, biological and therapeutic research.
Keywords: African Continental Ancestry Group; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Lipids; Triglycerides

Genetic loci for retinal arteriolar microcirculation. - Sim, Xueling; Jensen, Richard A; Ikram, M Kamran; Cotch, Mary Frances; Li, Xiaohui; Macgregor, Stuart; Xie, Jing; Smith, Albert Vernon; Boerwinkle, Eric; Mitchell, Paul; Klein, Ronald; Klein, Barbara E K; et al. (PLoS One, 2013)
Narrow arterioles in the retina have been shown to predict hypertension as well as other vascular diseases, likely through an increase in the peripheral resistance of the microcirculatory flow. In this study, we performed a genome-wide association study in 18,722 unrelated individuals of European ancestry from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium and the Blue Mountain Eye Study, to identify genetic determinants associated with variations in retinal arteriolar caliber. Retinal vascular calibers were measured on digitized retinal photographs using a standardized protocol. One variant (rs2194025 on chromosome 5q14 near the myocyte enhancer factor 2C MEF2C gene) was associated with retinal arteriolar caliber in the meta-analysis of the discovery cohorts at genome-wide significance of P-value <5×10(-8). This variant was replicated in an additional 3,939 individuals of European ancestry from the Australian Twins Study and Multi-Ethnic Study of Atherosclerosis (rs2194025, P-value = 2.11×10(-12) in combined meta-analysis of discovery and replication cohorts). In independent studies of modest sample sizes, no significant association was found between this variant and clinical outcomes including coronary artery disease, stroke, myocardial infarction or hypertension. In conclusion, we found one novel loci which underlie genetic variation in microvasculature which may be relevant to vascular disease. The relevance of these findings to clinical outcomes remains to be determined.
Keywords: Aged; Aged, 80 and over; Arterioles; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Male; MEF2 Transcription Factors; Microcirculation; Middle Aged; Models, Genetic; Retinal Vessels

Genetically elevated fetuin-A levels, fasting glucose levels, and risk of type 2 diabetes: the cardiovascular health study. - Jensen, Majken K; Bartz, Traci M; Djoussé, Luc; Kizer, Jorge R; Zieman, Susan J; Rimm, Eric B; Siscovick, David S; Psaty, Bruce M; Ix, Joachim H; Mukamal, Kenneth J (Diabetes Care, 2013)
OBJECTIVE: Fetuin-A levels are associated with higher risk of type 2 diabetes, but it is unknown if the association is causal. We investigated common (>5%) genetic variants in the fetuin-A gene (AHSG) fetuin-A levels, fasting glucose, and risk of type 2 diabetes. RESEARCH DESIGN AND METHODS: Genetic variation, fetuin-A levels, and fasting glucose were assessed in 2,893 Caucasian and 542 African American community-living individuals 65 years of age or older in 1992-1993. RESULTS: Common AHSG variants (rs4917 and rs2248690) were strongly associated with fetuin-A concentrations (P<0.0001). In analyses of 259 incident cases of type 2 diabetes, the single nucleotide polymorphisms (SNPs) were not associated with diabetes risk during follow-up and similar null associations were observed when 579 prevalent cases were included. As expected, higher fetuin-A levels were associated with higher fasting glucose concentrations (1.9 mg/dL [95% CI, 1.2-2.7] higher per SD in Caucasians), but Mendelian randomization analyses using both SNPs as unbiased proxies for measured fetuin-A did not support an association between genetically predicted fetuin-A levels and fasting glucose (-0.3 mg/dL [95% CI, -1.9 to 1.3] lower per SD in Caucasians). The difference between the associations of fasting glucose with actual and genetically predicted fetuin-A level was statistically significant (P=0.001). Results among the smaller sample of African Americans trended in similar directions but were statistically insignificant. CONCLUSIONS: Common variants in the AHSG gene are strongly associated with plasma fetuin-A concentrations, but not with risk of type 2 diabetes or glucose concentrations, raising the possibility that the association between fetuin-A and type 2 diabetes may not be causal.
Keywords: alpha-2-HS-Glycoprotein; Blood Glucose; Diabetes Mellitus, Type 2; Fasting; Female; Genotype; Humans; Male; Polymorphism, Single Nucleotide

Genome-wide and gene-centric analyses of circulating myeloperoxidase levels in the charge and care consortia. - Reiner, Alexander P; Hartiala, Jaana; Zeller, Tanja; Bis, Joshua C; Dupuis, Josée; Fornage, Myriam; Baumert, Jens; Kleber, Marcus E; Wild, Philipp S; Baldus, Stephan; Bielinski, Suzette J; Fontes, João D; et al. (Hum Mol Genet, 2013)
Increased systemic levels of myeloperoxidase (MPO) are associated with the risk of coronary artery disease (CAD). To identify the genetic factors that are associated with circulating MPO levels, we carried out a genome-wide association study (GWAS) and a gene-centric analysis in subjects of European ancestry and African Americans (AAs). A locus on chromosome 1q31.1 containing the complement factor H (CFH) gene was strongly associated with serum MPO levels in 9305 subjects of European ancestry (lead SNP rs800292; P = 4.89 × 10(-41)) and in 1690 AA subjects (rs505102; P = 1.05 × 10(-8)). Gene-centric analyses in 8335 subjects of European ancestry additionally identified two rare MPO coding sequence variants that were associated with serum MPO levels (rs28730837, P = 5.21 × 10(-12); rs35897051, P = 3.32 × 10(-8)). A GWAS for plasma MPO levels in 9260 European ancestry subjects identified a chromosome 17q22 region near MPO that was significantly associated (lead SNP rs6503905; P = 2.94 × 10(-12)), but the CFH locus did not exhibit evidence of association with plasma MPO levels. Functional analyses revealed that rs800292 was associated with levels of complement proteins in serum. Variants at chromosome 17q22 also had pleiotropic cis effects on gene expression. In a case-control analysis of ∼80 000 subjects from CARDIoGRAM, none of the identified single-nucleotide polymorphisms (SNPs) were associated with CAD. These results suggest that distinct genetic factors regulate serum and plasma MPO levels, which may have relevance for various acute and chronic inflammatory disorders. The clinical implications for CAD and a better understanding of the functional basis for the association of CFH and MPO variants with circulating MPO levels require further study.
Keywords: Adult; African Americans; Aged; Case-Control Studies; Complement Factor H; Coronary Artery Disease; European Continental Ancestry Group; Female; Gene Expression Regulation, Enzymologic; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Peroxidase; Polymorphism, Single Nucleotide; Young Adult

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

A genome-wide association study for venous thromboembolism: the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Tang, Weihong; Teichert, Martina; Chasman, Daniel I; Heit, John A; Morange, Pierre-Emmanuel; Li, Guo; Pankratz, Nathan; Leebeek, Frank W; Paré, Guillaume; de Andrade, Mariza; Tzourio, Christophe; Psaty, Bruce M; et al. (Genet Epidemiol, 2013)
Venous thromboembolism (VTE) is a common, heritable disease resulting in high rates of hospitalization and mortality. Yet few associations between VTE and genetic variants, all in the coagulation pathway, have been established. To identify additional genetic determinants of VTE, we conducted a two-stage genome-wide association study (GWAS) among individuals of European ancestry in the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) VTE consortium. The discovery GWAS comprised 1,618 incident VTE cases out of 44,499 participants from six community-based studies. Genotypes for genome-wide single-nucleotide polymorphisms (SNPs) were imputed to approximately 2.5 million SNPs in HapMap and association with VTE assessed using study-design appropriate regression methods. Meta-analysis of these results identified two known loci, in F5 and ABO. Top 1,047 tag SNPs (P ≤ 0.0016) from the discovery GWAS were tested for association in an additional 3,231 cases and 3,536 controls from three case-control studies. In the combined data from these two stages, additional genome-wide significant associations were observed on 4q35 at F11 (top SNP rs4253399, intronic to F11) and on 4q28 at FGG (rs6536024, 9.7 kb from FGG; P < 5.0 × 10(-13) for both). The associations at the FGG locus were not completely explained by previously reported variants. Loci at or near SUSD1 and OTUD7A showed borderline yet novel associations (P < 5.0 × 10(-6) ) and constitute new candidate genes. In conclusion, this large GWAS replicated key genetic associations in F5 and ABO, and confirmed the importance of F11 and FGG loci for VTE. Future studies are warranted to better characterize the associations with F11 and FGG and to replicate the new candidate associations.
Keywords: Aged; Aging; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; Venous Thromboembolism

Genome-wide association study identifies novel loci associated with concentrations of four plasma phospholipid fatty acids in the de novo lipogenesis pathway: results from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortiu - Wu, Jason H Y; Lemaitre, Rozenn N; Manichaikul, Ani; Guan, Weihua; Tanaka, Toshiko; Foy, Millennia; Kabagambe, Edmond K; Djoussé, Luc; Siscovick, David; Fretts, Amanda M; Johnson, Catherine; King, Irena B; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND- Palmitic acid (16:0), stearic acid (18:0), palmitoleic acid (16:1n-7), and oleic acid (18:1n-9) are major saturated and monounsaturated fatty acids that affect cellular signaling and metabolic pathways. They are synthesized via de novo lipogenesis and are the main saturated and monounsaturated fatty acids in the diet. Levels of these fatty acids have been linked to diseases including type 2 diabetes mellitus and coronary heart disease. METHODS AND RESULTS- Genome-wide association studies were conducted in 5 population-based cohorts comprising 8961 participants of European ancestry to investigate the association of common genetic variation with plasma levels of these 4 fatty acids. We identified polymorphisms in 7 novel loci associated with circulating levels of ≥1 of these fatty acids. ALG14 (asparagine-linked glycosylation 14 homolog) polymorphisms were associated with higher 16:0 (P=2.7×10(-11)) and lower 18:0 (P=2.2×10(-18)). FADS1 and FADS2 (desaturases) polymorphisms were associated with higher 16:1n-7 (P=6.6×10(-13)) and 18:1n-9 (P=2.2×10(-32)) and lower 18:0 (P=1.3×10(-20)). LPGAT1 (lysophosphatidylglycerol acyltransferase) polymorphisms were associated with lower 18:0 (P=2.8×10(-9)). GCKR (glucokinase regulator; P=9.8×10(-10)) and HIF1AN (factor inhibiting hypoxia-inducible factor-1; P=5.7×10(-9)) polymorphisms were associated with higher 16:1n-7, whereas PKD2L1 (polycystic kidney disease 2-like 1; P=5.7×10(-15)) and a locus on chromosome 2 (not near known genes) were associated with lower 16:1n-7 (P=4.1×10(-8)). CONCLUSIONS- Our findings provide novel evidence that common variations in genes with diverse functions, including protein-glycosylation, polyunsaturated fatty acid metabolism, phospholipid modeling, and glucose- and oxygen-sensing pathways, are associated with circulating levels of 4 fatty acids in the de novo lipogenesis pathway. These results expand our knowledge of genetic factors relevant to de novo lipogenesis and fatty acid biology.
Keywords: Adult; Aged; Chromosomes, Human, Pair 2; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Fatty Acids, Monounsaturated; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Lipogenesis; Male; Middle Aged; Oleic Acid; Palmitic Acid; Polymorphism, Single Nucleotide; Stearic Acids

Genome-wide association study of cardiac structure and systolic function in African Americans: the Candidate Gene Association Resource (CARe) study. - Fox, Ervin R; Musani, Solomon K; Barbalic, Maja; Lin, Honghuang; Yu, Bing; Ogunyankin, Kofo O; Smith, Nicholas L; Kutlar, Abdullah; Glazer, Nicole L; Post, Wendy S; Paltoo, Dina N; Dries, Daniel L; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: Using data from 4 community-based cohorts of African Americans, we tested the association between genome-wide markers (single-nucleotide polymorphisms) and cardiac phenotypes in the Candidate-gene Association Resource study. METHODS AND RESULTS: Among 6765 African Americans, we related age, sex, height, and weight-adjusted residuals for 9 cardiac phenotypes (assessed by echocardiogram or magnetic resonance imaging) to 2.5 million single-nucleotide polymorphisms genotyped using Genome-wide Affymetrix Human SNP Array 6.0 (Affy6.0) and the remainder imputed. Within the cohort, genome-wide association analysis was conducted, followed by meta-analysis across cohorts using inverse variance weights (genome-wide significance threshold=4.0 ×10(-7)). Supplementary pathway analysis was performed. We attempted replication in 3 smaller cohorts of African ancestry and tested lookups in 1 consortium of European ancestry (EchoGEN). Across the 9 phenotypes, variants in 4 genetic loci reached genome-wide significance: rs4552931 in UBE2V2 (P=1.43×10(-7)) for left ventricular mass, rs7213314 in WIPI1 (P=1.68×10(-7)) for left ventricular internal diastolic diameter, rs1571099 in PPAPDC1A (P=2.57×10(-8)) for interventricular septal wall thickness, and rs9530176 in KLF5 (P=4.02×10(-7)) for ejection fraction. Associated variants were enriched in 3 signaling pathways involved in cardiac remodeling. None of the 4 loci replicated in cohorts of African ancestry was confirmed in lookups in EchoGEN. CONCLUSIONS: In the largest genome-wide association study of cardiac structure and function to date in African Americans, we identified 4 genetic loci related to left ventricular mass, interventricular septal wall thickness, left ventricular internal diastolic diameter, and ejection fraction, which reached genome-wide significance. Replication results suggest that these loci may be unique to individuals of African ancestry. Additional large-scale studies are warranted for these complex phenotypes.
Keywords: African Americans; Aged; Cohort Studies; Diastole; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

A genome-wide association study of early menopause and the combined impact of identified variants. - Perry, John R B; Corre, Tanguy; Esko, Tõnu; Chasman, Daniel I; Fischer, Krista; Franceschini, Nora; He, Chunyan; Kutalik, Zoltán; Mangino, Massimo; Rose, Lynda M; Vernon Smith, Albert; Stolk, Lisette; et al. (Hum Mol Genet, 2013)
Early menopause (EM) affects up to 10% of the female population, reducing reproductive lifespan considerably. Currently, it constitutes the leading cause of infertility in the western world, affecting mainly those women who postpone their first pregnancy beyond the age of 30 years. The genetic aetiology of EM is largely unknown in the majority of cases. We have undertaken a meta-analysis of genome-wide association studies (GWASs) in 3493 EM cases and 13 598 controls from 10 independent studies. No novel genetic variants were discovered, but the 17 variants previously associated with normal age at natural menopause as a quantitative trait (QT) were also associated with EM and primary ovarian insufficiency (POI). Thus, EM has a genetic aetiology which overlaps variation in normal age at menopause and is at least partly explained by the additive effects of the same polygenic variants. The combined effect of the common variants captured by the single nucleotide polymorphism arrays was estimated to account for ∼30% of the variance in EM. The association between the combined 17 variants and the risk of EM was greater than the best validated non-genetic risk factor, smoking.
Keywords: Case-Control Studies; Female; Gene Frequency; Genome-Wide Association Study; Humans; Menopause, Premature; Polymorphism, Single Nucleotide; Primary Ovarian Insufficiency; Quantitative Trait Loci; Risk

Genome-wide association study of retinopathy in individuals without diabetes. - Jensen, Richard A; Sim, Xueling; Li, Xiaohui; Cotch, Mary Frances; Ikram, M Kamran; Holliday, Elizabeth G; Eiriksdottir, Gudny; Harris, Tamara B; Jonasson, Fridbert; Klein, Barbara E K; Launer, Lenore J; Smith, Albert Vernon; et al. (PLoS One, 2013)
BACKGROUND: Mild retinopathy (microaneurysms or dot-blot hemorrhages) is observed in persons without diabetes or hypertension and may reflect microvascular disease in other organs. We conducted a genome-wide association study (GWAS) of mild retinopathy in persons without diabetes. METHODS: A working group agreed on phenotype harmonization, covariate selection and analytic plans for within-cohort GWAS. An inverse-variance weighted fixed effects meta-analysis was performed with GWAS results from six cohorts of 19,411 Caucasians. The primary analysis included individuals without diabetes and secondary analyses were stratified by hypertension status. We also singled out the results from single nucleotide polymorphisms (SNPs) previously shown to be associated with diabetes and hypertension, the two most common causes of retinopathy. RESULTS: No SNPs reached genome-wide significance in the primary analysis or the secondary analysis of participants with hypertension. SNP, rs12155400, in the histone deacetylase 9 gene (HDAC9) on chromosome 7, was associated with retinopathy in analysis of participants without hypertension, -1.3±0.23 (beta ± standard error), p = 6.6×10(-9). Evidence suggests this was a false positive finding. The minor allele frequency was low (∼2%), the quality of the imputation was moderate (r(2) ∼0.7), and no other common variants in the HDAC9 gene were associated with the outcome. SNPs found to be associated with diabetes and hypertension in other GWAS were not associated with retinopathy in persons without diabetes or in subgroups with or without hypertension. CONCLUSIONS: This GWAS of retinopathy in individuals without diabetes showed little evidence of genetic associations. Further studies are needed to identify genes associated with these signs in order to help unravel novel pathways and determinants of microvascular diseases.
Keywords: Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Histone Deacetylases; Humans; Hypertension; Male; Polymorphism, Single Nucleotide; Repressor Proteins; Retinal Diseases

Genome-wide meta-analysis identifies 11 new loci for anthropometric traits and provides insights into genetic architecture. - Berndt, Sonja I; Gustafsson, Stefan; Mägi, Reedik; Ganna, Andrea; Wheeler, Eleanor; Feitosa, Mary F; Justice, Anne E; Monda, Keri L; Croteau-Chonka, Damien C; Day, Felix R; Esko, Tõnu; Fall, Tove; et al. (Nat Genet, 2013)
Approaches exploiting trait distribution extremes may be used to identify loci associated with common traits, but it is unknown whether these loci are generalizable to the broader population. In a genome-wide search for loci associated with the upper versus the lower 5th percentiles of body mass index, height and waist-to-hip ratio, as well as clinical classes of obesity, including up to 263,407 individuals of European ancestry, we identified 4 new loci (IGFBP4, H6PD, RSRC1 and PPP2R2A) influencing height detected in the distribution tails and 7 new loci (HNF4G, RPTOR, GNAT2, MRPS33P4, ADCY9, HS6ST3 and ZZZ3) for clinical classes of obesity. Further, we find a large overlap in genetic structure and the distribution of variants between traits based on extremes and the general population and little etiological heterogeneity between obesity subgroups.
Keywords: Anthropometry; Body Height; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Meta-Analysis as Topic; Obesity; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Waist-Hip Ratio

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD. - Hansel, Nadia N; Ruczinski, Ingo; Rafaels, Nicholas; Sin, Don D; Daley, Denise; Malinina, Alla; Huang, Lili; Sandford, Andrew; Murray, Tanda; Kim, Yoonhee; Vergara, Candelaria; Heckbert, Susan R; et al. (Hum Genet, 2013)
Accelerated lung function decline is a key COPD phenotype; however, its genetic control remains largely unknown. We performed a genome-wide association study using the Illumina Human660W-Quad v.1_A BeadChip. Generalized estimation equations were used to assess genetic contributions to lung function decline over a 5-year period in 4,048 European American Lung Health Study participants with largely mild COPD. Genotype imputation was performed using reference HapMap II data. To validate regions meeting genome-wide significance, replication of top SNPs was attempted in independent cohorts. Three genes (TMEM26, ANK3 and FOXA1) within the regions of interest were selected for tissue expression studies using immunohistochemistry. Two intergenic SNPs (rs10761570, rs7911302) on chromosome 10 and one SNP on chromosome 14 (rs177852) met genome-wide significance after Bonferroni. Further support for the chromosome 10 region was obtained by imputation, the most significantly associated imputed SNPs (rs10761571, rs7896712) being flanked by observed markers rs10761570 and rs7911302. Results were not replicated in four general population cohorts or a smaller cohort of subjects with moderate to severe COPD; however, we show novel expression of genes near regions of significantly associated SNPS, including TMEM26 and FOXA1 in airway epithelium and lung parenchyma, and ANK3 in alveolar macrophages. Levels of expression were associated with lung function and COPD status. We identified two novel regions associated with lung function decline in mild COPD. Genes within these regions were expressed in relevant lung cells and their expression related to airflow limitation suggesting they may represent novel candidate genes for COPD susceptibility.
Keywords: Adult; Ankyrins; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 14; Cohort Studies; Female; Genome-Wide Association Study; Hepatocyte Nuclear Factor 3-alpha; Humans; Linkage Disequilibrium; Lung; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive

Height and risk of incident intraparenchymal hemorrhage: Atherosclerosis Risk in Communities and Cardiovascular Health study cohorts. - Smith, Lindsay G; Yatsuya, Hiroshi; Psaty, Bruce M; Longstreth, W T; Folsom, Aaron R (J Stroke Cerebrovasc Dis, 2013)
BACKGROUND: Height is inversely associated with incident coronary disease and total stroke, but few studies have examined the association between height and intraparenchymal hemorrhage (IPH). We hypothesized that height would be inversely associated with incident IPH in the combined cohorts of the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. METHODS: Data on Caucasian and African American participants were used to estimate the association of height at baseline with incident IPH verified by clinician review of medical records and imaging reports. Sex-specific Cox proportional hazards regression models were used to calculate hazard ratios. RESULTS: A total of 20,983 participants initially free of stroke (11,788 women and 9195 men) were followed for an average of 15.9 years (standard deviation [SD] 5.1 years). Incident IPH occurred in 115 women and 73 men. Sex, but not age, race, study, or blood pressure, modified the association (P = .03). After adjustment for risk factors (age, systolic blood pressure, triglycerides, low-density lipoprotein cholesterol, fibrinogen, and race), among women, height was significantly inversely associated with incident IPH (hazard ratio [HR] per SD [6.3 cm] was 0.81; 95% confidence interval [CI] 0.66-0.99; P = .04). The HR for tertile 3 vs 1 in women was 0.63 (95% CI 0.37-1.08). Among men, height was not linearly associated with incident IPH (HR per SD [6.7 cm] was 1.09; 95% CI 0.84-1.40; P = .52). CONCLUSIONS: This large prospective study provides evidence that shorter height may be a risk factor for incident IPH in women.
Keywords: African Americans; Aged; Body Height; Cerebral Hemorrhage; European Continental Ancestry Group; Female; Humans; Incidence; Male; Middle Aged; Multivariate Analysis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Sex Factors; Time Factors; United States

Identification of heart rate-associated loci and their effects on cardiac conduction and rhythm disorders. - den Hoed, Marcel; Eijgelsheim, Mark; Esko, Tõnu; Brundel, Bianca J J M; Peal, David S; Evans, David M; Nolte, Ilja M; Segrè, Ayellet V; Holm, Hilma; Handsaker, Robert E; Westra, Harm-Jan; Johnson, Toby; et al. (Nat Genet, 2013)
Elevated resting heart rate is associated with greater risk of cardiovascular disease and mortality. In a 2-stage meta-analysis of genome-wide association studies in up to 181,171 individuals, we identified 14 new loci associated with heart rate and confirmed associations with all 7 previously established loci. Experimental downregulation of gene expression in Drosophila melanogaster and Danio rerio identified 20 genes at 11 loci that are relevant for heart rate regulation and highlight a role for genes involved in signal transmission, embryonic cardiac development and the pathophysiology of dilated cardiomyopathy, congenital heart failure and/or sudden cardiac death. In addition, genetic susceptibility to increased heart rate is associated with altered cardiac conduction and reduced risk of sick sinus syndrome, and both heart rate-increasing and heart rate-decreasing variants associate with risk of atrial fibrillation. Our findings provide fresh insights into the mechanisms regulating heart rate and identify new therapeutic targets.
Keywords: Animals; Arrhythmias, Cardiac; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Heart Rate; Humans; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Insights into the genetic architecture of early stage age-related macular degeneration: a genome-wide association study meta-analysis. - Holliday, Elizabeth G; Smith, Albert V; Cornes, Belinda K; Buitendijk, Gabriëlle H S; Jensen, Richard A; Sim, Xueling; Aspelund, Thor; Aung, Tin; Baird, Paul N; Boerwinkle, Eric; Cheng, Ching Yu; van Duijn, Cornelia M; et al. (PLoS One, 2013)
Genetic factors explain a majority of risk variance for age-related macular degeneration (AMD). While genome-wide association studies (GWAS) for late AMD implicate genes in complement, inflammatory and lipid pathways, the genetic architecture of early AMD has been relatively under studied. We conducted a GWAS meta-analysis of early AMD, including 4,089 individuals with prevalent signs of early AMD (soft drusen and/or retinal pigment epithelial changes) and 20,453 individuals without these signs. For various published late AMD risk loci, we also compared effect sizes between early and late AMD using an additional 484 individuals with prevalent late AMD. GWAS meta-analysis confirmed previously reported association of variants at the complement factor H (CFH) (peak P = 1.5×10(-31)) and age-related maculopathy susceptibility 2 (ARMS2) (P = 4.3×10(-24)) loci, and suggested Apolipoprotein E (ApoE) polymorphisms (rs2075650; P = 1.1×10(-6)) associated with early AMD. Other possible loci that did not reach GWAS significance included variants in the zinc finger protein gene GLI3 (rs2049622; P = 8.9×10(-6)) and upstream of GLI2 (rs6721654; P = 6.5×10(-6)), encoding retinal Sonic hedgehog signalling regulators, and in the tyrosinase (TYR) gene (rs621313; P = 3.5×10(-6)), involved in melanin biosynthesis. For a range of published, late AMD risk loci, estimated effect sizes were significantly lower for early than late AMD. This study confirms the involvement of multiple established AMD risk variants in early AMD, but suggests weaker genetic effects on the risk of early AMD relative to late AMD. Several biological processes were suggested to be potentially specific for early AMD, including pathways regulating RPE cell melanin content and signalling pathways potentially involved in retinal regeneration, generating hypotheses for further investigation.
Keywords: Apolipoproteins E; Complement Factor H; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Kruppel-Like Transcription Factors; Macular Degeneration; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Zinc Finger Protein Gli3

A meta-analysis identifies new loci associated with body mass index in individuals of African ancestry. - Monda, Keri L; Chen, Gary K; Taylor, Kira C; Palmer, Cameron; Edwards, Todd L; Lange, Leslie A; Ng, Maggie C Y; Adeyemo, Adebowale A; Allison, Matthew A; Bielak, Lawrence F; Chen, Guanjie; Graff, Mariaelisa; et al. (Nat Genet, 2013)
Genome-wide association studies (GWAS) have identified 36 loci associated with body mass index (BMI), predominantly in populations of European ancestry. We conducted a meta-analysis to examine the association of >3.2 million SNPs with BMI in 39,144 men and women of African ancestry and followed up the most significant associations in an additional 32,268 individuals of African ancestry. We identified one new locus at 5q33 (GALNT10, rs7708584, P = 3.4 × 10(-11)) and another at 7p15 when we included data from the GIANT consortium (MIR148A-NFE2L3, rs10261878, P = 1.2 × 10(-10)). We also found suggestive evidence of an association at a third locus at 6q16 in the African-ancestry sample (KLHL32, rs974417, P = 6.9 × 10(-8)). Thirty-two of the 36 previously established BMI variants showed directionally consistent effect estimates in our GWAS (binomial P = 9.7 × 10(-7)), five of which reached genome-wide significance. These findings provide strong support for shared BMI loci across populations, as well as for the utility of studying ancestrally diverse populations.
Keywords: African Americans; Body Mass Index; Case-Control Studies; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide

Meta-analysis of genome-wide association studies identifies six new Loci for serum calcium concentrations. - O'Seaghdha, Conall M; Wu, Hongsheng; Yang, Qiong; Kapur, Karen; Guessous, Idris; Zuber, Annie Mercier; Köttgen, Anna; Stoudmann, Candice; Teumer, Alexander; Kutalik, Zoltán; Mangino, Massimo; Dehghan, Abbas; et al. (PLoS Genet, 2013)
Calcium is vital to the normal functioning of multiple organ systems and its serum concentration is tightly regulated. Apart from CASR, the genes associated with serum calcium are largely unknown. We conducted a genome-wide association meta-analysis of 39,400 individuals from 17 population-based cohorts and investigated the 14 most strongly associated loci in ≤ 21,679 additional individuals. Seven loci (six new regions) in association with serum calcium were identified and replicated. Rs1570669 near CYP24A1 (P = 9.1E-12), rs10491003 upstream of GATA3 (P = 4.8E-09) and rs7481584 in CARS (P = 1.2E-10) implicate regions involved in Mendelian calcemic disorders: Rs1550532 in DGKD (P = 8.2E-11), also associated with bone density, and rs7336933 near DGKH/KIAA0564 (P = 9.1E-10) are near genes that encode distinct isoforms of diacylglycerol kinase. Rs780094 is in GCKR. We characterized the expression of these genes in gut, kidney, and bone, and demonstrate modulation of gene expression in bone in response to dietary calcium in mice. Our results shed new light on the genetics of calcium homeostasis.
Keywords: Animals; Bone and Bones; Bone Density; Calcium; European Continental Ancestry Group; Gene Expression Regulation; Genome-Wide Association Study; Homeostasis; Humans; Kidney; Mice; Polymorphism, Single Nucleotide

A meta-analysis of thyroid-related traits reveals novel loci and gender-specific differences in the regulation of thyroid function. - Porcu, Eleonora; Medici, Marco; Pistis, Giorgio; Volpato, Claudia B; Wilson, Scott G; Cappola, Anne R; Bos, Steffan D; Deelen, Joris; den Heijer, Martin; Freathy, Rachel M; Lahti, Jari; Liu, Chunyu; et al. (PLoS Genet, 2013)
Thyroid hormone is essential for normal metabolism and development, and overt abnormalities in thyroid function lead to common endocrine disorders affecting approximately 10% of individuals over their life span. In addition, even mild alterations in thyroid function are associated with weight changes, atrial fibrillation, osteoporosis, and psychiatric disorders. To identify novel variants underlying thyroid function, we performed a large meta-analysis of genome-wide association studies for serum levels of the highly heritable thyroid function markers TSH and FT4, in up to 26,420 and 17,520 euthyroid subjects, respectively. Here we report 26 independent associations, including several novel loci for TSH (PDE10A, VEGFA, IGFBP5, NFIA, SOX9, PRDM11, FGF7, INSR, ABO, MIR1179, NRG1, MBIP, ITPK1, SASH1, GLIS3) and FT4 (LHX3, FOXE1, AADAT, NETO1/FBXO15, LPCAT2/CAPNS2). Notably, only limited overlap was detected between TSH and FT4 associated signals, in spite of the feedback regulation of their circulating levels by the hypothalamic-pituitary-thyroid axis. Five of the reported loci (PDE8B, PDE10A, MAF/LOC440389, NETO1/FBXO15, and LPCAT2/CAPNS2) show strong gender-specific differences, which offer clues for the known sexual dimorphism in thyroid function and related pathologies. Importantly, the TSH-associated loci contribute not only to variation within the normal range, but also to TSH values outside the reference range, suggesting that they may be involved in thyroid dysfunction. Overall, our findings explain, respectively, 5.64% and 2.30% of total TSH and FT4 trait variance, and they improve the current knowledge of the regulation of hypothalamic-pituitary-thyroid axis function and the consequences of genetic variation for hypo- or hyperthyroidism.
Keywords: Female; Genome-Wide Association Study; Humans; Hyperthyroidism; Hypothyroidism; Male; Phenotype; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Sex Characteristics; Signal Transduction; Thyroid Gland; Thyrotropin; Thyroxine

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

Racial differences in the incidence of and risk factors for atrial fibrillation in older adults: the cardiovascular health study. - Jensen, Paul N; Thacker, Evan L; Dublin, Sascha; Psaty, Bruce M; Heckbert, Susan R (J Am Geriatr Soc, 2013)
This study examined whether different associations between risk factors and atrial fibrillation (AF) according to race could explain the lower incidence of AF in blacks. Baseline risk factor information was obtained from interviews, clinical examinations, and echocardiography in 4,774 white and 911 black Cardiovascular Health Study participants aged 65 and older without a history of AF at baseline in 1989/90 or 1992/93. Incident AF was determined according to hospital discharge diagnosis or annual study electrocardiogram. Cox regression was used to assess associations between risk factors and race and incident AF. During a mean 11.2 years of follow-up, 1,403 whites and 182 blacks had incident AF. Associations between all examined risk factors were similar in both races, except left ventricular posterior wall thickness, which was more strongly associated with AF in blacks (per 0.2 cm, blacks: hazard ratio (HR) = 1.72, 95% confidence interval (CI) = 1.44-2.06; whites: HR = 1.30, 95% CI = 1.18-1.43). Overall, the relative risk of AF was 25% lower in blacks than whites after adjustment for age and sex (HR = 0.75, 95% CI = 0.64-0.87) and 45% lower after adjustment for all considered risk factors (HR = 0.55, 95% CI = 0.35-0.88). Different associations of the considered risk factors and incident AF by race do not explain the lower incidence of AF in blacks.
Keywords: Aged; Atrial Fibrillation; Continental Population Groups; Female; Follow-Up Studies; Humans; Incidence; Male; Prevalence; Risk Assessment; Risk Factors; Stroke; United States

Resequencing and clinical associations of the 9p21.3 region: a comprehensive investigation in the Framingham heart study. - Johnson, Andrew D; Hwang, Shih-Jen; Voorman, Arend; Morrison, Alanna; Peloso, Gina M; Hsu, Yi-Hsiang; Thanassoulis, George; Newton-Cheh, Christopher; Rogers, Ian S; Hoffmann, Udo; Freedman, Jane E; Fox, Caroline S; et al. (Circulation, 2013)
BACKGROUND: 9p21.3 is among the most strongly replicated regions for cardiovascular disease. There are few reports of sequencing the associated 9p21.3 interval. We set out to sequence the 9p21.3 region followed by a comprehensive study of genetic associations with clinical and subclinical cardiovascular disease and its risk factors, as well as with copy number variation and gene expression, in the Framingham Heart Study (FHS). METHODS AND RESULTS: We sequenced 281 individuals (94 with myocardial infarction, 94 with high coronary artery calcium levels, and 93 control subjects free of elevated coronary artery calcium or myocardial infarction), followed by genotyping and association in >7000 additional FHS individuals. We assessed genetic associations with clinical and subclinical cardiovascular disease, risk factor phenotypes, and gene expression levels of the protein-coding genes CDKN2A and CDKN2B and the noncoding gene ANRIL in freshly harvested leukocytes and platelets. Within this large sample, we found strong associations of 9p21.3 variants with increased risk for myocardial infarction, higher coronary artery calcium levels, and larger abdominal aorta diameters and no evidence for association with traditional cardiovascular disease risk factors. No common protein-coding variation, variants in splice donor or acceptor sites, or copy number variation events were observed. By contrast, strong associations were observed between genetic variants and gene expression, particularly for a short isoform of ANRIL and for CDKN2B. CONCLUSIONS: Our thorough genomic characterization of 9p21.3 suggests common variants likely account for observed disease associations and provides further support for the hypothesis that complex regulatory variation affecting ANRIL and CDKN2B gene expression may contribute to increased risk for clinically apparent and subclinical coronary artery disease and aortic disease.
Keywords: Calcinosis; Chromosomes, Human, Pair 9; Coronary Artery Disease; Cyclin-Dependent Kinase Inhibitor p15; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Longitudinal Studies; Male; Massachusetts; Middle Aged; Myocardial Infarction; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; RNA, Long Noncoding; Sequence Analysis, DNA

Whole-genome sequence-based analysis of high-density lipoprotein cholesterol. - Morrison, Alanna C; Voorman, Arend; Johnson, Andrew D; Liu, Xiaoming; Yu, Jin; Li, Alexander; Muzny, Donna; Yu, Fuli; Rice, Kenneth; Zhu, Chengsong; Bis, Joshua; Heiss, Gerardo; et al. (Nat Genet, 2013)
We describe initial steps for interrogating whole-genome sequence data to characterize the genetic architecture of a complex trait, levels of high-density lipoprotein cholesterol (HDL-C). We report whole-genome sequencing and analysis of 962 individuals from the Cohorts for Heart and Aging Research in Genetic Epidemiology (CHARGE) studies. From this analysis, we estimate that common variation contributes more to heritability of HDL-C levels than rare variation, and screening for mendelian variants for dyslipidemia identified individuals with extreme HDL-C levels. Whole-genome sequencing analyses highlight the value of regulatory and non-protein-coding regions of the genome in addition to protein-coding regions.
Keywords: Cholesterol, HDL; Computational Biology; Databases, Genetic; Genetic Variation; Genome, Human; Genome-Wide Association Study; Genomics; Heterozygote; Humans; Open Reading Frames

ADAM19 and HTR4 variants and pulmonary function: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - London, Stephanie J; Gao, Wei; Gharib, Sina A; Hancock, Dana B; Wilk, Jemma B; House, John S; Gibbs, Richard A; Muzny, Donna M; Lumley, Thomas; Franceschini, Nora; North, Kari E; Psaty, Bruce M; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The pulmonary function measures of forced expiratory volume in 1 second (FEV1) and its ratio to forced vital capacity (FVC) are used in the diagnosis and monitoring of lung diseases and predict cardiovascular mortality in the general population. Genome-wide association studies (GWASs) have identified numerous loci associated with FEV1 and FEV1/FVC, but the causal variants remain uncertain. We hypothesized that novel or rare variants poorly tagged by GWASs may explain the significant associations between FEV1/FVC and 2 genes: ADAM19 and HTR4. METHODS AND RESULTS: We sequenced ADAM19 and its promoter region along with the ≈21-kb portion of HTR4 harboring GWAS single-nucleotide polymorphisms for pulmonary function and analyzed associations with FEV1/FVC among 3983 participants of European ancestry from Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Meta-analysis of common variants in each region identified statistically significant associations (316 tests; P<1.58×10(-4)) with FEV1/FVC for 14 ADAM19 single-nucleotide polymorphisms and 24 HTR4 single-nucleotide polymorphisms. After conditioning on the sentinel GWASs hit in each gene (ADAM19 rs1422795, minor allele frequency=0.33 and HTR4 rs11168048, minor allele frequency=0.40], 1 single-nucleotide polymorphism remained statistically significant (ADAM19 rs13155908, minor allele frequency=0.12; P=1.56×10(-4)). Analysis of rare variants (minor allele frequency <1%) using sequence kernel association test did not identify associations with either region. CONCLUSIONS: Sequencing identified 1 common variant associated with FEV1/FVC independent of the sentinel ADAM19 GWAS hit and supports the original HTR4 GWAS findings. Rare variants do not seem to underlie GWAS associations with pulmonary function for common variants in ADAM19 and HTR4.
Keywords: ADAM Proteins; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Advanced glycation/glycoxidation endproduct carboxymethyl-lysine and incidence of coronary heart disease and stroke in older adults. - Kizer, Jorge R; Benkeser, David; Arnold, Alice M; Ix, Joachim H; Mukamal, Kenneth J; Djoussé, Luc; Tracy, Russell P; Siscovick, David S; Psaty, Bruce M; Zieman, Susan J (Atherosclerosis, 2014)
BACKGROUND: Advanced glycation/glycoxidation endproducts (AGEs) accumulate in settings of increased oxidative stress--such as diabetes, chronic kidney disease and aging--where they promote vascular stiffness and atherogenesis, but the prospective association between AGEs and cardiovascular events in elders has not been previously examined. METHODS: To test the hypothesis that circulating levels of N(ɛ)-carboxymethyl-lysine (CML), a major AGE, increase the risk of incident coronary heart disease and stroke in older adults, we measured serum CML by immunoassay in 2111 individuals free of prevalent cardiovascular disease participating in a population-based study of U.S. adults ages 65 and older. RESULTS: During median follow-up of 9.1 years, 625 cardiovascular events occurred. CML was positively associated with incident cardiovascular events after adjustment for age, sex, race, systolic blood pressure, anti-hypertensive treatment, diabetes, smoking status, triglycerides, albumin, and self-reported health status (hazard ratio [HR] per SD [0.99 pmol/l] increase=1.11, 95% confidence interval [CI]=1.03-1.19). This association was not materially attenuated by additional adjustment for C-reactive protein, estimated glomerular filtration rate (eGFR), and urine albumin/creatinine ratio. Findings were similar for the component endpoints of coronary heart disease and stroke. CONCLUSIONS: In this large older cohort, CML was associated with an increased risk of cardiovascular events independent of a wide array of potential confounders and mediators. Although the moderate association limits CML's value for risk prediction, these community-based findings provide support for clinical trials to test AGE-lowering therapies for cardiovascular prevention in this population.
Keywords: Aged; Albumins; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Creatinine; Female; Glomerular Filtration Rate; Glycation End Products, Advanced; Humans; Immunoassay; Incidence; Lysine; Male; Oxidative Stress; Proportional Hazards Models; Stroke; Treatment Outcome

Association between alcohol and cardiovascular disease: Mendelian randomisation analysis based on individual participant data. - Holmes, Michael V; Dale, Caroline E; Zuccolo, Luisa; Silverwood, Richard J; Guo, Yiran; Ye, Zheng; Prieto-Merino, David; Dehghan, Abbas; Trompet, Stella; Wong, Andrew; Cavadino, Alana; Drogan, Dagmar; et al. (BMJ, 2014)
OBJECTIVE: To use the rs1229984 variant in the alcohol dehydrogenase 1B gene (ADH1B) as an instrument to investigate the causal role of alcohol in cardiovascular disease. DESIGN: Mendelian randomisation meta-analysis of 56 epidemiological studies. PARTICIPANTS: 261 991 individuals of European descent, including 20 259 coronary heart disease cases and 10 164 stroke events. Data were available on ADH1B rs1229984 variant, alcohol phenotypes, and cardiovascular biomarkers. MAIN OUTCOME MEASURES: Odds ratio for coronary heart disease and stroke associated with the ADH1B variant in all individuals and by categories of alcohol consumption. RESULTS: Carriers of the A-allele of ADH1B rs1229984 consumed 17.2% fewer units of alcohol per week (95% confidence interval 15.6% to 18.9%), had a lower prevalence of binge drinking (odds ratio 0.78 (95% CI 0.73 to 0.84)), and had higher abstention (odds ratio 1.27 (1.21 to 1.34)) than non-carriers. Rs1229984 A-allele carriers had lower systolic blood pressure (-0.88 (-1.19 to -0.56) mm Hg), interleukin-6 levels (-5.2% (-7.8 to -2.4%)), waist circumference (-0.3 (-0.6 to -0.1) cm), and body mass index (-0.17 (-0.24 to -0.10) kg/m(2)). Rs1229984 A-allele carriers had lower odds of coronary heart disease (odds ratio 0.90 (0.84 to 0.96)). The protective association of the ADH1B rs1229984 A-allele variant remained the same across all categories of alcohol consumption (P=0.83 for heterogeneity). Although no association of rs1229984 was identified with the combined subtypes of stroke, carriers of the A-allele had lower odds of ischaemic stroke (odds ratio 0.83 (0.72 to 0.95)). CONCLUSIONS: Individuals with a genetic variant associated with non-drinking and lower alcohol consumption had a more favourable cardiovascular profile and a reduced risk of coronary heart disease than those without the genetic variant. This suggests that reduction of alcohol consumption, even for light to moderate drinkers, is beneficial for cardiovascular health.
Keywords: Adult; Aged; Alcohol Dehydrogenase; Alcohol Drinking; Biomarkers; Coronary Disease; Female; Genetic Markers; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Models, Statistical; Polymorphism, Single Nucleotide; Stroke

Association of kidney disease measures with ischemic versus hemorrhagic strokes: pooled analyses of 4 prospective community-based cohorts. - Mahmoodi, Bakhtawar K; Yatsuya, Hiroshi; Matsushita, Kunihiro; Sang, Yinying; Gottesman, Rebecca F; Astor, Brad C; Woodward, Mark; Longstreth, W T; Psaty, Bruce M; Shlipak, Michael G; Folsom, Aaron R; Gansevoort, Ron T; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Although low glomerular filtration rate (GFR) and albuminuria are associated with increased risk of stroke, few studies compared their contribution to risk of ischemic versus hemorrhagic stroke separately. We contrasted the association of these kidney measures with ischemic versus hemorrhagic stroke. METHODS: We pooled individual participant data from 4 community-based cohorts: 3 from the United States and 1 from The Netherlands. GFR was estimated using both creatinine and cystatin C, and albuminuria was quantified by urinary albumin-to-creatinine ratio (ACR). Associations of estimated GFR and ACR were compared for each stroke type (ischemic versus intraparenchymal hemorrhagic) using study-stratified Cox regression. RESULTS: Among 29,595 participants (mean age, 61 [SD 12.5] years; 46% men; 17% black), 1261 developed stroke (12% hemorrhagic) during 280,549 person-years. Low estimated GFR was significantly associated with increased risk of ischemic stroke, but not hemorrhagic stroke, whereas high ACR was associated with both stroke types. Adjusted hazard ratios for ischemic and hemorrhagic stroke at estimated GFR of 45 (versus 95) mL/min per 1.73 m2 were 1.30 (95% confidence interval, 1.01-1.68) and 0.92 (0.47-1.81), respectively. In contrast, the corresponding hazard ratios for ACR of 300 (versus 5) mg/g were 1.62 (1.27-2.07) for ischemic and 2.57 (1.37-4.83) for hemorrhagic stroke, with significantly stronger association with hemorrhagic stroke (P=0.04). For hemorrhagic stroke, the association of elevated ACR was of similar magnitude as that of elevated systolic blood pressure. CONCLUSIONS: Whereas albuminuria showed significant association with both stroke types, the association of decreased estimated GFR was only significant for ischemic stroke. The strong association of albuminuria with both stroke types warrants clinical attention and further investigations.
Keywords: Aged; Albuminuria; Brain Ischemia; Comorbidity; Female; Glomerular Filtration Rate; Humans; Intracranial Hemorrhages; Kidney Diseases; Male; Middle Aged; Netherlands; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; United States

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; African Continental Ancestry Group; Aged; Alleles; Animals; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides

Association of sick sinus syndrome with incident cardiovascular disease and mortality: the Atherosclerosis Risk in Communities study and Cardiovascular Health Study. - Alonso, Alvaro; Jensen, Paul N; Lopez, Faye L; Chen, Lin Y; Psaty, Bruce M; Folsom, Aaron R; Heckbert, Susan R (PLoS One, 2014)
BACKGROUND: Sick sinus syndrome (SSS) is a common indication for pacemaker implantation. Limited information exists on the association of sick sinus syndrome (SSS) with mortality and cardiovascular disease (CVD) in the general population. METHODS: We studied 19,893 men and women age 45 and older in the Atherosclerosis Risk in Communities (ARIC) study and the Cardiovascular Health Study (CHS), two community-based cohorts, who were without a pacemaker or atrial fibrillation (AF) at baseline. Incident SSS cases were validated by review of medical charts. Incident CVD and mortality were ascertained using standardized protocols. Multivariable Cox models were used to estimate the association of incident SSS with selected outcomes. RESULTS: During a mean follow-up of 17 years, 213 incident SSS events were identified and validated (incidence, 0.6 events per 1,000 person-years). After adjustment for confounders, SSS incidence was associated with increased mortality (hazard ratio [HR] 1.39, 95% confidence interval [CI] 1.14-1.70), coronary heart disease (HR 1.72, 95%CI 1.11-2.66), heart failure (HR 2.87, 95%CI 2.17-3.80), stroke (HR 1.56, 95%CI 0.99-2.46), AF (HR 5.75, 95%CI 4.43-7.46), and pacemaker implantation (HR 53.7, 95%CI 42.9-67.2). After additional adjustment for other incident CVD during follow-up, SSS was no longer associated with increased mortality, coronary heart disease, or stroke, but remained associated with higher risk of heart failure (HR 2.00, 95%CI 1.51-2.66), AF (HR 4.25, 95%CI 3.28-5.51), and pacemaker implantation (HR 25.2, 95%CI 19.8-32.1). CONCLUSION: Individuals who develop SSS are at increased risk of death and CVD. The mechanisms underlying these associations warrant further investigation.
Keywords: Age Distribution; Atherosclerosis; Cohort Studies; Continental Population Groups; Female; Humans; Incidence; Male; Middle Aged; Residence Characteristics; Risk; Sex Distribution; Sick Sinus Syndrome

Associations of NINJ2 sequence variants with incident ischemic stroke in the Cohorts for Heart and Aging in Genomic Epidemiology (CHARGE) consortium. - Bis, Joshua C; DeStefano, Anita; Liu, Xiaoming; Brody, Jennifer A; Choi, Seung Hoan; Verhaaren, Benjamin F J; Debette, Stephanie; Ikram, M Arfan; Shahar, Eyal; Butler, Kenneth R; Gottesman, Rebecca F; Muzny, Donna; et al. (PLoS One, 2014)
BACKGROUND: Stroke, the leading neurologic cause of death and disability, has a substantial genetic component. We previously conducted a genome-wide association study (GWAS) in four prospective studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and demonstrated that sequence variants near the NINJ2 gene are associated with incident ischemic stroke. Here, we sought to fine-map functional variants in the region and evaluate the contribution of rare variants to ischemic stroke risk. METHODS AND RESULTS: We sequenced 196 kb around NINJ2 on chromosome 12p13 among 3,986 European ancestry participants, including 475 ischemic stroke cases, from the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, and Framingham Heart Study. Meta-analyses of single-variant tests for 425 common variants (minor allele frequency [MAF] ≥ 1%) confirmed the original GWAS results and identified an independent intronic variant, rs34166160 (MAF = 0.012), most significantly associated with incident ischemic stroke (HR = 1.80, p = 0.0003). Aggregating 278 putatively-functional variants with MAF≤ 1% using count statistics, we observed a nominally statistically significant association, with the burden of rare NINJ2 variants contributing to decreased ischemic stroke incidence (HR = 0.81; p = 0.026). CONCLUSION: Common and rare variants in the NINJ2 region were nominally associated with incident ischemic stroke among a subset of CHARGE participants. Allelic heterogeneity at this locus, caused by multiple rare, low frequency, and common variants with disparate effects on risk, may explain the difficulties in replicating the original GWAS results. Additional studies that take into account the complex allelic architecture at this locus are needed to confirm these findings.
Keywords: Cell Adhesion Molecules, Neuronal; European Continental Ancestry Group; Female; Genetic Association Studies; Genetic Heterogeneity; Humans; Introns; Ischemia; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

The challenges of genome-wide interaction studies: lessons to learn from the analysis of HDL blood levels. - van Leeuwen, Elisabeth M; Smouter, Françoise A S; Kam-Thong, Tony; Karbalai, Nazanin; Smith, Albert V; Harris, Tamara B; Launer, Lenore J; Sitlani, Colleen M; Li, Guo; Brody, Jennifer A; Bis, Joshua C; White, Charles C; et al. (PLoS One, 2014)
Genome-wide association studies (GWAS) have revealed 74 single nucleotide polymorphisms (SNPs) associated with high-density lipoprotein cholesterol (HDL) blood levels. This study is, to our knowledge, the first genome-wide interaction study (GWIS) to identify SNP×SNP interactions associated with HDL levels. We performed a GWIS in the Rotterdam Study (RS) cohort I (RS-I) using the GLIDE tool which leverages the massively parallel computing power of Graphics Processing Units (GPUs) to perform linear regression on all genome-wide pairs of SNPs. By performing a meta-analysis together with Rotterdam Study cohorts II and III (RS-II and RS-III), we were able to filter 181 interaction terms with a p-value<1 · 10-8 that replicated in the two independent cohorts. We were not able to replicate any of these interaction term in the AGES, ARIC, CHS, ERF, FHS and NFBC-66 cohorts (Ntotal = 30,011) when adjusting for multiple testing. Our GWIS resulted in the consistent finding of a possible interaction between rs774801 in ARMC8 (ENSG00000114098) and rs12442098 in SPATA8 (ENSG00000185594) being associated with HDL levels. However, p-values do not reach the preset Bonferroni correction of the p-values. Our study suggest that even for highly genetically determined traits such as HDL the sample sizes needed to detect SNP×SNP interactions are large and the 2-step filtering approaches do not yield a solution. Here we present our analysis plan and our reservations concerning GWIS.
Keywords: Cholesterol, HDL; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Circulating omega-6 polyunsaturated fatty acids and total and cause-specific mortality: the Cardiovascular Health Study. - Wu, Jason H Y; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Psaty, Bruce M; Siscovick, David S; Mozaffarian, Dariush (Circulation, 2014)
BACKGROUND: Although omega-6 polyunsaturated fatty acids (n-6 PUFA) have been recommended to reduce coronary heart disease (CHD), controversy remains about benefits versus harms, including concerns over theorized proinflammatory effects of n-6 PUFA. We investigated associations of circulating n-6 PUFA including linoleic acid (the major dietary PUFA), γ-linolenic acid, dihomo-γ-linolenic acid, and arachidonic acid, with total and cause-specific mortality in the Cardiovascular Health Study, a community-based U.S. cohort. METHODS AND RESULTS: Among 2792 participants(aged ≥65 years) free of cardiovascular disease at baseline, plasma phospholipid n-6 PUFA were measured at baseline using standardized methods. All-cause and cause-specific mortality, and total incident CHD and stroke, were assessed and adjudicated centrally. Associations of PUFA with risk were assessed by Cox regression. During 34 291 person-years of follow-up (1992-2010), 1994 deaths occurred (678 cardiovascular deaths), with 427 fatal and 418 nonfatal CHD, and 154 fatal and 399 nonfatal strokes. In multivariable models, higher linoleic acid was associated with lower total mortality, with extreme-quintile hazard ratio =0.87 (P trend=0.005). Lower death was largely attributable to cardiovascular disease causes, especially nonarrhythmic CHD mortality (hazard ratio, 0.51; 95% confidence interval, 0.32-0.82; P trend=0.001). Circulating γ-linolenic acid, dihomo-γ-linolenic acid, and arachidonic acid were not significantly associated with total or cause-specific mortality (eg, for arachidonic acid and CHD death, the extreme-quintile hazard ratio was 0.97; 95% confidence interval, 0.70-1.34; P trend=0.87). Evaluated semiparametrically, linoleic acid showed graded inverse associations with total mortality (P=0.005). There was little evidence that associations of n-6 PUFA with total mortality varied by age, sex, race, or plasma n-3 PUFA. Evaluating both n-6 and n-3 PUFA, lowest risk was evident with highest levels of both. CONCLUSIONS: High circulating linoleic acid, but not other n-6 PUFA, was inversely associated with total and CHD mortality in older adults.
Keywords: Aged; Arachidonic Acid; Biomarkers; Cohort Studies; Coronary Disease; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Fatty Acids, Unsaturated; Female; Follow-Up Studies; Humans; Linoleic Acid; Male; Prospective Studies; Regression Analysis; Risk Factors; Stroke; Survival Rate; United States

Common variation in fatty acid metabolic genes and risk of incident sudden cardiac arrest. - Lemaitre, Rozenn N; Johnson, Catherine O; Hesselson, Stephanie; Sotoodehnia, Nona; Sotoodhenia, Nona; McKnight, Barbara; Sitlani, Colleen M; Rea, Thomas D; King, Irena B; Kwok, Pui-Yan; Mak, Angel; Li, Guo; et al. (Heart Rhythm, 2014)
BACKGROUND: There is limited information on genetic factors associated with sudden cardiac arrest (SCA). OBJECTIVE: To assess the association of common variation in genes in fatty acid pathways with SCA risk. METHODS: We selected 85 candidate genes and 1155 single nucleotide polymorphisms (SNPs) tagging common variation in each gene. We investigated the SNP associations with SCA in a population-based case-control study. Cases (n = 2160) were from a repository of SCA in the greater Seattle area. Controls (n = 2615), frequency-matched on age and sex, were from the same area. We used linear logistic regression to examine SNP associations with SCA. We performed permutation-based p-min tests to account for multiple comparisons within each gene. The SNP associations with a corrected P value of <.05 were then examined in a meta-analysis of these SNP associations in 9 replication studies totaling 2129 SCA cases and 23,833 noncases. RESULTS: Eight SNPs in or near 8 genes were associated with SCA risk in the discovery study, one of which was nominally significant in the replication phase (rs7737692, minor allele frequency 36%, near the LPCAT1 gene). For each copy of the minor allele, rs7737692 was associated with 13% lower SCA risk (95% confidence interval -21% to -5%) in the discovery phase and 9% lower SCA risk (95% confidence interval -16% to -1%) in the replication phase. CONCLUSIONS: While none of the associations reached significance with Bonferroni correction, a common genetic variant near LPCAT1, a gene involved in the remodeling of phospholipids, was nominally associated with incident SCA risk. Further study is needed to validate this observation.
Keywords: 1-Acylglycerophosphocholine O-Acyltransferase; Aged; Algorithms; Alleles; Case-Control Studies; Death, Sudden, Cardiac; Fatty Acids; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Male; Polymorphism, Single Nucleotide; Risk Factors

Effect of genetic variants associated with plasma homocysteine levels on stroke risk. - Cotlarciuc, Ioana; Malik, Rainer; Holliday, Elizabeth G; Ahmadi, Kourosh R; Paré, Guillaume; Psaty, Bruce M; Fornage, Myriam; Hasan, Nazeeha; Rinne, Paul E; Ikram, M Arfan; Markus, Hugh S; Rosand, Jonathan; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Elevated total plasma homocysteine (tHcy) levels are known to be associated with increased risk of ischemic stroke (IS). Given that both tHcy and IS are heritable traits, we investigated a potential genetic relationship between homocysteine levels and stroke risk by assessing 18 polymorphisms previously associated with tHcy levels for their association with IS and its subtypes. METHODS: Previous meta-analysis results from an international stroke collaborative network, METASTROKE, were used to assess association of the 18 tHcy-associated single-nucleotide polymorphisms (SNPs) in 12 389 IS cases and 62 004 controls. We also investigated the associations in regions located within 50 kb from the 18 tHcy-related SNPs and the association of a genetic risk score, including the 18 SNPs. RESULTS: One SNP located in the RASIP1 gene and a cluster of 3 SNPs located at and near SLC17A3 were significantly associated with IS (P<0.0003) after correcting for multiple testing. For stroke subtypes, the sentinel SNP located upstream of MUT was significantly associated with small-vessel disease (P=0.0022), whereas 1 SNP located in MTHFR was significantly associated with large-vessel disease (P=0.00019). A genetic risk score, including the 18 SNPs, did not show significant association with IS or its subtypes. CONCLUSIONS: This study found several potential associations with IS and its subtypes: an association of an MUT variant with small-vessel disease, an MTHFR variant with large-vessel disease, and associations of RASIP1 and SLC17A3 variants with overall IS.
Keywords: Brain Ischemia; Cohort Studies; Europe; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome; Homocysteine; Humans; Polymorphism, Single Nucleotide; Risk; Stroke

Effects of long-term averaging of quantitative blood pressure traits on the detection of genetic associations. - Ganesh, Santhi K; Chasman, Daniel I; Larson, Martin G; Guo, Xiuqing; Verwoert, Germain; Bis, Joshua C; Gu, Xiangjun; Smith, Albert V; Yang, Min-Lee; Zhang, Yan; Ehret, Georg; Rose, Lynda M; et al. (Am J Hum Genet, 2014)
Blood pressure (BP) is a heritable, quantitative trait with intraindividual variability and susceptibility to measurement error. Genetic studies of BP generally use single-visit measurements and thus cannot remove variability occurring over months or years. We leveraged the idea that averaging BP measured across time would improve phenotypic accuracy and thereby increase statistical power to detect genetic associations. We studied systolic BP (SBP), diastolic BP (DBP), mean arterial pressure (MAP), and pulse pressure (PP) averaged over multiple years in 46,629 individuals of European ancestry. We identified 39 trait-variant associations across 19 independent loci (p < 5 × 10(-8)); five associations (in four loci) uniquely identified by our LTA analyses included those of SBP and MAP at 2p23 (rs1275988, near KCNK3), DBP at 2q11.2 (rs7599598, in FER1L5), and PP at 6p21 (rs10948071, near CRIP3) and 7p13 (rs2949837, near IGFBP3). Replication analyses conducted in cohorts with single-visit BP data showed positive replication of associations and a nominal association (p < 0.05). We estimated a 20% gain in statistical power with long-term average (LTA) as compared to single-visit BP association studies. Using LTA analysis, we identified genetic loci influencing BP. LTA might be one way of increasing the power of genetic associations for continuous traits in extant samples for other phenotypes that are measured serially over time.
Keywords: Blood Pressure; Genome-Wide Association Study; Humans; Longitudinal Studies; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Evidence of heterogeneity by race/ethnicity in genetic determinants of QT interval. - Seyerle, Amanda A; Young, Alicia M; Jeff, Janina M; Melton, Phillip E; Jorgensen, Neal W; Lin, Yi; Carty, Cara L; Deelman, Ewa; Heckbert, Susan R; Hindorff, Lucia A; Jackson, Rebecca D; Martin, Lisa W; et al. (Epidemiology, 2014)
BACKGROUND: QT interval (QT) prolongation is an established risk factor for ventricular tachyarrhythmia and sudden cardiac death. Previous genome-wide association studies in populations of the European descent have identified multiple genetic loci that influence QT, but few have examined these loci in ethnically diverse populations. METHODS: Here, we examine the direction, magnitude, and precision of effect sizes for 21 previously reported SNPs from 12 QT loci, in populations of European (n = 16,398), African (n = 5,437), American Indian (n = 5,032), Hispanic (n = 1,143), and Asian (n = 932) descent as part of the Population Architecture using Genomics and Epidemiology (PAGE) study. Estimates obtained from linear regression models stratified by race/ethnicity were combined using inverse-variance weighted meta-analysis. Heterogeneity was evaluated using Cochran's Q test. RESULTS: Of 21 SNPs, 7 showed consistent direction of effect across all 5 populations, and an additional 9 had estimated effects that were consistent across 4 populations. Despite consistent direction of effect, 9 of 16 SNPs had evidence (P < 0.05) of heterogeneity by race/ethnicity. For these 9 SNPs, linkage disequilibrium plots often indicated substantial variation in linkage disequilibrium patterns among the various racial/ethnic groups, as well as possible allelic heterogeneity. CONCLUSIONS: These results emphasize the importance of analyzing racial/ethnic groups separately in genetic studies. Furthermore, they underscore the possible utility of trans-ethnic studies to pinpoint underlying casual variants influencing heritable traits such as QT.
Keywords: Aged; Continental Population Groups; Electrocardiography; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Long QT Syndrome; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

Gene expression in thiazide diuretic or statin users in relation to incident type 2 diabetes. - Suchy-Dicey, Astrid; Heckbert, Susan R; Smith, Nicholas L; McKnight, Barbara; Rotter, Jerome I; Chen, Yd Ida; Psaty, Bruce M; Enquobahrie, Daniel A (Int J Mol Epidemiol Genet, 2014)
Thiazide diuretics and statins are used to improve cardiovascular outcomes, but may also cause type 2 diabetes (T2DM), although mechanisms are unknown. Gene expression studies may facilitate understanding of these associations. Participants from ongoing population-based studies were sampled for these longitudinal studies of peripheral blood microarray gene expression, and followed to incident diabetes. All sampled subjects were statin or thiazide users. Those who developed diabetes during follow-up comprised cases (44 thiazide users; 19 statin users), and were matched to drug-using controls who did not develop diabetes on several factors. Supervised normalization, surrogate variable analyses removed technical bias and confounding. Differentially-expressed genes were those with a false discovery rate Q-value<0.05. Among thiazide users, diabetes cases had significantly different expression of CCL14 (down-regulated 6%, Q-value=0.0257), compared with controls. Among statin users, diabetes cases had marginal but insignificantly different expression of ZNF532 (up-regulated 15%, Q-value=0.0584), CXORF21 (up-regulated 11%, Q-value=0.0584), and ZNHIT3 (up-regulated 19%, Q-value=0.0959), compared with controls. These genes comprise potential targets for future expression or mechanistic research on medication-related diabetes development.

Gene-age interactions in blood pressure regulation: a large-scale investigation with the CHARGE, Global BPgen, and ICBP Consortia. - Simino, Jeannette; Shi, Gang; Bis, Joshua C; Chasman, Daniel I; Ehret, Georg B; Gu, Xiangjun; Guo, Xiuqing; Hwang, Shih-Jen; Sijbrands, Eric; Smith, Albert V; Verwoert, Germaine C; Bragg-Gresham, Jennifer L; et al. (Am J Hum Genet, 2014)
Although age-dependent effects on blood pressure (BP) have been reported, they have not been systematically investigated in large-scale genome-wide association studies (GWASs). We leveraged the infrastructure of three well-established consortia (CHARGE, GBPgen, and ICBP) and a nonstandard approach (age stratification and metaregression) to conduct a genome-wide search of common variants with age-dependent effects on systolic (SBP), diastolic (DBP), mean arterial (MAP), and pulse (PP) pressure. In a two-staged design using 99,241 individuals of European ancestry, we identified 20 genome-wide significant (p ≤ 5 × 10(-8)) loci by using joint tests of the SNP main effect and SNP-age interaction. Nine of the significant loci demonstrated nominal evidence of age-dependent effects on BP by tests of the interactions alone. Index SNPs in the EHBP1L1 (DBP and MAP), CASZ1 (SBP and MAP), and GOSR2 (PP) loci exhibited the largest age interactions, with opposite directions of effect in the young versus the old. The changes in the genetic effects over time were small but nonnegligible (up to 1.58 mm Hg over 60 years). The EHBP1L1 locus was discovered through gene-age interactions only in whites but had DBP main effects replicated (p = 8.3 × 10(-4)) in 8,682 Asians from Singapore, indicating potential interethnic heterogeneity. A secondary analysis revealed 22 loci with evidence of age-specific effects (e.g., only in 20 to 29-year-olds). Age can be used to select samples with larger genetic effect sizes and more homogenous phenotypes, which may increase statistical power. Age-dependent effects identified through novel statistical approaches can provide insight into the biology and temporal regulation underlying BP associations.
Keywords: Adolescent; Adult; Age Factors; Aged; Blood Pressure; Cohort Studies; Humans; Middle Aged; Young Adult

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic diversity is a predictor of mortality in humans. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Lunetta, Kathryn L; Nalls, Mike; Smith, Jennifer A; Tanaka, Toshiko; Davies, Gail; Yu, Lei; Mirza, Saira Saeed; Teumer, Alexander; Coresh, Josef; et al. (BMC Genet, 2014)
BACKGROUND: It has been well-established, both by population genetics theory and direct observation in many organisms, that increased genetic diversity provides a survival advantage. However, given the limitations of both sample size and genome-wide metrics, this hypothesis has not been comprehensively tested in human populations. Moreover, the presence of numerous segregating small effect alleles that influence traits that directly impact health directly raises the question as to whether global measures of genomic variation are themselves associated with human health and disease. RESULTS: We performed a meta-analysis of 17 cohorts followed prospectively, with a combined sample size of 46,716 individuals, including a total of 15,234 deaths. We find a significant association between increased heterozygosity and survival (P = 0.03). We estimate that within a single population, every standard deviation of heterozygosity an individual has over the mean decreases that person's risk of death by 1.57%. CONCLUSIONS: This effect was consistent between European and African ancestry cohorts, men and women, and major causes of death (cancer and cardiovascular disease), demonstrating the broad positive impact of genomic diversity on human survival.
Keywords: Genome-Wide Association Study; Heterozygote; Humans; Mortality; Polymorphism, Single Nucleotide; Proportional Hazards Models

Genetic variants related to height and risk of atrial fibrillation: the cardiovascular health study. - Rosenberg, Michael A; Kaplan, Robert C; Siscovick, David S; Psaty, Bruce M; Heckbert, Susan R; Newton-Cheh, Christopher; Mukamal, Kenneth J (Am J Epidemiol, 2014)
Increased height is a known independent risk factor for atrial fibrillation (AF). However, whether genetic determinants of height influence risk is uncertain. In this candidate gene study, we examined the association of 209 height-associated single-nucleotide polymorphisms (SNPs) with incident AF in 3,309 persons of European descent from the Cardiovascular Health Study, a prospective cohort study of older adults (aged ≥ 65 years) enrolled in 1989-1990. After a median follow-up period of 13.2 years, 879 participants developed incident AF. The height-associated SNPs together explained approximately 10% of the variation in height (P = 6.0 × 10(-8)). Using an unweighted genetic height score, we found a nonsignificant association with risk of AF (per allele, hazard ratio = 1.01, 95% confidence interval: 1.00, 1.02; P = 0.06). In weighted analyses, we found that genetically predicted height was strongly associated with AF risk (per 10 cm, hazard ratio = 1.30, 95% confidence interval: 1.03, 1.64; P = 0.03). Importantly, for all models, the inclusion of actual height completely attenuated the genetic height effect. Finally, we identified 1 nonsynonymous SNP (rs1046934) that was independently associated with AF and may warrant future study. In conclusion, we found that genetic determinants of height appear to increase the risk of AF, primarily via height itself. This approach of examining SNPs associated with an intermediate phenotype should be considered as a method for identifying novel genetic targets.
Keywords: African Americans; Aged; Atrial Fibrillation; Body Height; Endonucleases; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genome-wide association analysis identifies six new loci associated with forced vital capacity. - Loth, Daan W; Soler Artigas, Maria; Gharib, Sina A; Wain, Louise V; Franceschini, Nora; Koch, Beate; Pottinger, Tess D; Smith, Albert Vernon; Duan, Qing; Oldmeadow, Chris; Lee, Mi Kyeong; Strachan, David P; et al. (Nat Genet, 2014)
Forced vital capacity (FVC), a spirometric measure of pulmonary function, reflects lung volume and is used to diagnose and monitor lung diseases. We performed genome-wide association study meta-analysis of FVC in 52,253 individuals from 26 studies and followed up the top associations in 32,917 additional individuals of European ancestry. We found six new regions associated at genome-wide significance (P < 5 × 10(-8)) with FVC in or near EFEMP1, BMP6, MIR129-2-HSD17B12, PRDM11, WWOX and KCNJ2. Two loci previously associated with spirometric measures (GSTCD and PTCH1) were related to FVC. Newly implicated regions were followed up in samples from African-American, Korean, Chinese and Hispanic individuals. We detected transcripts for all six newly implicated genes in human lung tissue. The new loci may inform mechanisms involved in lung development and the pathogenesis of restrictive lung disease.
Keywords: Cohort Studies; Databases, Genetic; Follow-Up Studies; Forced Expiratory Volume; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung Diseases; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Prognosis; Quantitative Trait Loci; Respiratory Function Tests; Spirometry; Vital Capacity

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Genome-wide association study of L-arginine and dimethylarginines reveals novel metabolic pathway for symmetric dimethylarginine. - Lüneburg, Nicole; Lieb, Wolfgang; Zeller, Tanja; Chen, Ming-Huei; Maas, Renke; Carter, Angela M; Xanthakis, Vanessa; Glazer, Nicole L; Schwedhelm, Edzard; Seshadri, Sudha; Ikram, Mohammad Arfan; Longstreth, William T; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Dimethylarginines (DMA) interfere with nitric oxide formation by inhibiting nitric oxide synthase (asymmetrical DMA [ADMA]) and l-arginine uptake into the cell (ADMA and symmetrical DMA [SDMA]). In prospective clinical studies, ADMA has been characterized as a cardiovascular risk marker, whereas SDMA is a novel marker for renal function and associated with all-cause mortality after ischemic stroke. The aim of the current study was to characterize the environmental and genetic contributions to interindividual variability of these biomarkers. METHODS AND RESULTS: This study comprised a genome-wide association analysis of 3 well-characterized population-based cohorts (Framingham Heart Study [FHS; n=2992], Gutenberg Health Study [GHS; n=4354], and Multinational Monitoring of Trends and Determinants in Cardiovascular Disease Study [MONICA]/Cooperative Health Research in the Augsburg Area, Augsburg, Bavaria, Germany [KORA] F3 [n=581]) and identified replicated loci (DDAH1, MED23, Arg1, and AGXT2) associated with the interindividual variability in ADMA, l-arginine, and SDMA. Experimental in silico and in vitro studies confirmed functional significance of the identified AGXT2 variants. Clinical outcome analysis in 384 patients of the Leeds stroke study demonstrated an association between increased plasma levels of SDMA, AGXT2 variants, and various cardiometabolic risk factors. AGXT2 variants were not associated with poststroke survival in the Leeds study or were they associated with incident stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. CONCLUSIONS: These genome-wide association study support the importance of DDAH1 and MED23/Arg1 in regulating ADMA and l-arginine metabolism, respectively, and identify a novel regulatory renal pathway for SDMA by AGXT2. AGXT2 variants might explain part of the pathogenic link between SDMA, renal function, and outcome. An association between AGXT2 variants and stroke is unclear and warrants further investigation.
Keywords: Adult; Aged; Amidohydrolases; Arginine; Binding Sites; Cohort Studies; Female; Genetic Loci; Genome-Wide Association Study; Genotype; HEK293 Cells; Humans; Male; Mediator Complex; Middle Aged; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Risk Factors; Stroke; Substrate Specificity; Transaminases

Genome-wide association study of plasma N6 polyunsaturated fatty acids within the cohorts for heart and aging research in genomic epidemiology consortium. - Guan, Weihua; Steffen, Brian T; Lemaitre, Rozenn N; Wu, Jason H Y; Tanaka, Toshiko; Manichaikul, Ani; Foy, Millennia; Rich, Stephen S; Wang, Lu; Nettleton, Jennifer A; Tang, Weihong; Gu, Xiangjun; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Omega6 (n6) polyunsaturated fatty acids (PUFAs) and their metabolites are involved in cell signaling, inflammation, clot formation, and other crucial biological processes. Genetic components, such as variants of fatty acid desaturase (FADS) genes, determine the composition of n6 PUFAs. METHODS AND RESULTS: To elucidate undiscovered biological pathways that may influence n6 PUFA composition, we conducted genome-wide association studies and meta-analyses of associations of common genetic variants with 6 plasma n6 PUFAs in 8631 white adults (55% women) across 5 prospective studies. Plasma phospholipid or total plasma fatty acids were analyzed by similar gas chromatography techniques. The n6 fatty acids linoleic acid (LA), γ-linolenic acid (GLA), dihomo-GLA, arachidonic acid, and adrenic acid were expressed as percentage of total fatty acids. We performed linear regression with robust SEs to test for single-nucleotide polymorphism-fatty acid associations, with pooling using inverse-variance-weighted meta-analysis. Novel regions were identified on chromosome 10 associated with LA (rs10740118; P=8.1×10(-9); near NRBF2), on chromosome 16 with LA, GLA, dihomo-GLA, and arachidonic acid (rs16966952; P=1.2×10(-15), 5.0×10(-11), 7.6×10(-65), and 2.4×10(-10), respectively; NTAN1), and on chromosome 6 with adrenic acid after adjustment for arachidonic acid (rs3134950; P=2.1×10(-10); AGPAT1). We confirmed previous findings of the FADS cluster on chromosome 11 with LA and arachidonic acid, and further observed novel genome-wide significant association of this cluster with GLA, dihomo-GLA, and adrenic acid (P=2.3×10(-72), 2.6×10(-151), and 6.3×10(-140), respectively). CONCLUSIONS: Our findings suggest that along with the FADS gene cluster, additional genes may influence n6 PUFA composition.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 6; Fatty Acid Desaturases; Fatty Acids, Omega-6; Female; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

Glycated hemoglobin measurement and prediction of cardiovascular disease. - Di Angelantonio, Emanuele; Gao, Pei; Khan, Hassan; Butterworth, Adam S; Wormser, David; Kaptoge, Stephen; Kondapally Seshasai, Sreenivasa Rao; Thompson, Alex; Sarwar, Nadeem; Willeit, Peter; Ridker, Paul M; Barr, Elizabeth L M; et al. (JAMA, 2014)
IMPORTANCE: The value of measuring levels of glycated hemoglobin (HbA1c) for the prediction of first cardiovascular events is uncertain. OBJECTIVE: To determine whether adding information on HbA1c values to conventional cardiovascular risk factors is associated with improvement in prediction of cardiovascular disease (CVD) risk. DESIGN, SETTING, AND PARTICIPANTS: Analysis of individual-participant data available from 73 prospective studies involving 294,998 participants without a known history of diabetes mellitus or CVD at the baseline assessment. MAIN OUTCOMES AND MEASURES: Measures of risk discrimination for CVD outcomes (eg, C-index) and reclassification (eg, net reclassification improvement) of participants across predicted 10-year risk categories of low (<5%), intermediate (5% to <7.5%), and high (≥ 7.5%) risk. RESULTS: During a median follow-up of 9.9 (interquartile range, 7.6-13.2) years, 20,840 incident fatal and nonfatal CVD outcomes (13,237 coronary heart disease and 7603 stroke outcomes) were recorded. In analyses adjusted for several conventional cardiovascular risk factors, there was an approximately J-shaped association between HbA1c values and CVD risk. The association between HbA1c values and CVD risk changed only slightly after adjustment for total cholesterol and triglyceride concentrations or estimated glomerular filtration rate, but this association attenuated somewhat after adjustment for concentrations of high-density lipoprotein cholesterol and C-reactive protein. The C-index for a CVD risk prediction model containing conventional cardiovascular risk factors alone was 0.7434 (95% CI, 0.7350 to 0.7517). The addition of information on HbA1c was associated with a C-index change of 0.0018 (0.0003 to 0.0033) and a net reclassification improvement of 0.42 (-0.63 to 1.48) for the categories of predicted 10-year CVD risk. The improvement provided by HbA1c assessment in prediction of CVD risk was equal to or better than estimated improvements for measurement of fasting, random, or postload plasma glucose levels. CONCLUSIONS AND RELEVANCE: In a study of individuals without known CVD or diabetes, additional assessment of HbA1c values in the context of CVD risk assessment provided little incremental benefit for prediction of CVD risk.
Keywords: Aged; C-Reactive Protein; Cholesterol, HDL; Coronary Disease; Diabetes Mellitus; Female; Glycated Hemoglobin A; Humans; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Risk Assessment; Stroke

Identification of novel genetic Loci associated with thyroid peroxidase antibodies and clinical thyroid disease. - Medici, Marco; Porcu, Eleonora; Pistis, Giorgio; Teumer, Alexander; Brown, Suzanne J; Jensen, Richard A; Rawal, Rajesh; Roef, Greet L; Plantinga, Theo S; Vermeulen, Sita H; Lahti, Jari; Simmonds, Matthew J; et al. (PLoS Genet, 2014)
Autoimmune thyroid diseases (AITD) are common, affecting 2-5% of the general population. Individuals with positive thyroid peroxidase antibodies (TPOAbs) have an increased risk of autoimmune hypothyroidism (Hashimoto's thyroiditis), as well as autoimmune hyperthyroidism (Graves' disease). As the possible causative genes of TPOAbs and AITD remain largely unknown, we performed GWAS meta-analyses in 18,297 individuals for TPOAb-positivity (1769 TPOAb-positives and 16,528 TPOAb-negatives) and in 12,353 individuals for TPOAb serum levels, with replication in 8,990 individuals. Significant associations (P<5×10(-8)) were detected at TPO-rs11675434, ATXN2-rs653178, and BACH2-rs10944479 for TPOAb-positivity, and at TPO-rs11675434, MAGI3-rs1230666, and KALRN-rs2010099 for TPOAb levels. Individual and combined effects (genetic risk scores) of these variants on (subclinical) hypo- and hyperthyroidism, goiter and thyroid cancer were studied. Individuals with a high genetic risk score had, besides an increased risk of TPOAb-positivity (OR: 2.18, 95% CI 1.68-2.81, P = 8.1×10(-8)), a higher risk of increased thyroid-stimulating hormone levels (OR: 1.51, 95% CI 1.26-1.82, P = 2.9×10(-6)), as well as a decreased risk of goiter (OR: 0.77, 95% CI 0.66-0.89, P = 6.5×10(-4)). The MAGI3 and BACH2 variants were associated with an increased risk of hyperthyroidism, which was replicated in an independent cohort of patients with Graves' disease (OR: 1.37, 95% CI 1.22-1.54, P = 1.2×10(-7) and OR: 1.25, 95% CI 1.12-1.39, P = 6.2×10(-5)). The MAGI3 variant was also associated with an increased risk of hypothyroidism (OR: 1.57, 95% CI 1.18-2.10, P = 1.9×10(-3)). This first GWAS meta-analysis for TPOAbs identified five newly associated loci, three of which were also associated with clinical thyroid disease. With these markers we identified a large subgroup in the general population with a substantially increased risk of TPOAbs. The results provide insight into why individuals with thyroid autoimmunity do or do not eventually develop thyroid disease, and these markers may therefore predict which TPOAb-positives are particularly at risk of developing clinical thyroid dysfunction.
Keywords: Autoantibodies; Genetic Loci; Genome-Wide Association Study; Graves Disease; Hashimoto Disease; Humans; Iodide Peroxidase; Risk Factors; Thyroiditis, Autoimmune; Thyrotropin

Integrating genetic, transcriptional, and functional analyses to identify 5 novel genes for atrial fibrillation. - Sinner, Moritz F; Tucker, Nathan R; Lunetta, Kathryn L; Ozaki, Kouichi; Smith, J Gustav; Trompet, Stella; Bis, Joshua C; Lin, Honghuang; Chung, Mina K; Nielsen, Jonas B; Lubitz, Steven A; Krijthe, Bouwe P; et al. (Circulation, 2014)
BACKGROUND: Atrial fibrillation (AF) affects >30 million individuals worldwide and is associated with an increased risk of stroke, heart failure, and death. AF is highly heritable, yet the genetic basis for the arrhythmia remains incompletely understood. METHODS AND RESULTS: To identify new AF-related genes, we used a multifaceted approach, combining large-scale genotyping in 2 ethnically distinct populations, cis-eQTL (expression quantitative trait loci) mapping, and functional validation. Four novel loci were identified in individuals of European descent near the genes NEURL (rs12415501; relative risk [RR]=1.18; 95% confidence interval [CI], 1.13-1.23; P=6.5×10(-16)), GJA1 (rs13216675; RR=1.10; 95% CI, 1.06-1.14; P=2.2×10(-8)), TBX5 (rs10507248; RR=1.12; 95% CI, 1.08-1.16; P=5.7×10(-11)), and CAND2 (rs4642101; RR=1.10; 95% CI, 1.06-1.14; P=9.8×10(-9)). In Japanese, novel loci were identified near NEURL (rs6584555; RR=1.32; 95% CI, 1.26-1.39; P=2.0×10(-25)) and CUX2 (rs6490029; RR=1.12; 95% CI, 1.08-1.16; P=3.9×10(-9)). The top single-nucleotide polymorphisms or their proxies were identified as cis-eQTLs for the genes CAND2 (P=2.6×10(-19)), GJA1 (P=2.66×10(-6)), and TBX5 (P=1.36×10(-5)). Knockdown of the zebrafish orthologs of NEURL and CAND2 resulted in prolongation of the atrial action potential duration (17% and 45%, respectively). CONCLUSIONS: We have identified 5 novel loci for AF. Our results expand the diversity of genetic pathways implicated in AF and provide novel molecular targets for future biological and pharmacological investigation.
Keywords: Aged; Animals; Atrial Fibrillation; Chromosome Mapping; Connexin 43; Europe; Female; Gene Knockdown Techniques; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Muscle Proteins; Nuclear Proteins; Quantitative Trait Loci; Repressor Proteins; T-Box Domain Proteins; Transcription Factors; Ubiquitin-Protein Ligases; Zebrafish; Zebrafish Proteins

Large-scale genome-wide association studies and meta-analyses of longitudinal change in adult lung function. - Tang, Wenbo; Kowgier, Matthew; Loth, Daan W; Soler Artigas, Maria; Joubert, Bonnie R; Hodge, Emily; Gharib, Sina A; Smith, Albert V; Ruczinski, Ingo; Gudnason, Vilmundur; Mathias, Rasika A; Harris, Tamara B; et al. (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified numerous loci influencing cross-sectional lung function, but less is known about genes influencing longitudinal change in lung function. METHODS: We performed GWAS of the rate of change in forced expiratory volume in the first second (FEV1) in 14 longitudinal, population-based cohort studies comprising 27,249 adults of European ancestry using linear mixed effects model and combined cohort-specific results using fixed effect meta-analysis to identify novel genetic loci associated with longitudinal change in lung function. Gene expression analyses were subsequently performed for identified genetic loci. As a secondary aim, we estimated the mean rate of decline in FEV1 by smoking pattern, irrespective of genotypes, across these 14 studies using meta-analysis. RESULTS: The overall meta-analysis produced suggestive evidence for association at the novel IL16/STARD5/TMC3 locus on chromosome 15 (P  =  5.71 × 10(-7)). In addition, meta-analysis using the five cohorts with ≥3 FEV1 measurements per participant identified the novel ME3 locus on chromosome 11 (P  =  2.18 × 10(-8)) at genome-wide significance. Neither locus was associated with FEV1 decline in two additional cohort studies. We confirmed gene expression of IL16, STARD5, and ME3 in multiple lung tissues. Publicly available microarray data confirmed differential expression of all three genes in lung samples from COPD patients compared with controls. Irrespective of genotypes, the combined estimate for FEV1 decline was 26.9, 29.2 and 35.7 mL/year in never, former, and persistent smokers, respectively. CONCLUSIONS: In this large-scale GWAS, we identified two novel genetic loci in association with the rate of change in FEV1 that harbor candidate genes with biologically plausible functional links to lung function.
Keywords: Adult; Chromosomes, Human, Pair 11; Female; Gene Expression Regulation; Genetic Loci; Genome-Wide Association Study; Humans; Longitudinal Studies; Male; Respiration

Loss-of-function mutations in APOC3, triglycerides, and coronary disease. - Crosby, Jacy; Peloso, Gina M; Auer, Paul L; Crosslin, David R; Stitziel, Nathan O; Lange, Leslie A; Lu, Yingchang; Tang, Zheng-Zheng; Zhang, He; Hindy, George; Masca, Nicholas; Stirrups, Kathleen; et al. (N Engl J Med, 2014)
BACKGROUND: Plasma triglyceride levels are heritable and are correlated with the risk of coronary heart disease. Sequencing of the protein-coding regions of the human genome (the exome) has the potential to identify rare mutations that have a large effect on phenotype. METHODS: We sequenced the protein-coding regions of 18,666 genes in each of 3734 participants of European or African ancestry in the Exome Sequencing Project. We conducted tests to determine whether rare mutations in coding sequence, individually or in aggregate within a gene, were associated with plasma triglyceride levels. For mutations associated with triglyceride levels, we subsequently evaluated their association with the risk of coronary heart disease in 110,970 persons. RESULTS: An aggregate of rare mutations in the gene encoding apolipoprotein C3 (APOC3) was associated with lower plasma triglyceride levels. Among the four mutations that drove this result, three were loss-of-function mutations: a nonsense mutation (R19X) and two splice-site mutations (IVS2+1G→A and IVS3+1G→T). The fourth was a missense mutation (A43T). Approximately 1 in 150 persons in the study was a heterozygous carrier of at least one of these four mutations. Triglyceride levels in the carriers were 39% lower than levels in noncarriers (P<1×10(-20)), and circulating levels of APOC3 in carriers were 46% lower than levels in noncarriers (P=8×10(-10)). The risk of coronary heart disease among 498 carriers of any rare APOC3 mutation was 40% lower than the risk among 110,472 noncarriers (odds ratio, 0.60; 95% confidence interval, 0.47 to 0.75; P=4×10(-6)). CONCLUSIONS: Rare mutations that disrupt APOC3 function were associated with lower levels of plasma triglycerides and APOC3. Carriers of these mutations were found to have a reduced risk of coronary heart disease. (Funded by the National Heart, Lung, and Blood Institute and others.).
Keywords: African Continental Ancestry Group; Apolipoprotein C-III; Coronary Disease; European Continental Ancestry Group; Exome; Genotype; Heterozygote; Humans; Liver; Mutation; Risk Factors; Sequence Analysis, DNA; Triglycerides

A low-frequency variant in MAPK14 provides mechanistic evidence of a link with myeloperoxidase: a prognostic cardiovascular risk marker. - Waterworth, Dawn M; Li, Li; Scott, Robert; Warren, Liling; Gillson, Christopher; Aponte, Jennifer; Sarov-Blat, Lea; Sprecher, Dennis; Dupuis, Josée; Reiner, Alex; Psaty, Bruce M; Tracy, Russell P; et al. (J Am Heart Assoc, 2014)
BACKGROUND: Genetics can be used to predict drug effects and generate hypotheses around alternative indications. To support Losmapimod, a p38 mitogen-activated protein kinase inhibitor in development for acute coronary syndrome, we characterized gene variation in MAPK11/14 genes by exome sequencing and follow-up genotyping or imputation in participants well-phenotyped for cardiovascular and metabolic traits. METHODS AND RESULTS: Investigation of genetic variation in MAPK11 and MAPK14 genes using additive genetic models in linear or logistic regression with cardiovascular, metabolic, and biomarker phenotypes highlighted an association of RS2859144 in MAPK14 with myeloperoxidase in a dyslipidemic population (Genetic Epidemiology of Metabolic Syndrome Study), P=2.3×10(-6)). This variant (or proxy) was consistently associated with myeloperoxidase in the Framingham Heart Study and Cardiovascular Health Study studies (replication meta-P=0.003), leading to a meta-P value of 9.96×10(-7) in the 3 dyslipidemic groups. The variant or its proxy was then profiled in additional population-based cohorts (up to a total of 58 930 subjects) including Cohorte Lausannoise, Ely, Fenland, European Prospective Investigation of Cancer, London Life Sciences Prospective Population Study, and the Genetics of Obesity Associations study obesity case-control for up to 40 cardiovascular and metabolic traits. Overall analysis identified the same single nucleotide polymorphisms to be nominally associated consistently with glomerular filtration rate (P=0.002) and risk of obesity (body mass index ≥30 kg/m(2), P=0.004). CONCLUSIONS: As myeloperoxidase is a prognostic marker of coronary events, the MAPK14 variant may provide a mechanistic link between p38 map kinase and these events, providing information consistent with current indication of Losmapimod for acute coronary syndrome. If replicated, the association with glomerular filtration rate, along with previous biological findings, also provides support for kidney diseases as alternative indications.
Keywords: Adult; Aged; Cardiovascular Diseases; Dyslipidemias; Exome; Female; Genotype; Humans; Linear Models; Logistic Models; Male; Metabolic Syndrome X; Middle Aged; Mitogen-Activated Protein Kinase 11; Mitogen-Activated Protein Kinase 14; Obesity; Peroxidase; Polymorphism, Single Nucleotide; Prognosis; Risk Factors; Sequence Analysis, DNA

Meta-analysis of genome-wide association studies in African Americans provides insights into the genetic architecture of type 2 diabetes. - Ng, Maggie C Y; Shriner, Daniel; Chen, Brian H; Li, Jiang; Chen, Wei-Min; Guo, Xiuqing; Liu, Jiankang; Bielinski, Suzette J; Yanek, Lisa R; Nalls, Michael A; Comeau, Mary E; Rasmussen-Torvik, Laura J; et al. (PLoS Genet, 2014)
Type 2 diabetes (T2D) is more prevalent in African Americans than in Europeans. However, little is known about the genetic risk in African Americans despite the recent identification of more than 70 T2D loci primarily by genome-wide association studies (GWAS) in individuals of European ancestry. In order to investigate the genetic architecture of T2D in African Americans, the MEta-analysis of type 2 DIabetes in African Americans (MEDIA) Consortium examined 17 GWAS on T2D comprising 8,284 cases and 15,543 controls in African Americans in stage 1 analysis. Single nucleotide polymorphisms (SNPs) association analysis was conducted in each study under the additive model after adjustment for age, sex, study site, and principal components. Meta-analysis of approximately 2.6 million genotyped and imputed SNPs in all studies was conducted using an inverse variance-weighted fixed effect model. Replications were performed to follow up 21 loci in up to 6,061 cases and 5,483 controls in African Americans, and 8,130 cases and 38,987 controls of European ancestry. We identified three known loci (TCF7L2, HMGA2 and KCNQ1) and two novel loci (HLA-B and INS-IGF2) at genome-wide significance (4.15 × 10(-94)<P<5 × 10(-8), odds ratio (OR)  = 1.09 to 1.36). Fine-mapping revealed that 88 of 158 previously identified T2D or glucose homeostasis loci demonstrated nominal to highly significant association (2.2 × 10(-23) < locus-wide P<0.05). These novel and previously identified loci yielded a sibling relative risk of 1.19, explaining 17.5% of the phenotypic variance of T2D on the liability scale in African Americans. Overall, this study identified two novel susceptibility loci for T2D in African Americans. A substantial number of previously reported loci are transferable to African Americans after accounting for linkage disequilibrium, enabling fine mapping of causal variants in trans-ethnic meta-analysis studies.
Keywords: African Americans; Diabetes Mellitus, Type 2; Genome-Wide Association Study; HLA-B27 Antigen; HMGA2 Protein; Humans; KCNQ1 Potassium Channel; Mutant Chimeric Proteins; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Multilocus genetic risk score associates with ischemic stroke in case-control and prospective cohort studies. - Malik, Rainer; Bevan, Steve; Nalls, Michael A; Holliday, Elizabeth G; Devan, William J; Cheng, Yu-Ching; Ibrahim-Verbaas, Carla A; Verhaaren, Benjamin F J; Bis, Joshua C; Joon, Aron Y; de Stefano, Anita L; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Genome-wide association studies have revealed multiple common variants associated with known risk factors for ischemic stroke (IS). However, their aggregate effect on risk is uncertain. We aimed to generate a multilocus genetic risk score (GRS) for IS based on genome-wide association studies data from clinical-based samples and to establish its external validity in prospective population-based cohorts. METHODS: Three thousand five hundred forty-eight clinic-based IS cases and 6399 controls from the Wellcome Trust Case Control Consortium 2 were used for derivation of the GRS. Subjects from the METASTROKE consortium served as a replication sample. The validation sample consisted of 22 751 participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. We selected variants that had reached genome-wide significance in previous association studies on established risk factors for IS. RESULTS: A combined GRS for atrial fibrillation, coronary artery disease, hypertension, and systolic blood pressure significantly associated with IS both in the case-control samples and in the prospective population-based studies. Subjects in the top quintile of the combined GRS had >2-fold increased risk of IS compared with subjects in the lowest quintile. Addition of the combined GRS to a simple model based on sex significantly improved the prediction of IS in the combined clinic-based samples but not in the population-based studies, and there was no significant improvement in net reclassification. CONCLUSIONS: A multilocus GRS based on common variants for established cardiovascular risk factors was significantly associated with IS both in clinic-based samples and in the general population. However, the improvement in clinical risk prediction was found to be small.
Keywords: Adult; Aged; Aged, 80 and over; Atrial Fibrillation; Blood Pressure; Brain Ischemia; Case-Control Studies; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Multilocus Sequence Typing; Polymorphism, Single Nucleotide; Population; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke

Novel genetic markers associate with atrial fibrillation risk in Europeans and Japanese. - Lubitz, Steven A; Lunetta, Kathryn L; Lin, Honghuang; Arking, Dan E; Trompet, Stella; Li, Guo; Krijthe, Bouwe P; Chasman, Daniel I; Barnard, John; Kleber, Marcus E; Dörr, Marcus; Ozaki, Kouichi; et al. (J Am Coll Cardiol, 2014)
OBJECTIVES: This study sought to identify nonredundant atrial fibrillation (AF) genetic susceptibility signals and examine their cumulative relations with AF risk. BACKGROUND: AF-associated loci span broad genomic regions that may contain multiple susceptibility signals. Whether multiple signals exist at AF loci has not been systematically explored. METHODS: We performed association testing conditioned on the most significant, independently associated genetic markers at 9 established AF loci using 2 complementary techniques in 64,683 individuals of European ancestry (3,869 incident and 3,302 prevalent AF cases). Genetic risk scores were created and tested for association with AF in Europeans and an independent sample of 11,309 individuals of Japanese ancestry (7,916 prevalent AF cases). RESULTS: We observed at least 4 distinct AF susceptibility signals on chromosome 4q25 upstream of PITX2, but not at the remaining 8 AF loci. A multilocus score comprised 12 genetic markers demonstrated an estimated 5-fold gradient in AF risk. We observed a similar spectrum of risk associated with these markers in Japanese. Regions containing AF signals on chromosome 4q25 displayed a greater degree of evolutionary conservation than the remainder of the locus, suggesting that they may tag regulatory elements. CONCLUSIONS: The chromosome 4q25 AF locus is architecturally complex and harbors at least 4 AF susceptibility signals in individuals of European ancestry. Similar polygenic AF susceptibility exists between Europeans and Japanese. Future work is necessary to identify causal variants, determine mechanisms by which associated loci predispose to AF, and explore whether AF susceptibility signals classify individuals at risk for AF and related morbidity.
Keywords: Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; Europe; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factors

Pharmacogenetic meta-analysis of genome-wide association studies of LDL cholesterol response to statins. - Postmus, Iris; Trompet, Stella; Deshmukh, Harshal A; Barnes, Michael R; Li, Xiaohui; Warren, Helen R; Chasman, Daniel I; Zhou, Kaixin; Arsenault, Benoit J; Donnelly, Louise A; Wiggins, Kerri L; Avery, Christy L; et al. (Nat Commun, 2014)
Statins effectively lower LDL cholesterol levels in large studies and the observed interindividual response variability may be partially explained by genetic variation. Here we perform a pharmacogenetic meta-analysis of genome-wide association studies (GWAS) in studies addressing the LDL cholesterol response to statins, including up to 18,596 statin-treated subjects. We validate the most promising signals in a further 22,318 statin recipients and identify two loci, SORT1/CELSR2/PSRC1 and SLCO1B1, not previously identified in GWAS. Moreover, we confirm the previously described associations with APOE and LPA. Our findings advance the understanding of the pharmacogenetic architecture of statin response.
Keywords: Cholesterol, LDL; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide

Plasma phospholipid and dietary α-linolenic acid, mortality, CHD and stroke: the Cardiovascular Health Study. - Fretts, Amanda M; Mozaffarian, Dariush; Siscovick, David S; Sitlani, Colleen; Psaty, Bruce M; Rimm, Eric B; Song, Xiaoling; McKnight, Barbara; Spiegelman, Donna; King, Irena B; Lemaitre, Rozenn N (Br J Nutr, 2014)
Previous studies have suggested that long-chain n-3 fatty acids derived from seafood are associated with a lower risk of mortality, CHD and stroke. Whether α-linolenic acid (ALA, 18 : 3n-3), a plant-derived long-chain essential n-3 fatty acid, is associated with a lower risk of these outcomes is unclear. The aim of the present study was to examine the associations of plasma phospholipid and dietary ALA with the risk of mortality, CHD and stroke among older adults who participated in the Cardiovascular Health Study, a cohort study of adults aged ≥ 65 years. A total of 2709 participants were included in the plasma phospholipid ALA analysis and 2583 participants were included in the dietary ALA analysis. Cox regression was used to assess the associations of plasma phospholipid and dietary ALA with the risk of mortality, incident CHD and stroke. In minimally and multivariable-adjusted models, plasma phospholipid ALA was found to be not associated with the risk of mortality, incident CHD or stroke. After adjustment for age, sex, race, enrolment site, education, smoking status, diabetes, BMI, alcohol consumption, treated hypertension and total energy intake, higher dietary ALA intake was found to be associated with a lower risk of total and non-cardiovascular mortality; on comparing the highest quintiles of dietary ALA with the lowest quintiles, the HR for total mortality and non-cardiovascular mortality were found to be 0·73 (95 % CI 0·61, 0·88) and 0·64 (95 % CI 0·52, 0·80), respectively. Dietary ALA was found to be not associated with the risk of cardiovascular mortality, incident CHD or stroke. In conclusion, the results of the present suggest study that dietary ALA, but not plasma phospholipid ALA, is associated with a lower risk of total and non-cardiovascular mortality in older adults.
Keywords: Aged; alpha-Linolenic Acid; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Diet; Female; Humans; Male; Mortality; Phospholipids; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; United States

Plasma-free fatty acids, fatty acid-binding protein 4, and mortality in older adults (from the Cardiovascular Health Study). - Miedema, Michael D; Maziarz, Marlena; Biggs, Mary L; Zieman, Susan J; Kizer, Jorge R; Ix, Joachim H; Mozaffarian, Dariush; Tracy, Russell P; Psaty, Bruce M; Siscovick, David S; Mukamal, Kenneth J; Djoussé, Luc (Am J Cardiol, 2014)
Plasma-free fatty acids (FFAs) are largely derived from adipose tissue. Elevated levels of FFA and fatty acid-binding protein 4 (FABP4), a key cytoplasmic chaperone of fatty acids, have been associated with adverse cardiovascular outcomes, but limited data are available on the relation of these biomarkers with cardiovascular and total mortality. We studied 4,707 participants with a mean age of 75 years who had plasma FFA and FABP4 measured in 1992 to 1993 as part of the Cardiovascular Health Study, an observational cohort of community-dwelling older adults. Over a median follow-up of 11.8 years, 3,555 participants died. Cox proportional hazard regression was used to determine the association between FFA, FABP4, and mortality. In fully adjusted models, FFA were associated with dose-dependent significantly higher total mortality (hazard ratio [HR] per SD: 1.14, 95% confidence interval [CI] 1.09 to 1.18), but FABP4 levels were not (HR 1.04, 95% CI 0.98 to 1.09). In a cause-specific mortality analysis, higher concentrations of FFA were associated with significantly higher risk of death because of cardiovascular disease, dementia, infection, and respiratory causes but not cancer or trauma. We did not find evidence of an interaction between FFA and FABP4 (p = 0.45), but FABP4 appeared to be associated with total mortality differentially in men and women (HR 1.17, 95% CI 1.08 to 1.26 for men; HR 1.02, 95% CI 0.96 to 1.07 for women, interaction p value <0.001). In conclusion, in a cohort of community-dwelling older subjects, elevated plasma concentrations of FFA, but not FABP4, were associated with cardiovascular and noncardiovascular mortality.
Keywords: Age Distribution; Age Factors; Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cause of Death; Fatty Acid-Binding Proteins; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Health Status; Humans; Male; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; Time Factors; United States

Predicting stroke through genetic risk functions: the CHARGE Risk Score Project. - Ibrahim-Verbaas, Carla A; Fornage, Myriam; Bis, Joshua C; Choi, Seung Hoan; Psaty, Bruce M; Meigs, James B; Rao, Madhu; Nalls, Mike; Fontes, João D; O'Donnell, Christopher J; Kathiresan, Sekar; Ehret, Georg B; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Beyond the Framingham Stroke Risk Score, prediction of future stroke may improve with a genetic risk score (GRS) based on single-nucleotide polymorphisms associated with stroke and its risk factors. METHODS: The study includes 4 population-based cohorts with 2047 first incident strokes from 22,720 initially stroke-free European origin participants aged ≥55 years, who were followed for up to 20 years. GRSs were constructed with 324 single-nucleotide polymorphisms implicated in stroke and 9 risk factors. The association of the GRS to first incident stroke was tested using Cox regression; the GRS predictive properties were assessed with area under the curve statistics comparing the GRS with age and sex, Framingham Stroke Risk Score models, and reclassification statistics. These analyses were performed per cohort and in a meta-analysis of pooled data. Replication was sought in a case-control study of ischemic stroke. RESULTS: In the meta-analysis, adding the GRS to the Framingham Stroke Risk Score, age and sex model resulted in a significant improvement in discrimination (all stroke: Δjoint area under the curve=0.016, P=2.3×10(-6); ischemic stroke: Δjoint area under the curve=0.021, P=3.7×10(-7)), although the overall area under the curve remained low. In all the studies, there was a highly significantly improved net reclassification index (P<10(-4)). CONCLUSIONS: The single-nucleotide polymorphisms associated with stroke and its risk factors result only in a small improvement in prediction of future stroke compared with the classical epidemiological risk factors for stroke.
Keywords: Age Factors; Aged; Aged, 80 and over; Area Under Curve; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; ROC Curve; Sex Factors; Stroke

Quantifying rare, deleterious variation in 12 human cytochrome P450 drug-metabolism genes in a large-scale exome dataset. - Gordon, Adam S; Tabor, Holly K; Johnson, Andrew D; Snively, Beverly M; Assimes, Themistocles L; Auer, Paul L; Ioannidis, John P A; Peters, Ulrike; Robinson, Jennifer G; Sucheston, Lara E; Wang, Danxin; Sotoodehnia, Nona; et al. (Hum Mol Genet, 2014)
The study of genetic influences on drug response and efficacy ('pharmacogenetics') has existed for over 50 years. Yet, we still lack a complete picture of how genetic variation, both common and rare, affects each individual's responses to medications. Exome sequencing is a promising alternative method for pharmacogenetic discovery as it provides information on both common and rare variation in large numbers of individuals. Using exome data from 2203 AA and 4300 Caucasian individuals through the NHLBI Exome Sequencing Project, we conducted a survey of coding variation within 12 Cytochrome P450 (CYP) genes that are collectively responsible for catalyzing nearly 75% of all known Phase I drug oxidation reactions. In addition to identifying many polymorphisms with known pharmacogenetic effects, we discovered over 730 novel nonsynonymous alleles across the 12 CYP genes of interest. These alleles include many with diverse functional effects such as premature stop codons, aberrant splicesites and mutations at conserved active site residues. Our analysis considering both novel, predicted functional alleles as well as known, actionable CYP alleles reveals that rare, deleterious variation contributes markedly to the overall burden of pharmacogenetic alleles within the populations considered, and that the contribution of rare variation to this burden is over three times greater in AA individuals as compared with Caucasians. While most of these impactful alleles are individually rare, 7.6-11.7% of individuals interrogated in the study carry at least one newly described potentially deleterious alleles in a major drug-metabolizing CYP.
Keywords: Cytochrome P-450 Enzyme System; Databases, Genetic; European Continental Ancestry Group; Exome; Humans; Pharmaceutical Preparations; Pharmacogenetics; Polymorphism, Genetic

Risk factors for cardiovascular disease across the spectrum of older age: the Cardiovascular Health Study. - Odden, Michelle C; Shlipak, Michael G; Whitson, Heather E; Katz, Ronit; Kearney, Patricia M; deFilippi, Chris; Shastri, Shani; Sarnak, Mark J; Siscovick, David S; Cushman, Mary; Psaty, Bruce M; Newman, Anne B (Atherosclerosis, 2014)
OBJECTIVE: The associations of some risk factors with cardiovascular disease (CVD) are attenuated in older age; whereas others appear robust. The present study aimed to compare CVD risk factors across older age. METHODS: Participants (n = 4883) in the Cardiovascular Health Study free of prevalent CVD, were stratified into three age groups: 65-74, 75-84, 85+ years. Traditional risk factors included systolic blood pressure (BP), LDL-cholesterol, HDL-cholesterol, obesity, and diabetes. Novel risk factors included kidney function, C-reactive protein (CRP), and N-terminal pro-B-type natriuretic peptide (NT pro-BNP). RESULTS: There were 1498 composite CVD events (stroke, myocardial infarction, and cardiovascular death) over 5 years. The associations of high systolic BP and diabetes appeared strongest, though both were attenuated with age (p-values for interaction = 0.01 and 0.002, respectively). The demographic-adjusted hazard ratios (HR) for elevated systolic BP were 1.79 (95% confidence interval: 1.49, 2.15), 1.59 (1.37, 1.85) and 1.10 (0.86, 1.41) in participants aged 65-74, 75-84, 85+, and for diabetes, 2.36 (1.89, 2.95), 1.55 (1.27, 1.89), 1.51 (1.10, 2.09). The novel risk factors had consistent associations with the outcome across the age spectrum; low kidney function: 1.69 (1.31, 2.19), 1.61 (1.36, 1.90), and 1.57 (1.16, 2.14) for 65-74, 75-84, and 85+ years, respectively; elevated CRP: 1.54 (1.28, 1.87), 1.33 (1.13, 1.55), and 1.51 (1.15, 1.97); elevated NT pro-BNP: 2.67 (1.96, 3.64), 2.71 (2.25, 3.27), and 2.18 (1.43, 3.45). CONCLUSIONS: The associations of most traditional risk factors with CVD were minimal in the oldest old, whereas diabetes, eGFR, CRP, and NT pro-BNP were associated with CVD across older age.
Keywords: Aged; Aged, 80 and over; Blood Pressure; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Diabetes Complications; Diabetes Mellitus; Female; Humans; Inflammation; Kidney; Kidney Diseases; Lipids; Male; Natriuretic Peptide, Brain; Obesity; Peptide Fragments; Risk Factors

Separate prediction of intracerebral hemorrhage and ischemic stroke. - Ferket, Bart S; van Kempen, Bob J H; Wieberdink, Renske G; Steyerberg, Ewout W; Koudstaal, Peter J; Hofman, Albert; Shahar, Eyal; Gottesman, Rebecca F; Rosamond, Wayne; Kizer, Jorge R; Kronmal, Richard A; Psaty, Bruce M; et al. (Neurology, 2014)
OBJECTIVES: To develop and validate 10-year cumulative incidence functions of intracerebral hemorrhage (ICH) and ischemic stroke (IS). METHODS: We used data on 27,493 participants from 3 population-based cohort studies: the Atherosclerosis Risk in Communities Study, median age 54 years, 45% male, median follow-up 20.7 years; the Rotterdam Study, median age 68 years, 38% male, median follow-up 14.3 years; and the Cardiovascular Health Study, median age 71 years, 41% male, median follow-up 12.8 years. Among these participants, 325 ICH events, 2,559 IS events, and 9,909 nonstroke deaths occurred. We developed 10-year cumulative incidence functions for ICH and IS using stratified Cox regression and competing risks analysis. Basic models including only established nonlaboratory risk factors were extended with diastolic blood pressure, total cholesterol/high-density lipoprotein cholesterol ratio, body mass index, waist-to-hip ratio, and glomerular filtration rate. The cumulative incidence functions' performances were cross-validated in each cohort separately by Harrell C-statistic and calibration plots. RESULTS: High total cholesterol/high-density lipoprotein cholesterol ratio decreased the ICH rates but increased IS rates (p for difference across stroke types <0.001). For both the ICH and IS models, C statistics increased more by model extension in the Atherosclerosis Risk in Communities and Cardiovascular Health Study cohorts. Improvements in C statistics were reproduced by cross-validation. Models were well calibrated in all cohorts. Correlations between 10-year ICH and IS risks were moderate in each cohort. CONCLUSIONS: We developed and cross-validated cumulative incidence functions for separate prediction of 10-year ICH and IS risk. These functions can be useful to further specify an individual's stroke risk.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Body Mass Index; Brain Ischemia; Cholesterol; Female; Humans; Incidence; Intracranial Hemorrhages; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Risk Assessment; Risk Factors; Stroke

Sequence analysis of six blood pressure candidate regions in 4,178 individuals: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) targeted sequencing study. - Morrison, Alanna C; Bis, Joshua C; Hwang, Shih-Jen; Ehret, Georg B; Lumley, Thomas; Rice, Kenneth; Muzny, Donna; Gibbs, Richard A; Boerwinkle, Eric; Psaty, Bruce M; Chakravarti, Aravinda; Levy, Daniel (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) identified multiple loci for blood pressure (BP) and hypertension. Six genes--ATP2B1, CACNB2, CYP17A1, JAG1, PLEKHA7, and SH2B3--were evaluated for sequence variation with large effects on systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), and mean arterial pressure (MAP). METHODS AND RESULTS: Targeted genomic sequence was determined in 4,178 European ancestry participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Common variants (≥50 minor allele copies) were evaluated individually and rare variants (minor allele frequency, MAF≤1%) were aggregated by locus. 464 common variants were identified across the 6 genes. An upstream CYP17A1 variant, rs11191416 (MAF = 0.09), was the most significant association for SBP (P = 0.0005); however the association was attenuated (P = 0.0469) after conditioning on the GWAS index single nucleotide polymorphism (SNP). A PLEKHA7 intronic variant was the strongest DBP association (rs12806040, MAF = 0.007, P = 0.0006) and was not in LD (r² = 0.01) with the GWAS SNP. A CACNB2 intronic SNP, rs1571787, was the most significant association with PP (MAF = 0.27, P = 0.0003), but was not independent from the GWAS SNP (r² = 0.34). Three variants (rs6163 and rs743572 in the CYP17A1 region and rs112467382 in PLEKHA7) were associated with BP traits (P<0.001). Rare variation, aggregately assessed in the 6 regions, was not significantly associated with BP measures. CONCLUSION: Six targeted gene regions, previously identified by GWAS, did not harbor novel variation with large effects on BP in this sample.
Keywords: Aging; Blood Pressure; Cohort Studies; Heart; Humans; Sequence Analysis

Sequencing of 2 subclinical atherosclerosis candidate regions in 3669 individuals: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Bis, Joshua C; White, Charles C; Franceschini, Nora; Brody, Jennifer; Zhang, Xiaoling; Muzny, Donna; Santibanez, Jireh; Gibbs, Richard; Liu, Xiaoming; Lin, Honghuang; Boerwinkle, Eric; Psaty, Bruce M; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Atherosclerosis, the precursor to coronary heart disease and stroke, is characterized by an accumulation of fatty cells in the arterial intimal-medial layers. Common carotid intima media thickness (cIMT) and plaque are subclinical atherosclerosis measures that predict cardiovascular disease events. Previously, genome-wide association studies demonstrated evidence for association with cIMT (SLC17A4) and plaque (PIK3CG). METHODS AND RESULTS: We sequenced 120 kb around SLC17A4 (6p22.2) and 251 kb around PIK3CG (7q22.3) among 3669 European ancestry participants from the Atherosclerosis Risk in Communities (ARIC) study, Cardiovascular Health Study (CHS), and Framingham Heart Study (FHS) in Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Primary analyses focused on 438 common variants (minor allele frequency ≥1%), which were independently meta-analyzed. A 3' untranslated region CCDC71L variant (rs2286149), upstream from PIK3CG, was the most significant finding in cIMT (P=0.00033) and plaque (P=0.0004) analyses. A SLC17A4 intronic variant was also associated with cIMT (P=0.008). Both were in low linkage disequilibrium with the genome-wide association study single nucleotide polymorphisms. Gene-based tests including T1 count and sequence kernel association test for rare variants (minor allele frequency <1%) did not yield statistically significant associations. However, we observed nominal associations for rare variants in CCDC71L and SLC17A3 with cIMT and of the entire 7q22 region with plaque (P=0.05). CONCLUSIONS: Common and rare variants in PIK3CG and SLC17A4 regions demonstrated modest association with subclinical atherosclerosis traits. Although not conclusive, these findings may help to understand the genetic architecture of regions previously implicated by genome-wide association studies and identify variants within these regions for further investigation in larger samples.
Keywords: Aged; Aged, 80 and over; Aging; Atherosclerosis; Class Ib Phosphatidylinositol 3-Kinase; Cohort Studies; European Continental Ancestry Group; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Sodium-Phosphate Cotransporter Proteins, Type I

Sequencing of SCN5A identifies rare and common variants associated with cardiac conduction: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Magnani, Jared W; Brody, Jennifer A; Prins, Bram P; Arking, Dan E; Lin, Honghuang; Yin, Xiaoyan; Liu, Ching-Ti; Morrison, Alanna C; Zhang, Feng; Spector, Tim D; Alonso, Alvaro; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The cardiac sodium channel SCN5A regulates atrioventricular and ventricular conduction. Genetic variants in this gene are associated with PR and QRS intervals. We sought to characterize further the contribution of rare and common coding variation in SCN5A to cardiac conduction. METHODS AND RESULTS: In Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study, we performed targeted exonic sequencing of SCN5A (n=3699, European ancestry individuals) and identified 4 common (minor allele frequency >1%) and 157 rare variants. Common and rare SCN5A coding variants were examined for association with PR and QRS intervals through meta-analysis of European ancestry participants from CHARGE, National Heart, Lung, and Blood Institute's Exome Sequencing Project (n=607), and the UK10K (n=1275) and by examining Exome Sequencing Project African ancestry participants (n=972). Rare coding SCN5A variants in aggregate were associated with PR interval in European and African ancestry participants (P=1.3×10(-3)). Three common variants were associated with PR and QRS interval duration among European ancestry participants and one among African ancestry participants. These included 2 well-known missense variants: rs1805124 (H558R) was associated with PR and QRS shortening in European ancestry participants (P=6.25×10(-4) and P=5.2×10(-3), respectively) and rs7626962 (S1102Y) was associated with PR shortening in those of African ancestry (P=2.82×10(-3)). Among European ancestry participants, 2 novel synonymous variants, rs1805126 and rs6599230, were associated with cardiac conduction. Our top signal, rs1805126 was associated with PR and QRS lengthening (P=3.35×10(-7) and P=2.69×10(-4), respectively) and rs6599230 was associated with PR shortening (P=2.67×10(-5)). CONCLUSIONS: By sequencing SCN5A, we identified novel common and rare coding variants associated with cardiac conduction.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Conduction System; Heart Diseases; Humans; Male; Middle Aged; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Shared genetic susceptibility to ischemic stroke and coronary artery disease: a genome-wide analysis of common variants. - Dichgans, Martin; Malik, Rainer; König, Inke R; Rosand, Jonathan; Clarke, Robert; Gretarsdottir, Solveig; Thorleifsson, Gudmar; Mitchell, Braxton D; Assimes, Themistocles L; Levi, Christopher; O'Donnell, Christopher J; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Ischemic stroke (IS) and coronary artery disease (CAD) share several risk factors and each has a substantial heritability. We conducted a genome-wide analysis to evaluate the extent of shared genetic determination of the two diseases. METHODS: Genome-wide association data were obtained from the METASTROKE, Coronary Artery Disease Genome-wide Replication and Meta-analysis (CARDIoGRAM), and Coronary Artery Disease (C4D) Genetics consortia. We first analyzed common variants reaching a nominal threshold of significance (P<0.01) for CAD for their association with IS and vice versa. We then examined specific overlap across phenotypes for variants that reached a high threshold of significance. Finally, we conducted a joint meta-analysis on the combined phenotype of IS or CAD. Corresponding analyses were performed restricted to the 2167 individuals with the ischemic large artery stroke (LAS) subtype. RESULTS: Common variants associated with CAD at P<0.01 were associated with a significant excess risk for IS and for LAS and vice versa. Among the 42 known genome-wide significant loci for CAD, 3 and 5 loci were significantly associated with IS and LAS, respectively. In the joint meta-analyses, 15 loci passed genome-wide significance (P<5×10(-8)) for the combined phenotype of IS or CAD and 17 loci passed genome-wide significance for LAS or CAD. Because these loci had prior evidence for genome-wide significance for CAD, we specifically analyzed the respective signals for IS and LAS and found evidence for association at chr12q24/SH2B3 (PIS=1.62×10(-7)) and ABO (PIS=2.6×10(-4)), as well as at HDAC9 (PLAS=2.32×10(-12)), 9p21 (PLAS=3.70×10(-6)), RAI1-PEMT-RASD1 (PLAS=2.69×10(-5)), EDNRA (PLAS=7.29×10(-4)), and CYP17A1-CNNM2-NT5C2 (PLAS=4.9×10(-4)). CONCLUSIONS: Our results demonstrate substantial overlap in the genetic risk of IS and particularly the LAS subtype with CAD.
Keywords: Brain Ischemia; Coronary Artery Disease; Data Interpretation, Statistical; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Stroke

Strategies to design and analyze targeted sequencing data: cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Lin, Honghuang; Wang, Min; Brody, Jennifer A; Bis, Joshua C; Dupuis, Josée; Lumley, Thomas; McKnight, Barbara; Rice, Kenneth M; Sitlani, Colleen M; Reid, Jeffrey G; Bressler, Jan; Liu, Xiaoming; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Genome-wide association studies have identified thousands of genetic variants that influence a variety of diseases and health-related quantitative traits. However, the causal variants underlying the majority of genetic associations remain unknown. Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study aims to follow up genome-wide association study signals and identify novel associations of the allelic spectrum of identified variants with cardiovascular-related traits. METHODS AND RESULTS: The study included 4231 participants from 3 CHARGE cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, and the Framingham Heart Study. We used a case-cohort design in which we selected both a random sample of participants and participants with extreme phenotypes for each of 14 traits. We sequenced and analyzed 77 genomic loci, which had previously been associated with ≥1 of 14 phenotypes. A total of 52 736 variants were characterized by sequencing and passed our stringent quality control criteria. For common variants (minor allele frequency ≥1%), we performed unweighted regression analyses to obtain P values for associations and weighted regression analyses to obtain effect estimates that accounted for the sampling design. For rare variants, we applied 2 approaches: collapsed aggregate statistics and joint analysis of variants using the sequence kernel association test. CONCLUSIONS: We sequenced 77 genomic loci in participants from 3 cohorts. We established a set of filters to identify high-quality variants and implemented statistical and bioinformatics strategies to analyze the sequence data and identify potentially functional variants within genome-wide association study loci.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Research Design; Sequence Analysis, DNA

Systolic and diastolic blood pressure, incident cardiovascular events, and death in elderly persons: the role of functional limitation in the Cardiovascular Health Study. - Peralta, Carmen A; Katz, Ronit; Newman, Anne B; Psaty, Bruce M; Odden, Michelle C (Hypertension, 2014)
Whether limitation in the ability to perform activities of daily living (ADL) or gait speed can identify elders in whom the association of systolic and diastolic blood pressure (DBP) with cardiovascular events (CVDs) and death differs is unclear. We evaluated whether limitation in ADL or gait speed modifies the association of systolic blood pressure or DBP with incident CVD (n=2358) and death (n=3547) in the Cardiovascular Health Study. Mean age was 78±5 and 21% reported limitation in ≥1 ADL. There were 778 CVD and 1289 deaths over 9 years. Among persons without and those with ADL limitation, systolic blood pressure was associated with incident CVD: hazard ratio [HR] (per 10-mm Hg increase) 1.08 (95% confidence interval, 1.03, 1.13) and 1.06 (0.97, 1.17), respectively. ADL modified the association of DBP with incident CVD. Among those without ADL limitation, DBP was weakly associated with incident CVD, HR 1.04 (0.79, 1.37) for DBP >80, compared with <65 mm Hg. Among those with ADL limitation, DBP was inversely associated with CVD: HR 0.65 (0.44, 0.96) for DBP 66 to 80 mm Hg and HR 0.49 (0.25, 0.94) for DBP >80, compared with DBP ≤65. Among people with ADL limitation, a DBP of 66 to 80 had the lowest risk of death, HR 0.72 (0.57, 0.91), compared with a DBP of ≤65. Associations did not vary by 15-feet walking speed. ADL can identify elders in whom diastolic hypotension is associated with higher cardiovascular risk and death. Functional status, rather than chronologic age alone, should inform design of hypertension trials in elders.
Keywords: Activities of Daily Living; African Continental Ancestry Group; Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Diastole; European Continental Ancestry Group; Female; Follow-Up Studies; Gait; Heart Rate; Humans; Incidence; Longitudinal Studies; Male; Risk Factors; Survival Rate; Systole

Targeted sequencing in candidate genes for atrial fibrillation: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Lin, Honghuang; Sinner, Moritz F; Brody, Jennifer A; Arking, Dan E; Lunetta, Kathryn L; Rienstra, Michiel; Lubitz, Steven A; Magnani, Jared W; Sotoodehnia, Nona; McKnight, Barbara; McManus, David D; Boerwinkle, Eric; et al. (Heart Rhythm, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified common genetic variants that predispose to atrial fibrillation (AF). It is unclear whether rare and low-frequency variants in genes implicated by such GWAS confer additional risk of AF. OBJECTIVE: To study the association of genetic variants with AF at GWAS top loci. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study, we selected and sequenced 77 target gene regions from GWAS loci of complex diseases or traits, including 4 genes hypothesized to be related to AF (PRRX1, CAV1, CAV2, and ZFHX3). Sequencing was performed in participants with (n = 948) and without (n = 3330) AF from the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Massachusetts General Hospital. RESULTS: One common variant (rs11265611; P = 1.70 × 10(-6)) intronic to IL6R (interleukin-6 receptor gene) was significantly associated with AF after Bonferroni correction (odds ratio 0.70; 95% confidence interval 0.58-0.85). The variant was not genotyped or imputed by prior GWAS, but it is in linkage disequilibrium (r(2) = .69) with the single-nucleotide polymorphism, with the strongest association with AF so far at this locus (rs4845625). In the rare variant joint analysis, damaging variants within the PRRX1 region showed significant association with AF after Bonferroni correction (P = .01). CONCLUSIONS: We identified 1 common single-nucleotide polymorphism and 1 gene region that were significantly associated with AF. Future sequencing efforts with larger sample sizes and more comprehensive genome coverage are anticipated to identify additional AF-related variants.
Keywords: Aged; Atrial Fibrillation; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Interleukin-6

Telomere length and the risk of atrial fibrillation: insights into the role of biological versus chronological aging. - Roberts, Jason D; Dewland, Thomas A; Longoria, James; Fitzpatrick, Annette L; Ziv, Elad; Hu, Donglei; Lin, Jue; Glidden, David V; Psaty, Bruce M; Burchard, Esteban G; Blackburn, Elizabeth H; Olgin, Jeffrey E; et al. (Circ Arrhythm Electrophysiol, 2014)
BACKGROUND: Advanced age is the most important risk factor for atrial fibrillation (AF); however, the mechanism remains unknown. Telomeres, regions of DNA that shorten with cell division, are considered reliable markers of biological aging. We sought to examine the association between leukocyte telomere length (LTL) and incident AF in a large population-based cohort using direct LTL measurements and genetic data. To further explore our findings, we compared atrial cell telomere length and LTL in cardiac surgery patients. METHODS AND RESULTS: Mean LTL and the TERT rs2736100 single nucleotide polymorphism were assessed as predictors of incident AF in the Cardiovascular Health Study (CHS). Among the surgical patients, within subject comparison of atrial cell telomere length versus LTL was assessed. Among 1639 CHS participants, we observed no relationship between mean LTL and incident AF before and after adjustment for potential confounders (adjusted hazard ratio, 1.09; 95% confidence interval: 0.92-1.29; P=0.299); chronologic age remained strongly associated with AF in the same model. No association was observed between the TERT rs2736100 single nucleotide polymorphism and incident AF (adjusted hazard ratio: 0.95; 95% confidence interval: 0.88-1.04; P=0.265). In 35 cardiac surgery patients (26 with AF), atrial cell telomere length was longer than LTL (1.19 ± 0.20 versus 1.02 ± 0.25 [T/S ratio], P<0.001), a finding that remained consistent within the AF subgroup. CONCLUSIONS: Our study revealed no evidence of an association between LTL and incident AF and no evidence of relative atrial cell telomere shortening in AF. Chronological aging independent of biological markers of aging is the primary risk factor for AF.
Keywords: Age Factors; Aged; Aging; Atrial Fibrillation; California; Cardiac Surgical Procedures; Cellular Senescence; Cross-Sectional Studies; Female; Genetic Predisposition to Disease; Humans; Incidence; Leukocytes; Male; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Telomerase; Telomere; Time Factors

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Whole-exome sequencing identifies rare and low-frequency coding variants associated with LDL cholesterol. - Lange, Leslie A; Hu, Youna; Zhang, He; Xue, Chenyi; Schmidt, Ellen M; Tang, Zheng-Zheng; Bizon, Chris; Lange, Ethan M; Smith, Joshua D; Turner, Emily H; Jun, Goo; Kang, Hyun Min; et al. (Am J Hum Genet, 2014)
Elevated low-density lipoprotein cholesterol (LDL-C) is a treatable, heritable risk factor for cardiovascular disease. Genome-wide association studies (GWASs) have identified 157 variants associated with lipid levels but are not well suited to assess the impact of rare and low-frequency variants. To determine whether rare or low-frequency coding variants are associated with LDL-C, we exome sequenced 2,005 individuals, including 554 individuals selected for extreme LDL-C (>98(th) or <2(nd) percentile). Follow-up analyses included sequencing of 1,302 additional individuals and genotype-based analysis of 52,221 individuals. We observed significant evidence of association between LDL-C and the burden of rare or low-frequency variants in PNPLA5, encoding a phospholipase-domain-containing protein, and both known and previously unidentified variants in PCSK9, LDLR and APOB, three known lipid-related genes. The effect sizes for the burden of rare variants for each associated gene were substantially higher than those observed for individual SNPs identified from GWASs. We replicated the PNPLA5 signal in an independent large-scale sequencing study of 2,084 individuals. In conclusion, this large whole-exome-sequencing study for LDL-C identified a gene not known to be implicated in LDL-C and provides unique insight into the design and analysis of similar experiments.
Keywords: Adult; Aged; Apolipoproteins E; Cholesterol, LDL; Cohort Studies; Dyslipidemias; Exome; Female; Follow-Up Studies; Gene Frequency; Genetic Code; Genome-Wide Association Study; Genotype; Humans; Lipase; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Proprotein Convertases; Receptors, LDL; Sequence Analysis, DNA; Serine Endopeptidases

Association of Cardiometabolic Multimorbidity With Mortality. - Di Angelantonio, Emanuele; Kaptoge, Stephen; Wormser, David; Willeit, Peter; Butterworth, Adam S; Bansal, Narinder; O'Keeffe, Linda M; Gao, Pei; Wood, Angela M; Burgess, Stephen; Freitag, Daniel F; Pennells, Lisa; et al. (JAMA, 2015)
IMPORTANCE: The prevalence of cardiometabolic multimorbidity is increasing. OBJECTIVE: To estimate reductions in life expectancy associated with cardiometabolic multimorbidity. DESIGN, SETTING, AND PARTICIPANTS: Age- and sex-adjusted mortality rates and hazard ratios (HRs) were calculated using individual participant data from the Emerging Risk Factors Collaboration (689,300 participants; 91 cohorts; years of baseline surveys: 1960-2007; latest mortality follow-up: April 2013; 128,843 deaths). The HRs from the Emerging Risk Factors Collaboration were compared with those from the UK Biobank (499,808 participants; years of baseline surveys: 2006-2010; latest mortality follow-up: November 2013; 7995 deaths). Cumulative survival was estimated by applying calculated age-specific HRs for mortality to contemporary US age-specific death rates. EXPOSURES: A history of 2 or more of the following: diabetes mellitus, stroke, myocardial infarction (MI). MAIN OUTCOMES AND MEASURES: All-cause mortality and estimated reductions in life expectancy. RESULTS: In participants in the Emerging Risk Factors Collaboration without a history of diabetes, stroke, or MI at baseline (reference group), the all-cause mortality rate adjusted to the age of 60 years was 6.8 per 1000 person-years. Mortality rates per 1000 person-years were 15.6 in participants with a history of diabetes, 16.1 in those with stroke, 16.8 in those with MI, 32.0 in those with both diabetes and MI, 32.5 in those with both diabetes and stroke, 32.8 in those with both stroke and MI, and 59.5 in those with diabetes, stroke, and MI. Compared with the reference group, the HRs for all-cause mortality were 1.9 (95% CI, 1.8-2.0) in participants with a history of diabetes, 2.1 (95% CI, 2.0-2.2) in those with stroke, 2.0 (95% CI, 1.9-2.2) in those with MI, 3.7 (95% CI, 3.3-4.1) in those with both diabetes and MI, 3.8 (95% CI, 3.5-4.2) in those with both diabetes and stroke, 3.5 (95% CI, 3.1-4.0) in those with both stroke and MI, and 6.9 (95% CI, 5.7-8.3) in those with diabetes, stroke, and MI. The HRs from the Emerging Risk Factors Collaboration were similar to those from the more recently recruited UK Biobank. The HRs were little changed after further adjustment for markers of established intermediate pathways (eg, levels of lipids and blood pressure) and lifestyle factors (eg, smoking, diet). At the age of 60 years, a history of any 2 of these conditions was associated with 12 years of reduced life expectancy and a history of all 3 of these conditions was associated with 15 years of reduced life expectancy. CONCLUSIONS AND RELEVANCE: Mortality associated with a history of diabetes, stroke, or MI was similar for each condition. Because any combination of these conditions was associated with multiplicative mortality risk, life expectancy was substantially lower in people with multimorbidity.
Keywords: Adult; Aged; Comorbidity; Diabetes Mellitus; Female; Humans; Life Expectancy; Male; Middle Aged; Mortality; Myocardial Infarction; Risk Factors; Stroke

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; African Americans; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Muzny, Donna; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, Andre; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; African Americans; Alleles; Coronary Disease; European Continental Ancestry Group; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation

Changes in insulin-like growth factor-I and its binding proteins are associated with diabetes mellitus in older adults. - Aneke-Nash, Chino S; Parrinello, Christina M; Rajpathak, Swapnil N; Rohan, Thomas E; Strotmeyer, Elsa S; Kritchevsky, Stephen B; Psaty, Bruce M; Bůzková, Petra; Kizer, Jorge R; Newman, Anne B; Strickler, Howard D; Kaplan, Robert C (J Am Geriatr Soc, 2015)
OBJECTIVES: To determine whether changes in insulin-like growth factor (IGF) protein levels are greater in participants with type 2 diabetes mellitus or worsening glycemia than in normoglycemic individuals over a 9-year follow-up period. DESIGN: Retrospective analysis of a cohort study. SETTING: Participants were recruited from North Carolina, California, Maryland, and Pennsylvania. PARTICIPANTS: Cardiovascular Health Study All Stars participants, a cohort study of community-dwelling adults aged 65 and older (N=897). MEASUREMENTS: Plasma IGF-I, IGF binding protein (IGFBP)-1, and IGFBP-3 levels were assessed and American Diabetes Association cut-points for impaired glucose tolerance (IGT), impaired fasting glucose (IFG), and diabetes mellitus were used to classify participants at baseline (1996-97) and follow-up (2005-06). RESULTS: At baseline, mean age was 76.3±3.6, and 18.5% had diabetes mellitus. Participants with IFG alone and IGT plus IFG had higher IGF-I levels and lower IGFBP-1 levels than those with normoglycemia or diabetes mellitus. The greatest percentage change in IGF levels occurred in those who had diabetes mellitus at baseline (9-year changes: -9.3% for IGF-I, 59.7% for IGFBP-1, -13.4% for IGFBP-3), the smallest in individuals who remained normoglycemic at follow-up (9-year changes: -3.7% for IGF-I, 25.6% for IGFBP-1, -6.4% for IGFBP-3), and intermediate in those who were normoglycemic but developed IFG at follow-up. CONCLUSION: Degrees of glycemic impairment are associated with varying degrees of change in IGF protein levels. The changes observed in the diabetes mellitus group have been previously shown to be associated with heart failure, cancer, and noncancer mortality.
Keywords: Aged; Blood Glucose; Cohort Studies; Diabetes Mellitus, Type 2; Female; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Retrospective Studies

Common variation in COL4A1/COL4A2 is associated with sporadic cerebral small vessel disease. - Rannikmae, Kristiina; Davies, Gail; Thomson, Pippa A; Bevan, Steve; Devan, William J; Falcone, Guido J; Traylor, Matthew; Anderson, Christopher D; Battey, Thomas W K; Radmanesh, Farid; Deka, Ranjan; Woo, Jessica G; et al. (Neurology, 2015)
OBJECTIVES: We hypothesized that common variants in the collagen genes COL4A1/COL4A2 are associated with sporadic forms of cerebral small vessel disease. METHODS: We conducted meta-analyses of existing genotype data among individuals of European ancestry to determine associations of 1,070 common single nucleotide polymorphisms (SNPs) in the COL4A1/COL4A2 genomic region with the following: intracerebral hemorrhage and its subtypes (deep, lobar) (1,545 cases, 1,485 controls); ischemic stroke and its subtypes (cardioembolic, large vessel disease, lacunar) (12,389 cases, 62,004 controls); and white matter hyperintensities (2,733 individuals with ischemic stroke and 9,361 from population-based cohorts with brain MRI data). We calculated a statistical significance threshold that accounted for multiple testing and linkage disequilibrium between SNPs (p < 0.000084). RESULTS: Three intronic SNPs in COL4A2 were significantly associated with deep intracerebral hemorrhage (lead SNP odds ratio [OR] 1.29, 95% confidence interval [CI] 1.14-1.46, p = 0.00003; r(2) > 0.9 between SNPs). Although SNPs associated with deep intracerebral hemorrhage did not reach our significance threshold for association with lacunar ischemic stroke (lead SNP OR 1.10, 95% CI 1.03-1.18, p = 0.0073), and with white matter hyperintensity volume in symptomatic ischemic stroke patients (lead SNP OR 1.07, 95% CI 1.01-1.13, p = 0.016), the direction of association was the same. There was no convincing evidence of association with white matter hyperintensities in population-based studies or with non-small vessel disease cerebrovascular phenotypes. CONCLUSIONS: Our results indicate an association between common variation in the COL4A2 gene and symptomatic small vessel disease, particularly deep intracerebral hemorrhage. These findings merit replication studies, including in ethnic groups of non-European ancestry.
Keywords: Cerebral Small Vessel Diseases; Collagen Type IV; Genetic Association Studies; Genetic Variation; Humans; Polymorphism, Single Nucleotide

Consumption of meat is associated with higher fasting glucose and insulin concentrations regardless of glucose and insulin genetic risk scores: a meta-analysis of 50,345 Caucasians. - Fretts, Amanda M; Follis, Jack L; Nettleton, Jennifer A; Lemaitre, Rozenn N; Ngwa, Julius S; Wojczynski, Mary K; Kalafati, Ioanna Panagiota; Varga, Tibor V; Frazier-Wood, Alexis C; Houston, Denise K; Lahti, Jari; Ericson, Ulrika; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Recent studies suggest that meat intake is associated with diabetes-related phenotypes. However, whether the associations of meat intake and glucose and insulin homeostasis are modified by genes related to glucose and insulin is unknown. OBJECTIVE: We investigated the associations of meat intake and the interaction of meat with genotype on fasting glucose and insulin concentrations in Caucasians free of diabetes mellitus. DESIGN: Fourteen studies that are part of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium participated in the analysis. Data were provided for up to 50,345 participants. Using linear regression within studies and a fixed-effects meta-analysis across studies, we examined 1) the associations of processed meat and unprocessed red meat intake with fasting glucose and insulin concentrations; and 2) the interactions of processed meat and unprocessed red meat with genetic risk score related to fasting glucose or insulin resistance on fasting glucose and insulin concentrations. RESULTS: Processed meat was associated with higher fasting glucose, and unprocessed red meat was associated with both higher fasting glucose and fasting insulin concentrations after adjustment for potential confounders [not including body mass index (BMI)]. For every additional 50-g serving of processed meat per day, fasting glucose was 0.021 mmol/L (95% CI: 0.011, 0.030 mmol/L) higher. Every additional 100-g serving of unprocessed red meat per day was associated with a 0.037-mmol/L (95% CI: 0.023, 0.051-mmol/L) higher fasting glucose concentration and a 0.049-ln-pmol/L (95% CI: 0.035, 0.063-ln-pmol/L) higher fasting insulin concentration. After additional adjustment for BMI, observed associations were attenuated and no longer statistically significant. The association of processed meat and fasting insulin did not reach statistical significance after correction for multiple comparisons. Observed associations were not modified by genetic loci known to influence fasting glucose or insulin resistance. CONCLUSION: The association of higher fasting glucose and insulin concentrations with meat consumption was not modified by an index of glucose- and insulin-related single-nucleotide polymorphisms. Six of the participating studies are registered at clinicaltrials.gov as NCT0000513 (Atherosclerosis Risk in Communities), NCT00149435 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetics of Lipid Lowering Drugs and Diet Network), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Blood Glucose; Cohort Studies; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hyperglycemia; Hyperinsulinism; Insulin; Insulin Resistance; Insulin-Secreting Cells; Meat; Meat Products; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Contribution of Major Lifestyle Risk Factors for Incident Heart Failure in Older Adults: The Cardiovascular Health Study. - Del Gobbo, Liana C; Kalantarian, Shadi; Imamura, Fumiaki; Lemaitre, Rozenn; Siscovick, David S; Psaty, Bruce M; Mozaffarian, Dariush (JACC Heart Fail, 2015)
OBJECTIVES: The goal of this study was to determine the relative contribution of major lifestyle factors on the development of heart failure (HF) in older adults. BACKGROUND: HF incurs high morbidity, mortality, and health care costs among adults ≥65 years of age, which is the most rapidly growing segment of the U.S. METHODS: We prospectively investigated separate and combined associations of lifestyle risk factors with incident HF (1,380 cases) over 21.5 years among 4,490 men and women in the Cardiovascular Health Study, which is a community-based cohort of older adults. Lifestyle factors included 4 dietary patterns (Alternative Healthy Eating Index, Dietary Approaches to Stop Hypertension, an American Heart Association 2020 dietary goals score, and a Biologic pattern, which was constructed using previous knowledge of cardiovascular disease dietary risk factors), 4 physical activity metrics (exercise intensity, walking pace, energy expended in leisure activity, and walking distance), alcohol intake, smoking, and obesity. RESULTS: No dietary pattern was associated with developing HF (p > 0.05). Walking pace and leisure activity were associated with a 26% and 22% lower risk of HF, respectively (pace >3 mph vs. <2 mph; hazard ratio [HR]: 0.74; 95% confidence interval [CI]: 0.63 to 0.86; leisure activity ≥845 kcal/week vs. <845 kcal/week; HR: 0.78; 95% CI: 0.69 to 0.87). Modest alcohol intake, maintaining a body mass index <30 kg/m(2), and not smoking were also independently associated with a lower risk of HF. Participants with ≥4 healthy lifestyle factors had a 45% (HR: 0.55; 95% CI: 0.42 to 0.74) lower risk of HF. Heterogeneity by age, sex, cardiovascular disease, hypertension medication use, and diabetes was not observed. CONCLUSIONS: Among older U.S. adults, physical activity, modest alcohol intake, avoiding obesity, and not smoking, but not dietary patterns, were associated with a lower risk of HF.
Keywords: Aged; Alcohol Drinking; Cohort Studies; Diet; Female; Heart Failure; Humans; Incidence; Male; Motor Activity; Obesity; Proportional Hazards Models; Prospective Studies; Risk Factors; Sedentary Lifestyle; Smoking; United States

Dietary fatty acids modulate associations between genetic variants and circulating fatty acids in plasma and erythrocyte membranes: Meta-analysis of nine studies in the CHARGE consortium. - Smith, Caren E; Follis, Jack L; Nettleton, Jennifer A; Foy, Millennia; Wu, Jason H Y; Ma, Yiyi; Tanaka, Toshiko; Manichakul, Ani W; Wu, Hongyu; Chu, Audrey Y; Steffen, Lyn M; Fornage, Myriam; et al. (Mol Nutr Food Res, 2015)
SCOPE: Tissue concentrations of omega-3 fatty acids may reduce cardiovascular disease risk, and genetic variants are associated with circulating fatty acids concentrations. Whether dietary fatty acids interact with genetic variants to modify circulating omega-3 fatty acids is unclear. We evaluated interactions between genetic variants and fatty acid intakes for circulating alpha-linoleic acid, eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid. METHODS AND RESULTS: We conducted meta-analyses (N = 11 668) evaluating interactions between dietary fatty acids and genetic variants (rs174538 and rs174548 in FADS1 (fatty acid desaturase 1), rs7435 in AGPAT3 (1-acyl-sn-glycerol-3-phosphate), rs4985167 in PDXDC1 (pyridoxal-dependent decarboxylase domain-containing 1), rs780094 in GCKR (glucokinase regulatory protein), and rs3734398 in ELOVL2 (fatty acid elongase 2)). Stratification by measurement compartment (plasma versus erthyrocyte) revealed compartment-specific interactions between FADS1 rs174538 and rs174548 and dietary alpha-linolenic acid and linoleic acid for docosahexaenoic acid and docosapentaenoic acid. CONCLUSION: Our findings reinforce earlier reports that genetically based differences in circulating fatty acids may be partially due to differences in the conversion of fatty acid precursors. Further, fatty acids measurement compartment may modify gene-diet relationships, and considering compartment may improve the detection of gene-fatty acids interactions for circulating fatty acid outcomes.
Keywords: Acetyltransferases; Acyltransferases; Adaptor Proteins, Signal Transducing; Carboxy-Lyases; Diet; Docosahexaenoic Acids; Eicosapentaenoic Acid; Erythrocyte Membrane; Fatty Acid Desaturases; Fatty Acids; Fatty Acids, Omega-3; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Drug-Gene Interactions of Antihypertensive Medications and Risk of Incident Cardiovascular Disease: A Pharmacogenomics Study from the CHARGE Consortium. - Bis, Joshua C; Sitlani, Colleen; Irvin, Ryan; Avery, Christy L; Smith, Albert Vernon; Sun, Fangui; Evans, Daniel S; Musani, Solomon K; Li, Xiaohui; Trompet, Stella; Krijthe, Bouwe P; Harris, Tamara B; et al. (PLoS One, 2015)
BACKGROUND: Hypertension is a major risk factor for a spectrum of cardiovascular diseases (CVD), including myocardial infarction, sudden death, and stroke. In the US, over 65 million people have high blood pressure and a large proportion of these individuals are prescribed antihypertensive medications. Although large long-term clinical trials conducted in the last several decades have identified a number of effective antihypertensive treatments that reduce the risk of future clinical complications, responses to therapy and protection from cardiovascular events vary among individuals. METHODS: Using a genome-wide association study among 21,267 participants with pharmaceutically treated hypertension, we explored the hypothesis that genetic variants might influence or modify the effectiveness of common antihypertensive therapies on the risk of major cardiovascular outcomes. The classes of drug treatments included angiotensin-converting enzyme inhibitors, beta-blockers, calcium channel blockers, and diuretics. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, each study performed array-based genome-wide genotyping, imputed to HapMap Phase II reference panels, and used additive genetic models in proportional hazards or logistic regression models to evaluate drug-gene interactions for each of four therapeutic drug classes. We used meta-analysis to combine study-specific interaction estimates for approximately 2 million single nucleotide polymorphisms (SNPs) in a discovery analysis among 15,375 European Ancestry participants (3,527 CVD cases) with targeted follow-up in a case-only study of 1,751 European Ancestry GenHAT participants as well as among 4,141 African-Americans (1,267 CVD cases). RESULTS: Although drug-SNP interactions were biologically plausible, exposures and outcomes were well measured, and power was sufficient to detect modest interactions, we did not identify any statistically significant interactions from the four antihypertensive therapy meta-analyses (Pinteraction > 5.0×10-8). Similarly, findings were null for meta-analyses restricted to 66 SNPs with significant main effects on coronary artery disease or blood pressure from large published genome-wide association studies (Pinteraction ≥ 0.01). Our results suggest that there are no major pharmacogenetic influences of common SNPs on the relationship between blood pressure medications and the risk of incident CVD.
Keywords: African Americans; Aged; Antihypertensive Agents; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Treatment Outcome

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Generalized estimating equations for genome-wide association studies using longitudinal phenotype data. - Sitlani, Colleen M; Rice, Kenneth M; Lumley, Thomas; McKnight, Barbara; Cupples, L Adrienne; Avery, Christy L; Noordam, Raymond; Stricker, Bruno H C; Whitsel, Eric A; Psaty, Bruce M (Stat Med, 2015)
Many longitudinal cohort studies have both genome-wide measures of genetic variation and repeated measures of phenotypes and environmental exposures. Genome-wide association study analyses have typically used only cross-sectional data to evaluate quantitative phenotypes and binary traits. Incorporation of repeated measures may increase power to detect associations, but also requires specialized analysis methods. Here, we discuss one such method-generalized estimating equations (GEE)-in the contexts of analysis of main effects of rare genetic variants and analysis of gene-environment interactions. We illustrate the potential for increased power using GEE analyses instead of cross-sectional analyses. We also address challenges that arise, such as the need for small-sample corrections when the minor allele frequency of a genetic variant and/or the prevalence of an environmental exposure is low. To illustrate methods for detection of gene-drug interactions on a genome-wide scale, using repeated measures data, we conduct single-study analyses and meta-analyses across studies in three large cohort studies participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium-the Atherosclerosis Risk in Communities study, the Cardiovascular Health Study, and the Rotterdam Study.
Keywords: Aged; Aging; Cardiovascular Diseases; Cohort Studies; Computer Simulation; Cross-Sectional Studies; Epidemiologic Research Design; Gene-Environment Interaction; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Longitudinal Studies; Meta-Analysis as Topic; Models, Genetic; Pharmacogenetics; Risk Assessment; United States

Genetic loci associated with circulating levels of very long-chain saturated fatty acids. - Lemaitre, Rozenn N; King, Irena B; Kabagambe, Edmond K; Wu, Jason H Y; McKnight, Barbara; Manichaikul, Ani; Guan, Weihua; Sun, Qi; Chasman, Daniel I; Foy, Millennia; Wang, Lu; Zhu, Jingwen; et al. (J Lipid Res, 2015)
Very long-chain saturated fatty acids (VLSFAs) are saturated fatty acids with 20 or more carbons. In contrast to the more abundant saturated fatty acids, such as palmitic acid, there is growing evidence that circulating VLSFAs may have beneficial biological properties. Whether genetic factors influence circulating levels of VLSFAs is not known. We investigated the association of common genetic variation with plasma phospholipid/erythrocyte levels of three VLSFAs by performing genome-wide association studies in seven population-based cohorts comprising 10,129 subjects of European ancestry. We observed associations of circulating VLSFA concentrations with common variants in two genes, serine palmitoyl-transferase long-chain base subunit 3 (SPTLC3), a gene involved in the rate-limiting step of de novo sphingolipid synthesis, and ceramide synthase 4 (CERS4). The SPTLC3 variant at rs680379 was associated with higher arachidic acid (20:0 , P = 5.81 × 10(-13)). The CERS4 variant at rs2100944 was associated with higher levels of 20:0 (P = 2.65 × 10(-40)) and in analyses that adjusted for 20:0, with lower levels of behenic acid (P = 4.22 × 10(-26)) and lignoceric acid (P = 3.20 × 10(-21)). These novel associations suggest an inter-relationship of circulating VLSFAs and sphingolipid synthesis.
Keywords: Cohort Studies; Fatty Acids; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans

Genetic loci associated with circulating phospholipid trans fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Mozaffarian, Dariush; Kabagambe, Edmond K; Johnson, Catherine O; Lemaitre, Rozenn N; Manichaikul, Ani; Sun, Qi; Foy, Millennia; Wang, Lu; Wiener, Howard; Irvin, Marguerite R; Rich, Stephen S; Wu, Hongyu; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Circulating trans fatty acids (TFAs), which cannot be synthesized by humans, are linked to adverse health outcomes. Although TFAs are obtained from diet, little is known about subsequent influences (e.g., relating to incorporation, metabolism, or intercompetition with other fatty acids) that could alter circulating concentrations and possibly modulate or mediate impacts on health. OBJECTIVE: The objective was to elucidate novel biologic pathways that may influence circulating TFAs by evaluating associations between common genetic variation and TFA biomarkers. DESIGN: We performed meta-analyses using 7 cohorts of European-ancestry participants (n = 8013) having measured genome-wide variation in single-nucleotide polymorphisms (SNPs) and circulating TFA biomarkers (erythrocyte or plasma phospholipids), including trans-16:1n-7, total trans-18:1, trans/cis-18:2, cis/trans-18:2, and trans/trans-18:2. We further evaluated SNPs with genome-wide significant associations among African Americans (n = 1082), Chinese Americans (n = 669), and Hispanic Americans (n = 657) from 2 of these cohorts. RESULTS: Among European-ancestry participants, 31 SNPs in or near the fatty acid desaturase (FADS) 1 and 2 cluster were associated with cis/trans-18:2; a top hit was rs174548 (β = 0.0035, P = 4.90 × 10(-15)), an SNP previously associated with circulating n-3 and n-6 polyunsaturated fatty acid concentrations. No significant association was identified for other TFAs. rs174548 in FADS1/2 was also associated with cis/trans-18:2 in Hispanic Americans (β = 0.0053, P = 1.05 × 10(-6)) and Chinese Americans (β = 0.0028, P = 0.002) but not African Americans (β = 0.0009, P = 0.34); however, in African Americans, fine mapping identified a top hit in FADS2 associated with cis/trans-18:2 (rs174579: β = 0.0118, P = 4.05 × 10(-5)). The association between rs174548 and cis/trans-18:2 remained significant after further adjustment for individual circulating n-3 and n-6 fatty acids, except arachidonic acid. After adjustment for arachidonic acid concentrations, the association between rs174548 and cis/trans-18:2 was nearly eliminated in European-ancestry participants (β-coefficient reduced by 86%), with similar reductions in Hispanic Americans and Chinese Americans. CONCLUSIONS: Our findings provide novel evidence for genetic regulation of cis/trans-18:2 by the FADS1/2 cluster and suggest that this regulation may be influenced/mediated by concentrations of arachidonic acid, an n-6 polyunsaturated fat.
Keywords: African Americans; Arachidonic Acid; Asian Americans; Biomarkers; European Continental Ancestry Group; Fatty Acids, Omega-6; Gene Frequency; Genetic Association Studies; Genetic Loci; Genotyping Techniques; Humans; Phospholipids; Polymorphism, Single Nucleotide; Trans Fatty Acids

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Boerwinkle, Eric; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

Genome of The Netherlands population-specific imputations identify an ABCA6 variant associated with cholesterol levels. - van Leeuwen, Elisabeth M; Karssen, Lennart C; Deelen, Joris; Isaacs, Aaron; Medina-Gómez, Carolina; Mbarek, Hamdi; Kanterakis, Alexandros; Trompet, Stella; Postmus, Iris; Verweij, Niek; van Enckevort, David J; Huffman, Jennifer E; et al. (Nat Commun, 2015)
Variants associated with blood lipid levels may be population-specific. To identify low-frequency variants associated with this phenotype, population-specific reference panels may be used. Here we impute nine large Dutch biobanks (~35,000 samples) with the population-specific reference panel created by the Genome of The Netherlands Project and perform association testing with blood lipid levels. We report the discovery of five novel associations at four loci (P value <6.61 × 10(-4)), including a rare missense variant in ABCA6 (rs77542162, p.Cys1359Arg, frequency 0.034), which is predicted to be deleterious. The frequency of this ABCA6 variant is 3.65-fold increased in the Dutch and its effect (βLDL-C=0.135, βTC=0.140) is estimated to be very similar to those observed for single variants in well-known lipid genes, such as LDLR.
Keywords: ATP-Binding Cassette Transporters; Cholesterol; Gene Frequency; Genetic Association Studies; Humans; Mutation, Missense; Netherlands

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

GWAS of longevity in CHARGE consortium confirms APOE and FOXO3 candidacy. - Broer, Linda; Buchman, Aron S; Deelen, Joris; Evans, Daniel S; Faul, Jessica D; Lunetta, Kathryn L; Sebastiani, Paola; Smith, Jennifer A; Smith, Albert V; Tanaka, Toshiko; Yu, Lei; Arnold, Alice M; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The genetic contribution to longevity in humans has been estimated to range from 15% to 25%. Only two genes, APOE and FOXO3, have shown association with longevity in multiple independent studies. METHODS: We conducted a meta-analysis of genome-wide association studies including 6,036 longevity cases, age ≥90 years, and 3,757 controls that died between ages 55 and 80 years. We additionally attempted to replicate earlier identified single nucleotide polymorphism (SNP) associations with longevity. RESULTS: In our meta-analysis, we found suggestive evidence for the association of SNPs near CADM2 (odds ratio [OR] = 0.81; p value = 9.66 × 10(-7)) and GRIK2 (odds ratio = 1.24; p value = 5.09 × 10(-8)) with longevity. When attempting to replicate findings earlier identified in genome-wide association studies, only the APOE locus consistently replicated. In an additional look-up of the candidate gene FOXO3, we found that an earlier identified variant shows a highly significant association with longevity when including published data with our meta-analysis (odds ratio = 1.17; p value = 1.85×10(-10)). CONCLUSIONS: We did not identify new genome-wide significant associations with longevity and did not replicate earlier findings except for APOE and FOXO3. Our inability to find new associations with survival to ages ≥90 years because longevity represents multiple complex traits with heterogeneous genetic underpinnings, or alternatively, that longevity may be regulated by rare variants that are not captured by standard genome-wide genotyping and imputation of common variants.
Keywords: Aged; Aged, 80 and over; Apolipoproteins E; Cell Adhesion Molecules; Cohort Studies; Female; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome-Wide Association Study; Humans; Longevity; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Kainic Acid

Habitual sleep duration is associated with BMI and macronutrient intake and may be modified by CLOCK genetic variants. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Cade, Brian E; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Lamon-Fava, Stefania; Richardson, Kris; Saxena, Richa; Scheer, Frank A J L; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Short sleep duration has been associated with greater risks of obesity, hypertension, diabetes, and cardiovascular disease. Also, common genetic variants in the human Circadian Locomotor Output Cycles Kaput (CLOCK) show associations with ghrelin and total energy intake. OBJECTIVES: We examined associations between habitual sleep duration, body mass index (BMI), and macronutrient intake and assessed whether CLOCK variants modify these associations. DESIGN: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations of sleep duration and BMI and macronutrient intake as percentages of total energy as well as interactions with CLOCK variants from 9 cohort studies including up to 14,906 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. RESULTS: We observed a significant association between sleep duration and lower BMI (β ± SE = 0.16 ± 0.04, P < 0.0001) in the overall sample; however, associations between sleep duration and relative macronutrient intake were evident in age- and sex-stratified analyses only. We observed a significant association between sleep duration and lower saturated fatty acid intake in younger (aged 20-64 y) adults (men: 0.11 ± 0.06%, P = 0.03; women: 0.10 ± 0.05%, P = 0.04) and with lower carbohydrate (-0.31 ± 0.12%, P < 0.01), higher total fat (0.18 ± 0.09%, P = 0.05), and higher PUFA (0.05 ± 0.02%, P = 0.02) intakes in older (aged 65-80 y) women. In addition, the following 2 nominally significant interactions were observed: between sleep duration and rs12649507 on PUFA intake and between sleep duration and rs6858749 on protein intake. CONCLUSIONS: Our results indicate that longer habitual sleep duration is associated with lower BMI and age- and sex-specific favorable dietary behaviors. Differences in the relative intake of specific macronutrients associated with short sleep duration could, at least in part, explain previously reported associations between short sleep duration and chronic metabolic abnormalities. In addition, the influence of obesity-associated CLOCK variants on the association between sleep duration and macronutrient intake suggests that longer habitual sleep duration could ameliorate the genetic predisposition to obesity via a favorable dietary profile.
Keywords: Adult; Body Mass Index; CLOCK Proteins; Cohort Studies; Cross-Sectional Studies; Diet; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fatty Acids, Unsaturated; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Sleep; Young Adult

Higher circulating adiponectin levels are associated with increased risk of atrial fibrillation in older adults. - Macheret, Fima; Bartz, Traci M; Djoussé, Luc; Ix, Joachim H; Mukamal, Kenneth J; Zieman, Susan J; Siscovick, David S; Tracy, Russell P; Heckbert, Susan R; Psaty, Bruce M; Kizer, Jorge R (Heart, 2015)
BACKGROUND: Adiponectin has cardioprotective properties, suggesting that lower levels seen in obesity and diabetes could heighten risk of atrial fibrillation (AF). Among older adults, however, higher adiponectin has been linked to greater incidence of adverse outcomes associated with AF, although recent reports have shown this association to be U-shaped. We postulated that higher adiponectin would be linked to increased risk for AF in older adults in a U-shaped manner. METHODS: We examined the associations of total and high-molecular-weight (HMW) adiponectin with incident AF among individuals free of prevalent cardiovascular disease (CVD) participating in a population-based cohort study of older adults (n=3190; age=74±5 years). RESULTS: During median follow-up of 11.4 years, there were 886 incident AF events. Adjusted cubic splines showed a positive and linear association between adiponectin and incident AF. After adjusting for potential confounders, including amino-terminal pro-B-type natriuretic peptide 1-76, the HR (95% CI) for AF per SD increase in total adiponectin was 1.14 (1.05 to 1.24), while that for HMW adiponectin was 1.17 (1.08 to 1.27). Additional adjustment for putative mediators, including subclinical CVD, diabetes, lipids and inflammation, did not significantly affect these estimates. CONCLUSIONS: The present findings demonstrate that higher, not lower, levels of adiponectin are independently associated with increased risk of AF in older adults despite its documented cardiometabolic benefits. Additional work is necessary to determine if adiponectin is a marker of failed counter-regulatory pathways or whether this hormone is directly harmful in the setting of or as a result of advanced age.
Keywords: Adiponectin; Age Factors; Aged; Aged, 80 and over; Aging; Atrial Fibrillation; Biomarkers; Female; Humans; Incidence; Linear Models; Male; Multivariate Analysis; Natriuretic Peptide, Brain; Peptide Fragments; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

HMG-coenzyme A reductase inhibition, type 2 diabetes, and bodyweight: evidence from genetic analysis and randomised trials. - Swerdlow, Daniel I; Preiss, David; Kuchenbaecker, Karoline B; Holmes, Michael V; Engmann, Jorgen E L; Shah, Tina; Sofat, Reecha; Stender, Stefan; Johnson, Paul C D; Scott, Robert A; Leusink, Maarten; Verweij, Niek; et al. (Lancet, 2015)
BACKGROUND: Statins increase the risk of new-onset type 2 diabetes mellitus. We aimed to assess whether this increase in risk is a consequence of inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the intended drug target. METHODS: We used single nucleotide polymorphisms in the HMGCR gene, rs17238484 (for the main analysis) and rs12916 (for a subsidiary analysis) as proxies for HMGCR inhibition by statins. We examined associations of these variants with plasma lipid, glucose, and insulin concentrations; bodyweight; waist circumference; and prevalent and incident type 2 diabetes. Study-specific effect estimates per copy of each LDL-lowering allele were pooled by meta-analysis. These findings were compared with a meta-analysis of new-onset type 2 diabetes and bodyweight change data from randomised trials of statin drugs. The effects of statins in each randomised trial were assessed using meta-analysis. FINDINGS: Data were available for up to 223 463 individuals from 43 genetic studies. Each additional rs17238484-G allele was associated with a mean 0·06 mmol/L (95% CI 0·05-0·07) lower LDL cholesterol and higher body weight (0·30 kg, 0·18-0·43), waist circumference (0·32 cm, 0·16-0·47), plasma insulin concentration (1·62%, 0·53-2·72), and plasma glucose concentration (0·23%, 0·02-0·44). The rs12916 SNP had similar effects on LDL cholesterol, bodyweight, and waist circumference. The rs17238484-G allele seemed to be associated with higher risk of type 2 diabetes (odds ratio [OR] per allele 1·02, 95% CI 1·00-1·05); the rs12916-T allele association was consistent (1·06, 1·03-1·09). In 129 170 individuals in randomised trials, statins lowered LDL cholesterol by 0·92 mmol/L (95% CI 0·18-1·67) at 1-year of follow-up, increased bodyweight by 0·24 kg (95% CI 0·10-0·38 in all trials; 0·33 kg, 95% CI 0·24-0·42 in placebo or standard care controlled trials and -0·15 kg, 95% CI -0·39 to 0·08 in intensive-dose vs moderate-dose trials) at a mean of 4·2 years (range 1·9-6·7) of follow-up, and increased the odds of new-onset type 2 diabetes (OR 1·12, 95% CI 1·06-1·18 in all trials; 1·11, 95% CI 1·03-1·20 in placebo or standard care controlled trials and 1·12, 95% CI 1·04-1·22 in intensive-dose vs moderate dose trials). INTERPRETATION: The increased risk of type 2 diabetes noted with statins is at least partially explained by HMGCR inhibition. FUNDING: The funding sources are cited at the end of the paper.
Keywords: Aged; Body Mass Index; Body Weight; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus, Type 2; Female; Genetic Testing; Humans; Hydroxymethylglutaryl CoA Reductases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic; Risk Factors

Integrative pathway genomics of lung function and airflow obstruction. - Gharib, Sina A; Loth, Daan W; Soler Artigas, Maria; Birkland, Timothy P; Wilk, Jemma B; Wain, Louise V; Brody, Jennifer A; Obeidat, Ma'en; Hancock, Dana B; Tang, Wenbo; Rawal, Rajesh; Boezen, H Marike; et al. (Hum Mol Genet, 2015)
Chronic respiratory disorders are important contributors to the global burden of disease. Genome-wide association studies (GWASs) of lung function measures have identified several trait-associated loci, but explain only a modest portion of the phenotypic variability. We postulated that integrating pathway-based methods with GWASs of pulmonary function and airflow obstruction would identify a broader repertoire of genes and processes influencing these traits. We performed two independent GWASs of lung function and applied gene set enrichment analysis to one of the studies and validated the results using the second GWAS. We identified 131 significantly enriched gene sets associated with lung function and clustered them into larger biological modules involved in diverse processes including development, immunity, cell signaling, proliferation and arachidonic acid. We found that enrichment of gene sets was not driven by GWAS-significant variants or loci, but instead by those with less stringent association P-values. Next, we applied pathway enrichment analysis to a meta-analyzed GWAS of airflow obstruction. We identified several biologic modules that functionally overlapped with those associated with pulmonary function. However, differences were also noted, including enrichment of extracellular matrix (ECM) processes specifically in the airflow obstruction study. Network analysis of the ECM module implicated a candidate gene, matrix metalloproteinase 10 (MMP10), as a putative disease target. We used a knockout mouse model to functionally validate MMP10's role in influencing lung's susceptibility to cigarette smoke-induced emphysema. By integrating pathway analysis with population-based genomics, we unraveled biologic processes underlying pulmonary function traits and identified a candidate gene for obstructive lung disease.
Keywords: Airway Obstruction; Animals; Cell Proliferation; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Immune System; Lung; Male; Metabolic Networks and Pathways; Mice; Phenotype; Polymorphism, Single Nucleotide; Signal Transduction

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

Meta-analysis of 65,734 individuals identifies TSPAN15 and SLC44A2 as two susceptibility loci for venous thromboembolism. - Germain, Marine; Chasman, Daniel I; de Haan, Hugoline; Tang, Weihong; Lindström, Sara; Weng, Lu-Chen; de Andrade, Mariza; de Visser, Marieke C H; Wiggins, Kerri L; Suchon, Pierre; Saut, Noémie; Smadja, David M; et al. (Am J Hum Genet, 2015)
Venous thromboembolism (VTE), the third leading cause of cardiovascular mortality, is a complex thrombotic disorder with environmental and genetic determinants. Although several genetic variants have been found associated with VTE, they explain a minor proportion of VTE risk in cases. We undertook a meta-analysis of genome-wide association studies (GWASs) to identify additional VTE susceptibility genes. Twelve GWASs totaling 7,507 VTE case subjects and 52,632 control subjects formed our discovery stage where 6,751,884 SNPs were tested for association with VTE. Nine loci reached the genome-wide significance level of 5 × 10(-8) including six already known to associate with VTE (ABO, F2, F5, F11, FGG, and PROCR) and three unsuspected loci. SNPs mapping to these latter were selected for replication in three independent case-control studies totaling 3,009 VTE-affected individuals and 2,586 control subjects. This strategy led to the identification and replication of two VTE-associated loci, TSPAN15 and SLC44A2, with lead risk alleles associated with odds ratio for disease of 1.31 (p = 1.67 × 10(-16)) and 1.21 (p = 2.75 × 10(-15)), respectively. The lead SNP at the TSPAN15 locus is the intronic rs78707713 and the lead SLC44A2 SNP is the non-synonymous rs2288904 previously shown to associate with transfusion-related acute lung injury. We further showed that these two variants did not associate with known hemostatic plasma markers. TSPAN15 and SLC44A2 do not belong to conventional pathways for thrombosis and have not been associated to other cardiovascular diseases nor related quantitative biomarkers. Our findings uncovered unexpected actors of VTE etiology and pave the way for novel mechanistic concepts of VTE pathophysiology.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Membrane Glycoproteins; Membrane Transport Proteins; Odds Ratio; Tetraspanins; Venous Thromboembolism

Meta-Analysis of Genome-Wide Association Studies Identifies Genetic Risk Factors for Stroke in African Americans. - Carty, Cara L; Keene, Keith L; Cheng, Yu-Ching; Meschia, James F; Chen, Wei-Min; Nalls, Mike; Bis, Joshua C; Kittner, Steven J; Rich, Stephen S; Tajuddin, Salman; Zonderman, Alan B; Evans, Michele K; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: The majority of genome-wide association studies (GWAS) of stroke have focused on European-ancestry populations; however, none has been conducted in African Americans, despite the disproportionately high burden of stroke in this population. The Consortium of Minority Population Genome-Wide Association Studies of Stroke (COMPASS) was established to identify stroke susceptibility loci in minority populations. METHODS: Using METAL, we conducted meta-analyses of GWAS in 14 746 African Americans (1365 ischemic and 1592 total stroke cases) from COMPASS, and tested genetic variants with P<10(-6) for validation in METASTROKE, a consortium of ischemic stroke genetic studies in European-ancestry populations. We also evaluated stroke loci previously identified in European-ancestry populations. RESULTS: The 15q21.3 locus linked with lipid levels and hypertension was associated with total stroke (rs4471613; P=3.9×10(-8)) in African Americans. Nominal associations (P<10(-6)) for total or ischemic stroke were observed for 18 variants in or near genes implicated in cell cycle/mRNA presplicing (PTPRG, CDC5L), platelet function (HPS4), blood-brain barrier permeability (CLDN17), immune response (ELTD1, WDFY4, and IL1F10-IL1RN), and histone modification (HDAC9). Two of these loci achieved nominal significance in METASTROKE: 5q35.2 (P=0.03), and 1p31.1 (P=0.018). Four of 7 previously reported ischemic stroke loci (PITX2, HDAC9, CDKN2A/CDKN2B, and ZFHX3) were nominally associated (P<0.05) with stroke in COMPASS. CONCLUSIONS: We identified a novel genetic variant associated with total stroke in African Americans and found that ischemic stroke loci identified in European-ancestry populations may also be relevant for African Americans. Our findings support investigation of diverse populations to identify and characterize genetic risk factors, and the importance of shared genetic risk across populations.
Keywords: African Americans; Case-Control Studies; Cohort Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors; Stroke

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Continental Population Groups; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Stroke; White Matter

Plasma Levels of Soluble Interleukin-2 Receptor α: Associations With Clinical Cardiovascular Events and Genome-Wide Association Scan. - Durda, Peter; Sabourin, Jeremy; Lange, Ethan M; Nalls, Mike A; Mychaleckyj, Josyf C; Jenny, Nancy Swords; Li, Jin; Walston, Jeremy; Harris, Tamara B; Psaty, Bruce M; Valdar, William; Liu, Yongmei; et al. (Arterioscler Thromb Vasc Biol, 2015)
OBJECTIVE: Interleukin (IL) -2 receptor subunit α regulates lymphocyte activation, which plays an important role in atherosclerosis. Associations between soluble IL-2Rα (sIL-2Rα) and cardiovascular disease (CVD) have not been widely studied and little is known about the genetic determinants of sIL-2Rα levels. APPROACH AND RESULTS: We measured baseline levels of sIL-2Rα in 4408 European American (EA) and 766 African American (AA) adults from the Cardiovascular Health Study (CHS) and examined associations with baseline CVD risk factors, subclinical CVD, and incident CVD events. We also performed a genome-wide association study for sIL-2Rα in CHS (2964 EAs and 683 AAs) and further combined CHS EA results with those from two other EA cohorts in a meta-analysis (n=4464 EAs). In age, sex- and race- adjusted models, sIL-2Rα was positively associated with current smoking, type 2 diabetes mellitus, hypertension, insulin, waist circumference, C-reactive protein, IL-6, fibrinogen, internal carotid wall thickness, all-cause mortality, CVD mortality, and incident CVD, stroke, and heart failure. When adjusted for baseline CVD risk factors and subclinical CVD, associations with all-cause mortality, CVD mortality, and heart failure remained significant in both EAs and AAs. In the EA genome-wide association study analysis, we observed 52 single-nucleotide polymorphisms in the chromosome 10p15-14 region, which contains IL2RA, IL15RA, and RMB17, that reached genome-wide significance (P<5×10(-8)). The most significant single-nucleotide polymorphism was rs7911500 (P=1.31×10(-75)). The EA meta-analysis results were highly consistent with CHS-only results. No single-nucleotide polymorphisms reached statistical significance in the AAs. CONCLUSIONS: These results support a role for sIL-2Rα in atherosclerosis and provide evidence for multiple-associated single-nucleotide polymorphisms at chromosome 10p15-14.
Keywords: Adult; African Americans; Age Distribution; Aged; Cardiovascular Diseases; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Incidence; Interleukin-2 Receptor alpha Subunit; Kaplan-Meier Estimate; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Distribution; Survival Analysis

Population genomic analysis of 962 whole genome sequences of humans reveals natural selection in non-coding regions. - Yu, Fuli; Lu, Jian; Liu, Xiaoming; Gazave, Elodie; Chang, Diana; Raj, Srilakshmi; Hunter-Zinck, Haley; Blekhman, Ran; Arbiza, Leonardo; Van Hout, Cris; Morrison, Alanna; Johnson, Andrew D; et al. (PLoS One, 2015)
Whole genome analysis in large samples from a single population is needed to provide adequate power to assess relative strengths of natural selection across different functional components of the genome. In this study, we analyzed next-generation sequencing data from 962 European Americans, and found that as expected approximately 60% of the top 1% of positive selection signals lie in intergenic regions, 33% in intronic regions, and slightly over 1% in coding regions. Several detailed functional annotation categories in intergenic regions showed statistically significant enrichment in positively selected loci when compared to the null distribution of the genomic span of ENCODE categories. There was a significant enrichment of purifying selection signals detected in enhancers, transcription factor binding sites, microRNAs and target sites, but not on lincRNA or piRNAs, suggesting different evolutionary constraints for these domains. Loci in "repressed or low activity regions" and loci near or overlapping the transcription start site were the most significantly over-represented annotations among the top 1% of signals for positive selection.
Keywords: DNA, Intergenic; Genetic Loci; Humans; Metagenomics; Open Reading Frames; Polymorphism, Single Nucleotide

Predicting Future Years of Life, Health, and Functional Ability: A Healthy Life Calculator for Older Adults. - Diehr, Paula; Diehr, Michael; Arnold, Alice; Yee, Laura M; Odden, Michelle C; Hirsch, Calvin H; Thielke, Stephen; Psaty, Bruce M; Johnson, W Craig; Kizer Md, Jorge R; Newman, Anne (Gerontol Geriatr Med, 2015)
To create personalized estimates of future health and ability status for older adults.Data came from the Cardiovascular Health Study (CHS), a large longitudinal study. Outcomes included years of life, years of healthy life (based on self-rated health), years of able life (based on activities of daily living), and years of healthy and able life. We developed regression estimates using the demographic and health characteristics that best predicted the four outcomes. Internal and external validity were assessed.A prediction equation based on 11 variables accounted for about 40% of the variability for each outcome. Internal validity was excellent, and external validity was satisfactory. The resulting CHS Healthy Life Calculator (CHSHLC) is available at http://healthylifecalculator.org.CHSHLC provides a well-documented estimate of future years of healthy and able life for older adults, who may use it in planning for the future.

Rare and low-frequency variants and their association with plasma levels of fibrinogen, FVII, FVIII, and vWF. - Huffman, Jennifer E; de Vries, Paul S; Morrison, Alanna C; Sabater-Lleal, Maria; Kacprowski, Tim; Auer, Paul L; Brody, Jennifer A; Chasman, Daniel I; Chen, Ming-Huei; Guo, Xiuqing; Lin, Li-An; Marioni, Riccardo E; et al. (Blood, 2015)
Fibrinogen, coagulation factor VII (FVII), and factor VIII (FVIII) and its carrier von Willebrand factor (vWF) play key roles in hemostasis. Previously identified common variants explain only a small fraction of the trait heritabilities, and additional variations may be explained by associations with rarer variants with larger effects. The aim of this study was to identify low-frequency (minor allele frequency [MAF] ≥0.01 and <0.05) and rare (MAF <0.01) variants that influence plasma concentrations of these 4 hemostatic factors by meta-analyzing exome chip data from up to 76,000 participants of 4 ancestries. We identified 12 novel associations of low-frequency (n = 2) and rare (n = 10) variants across the fibrinogen, FVII, FVIII, and vWF traits that were independent of previously identified associations. Novel loci were found within previously reported genes and had effect sizes much larger than and independent of previously identified common variants. In addition, associations at KCNT1, HID1, and KATNB1 identified new candidate genes related to hemostasis for follow-up replication and functional genomic analysis. Newly identified low-frequency and rare-variant associations accounted for modest amounts of trait variance and therefore are unlikely to increase predicted trait heritability but provide new information for understanding individual variation in hemostasis pathways.
Keywords: Cohort Studies; Factor VII; Factor VIII; Fibrinogen; Gene Frequency; Genetic Association Studies; Genetic Variation; Humans; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels; von Willebrand Factor

Thyroid function in the euthyroid range and adverse outcomes in older adults. - Cappola, Anne R; Arnold, Alice M; Wulczyn, Kendra; Carlson, Michelle; Robbins, John; Psaty, Bruce M (J Clin Endocrinol Metab, 2015)
CONTEXT: The appropriateness of current reference ranges for thyroid function testing in older adults has been questioned. OBJECTIVE: This study aimed to determine the relationship between thyroid function tests within the euthyroid range and adverse outcomes in older adults not taking thyroid medication. DESIGN, SETTING, AND PARTICIPANTS: US community-dwelling adults years of older (n = 2843) enrolled onto the Cardiovascular Health Study with TSH, free T4 (FT4), and total T3 concentrations in the euthyroid range. MAIN OUTCOME MEASURES: Incidence of atrial fibrillation, coronary heart disease, heart failure, hip fracture, dementia, and all-cause death were measured. RESULTS: No departures from linearity were detected. Higher TSH was negatively associated (P = .03) and higher FT4 was positively associated (P = .007) with mortality. Higher FT4 was associated with atrial fibrillation (P < .001) and heart failure (P = .004). Compared with the first quartile, individuals with TSH in the fourth quartile had a 9.6 per 1000 person-year lower incidence of dementia (P < .05) and those with FT4 in the fourth quartile had higher incidences of atrial fibrillation, coronary heart disease, heart failure, and mortality (11.0, 8.0, 7.8, and 14.3 per 1000 person-years, respectively, all P < .05). Total T3 was not associated with any outcome. CONCLUSIONS: Higher TSH and lower FT4 concentrations within the euthyroid range are associated with lower risk of multiple adverse events in older people, including mortality. This suggests tolerance for lower thyroid hormone levels in this age group. Clinical trials are needed to evaluate the risk-benefit profile of new thresholds for initiating treatment and optimal target concentrations for thyroid hormone replacement in older people.
Keywords: Aged; Aged, 80 and over; Aging; Atrial Fibrillation; Cause of Death; Coronary Disease; Dementia; Female; Heart Failure; Hip Fractures; Humans; Incidence; Male; Prognosis; Reference Values; Survival Analysis; Thyroid Function Tests; Thyroid Gland

Thyroid function within the normal range and risk of coronary heart disease: an individual participant data analysis of 14 cohorts. - Asvold, Bjørn O; Vatten, Lars J; Bjøro, Trine; Bauer, Douglas C; Bremner, Alexandra; Cappola, Anne R; Ceresini, Graziano; den Elzen, Wendy P J; Ferrucci, Luigi; Franco, Oscar H; Franklyn, Jayne A; Gussekloo, Jacobijn; et al. (JAMA Intern Med, 2015)
IMPORTANCE: Some experts suggest that serum thyrotropin levels in the upper part of the current reference range should be considered abnormal, an approach that would reclassify many individuals as having mild hypothyroidism. Health hazards associated with such thyrotropin levels are poorly documented, but conflicting evidence suggests that thyrotropin levels in the upper part of the reference range may be associated with an increased risk of coronary heart disease (CHD). OBJECTIVE: To assess the association between differences in thyroid function within the reference range and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: Individual participant data analysis of 14 cohorts with baseline examinations between July 1972 and April 2002 and with median follow-up ranging from 3.3 to 20.0 years. Participants included 55,412 individuals with serum thyrotropin levels of 0.45 to 4.49 mIU/L and no previously known thyroid or cardiovascular disease at baseline. EXPOSURES: Thyroid function as expressed by serum thyrotropin levels at baseline. MAIN OUTCOMES AND MEASURES: Hazard ratios (HRs) of CHD mortality and CHD events according to thyrotropin levels after adjustment for age, sex, and smoking status. RESULTS: Among 55,412 individuals, 1813 people (3.3%) died of CHD during 643,183 person-years of follow-up. In 10 cohorts with information on both nonfatal and fatal CHD events, 4666 of 48,875 individuals (9.5%) experienced a first-time CHD event during 533,408 person-years of follow-up. For each 1-mIU/L higher thyrotropin level, the HR was 0.97 (95% CI, 0.90-1.04) for CHD mortality and 1.00 (95% CI, 0.97-1.03) for a first-time CHD event. Similarly, in analyses by categories of thyrotropin, the HRs of CHD mortality (0.94 [95% CI, 0.74-1.20]) and CHD events (0.97 [95% CI, 0.83-1.13]) were similar among participants with the highest (3.50-4.49 mIU/L) compared with the lowest (0.45-1.49 mIU/L) thyrotropin levels. Subgroup analyses by sex and age group yielded similar results. CONCLUSIONS AND RELEVANCE: Thyrotropin levels within the reference range are not associated with risk of CHD events or CHD mortality. This finding suggests that differences in thyroid function within the population reference range do not influence the risk of CHD. Increased CHD risk does not appear to be a reason for lowering the upper thyrotropin reference limit.
Keywords: Cohort Studies; Coronary Disease; Humans; Hypothyroidism; Thyrotropin

Variation in resting heart rate over 4 years and the risks of myocardial infarction and death among older adults. - Floyd, James S; Sitlani, Colleen M; Wiggins, Kerri L; Wallace, Erin; Suchy-Dicey, Astrid; Abbasi, Siddique A; Carnethon, Mercedes R; Siscovick, David S; Sotoodehnia, Nona; Heckbert, Susan R; McKnight, Barbara; Rice, Kenneth M; et al. (Heart, 2015)
OBJECTIVE: Resting heart rate (RHR) is an established predictor of myocardial infarction (MI) and mortality, but the relationship between variation in RHR over a period of several years and health outcomes is unclear. We evaluated the relationship between long-term variation in RHR and the risks of incident MI and mortality among older adults. METHODS: 1991 subjects without cardiovascular disease from the Cardiovascular Health Study were included. RHR was taken from resting ECGs at the first five annual study visits. RHR mean, trend and variation were estimated with linear regression. Subjects were followed for incident MI and death until December 2010. HRs for RHR mean, trend and variation are reported for differences of 10 bpm, 2 bpm/year and 2 bpm, respectively. RESULTS: 262 subjects had an incident MI event (13%) and 1326 died (67%) during 12 years of median follow-up. In primary analyses adjusted for cardiovascular risk factors, RHR mean (HR 1.12; 95% CI 1.05 to 1.20) and variation (HR 1.08; 95% CI 1.03 to 1.13) were associated with the risk of death while trend was not. None of the RHR variables were significantly associated with the risk of incident MI events; however, CIs were wide and the MI associations with RHR variables were not significantly different from the mortality associations. Adjusting for additional variables did not affect estimates, and there were no significant interactions with sex. CONCLUSIONS: Variation in RHR over a period of several years represents a potential predictor of long-term mortality among older persons free of cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Cause of Death; Electrocardiography; Female; Follow-Up Studies; Heart Rate; Humans; Incidence; Linear Models; Male; Myocardial Infarction; Outcome Assessment (Health Care); Prognosis; Proportional Hazards Models; Prospective Studies; Rest; Risk Factors; Time; Washington

Ventricular Ectopy as a Predictor of Heart Failure and Death. - Dukes, Jonathan W; Dewland, Thomas A; Vittinghoff, Eric; Mandyam, Mala C; Heckbert, Susan R; Siscovick, David S; Stein, Phyllis K; Psaty, Bruce M; Sotoodehnia, Nona; Gottdiener, John S; Marcus, Gregory M (J Am Coll Cardiol, 2015)
BACKGROUND: Studies of patients presenting for catheter ablation suggest that premature ventricular contractions (PVCs) are a modifiable risk factor for congestive heart failure (CHF). The relationship among PVC frequency, incident CHF, and mortality in the general population remains unknown. OBJECTIVES: The goal of this study was to determine whether PVC frequency ascertained using a 24-h Holter monitor is a predictor of a decrease in the left ventricular ejection fraction (LVEF), incident CHF, and death in a population-based cohort. METHODS: We studied 1,139 Cardiovascular Health Study (CHS) participants who were randomly assigned to 24-h ambulatory electrocardiography (Holter) monitoring and who had a normal LVEF and no history of CHF. PVC frequency was quantified using Holter studies, and LVEF was measured from baseline and 5-year echocardiograms. Participants were followed for incident CHF and death. RESULTS: Those in the upper quartile versus the lowest quartile of PVC frequency had a multivariable-adjusted, 3-fold greater odds of a 5-year decrease in LVEF (odds ratio [OR]: 3.10; 95% confidence interval [CI]: 1.42 to 6.77; p = 0.005), a 48% increased risk of incident CHF (HR: 1.48; 95% CI: 1.08 to 2.04; p = 0.02), and a 31% increased risk of death (HR: 1.31; 95% CI: 1.06 to 1.63; p = 0.01) during a median follow-up of >13 years. Similar statistically significant results were observed for PVCs analyzed as a continuous variable. The specificity for the 15-year risk of CHF exceeded 90% when PVCs included at least 0.7% of ventricular beats. The population-level risk for incident CHF attributed to PVCs was 8.1% (95% CI: 1.2% to 14.9%). CONCLUSIONS: In a population-based sample, a higher frequency of PVCs was associated with a decrease in LVEF, an increase in incident CHF, and increased mortality. Because of the capacity to prevent PVCs through medical or ablation therapy, PVCs may represent a modifiable risk factor for CHF and death.
Keywords: Aged; Catheter Ablation; Echocardiography; Electrocardiography, Ambulatory; Female; Forecasting; Heart Failure; Humans; Male; Risk Factors; Stroke Volume; Ventricular Premature Complexes

White Matter Lesion Progression: Genome-Wide Search for Genetic Influences. - Hofer, Edith; Cavalieri, Margherita; Bis, Joshua C; DeCarli, Charles; Fornage, Myriam; Sigurdsson, Sigurdur; Srikanth, Velandai; Trompet, Stella; Verhaaren, Benjamin F J; Wolf, Christiane; Yang, Qiong; Adams, Hieab H H; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter lesion (WML) progression on magnetic resonance imaging is related to cognitive decline and stroke, but its determinants besides baseline WML burden are largely unknown. Here, we estimated heritability of WML progression, and sought common genetic variants associated with WML progression in elderly participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Heritability of WML progression was calculated in the Framingham Heart Study. The genome-wide association study included 7773 elderly participants from 10 cohorts. To assess the relative contribution of genetic factors to progression of WML, we compared in 7 cohorts risk models including demographics, vascular risk factors plus single-nucleotide polymorphisms that have been shown to be associated cross-sectionally with WML in the current and previous association studies. RESULTS: A total of 1085 subjects showed WML progression. The heritability estimate for WML progression was low at 6.5%, and no single-nucleotide polymorphisms achieved genome-wide significance (P<5×10(-8)). Four loci were suggestive (P<1×10(-5)) of an association with WML progression: 10q24.32 (rs10883817, P=1.46×10(-6)); 12q13.13 (rs4761974, P=8.71×10(-7)); 20p12.1 (rs6135309, P=3.69×10(-6)); and 4p15.31 (rs7664442, P=2.26×10(-6)). Variants that have been previously related to WML explained only 0.8% to 11.7% more of the variance in WML progression than age, vascular risk factors, and baseline WML burden. CONCLUSIONS: Common genetic factors contribute little to the progression of age-related WML in middle-aged and older adults. Future research on determinants of WML progression should focus more on environmental, lifestyle, or host-related biological factors.
Keywords: Adult; Aged; Cohort Studies; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Middle Aged; Prospective Studies; White Matter

52 Genetic Loci Influencing Myocardial Mass. - van der Harst, Pim; van Setten, Jessica; Verweij, Niek; Vogler, Georg; Franke, Lude; Maurano, Matthew T; Wang, Xinchen; Mateo Leach, Irene; Eijgelsheim, Mark; Sotoodehnia, Nona; Hayward, Caroline; Sorice, Rossella; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Myocardial mass is a key determinant of cardiac muscle function and hypertrophy. Myocardial depolarization leading to cardiac muscle contraction is reflected by the amplitude and duration of the QRS complex on the electrocardiogram (ECG). Abnormal QRS amplitude or duration reflect changes in myocardial mass and conduction, and are associated with increased risk of heart failure and death. OBJECTIVES: This meta-analysis sought to gain insights into the genetic determinants of myocardial mass. METHODS: We carried out a genome-wide association meta-analysis of 4 QRS traits in up to 73,518 individuals of European ancestry, followed by extensive biological and functional assessment. RESULTS: We identified 52 genomic loci, of which 32 are novel, that are reliably associated with 1 or more QRS phenotypes at p < 1 × 10(-8). These loci are enriched in regions of open chromatin, histone modifications, and transcription factor binding, suggesting that they represent regions of the genome that are actively transcribed in the human heart. Pathway analyses provided evidence that these loci play a role in cardiac hypertrophy. We further highlighted 67 candidate genes at the identified loci that are preferentially expressed in cardiac tissue and associated with cardiac abnormalities in Drosophila melanogaster and Mus musculus. We validated the regulatory function of a novel variant in the SCN5A/SCN10A locus in vitro and in vivo. CONCLUSIONS: Taken together, our findings provide new insights into genes and biological pathways controlling myocardial mass and may help identify novel therapeutic targets.

Association of the IGF1 gene with fasting insulin levels. - Willems, Sara M; Cornes, Belinda K; Brody, Jennifer A; Morrison, Alanna C; Lipovich, Leonard; Dauriz, Marco; Chen, Yuning; Liu, Ching-Ti; Rybin, Denis V; Gibbs, Richard A; Muzny, Donna; Pankow, James S; et al. (Eur J Hum Genet, 2016)
Insulin-like growth factor 1 (IGF-I) has been associated with insulin resistance. Genome-wide association studies (GWASs) of fasting insulin (FI) identified single-nucleotide variants (SNVs) near the IGF1 gene, raising two hypotheses: (1) these associations are mediated by IGF-I levels and (2) these noncoding variants either tag other functional variants in the region or are directly functional. In our study, analyses including 5141 individuals from population-based cohorts suggest that FI associations near IGF1 are not mediated by IGF-I. Analyses of targeted sequencing data in 3539 individuals reveal a large number of novel rare variants at the IGF1 locus and show a FI association with a subset of rare nonsynonymous variants (PSKAT=5.7 × 10(-4)). Conditional analyses suggest that this association is partly explained by the GWAS signal and the presence of a residual independent rare variant effect (Pconditional=0.019). Annotation using ENCODE data suggests that the GWAS variants may have a direct functional role in insulin biology. In conclusion, our study provides insight into variation present at the IGF1 locus and into the genetic architecture underlying FI levels, suggesting that FI associations of SNVs near IGF1 are not mediated by IGF-I and suggesting a role for both rare nonsynonymous and common functional variants in insulin biology.

Associations of Plasma Phospholipid SFAs with Total and Cause-Specific Mortality in Older Adults Differ According to SFA Chain Length. - Fretts, Amanda M; Mozaffarian, Dariush; Siscovick, David S; King, Irena B; McKnight, Barbara; Psaty, Bruce M; Rimm, Eric B; Sitlani, Colleen; Sacks, Frank M; Song, Xiaoling; Sotoodehnia, Nona; Spiegelman, Donna; et al. (J Nutr, 2016)
BACKGROUND: Not much is known about the relations of circulating saturated fatty acids (SFAs), which are influenced by both metabolic and dietary determinants, with total and cause-specific mortality. OBJECTIVE: We examined the associations of plasma phospholipid SFAs with total and cause-specific mortality among 3941 older adults from the Cardiovascular Health Study, a population-based prospective study of adults aged ≥65 y who were followed from 1992 through 2011. METHODS: The relations of total and cause-specific mortality with plasma phospholipid palmitic acid (16:0), stearic acid (18:0), arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0) were assessed using Cox proportional hazards models. RESULTS: During 45,450 person-years of follow-up, 3134 deaths occurred. Higher concentrations of the plasma phospholipid SFAs 18:0, 22:0, and 24:0 were associated with a lower risk of total mortality [multivariable-adjusted HRs (95% CIs)] for the top compared with the bottom quintile: 0.85 (0.75, 0.95) for 18:0; 0.85 (0.75, 0.95) for 22:0; and 0.80 (0.71, 0.90) for 24:0. In contrast, plasma 16:0 concentrations in the highest quintile were associated with a higher risk of total mortality compared with concentrations in the lowest quintile [1.25 (1.11, 1.41)]. We also found no association of plasma phospholipid 20:0 with total mortality. CONCLUSIONS: These findings suggest that the associations of plasma phospholipid SFAs with the risk of death differ according to SFA chain length and support future studies to better characterize the determinants of circulating SFAs and to explore the mechanisms underlying these relations.
Keywords: Aged; Aged, 80 and over; Cause of Death; Diet; Dietary Fats; Eicosanoic Acids; Fatty Acids; Female; Humans; Male; Mortality; Palmitic Acid; Phospholipids; Prospective Studies; Risk Factors; Stearic Acids

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.

An Empirical Comparison of Joint and Stratified Frameworks for Studying G × E Interactions: Systolic Blood Pressure and Smoking in the CHARGE Gene-Lifestyle Interactions Working Group. - Sung, Yun Ju; Winkler, Thomas W; Manning, Alisa K; Aschard, Hugues; Gudnason, Vilmundur; Harris, Tamara B; Smith, Albert V; Boerwinkle, Eric; Brown, Michael R; Morrison, Alanna C; Fornage, Myriam; Lin, Li-An; et al. (Genet Epidemiol, 2016)
Studying gene-environment (G × E) interactions is important, as they extend our knowledge of the genetic architecture of complex traits and may help to identify novel variants not detected via analysis of main effects alone. The main statistical framework for studying G × E interactions uses a single regression model that includes both the genetic main and G × E interaction effects (the "joint" framework). The alternative "stratified" framework combines results from genetic main-effect analyses carried out separately within the exposed and unexposed groups. Although there have been several investigations using theory and simulation, an empirical comparison of the two frameworks is lacking. Here, we compare the two frameworks using results from genome-wide association studies of systolic blood pressure for 3.2 million low frequency and 6.5 million common variants across 20 cohorts of European ancestry, comprising 79,731 individuals. Our cohorts have sample sizes ranging from 456 to 22,983 and include both family-based and population-based samples. In cohort-specific analyses, the two frameworks provided similar inference for population-based cohorts. The agreement was reduced for family-based cohorts. In meta-analyses, agreement between the two frameworks was less than that observed in cohort-specific analyses, despite the increased sample size. In meta-analyses, agreement depended on (1) the minor allele frequency, (2) inclusion of family-based cohorts in meta-analysis, and (3) filtering scheme. The stratified framework appears to approximate the joint framework well only for common variants in population-based cohorts. We conclude that the joint framework is the preferred approach and should be used to control false positives when dealing with low-frequency variants and/or family-based cohorts.

Epigenetic Signatures of Cigarette Smoking. - Joehanes, Roby; Just, Allan C; Marioni, Riccardo E; Pilling, Luke C; Reynolds, Lindsay M; Mandaviya, Pooja R; Guan, Weihua; Xu, Tao; Elks, Cathy E; Aslibekyan, Stella; Moreno-Macias, Hortensia; Smith, Jennifer A; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: DNA methylation leaves a long-term signature of smoking exposure and is one potential mechanism by which tobacco exposure predisposes to adverse health outcomes, such as cancers, osteoporosis, lung, and cardiovascular disorders. METHODS AND RESULTS: To comprehensively determine the association between cigarette smoking and DNA methylation, we conducted a meta-analysis of genome-wide DNA methylation assessed using the Illumina BeadChip 450K array on 15 907 blood-derived DNA samples from participants in 16 cohorts (including 2433 current, 6518 former, and 6956 never smokers). Comparing current versus never smokers, 2623 cytosine-phosphate-guanine sites (CpGs), annotated to 1405 genes, were statistically significantly differentially methylated at Bonferroni threshold of P<1×10(-7) (18 760 CpGs at false discovery rate <0.05). Genes annotated to these CpGs were enriched for associations with several smoking-related traits in genome-wide studies including pulmonary function, cancers, inflammatory diseases, and heart disease. Comparing former versus never smokers, 185 of the CpGs that differed between current and never smokers were significant P<1×10(-7) (2623 CpGs at false discovery rate <0.05), indicating a pattern of persistent altered methylation, with attenuation, after smoking cessation. Transcriptomic integration identified effects on gene expression at many differentially methylated CpGs. CONCLUSIONS: Cigarette smoking has a broad impact on genome-wide methylation that, at many loci, persists many years after smoking cessation. Many of the differentially methylated genes were novel genes with respect to biological effects of smoking and might represent therapeutic targets for prevention or treatment of tobacco-related diseases. Methylation at these sites could also serve as sensitive and stable biomarkers of lifetime exposure to tobacco smoke.

Exome Genotyping Identifies Pleiotropic Variants Associated with Red Blood Cell Traits. - Chami, Nathalie; Chen, Ming-Huei; Slater, Andrew J; Eicher, John D; Evangelou, Evangelos; Tajuddin, Salman M; Love-Gregory, Latisha; Kacprowski, Tim; Schick, Ursula M; Nomura, Akihiro; Giri, Ayush; Lessard, Samuel; et al. (Am J Hum Genet, 2016)
Red blood cell (RBC) traits are important heritable clinical biomarkers and modifiers of disease severity. To identify coding genetic variants associated with these traits, we conducted meta-analyses of seven RBC phenotypes in 130,273 multi-ethnic individuals from studies genotyped on an exome array. After conditional analyses and replication in 27,480 independent individuals, we identified 16 new RBC variants. We found low-frequency missense variants in MAP1A (rs55707100, minor allele frequency [MAF] = 3.3%, p = 2 × 10(-10) for hemoglobin [HGB]) and HNF4A (rs1800961, MAF = 2.4%, p < 3 × 10(-8) for hematocrit [HCT] and HGB). In African Americans, we identified a nonsense variant in CD36 associated with higher RBC distribution width (rs3211938, MAF = 8.7%, p = 7 × 10(-11)) and showed that it is associated with lower CD36 expression and strong allelic imbalance in ex vivo differentiated human erythroblasts. We also identified a rare missense variant in ALAS2 (rs201062903, MAF = 0.2%) associated with lower mean corpuscular volume and mean corpuscular hemoglobin (p < 8 × 10(-9)). Mendelian mutations in ALAS2 are a cause of sideroblastic anemia and erythropoietic protoporphyria. Gene-based testing highlighted three rare missense variants in PKLR, a gene mutated in Mendelian non-spherocytic hemolytic anemia, associated with HGB and HCT (SKAT p < 8 × 10(-7)). These rare, low-frequency, and common RBC variants showed pleiotropy, being also associated with platelet, white blood cell, and lipid traits. Our association results and functional annotation suggest the involvement of new genes in human erythropoiesis. We also confirm that rare and low-frequency variants play a role in the architecture of complex human traits, although their phenotypic effect is generally smaller than originally anticipated.

Fine-mapping, novel loci identification, and SNP association transferability in a genome-wide association study of QRS duration in African Americans. - Evans, Daniel S; Avery, Christy L; Nalls, Mike A; Li, Guo; Barnard, John; Smith, Erin N; Tanaka, Toshiko; Butler, Anne M; Buxbaum, Sarah G; Alonso, Alvaro; Arking, Dan E; Berenson, Gerald S; et al. (Hum Mol Genet, 2016)
The electrocardiographic QRS duration, a measure of ventricular depolarization and conduction, is associated with cardiovascular mortality. While single nucleotide polymorphisms (SNPs) associated with QRS duration have been identified at 22 loci in populations of European descent, the genetic architecture of QRS duration in non-European populations is largely unknown. We therefore performed a genome-wide association study (GWAS) meta-analysis of QRS duration in 13,031 African Americans from ten cohorts and a transethnic GWAS meta-analysis with additional results from populations of European descent. In the African American GWAS, a single genome-wide significant SNP association was identified (rs3922844, P = 4 × 10(-14)) in intron 16 of SCN5A, a voltage-gated cardiac sodium channel gene. The QRS-prolonging rs3922844 C allele was also associated with decreased SCN5A RNA expression in human atrial tissue (P = 1.1 × 10(-4)). High density genotyping revealed that the SCN5A association region in African Americans was confined to intron 16. Transethnic GWAS meta-analysis identified novel SNP associations on chromosome 18 in MYL12A (rs1662342, P = 4.9 × 10(-8)) and chromosome 1 near CD1E and SPTA1 (rs7547997, P = 7.9 × 10(-9)). The 22 QRS loci previously identified in populations of European descent were enriched for significant SNP associations with QRS duration in African Americans (P = 9.9 × 10(-7)), and index SNP associations in or near SCN5A, SCN10A, CDKN1A, NFIA, HAND1, TBX5 and SETBP1 replicated in African Americans. In summary, rs3922844 was associated with QRS duration and SCN5A expression, two novel QRS loci were identified using transethnic meta-analysis, and a significant proportion of QRS-SNP associations discovered in populations of European descent were transferable to African Americans when adequate power was achieved.

Genetic Investigation Into the Differential Risk of Atrial Fibrillation Among Black and White Individuals. - Roberts, Jason D; Hu, Donglei; Heckbert, Susan R; Alonso, Alvaro; Dewland, Thomas A; Vittinghoff, Eric; Liu, Yongmei; Psaty, Bruce M; Olgin, Jeffrey E; Magnani, Jared W; Huntsman, Scott; Burchard, Esteban G; et al. (JAMA Cardiol, 2016)
IMPORTANCE: White persons have a higher risk of atrial fibrillation (AF) compared with black individuals despite a lower prevalence of risk factors. This difference may be due, at least in part, to genetic factors. OBJECTIVES: To determine whether 9 single-nucleotide polymorphisms (SNPs) associated with AF account for this paradoxical differential racial risk for AF and to use admixture mapping to search genome-wide for loci that may account for this phenomenon. DESIGN, SETTING, AND PARTICIPANTS: Genome-wide admixture analysis and candidate SNP study involving 3 population-based cohort studies that were initiated between 1987 and 1997, including the Cardiovascular Health Study (CHS) (n = 4173), the Atherosclerosis Risk in Communities (ARIC) (n = 12 341) study, and the Health, Aging, and Body Composition (Health ABC) (n = 1015) study. In all 3 studies, race was self-identified. Cox proportional hazards regression models and the proportion of treatment effect method were used to determine the impact of 9 AF-risk SNPs among participants from CHS and the ARIC study. The present study began July 1, 2012, and was completed in 2015. MAIN OUTCOMES AND MEASURES: Incident AF systematically ascertained using clinic visit electrocardiograms, hospital discharge diagnosis codes, death certificates, and Medicare claims data. RESULTS: A single SNP, rs10824026 (chromosome 10: position 73661450), was found to significantly mediate the higher risk for AF in white participants compared with black participants in CHS (11.4%; 95% CI, 2.9%-29.9%) and ARIC (31.7%; 95% CI, 16.0%-53.0%). Admixture mapping was performed in a meta-analysis of black participants within CHS (n = 811), ARIC (n = 3112), and Health ABC (n = 1015). No loci that reached the prespecified statistical threshold for genome-wide significance were identified. CONCLUSIONS AND RELEVANCE: The rs10824026 SNP on chromosome 10q22 mediates a modest proportion of the increased risk of AF among white individuals compared with black individuals, potentially through an effect on gene expression levels of MYOZ1. No additional genetic variants accounting for a significant portion of the differential racial risk of AF were identified with genome-wide admixture mapping, suggesting that additional genetic or environmental influences beyond single SNPs in isolation may account for the paradoxical racial risk of AF among white individuals and black individuals.

Genetic Variants Associated with Circulating Parathyroid Hormone. - Robinson-Cohen, Cassianne; Lutsey, Pamela L; Kleber, Marcus E; Nielson, Carrie M; Mitchell, Braxton D; Bis, Joshua C; Eny, Karen M; Portas, Laura; Eriksson, Joel; Lorentzon, Mattias; Koller, Daniel L; Milaneschi, Yuri; et al. (J Am Soc Nephrol, 2016)
Parathyroid hormone (PTH) is a primary calcium regulatory hormone. Elevated serum PTH concentrations in primary and secondary hyperparathyroidism have been associated with bone disease, hypertension, and in some studies, cardiovascular mortality. Genetic causes of variation in circulating PTH concentrations are incompletely understood. We performed a genome-wide association study of serum PTH concentrations among 29,155 participants of European ancestry from 13 cohort studies (n=22,653 and n=6502 in discovery and replication analyses, respectively). We evaluated the association of single nucleotide polymorphisms (SNPs) with natural log-transformed PTH concentration adjusted for age, sex, season, study site, and principal components of ancestry. We discovered associations of SNPs from five independent regions with serum PTH concentration, including the strongest association with rs6127099 upstream of CYP24A1 (P=4.2 × 10(-53)), a gene that encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-dihydroxyvitamin D. Each additional copy of the minor allele at this SNP associated with 7% higher serum PTH concentration. The other SNPs associated with serum PTH concentration included rs4074995 within RGS14 (P=6.6 × 10(-17)), rs219779 adjacent to CLDN14 (P=3.5 × 10(-16)), rs4443100 near RTDR1 (P=8.7 × 10(-9)), and rs73186030 near CASR (P=4.8 × 10(-8)). Of these five SNPs, rs6127099, rs4074995, and rs219779 replicated. Thus, common genetic variants located near genes involved in vitamin D metabolism and calcium and renal phosphate transport associated with differences in circulating PTH concentrations. Future studies could identify the causal variants at these loci, and the clinical and functional relevance of these variants should be pursued.

Genetic variants in RBFOX3 are associated with sleep latency. - Amin, Najaf; Allebrandt, Karla V; van der Spek, Ashley; Müller-Myhsok, Bertram; Hek, Karin; Teder-Laving, Maris; Hayward, Caroline; Esko, Tõnu; van Mill, Josine G; Mbarek, Hamdi; Watson, Nathaniel F; Melville, Scott A; et al. (Eur J Hum Genet, 2016)
Time to fall asleep (sleep latency) is a major determinant of sleep quality. Chronic, long sleep latency is a major characteristic of sleep-onset insomnia and/or delayed sleep phase syndrome. In this study we aimed to discover common polymorphisms that contribute to the genetics of sleep latency. We performed a meta-analysis of genome-wide association studies (GWAS) including 2 572 737 single nucleotide polymorphisms (SNPs) established in seven European cohorts including 4242 individuals. We found a cluster of three highly correlated variants (rs9900428, rs9907432 and rs7211029) in the RNA-binding protein fox-1 homolog 3 gene (RBFOX3) associated with sleep latency (P-values=5.77 × 10(-08), 6.59 × 10(-)(08) and 9.17 × 10(-)(08)). These SNPs were replicated in up to 12 independent populations including 30 377 individuals (P-values=1.5 × 10(-)(02), 7.0 × 10(-)(03) and 2.5 × 10(-)(03); combined meta-analysis P-values=5.5 × 10(-07), 5.4 × 10(-07) and 1.0 × 10(-07)). A functional prediction of RBFOX3 based on co-expression with other genes shows that this gene is predominantly expressed in brain (P-value=1.4 × 10(-316)) and the central nervous system (P-value=7.5 × 10(-)(321)). The predicted function of RBFOX3 based on co-expression analysis with other genes shows that this gene is significantly involved in the release cycle of neurotransmitters including gamma-aminobutyric acid and various monoamines (P-values<2.9 × 10(-11)) that are crucial in triggering the onset of sleep. To conclude, in this first large-scale GWAS of sleep latency we report a novel association of variants in RBFOX3 gene. Further, a functional prediction of RBFOX3 supports the involvement of RBFOX3 with sleep latency.

Genome-Wide Association Study for Incident Myocardial Infarction and Coronary Heart Disease in Prospective Cohort Studies: The CHARGE Consortium. - Dehghan, Abbas; Bis, Joshua C; White, Charles C; Smith, Albert Vernon; Morrison, Alanna C; Cupples, L Adrienne; Trompet, Stella; Chasman, Daniel I; Lumley, Thomas; Völker, Uwe; Buckley, Brendan M; Ding, Jingzhong; et al. (PLoS One, 2016)
BACKGROUND: Data are limited on genome-wide association studies (GWAS) for incident coronary heart disease (CHD). Moreover, it is not known whether genetic variants identified to date also associate with risk of CHD in a prospective setting. METHODS: We performed a two-stage GWAS analysis of incident myocardial infarction (MI) and CHD in a total of 64,297 individuals (including 3898 MI cases, 5465 CHD cases). SNPs that passed an arbitrary threshold of 5×10-6 in Stage I were taken to Stage II for further discovery. Furthermore, in an analysis of prognosis, we studied whether known SNPs from former GWAS were associated with total mortality in individuals who experienced MI during follow-up. RESULTS: In Stage I 15 loci passed the threshold of 5×10-6; 8 loci for MI and 8 loci for CHD, for which one locus overlapped and none were reported in previous GWAS meta-analyses. We took 60 SNPs representing these 15 loci to Stage II of discovery. Four SNPs near QKI showed nominally significant association with MI (p-value<8.8×10-3) and three exceeded the genome-wide significance threshold when Stage I and Stage II results were combined (top SNP rs6941513: p = 6.2×10-9). Despite excellent power, the 9p21 locus SNP (rs1333049) was only modestly associated with MI (HR = 1.09, p-value = 0.02) and marginally with CHD (HR = 1.06, p-value = 0.08). Among an inception cohort of those who experienced MI during follow-up, the risk allele of rs1333049 was associated with a decreased risk of subsequent mortality (HR = 0.90, p-value = 3.2×10-3). CONCLUSIONS: QKI represents a novel locus that may serve as a predictor of incident CHD in prospective studies. The association of the 9p21 locus both with increased risk of first myocardial infarction and longer survival after MI highlights the importance of study design in investigating genetic determinants of complex disorders.
Keywords: Aged; Cohort Studies; Cooperative Behavior; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

Genome-Wide Association Study of the Modified Stumvoll Insulin Sensitivity Index Identifies BCL2 and FAM19A2 as Novel Insulin Sensitivity Loci. - Walford, Geoffrey A; Gustafsson, Stefan; Rybin, Denis; Stančáková, Alena; Chen, Han; Liu, Ching-Ti; Hong, Jaeyoung; Jensen, Richard A; Rice, Ken; Morris, Andrew P; Mägi, Reedik; Tönjes, Anke; et al. (Diabetes, 2016)
Genome-wide association studies (GWAS) have found few common variants that influence fasting measures of insulin sensitivity. We hypothesized that a GWAS of an integrated assessment of fasting and dynamic measures of insulin sensitivity would detect novel common variants. We performed a GWAS of the modified Stumvoll Insulin Sensitivity Index (ISI) within the Meta-Analyses of Glucose and Insulin-Related Traits Consortium. Discovery for genetic association was performed in 16,753 individuals, and replication was attempted for the 23 most significant novel loci in 13,354 independent individuals. Association with ISI was tested in models adjusted for age, sex, and BMI and in a model analyzing the combined influence of the genotype effect adjusted for BMI and the interaction effect between the genotype and BMI on ISI (model 3). In model 3, three variants reached genome-wide significance: rs13422522 (NYAP2; P = 8.87 × 10(-11)), rs12454712 (BCL2; P = 2.7 × 10(-8)), and rs10506418 (FAM19A2; P = 1.9 × 10(-8)). The association at NYAP2 was eliminated by conditioning on the known IRS1 insulin sensitivity locus; the BCL2 and FAM19A2 associations were independent of known cardiometabolic loci. In conclusion, we identified two novel loci and replicated known variants associated with insulin sensitivity. Further studies are needed to clarify the causal variant and function at the BCL2 and FAM19A2 loci.

Genomewide meta-analysis identifies loci associated with IGF-I and IGFBP-3 levels with impact on age-related traits. - Teumer, Alexander; Qi, Qibin; Nethander, Maria; Aschard, Hugues; Bandinelli, Stefania; Beekman, Marian; Berndt, Sonja I; Bidlingmaier, Martin; Broer, Linda; Cappola, Anne; Ceda, Gian Paolo; Chanock, Stephen; et al. (Aging Cell, 2016)
The growth hormone/insulin-like growth factor (IGF) axis can be manipulated in animal models to promote longevity, and IGF-related proteins including IGF-I and IGF-binding protein-3 (IGFBP-3) have also been implicated in risk of human diseases including cardiovascular diseases, diabetes, and cancer. Through genomewide association study of up to 30 884 adults of European ancestry from 21 studies, we confirmed and extended the list of previously identified loci associated with circulating IGF-I and IGFBP-3 concentrations (IGF1, IGFBP3, GCKR, TNS3, GHSR, FOXO3, ASXL2, NUBP2/IGFALS, SORCS2, and CELSR2). Significant sex interactions, which were characterized by different genotype-phenotype associations between men and women, were found only for associations of IGFBP-3 concentrations with SNPs at the loci IGFBP3 and SORCS2. Analyses of SNPs, gene expression, and protein levels suggested that interplay between IGFBP3 and genes within the NUBP2 locus (IGFALS and HAGH) may affect circulating IGF-I and IGFBP-3 concentrations. The IGF-I-decreasing allele of SNP rs934073, which is an eQTL of ASXL2, was associated with lower adiposity and higher likelihood of survival beyond 90 years. The known longevity-associated variant rs2153960 (FOXO3) was observed to be a genomewide significant SNP for IGF-I concentrations. Bioinformatics analysis suggested enrichment of putative regulatory elements among these IGF-I- and IGFBP-3-associated loci, particularly of rs646776 at CELSR2. In conclusion, this study identified several loci associated with circulating IGF-I and IGFBP-3 concentrations and provides clues to the potential role of the IGF axis in mediating effects of known (FOXO3) and novel (ASXL2) longevity-associated loci.

GWAS analysis of handgrip and lower body strength in older adults in the CHARGE consortium. - Matteini, Amy M; Tanaka, Toshiko; Karasik, David; Atzmon, Gil; Chou, Wen-Chi; Eicher, John D; Johnson, Andrew D; Arnold, Alice M; Callisaya, Michele L; Davies, Gail; Evans, Daniel S; Holtfreter, Birte; et al. (Aging Cell, 2016)
Decline in muscle strength with aging is an important predictor of health trajectory in the elderly. Several factors, including genetics, are proposed contributors to variability in muscle strength. To identify genetic contributors to muscle strength, a meta-analysis of genomewide association studies of handgrip was conducted. Grip strength was measured using a handheld dynamometer in 27 581 individuals of European descent over 65 years of age from 14 cohort studies. Genomewide association analysis was conducted on ~2.7 million imputed and genotyped variants (SNPs). Replication of the most significant findings was conducted using data from 6393 individuals from three cohorts. GWAS of lower body strength was also characterized in a subset of cohorts. Two genomewide significant (P-value< 5 × 10(-8) ) and 39 suggestive (P-value< 5 × 10(-5) ) associations were observed from meta-analysis of the discovery cohorts. After meta-analysis with replication cohorts, genomewide significant association was observed for rs752045 on chromosome 8 (β = 0.47, SE = 0.08, P-value = 5.20 × 10(-10) ). This SNP is mapped to an intergenic region and is located within an accessible chromatin region (DNase hypersensitivity site) in skeletal muscle myotubes differentiated from the human skeletal muscle myoblasts cell line. This locus alters a binding motif of the CCAAT/enhancer-binding protein-β (CEBPB) that is implicated in muscle repair mechanisms. GWAS of lower body strength did not yield significant results. A common genetic variant in a chromosomal region that regulates myotube differentiation and muscle repair may contribute to variability in grip strength in the elderly. Further studies are needed to uncover the mechanisms that link this genetic variant with muscle strength.

Impact of genetic variants on the upstream efficacy of renin-angiotensin system inhibitors for the prevention of atrial fibrillation. - Roberts, Jason D; Dewland, Thomas A; Glidden, David V; Hoffmann, Thomas J; Arking, Dan E; Chen, Lin Y; Psaty, Bruce M; Olgin, Jeffrey E; Alonso, Alvaro; Heckbert, Susan R; Marcus, Gregory M (Am Heart J, 2016)
BACKGROUND: Renin-angiotensin system (RAS) inhibition via angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers may reduce the risk of developing atrial fibrillation (AF) in certain populations, but the evidence is conflicting. Recent genome-wide association studies have identified several single nucleotide polymorphisms (SNPs) associated with AF, potentially identifying clinically relevant subtypes of the disease. We sought to investigate the impact of carrier status of 9 AF-associated SNPs on the efficacy of RAS inhibition for the primary prevention of AF. METHODS: We performed SNP-RAS inhibitor interaction testing with unadjusted and adjusted Cox proportional hazards models using a discovery (Cardiovascular Health Study) and a replication (Atherosclerosis Risk in Communities) cohort. Additive genetic models were used for the SNP analyses, and 2-tailed P values <.05 were considered statistically significant. RESULTS: Among 2,796 Cardiovascular Health Study participants, none of the 9 a priori identified candidate SNPs exhibited a significant SNP-drug interaction. Two of the 9 SNPs, rs2106261 (16q22) and rs6666258 (1q21), revealed interaction relationships that neared statistical significance (with point estimates in the same direction for angiotensin-converting enzyme inhibitor only and angiotensin II receptor blocker only analyses), but neither association could be replicated among 8,604 participants in Atherosclerosis Risk in Communities. CONCLUSIONS: Our study failed to identify AF-associated SNP genetic subtypes of AF that derive increased benefit from upstream RAS inhibition for AF prevention. Future studies should continue to investigate the impact of genotype on the response to AF treatment strategies in an effort to develop personalized approaches to therapy and prevention.

Insulinlike growth factor binding protein-1 and ghrelin predict health outcomes among older adults: CHS cohort. - Kaplan, Robert C; Strizich, Garrett; Aneke-Nash, Chino; Dominguez-Islas, Clara; Bůzková, Petra; Strickler, Howard; Rohan, Thomas; Pollak, Michael; Kuller, Lewis; Kizer, Jorge R; Cappola, Anne; Li, Christopher I; et al. (J Clin Endocrinol Metab, 2016)
CONTEXT: Multiple diseases may explain the association of the growth hormone / insulinlike growth factor-I (GH/IGF-I) axis with longevity. OBJECTIVE: To relate circulating GH/IGF-I system protein levels with major health events. DESIGN: Cohort study Setting: Four US communities Participants: Adults (n=2268) 65 years and older free of diabetes and cardiovascular disease. MEASUREMENTS: We assessed insulinlike growth factor binding protein-1 (IGFBP-1) and ghrelin in fasting and 2-hour oral glucose tolerance test (OGTT) blood samples, as well as fasting IGF-I and IGFBP-3. Hazard ratios for mortality and a composite outcome for first incident myocardial infarction, stroke, heart failure, hip fracture, or death were adjusted for sociodemographic, behavioral, and physiologic covariates. RESULTS: During 13,930 person-years of follow-up, 48.1% individuals sustained one or more components of the composite outcome and 31.8% died. Versus the lowest quartiles, the highest quartiles of fasting and 2-h ghrelin were associated with a 27% higher (95% CI: 6%, 53%) and 39% higher (95% CI: 14%, 71%) risks of the composite outcome, respectively. The highest quartile of 2-h IGFBP-1 was associated with 35% higher (95% CI: 1%, 52%) risk of the composite endpoint. Similarly, higher mortality was significantly associated with higher fasting and 2-h ghrelin level, and with 2-h IGFBP-1 level. When examined together, 2-h post-OGTT levels of IGFBP-1 and ghrelin tended to predict outcomes better than fasting levels. CONCLUSIONS: Circulating IGFBP-1 and ghrelin measured during an OGTT predict major health events and death in older adults, which may explain the influence of the GH-IGF-axis on lifespan and health.

Interaction of methylation-related genetic variants with circulating fatty acids on plasma lipids: a meta-analysis of 7 studies and methylation analysis of 3 studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Ma, Yiyi; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Manichaikul, Ani W; Chu, Audrey Y; Samieri, Cecilia; Zhou, Xia; Guan, Weihua; Wang, Lu; Biggs, Mary L; Chen, Yii-der I; et al. (Am J Clin Nutr, 2016)
BACKGROUND: DNA methylation is influenced by diet and single nucleotide polymorphisms (SNPs), and methylation modulates gene expression. OBJECTIVE: We aimed to explore whether the gene-by-diet interactions on blood lipids act through DNA methylation. DESIGN: We selected 7 SNPs on the basis of predicted relations in fatty acids, methylation, and lipids. We conducted a meta-analysis and a methylation and mediation analysis with the use of data from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium and the ENCODE (Encyclopedia of DNA Elements) consortium. RESULTS: On the basis of the meta-analysis of 7 cohorts in the CHARGE consortium, higher plasma HDL cholesterol was associated with fewer C alleles at ATP-binding cassette subfamily A member 1 (ABCA1) rs2246293 (β = -0.6 mg/dL, P = 0.015) and higher circulating eicosapentaenoic acid (EPA) (β = 3.87 mg/dL, P = 5.62 × 10(21)). The difference in HDL cholesterol associated with higher circulating EPA was dependent on genotypes at rs2246293, and it was greater for each additional C allele (β = 1.69 mg/dL, P = 0.006). In the GOLDN (Genetics of Lipid Lowering Drugs and Diet Network) study, higher ABCA1 promoter cg14019050 methylation was associated with more C alleles at rs2246293 (β = 8.84%, P = 3.51 × 10(18)) and lower circulating EPA (β = -1.46%, P = 0.009), and the mean difference in methylation of cg14019050 that was associated with higher EPA was smaller with each additional C allele of rs2246293 (β = -2.83%, P = 0.007). Higher ABCA1 cg14019050 methylation was correlated with lower ABCA1 expression (r = -0.61, P = 0.009) in the ENCODE consortium and lower plasma HDL cholesterol in the GOLDN study (r = -0.12, P = 0.0002). An additional mediation analysis was meta-analyzed across the GOLDN study, Cardiovascular Health Study, and the Multi-Ethnic Study of Atherosclerosis. Compared with the model without the adjustment of cg14019050 methylation, the model with such adjustment provided smaller estimates of the mean plasma HDL cholesterol concentration in association with both the rs2246293 C allele and EPA and a smaller difference by rs2246293 genotypes in the EPA-associated HDL cholesterol. However, the differences between 2 nested models were NS (P > 0.05). CONCLUSION: We obtained little evidence that the gene-by-fatty acid interactions on blood lipids act through DNA methylation.
Keywords: Apolipoproteins E; ATP Binding Cassette Transporter 1; Cholesterol, HDL; Cohort Studies; Diet; DNA Methylation; Eicosapentaenoic Acid; Epigenesis, Genetic; Fatty Acids; Gene Expression Regulation; Humans; Lipids; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Triglycerides

Lack of association of plasma gamma prime (γ') fibrinogen with incident cardiovascular disease. - Appiah, Duke; Heckbert, Susan R; Cushman, Mary; Psaty, Bruce M; Folsom, Aaron R (Thromb Res, 2016)
INTRODUCTION: The association of gamma prime (γ') fibrinogen; a fibrinogen γ chain variant generated via alternative mRNA processing, with cardiovascular disease (CVD) remains equivocal. We prospectively examine the association of plasma γ' fibrinogen with the incidence of multiple cardiovascular disease (CVD) endpoints, independent of established CVD risk factors and total fibrinogen. MATERIALS AND METHODS: We measured plasma γ' fibrinogen on plasma samples collected in 1992-1993 from adults ≥65years (n=3219) enrolled in the Cardiovascular Health Study, who were followed through 2013 for incident CVD events. RESULTS AND CONCLUSIONS: In multivariable Cox models adjusted for traditional CVD risk factors and total fibrinogen, the hazard ratio per 1 standard deviation (10.7mg/dl) increment of γ' fibrinogen was 1.02 (95%CI: 0.95-1.10) for coronary heart disease; 0.88 (0.77-1.00) for ischemic stroke; 1.07 (0.87-1.32) for peripheral artery disease; 1.00 (0.92-1.08) for heart failure and 1.01 (0.92-1.10) for CVD mortality. Likewise, we failed to show a statistically significant association of γ'/total fibrinogen ratio with any CVD endpoint. These results suggest that among the elderly, γ' fibrinogen does not add much to CVD prediction beyond traditional risk factors and total fibrinogen level.

Large-Scale Exome-wide Association Analysis Identifies Loci for White Blood Cell Traits and Pleiotropy with Immune-Mediated Diseases. - Tajuddin, Salman M; Schick, Ursula M; Eicher, John D; Chami, Nathalie; Giri, Ayush; Brody, Jennifer A; Hill, W David; Kacprowski, Tim; Li, Jin; Lyytikäinen, Leo-Pekka; Manichaikul, Ani; Mihailov, Evelin; et al. (Am J Hum Genet, 2016)
White blood cells play diverse roles in innate and adaptive immunity. Genetic association analyses of phenotypic variation in circulating white blood cell (WBC) counts from large samples of otherwise healthy individuals can provide insights into genes and biologic pathways involved in production, differentiation, or clearance of particular WBC lineages (myeloid, lymphoid) and also potentially inform the genetic basis of autoimmune, allergic, and blood diseases. We performed an exome array-based meta-analysis of total WBC and subtype counts (neutrophils, monocytes, lymphocytes, basophils, and eosinophils) in a multi-ancestry discovery and replication sample of ∼157,622 individuals from 25 studies. We identified 16 common variants (8 of which were coding variants) associated with one or more WBC traits, the majority of which are pleiotropically associated with autoimmune diseases. Based on functional annotation, these loci included genes encoding surface markers of myeloid, lymphoid, or hematopoietic stem cell differentiation (CD69, CD33, CD87), transcription factors regulating lineage specification during hematopoiesis (ASXL1, IRF8, IKZF1, JMJD1C, ETS2-PSMG1), and molecules involved in neutrophil clearance/apoptosis (C10orf54, LTA), adhesion (TNXB), or centrosome and microtubule structure/function (KIF9, TUBD1). Together with recent reports of somatic ASXL1 mutations among individuals with idiopathic cytopenias or clonal hematopoiesis of undetermined significance, the identification of a common regulatory 3' UTR variant of ASXL1 suggests that both germline and somatic ASXL1 mutations contribute to lower blood counts in otherwise asymptomatic individuals. These association results shed light on genetic mechanisms that regulate circulating WBC counts and suggest a prominent shared genetic architecture with inflammatory and autoimmune diseases.

Meta-analysis identifies common and rare variants influencing blood pressure and overlapping with metabolic trait loci. - Liu, Chunyu; Kraja, Aldi T; Smith, Jennifer A; Brody, Jennifer A; Franceschini, Nora; Bis, Joshua C; Rice, Kenneth; Morrison, Alanna C; Lu, Yingchang; Weiss, Stefan; Guo, Xiuqing; Palmas, Walter; et al. (Nat Genet, 2016)
Meta-analyses of association results for blood pressure using exome-centric single-variant and gene-based tests identified 31 new loci in a discovery stage among 146,562 individuals, with follow-up and meta-analysis in 180,726 additional individuals (total n = 327,288). These blood pressure-associated loci are enriched for known variants for cardiometabolic traits. Associations were also observed for the aggregation of rare and low-frequency missense variants in three genes, NPR1, DBH, and PTPMT1. In addition, blood pressure associations at 39 previously reported loci were confirmed. The identified variants implicate biological pathways related to cardiometabolic traits, vascular function, and development. Several new variants are inferred to have roles in transcription or as hubs in protein-protein interaction networks. Genetic risk scores constructed from the identified variants were strongly associated with coronary disease and myocardial infarction. This large collection of blood pressure-associated loci suggests new therapeutic strategies for hypertension, emphasizing a link with cardiometabolic risk.

A meta-analysis of 120 246 individuals identifies 18 new loci for fibrinogen concentration. - de Vries, Paul S; Chasman, Daniel I; Sabater-Lleal, Maria; Chen, Ming-Huei; Huffman, Jennifer E; Steri, Maristella; Tang, Weihong; Teumer, Alexander; Marioni, Riccardo E; Grossmann, Vera; Hottenga, Jouke J; Trompet, Stella; et al. (Hum Mol Genet, 2016)
Genome-wide association studies have previously identified 23 genetic loci associated with circulating fibrinogen concentration. These studies used HapMap imputation and did not examine the X-chromosome. 1000 Genomes imputation provides better coverage of uncommon variants, and includes indels. We conducted a genome-wide association analysis of 34 studies imputed to the 1000 Genomes Project reference panel and including ∼120 000 participants of European ancestry (95 806 participants with data on the X-chromosome). Approximately 10.7 million single-nucleotide polymorphisms and 1.2 million indels were examined. We identified 41 genome-wide significant fibrinogen loci; of which, 18 were newly identified. There were no genome-wide significant signals on the X-chromosome. The lead variants of five significant loci were indels. We further identified six additional independent signals, including three rare variants, at two previously characterized loci: FGB and IRF1. Together the 41 loci explain 3% of the variance in plasma fibrinogen concentration.

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Sabo, Aniko; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.

Meta-analysis of genome-wide association studies of HDL cholesterol response to statins. - Postmus, Iris; Warren, Helen R; Trompet, Stella; Arsenault, Benoit J; Avery, Christy L; Bis, Joshua C; Chasman, Daniel I; de Keyser, Catherine E; Deshmukh, Harshal A; Evans, Daniel S; Feng, QiPing; Li, Xiaohui; et al. (J Med Genet, 2016)
BACKGROUND: In addition to lowering low density lipoprotein cholesterol (LDL-C), statin therapy also raises high density lipoprotein cholesterol (HDL-C) levels. Inter-individual variation in HDL-C response to statins may be partially explained by genetic variation. METHODS AND RESULTS: We performed a meta-analysis of genome-wide association studies (GWAS) to identify variants with an effect on statin-induced high density lipoprotein cholesterol (HDL-C) changes. The 123 most promising signals with p<1×10(-4) from the 16 769 statin-treated participants in the first analysis stage were followed up in an independent group of 10 951 statin-treated individuals, providing a total sample size of 27 720 individuals. The only associations of genome-wide significance (p<5×10(-8)) were between minor alleles at the CETP locus and greater HDL-C response to statin treatment. CONCLUSIONS: Based on results from this study that included a relatively large sample size, we suggest that CETP may be the only detectable locus with common genetic variants that influence HDL-C response to statins substantially in individuals of European descent. Although CETP is known to be associated with HDL-C, we provide evidence that this pharmacogenetic effect is independent of its association with baseline HDL-C levels.

Multiethnic Exome-Wide Association Study of Subclinical Atherosclerosis. - Natarajan, Pradeep; Bis, Joshua C; Bielak, Lawrence F; Cox, Amanda J; Dörr, Marcus; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; Isaacs, Aaron; Jhun, Min A; Kavousi, Maryam; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: -The burden of subclinical atherosclerosis in asymptomatic individuals is heritable and associated with elevated risk of developing clinical coronary heart disease (CHD). We sought to identify genetic variants in protein-coding regions associated with subclinical atherosclerosis and the risk of subsequent CHD. METHODS AND RESULTS: -We studied a total of 25,109 European ancestry and African-American participants with coronary artery calcification (CAC) measured by cardiac computed tomography and 52,869 with common carotid intima media thickness (CIMT) measured by ultrasonography within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Participants were genotyped for 247,870 DNA sequence variants (231,539 in exons) across the genome. A meta-analysis of exome-wide association studies was performed across cohorts for CAC and CIMT. APOB p.Arg3527Gln was associated with four-fold excess CAC (P = 3×10(-10)). The APOE ε2 allele (p.Arg176Cys) was associated with both 22.3% reduced CAC (P = 1×10(-12)) and 1.4% reduced CIMT (P = 4×10(-14)) in carriers compared with non-carriers. In secondary analyses conditioning on LDL cholesterol concentration, the ε2 protective association with CAC, although attenuated, remained strongly significant. Additionally, the presence of ε2 was associated with reduced risk for CHD (OR 0.77; P = 1×10(-11)). CONCLUSIONS: -Exome-wide association meta-analysis demonstrates that protein-coding variants in APOB and APOE associate with subclinical atherosclerosis. APOE ε2 represents the first significant association for multiple subclinical atherosclerosis traits across multiple ethnicities as well as clinical CHD.

Novel Genetic Loci Associated With Retinal Microvascular Diameter. - Jensen, Richard A; Sim, Xueling; Smith, Albert Vernon; Li, Xiaohui; Jakobsdottir, Johanna; Cheng, Ching-Yu; Brody, Jennifer A; Cotch, Mary Frances; McKnight, Barbara; Klein, Ronald; Wang, Jie Jin; Kifley, Annette; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: There is increasing evidence that retinal microvascular diameters are associated with cardiovascular and cerebrovascular conditions. The shared genetic effects of these associations are currently unknown. The aim of this study was to increase our understanding of the genetic factors that mediate retinal vessel size. METHODS AND RESULTS: This study extends previous genome-wide association study results using 24 000+ multiethnic participants from 7 discovery cohorts and 5000+ subjects of European ancestry from 2 replication cohorts. Using the Illumina HumanExome BeadChip, we investigate the association of single-nucleotide polymorphisms and variants collectively across genes with summary measures of retinal vessel diameters, referred to as the central retinal venule equivalent and the central retinal arteriole equivalent. We report 4 new loci associated with central retinal venule equivalent, one of which is also associated with central retinal arteriole equivalent. The 4 single-nucleotide polymorphisms are rs7926971 in TEAD1 (P=3.1×10(-) (11); minor allele frequency=0.43), rs201259422 in TSPAN10 (P=4.4×10(-9); minor allele frequency=0.27), rs5442 in GNB3 (P=7.0×10(-10); minor allele frequency=0.05), and rs1800407 in OCA2 (P=3.4×10(-8); minor allele frequency=0.05). The latter single-nucleotide polymorphism, rs1800407, was also associated with central retinal arteriole equivalent (P=6.5×10(-12)). Results from the gene-based burden tests were null. In phenotype look-ups, single-nucleotide polymorphism rs201255422 was associated with both systolic (P=0.001) and diastolic blood pressures (P=8.3×10(-04)). CONCLUSIONS: Our study expands the understanding of genetic factors influencing the size of the retinal microvasculature. These findings may also provide insight into the relationship between retinal and systemic microvascular disease.

Physical Activity and Risk of Coronary Heart Disease and Stroke in Older Adults: The Cardiovascular Health Study. - Soares-Miranda, Luisa; Siscovick, David S; Psaty, Bruce M; Longstreth, W T; Mozaffarian, Dariush (Circulation, 2016)
BACKGROUND: Although guidelines suggest that older adults engage in regular physical activity (PA) to reduce cardiovascular disease (CVD), surprisingly few studies have evaluated this relationship, especially in those >75 years. In addition, with advancing age the ability to perform some types of PA might decrease, making light-moderate exercise such as walking especially important to meet recommendations. METHODS AND RESULTS: Prospective cohort analysis among 4207 US men and women of a mean age of 73 years (standard deviation=6) who were free of CVD at baseline in the Cardiovascular Health Study were followed from 1989 to 1999. PA was assessed and cumulatively updated over time to minimize misclassification and assess the long-term effects of habitual activity. Walking (pace, blocks, combined walking score) was updated annually from baseline through 1999. Leisure-time activity and exercise intensity were updated at baseline, 1992, and 1996. Incident CVD (fatal or nonfatal myocardial infarction, coronary death, or stroke) was adjudicated using medical records. During 41,995 person-years of follow-up, 1182 CVD events occurred. After multivariable adjustment, greater PA was inversely associated with coronary heart disease, stroke (especially ischemic stroke), and total CVD, even in those ≥75 years. Walking pace, distance, and overall walking score, leisure-time activity, and exercise intensity were each associated with lower risk. For example, in comparison with a walking pace <2 mph, those that habitually walked at a pace >3 mph had a lower risk of coronary heart disease (0.50; confidence interval, 0.38-0.67), stroke (0.47; confidence interval, 033-0.66), and CVD (0.50; confidence interval, 0.40-0.62). CONCLUSIONS: These data provide empirical evidence supporting PA recommendations, in particular, walking, to reduce the incidence of CVD among older adults.
Keywords: Aged; Aged, 80 and over; Coronary Disease; Female; Follow-Up Studies; Health Status; Humans; Leisure Activities; Male; Motor Activity; Proportional Hazards Models; Prospective Studies; Sampling Studies; Stroke; United States; Walking

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals. - Eicher, John D; Chami, Nathalie; Kacprowski, Tim; Nomura, Akihiro; Chen, Ming-Huei; Yanek, Lisa R; Tajuddin, Salman M; Schick, Ursula M; Slater, Andrew J; Pankratz, Nathan; Polfus, Linda; Schurmann, Claudia; et al. (Am J Hum Genet, 2016)
Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Therefore, we formed the Blood Cell Consortium (BCX) to perform a large-scale meta-analysis of Exomechip association results for PLT and MPV in 157,293 and 57,617 individuals, respectively. Using the low-frequency/rare coding variant-enriched Exomechip genotyping array, we sought to identify genetic variants associated with PLT and MPV. In addition to confirming 47 known PLT and 20 known MPV associations, we identified 32 PLT and 18 MPV associations not previously observed in the literature across the allele frequency spectrum, including rare large effect (FCER1A), low-frequency (IQGAP2, MAP1A, LY75), and common (ZMIZ2, SMG6, PEAR1, ARFGAP3/PACSIN2) variants. Several variants associated with PLT/MPV (PEAR1, MRVI1, PTGES3) were also associated with platelet reactivity. In concurrent BCX analyses, there was overlap of platelet-associated variants with red (MAP1A, TMPRSS6, ZMIZ2) and white (PEAR1, ZMIZ2, LY75) blood cell traits, suggesting common regulatory pathways with shared genetic architecture among these hematopoietic lineages. Our large-scale Exomechip analyses identified previously undocumented associations with platelet traits and further indicate that several complex quantitative hematological, lipid, and cardiovascular traits share genetic factors.

Predicting Heart Failure With Preserved and Reduced Ejection Fraction: The International Collaboration on Heart Failure Subtypes. - Ho, Jennifer E; Enserro, Danielle; Brouwers, Frank P; Kizer, Jorge R; Shah, Sanjiv J; Psaty, Bruce M; Bartz, Traci M; Santhanakrishnan, Rajalakshmi; Lee, Douglas S; Chan, Cheeling; Liu, Kiang; Blaha, Michael J; et al. (Circ Heart Fail, 2016)
BACKGROUND: Heart failure (HF) is a prevalent and deadly disease, and preventive strategies focused on at-risk individuals are needed. Current HF prediction models have not examined HF subtypes. We sought to develop and validate risk prediction models for HF with preserved and reduced ejection fraction (HFpEF, HFrEF). METHODS AND RESULTS: Of 28,820 participants from 4 community-based cohorts, 982 developed incident HFpEF and 909 HFrEF during a median follow-up of 12 years. Three cohorts were combined, and a 2:1 random split was used for derivation and internal validation, with the fourth cohort as external validation. Models accounted for multiple competing risks (death, other HF subtype, and unclassified HF). The HFpEF-specific model included age, sex, systolic blood pressure, body mass index, antihypertensive treatment, and previous myocardial infarction; it had good discrimination in derivation (c-statistic 0.80; 95% confidence interval [CI], 0.78-0.82) and validation samples (internal: 0.79; 95% CI, 0.77-0.82 and external: 0.76; 95% CI: 0.71-0.80). The HFrEF-specific model additionally included smoking, left ventricular hypertrophy, left bundle branch block, and diabetes mellitus; it had good discrimination in derivation (c-statistic 0.82; 95% CI, 0.80-0.84) and validation samples (internal: 0.80; 95% CI, 0.78-0.83 and external: 0.76; 95% CI, 0.71-0.80). Age was more strongly associated with HFpEF, and male sex, left ventricular hypertrophy, bundle branch block, previous myocardial infarction, and smoking with HFrEF (P value for each comparison ≤0.02). CONCLUSIONS: We describe and validate risk prediction models for HF subtypes and show good discrimination in a large sample. Some risk factors differed between HFpEF and HFrEF, supporting the notion of pathogenetic differences among HF subtypes.

A principal component meta-analysis on multiple anthropometric traits identifies novel loci for body shape. - Ried, Janina S; Jeff M, Janina; Chu, Audrey Y; Bragg-Gresham, Jennifer L; van Dongen, Jenny; Huffman, Jennifer E; Ahluwalia, Tarunveer S; Cadby, Gemma; Eklund, Niina; Eriksson, Joel; Esko, Tõnu; Feitosa, Mary F; et al. (Nat Commun, 2016)
Large consortia have revealed hundreds of genetic loci associated with anthropometric traits, one trait at a time. We examined whether genetic variants affect body shape as a composite phenotype that is represented by a combination of anthropometric traits. We developed an approach that calculates averaged PCs (AvPCs) representing body shape derived from six anthropometric traits (body mass index, height, weight, waist and hip circumference, waist-to-hip ratio). The first four AvPCs explain >99% of the variability, are heritable, and associate with cardiometabolic outcomes. We performed genome-wide association analyses for each body shape composite phenotype across 65 studies and meta-analysed summary statistics. We identify six novel loci: LEMD2 and CD47 for AvPC1, RPS6KA5/C14orf159 and GANAB for AvPC3, and ARL15 and ANP32 for AvPC4. Our findings highlight the value of using multiple traits to define complex phenotypes for discovery, which are not captured by single-trait analyses, and may shed light onto new pathways.
Keywords: Anthropometry; Body Size; Genome-Wide Association Study; Genotype; Humans; Models, Genetic; Principal Component Analysis

Rare Exome Sequence Variants in CLCN6 Reduce Blood Pressure Levels and Hypertension Risk. - Yu, Bing; Pulit, Sara L; Hwang, Shih-Jen; Brody, Jennifer A; Amin, Najaf; Auer, Paul L; Bis, Joshua C; Boerwinkle, Eric; Burke, Gregory L; Chakravarti, Aravinda; Correa, Adolfo; Dreisbach, Albert W; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: Rare genetic variants influence blood pressure (BP). METHODS AND RESULTS: Whole-exome sequencing was performed on DNA samples from 17 956 individuals of European ancestry and African ancestry (14 497, first-stage discovery and 3459, second-stage discovery) to examine the effect of rare variants on hypertension and 4 BP traits: systolic BP, diastolic BP, pulse pressure, and mean arterial pressure. Tests of ≈170 000 common variants (minor allele frequency, ≥1%; statistical significance, P≤2.9×10(-7)) and gene-based tests of rare variants (minor allele frequency, <1%; ≈17 000 genes; statistical significance, P≤1.5×10(-6)) were evaluated for each trait and ancestry, followed by multiethnic meta-analyses. In the first-stage discovery, rare coding variants (splicing, stop-gain, stop-loss, nonsynonymous variants, or indels) in CLCN6 were associated with lower diastolic BP (cumulative minor allele frequency, 1.3%; β=-3.20; P=4.1×10(-6)) and were independent of a nearby common variant (rs17367504) previously associated with BP. CLCN6 rare variants were also associated with lower systolic BP (β=-4.11; P=2.8×10(-4)), mean arterial pressure (β=-3.50; P=8.9×10(-6)), and reduced hypertension risk (odds ratio, 0.72; P=0.017). Meta-analysis of the 2-stage discovery samples showed that CLCN6 was associated with lower diastolic BP at exome-wide significance (cumulative minor allele frequency, 1.1%; β=-3.30; P=5.0×10(-7)). CONCLUSIONS: These findings implicate the effect of rare coding variants in CLCN6 in BP variation and offer new insights into BP regulation.

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.

Relation of coagulation factor XI with incident coronary heart disease and stroke: the Cardiovascular Health Study. - Appiah, Duke; Fashanu, Oluwaseun E; Heckbert, Susa R; Cushman, Mary; Psaty, Bruce M; Folsom, Aaron R (Blood Coagul Fibrinolysis, 2016)
The role of coagulation factor XI (FXI) in the cause of arterial thrombotic events remains uncertain. We examined the association of FXI with incident coronary heart disease (CHD), ischemic stroke, and hemorrhagic stroke. Data were from 3394 adults (mean age: 74.5 years) enrolled in the Cardiovascular Health Study who had FXI antigen from plasma samples drawn in 1992-1993 and were followed for cardiovascular events until 30 June 2013. Approximately 63% of participants were women and 17% were black. FXI levels were higher in blacks and women, showed positive associations with high-density lipoprotein and total cholesterol, BMI and diabetes, and negative associations with age and alcohol intake. During median follow-up of 13 years, we identified 1232 incident CHD, 473 ischemic stroke, and 84 hemorrhagic stroke events. In multivariable Cox models adjusted for traditional cardiovascular disease risk factors, the hazard ratio per one SD (32.2 mg/dl) increment of FXI was 1.02 (95% confidence interval: 0.96-1.08) for CHD; 0.94 (0.85-1.04) for ischemic stroke, and 0.85 (0.65-1.10) for hemorrhagic stroke. In this prospective cohort of elderly adults, there was no statistically significant association of higher FXI levels with incident CHD and stroke.

Relations of Postload and Fasting Glucose With Incident Cardiovascular Disease and Mortality Late in Life: The Cardiovascular Health Study. - Brutsaert, Erika F; Shitole, Sanyog; Biggs, Mary Lou; Mukamal, Kenneth J; deBoer, Ian H; Thacker, Evan L; Barzilay, Joshua I; Djoussé, Luc; Ix, Joachim H; Smith, Nicholas L; Kaplan, Robert C; Siscovick, David S; et al. (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: Older adults have a high prevalence of postload hyperglycemia. Postload glucose has shown more robust associations with cardiovascular disease (CVD) and death than fasting glucose, but data in the oldest old are sparse. METHODS: Fasting and 2-hour postload glucose were measured in community-dwelling older adults, mean age 78, at the 1996-1997 follow-up visit of the Cardiovascular Health Study. We evaluated their associations with atherosclerotic CVD (ASCVD) and mortality using standard Cox regression and competing-risks analyses and assessed improvement in prediction-model discrimination with the c-statistic. RESULTS: Among 2,394 participants without treated diabetes and available data on glycemic measures, there were 579 ASCVD events and 1,698 deaths during median follow-up of 11.2 years. In fully adjusted models, both fasting and 2-hour glucose were associated with ASCVD (HR per SD, 1.13 [1.03-1.25] and 1.17 [1.07-1.28], respectively) and all-cause mortality (HR 1.12 [1.07-1.18] and 1.14 [1.08-1.20]). After mutual adjustment, however, the associations for fasting glucose with both outcomes were abolished, but those for postload glucose were largely unchanged. Consistent findings were observed for ASCVD in competing-risks models. CONCLUSION: In adults surviving to advanced old age, postload glucose was associated with ASCVD and mortality independently of fasting glucose, but fasting glucose was not associated with these outcomes independently of postload glucose. These findings affirm the robust association of postload glucose with ASCVD and death late in life.
Keywords: Aged; Aging; Blood Glucose; Cardiovascular Diseases; Fasting; Female; Follow-Up Studies; Glucose; Glucose Tolerance Test; Health Surveys; Humans; Incidence; Male; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; United States

Rooted in risk: genetic predisposition for low-density lipoprotein cholesterol level associates with diminished low-density lipoprotein cholesterol response to statin treatment. - Smit, Roelof Aj; Postmus, Iris; Trompet, Stella; Barnes, Michael R; Warren, Helen; Arsenault, Benoit J; Chasman, Daniel I; Cupples, L Adrienne; Hitman, Graham A; Krauss, Ronald M; Li, Xiaohui; Psaty, Bruce M; et al. (Pharmacogenomics, 2016)
AIMS: To utilize previously reported lead SNPs for low-density lipoprotein cholesterol (LDL-c) levels to find additional loci of importance to statin response, and examine whether genetic predisposition to LDL-c levels associates with differential statin response. METHODS: We investigated effects on statin response of 59 LDL-c SNPs, by combining summary level statistics from the Global Lipids Genetics and Genomic Investigation of Statin Therapy consortia. RESULTS: Lead SNPs for APOE, SORT1 and NPC1L1 were associated with a decreased LDL-c response to statin treatment, as was overall genetic predisposition for increased LDL-c levels as quantified with 59 SNPs, with a 5.4% smaller statin response per standard deviation increase in genetically raised LDL-c levels. CONCLUSION: Genetic predisposition for increased LDL-c level may decrease efficacy of statin therapy.
Keywords: Cholesterol, LDL; Genetic Predisposition to Disease; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide; Triglycerides

Soluble ST2 for Prediction of Heart Failure and Cardiovascular Death in an Elderly, Community-Dwelling Population. - Parikh, Ravi H; Seliger, Stephen L; Christenson, Robert; Gottdiener, John S; Psaty, Bruce M; deFilippi, Christopher R (J Am Heart Assoc, 2016)
BACKGROUND: Soluble ST2 (sST2), a marker of myocyte stretch and fibrosis, has prognostic value in many cardiovascular diseases. We hypothesized that sST2 levels are associated with incident heart failure (HF), including subtypes of preserved (HFpEF) and reduced (HFrEF) ejection fraction, and cardiovascular death. METHODS AND RESULTS: Baseline serum sST2 was measured in 3915 older, community-dwelling subjects from the Cardiovascular Health Study without prevalent HF. sST2 levels were associated with older age, male sex, black race, traditional cardiovascular risk factors, other biomarkers of inflammation, cardiac stretch, myocardial injury, and fibrosis, and abnormal echocardiographic parameters. In longitudinal analysis, greater sST2 was associated with a higher risk of incident HF and cardiovascular death; however, in multivariate models adjusting for other cardiac risk factors and the cardiac-specific biomarker, N-terminal pro-type B natriuretic peptide, these associations were attenuated. In these models, an sST2 level above the US Food and Drug Administration-approved cut-off value (>35 ng/mL) was significantly associated with incident HF (hazard ratio [HR], 1.20; 95% CI, 1.02-1.43) and cardiovascular death (HR, 1.21; 95% CI, 1.02-1.44), and greater sST2 was continuously associated with cardiovascular death (per 1-ln increment: HR, 1.24; 95% CI, 1.02-1.50). sST2 was not associated with the HF subtypes of HFpEF and HFrEF in adjusted analysis. Addition of sST2 to existing risk models of HF and cardiovascular death modestly improved discrimination and reclassification into a higher risk. CONCLUSIONS: The predictive value of sST2 for HF of all subtypes and cardiovascular death is modest in an elderly population despite strong cross-sectional associations with risk factors and underlying cardiac pathology.

SOS2 and ACP1 Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2016)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (nStage1: 111,666; nStage2: 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (PPM1J, EDEM3, ACP1, SPEG, EYA4, CYP1A1, and ATXN2L; PStage1<3.7×10(-7)), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, SOS2 (P=5.4×10(-8) by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of acp1- and sos2-knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.

Study of Cardiovascular Health Outcomes in the Era of Claims Data: The Cardiovascular Health Study. - Psaty, Bruce M; Delaney, Joseph A; Arnold, Alice M; Curtis, Lesley H; Fitzpatrick, Annette L; Heckbert, Susan R; McKnight, Barbara; Ives, Diane; Gottdiener, John S; Kuller, Lewis H; Longstreth, W T (Circulation, 2016)
BACKGROUND: Increasingly, the diagnostic codes from administrative claims data are being used as clinical outcomes. METHODS AND RESULTS: Data from the Cardiovascular Health Study (CHS) were used to compare event rates and risk factor associations between adjudicated hospitalized cardiovascular events and claims-based methods of defining events. The outcomes of myocardial infarction (MI), stroke, and heart failure were defined in 3 ways: the CHS adjudicated event (CHS[adj]), selected International Classification of Diseases, Ninth Edition diagnostic codes only in the primary position for Medicare claims data from the Center for Medicare & Medicaid Services (CMS[1st]), and the same selected diagnostic codes in any position (CMS[any]). Conventional claims-based methods of defining events had high positive predictive values but low sensitivities. For instance, the positive predictive value of International Classification of Diseases, Ninth Edition code 410.x1 for a new acute MI in the first position was 90.6%, but this code identified only 53.8% of incident MIs. The observed event rates for CMS[1st] were low. For MI, the incidence was 14.9 events per 1000 person-years for CHS[adj] MI, 8.6 for CMS[1st] MI, and 12.2 for CMS[any] MI. In general, cardiovascular disease risk factor associations were similar across the 3 methods of defining events. Indeed, traditional cardiovascular disease risk factors were also associated with all first hospitalizations not resulting from an MI. CONCLUSIONS: The use of diagnostic codes from claims data as clinical events, especially when restricted to primary diagnoses, leads to an underestimation of event rates. Additionally, claims-based events data represent a composite end point that includes the outcome of interest and selected (misclassified) nonevent hospitalizations.
Keywords: Blood Glucose; Cardiovascular Diseases; Female; Follow-Up Studies; Health Surveys; Hospitalization; Hospitals, Veterans; Humans; Insurance Claim Review; International Classification of Diseases; Lipids; Male; Managed Care Programs; Medicare; Risk Factors; Sampling Studies; Treatment Outcome; United States

Targeted Sequencing of Genome Wide Significant Loci Associated with Bone Mineral Density (BMD) Reveals Significant Novel and Rare Variants: The Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Hsu, Yi-Hsiang; Li, Guo; Liu, Ching-Ti; Brody, Jennifer A; Karasik, David; Chou, Wen-Chi; Demissie, Serkalem; Nandakumar, Kannabiran; Zhou, Yanhua; Cheng, Chia-Ho; Gill, Richard; Gibbs, Richard A; et al. (Hum Mol Genet, 2016)
BACKGROUND: Bone mineral density (BMD) is a heritable phenotype that predicts fracture risk. We performed fine-mapping by targeted sequencing at WLS, MEF2C, ARHGAP1/F2 and JAG1 loci prioritized by eQTL and bioinformatic approaches among 56 BMD loci from our previous GWAS meta-analysis. METHODS AND RESULTS: Targeted sequencing was conducted in 1,291 Caucasians from the Framingham Heart Study (n=925) and Cardiovascular Health Study (n=366), including 206 women and men with extreme low femoral neck (FN) BMD. A total of 4,964 sequence variants (SNVs) were observed and 80% were rare with MAF <1%. The associations between previously identified SNPs in these loci and BMD, while nominally significant in sequenced participants, were no longer significant after multiple testing corrections. Conditional analyses did not find protein-coding variants that may be responsible for GWAS signals. On the other hand, in the sequenced subjects, we identified novel associations in WLS, ARHGAP1, and 5' of MEF2C (p-values < 8x10(-5); false discovery rate (FDR) q-values < 0.01) that were much more strongly associated with BMD compared to the GWAS SNPs. These associated SNVs are less-common; independent from previous GWAS signals in the same loci; and located in gene regulatory elements. CONCLUSIONS: Our findings suggest that protein-coding variants in selected GWAS loci did not contribute to GWAS signals. By performing targeted sequencing in GWAS loci, we identified less-common and rare non-coding SNVs associated with BMD independently from GWAS common SNPs, suggesting both common and less-common variants may associate with disease risks and phenotypes in the same loci.

Thyroid Function Within the Reference Range and the Risk of Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Collet, Tinh-Hai; Ikram, M Arfan; Blum, Manuel R; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Portegies, Marileen L P; Iervasi, Giorgio; Medici, Marco; et al. (J Clin Endocrinol Metab, 2016)
CONTEXT: The currently applied reference ranges for thyroid function are under debate. Despite evidence that thyroid function within the reference range is related with several cardiovascular disorders, its association with the risk of stroke has not been evaluated previously. DESIGN AND SETTING: We identified studies through a systematic literature search and the Thyroid Studies Collaboration, a collaboration of prospective cohort studies. Studies measuring baseline TSH, free T4, and stroke outcomes were included, and we collected individual participant data from each study, including thyroid function measurements and incident all stroke (combined fatal and nonfatal) and fatal stroke. The applied reference range for TSH levels was between 0.45 and 4.49 mIU/L. RESULTS: We collected individual participant data on 43 598 adults with TSH within the reference range from 17 cohorts, with a median follow-up of 11.6 years (interquartile range 5.1-13.9), including 449 908 person-years. Age- and sex-adjusted pooled hazard ratio for TSH was 0.78 (95% confidence interval [CI] 0.65-0.95 across the reference range of TSH) for all stroke and 0.83 (95% CI 0.62-1.09) for fatal stroke. For the free T4 analyses, the hazard ratio was 1.08 (95% CI 0.99-1.15 per SD increase) for all stroke and 1.10 (95% CI 1.04-1.19) for fatal stroke. This was independent of cardiovascular risk factors including systolic blood pressure, total cholesterol, smoking, and prevalent diabetes. CONCLUSION: Higher levels of TSH within the reference range may decrease the risk of stroke, highlighting the need for further research focusing on the clinical consequences associated with differences within the reference range of thyroid function.

Trans-ethnic Meta-analysis and Functional Annotation Illuminates the Genetic Architecture of Fasting Glucose and Insulin. - Liu, Ching-Ti; Raghavan, Sridharan; Maruthur, Nisa; Kabagambe, Edmond Kato; Hong, Jaeyoung; Ng, Maggie C Y; Hivert, Marie-France; Lu, Yingchang; An, Ping; Bentley, Amy R; Drolet, Anne M; Gaulton, Kyle J; et al. (Am J Hum Genet, 2016)
Knowledge of the genetic basis of the type 2 diabetes (T2D)-related quantitative traits fasting glucose (FG) and insulin (FI) in African ancestry (AA) individuals has been limited. In non-diabetic subjects of AA (n = 20,209) and European ancestry (EA; n = 57,292), we performed trans-ethnic (AA+EA) fine-mapping of 54 established EA FG or FI loci with detailed functional annotation, assessed their relevance in AA individuals, and sought previously undescribed loci through trans-ethnic (AA+EA) meta-analysis. We narrowed credible sets of variants driving association signals for 22/54 EA-associated loci; 18/22 credible sets overlapped with active islet-specific enhancers or transcription factor (TF) binding sites, and 21/22 contained at least one TF motif. Of the 54 EA-associated loci, 23 were shared between EA and AA. Replication with an additional 10,096 AA individuals identified two previously undescribed FI loci, chrX FAM133A (rs213676) and chr5 PELO (rs6450057). Trans-ethnic analyses with regulatory annotation illuminate the genetic architecture of glycemic traits and suggest gene regulation as a target to advance precision medicine for T2D. Our approach to utilize state-of-the-art functional annotation and implement trans-ethnic association analysis for discovery and fine-mapping offers a framework for further follow-up and characterization of GWAS signals of complex trait loci.

Whole Exome Sequencing in Atrial Fibrillation. - Lubitz, Steven A; Brody, Jennifer A; Bihlmeyer, Nathan A; Roselli, Carolina; Weng, Lu-Chen; Christophersen, Ingrid E; Alonso, Alvaro; Boerwinkle, Eric; Gibbs, Richard A; Bis, Joshua C; Cupples, L Adrienne; Mohler, Peter J; et al. (PLoS Genet, 2016)
Atrial fibrillation (AF) is a morbid and heritable arrhythmia. Over 35 genes have been reported to underlie AF, most of which were described in small candidate gene association studies. Replication remains lacking for most, and therefore the contribution of coding variation to AF susceptibility remains poorly understood. We examined whole exome sequencing data in a large community-based sample of 1,734 individuals with and 9,423 without AF from the Framingham Heart Study, Cardiovascular Health Study, Atherosclerosis Risk in Communities Study, and NHLBI-GO Exome Sequencing Project and meta-analyzed the results. We also examined whether genetic variation was enriched in suspected AF genes (N = 37) in AF cases versus controls. The mean age ranged from 59 to 73 years; 8,656 (78%) were of European ancestry. None of the 99,404 common variants evaluated was significantly associated after adjusting for multiple testing. Among the most significantly associated variants was a common (allele frequency = 86%) missense variant in SYNPO2L (rs3812629, p.Pro707Leu, [odds ratio 1.27, 95% confidence interval 1.13-1.43, P = 6.6x10-5]) which lies at a known AF susceptibility locus and is in linkage disequilibrium with a top marker from prior analyses at the locus. We did not observe significant associations between rare variants and AF in gene-based tests. Individuals with AF did not display any statistically significant enrichment for common or rare coding variation in previously implicated AF genes. In conclusion, we did not observe associations between coding genetic variants and AF, suggesting that large-effect coding variation is not the predominant mechanism underlying AF. A coding variant in SYNPO2L requires further evaluation to determine whether it is causally related to AF. Efforts to identify biologically meaningful coding variation underlying AF may require large sample sizes or populations enriched for large genetic effects.

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis. - Polfus, Linda M; Khajuria, Rajiv K; Schick, Ursula M; Pankratz, Nathan; Pazoki, Raha; Brody, Jennifer A; Chen, Ming-Huei; Auer, Paul L; Floyd, James S; Huang, Jie; Lange, Leslie; van Rooij, Frank J A; et al. (Am J Hum Genet, 2016)

Absolute Rates of Heart Failure, Coronary Heart Disease, and Stroke in Chronic Kidney Disease: An Analysis of 3 Community-Based Cohort Studies. - Bansal, Nisha; Katz, Ronit; Robinson-Cohen, Cassianne; Odden, Michelle C; Dalrymple, Lorien; Shlipak, Michael G; Sarnak, Mark J; Siscovick, David S; Zelnick, Leila; Psaty, Bruce M; Kestenbaum, Bryan; Correa, Adolfo; et al. (JAMA Cardiol, 2017)
Importance: Cardiovascular disease is the leading cause of morbidity and mortality in patients with chronic kidney disease (CKD). Understanding the relative contributions of cardiovascular disease event types to the excess burden of cardiovascular disease is important for developing effective strategies to improve outcomes. Objective: To determine absolute rates and risk differences of incident heart failure (HF), coronary heart disease (CHD), and stroke in participants with vs without CKD. Design, Setting and Participants: We pooled participants without prevalent cardiovascular disease from 3 community-based cohort studies: the Jackson Heart Study, Cardiovascular Health Study, and Multi-Ethnic Study of Atherosclerosis. The Jackson Heart Study was conducted between 2000 and 2010, the Cardiovascular Health Study was conducted between 1989 and 2003, and the Multi-Ethnic Study of Atherosclerosis was conducted between 2000 and 2012. Exposures: Chronic kidney disease was defined as estimated glomerular filtration rate less than 60 mL/min/1.73 m2, calculated using the combined creatinine-cystatin C CKD-Epidemiology Collaboration Equation. Main Outcomes and Measures: Poisson regression was used to calculate incidence rates (IRs) and risk differences of adjudicated incident HF, CHD, and stroke, comparing participants with vs without CKD. Results: Among 14 462 participants, the mean (SD) age was 63 (12) years, 59% (n = 8533) were women, and 44% (n = 6363) were African American. Overall, 1461 (10%) had CKD (mean [SD] estimated glomerular filtration rate, 49 [10] mL/min/1.73 m2). Unadjusted IRs for participants with and without CKD, respectively, were 22.0 (95% CI, 19.3-24.8) and 6.2 (95% CI, 5.8-6.7) per 1000 person-years for HF; 24.5 (95% CI, 21.6-27.5) and 8.4 (95% CI, 7.9-9.0) per 1000 person-years for CHD; and 13.4 (95% CI, 11.3-15.5) and 4.8 (95% CI, 4.4-5.3) for stroke. Adjusting for demographics, cohort, hypertension, diabetes, hyperlipidemia, and tobacco use, risk differences comparing participants with vs without CKD (per 1000 person-years) were 2.3 (95% CI, 1.2-3.3) for HF, 2.3 (95% CI, 1.2-3.4) for CHD, and 0.8 (95% CI, 0.09-1.5) for stroke. Among African American and Hispanic participants, adjusted risk differences comparing participants with vs without CKD for HF were 3.5 (95% CI, 1.5-5.5) and 7.8 (95% CI, 2.2-13.3) per 1000 person-years, respectively. Conclusions and Relevance: Among 3 diverse community-based cohorts, CKD was associated with an increased risk of HF that was similar in magnitude to CHD and greater than stroke. The excess risk of HF associated with CKD was particularly large among African American and Hispanic individuals. Efforts to improve health outcomes for patients with CKD should prioritize HF in addition to CHD prevention.

Analysis commons, a team approach to discovery in a big-data environment for genetic epidemiology. - Brody, Jennifer A; Morrison, Alanna C; Bis, Joshua C; O'Connell, Jeffrey R; Brown, Michael R; Huffman, Jennifer E; Ames, Darren C; Carroll, Andrew; Conomos, Matthew P; Gabriel, Stacey; Gibbs, Richard A; Gogarten, Stephanie M; et al. (Nat Genet, 2017)

The Association Between IGF-I and IGFBP-3 and Incident Diabetes in an Older Population of Men and Women in the Cardiovascular Health Study. - Aneke-Nash, Chino S; Xue, XiaoNan; Qi, Qibin; Biggs, Mary L; Cappola, Anne; Kuller, Lewis; Pollak, Michael; Psaty, Bruce M; Siscovick, David; Mukamal, Kenneth; Strickler, Howard D; Kaplan, Robert C (J Clin Endocrinol Metab, 2017)
Context: Insulin-like growth factor-I (IGF-I) has structural and functional similarities to insulin and may play a role in glucose homeostasis, along with insulin-like growth factor binding protein-3 (IGFBP-3), which binds the majority of circulating IGF-I. Objective: To assess whether IGF-I and IGFBP-3 are associated with a higher risk of incident diabetes in older adults. Design: Participants in the Cardiovascular Health Study (n = 3133), a cohort of adults aged ≥65 years, were observed for 16 years (n = 3133) for the development of incident diabetes. Statistical models were fit separately for men and women because of interactions with sex (P interaction: IGF-I, 0.02; IGFBP-3, 0.009) and were adjusted for relevant covariates. Setting: General community. Participants: Older adults who were nondiabetic at baseline and who did not develop diabetes within the first year of follow-up. Interventions: Not applicable. Main Outcome Measure: Incident diabetes as measured by fasting plasma glucose (FPG) ≥126 mg/dL, non-FPG ≥200 mg/dL, use of pharmacological treatment of diabetes, or existence of two or more inpatient or three or more outpatient or (at least one inpatient and at least one outpatient) Centers for Medicare & Medicaid Services claims with the diagnostic International Classification of Diseases, Ninth Revision, Clinical Modification code of 250.xx. Results: In women, higher IGFBP-3 (hazard ratio tertile 3 vs tertile 1 = 2.30; 95% confidence interval, 1.55 to 3.40; P trend < 0.0001) was significantly associated with incident diabetes. Total IGF-I was not significantly associated with incident diabetes. In men, neither IGF-I nor IGFBP-3 was significantly associated with incident diabetes. Conclusions: We confirmed a previously reported association between circulating IGFBP-3 and diabetes risk in the older adult population, establishing that this association is present among women but could not be shown to be associated in men.
Keywords: Aged; Aged, 80 and over; Biomarkers; Blood Glucose; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus; Female; Humans; Incidence; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Longitudinal Studies; Male; New England; Prospective Studies; Risk

Association of Blood Pressure Trajectory With Mortality, Incident Cardiovascular Disease, and Heart Failure in the Cardiovascular Health Study. - Smitson, Christopher C; Scherzer, Rebecca; Shlipak, Michael G; Psaty, Bruce M; Newman, Anne B; Sarnak, Mark J; Odden, Michelle C; Peralta, Carmen A (Am J Hypertens, 2017)
BACKGROUND: Common blood pressure (BP) trajectories are not well established in elderly persons, and their association with clinical outcomes is uncertain. METHODS: We used hierarchical cluster analysis to identify discrete BP trajectories among 4,067 participants in the Cardiovascular Health Study using repeated BP measures from years 0 to 7. We then evaluated associations of each BP trajectory cluster with all-cause mortality, incident cardiovascular disease (CVD, defined as stroke or myocardial infarction) (N = 2,837), and incident congestive heart failure (HF) (N = 3,633) using Cox proportional hazard models. RESULTS: Median age was 77 years at year 7. Over a median 9.3 years of follow-up, there were 2,475 deaths, 659 CVD events, and 1,049 HF events. The cluster analysis identified 3 distinct trajectory groups. Participants in cluster 1 (N = 1,838) had increases in both systolic (SBP) and diastolic (DBP) BPs, whereas persons in cluster 2 (N = 1,109) had little change in SBP but declines in DBP. Persons in cluster 3 (N = 1,120) experienced declines in both SBP and DBP. After multivariable adjustment, clusters 2 and 3 were associated with increased mortality risk relative to cluster 1 (hazard ratio = 1.21, 95% confidence interval: 1.06-1.37 and hazard ratio = 1.20, 95% confidence interval: 1.05-1.36, respectively). Compared to cluster 1, cluster 3 had higher rates of incident CVD but associations were not statistically significant in demographic-adjusted models (hazard ratio = 1.16, 95% confidence interval: 0.96-1.39). Findings were similar when stratified by use of antihypertensive therapy. CONCLUSIONS: Among community-dwelling elders, distinct BP trajectories were identified by integrating both SBP and DBP. These clusters were found to have differential associations with outcomes.

Atrial ectopy as a mediator of the association between race and atrial fibrillation. - Christensen, Matthew A; Nguyen, Kaylin T; Stein, Phyllis K; Fohtung, Raymond B; Soliman, Elsayed Z; Dewland, Thomas A; Vittinghoff, Eric; Psaty, Bruce M; Heckbert, Susan R; Marcus, Gregory M (Heart Rhythm, 2017)
BACKGROUND: Blacks have a lower risk of atrial fibrillation (AF) despite having more AF risk factors, but the mechanism remains unknown. Premature atrial contraction (PAC) burden is a recently identified risk factor for AF. OBJECTIVE: The purpose of this study was to determine whether the burden of PACs explains racial differences in AF risk. METHODS: PAC burden (number per hour) was assessed by 24-hour ambulatory electrocardiographic (ECG) monitoring in a randomly selected subset of patients in the Cardiovascular Health Study. Participants were followed prospectively for the development of AF, diagnosed by study ECG and hospital admission records. RESULTS: Among 938 participants (median age 73 years; 34% black; 58% female), 206 (22%) developed AF over a median follow-up of 11.0 years (interquartile range 6.1-13.4). After adjusting for age, sex, body mass index, coronary disease, congestive heart failure, diabetes, hypertension, alcohol consumption, smoking status, and study site, black race was associated with a 42% lower risk of AF (hazard ratio 0.58, 95% confidence interval [CI] 0.40-0.85; P = .005). The baseline PAC burden was 2.10 times (95% CI 1.57-2.83; P <.001) higher in whites than blacks. There was no detectable difference in premature ventricular contraction (PVC) burden by race. PAC burden mediated 19.5% (95% CI 6.3-52.5) of the adjusted association between race and AF. CONCLUSION: On average, whites exhibited more PACs than blacks, and this difference statistically explains a modest proportion of the differential risk of AF by race. The differential PAC burden, without differences in PVCs, by race suggests that identifiable common exposures or genetic influences might be important to atrial pathophysiology.

Comparing methods to address bias in observational data: statin use and cardiovascular events in a US cohort. - Kaiser, Paulina; Arnold, Alice M; Benkeser, David; Zeki Al Hazzouri, Adina; Hirsch, Calvin H; Psaty, Bruce M; Odden, Michelle C (Int J Epidemiol, 2017)
Background: The theoretical conditions under which causal estimates can be derived from observational data are challenging to achieve in the real world. Applied examples can help elucidate the practical limitations of methods to estimate randomized-controlled trial effects from observational data. Methods: We used six methods with varying design and analytic features to compare the 5-year risk of incident myocardial infarction among statin users and non-users, and used non-cardiovascular mortality as a negative control outcome. Design features included restriction to a statin-eligible population and new users only; analytic features included multivariable adjustment and propensity score matching. Results: We used data from 5294 participants in the Cardiovascular Health Study from 1989 to 2004. For non-cardiovascular mortality, most methods produced protective estimates with confidence intervals that crossed the null. The hazard ratio (HR) was 0.92, 95% confidence interval: 0.58, 1.46 using propensity score matching among eligible new users. For myocardial infarction, all estimates were strongly protective; the propensity score-matched analysis among eligible new users resulted in a HR of 0.55 (0.29, 1.05)-a much stronger association than observed in randomized controlled trials. Conclusions: In designs that compare active treatment with non-treated participants to evaluate effectiveness, methods to address bias in observational data may be limited in real-world settings by residual bias.

Comparison of HapMap and 1000 Genomes Reference Panels in a Large-Scale Genome-Wide Association Study. - de Vries, Paul S; Sabater-Lleal, Maria; Chasman, Daniel I; Trompet, Stella; Ahluwalia, Tarunveer S; Teumer, Alexander; Kleber, Marcus E; Chen, Ming-Huei; Wang, Jie Jin; Attia, John R; Marioni, Riccardo E; Steri, Maristella; et al. (PLoS One, 2017)
An increasing number of genome-wide association (GWA) studies are now using the higher resolution 1000 Genomes Project reference panel (1000G) for imputation, with the expectation that 1000G imputation will lead to the discovery of additional associated loci when compared to HapMap imputation. In order to assess the improvement of 1000G over HapMap imputation in identifying associated loci, we compared the results of GWA studies of circulating fibrinogen based on the two reference panels. Using both HapMap and 1000G imputation we performed a meta-analysis of 22 studies comprising the same 91,953 individuals. We identified six additional signals using 1000G imputation, while 29 loci were associated using both HapMap and 1000G imputation. One locus identified using HapMap imputation was not significant using 1000G imputation. The genome-wide significance threshold of 5×10-8 is based on the number of independent statistical tests using HapMap imputation, and 1000G imputation may lead to further independent tests that should be corrected for. When using a stricter Bonferroni correction for the 1000G GWA study (P-value < 2.5×10-8), the number of loci significant only using HapMap imputation increased to 4 while the number of loci significant only using 1000G decreased to 5. In conclusion, 1000G imputation enabled the identification of 20% more loci than HapMap imputation, although the advantage of 1000G imputation became less clear when a stricter Bonferroni correction was used. More generally, our results provide insights that are applicable to the implementation of other dense reference panels that are under development.

Concordance With Prevention Guidelines and Subsequent Cancer, Cardiovascular Disease, and Mortality: A Longitudinal Study of Older Adults. - Greenlee, Heather; Strizich, Garrett; Lovasi, Gina S; Kaplan, Robert C; Biggs, Mary L; Li, Christopher I; Richardson, John; Burke, Gregory L; Fitzpatrick, Annette L; Fretts, Amanda M; Psaty, Bruce M; Fried, Linda P (Am J Epidemiol, 2017)
Reports on the associations between multiple clinical and behavioral health indicators and major health outcomes among older adults are scarce. We prospectively examined concordance with guidelines from the American Cancer Society and American Heart Association for disease prevention in relation to cancer, cardiovascular disease (CVD), and mortality among Cardiovascular Health Study enrollees aged 65-98 years who, at baseline assessment in 1989-1996 (n = 3,491), were free of CVD and cancer. Total and cause-specific mortality, as well as incidence of cancer and CVD, were lower with higher guideline concordance. Independent of body mass index, blood pressure, total cholesterol, and fasting plasma glucose, better health behaviors (diet, physical activity, and alcohol consumption) were associated with lower mortality (2-sided P < 0.0001). Among individuals with ideal levels for 3-4 of these 4 cardiometabolic biomarkers, those with poor concordance with health behavior recommendations had higher mortality compared with those who had the highest concordance with these behavioral recommendations (adjusted mortality hazard ratio = 1.82, 95% confidence interval: 1.25, 2.67). Older adults who are concordant with recommendations for cancer and CVD prevention have reduced rates of chronic disease and mortality. Interventions to achieve and maintain healthy lifestyle behaviors may offer benefits both in the presence and absence of adverse traditional clinical risk factors.
Keywords: Aged; Aged, 80 and over; American Cancer Society; American Heart Association; Body Mass Index; Cardiovascular Diseases; Cause of Death; Diet; Exercise; Female; Guideline Adherence; Healthy Lifestyle; Humans; Incidence; Longitudinal Studies; Male; Neoplasms; Practice Guidelines as Topic; Prospective Studies; United States

Detection of genetic loci associated with plasma fetuin-A: A meta-analysis of genome-wide association studies from the CHARGE Consortium. - Jensen, Majken K; Jensen, Richard A; Mukamal, Kenneth J; Guo, Xiuqing; Yao, Jie; Sun, Qi; Cornelis, Marilyn; Liu, Yongmei; Chen, Ming-Huei; Kizer, Jorge R; Djoussé, Luc; Siscovick, David S; et al. (Hum Mol Genet, 2017)
Plasma fetuin-A is associated with type 2 diabetes, and AHSG, the gene encoding fetuin-A, has been identified as a susceptibility locus for diabetes and metabolic syndrome. Thus far, unbiased investigations of the genetic determinants of plasma fetuin-A concentrations have not been conducted. We searched for single nucleotide polymorphisms (SNPs) related to fetuin-A concentrations by a genome-wide association study in six population-based studies.We examined the association of fetuin-A levels with ∼ 2.5 million genotyped and imputed SNPs in 9,055 participants of European descent and 2,119 African Americans. In both ethnicities, strongest associations were centered in a region with a high degree of LD near the AHSG locus. Among 136 genome-wide significant (p < 0.05x10-8) SNPs near the AHSG locus, the top SNP was rs4917 (p = 1.27x10-303), a known coding SNP in exon 6 that is associated with a 0.06 g/L (∼13%) lower fetuin-A level. This variant alone explained 14% of the variation in fetuin-A levels. Analyses conditioned on rs4917 indicated that the strong association with the AHSG locus stems from additional independent associations of multiple variants among European Americans. In conclusion, levels of fetuin-A in plasma are strongly associated with SNPs in its encoding gene, AHSG, but not elsewhere in the genome. Given the strength of the associations observed for multiple independent SNPs, the AHSG gene is an example of a candidate locus suitable for additional investigations including fine mapping to elucidate the biological basis of the findings and further functional experiments to clarify AHSG as a potential therapeutic target.

Discovery and fine-mapping of adiposity loci using high density imputation of genome-wide association studies in individuals of African ancestry: African ancestry anthropometry genetics consortium. - Ng, Maggie C Y; Graff, Mariaelisa; Lu, Yingchang; Justice, Anne E; Mudgal, Poorva; Liu, Ching-Ti; Young, Kristin; Yanek, Lisa R; Feitosa, Mary F; Wojczynski, Mary K; Rand, Kristin; Brody, Jennifer A; et al. (PLoS Genet, 2017)
Genome-wide association studies (GWAS) have identified >300 loci associated with measures of adiposity including body mass index (BMI) and waist-to-hip ratio (adjusted for BMI, WHRadjBMI), but few have been identified through screening of the African ancestry genomes. We performed large scale meta-analyses and replications in up to 52,895 individuals for BMI and up to 23,095 individuals for WHRadjBMI from the African Ancestry Anthropometry Genetics Consortium (AAAGC) using 1000 Genomes phase 1 imputed GWAS to improve coverage of both common and low frequency variants in the low linkage disequilibrium African ancestry genomes. In the sex-combined analyses, we identified one novel locus (TCF7L2/HABP2) for WHRadjBMI and eight previously established loci at P < 5×10-8: seven for BMI, and one for WHRadjBMI in African ancestry individuals. An additional novel locus (SPRYD7/DLEU2) was identified for WHRadjBMI when combined with European GWAS. In the sex-stratified analyses, we identified three novel loci for BMI (INTS10/LPL and MLC1 in men, IRX4/IRX2 in women) and four for WHRadjBMI (SSX2IP, CASC8, PDE3B and ZDHHC1/HSD11B2 in women) in individuals of African ancestry or both African and European ancestry. For four of the novel variants, the minor allele frequency was low (<5%). In the trans-ethnic fine mapping of 47 BMI loci and 27 WHRadjBMI loci that were locus-wide significant (P < 0.05 adjusted for effective number of variants per locus) from the African ancestry sex-combined and sex-stratified analyses, 26 BMI loci and 17 WHRadjBMI loci contained ≤ 20 variants in the credible sets that jointly account for 99% posterior probability of driving the associations. The lead variants in 13 of these loci had a high probability of being causal. As compared to our previous HapMap imputed GWAS for BMI and WHRadjBMI including up to 71,412 and 27,350 African ancestry individuals, respectively, our results suggest that 1000 Genomes imputation showed modest improvement in identifying GWAS loci including low frequency variants. Trans-ethnic meta-analyses further improved fine mapping of putative causal variants in loci shared between the African and European ancestry populations.

Discovery and fine-mapping of loci associated with monounsaturated fatty acids through trans-ethnic meta-analysis in Chinese and European populations. - Hu, Yao; Tanaka, Toshiko; Zhu, Jingwen; Guan, Weihua; Wu, Jason H Y; Psaty, Bruce M; McKnight, Barbara; King, Irena B; Sun, Qi; Richard, Melissa; Manichaikul, Ani; Frazier-Wood, Alexis C; et al. (J Lipid Res, 2017)
Monounsaturated fatty acids (MUFAs) are unsaturated fatty acids with one double bond and are derived from endogenous synthesis and dietary intake. Accumulating evidence has suggested that plasma and erythrocyte MUFA levels were associated with cardiometabolic disorders including cardiovascular disease (CVD), type 2 diabetes (T2D) and metabolic syndrome (MS). Previous genome-wide association studies (GWAS) have identified seven loci for plasma and erythrocyte palmitoleic acid and oleic acid levels in populations of European origin. To identify additional MUFA-associated loci and the potential causal variant at each locus, we performed ethnic-specific GWAS meta-analyses and trans-ethnic meta-analyses in over 15,000 participants of Chinese- and European-ancestry. We identified novel genome-wide significant associations for vaccenic acid at FADS1/2 and PKD2L1 [log10(Bayes factor)>=8.07] and for gondoic acid at FADS1/2 and GCKR [log10(Bayes factor)>=61619;6.22], and also observed improved fine-mapping resolutions at FADS1/2 and GCKR loci. The greatest improvement was observed at GCKR, where the number of variants in the 99% credible set was reduced from 16 (covering ~95kb) to five (covering ~20kb, including a missense variant rs1260326) after trans-ethnic meta-analysis. We also confirmed the previously reported associations of PKD2L1, FADS1/2, GCKR and HIF1AN with palmitoleic acid and of FADS1/2 and LPCAT3 with oleic acid in the Chinese-specific GWAS and trans-ethnic meta-analyses. Pathway-based analyses suggested that the identified loci were enriched in unsaturated fatty acids metabolism and signaling pathways. Our findings provided novel insight into the genetic basis relevant to MUFA metabolism and biology.

Discovery of novel heart rate-associated loci using the Exome Chip. - van den Berg, Marten E; Warren, Helen R; Cabrera, Claudia P; Verweij, Niek; Mifsud, Borbala; Haessler, Jeffrey; Bihlmeyer, Nathan A; Fu, Yi-Ping; Weiss, Stefan; Lin, Henry J; Grarup, Niels; Li-Gao, Ruifang; et al. (Hum Mol Genet, 2017)
Background Resting heart rate is a heritable trait, and an increase in heart rate is associated with increased mortality risk. GWAS analyses have found loci associated with resting heart rate, at the time of our study these loci explained 0.9% of the variation.Aim To discover new genetic loci associated with heart rate from Exome Chip meta-analyses.Methods Heart rate was measured from either elecrtrocardiograms or pulse recordings. We meta-analysed heart rate association results from 104,452 European-ancestry individuals from 30 cohorts, genotyped using the Exome Chip. Twenty-four variants were selected for follow-up in an independent dataset (UK Biobank, N = 134,251). Conditional and gene-based testing was undertaken, and variants were investigated with bioinformatics methods.Results We discovered five novel heart rate loci, and one new independent low-frequency non-synonymous variant in an established heart rate locus (KIAA1755). Lead variants in four of the novel loci are non-synonymous variants in the genes C10orf71, DALDR3, TESK2, SEC31B. The variant at SEC31B is significantly associated with SEC31B expression in heart and tibial nerve tissue. Further candidate genes were detected from long range regulatory chromatin interactions in heart tissue (SCD, SLF2, MAPK8). We observed significant enrichment in DNase I hypersensitive sites in fetal heart and lung. Moreover, enrichment was seen for the first time in human neuronal progenitor cells (derived from embryonic stem cells) and fetal muscle samples by including our novel variants.Conclusion Our findings advance the knowledge of the genetic architecture of heart rate, and indicate new candidate genes for follow-up functional studies.

DNA Methylation Analysis Identifies Loci for Blood Pressure Regulation. - Richard, Melissa A; Huan, Tianxiao; Ligthart, Symen; Gondalia, Rahul; Jhun, Min A; Brody, Jennifer A; Irvin, Marguerite R; Marioni, Riccardo; Shen, Jincheng; Tsai, Pei-Chien; Montasser, May E; Jia, Yucheng; et al. (Am J Hum Genet, 2017)
Genome-wide association studies have identified hundreds of genetic variants associated with blood pressure (BP), but sequence variation accounts for a small fraction of the phenotypic variance. Epigenetic changes may alter the expression of genes involved in BP regulation and explain part of the missing heritability. We therefore conducted a two-stage meta-analysis of the cross-sectional associations of systolic and diastolic BP with blood-derived genome-wide DNA methylation measured on the Infinium HumanMethylation450 BeadChip in 17,010 individuals of European, African American, and Hispanic ancestry. Of 31 discovery-stage cytosine-phosphate-guanine (CpG) dinucleotides, 13 replicated after Bonferroni correction (discovery: N = 9,828, p < 1.0 × 10-7; replication: N = 7,182, p < 1.6 × 10-3). The replicated methylation sites are heritable (h2 > 30%) and independent of known BP genetic variants, explaining an additional 1.4% and 2.0% of the interindividual variation in systolic and diastolic BP, respectively. Bidirectional Mendelian randomization among up to 4,513 individuals of European ancestry from 4 cohorts suggested that methylation at cg08035323 (TAF1B-YWHAQ) influences BP, while BP influences methylation at cg00533891 (ZMIZ1), cg00574958 (CPT1A), and cg02711608 (SLC1A5). Gene expression analyses further identified six genes (TSPAN2, SLC7A11, UNC93B1, CPT1A, PTMS, and LPCAT3) with evidence of triangular associations between methylation, gene expression, and BP. Additional integrative Mendelian randomization analyses of gene expression and DNA methylation suggested that the expression of TSPAN2 is a putative mediator of association between DNA methylation at cg23999170 and BP. These findings suggest that heritable DNA methylation plays a role in regulating BP independently of previously known genetic variants.
Keywords: Aged; Blood Pressure; CpG Islands; Cross-Sectional Studies; DNA Methylation; Epigenesis, Genetic; Genetic Variation; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Middle Aged; Nerve Tissue Proteins; Quantitative Trait Loci; Tetraspanins

Ectopy on a Single 12-Lead ECG, Incident Cardiac Myopathy, and Death in the Community. - Nguyen, Kaylin T; Vittinghoff, Eric; Dewland, Thomas A; Dukes, Jonathan W; Soliman, Elsayed Z; Stein, Phyllis K; Gottdiener, John S; Alonso, Alvaro; Chen, Lin Y; Psaty, Bruce M; Heckbert, Susan R; Marcus, Gregory M (J Am Heart Assoc, 2017)
BACKGROUND: Atrial fibrillation and heart failure are 2 of the most common diseases, yet ready means to identify individuals at risk are lacking. The 12-lead ECG is one of the most accessible tests in medicine. Our objective was to determine whether a premature atrial contraction observed on a standard 12-lead ECG would predict atrial fibrillation and mortality and whether a premature ventricular contraction would predict heart failure and mortality. METHODS AND RESULTS: We utilized the CHS (Cardiovascular Health) Study, which followed 5577 participants for a median of 12 years, as the primary cohort. The ARIC (Atherosclerosis Risk in Communities Study), the replication cohort, captured data from 15 792 participants over a median of 22 years. In the CHS, multivariable analyses revealed that a baseline 12-lead ECG premature atrial contraction predicted a 60% increased risk of atrial fibrillation (hazard ratio, 1.6; 95% CI, 1.3-2.0; P<0.001) and a premature ventricular contraction predicted a 30% increased risk of heart failure (hazard ratio, 1.3; 95% CI, 1.0-1.6; P=0.021). In the negative control analyses, neither predicted incident myocardial infarction. A premature atrial contraction was associated with a 30% increased risk of death (hazard ratio, 1.3; 95% CI, 1.1-1.5; P=0.008) and a premature ventricular contraction was associated with a 20% increased risk of death (hazard ratio, 1.2; 95% CI, 1.0-1.3; P=0.044). Similarly statistically significant results for each analysis were also observed in ARIC. CONCLUSIONS: Based on a single standard ECG, a premature atrial contraction predicted incident atrial fibrillation and death and a premature ventricular contraction predicted incident heart failure and death, suggesting that this commonly used test may predict future disease.

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

Fibroblast Growth Factor 23, Mineral Metabolism, and Adiposity in Normal Kidney Function. - Zaheer, Sarah; de Boer, Ian H; Allison, Matthew; Brown, Jenifer M; Psaty, Bruce M; Robinson-Cohen, Cassianne; Michos, Erin D; Ix, Joachim H; Kestenbaum, Bryan; Siscovick, David; Vaidya, Anand (J Clin Endocrinol Metab, 2017)
Context: Obesity is associated with poor bone mineralization and quality. Fibroblast growth factor 23 (FGF23) plays an important role in skeletal physiology. Objective: To test hypothesis that greater adiposity results in higher FGF23 levels among individuals with normal estimated glomerular filtration rate (eGFR). Design, Setting, Participants: Cross-sectional analyses among participants with eGFR ≥60 mL/min/1.73m2. We assessed the association between crude [body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR); n = 5610] and refined (abdominal adipose tissue area by computed tomography; n = 1313) measures of adiposity and FGF23 using multivariable linear regression. Main Outcome Measure: Serum FGF23. Results: FGF23 was higher across BMI categories (BMI <25: 37.7; BMI 25 to 29.99: 38.7; BMI 30 to 39.99: 39.8; BMI ≥40: 40.9 pg/mL, unadjusted P trend < 0.0001). The association between BMI and FGF23 was independent of known confounders of FGF23 (adjusted β = +7.2% higher FGF23 per 10 kg/m2; P < 0.0001). Similar results were observed using WC and WHR. Abdominal adipose tissue area was also independently associated with higher FGF23 (P < 0.01). Notably, the positive associations between FGF23 and adiposity were observed despite the fact that eGFR did not decline and serum phosphate levels did not increase with adiposity. Conclusion: In a large cohort with normal kidney function, adiposity was associated with higher FGF23 levels independent of known confounders, including eGFR and phosphate. Further studies are needed to evaluate the causes of higher FGF23 in settings of greater adiposity and the potential impact on skeletal health.
Keywords: Adiposity; Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Fibroblast Growth Factors; Glomerular Filtration Rate; Humans; Kidney; Male; Middle Aged; Minerals; Renal Insufficiency, Chronic; Risk Factors

Fifteen Genetic Loci Associated With the Electrocardiographic P Wave. - Christophersen, Ingrid E; Magnani, Jared W; Yin, Xiaoyan; Barnard, John; Weng, Lu-Chen; Arking, Dan E; Niemeijer, Maartje N; Lubitz, Steven A; Avery, Christy L; Duan, Qing; Felix, Stephan B; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: The P wave on an ECG is a measure of atrial electric function, and its characteristics may serve as predictors for atrial arrhythmias. Increased mean P-wave duration and P-wave terminal force traditionally have been used as markers for left atrial enlargement, and both have been associated with increased risk of atrial fibrillation. Here, we explore the genetic basis of P-wave morphology through meta-analysis of genome-wide association study results for P-wave duration and P-wave terminal force from 12 cohort studies. METHODS AND RESULTS: We included 44 456 individuals, of which 6778 (16%) were of African ancestry. Genotyping, imputation, and genome-wide association study were performed at each study site. Summary-level results were meta-analyzed centrally using inverse-variance weighting. In meta-analyses of P-wave duration, we identified 6 significant (P<5×10-8) novel loci and replicated a prior association with SCN10A. We identified 3 loci at SCN5A, TBX5, and CAV1/CAV2 that were jointly associated with the PR interval, PR segment, and P-wave duration. We identified 6 novel loci in meta-analysis of P-wave terminal force. Four of the identified genetic loci were significantly associated with gene expression in 329 left atrial samples. Finally, we observed that some of the loci associated with the P wave were linked to overall atrial conduction, whereas others identified distinct phases of atrial conduction. CONCLUSIONS: We have identified 6 novel genetic loci associated with P-wave duration and 6 novel loci associated with P-wave terminal force. Future studies of these loci may aid in identifying new targets for drugs that may modify atrial conduction or treat atrial arrhythmias.
Keywords: Arrhythmias, Cardiac; Caveolin 1; Caveolin 2; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Genotype; Heart Atria; Humans; NAV1.5 Voltage-Gated Sodium Channel; NAV1.8 Voltage-Gated Sodium Channel; T-Box Domain Proteins

Genetic Interactions with Age, Sex, Body Mass Index, and Hypertension in Relation to Atrial Fibrillation: The AFGen Consortium. - Weng, Lu-Chen; Lunetta, Kathryn L; Müller-Nurasyid, Martina; Smith, Albert Vernon; Thériault, Sébastien; Weeke, Peter E; Barnard, John; Bis, Joshua C; Lyytikäinen, Leo-Pekka; Kleber, Marcus E; Martinsson, Andreas; Lin, Henry J; et al. (Sci Rep, 2017)
It is unclear whether genetic markers interact with risk factors to influence atrial fibrillation (AF) risk. We performed genome-wide interaction analyses between genetic variants and age, sex, hypertension, and body mass index in the AFGen Consortium. Study-specific results were combined using meta-analysis (88,383 individuals of European descent, including 7,292 with AF). Variants with nominal interaction associations in the discovery analysis were tested for association in four independent studies (131,441 individuals, including 5,722 with AF). In the discovery analysis, the AF risk associated with the minor rs6817105 allele (at the PITX2 locus) was greater among subjects ≤ 65 years of age than among those > 65 years (interaction p-value = 4.0 × 10-5). The interaction p-value exceeded genome-wide significance in combined discovery and replication analyses (interaction p-value = 1.7 × 10-8). We observed one genome-wide significant interaction with body mass index and several suggestive interactions with age, sex, and body mass index in the discovery analysis. However, none was replicated in the independent sample. Our findings suggest that the pathogenesis of AF may differ according to age in individuals of European descent, but we did not observe evidence of statistically significant genetic interactions with sex, body mass index, or hypertension on AF risk.

Genetic loci associated with chronic obstructive pulmonary disease overlap with loci for lung function and pulmonary fibrosis. - Hobbs, Brian D; de Jong, Kim; Lamontagne, Maxime; Bossé, Yohan; Shrine, Nick; Artigas, Maria Soler; Wain, Louise V; Hall, Ian P; Jackson, Victoria E; Wyss, Annah B; London, Stephanie J; North, Kari E; et al. (Nat Genet, 2017)
Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality worldwide. We performed a genetic association study in 15,256 cases and 47,936 controls, with replication of select top results (P < 5 × 10(-6)) in 9,498 cases and 9,748 controls. In the combined meta-analysis, we identified 22 loci associated at genome-wide significance, including 13 new associations with COPD. Nine of these 13 loci have been associated with lung function in general population samples, while 4 (EEFSEC, DSP, MTCL1, and SFTPD) are new. We noted two loci shared with pulmonary fibrosis (FAM13A and DSP) but that had opposite risk alleles for COPD. None of our loci overlapped with genome-wide associations for asthma, although one locus has been implicated in joint susceptibility to asthma and obesity. We also identified genetic correlation between COPD and asthma. Our findings highlight new loci associated with COPD, demonstrate the importance of specific loci associated with lung function to COPD, and identify potential regions of genetic overlap between COPD and other respiratory diseases.

Genetic loci associated with heart rate variability and their effects on cardiac disease risk. - Nolte, Ilja M; Munoz, M Loretto; Tragante, Vinicius; Amare, Azmeraw T; Jansen, Rick; Vaez, Ahmad; von der Heyde, Benedikt; Avery, Christy L; Bis, Joshua C; Dierckx, Bram; van Dongen, Jenny; Gogarten, Stephanie M; et al. (Nat Commun, 2017)
Reduced cardiac vagal control reflected in low heart rate variability (HRV) is associated with greater risks for cardiac morbidity and mortality. In two-stage meta-analyses of genome-wide association studies for three HRV traits in up to 53,174 individuals of European ancestry, we detect 17 genome-wide significant SNPs in eight loci. HRV SNPs tag non-synonymous SNPs (in NDUFA11 and KIAA1755), expression quantitative trait loci (eQTLs) (influencing GNG11, RGS6 and NEO1), or are located in genes preferentially expressed in the sinoatrial node (GNG11, RGS6 and HCN4). Genetic risk scores account for 0.9 to 2.6% of the HRV variance. Significant genetic correlation is found for HRV with heart rate (-0.74<rg<-0.55) and blood pressure (-0.35<rg<-0.20). These findings provide clinically relevant biological insight into heritable variation in vagal heart rhythm regulation, with a key role for genetic variants (GNG11, RGS6) that influence G-protein heterotrimer action in GIRK-channel induced pacemaker membrane hyperpolarization.

Genetically Determined Plasma Lipid Levels and Risk of Diabetic Retinopathy: A Mendelian Randomization Study. - Sobrin, Lucia; Chong, Yong He; Fan, Qiao; Gan, Alfred; Stanwyck, Lynn K; Kaidonis, Georgia; Craig, Jamie E; Kim, Jihye; Liao, Wen-Ling; Huang, Yu-Chuen; Lee, Wen-Jane; Hung, Yi-Jen; et al. (Diabetes, 2017)
Results from observational studies examining dyslipidemia as a risk factor for diabetic retinopathy (DR) have been inconsistent. We evaluated the causal relationship between plasma lipids and DR using a Mendelian randomization approach. We pooled genome-wide association studies summary statistics from 18 studies for two DR phenotypes: any DR (N = 2,969 case and 4,096 control subjects) and severe DR (N = 1,277 case and 3,980 control subjects). Previously identified lipid-associated single nucleotide polymorphisms served as instrumental variables. Meta-analysis to combine the Mendelian randomization estimates from different cohorts was conducted. There was no statistically significant change in odds ratios of having any DR or severe DR for any of the lipid fractions in the primary analysis that used single nucleotide polymorphisms that did not have a pleiotropic effect on another lipid fraction. Similarly, there was no significant association in the Caucasian and Chinese subgroup analyses. This study did not show evidence of a causal role of the four lipid fractions on DR. However, the study had limited power to detect odds ratios less than 1.23 per SD in genetically induced increase in plasma lipid levels, thus we cannot exclude that causal relationships with more modest effect sizes exist.
Keywords: Aged; Diabetic Retinopathy; Female; Genome-Wide Association Study; Humans; Lipids; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk

A genome-wide interaction analysis of tricyclic/tetracyclic antidepressants and RR and QT intervals: a pharmacogenomics study from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. - Noordam, Raymond; Sitlani, Colleen M; Avery, Christy L; Stewart, James D; Gogarten, Stephanie M; Wiggins, Kerri L; Trompet, Stella; Warren, Helen R; Sun, Fangui; Evans, Daniel S; Li, Xiaohui; Li, Jin; et al. (J Med Genet, 2017)
BACKGROUND: Increased heart rate and a prolonged QT interval are important risk factors for cardiovascular morbidity and mortality, and can be influenced by the use of various medications, including tricyclic/tetracyclic antidepressants (TCAs). We aim to identify genetic loci that modify the association between TCA use and RR and QT intervals. METHODS AND RESULTS: We conducted race/ethnic-specific genome-wide interaction analyses (with HapMap phase II imputed reference panel imputation) of TCAs and resting RR and QT intervals in cohorts of European (n=45 706; n=1417 TCA users), African (n=10 235; n=296 TCA users) and Hispanic/Latino (n=13 808; n=147 TCA users) ancestry, adjusted for clinical covariates. Among the populations of European ancestry, two genome-wide significant loci were identified for RR interval: rs6737205 in BRE (β=56.3, pinteraction=3.9e(-9)) and rs9830388 in UBE2E2 (β=25.2, pinteraction=1.7e(-8)). In Hispanic/Latino cohorts, rs2291477 in TGFBR3 significantly modified the association between TCAs and QT intervals (β=9.3, pinteraction=2.55e(-8)). In the meta-analyses of the other ethnicities, these loci either were excluded from the meta-analyses (as part of quality control), or their effects did not reach the level of nominal statistical significance (pinteraction>0.05). No new variants were identified in these ethnicities. No additional loci were identified after inverse-variance-weighted meta-analysis of the three ancestries. CONCLUSIONS: Among Europeans, TCA interactions with variants in BRE and UBE2E2 were identified in relation to RR intervals. Among Hispanic/Latinos, variants in TGFBR3 modified the relation between TCAs and QT intervals. Future studies are required to confirm our results.

Genome-Wide Interactions with Dairy Intake for Body Mass Index in Adults of European Descent. - Smith, Caren E; Follis, Jack L; Dashti, Hassan S; Tanaka, Toshiko; Graff, Mariaelisa; Fretts, Amanda M; Kilpeläinen, Tuomas O; Wojczynski, Mary K; Richardson, Kris; Nalls, Mike A; Schulz, Christina-Alexandra; Liu, Yongmei; et al. (Mol Nutr Food Res, 2017)
SCOPE: Body weight responds variably to the intake of dairy foods. Genetic variation may contribute to inter-individual variability in associations between body weight and dairy consumption. METHODS AND RESULTS: A genome-wide interaction study to discover genetic variants that account for variation in BMI in the context of low-fat, high-fat and total dairy intake in cross-sectional analysis was conducted. Data from nine discovery studies (up to 25 513 European descent individuals) were meta-analyzed. Twenty-six genetic variants reached the selected significance threshold (p-interaction <10-7) , and six independent variants (LINC01512-rs7751666, PALM2/AKAP2-rs914359, ACTA2-rs1388, PPP1R12A-rs7961195, LINC00333-rs9635058, AC098847.1-rs1791355) were evaluated meta-analytically for replication of interaction in up to 17 675 individuals. Variant rs9635058 (128 kb 3' of LINC00333) was replicated (p-interaction = 0.004). In the discovery cohorts, rs9635058 interacted with dairy (p-interaction = 7.36 × 10-8) such that each serving of low-fat dairy was associated with 0.225 kg m-2 lower BMI per each additional copy of the effect allele (A). A second genetic variant (ACTA2-rs1388) approached interaction replication significance for low-fat dairy exposure. CONCLUSION: Body weight responses to dairy intake may be modified by genotype, in that greater dairy intake may protect a genetic subgroup from higher body weight.

Genome-wide meta-analysis associates HLA-DQA1/DRB1 and LPA and lifestyle factors with human longevity. - Joshi, Peter K; Pirastu, Nicola; Kentistou, Katherine A; Fischer, Krista; Hofer, Edith; Schraut, Katharina E; Clark, David W; Nutile, Teresa; Barnes, Catriona L K; Timmers, Paul R H J; Shen, Xia; Gandin, Ilaria; et al. (Nat Commun, 2017)
Genomic analysis of longevity offers the potential to illuminate the biology of human aging. Here, using genome-wide association meta-analysis of 606,059 parents' survival, we discover two regions associated with longevity (HLA-DQA1/DRB1 and LPA). We also validate previous suggestions that APOE, CHRNA3/5, CDKN2A/B, SH2B3 and FOXO3A influence longevity. Next we show that giving up smoking, educational attainment, openness to new experience and high-density lipoprotein (HDL) cholesterol levels are most positively genetically correlated with lifespan while susceptibility to coronary artery disease (CAD), cigarettes smoked per day, lung cancer, insulin resistance and body fat are most negatively correlated. We suggest that the effect of education on lifespan is principally mediated through smoking while the effect of obesity appears to act via CAD. Using instrumental variables, we suggest that an increase of one body mass index unit reduces lifespan by 7 months while 1 year of education adds 11 months to expected lifespan.Variability in human longevity is genetically influenced. Using genetic data of parental lifespan, the authors identify associations at HLA-DQA/DRB1 and LPA and find that genetic variants that increase educational attainment have a positive effect on lifespan whereas increasing BMI negatively affects lifespan.

Genome-wide Trans-ethnic Meta-analysis Identifies Seven Genetic Loci Influencing Erythrocyte Traits and a Role for RBPMS in Erythropoiesis. - van Rooij, Frank J A; Qayyum, Rehan; Smith, Albert V; Zhou, Yi; Trompet, Stella; Tanaka, Toshiko; Keller, Margaux F; Chang, Li-Ching; Schmidt, Helena; Yang, Min-Lee; Chen, Ming-Huei; Hayes, James; et al. (Am J Hum Genet, 2017)
Genome-wide association studies (GWASs) have identified loci for erythrocyte traits in primarily European ancestry populations. We conducted GWAS meta-analyses of six erythrocyte traits in 71,638 individuals from European, East Asian, and African ancestries using a Bayesian approach to account for heterogeneity in allelic effects and variation in the structure of linkage disequilibrium between ethnicities. We identified seven loci for erythrocyte traits including a locus (RBPMS/GTF2E2) associated with mean corpuscular hemoglobin and mean corpuscular volume. Statistical fine-mapping at this locus pointed to RBPMS at this locus and excluded nearby GTF2E2. Using zebrafish morpholino to evaluate loss of function, we observed a strong in vivo erythropoietic effect for RBPMS but not for GTF2E2, supporting the statistical fine-mapping at this locus and demonstrating that RBPMS is a regulator of erythropoiesis. Our findings show the utility of trans-ethnic GWASs for discovery and characterization of genetic loci influencing hematologic traits.

Health and Functional Status of Adults Aged 90 Years in the United States. - Odden, Michelle C; Koh, William Jen Hoe; Arnold, Alice M; Psaty, Bruce M; Newman, Anne B (JAMA Intern Med, 2017)

Large meta-analysis of genome-wide association studies identifies five loci for lean body mass. - Zillikens, M Carola; Demissie, Serkalem; Hsu, Yi-Hsiang; Yerges-Armstrong, Laura M; Chou, Wen-Chi; Stolk, Lisette; Livshits, Gregory; Broer, Linda; Johnson, Toby; Koller, Daniel L; Kutalik, Zoltán; Luan, Jian'an; et al. (Nat Commun, 2017)
Lean body mass, consisting mostly of skeletal muscle, is important for healthy aging. We performed a genome-wide association study for whole body (20 cohorts of European ancestry with n = 38,292) and appendicular (arms and legs) lean body mass (n = 28,330) measured using dual energy X-ray absorptiometry or bioelectrical impedance analysis, adjusted for sex, age, height, and fat mass. Twenty-one single-nucleotide polymorphisms were significantly associated with lean body mass either genome wide (p < 5 × 10-8) or suggestively genome wide (p < 2.3 × 10-6). Replication in 63,475 (47,227 of European ancestry) individuals from 33 cohorts for whole body lean body mass and in 45,090 (42,360 of European ancestry) subjects from 25 cohorts for appendicular lean body mass was successful for five single-nucleotide polymorphisms in/near HSD17B11, VCAN, ADAMTSL3, IRS1, and FTO for total lean body mass and for three single-nucleotide polymorphisms in/near VCAN, ADAMTSL3, and IRS1 for appendicular lean body mass. Our findings provide new insight into the genetics of lean body mass.Lean body mass is a highly heritable trait and is associated with various health conditions. Here, Kiel and colleagues perform a meta-analysis of genome-wide association studies for whole body lean body mass and find five novel genetic loci to be significantly associated.

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation. - Christophersen, Ingrid E; Rienstra, Michiel; Roselli, Carolina; Yin, Xiaoyan; Geelhoed, Bastiaan; Barnard, John; Lin, Honghuang; Arking, Dan E; Smith, Albert V; Albert, Christine M; Chaffin, Mark; Tucker, Nathan R; et al. (Nat Genet, 2017)
Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death. Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups. To further define the genetic basis of atrial fibrillation, we performed large-scale, trans-ancestry meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 17,931 individuals with atrial fibrillation and 115,142 referents; the exome-wide association studies (ExWAS) and rare variant association studies (RVAS) involved 22,346 cases and 132,086 referents. We identified 12 new genetic loci that exceeded genome-wide significance, implicating genes involved in cardiac electrical and structural remodeling. Our results nearly double the number of known genetic loci for atrial fibrillation, provide insights into the molecular basis of atrial fibrillation, and may facilitate the identification of new potential targets for drug discovery.

Large-scale genome-wide analysis identifies genetic variants associated with cardiac structure and function. - Wild, Philipp S; Felix, Janine F; Schillert, Arne; Teumer, Alexander; Chen, Ming-Huei; Leening, Maarten J G; Völker, Uwe; Großmann, Vera; Brody, Jennifer A; Irvin, Marguerite R; Shah, Sanjiv J; Pramana, Setia; et al. (J Clin Invest, 2017)
BACKGROUND: Understanding the genetic architecture of cardiac structure and function may help to prevent and treat heart disease. This investigation sought to identify common genetic variations associated with inter-individual variability in cardiac structure and function. METHODS: A GWAS meta-analysis of echocardiographic traits was performed, including 46,533 individuals from 30 studies (EchoGen consortium). The analysis included 16 traits of left ventricular (LV) structure, and systolic and diastolic function. RESULTS: The discovery analysis included 21 cohorts for structural and systolic function traits (n = 32,212) and 17 cohorts for diastolic function traits (n = 21,852). Replication was performed in 5 cohorts (n = 14,321) and 6 cohorts (n = 16,308), respectively. Besides 5 previously reported loci, the combined meta-analysis identified 10 additional genome-wide significant SNPs: rs12541595 near MTSS1 and rs10774625 in ATXN2 for LV end-diastolic internal dimension; rs806322 near KCNRG, rs4765663 in CACNA1C, rs6702619 near PALMD, rs7127129 in TMEM16A, rs11207426 near FGGY, rs17608766 in GOSR2, and rs17696696 in CFDP1 for aortic root diameter; and rs12440869 in IQCH for Doppler transmitral A-wave peak velocity. Findings were in part validated in other cohorts and in GWAS of related disease traits. The genetic loci showed associations with putative signaling pathways, and with gene expression in whole blood, monocytes, and myocardial tissue. CONCLUSION: The additional genetic loci identified in this large meta-analysis of cardiac structure and function provide insights into the underlying genetic architecture of cardiac structure and warrant follow-up in future functional studies. FUNDING: For detailed information per study, see Acknowledgments.

Low-Frequency Synonymous Coding Variation in CYP2R1 Has Large Effects on Vitamin D Levels and Risk of Multiple Sclerosis. - Manousaki, Despoina; Dudding, Tom; Haworth, Simon; Hsu, Yi-Hsiang; Liu, Ching-Ti; Medina-Gómez, Carolina; Voortman, Trudy; van der Velde, Nathalie; Melhus, Håkan; Robinson-Cohen, Cassianne; Cousminer, Diana L; Nethander, Maria; et al. (Am J Hum Genet, 2017)
Vitamin D insufficiency is common, correctable, and influenced by genetic factors, and it has been associated with risk of several diseases. We sought to identify low-frequency genetic variants that strongly increase the risk of vitamin D insufficiency and tested their effect on risk of multiple sclerosis, a disease influenced by low vitamin D concentrations. We used whole-genome sequencing data from 2,619 individuals through the UK10K program and deep-imputation data from 39,655 individuals genotyped genome-wide. Meta-analysis of the summary statistics from 19 cohorts identified in CYP2R1 the low-frequency (minor allele frequency = 2.5%) synonymous coding variant g.14900931G>A (p.Asp120Asp) (rs117913124[A]), which conferred a large effect on 25-hydroxyvitamin D (25OHD) levels (-0.43 SD of standardized natural log-transformed 25OHD per A allele; p value = 1.5 × 10(-88)). The effect on 25OHD was four times larger and independent of the effect of a previously described common variant near CYP2R1. By analyzing 8,711 individuals, we showed that heterozygote carriers of this low-frequency variant have an increased risk of vitamin D insufficiency (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.78-2.78, p = 1.26 × 10(-12)). Individuals carrying one copy of this variant also had increased odds of multiple sclerosis (OR = 1.4, 95% CI = 1.19-1.64, p = 2.63 × 10(-5)) in a sample of 5,927 case and 5,599 control subjects. In conclusion, we describe a low-frequency CYP2R1 coding variant that exerts the largest effect upon 25OHD levels identified to date in the general European population and implicates vitamin D in the etiology of multiple sclerosis.
Keywords: Cholestanetriol 26-Monooxygenase; Cytochrome P450 Family 2; Gene Frequency; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Multiple Sclerosis; Polymorphism, Single Nucleotide; Risk Factors; Vitamin D; Vitamin D Deficiency

Multiancestry Study of Gene-Lifestyle Interactions for Cardiovascular Traits in 610 475 Individuals From 124 Cohorts: Design and Rationale. - Rao, D C; Sung, Yun J; Winkler, Thomas W; Schwander, Karen; Borecki, Ingrid; Cupples, L Adrienne; Gauderman, W James; Rice, Kenneth; Munroe, Patricia B; Psaty, Bruce M (Circ Cardiovasc Genet, 2017)
BACKGROUND: Several consortia have pursued genome-wide association studies for identifying novel genetic loci for blood pressure, lipids, hypertension, etc. They demonstrated the power of collaborative research through meta-analysis of study-specific results. METHODS AND RESULTS: The Gene-Lifestyle Interactions Working Group was formed to facilitate the first large, concerted, multiancestry study to systematically evaluate gene-lifestyle interactions. In stage 1, genome-wide interaction analysis is performed in 53 cohorts with a total of 149 684 individuals from multiple ancestries. In stage 2 involving an additional 71 cohorts with 460 791 individuals from multiple ancestries, focused analysis is performed for a subset of the most promising variants from stage 1. In all, the study involves up to 610 475 individuals. Current focus is on cardiovascular traits including blood pressure and lipids, and lifestyle factors including smoking, alcohol, education (as a surrogate for socioeconomic status), physical activity, psychosocial variables, and sleep. The total sample sizes vary among projects because of missing data. Large-scale gene-lifestyle or more generally gene-environment interaction (G×E) meta-analysis studies can be cumbersome and challenging. This article describes the design and some of the approaches pursued in the interaction projects. CONCLUSIONS: The Gene-Lifestyle Interactions Working Group provides an excellent framework for understanding the lifestyle context of genetic effects and to identify novel trait loci through analysis of interactions. An important and novel feature of our study is that the gene-lifestyle interaction (G×E) results may improve our knowledge about the underlying mechanisms for novel and already known trait loci.

New Blood Pressure-Associated Loci Identified in Meta-Analyses of 475 000 Individuals. - Kraja, Aldi T; Cook, James P; Warren, Helen R; Surendran, Praveen; Liu, Chunyu; Evangelou, Evangelos; Manning, Alisa K; Grarup, Niels; Drenos, Fotios; Sim, Xueling; Smith, Albert Vernon; Amin, Najaf; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide association studies have recently identified >400 loci that harbor DNA sequence variants that influence blood pressure (BP). Our earlier studies identified and validated 56 single nucleotide variants (SNVs) associated with BP from meta-analyses of exome chip genotype data. An additional 100 variants yielded suggestive evidence of association. METHODS AND RESULTS: Here, we augment the sample with 140 886 European individuals from the UK Biobank, in whom 77 of the 100 suggestive SNVs were available for association analysis with systolic BP or diastolic BP or pulse pressure. We performed 2 meta-analyses, one in individuals of European, South Asian, African, and Hispanic descent (pan-ancestry, ≈475 000), and the other in the subset of individuals of European descent (≈423 000). Twenty-one SNVs were genome-wide significant (P<5×10-8) for BP, of which 4 are new BP loci: rs9678851 (missense, SLC4A1AP), rs7437940 (AFAP1), rs13303 (missense, STAB1), and rs1055144 (7p15.2). In addition, we identified a potentially independent novel BP-associated SNV, rs3416322 (missense, SYNPO2L) at a known locus, uncorrelated with the previously reported SNVs. Two SNVs are associated with expression levels of nearby genes, and SNVs at 3 loci are associated with other traits. One SNV with a minor allele frequency <0.01, (rs3025380 at DBH) was genome-wide significant. CONCLUSIONS: We report 4 novel loci associated with BP regulation, and 1 independent variant at an established BP locus. This analysis highlights several candidate genes with variation that alter protein function or gene expression for potential follow-up.

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near HSPB7, TNXB, LRP12, LOC283335, SEPT9, and AKT2, and provide new replication evidence for a further 2 signals in EBF2 and NFKBIA Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

PCSK9 Loss-of-Function Variants, Low-Density Lipoprotein Cholesterol, and Risk of Coronary Heart Disease and Stroke: Data From 9 Studies of Blacks and Whites. - Kent, Shia T; Rosenson, Robert S; Avery, Christy L; Chen, Yii-der I; Correa, Adolfo; Cummings, Steven R; Cupples, L Adrienne; Cushman, Mary; Evans, Daniel S; Gudnason, Vilmundur; Harris, Tamara B; Howard, George; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: PCSK9 loss-of-function (LOF) variants allow for the examination of the effects of lifetime reduced low-density lipoprotein cholesterol (LDL-C) on cardiovascular events. We examined the association of PCSK9 LOF variants with LDL-C and incident coronary heart disease and stroke through a meta-analysis of data from 8 observational cohorts and 1 randomized trial of statin therapy. METHODS AND RESULTS: These 9 studies together included 17 459 blacks with 403 (2.3%) having at least 1 Y142X or C679X variant and 31 306 whites with 955 (3.1%) having at least 1 R46L variant. Unadjusted odds ratios for associations between PCSK9 LOF variants and incident coronary heart disease (851 events in blacks and 2662 events in whites) and stroke (523 events in blacks and 1660 events in whites) were calculated using pooled Mantel-Haenszel estimates with continuity correction factors. Pooling results across studies using fixed-effects inverse-variance-weighted models, PCSK9 LOF variants were associated with 35 mg/dL (95% confidence interval [CI], 32-39) lower LDL-C in blacks and 13 mg/dL (95% CI, 11-16) lower LDL-C in whites. PCSK9 LOF variants were associated with a pooled odds ratio for coronary heart disease of 0.51 (95% CI, 0.28-0.92) in blacks and 0.82 (95% CI, 0.63-1.06) in whites. PCSK9 LOF variants were not associated with incident stroke (odds ratio, 0.84; 95% CI, 0.48-1.47 in blacks and odds ratio, 1.06; 95% CI, 0.80-1.41 in whites). CONCLUSIONS: PCSK9 LOF variants were associated with lower LDL-C and coronary heart disease incidence. PCSK9 LOF variants were not associated with stroke risk.

Predictors and outcomes of heart failure with mid-range ejection fraction. - Bhambhani, Vijeta; Kizer, Jorge R; Lima, João A C; van der Harst, Pim; Bahrami, Hossein; Nayor, Matthew; de Filippi, Christopher R; Enserro, Danielle; Blaha, Michael J; Cushman, Mary; Wang, Thomas J; Gansevoort, Ron T; et al. (Eur J Heart Fail, 2017)
AIMS: While heart failure with preserved (HFpEF) and reduced ejection fraction (HFrEF) are well described, determinants and outcomes of heart failure with mid-range ejection fraction (HFmrEF) remain unclear. We sought to examine clinical and biochemical predictors of incident HFmrEF in the community. METHODS AND RESULTS: We pooled data from four community-based longitudinal cohorts, with ascertainment of new heart failure (HF) classified into HFmrEF [ejection fraction (EF) 41-49%], HFpEF (EF ≥50%), and HFrEF (EF ≤40%). Predictors of incident HF subtypes were assessed using multivariable Cox models. Among 28 820 participants free of HF followed for a median of 12 years, there were 200 new HFmrEF cases, compared with 811 HFpEF and 1048 HFrEF. Clinical predictors of HFmrEF included age, male sex, systolic blood pressure, diabetes mellitus, and prior myocardial infarction (multivariable adjusted P ≤ 0.003 for all). Biomarkers that predicted HFmrEF included natriuretic peptides, cystatin-C, and high-sensitivity troponin (P ≤ 0.0004 for all). Natriuretic peptides were stronger predictors of HFrEF [hazard ratio (HR) 2.00 per 1 standard deviation increase, 95% confidence interval (CI) 1.81-2.20] than of HFmrEF (HR 1.51, 95% CI 1.20-1.90, P = 0.01 for difference), and did not differ in their association with incident HFmrEF and HFpEF (HR 1.56, 95% CI 1.41-1.73, P = 0.68 for difference). All-cause mortality following the onset of HFmrEF was worse than that of HFpEF (50 vs. 39 events per 1000 person-years, P = 0.02), but comparable to that of HFrEF (46 events per 1000 person-years, P = 0.78). CONCLUSIONS: We found overlap in predictors of incident HFmrEF with other HF subtypes. In contrast, mortality risk after HFmrEF was worse than HFpEF, and similar to HFrEF.

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10-4) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10-8) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10-10, odds ratio (OR) = 0.68, minor allele frequency (MAF)cases = 0.0059, MAFcontrols = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10-10, OR = 1.43, MAFcases = 0.011, MAFcontrols = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10-14, OR = 1.67, MAFcases = 0.0143, MAFcontrols = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

Rare coding variants pinpoint genes that control human hematological traits. - Mousas, Abdou; Ntritsos, Georgios; Chen, Ming-Huei; Song, Ci; Huffman, Jennifer E; Tzoulaki, Ioanna; Elliott, Paul; Psaty, Bruce M; Auer, Paul L; Johnson, Andrew D; Evangelou, Evangelos; Lettre, Guillaume; et al. (PLoS Genet, 2017)
The identification of rare coding or splice site variants remains the most straightforward strategy to link genes with human phenotypes. Here, we analyzed the association between 137,086 rare (minor allele frequency (MAF) <1%) coding or splice site variants and 15 hematological traits in up to 308,572 participants. We found 56 such rare coding or splice site variants at P<5x10-8, including 31 that are associated with a blood-cell phenotype for the first time. All but one of these 31 new independent variants map to loci previously implicated in hematopoiesis by genome-wide association studies (GWAS). This includes a rare splice acceptor variant (rs146597587, MAF = 0.5%) in interleukin 33 (IL33) associated with reduced eosinophil count (P = 2.4x10-23), and lower risk of asthma (P = 2.6x10-7, odds ratio [95% confidence interval] = 0.56 [0.45-0.70]) and allergic rhinitis (P = 4.2x10-4, odds ratio = 0.55 [0.39-0.76]). The single new locus identified in our study is defined by a rare p.Arg172Gly missense variant (rs145535174, MAF = 0.05%) in plasminogen (PLG) associated with increased platelet count (P = 6.8x10-9), and decreased D-dimer concentration (P = 0.018) and platelet reactivity (P<0.03). Finally, our results indicate that searching for rare coding or splice site variants in very large sample sizes can help prioritize causal genes at many GWAS loci associated with complex human diseases and traits.
Keywords: Asthma; Databases, Genetic; Endometriosis; Female; Fibrin Fibrinogen Degradation Products; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Interleukin-33; Linear Models; Logistic Models; Male; Mutation, Missense; Phenotype; Plasminogen; Platelet Count; Polymorphism, Single Nucleotide; Principal Component Analysis; Protein Splicing; Rhinitis, Allergic; Sequence Analysis, DNA

The Relation of Serum Potassium Concentration with Cardiovascular Events and Mortality in Community-Living Individuals. - Hughes-Austin, Jan M; Rifkin, Dena E; Beben, Tomasz; Katz, Ronit; Sarnak, Mark J; Deo, Rajat; Hoofnagle, Andrew N; Homma, Shunichi; Siscovick, David S; Sotoodehnia, Nona; Psaty, Bruce M; de Boer, Ian H; et al. (Clin J Am Soc Nephrol, 2017)
BACKGROUND AND OBJECTIVES: Hyperkalemia is associated with adverse outcomes in patients with CKD and in hospitalized patients with acute medical conditions. Little is known regarding hyperkalemia, cardiovascular disease (CVD), and mortality in community-living populations. In a pooled analysis of two large observational cohorts, we investigated associations between serum potassium concentrations and CVD events and mortality, and whether potassium-altering medications and eGFR<60 ml/min per 1.73 m(2) modified these associations. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Among 9651 individuals from the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS), who were free of CVD at baseline (2000-2002 in the MESA and 1989-1993 in the CHS), we investigated associations between serum potassium categories (<3.5, 3.5-3.9, 4.0-4.4, 4.5-4.9, and ≥5.0 mEq/L) and CVD events, mortality, and mortality subtypes (CVD versus non-CVD) using Cox proportional hazards models, adjusting for demographics, time-varying eGFR, traditional CVD risk factors, and use of potassium-altering medications. RESULTS: Compared with serum potassium concentrations between 4.0 and 4.4 mEq/L, those with concentrations ≥5.0 mEq/L were at higher risk for all-cause mortality (hazard ratio, 1.41; 95% confidence interval, 1.12 to 1.76), CVD death (hazard ratio, 1.50; 95% confidence interval, 1.00 to 2.26), and non-CVD death (hazard ratio, 1.40; 95% confidence interval, 1.07 to 1.83) in fully adjusted models. Associations of serum potassium with these end points differed among diuretic users (Pinteraction<0.02 for all), such that participants who had serum potassium ≥5.0 mEq/L and were concurrently using diuretics were at higher risk of each end point compared with those not using diuretics. CONCLUSIONS: Serum potassium concentration ≥5.0 mEq/L was associated with all-cause mortality, CVD death, and non-CVD death in community-living individuals; associations were stronger in diuretic users. Whether maintenance of potassium within the normal range may improve clinical outcomes requires future study.

Relation of the Myocardial Contraction Fraction, as Calculated from M-Mode Echocardiography, With Incident Heart Failure, Atherosclerotic Cardiovascular Disease and Mortality (Results from the Cardiovascular Health Study). - Maurer, Mathew S; Koh, William J H; Bartz, Traci M; Vullaganti, Sirish; Barasch, Eddy; Gardin, Julius M; Gottdiener, John S; Psaty, Bruce M; Kizer, Jorge R (Am J Cardiol, 2017)
We evaluated the association between 2-dimensional (2D) echocardiography (echo)-determined myocardial contraction fraction (MCF) and adverse cardiovascular outcomes including incident heart failure (HF), atherosclerotic cardiovascular disease (ASCVD), and mortality. The MCF, the ratio of left ventricular (LV) stroke volume (SV) to myocardial volume (MV), is a volumetric measure of myocardial shortening that can distinguish pathologic from physiological hypertrophy. Using 2D echo-guided M-mode data from the Cardiovascular Health Study, we calculated MCF in subjects with LV ejection fraction (EF) ≥55% and used Cox models to evaluate its association with incident HF, ASCVD, and all-cause mortality after adjusting for clinical and echo parameters. We assessed whether log2(SV) and log2(MV) were consistent with the expected 1:-1 ratio used in the definition of MCF. Among 2,147 participants (age 72 ± 5 years), average MCF was 59 ± 13%. After controlling for clinical and echo variables, each 10% absolute increment in MCF was associated with lower risk of HF (hazard ratio [HR] 0.88; 95% confidence interval [CI] 0.82, 0.94), ASCVD (HR 0.90; 95% CI 0.85, 0.95), and death (HR 0.93; 95% CI 0.89, 0.97). Moreover, the MCF was still significantly associated with ASCVD and mortality, but not HF, after adjustment for percent-predicted LV mass. Significant departure from the 1:-1 ratio was not observed for ASCVD or death, but did occur for HF, driven by a stronger association for MV than SV. In conclusion, among older adults without CVD or low LV ejection fraction, 2D echo-guided M-mode-derived MCF was independently associated with lower risk of adverse cardiovascular outcomes, but this ratiometric index may not capture the full relation that is apparent when its components are modeled separately in the case of HF.

Relationship Between Physical Activity, Body Mass Index, and Risk of Heart Failure. - Pandey, Ambarish; LaMonte, Michael; Klein, Liviu; Ayers, Colby; Psaty, Bruce M; Eaton, Charles B; Allen, Norrina B; de Lemos, James A; Carnethon, Mercedes; Greenland, Philip; Berry, Jarett D (J Am Coll Cardiol, 2017)
BACKGROUND: Lower leisure-time physical activity (LTPA) and higher body mass index (BMI) are independently associated with risk of heart failure (HF). However, it is unclear if this relationship is consistent for both heart failure with preserved ejection fraction (HFpEF) and heart failure with reduced ejection fraction (HFrEF). OBJECTIVES: This study sought to quantify dose-response associations between LTPA, BMI, and the risk of different HF subtypes. METHODS: Individual-level data from 3 cohort studies (WHI [Women's Health Initiative], MESA [Multi-Ethnic Study of Atherosclerosis], and CHS [Cardiovascular Health Study]) were pooled and participants were stratified into guideline-recommended categories of LTPA and BMI. Associations between LTPA, BMI, and risk of overall HF, HFpEF (ejection fraction ≥45%), and HFrEF (ejection fraction <45%) were assessed by using multivariable adjusted Cox models and restricted cubic splines. RESULTS: The study included 51,451 participants with 3,180 HF events (1,252 HFpEF, 914 HFrEF, and 1,014 unclassified HF). In the adjusted analysis, there was a dose-dependent association between higher LTPA levels, lower BMI, and overall HF risk. Among HF subtypes, LTPA in any dose range was not associated with HFrEF risk. In contrast, lower levels of LTPA (<500 MET-min/week) were not associated with HFpEF risk, and dose-dependent associations with lower HFpEF risk were observed at higher levels. Compared with no LTPA, higher than twice the guideline-recommended minimum LTPA levels (>1,000 MET-min/week) were associated with an 19% lower risk of HFpEF (hazard ratio: 0.81; 95% confidence interval: 0.68 to 0.97). The dose-response relationship for BMI with HFpEF risk was also more consistent than with HFrEF risk, such that increasing BMI above the normal range (≥25 kg/m(2)) was associated with a greater increase in risk of HFpEF than HFrEF. CONCLUSIONS: Our study findings show strong, dose-dependent associations between LTPA levels, BMI, and risk of overall HF. Among HF subtypes, higher LTPA levels and lower BMI were more consistently associated with lower risk of HFpEF compared with HFrEF.

REPEATED MEASUREMENTS OF BLOOD PRESSURE AND CHOLESTEROL IMPROVES CARDIOVASCULAR DISEASE RISK PREDICTION: AN INDIVIDUAL-PARTICIPANT-DATA META-ANALYSIS. - Paige, Ellie; Barrett, Jessica; Pennells, Lisa; Sweeting, Michael; Willeit, Peter; Di Angelantonio, Emanuele; Gudnason, Vilmundur; Nordestgaard, Børge G; Psaty, Bruce M; Goldbourt, Uri; Best, Lyle G; Assmann, Gerd; et al. (Am J Epidemiol, 2017)
The added value of incorporating information from repeated measurements of blood pressure and cholesterol for cardiovascular disease (CVD) risk prediction has not been rigorously assessed. We used data from the Emerging Risk Factors Collaboration on 191,445 adults (38 cohorts from across 17 countries with data from 1962-2014) with > 1 million measurements of systolic blood pressure, total cholesterol and high-density lipoprotein cholesterol; over a median 12 years of follow-up, 21,170 CVD events occurred. Risk prediction models using cumulative means of repeated measurements and summary measures from longitudinal modelling of the repeated measurements were compared to models using measurements from a single time point. Risk discrimination (C-index) and net reclassification were calculated, and changes in C-indices were meta-analysed across studies. Compared to the single time point model, the cumulative means and the longitudinal models increased the C-index by 0.0040 (95% CI: 0.0023, 0.0057) and 0.0023 (0.0005, 0.0042), respectively. Reclassification was also improved in both models; compared to the single time point model, overall net reclassification improvements were 0.0369 (0.0303, 0.0436) for the cumulative means model and 0.0177 (0.0110, 0.0243) for the longitudinal model. In conclusion, incorporating repeated measurements of blood pressure and cholesterol into CVD risk prediction models slightly improves risk prediction.

Single-trait and multi-trait genome-wide association analyses identify novel loci for blood pressure in African-ancestry populations. - Liang, Jingjing; Le, Thu H; Edwards, Digna R Velez; Tayo, Bamidele O; Gaulton, Kyle J; Smith, Jennifer A; Lu, Yingchang; Jensen, Richard A; Chen, Guanjie; Yanek, Lisa R; Schwander, Karen; Tajuddin, Salman M; et al. (PLoS Genet, 2017)
Hypertension is a leading cause of global disease, mortality, and disability. While individuals of African descent suffer a disproportionate burden of hypertension and its complications, they have been underrepresented in genetic studies. To identify novel susceptibility loci for blood pressure and hypertension in people of African ancestry, we performed both single and multiple-trait genome-wide association analyses. We analyzed 21 genome-wide association studies comprised of 31,968 individuals of African ancestry, and validated our results with additional 54,395 individuals from multi-ethnic studies. These analyses identified nine loci with eleven independent variants which reached genome-wide significance (P < 1.25×10-8) for either systolic and diastolic blood pressure, hypertension, or for combined traits. Single-trait analyses identified two loci (TARID/TCF21 and LLPH/TMBIM4) and multiple-trait analyses identified one novel locus (FRMD3) for blood pressure. At these three loci, as well as at GRP20/CDH17, associated variants had alleles common only in African-ancestry populations. Functional annotation showed enrichment for genes expressed in immune and kidney cells, as well as in heart and vascular cells/tissues. Experiments driven by these findings and using angiotensin-II induced hypertension in mice showed altered kidney mRNA expression of six genes, suggesting their potential role in hypertension. Our study provides new evidence for genes related to hypertension susceptibility, and the need to study African-ancestry populations in order to identify biologic factors contributing to hypertension.
Keywords: African Americans; Animals; Basic Helix-Loop-Helix Transcription Factors; Blood Pressure; Cadherins; Case-Control Studies; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Mice; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Soluble Inflammatory Markers and Risk of Incident Fractures in Older Adults: The Cardiovascular Health Study. - Stojanović, Danijela; Bůzková, Petra; Mukamal, Kenneth J; Heckbert, Susan R; Psaty, Bruce M; Fink, Howard A; Cauley, Jane A; Wallace, Erin; Curtis, Lesley H; Hirsch, Calvin; Budoff, Matthew; Li, Dong; et al. (J Bone Miner Res, 2017)
Several in vitro and animal studies have showed that inflammatory markers play a role in bone remodeling and pathogenesis of osteoporosis. Additionally, some human longitudinal studies showed suggestive associations between elevated inflammatory markers and increased risk of nontraumatic fractures. We examined several inflammatory markers and multiple fracture types in a single study of older individuals with extensive follow-up. We assessed the association of four inflammatory markers with the risk of incident hip fractures among 5265 participants of the Cardiovascular Health Study (CHS) and a composite endpoint of incident fractures of the hip, pelvis, humerus, or proximal forearm in 4477 participants. Among CHS participants followed between 1992 and 2009, we observed 480 incident hip fractures during a median follow-up of 11 years. In the composite fracture analysis cohort of 4477 participants, we observed 711 fractures during a median follow-up of 7 years. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for hip fracture associated with doubling of IL-6 were HR 1.15 (95% CI, 1.02 to 1.30) overall and HR 1.17 (95% CI, 1.01 to 1.35) in women. We also observed a positive association between each unit increase in white blood cell (WBC) count and risk of hip fracture: HR 1.04 (95% CI, 1.01 to 1.06) overall and HR 1.06 (95% CI, 0.95 to 1.20) in women. We observed no significant associations between any of the four inflammatory markers and a composite fracture endpoint. Our findings suggest that chronic inflammatory and immune processes may be related to higher rates of incident hip fractures. © 2017 American Society for Bone and Mineral Research.

Trends in the incidence of dementia: design and methods in the Alzheimer Cohorts Consortium. - Chibnik, Lori B; Wolters, Frank J; Bäckman, Kristoffer; Beiser, Alexa; Berr, Claudine; Bis, Joshua C; Boerwinkle, Eric; Bos, Daniel; Brayne, Carol; Dartigues, Jean-François; Darweesh, Sirwan K L; Debette, Stephanie; et al. (Eur J Epidemiol, 2017)
Several studies have reported a decline in incidence of dementia which may have large implications for the projected burden of disease, and provide important guidance to preventive efforts. However, reports are conflicting or inconclusive with regard to the impact of gender and education with underlying causes of a presumed declining trend remaining largely unidentified. The Alzheimer Cohorts Consortium aggregates data from nine international population-based cohorts to determine changes in the incidence of dementia since 1990. We will employ Poisson regression models to calculate incidence rates in each cohort and Cox proportional hazard regression to compare 5-year cumulative hazards across study-specific epochs. Finally, we will meta-analyse changes per decade across cohorts, and repeat all analysis stratified by sex, education and APOE genotype. In all cohorts combined, there are data on almost 69,000 people at risk of dementia with the range of follow-up years between 2 and 27. The average age at baseline is similar across cohorts ranging between 72 and 77. Uniting a wide range of disease-specific and methodological expertise in research teams, the first analyses within the Alzheimer Cohorts Consortium are underway to tackle outstanding challenges in the assessment of time-trends in dementia occurrence.

Visit-to-Visit Blood Pressure Variability and Mortality and Cardiovascular Outcomes Among Older Adults: The Health, Aging, and Body Composition Study. - Wu, Chenkai; Shlipak, Michael G; Stawski, Robert S; Peralta, Carmen A; Psaty, Bruce M; Harris, Tamara B; Satterfield, Suzanne; Shiroma, Eric J; Newman, Anne B; Odden, Michelle C (Am J Hypertens, 2017)
BACKGROUND: Level of blood pressure (BP) is strongly associated with cardiovascular (CV) events and mortality. However, it is questionable whether mean BP can fully capture BP-related vascular risk. Increasing attention has been given to the value of visit-to-visit BP variability. METHODS: We examined the association of visit-to-visit BP variability with mortality, incident myocardial infarction (MI), and incident stroke among 1,877 well-functioning elders in the Health, Aging, and Body Composition Study. We defined visit-to-visit diastolic BP (DBP) and systolic BP (SBP) variability as the root-mean-square error of person-specific linear regression of BP as a function of time. Alternatively, we counted the number of considerable BP increases and decreases (separately; 10mm Hg for DBP and 20mm Hg for SBP) between consecutive visits for each individual. RESULTS: Over an average follow-up of 8.5 years, 623 deaths (207 from CV disease), 153 MIs, and 156 strokes occurred. The median visit-to-visit DBP and SBP variability was 4.96 mmHg and 8.53 mmHg, respectively. After multivariable adjustment, visit-to-visit DBP variability was related to higher all-cause (hazard ratio (HR) = 1.18 per 1 SD, 95% confidence interval (CI) = 1.01-1.37) and CV mortality (HR = 1.35, 95% CI = 1.05-1.73). Additionally, individuals having more considerable decreases of DBP (≥10mm Hg between 2 consecutive visits) had higher risk of all-cause (HR = 1.13, 95% CI = 0.99-1.28) and CV mortality (HR = 1.30, 95% CI = 1.05-1.61); considerable increases of SBP (≥20mm Hg) were associated with higher risk of all-cause (HR = 1.18, 95% CI = 1.03-1.36) and CV mortality (HR = 1.37, 95% CI = 1.08-1.74). CONCLUSIONS: Visit-to-visit DBP variability and considerable changes in DBP and SBP were risk factors for mortality in the elderly.
Keywords: Aged; Aging; Blood Pressure; Blood Pressure Determination; Body Composition; California; Cohort Studies; Female; Health Status; Humans; Hypertension; Incidence; Longitudinal Studies; Male; Myocardial Infarction; Office Visits; Prognosis; Retrospective Studies; Risk Factors; Stroke; Survival Rate

Association of Alcohol Consumption After Development of Heart Failure With Survival Among Older Adults in the Cardiovascular Health Study. - Sadhu, Justin S; Novak, Eric; Mukamal, Kenneth J; Kizer, Jorge R; Psaty, Bruce M; Stein, Phyllis K; Brown, David L (JAMA Netw Open, 2018)
Importance: More than 1 million older adults develop heart failure annually. The association of alcohol consumption with survival among these individuals after diagnosis is unknown. Objective: To determine whether alcohol use is associated with increased survival among older adults with incident heart failure. Design, Setting, and Participants: This prospective cohort study included 5888 community-dwelling adults aged 65 years or older who were recruited to participate in the Cardiovascular Health Study between June 12, 1989, and June 1993, from 4 US sites. Of the total participants, 393 individuals had a new diagnosis of heart failure within the first 9 years of follow-up through June 2013. The study analysis was performed between January 19, 2016, and September 22, 2016. Exposures: Alcohol consumption was divided into 4 categories: abstainers (never drinkers), former drinkers, 7 or fewer alcoholic drinks per week, and more than 7 drinks per week. Primary Outcomes and Measures: Participant survival after the diagnosis of incident heart failure. Results: Among the 393 adults diagnosed with incident heart failure, 213 (54.2%) were female, 339 (86.3%) were white, and the mean (SD) age was 78.7 (6.0) years. Alcohol consumption after diagnosis was reported in 129 (32.8%) of the participants. Across alcohol consumption categories of long-term abstainers, former drinkers, consumers of 1-7 drinks weekly and consumers of more than 7 drinks weekly, the percentage of men (32.1%, 49.0%, 58.0%, and 82.4%, respectively; P < .001 for trend), white individuals (78.0%, 92.7%, 92.0%, and 94.1%, respectively, P <. 001 for trend), and high-income participants (22.0%, 43.8%, 47.3%, and 64.7%, respectively; P < .001 for trend) increased with increasing alcohol consumption. Across the 4 categories, participants who consumed more alcohol had more years of education (mean, 12 years [interquartile range (IQR), 8.0-10.0 years], 12 years [IQR, 11.0-14.0 years], 13 years [IQR, 12.0-15.0 years], and 13 years [IQR, 12.0-14.0 years]; P < .001 for trend). Diabetes was less common across the alcohol consumption categories (32.1%, 26.0%, 22.3%, and 5.9%, respectively; P = .01 for trend). Across alcohol consumption categories, there were fewer never smokers (58.3%, 44.8%, 35.7%, and 29.4%, respectively; P < .001 for trend) and more former smokers (34.5%, 38.5%, 50.0%, and 52.9%, respectively; P = .006 for trend). After controlling for other factors, consumption of 7 or fewer alcoholic drinks per week was associated with additional mean survival of 383 days (95% CI, 17-748 days; P = .04) compared with abstinence from alcohol. Although the robustness was limited by the small number of individuals who consumed more than 7 drinks per week, a significant inverted U-shaped association between alcohol consumption and survival was observed. Multivariable model estimates of mean time from heart failure diagnosis to death were 2640 days (95% CI, 1967-3313 days) for never drinkers, 3046 days (95% CI, 2372-3719 days) for consumers of 0 to 7 drinks per week, and 2806 (95% CI, 1879-3734 days) for consumers of more than 7 drinks per week (P = .02). Consumption of 10 drinks per week was associated with the longest survival, a mean of 3381 days (95% CI, 2806-3956 days) after heart failure diagnosis. Conclusions and Relevance: These findings suggest that limited alcohol consumption among older adults with incident heart failure is associated with survival benefit compared with long-term abstinence. These findings suggest that older adults who develop heart failure may not need to abstain from moderate levels of alcohol consumption.

Association of Cardiovascular Biomarkers With Incident Heart Failure With Preserved and Reduced Ejection Fraction. - de Boer, Rudolf A; Nayor, Matthew; deFilippi, Christopher R; Enserro, Danielle; Bhambhani, Vijeta; Kizer, Jorge R; Blaha, Michael J; Brouwers, Frank P; Cushman, Mary; Lima, João A C; Bahrami, Hossein; van der Harst, Pim; et al. (JAMA Cardiol, 2018)
Importance: Nearly half of all patients with heart failure have preserved ejection fraction (HFpEF) as opposed to reduced ejection fraction (HFrEF), yet associations of biomarkers with future heart failure subtype are incompletely understood. Objective: To evaluate the associations of 12 cardiovascular biomarkers with incident HFpEF vs HFrEF among adults from the general population. Design, Setting, and Participants: This study included 4 longitudinal community-based cohorts: the Cardiovascular Health Study (1989-1990; 1992-1993 for supplemental African-American cohort), the Framingham Heart Study (1995-1998), the Multi-Ethnic Study of Atherosclerosis (2000-2002), and the Prevention of Renal and Vascular End-stage Disease study (1997-1998). Each cohort had prospective ascertainment of incident HFpEF and HFrEF. Data analysis was performed from June 25, 2015, to November 9, 2017. Exposures: The following biomarkers were examined: N-terminal pro B-type natriuretic peptide or brain natriuretic peptide, high-sensitivity troponin T or I, C-reactive protein (CRP), urinary albumin to creatinine ratio (UACR), renin to aldosterone ratio, D-dimer, fibrinogen, soluble suppressor of tumorigenicity, galectin-3, cystatin C, plasminogen activator inhibitor 1, and interleukin 6. Main Outcomes and Measures: Development of incident HFpEF and incident HFrEF. Results: Among the 22 756 participants in these 4 cohorts (12 087 women and 10 669 men; mean [SD] age, 60 [13] years) in the study, during a median follow-up of 12 years, 633 participants developed incident HFpEF, and 841 developed HFrEF. In models adjusted for clinical risk factors of heart failure, 2 biomarkers were significantly associated with incident HFpEF: UACR (hazard ratio [HR], 1.33; 95% CI, 1.20-1.48; P < .001) and natriuretic peptides (HR, 1.27; 95% CI, 1.16-1.40; P < .001), with suggestive associations for high-sensitivity troponin (HR, 1.11; 95% CI, 1.03-1.19; P = .008), plasminogen activator inhibitor 1 (HR, 1.22; 95% CI, 1.03-1.45; P = .02), and fibrinogen (HR, 1.12; 95% CI, 1.03-1.22; P = .01). By contrast, 6 biomarkers were associated with incident HFrEF: natriuretic peptides (HR, 1.54; 95% CI, 1.41-1.68; P < .001), UACR (HR, 1.21; 95% CI, 1.11-1.32; P < .001), high-sensitivity troponin (HR, 1.37; 95% CI, 1.29-1.46; P < .001), cystatin C (HR, 1.19; 95% CI, 1.11-1.27; P < .001), D-dimer (HR, 1.22; 95% CI, 1.11-1.35; P < .001), and CRP (HR, 1.19; 95% CI, 1.11-1.28; P < .001). When directly compared, natriuretic peptides, high-sensitivity troponin, and CRP were more strongly associated with HFrEF compared with HFpEF. Conclusions and Relevance: Biomarkers of renal dysfunction, endothelial dysfunction, and inflammation were associated with incident HFrEF. By contrast, only natriuretic peptides and UACR were associated with HFpEF. These findings highlight the need for future studies focused on identifying novel biomarkers of the risk of HFpEF.

The Association of Obesity and Cardiometabolic Traits With Incident HFpEF and HFrEF. - Savji, Nazir; Meijers, Wouter C; Bartz, Traci M; Bhambhani, Vijeta; Cushman, Mary; Nayor, Matthew; Kizer, Jorge R; Sarma, Amy; Blaha, Michael J; Gansevoort, Ron T; Gardin, Julius M; Hillege, Hans L; et al. (JACC Heart Fail, 2018)
OBJECTIVES: This study evaluated the associations of obesity and cardiometabolic traits with incident heart failure with preserved versus reduced ejection fraction (HFpEF vs. HFrEF). Given known sex differences in HF subtype, we examined men and women separately. BACKGROUND: Recent studies suggest that obesity confers greater risk of HFpEF versus HFrEF. Contributions of associated metabolic traits to HFpEF are less clear. METHODS: We studied 22,681 participants from 4 community-based cohorts followed for incident HFpEF versus HFrEF (ejection fraction ≥50% vs. <50%). We evaluated the association of body mass index (BMI) and cardiometabolic traits with incident HF subtype using Cox models. RESULTS: The mean age was 60 ± 13 years, and 53% were women. Over a median follow-up of 12 years, 628 developed incident HFpEF and 835 HFrEF. Greater BMI portended higher risk of HFpEF compared with HFrEF (hazard ratio [HR]: 1.34 per 1-SD increase in BMI; 95% confidence interval [CI]: 1.24 to 1.45 vs. HR: 1.18; 95% CI: 1.10 to 1.27). Similarly, insulin resistance (homeostatic model assessment of insulin resistance) was associated with HFpEF (HR: 1.20 per 1-SD; 95% CI: 1.05 to 1.37), but not HFrEF (HR: 0.99; 95% CI: 0.88 to 1.11; p < 0.05 for difference HFpEF vs. HFrEF). We found that the differential association of BMI with HFpEF versus HFrEF was more pronounced among women (p for difference HFpEF vs. HFrEF = 0.01) when compared with men (p = 0.34). CONCLUSIONS: Obesity and related cardiometabolic traits including insulin resistance are more strongly associated with risk of future HFpEF versus HFrEF. The differential risk of HFpEF with obesity seems particularly pronounced among women and may underlie sex differences in HF subtypes.

Circulating Very Long-Chain Saturated Fatty Acids and Heart Failure: The Cardiovascular Health Study. - Lemaitre, Rozenn N; McKnight, Barbara; Sotoodehnia, Nona; Fretts, Amanda M; Qureshi, Waqas T; Song, Xiaoling; King, Irena B; Sitlani, Colleen M; Siscovick, David S; Psaty, Bruce M; Mozaffarian, Dariush (J Am Heart Assoc, 2018)
Background Circulating very-long-chain saturated fatty acids ( VLSFAs ) are integrated biomarkers of diet and metabolism that may point to new risk pathways and potential targets for heart failure ( HF ) prevention. The associations of VLSFA to HF in humans are not known. Methods and Results Using a cohort study design, we studied the associations of serially measured plasma phospholipid VLSFA with incident HF in the Cardiovascular Health Study. We investigated the associations of time-varying levels of the 3 major circulating VLSFAs , lignoceric acid (24:0), behenic acid (22:0), and arachidic acid (20:0), with the risk of incident HF using Cox regression. During 45030 person-years among 4249 participants, we identified 1304 cases of incident HF , including 489 with preserved and 310 with reduced ejection fraction. Adjusting for major HF risk factors and other circulating fatty acids, higher levels of each VLSFAs were associated with lower risk of incident HF ( P trend≤0.0007 each). The hazard ratio comparing the highest quintile to the lowest quintile was 0.67 (95% confidence interval, 0.55-0.81) for 24:0, 0.72 (95% confidence interval, 0.60-0.87) for 22:0 and 0.72 (95% confidence interval, 0.59-0.88) for 20:0. The associations were similar in subgroups defined by sex, age, body mass index, coronary heart disease, and diabetes mellitus. Among those with ejection fraction data, the associations appeared similar for those with preserved and with reduced ejection fraction. Conclusions Higher levels of circulating VLSFAs are associated with lower risk of incident HF in older adults. These novel associations should prompt further research on the role of VLSFA in HF , including relevant new risk pathways. Clinical Trial Registration URL : https://www.clinicaltrials.gov . Unique identifier: NCT 00005133.

Common and Rare Coding Genetic Variation Underlying the Electrocardiographic PR Interval. - Lin, Honghuang; van Setten, Jessica; Smith, Albert V; Bihlmeyer, Nathan A; Warren, Helen R; Brody, Jennifer A; Radmanesh, Farid; Hall, Leanne; Grarup, Niels; Müller-Nurasyid, Martina; Boutin, Thibaud; Verweij, Niek; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Electrical conduction from the cardiac sinoatrial node to the ventricles is critical for normal heart function. Genome-wide association studies have identified more than a dozen common genetic loci that are associated with PR interval. However, it is unclear whether rare and low-frequency variants also contribute to PR interval heritability. METHODS: We performed large-scale meta-analyses of the PR interval that included 83 367 participants of European ancestry and 9436 of African ancestry. We examined both common and rare variants associated with the PR interval. RESULTS: We identified 31 genetic loci that were significantly associated with PR interval after Bonferroni correction (<1.2×10), including 11 novel loci that have not been reported previously. Many of these loci are involved in heart morphogenesis. In gene-based analysis, we found that multiple rare variants at (=5.9×10) and (=1.1×10) were associated with PR interval. locus also was implicated in the common variant analysis, whereas was a novel locus. CONCLUSIONS: We identified common variants at 11 novel loci and rare variants within 2 gene regions that were significantly associated with PR interval. Our findings provide novel insights to the current understanding of atrioventricular conduction, which is critical for cardiac activity and an important determinant of health.

Common Coding Variants in Are Associated With the Nav1.8 Late Current and Cardiac Conduction. - Macri, Vincenzo; Brody, Jennifer A; Arking, Dan E; Hucker, William J; Yin, Xiaoyan; Lin, Honghuang; Mills, Robert W; Sinner, Moritz F; Lubitz, Steven A; Liu, Ching-Ti; Morrison, Alanna C; Alonso, Alvaro; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Genetic variants at the / locus are strongly associated with electrocardiographic PR and QRS intervals. While is the canonical cardiac sodium channel gene, the role of in cardiac conduction is less well characterized. METHODS: We sequenced the locus in 3699 European-ancestry individuals to identify variants associated with cardiac conduction, and replicated our findings in 21,000 individuals of European ancestry. We examined association with expression in human atrial tissue. We explored the biophysical effect of variation on channel function using cellular electrophysiology. RESULTS: We identified 2 intronic single nucleotide polymorphisms in high linkage disequilibrium (  =0.86) with each other to be the strongest signals for PR (rs10428132, β=-4.74, =1.52×10) and QRS intervals (rs6599251, QRS β=-0.73; =1.2×10), respectively. Although these variants were not associated with or expression in human atrial tissue (n=490), they were in high linkage disequilibrium (  ≥0.72) with a common missense variant, rs6795970 (V1073A). In total, we identified 7 missense variants, 4 of which (I962V, P1045T, V1073A, and L1092P) were associated with cardiac conduction. These 4 missense variants cluster in the cytoplasmic linker of the second and third domains of the SCN10A protein and together form 6 common haplotypes. Using cellular electrophysiology, we found that haplotypes associated with shorter PR intervals had a significantly larger percentage of late current compared with wild-type (I962V+V1073A+L1092P, 20.2±3.3%, =0.03, and I962V+V1073A, 22.4±0.8%, =0.0004 versus wild-type 11.7±1.6%), and the haplotype associated with the longest PR interval had a significantly smaller late current percentage (P1045T, 6.4±1.2%, =0.03). CONCLUSIONS: Our findings suggest an association between genetic variation in , the late sodium current, and alterations in cardiac conduction.

Comparison of 2 Treatment Models: Precision Medicine and Preventive Medicine. - Psaty, Bruce M; Dekkers, Olaf M; Cooper, Richard S (JAMA, 2018)
Keywords: Humans; Precision Medicine; Preventive Medicine

A comprehensive evaluation of the genetic architecture of sudden cardiac arrest. - Ashar, Foram N; Mitchell, Rebecca N; Albert, Christine M; Newton-Cheh, Christopher; Brody, Jennifer A; Müller-Nurasyid, Martina; Moes, Anna; Meitinger, Thomas; Mak, Angel; Huikuri, Heikki; Junttila, M Juhani; Goyette, Philippe; et al. (Eur Heart J, 2018)
Aims: Sudden cardiac arrest (SCA) accounts for 10% of adult mortality in Western populations. We aim to identify potential loci associated with SCA and to identify risk factors causally associated with SCA. Methods and results: We carried out a large genome-wide association study (GWAS) for SCA (n = 3939 cases, 25 989 non-cases) to examine common variation genome-wide and in candidate arrhythmia genes. We also exploited Mendelian randomization (MR) methods using cross-trait multi-variant genetic risk score associations (GRSA) to assess causal relationships of 18 risk factors with SCA. No variants were associated with SCA at genome-wide significance, nor were common variants in candidate arrhythmia genes associated with SCA at nominal significance. Using cross-trait GRSA, we established genetic correlation between SCA and (i) coronary artery disease (CAD) and traditional CAD risk factors (blood pressure, lipids, and diabetes), (ii) height and BMI, and (iii) electrical instability traits (QT and atrial fibrillation), suggesting aetiologic roles for these traits in SCA risk. Conclusions: Our findings show that a comprehensive approach to the genetic architecture of SCA can shed light on the determinants of a complex life-threatening condition with multiple influencing factors in the general population. The results of this genetic analysis, both positive and negative findings, have implications for evaluating the genetic architecture of patients with a family history of SCA, and for efforts to prevent SCA in high-risk populations and the general community.

DNA methylation age is associated with an altered hemostatic profile in a multi-ethnic meta-analysis. - Ward-Caviness, Cavin K; Huffman, Jennifer E; Evertt, Karl; Germain, Marine; van Dongen, Jenny; Hill, W David; Jhun, Min A; Brody, Jennifer A; Ghanbari, Mohsen; Du, Lei; Roetker, Nicholas S; de Vries, Paul S; et al. (Blood, 2018)
Many hemostatic factors are associated with age and age-related diseases, however much remains unknown about the biological mechanisms linking aging and hemostatic factors. DNA methylation is a novel means by which to assess epigenetic aging, which is a measure of age and the aging processes as determined by altered epigenetic states. We used a meta-analysis approach to examine the association between measures of epigenetic aging and hemostatic factors, as well as a clotting time measure. For fibrinogen, we used European and African-ancestry participants who were meta-analyzed separately and combined via a random effects meta-analysis. All other measures only included participants of European-ancestry. We found that 1-year higher extrinsic epigenetic age as compared to chronological age was associated with higher fibrinogen (0.004 g/L per year; 95% CI: 0.001, 0.007; P = 0.01) and plasminogen activator inhibitor 1 (PAI-1; 0.13 U/mL per year; 95% CI: 0.07, 0.20; P = 6.6x10-5) concentrations as well as lower activated partial thromboplastin time, a measure of clotting time. We replicated PAI-1 associations using an independent cohort. To further elucidate potential functional mechanisms we associated epigenetic aging with expression levels of the PAI-1 protein encoding gene (SERPINE1) and the three fibrinogen subunit-encoding genes (FGA, FGG, and FGB), in both peripheral blood and aorta intima-media samples. We observed associations between accelerated epigenetic aging and transcription of FGG in both tissues. Collectively, our results indicate that accelerated epigenetic aging is associated with a pro-coagulation hemostatic profile, and that epigenetic aging may regulate hemostasis in part via gene transcription.

Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies. - Pennells, Lisa; Kaptoge, Stephen; Wood, Angela; Sweeting, Mike; Zhao, Xiaohui; White, Ian; Burgess, Stephen; Willeit, Peter; Bolton, Thomas; Moons, Karel G M; van der Schouw, Yvonne T; Selmer, Randi; et al. (Eur Heart J, 2018)
Aims: There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied. Methods and results: Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged ≥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms. Conclusion: Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

Exome Chip Analysis Identifies Low-Frequency and Rare Variants in for White Matter Hyperintensities on Brain Magnetic Resonance Imaging. - Jian, Xueqiu; Satizabal, Claudia L; Smith, Albert V; Wittfeld, Katharina; Bis, Joshua C; Smith, Jennifer A; Hsu, Fang-Chi; Nho, Kwangsik; Hofer, Edith; Hagenaars, Saskia P; Nyquist, Paul A; Mishra, Aniket; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) on brain magnetic resonance imaging are typical signs of cerebral small vessel disease and may indicate various preclinical, age-related neurological disorders, such as stroke. Though WMH are highly heritable, known common variants explain a small proportion of the WMH variance. The contribution of low-frequency/rare coding variants to WMH burden has not been explored. METHODS: In the discovery sample we recruited 20 719 stroke/dementia-free adults from 13 population-based cohort studies within the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, among which 17 790 were of European ancestry and 2929 of African ancestry. We genotyped these participants at ≈250 000 mostly exonic variants with Illumina HumanExome BeadChip arrays. We performed ethnicity-specific linear regression on rank-normalized WMH in each study separately, which were then combined in meta-analyses to test for association with single variants and genes aggregating the effects of putatively functional low-frequency/rare variants. We then sought replication of the top findings in 1192 adults (European ancestry) with whole exome/genome sequencing data from 2 independent studies. RESULTS: At 17q25, we confirmed the association of multiple common variants in , , and (<6×10). We also identified a novel association with 2 low-frequency nonsynonymous variants in (lead, rs34136221; =4.5×10) partially independent of known common signal (=1.4×10). We further identified a locus at 2q33 containing common variants in , , and (lead, rs2351524; =1.9×10). Although our novel findings were not replicated because of limited power and possible differences in study design, meta-analysis of the discovery and replication samples yielded stronger association for the 2 low-frequency variants (=2.8×10). CONCLUSIONS: Both common and low-frequency/rare functional variants influence WMH. Larger replication and experimental follow-up are essential to confirm our findings and uncover the biological causal mechanisms of age-related WMH.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.

ExomeChip-Wide Analysis of 95 626 Individuals Identifies 10 Novel Loci Associated With QT and JT Intervals. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Warren, Helen R; Lin, Honghuang; Isaacs, Aaron; Liu, Ching-Ti; Marten, Jonathan; Radmanesh, Farid; Hall, Leanne M; Grarup, Niels; Mei, Hao; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: QT interval, measured through a standard ECG, captures the time it takes for the cardiac ventricles to depolarize and repolarize. JT interval is the component of the QT interval that reflects ventricular repolarization alone. Prolonged QT interval has been linked to higher risk of sudden cardiac arrest. METHODS AND RESULTS: We performed an ExomeChip-wide analysis for both QT and JT intervals, including 209 449 variants, both common and rare, in 17 341 genes from the Illumina Infinium HumanExome BeadChip. We identified 10 loci that modulate QT and JT interval duration that have not been previously reported in the literature using single-variant statistical models in a meta-analysis of 95 626 individuals from 23 cohorts (comprised 83 884 European ancestry individuals, 9610 blacks, 1382 Hispanics, and 750 Asians). This brings the total number of ventricular repolarization associated loci to 45. In addition, our approach of using coding variants has highlighted the role of 17 specific genes for involvement in ventricular repolarization, 7 of which are in novel loci. CONCLUSIONS: Our analyses show a role for myocyte internal structure and interconnections in modulating QT interval duration, adding to previous known roles of potassium, sodium, and calcium ion regulation, as well as autonomic control. We anticipate that these discoveries will open new paths to the goal of making novel remedies for the prevention of lethal ventricular arrhythmias and sudden cardiac arrest.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic Variants Associated with Circulating Fibroblast Growth Factor 23. - Robinson-Cohen, Cassianne; Bartz, Traci M; Lai, Dongbing; Ikizler, T Alp; Peacock, Munro; Imel, Erik A; Michos, Erin D; Foroud, Tatiana M; Åkesson, Kristina; Taylor, Kent D; Malmgren, Linnea; Matsushita, Kunihiro; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Fibroblast growth factor 23 (FGF23), a bone-derived hormone that regulates phosphorus and vitamin D metabolism, contributes to the pathogenesis of mineral and bone disorders in CKD and is an emerging cardiovascular risk factor. Central elements of FGF23 regulation remain incompletely understood; genetic variation may help explain interindividual differences. METHODS: We performed a meta-analysis of genome-wide association studies of circulating FGF23 concentrations among 16,624 participants of European ancestry from seven cohort studies, excluding participants with eGFR<30 ml/min per 1.73 m to focus on FGF23 under normal conditions. We evaluated the association of single-nucleotide polymorphisms (SNPs) with natural log-transformed FGF23 concentration, adjusted for age, sex, study site, and principal components of ancestry. A second model additionally adjusted for BMI and eGFR. RESULTS: We discovered 154 SNPs from five independent regions associated with FGF23 concentration. The SNP with the strongest association, rs17216707 (=3.0×10), lies upstream of , which encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-hydroxyvitamin D. Each additional copy of the T allele at this locus is associated with 5% higher FGF23 concentration. Another locus strongly associated with variations in FGF23 concentration is rs11741640, within and upstream of (a gene involved in renal phosphate transport). Additional adjustment for BMI and eGFR did not materially alter the magnitude of these associations. Another top locus (within , the ABO blood group transferase gene) was no longer statistically significant at the genome-wide level. CONCLUSIONS: Common genetic variants located near genes involved in vitamin D metabolism and renal phosphate transport are associated with differences in circulating FGF23 concentrations.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation. - Teumer, Alexander; Chaker, Layal; Groeneweg, Stefan; Li, Yong; Di Munno, Celia; Barbieri, Caterina; Schultheiss, Ulla T; Traglia, Michela; Ahluwalia, Tarunveer S; Akiyama, Masato; Appel, Emil Vincent R; Arking, Dan E; et al. (Nat Commun, 2018)
Thyroid dysfunction is an important public health problem, which affects 10% of the general population and increases the risk of cardiovascular morbidity and mortality. Many aspects of thyroid hormone regulation have only partly been elucidated, including its transport, metabolism, and genetic determinants. Here we report a large meta-analysis of genome-wide association studies for thyroid function and dysfunction, testing 8 million genetic variants in up to 72,167 individuals. One-hundred-and-nine independent genetic variants are associated with these traits. A genetic risk score, calculated to assess their combined effects on clinical end points, shows significant associations with increased risk of both overt (Graves' disease) and subclinical thyroid disease, as well as clinical complications. By functional follow-up on selected signals, we identify a novel thyroid hormone transporter (SLC17A4) and a metabolizing enzyme (AADAT). Together, these results provide new knowledge about thyroid hormone physiology and disease, opening new possibilities for therapeutic targets.

Genome-wide association meta-analysis of circulating odd-numbered chain saturated fatty acids: Results from the CHARGE Consortium. - de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Sun, Qi; King, Irena B; Wu, Jason H Y; Manichaikul, Ani; Rich, Stephen S; Tsai, Michael Y; Chen, Y D; Fornage, Myriam; Weihua, Guan; Aslibekyan, Stella; et al. (PLoS One, 2018)
BACKGROUND: Odd-numbered chain saturated fatty acids (OCSFA) have been associated with potential health benefits. Although some OCSFA (e.g., C15:0 and C17:0) are found in meats and dairy products, sources and metabolism of C19:0 and C23:0 are relatively unknown, and the influence of non-dietary determinants, including genetic factors, on circulating levels of OCSFA is not established. OBJECTIVE: To elucidate the biological processes that influence circulating levels of OCSFA by investigating associations between genetic variation and OCSFA. DESIGN: We performed a meta-analysis of genome-wide association studies (GWAS) of plasma phospholipid/erythrocyte levels of C15:0, C17:0, C19:0, and C23:0 among 11,494 individuals of European descent. We also investigated relationships between specific single nucleotide polymorphisms (SNPs) in the lactase (LCT) gene, associated with adult-onset lactase intolerance, with circulating levels of dairy-derived OCSFA, and evaluated associations of candidate sphingolipid genes with C23:0 levels. RESULTS: We found no genome-wide significant evidence that common genetic variation is associated with circulating levels of C15:0 or C23:0. In two cohorts with available data, we identified one intronic SNP (rs13361131) in myosin X gene (MYO10) associated with C17:0 level (P = 1.37×10-8), and two intronic SNP (rs12874278 and rs17363566) in deleted in lymphocytic leukemia 1 (DLEU1) region associated with C19:0 level (P = 7.07×10-9). In contrast, when using a candidate-gene approach, we found evidence that three SNPs in LCT (rs11884924, rs16832067, and rs3816088) are associated with circulating C17:0 level (adjusted P = 4×10-2). In addition, nine SNPs in the ceramide synthase 4 (CERS4) region were associated with circulating C23:0 levels (adjusted P<5×10-2). CONCLUSIONS: Our findings suggest that circulating levels of OCSFA may be predominantly influenced by non-genetic factors. SNPs associated with C17:0 level in the LCT gene may reflect genetic influence in dairy consumption or in metabolism of dairy foods. SNPs associated with C23:0 may reflect a role of genetic factors in the synthesis of sphingomyelin.
Keywords: Fatty Acids; Genome-Wide Association Study; Humans; Introns; Lactase; Myosins; Polymorphism, Single Nucleotide; Sphingomyelins; Sphingosine N-Acyltransferase; Tumor Suppressor Proteins

Genome-wide association study and meta-analysis identify loci associated with ventricular and supraventricular ectopy. - Napier, Melanie D; Franceschini, Nora; Gondalia, Rahul; Stewart, James D; Méndez-Giráldez, Rául; Sitlani, Colleen M; Seyerle, Amanda A; Highland, Heather M; Li, Yun; Wilhelmsen, Kirk C; Yan, Song; Duan, Qing; et al. (Sci Rep, 2018)
The genetic basis of supraventricular and ventricular ectopy (SVE, VE) remains largely uncharacterized, despite established genetic mechanisms of arrhythmogenesis. To identify novel genetic variants associated with SVE/VE in ancestrally diverse human populations, we conducted a genome-wide association study of electrocardiographically identified SVE and VE in five cohorts including approximately 43,000 participants of African, European and Hispanic/Latino ancestry. In thirteen ancestry-stratified subgroups, we tested multivariable-adjusted associations of SVE and VE with single nucleotide polymorphism (SNP) dosage. We combined subgroup-specific association estimates in inverse variance-weighted, fixed-effects and Bayesian meta-analyses. We also combined fixed-effects meta-analytic t-test statistics for SVE and VE in multi-trait SNP association analyses. No loci reached genome-wide significance in trans-ethnic meta-analyses. However, we found genome-wide significant SNPs intronic to an apoptosis-enhancing gene previously associated with QRS interval duration (FAF1; lead SNP rs7545860; effect allele frequency = 0.02; P = 2.0 × 10) in multi-trait analysis among European ancestry participants and near a locus encoding calcium-dependent glycoproteins (DSC3; lead SNP rs8086068; effect allele frequency = 0.17) in meta-analysis of SVE (P = 4.0 × 10) and multi-trait analysis (P = 2.9 × 10) among African ancestry participants. The novel findings suggest several mechanisms by which genetic variation may predispose to ectopy in humans and highlight the potential value of leveraging pleiotropy in future studies of ectopy-related phenotypes.

Genome-wide association study of 23,500 individuals identifies 7 loci associated with brain ventricular volume. - Vojinovic, Dina; Adams, Hieab H; Jian, Xueqiu; Yang, Qiong; Smith, Albert Vernon; Bis, Joshua C; Teumer, Alexander; Scholz, Markus; Armstrong, Nicola J; Hofer, Edith; Saba, Yasaman; Luciano, Michelle; et al. (Nat Commun, 2018)
The volume of the lateral ventricles (LV) increases with age and their abnormal enlargement is a key feature of several neurological and psychiatric diseases. Although lateral ventricular volume is heritable, a comprehensive investigation of its genetic determinants is lacking. In this meta-analysis of genome-wide association studies of 23,533 healthy middle-aged to elderly individuals from 26 population-based cohorts, we identify 7 genetic loci associated with LV volume. These loci map to chromosomes 3q28, 7p22.3, 10p12.31, 11q23.1, 12q23.3, 16q24.2, and 22q13.1 and implicate pathways related to tau pathology, S1P signaling, and cytoskeleton organization. We also report a significant genetic overlap between the thalamus and LV volumes (ρ = -0.59, p-value = 3.14 × 10), suggesting that these brain structures may share a common biology. These genetic associations of LV volume provide insights into brain morphology.

Genome-Wide Association Trans-Ethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels. - Sabater-Lleal, Maria; Huffman, Jennifer E; de Vries, Paul S; Marten, Jonathan; Mastrangelo, Michael A; Song, Ci; Pankratz, Nathan; Ward-Caviness, Cavin K; Yanek, Lisa R; Trompet, Stella; Delgado, Graciela E; Guo, Xiuqing; et al. (Circulation, 2018)
BACKGROUND: Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF. METHODS: We meta-analyzed genome-wide association results from 46,354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated approximately 35 million imputed variants with natural-log transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization (MR) analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events. RESULTS: We identified 13 novel genome-wide significant (p≤2.5x10) associations; 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. MR suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk. CONCLUSIONS: The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

Genome-wide meta-analysis of 158,000 individuals of European ancestry identifies three loci associated with chronic back pain. - Suri, Pradeep; Palmer, Melody R; Tsepilov, Yakov A; Freidin, Maxim B; Boer, Cindy G; Yau, Michelle S; Evans, Daniel S; Gelemanovic, Andrea; Bartz, Traci M; Nethander, Maria; Arbeeva, Liubov; Karssen, Lennart; et al. (PLoS Genet, 2018)
Back pain is the #1 cause of years lived with disability worldwide, yet surprisingly little is known regarding the biology underlying this symptom. We conducted a genome-wide association study (GWAS) meta-analysis of chronic back pain (CBP). Adults of European ancestry were included from 15 cohorts in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and from the UK Biobank interim data release. CBP cases were defined as those reporting back pain present for ≥3-6 months; non-cases were included as comparisons ("controls"). Each cohort conducted genotyping using commercially available arrays followed by imputation. GWAS used logistic regression models with additive genetic effects, adjusting for age, sex, study-specific covariates, and population substructure. The threshold for genome-wide significance in the fixed-effect inverse-variance weighted meta-analysis was p<5×10-8. Suggestive (p<5×10-7) and genome-wide significant (p<5×10-8) variants were carried forward for replication or further investigation in the remaining UK Biobank participants not included in the discovery sample. The discovery sample comprised 158,025 individuals, including 29,531 CBP cases. A genome-wide significant association was found for the intronic variant rs12310519 in SOX5 (OR 1.08, p = 7.2×10-10). This was subsequently replicated in 283,752 UK Biobank participants not included in the discovery sample, including 50,915 cases (OR 1.06, p = 5.3×10-11), and exceeded genome-wide significance in joint meta-analysis (OR 1.07, p = 4.5×10-19). We found suggestive associations at three other loci in the discovery sample, two of which exceeded genome-wide significance in joint meta-analysis: an intergenic variant, rs7833174, located between CCDC26 and GSDMC (OR 1.05, p = 4.4×10-13), and an intronic variant, rs4384683, in DCC (OR 0.97, p = 2.4×10-10). In this first reported meta-analysis of GWAS for CBP, we identified and replicated a genetic locus associated with CBP (SOX5). We also identified 2 other loci that reached genome-wide significance in a 2-stage joint meta-analysis (CCDC26/GSDMC and DCC).

Genome-wide meta-analysis of SNP-by9-ACEI/ARB and SNP-by-thiazide diuretic and effect on serum potassium in cohorts of European and African ancestry. - Irvin, Marguerite R; Sitlani, Colleen M; Noordam, Raymond; Avery, Christie L; Bis, Joshua C; Floyd, James S; Li, Jin; Limdi, Nita A; Srinivasasainagendra, Vinodh; Stewart, James; de Mutsert, Renée; Mook-Kanamori, Dennis O; et al. (Pharmacogenomics J, 2018)
We evaluated interactions of SNP-by-ACE-I/ARB and SNP-by-TD on serum potassium (K+) among users of antihypertensive treatments (anti-HTN). Our study included seven European-ancestry (EA) (N = 4835) and four African-ancestry (AA) cohorts (N = 2016). We performed race-stratified, fixed-effect, inverse-variance-weighted meta-analyses of 2.5 million SNP-by-drug interaction estimates; race-combined meta-analysis; and trans-ethnic fine-mapping. Among EAs, we identified 11 significant SNPs (P < 5 × 10) for SNP-ACE-I/ARB interactions on serum K+ that were located between NR2F1-AS1 and ARRDC3-AS1 on chromosome 5 (top SNP rs6878413 P = 1.7 × 10; ratio of serum K+ in ACE-I/ARB exposed compared to unexposed is 1.0476, 1.0280, 1.0088 for the TT, AT, and AA genotypes, respectively). Trans-ethnic fine mapping identified the same group of SNPs on chromosome 5 as genome-wide significant for the ACE-I/ARB analysis. In conclusion, SNP-by-ACE-I /ARB interaction analyses uncovered loci that, if replicated, could have future implications for the prevention of arrhythmias due to anti-HTN treatment-related hyperkalemia. Before these loci can be identified as clinically relevant, future validation studies of equal or greater size in comparison to our discovery effort are needed.

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).

Large-scale whole-exome sequencing association studies identify rare functional variants influencing serum urate levels. - Tin, Adrienne; Li, Yong; Brody, Jennifer A; Nutile, Teresa; Chu, Audrey Y; Huffman, Jennifer E; Yang, Qiong; Chen, Ming-Huei; Robinson-Cohen, Cassianne; Mace, Aurelien; Liu, Jun; Demirkan, Ayse; et al. (Nat Commun, 2018)
Elevated serum urate levels can cause gout, an excruciating disease with suboptimal treatment. Previous GWAS identified common variants with modest effects on serum urate. Here we report large-scale whole-exome sequencing association studies of serum urate and kidney function among ≤19,517 European ancestry and African-American individuals. We identify aggregate associations of low-frequency damaging variants in the urate transporters SLC22A12 (URAT1; p = 1.3 × 10) and SLC2A9 (p = 4.5 × 10). Gout risk in rare SLC22A12 variant carriers is halved (OR = 0.5, p = 4.9 × 10). Selected rare variants in SLC22A12 are validated in transport studies, confirming three as loss-of-function (R325W, R405C, and T467M) and illustrating the therapeutic potential of the new URAT1-blocker lesinurad. In SLC2A9, mapping of rare variants of large effects onto the predicted protein structure reveals new residues that may affect urate binding. These findings provide new insights into the genetic architecture of serum urate, and highlight molecular targets in SLC22A12 and SLC2A9 for lowering serum urate and preventing gout.
Keywords: Exome; Genetic Predisposition to Disease; Glucose Transport Proteins, Facilitative; Humans; Kidney Function Tests; Meta-Analysis as Topic; Organic Anion Transporters; Organic Cation Transport Proteins; Protein Structure, Secondary; Uric Acid

Long-Term Cognitive Decline After Newly Diagnosed Heart Failure: Longitudinal Analysis in the CHS (Cardiovascular Health Study). - Hammond, Christa A; Blades, Natalie J; Chaudhry, Sarwat I; Dodson, John A; Longstreth, W T; Heckbert, Susan R; Psaty, Bruce M; Arnold, Alice M; Dublin, Sascha; Sitlani, Colleen M; Gardin, Julius M; Thielke, Stephen M; et al. (Circ Heart Fail, 2018)
BACKGROUND: Heart failure (HF) is associated with cognitive impairment. However, we know little about the time course of cognitive change after HF diagnosis, the importance of comorbid atrial fibrillation, or the role of ejection fraction. We sought to determine the associations of incident HF with rates of cognitive decline and whether these differed by atrial fibrillation status or reduced versus preserved ejection fraction. METHODS AND RESULTS: Participants were 4864 men and women aged ≥65 years without a history of HF and free of clinical stroke in the CHS (Cardiovascular Health Study)-a community-based prospective cohort study in the United States, with cognition assessed annually from 1989/1990 through 1998/1999. We identified 496 participants with incident HF by review of hospital discharge summaries and Medicare claims data, with adjudication according to standard criteria. Global cognitive ability was measured by the Modified Mini-Mental State Examination. In adjusted models, 5-year decline in model-predicted mean Modified Mini-Mental State Examination score was 10.2 points (95% confidence interval, 8.6-11.8) after incident HF diagnosed at 80 years of age, compared with a mean 5-year decline of 5.8 points (95% confidence interval, 5.3-6.2) from 80 to 85 years of age without HF. The association was stronger at older ages than at younger ages, did not vary significantly in the presence versus absence of atrial fibrillation (=0.084), and did not vary significantly by reduced versus preserved ejection fraction (=0.734). CONCLUSIONS: Decline in global cognitive ability tends to be faster after HF diagnosis than without HF. Clinical and public health implications of this finding warrant further attention.

Meta-analysis across Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium provides evidence for an association of serum vitamin D with pulmonary function. - Xu, Jiayi; Bartz, Traci M; Chittoor, Geetha; Eiriksdottir, Gudny; Manichaikul, Ani W; Sun, Fangui; Terzikhan, Natalie; Zhou, Xia; Booth, Sarah L; Brusselle, Guy G; de Boer, Ian H; Fornage, Myriam; et al. (Br J Nutr, 2018)
The role that vitamin D plays in pulmonary function remains uncertain. Epidemiological studies reported mixed findings for serum 25-hydroxyvitamin D (25(OH)D)-pulmonary function association. We conducted the largest cross-sectional meta-analysis of the 25(OH)D-pulmonary function association to date, based on nine European ancestry (EA) cohorts (n 22 838) and five African ancestry (AA) cohorts (n 4290) in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Data were analysed using linear models by cohort and ancestry. Effect modification by smoking status (current/former/never) was tested. Results were combined using fixed-effects meta-analysis. Mean serum 25(OH)D was 68 (sd 29) nmol/l for EA and 49 (sd 21) nmol/l for AA. For each 1 nmol/l higher 25(OH)D, forced expiratory volume in the 1st second (FEV1) was higher by 1·1 ml in EA (95 % CI 0·9, 1·3; P<0·0001) and 1·8 ml (95 % CI 1·1, 2·5; P<0·0001) in AA (P race difference=0·06), and forced vital capacity (FVC) was higher by 1·3 ml in EA (95 % CI 1·0, 1·6; P<0·0001) and 1·5 ml (95 % CI 0·8, 2·3; P=0·0001) in AA (P race difference=0·56). Among EA, the 25(OH)D-FVC association was stronger in smokers: per 1 nmol/l higher 25(OH)D, FVC was higher by 1·7 ml (95 % CI 1·1, 2·3) for current smokers and 1·7 ml (95 % CI 1·2, 2·1) for former smokers, compared with 0·8 ml (95 % CI 0·4, 1·2) for never smokers. In summary, the 25(OH)D associations with FEV1 and FVC were positive in both ancestries. In EA, a stronger association was observed for smokers compared with never smokers, which supports the importance of vitamin D in vulnerable populations.

Meta-analysis of exome array data identifies six novel genetic loci for lung function. - Jackson, Victoria E; Latourelle, Jeanne C; Wain, Louise V; Smith, Albert V; Grove, Megan L; Bartz, Traci M; Obeidat, Ma'en; Province, Michael A; Gao, Wei; Qaiser, Beenish; Porteous, David J; Cassano, Patricia A; et al. (Wellcome Open Res, 2018)
Over 90 regions of the genome have been associated with lung function to date, many of which have also been implicated in chronic obstructive pulmonary disease. We carried out meta-analyses of exome array data and three lung function measures: forced expiratory volume in one second (FEV ), forced vital capacity (FVC) and the ratio of FEV to FVC (FEV /FVC). These analyses by the SpiroMeta and CHARGE consortia included 60,749 individuals of European ancestry from 23 studies, and 7,721 individuals of African Ancestry from 5 studies in the discovery stage, with follow-up in up to 111,556 independent individuals. We identified significant (P<2·8x10 ) associations with six SNPs: a nonsynonymous variant in , which is predicted to be damaging, three intronic SNPs ( and ) and two intergenic SNPs near to and Expression quantitative trait loci analyses found evidence for regulation of gene expression at three signals and implicated several genes, including and . Further interrogation of these loci could provide greater understanding of the determinants of lung function and pulmonary disease.

Multiancestry genome-wide association study of 520,000 subjects identifies 32 loci associated with stroke and stroke subtypes. - Malik, Rainer; Chauhan, Ganesh; Traylor, Matthew; Sargurupremraj, Muralidharan; Okada, Yukinori; Mishra, Aniket; Rutten-Jacobs, Loes; Giese, Anne-Katrin; van der Laan, Sander W; Gretarsdottir, Solveig; Anderson, Christopher D; Chong, Michael; et al. (Nat Genet, 2018)
Stroke has multiple etiologies, but the underlying genes and pathways are largely unknown. We conducted a multiancestry genome-wide-association meta-analysis in 521,612 individuals (67,162 cases and 454,450 controls) and discovered 22 new stroke risk loci, bringing the total to 32. We further found shared genetic variation with related vascular traits, including blood pressure, cardiac traits, and venous thromboembolism, at individual loci (n = 18), and using genetic risk scores and linkage-disequilibrium-score regression. Several loci exhibited distinct association and pleiotropy patterns for etiological stroke subtypes. Eleven new susceptibility loci indicate mechanisms not previously implicated in stroke pathophysiology, with prioritization of risk variants and genes accomplished through bioinformatics analyses using extensive functional datasets. Stroke risk loci were significantly enriched in drug targets for antithrombotic therapy.

Multi-ethnic genome-wide association study for atrial fibrillation. - Roselli, Carolina; Chaffin, Mark D; Weng, Lu-Chen; Aeschbacher, Stefanie; Ahlberg, Gustav; Albert, Christine M; Almgren, Peter; Alonso, Alvaro; Anderson, Christopher D; Aragam, Krishna G; Arking, Dan E; Barnard, John; et al. (Nat Genet, 2018)
Atrial fibrillation (AF) affects more than 33 million individuals worldwide and has a complex heritability. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for AF to date, consisting of more than half a million individuals, including 65,446 with AF. In total, we identified 97 loci significantly associated with AF, including 67 that were novel in a combined-ancestry analysis, and 3 that were novel in a European-specific analysis. We sought to identify AF-associated genes at the GWAS loci by performing RNA-sequencing and expression quantitative trait locus analyses in 101 left atrial samples, the most relevant tissue for AF. We also performed transcriptome-wide analyses that identified 57 AF-associated genes, 42 of which overlap with GWAS loci. The identified loci implicate genes enriched within cardiac developmental, electrophysiological, contractile and structural pathways. These results extend our understanding of the biological pathways underlying AF and may facilitate the development of therapeutics for AF.

Multiethnic meta-analysis identifies ancestry-specific and cross-ancestry loci for pulmonary function. - Wyss, Annah B; Sofer, Tamar; Lee, Mi Kyeong; Terzikhan, Natalie; Nguyen, Jennifer N; Lahousse, Lies; Latourelle, Jeanne C; Smith, Albert Vernon; Bartz, Traci M; Feitosa, Mary F; Gao, Wei; Ahluwalia, Tarunveer S; et al. (Nat Commun, 2018)
Nearly 100 loci have been identified for pulmonary function, almost exclusively in studies of European ancestry populations. We extend previous research by meta-analyzing genome-wide association studies of 1000 Genomes imputed variants in relation to pulmonary function in a multiethnic population of 90,715 individuals of European (N = 60,552), African (N = 8429), Asian (N = 9959), and Hispanic/Latino (N = 11,775) ethnicities. We identify over 50 additional loci at genome-wide significance in ancestry-specific or multiethnic meta-analyses. Using recent fine-mapping methods incorporating functional annotation, gene expression, and differences in linkage disequilibrium between ethnicities, we further shed light on potential causal variants and genes at known and newly identified loci. Several of the novel genes encode proteins with predicted or established drug targets, including KCNK2 and CDK12. Our study highlights the utility of multiethnic and integrative genomics approaches to extend existing knowledge of the genetics of lung function and clinical relevance of implicated loci.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.

Omega-3 Fatty Acids and Genome-wide Interaction Analyses Reveal DPP10-Pulmonary Function Association. - Xu, Jiayi; Gaddis, Nathan C; Bartz, Traci M; Hou, Ruixue; Manichaikul, Ani W; Pankratz, Nathan; Smith, Albert V; Sun, Fangui; Terzikhan, Natalie; Markunas, Christina A; Patchen, Bonnie K; Schu, Matthew; et al. (Am J Respir Crit Care Med, 2018)
RATIONALE: Omega-3 poly-unsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health. OBJECTIVE: To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility. METHODS: Associations of n-3 PUFA biomarkers (alpha-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (forced expiratory volume in the first second [FEV], forced vital capacity [FVC], and [FEV/FVC]) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N=16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N=11,962) and replicated in one cohort (N=1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of single nucleotide polymorphism (SNP) associations and their interactions with n-3 PUFAs. RESULTS: DPA and DHA were positively associated with FEV1 and FVC (P<0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P=9.4×10 across discovery and replication cohorts). The rs11693320-A allele (frequency~80%) was associated with lower FVC (P=2.1×10; β= -161.0mL), and the association was attenuated by higher DHA levels (P=2.1×10; β=36.2mL). CONCLUSIONS: We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

Outdoor air pollution and mosaic loss of chromosome Y in older men from the Cardiovascular Health Study. - Wong, Jason Y Y; Margolis, Helene G; Machiela, Mitchell; Zhou, Weiyin; Odden, Michelle C; Psaty, Bruce M; Robbins, John; Jones, Rena R; Rotter, Jerome I; Chanock, Stephen J; Rothman, Nathaniel; Lan, Qing; et al. (Environ Int, 2018)
BACKGROUND: Mosaic loss of chromosome Y (mLOY) can occur in a fraction of cells as men age, which is potentially linked to increased mortality risk. Smoking is related to mLOY; however, the contribution of air pollution is unclear. OBJECTIVE: We investigated whether exposure to outdoor air pollution, age, and smoking were associated with mLOY. METHODS: We analyzed baseline (1989-1993) blood samples from 933 men ≥65 years of age from the prospective Cardiovascular Health Study. Particulate matter ≤10 μm (PM), carbon monoxide, nitrogen dioxide, sulfur dioxide, and ozone data were obtained from the U.S. EPA Aerometric Information Retrieval System for the year prior to baseline. Inverse-distance weighted air monitor data were used to estimate each participants' monthly residential exposure. mLOY was detected with standard methods using signal intensity (median log-R ratio (mLRR)) of the male-specific chromosome Y regions from Illumina array data. Linear regression models were used to evaluate relations between mean exposure in the prior year, age, smoking and continuous mLRR. RESULTS: Increased PM was associated with mLOY, namely decreased mLRR (p-trend = 0.03). Compared with the lowest tertile (≤28.5 μg/m), the middle (28.5-31.0 μg/m; β = -0.0044, p = 0.09) and highest (≥31 μg/m; β = -0.0054, p = 0.04) tertiles had decreased mLRR, adjusted for age, clinic, race/cohort, smoking status and pack-years. Additionally, increasing age (β = -0.00035, p = 0.06) and smoking pack-years (β = -0.00011, p = 1.4E-3) were associated with decreased mLRR, adjusted for each other and race/cohort. No significant associations were found for other pollutants. CONCLUSIONS: PM may increase leukocyte mLOY, a marker of genomic instability. The sample size was modest and replication is warranted.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.

The relation between thyroid function and anemia: a pooled analysis of individual participant data. - Wopereis, Daisy M; Du Puy, Robert S; van Heemst, Diana; Walsh, John P; Bremner, Alexandra; Bakker, Stephan J L; Bauer, Douglas C; Cappola, Anne R; Ceresini, Graziano; Degryse, Jean; Dullaart, Robin P F; Feller, Martin; et al. (J Clin Endocrinol Metab, 2018)
Context: Anemia and thyroid dysfunction often co-occur and both increase with age. Human data on the relationship between thyroid disease and anemia are scarce. Objective: To investigate the cross-sectional and longitudinal associations between clinical thyroid status and anemia. Design: Individual participant data meta-analysis. Setting: Sixteen cohorts participating in the Thyroid Studies Collaboration (n=42 162). Main outcome measures: Primary outcome measure was anemia (hemoglobin <130 g/L in men and <120 g/L in women). Results: Cross-sectionally, participants with abnormal thyroid status had an increased risk of having anemia compared with euthyroid participants (overt hypothyroidism, pooled odds ratio 1.84 [95% CI: 1.35-2.50], subclinical hypothyroidism 1.21 [1.02-1.43], subclinical hyperthyroidism 1.27 [1.03-1.57], overt hyperthyroidism 1.69 [1.00-2.87]). Hemoglobin levels were lower in all groups compared to participants with euthyroidism. In the longitudinal analyses (n=25,466 from 14 cohorts), the pooled hazard ratio for the risk of development of anemia was 1.38 [95% CI: 0.86-2.20] for overt hypothyroidism, 1.18 [1.00-1.38] for subclinical hypothyroidism, 1.15 [0.94-1.42] for subclinical hyperthyroidism and 1.47 [0.91-2.38] for overt hyperthyroidism. Sensitivity analyses excluding thyroid medication or high levels of C-reactive protein yielded similar results. No differences in mean annual change in hemoglobin levels were observed between the thyroid hormone status groups. Conclusion: Higher odds of having anemia were observed in both participants with hypothyroid function and hyperthyroid function. In addition, reduced thyroid function at baseline showed a trend of increased risk of developing anemia during follow-up. It remains to be assessed in a randomized controlled trial whether treatment is effective in reducing anemia.

Risk thresholds for alcohol consumption: combined analysis of individual-participant data for 599 912 current drinkers in 83 prospective studies. - Wood, Angela M; Kaptoge, Stephen; Butterworth, Adam S; Willeit, Peter; Warnakula, Samantha; Bolton, Thomas; Paige, Ellie; Paul, Dirk S; Sweeting, Michael; Burgess, Stephen; Bell, Steven; Astle, William; et al. (Lancet, 2018)
BACKGROUND: Low-risk limits recommended for alcohol consumption vary substantially across different national guidelines. To define thresholds associated with lowest risk for all-cause mortality and cardiovascular disease, we studied individual-participant data from 599 912 current drinkers without previous cardiovascular disease. METHODS: We did a combined analysis of individual-participant data from three large-scale data sources in 19 high-income countries (the Emerging Risk Factors Collaboration, EPIC-CVD, and the UK Biobank). We characterised dose-response associations and calculated hazard ratios (HRs) per 100 g per week of alcohol (12·5 units per week) across 83 prospective studies, adjusting at least for study or centre, age, sex, smoking, and diabetes. To be eligible for the analysis, participants had to have information recorded about their alcohol consumption amount and status (ie, non-drinker vs current drinker), plus age, sex, history of diabetes and smoking status, at least 1 year of follow-up after baseline, and no baseline history of cardiovascular disease. The main analyses focused on current drinkers, whose baseline alcohol consumption was categorised into eight predefined groups according to the amount in grams consumed per week. We assessed alcohol consumption in relation to all-cause mortality, total cardiovascular disease, and several cardiovascular disease subtypes. We corrected HRs for estimated long-term variability in alcohol consumption using 152 640 serial alcohol assessments obtained some years apart (median interval 5·6 years [5th-95th percentile 1·04-13·5]) from 71 011 participants from 37 studies. FINDINGS: In the 599 912 current drinkers included in the analysis, we recorded 40 310 deaths and 39 018 incident cardiovascular disease events during 5·4 million person-years of follow-up. For all-cause mortality, we recorded a positive and curvilinear association with the level of alcohol consumption, with the minimum mortality risk around or below 100 g per week. Alcohol consumption was roughly linearly associated with a higher risk of stroke (HR per 100 g per week higher consumption 1·14, 95% CI, 1·10-1·17), coronary disease excluding myocardial infarction (1·06, 1·00-1·11), heart failure (1·09, 1·03-1·15), fatal hypertensive disease (1·24, 1·15-1·33); and fatal aortic aneurysm (1·15, 1·03-1·28). By contrast, increased alcohol consumption was log-linearly associated with a lower risk of myocardial infarction (HR 0·94, 0·91-0·97). In comparison to those who reported drinking >0-≤100 g per week, those who reported drinking >100-≤200 g per week, >200-≤350 g per week, or >350 g per week had lower life expectancy at age 40 years of approximately 6 months, 1-2 years, or 4-5 years, respectively. INTERPRETATION: In current drinkers of alcohol in high-income countries, the threshold for lowest risk of all-cause mortality was about 100 g/week. For cardiovascular disease subtypes other than myocardial infarction, there were no clear risk thresholds below which lower alcohol consumption stopped being associated with lower disease risk. These data support limits for alcohol consumption that are lower than those recommended in most current guidelines. FUNDING: UK Medical Research Council, British Heart Foundation, National Institute for Health Research, European Union Framework 7, and European Research Council.

Sleep characteristics that predict atrial fibrillation. - Christensen, Matthew A; Dixit, Shalini; Dewland, Thomas A; Whitman, Isaac R; Nah, Gregory; Vittinghoff, Eric; Mukamal, Kenneth J; Redline, Susan; Robbins, John A; Newman, Anne B; Patel, Sanjay R; Magnani, Jared W; et al. (Heart Rhythm, 2018)
BACKGROUND: The relationship between sleep disruption, independent of obstructive sleep apnea (OSA), and atrial fibrillation (AF) is unknown. OBJECTIVE: The purpose of this study was to determine whether poor sleep itself is a risk factor for AF. METHODS: We first performed an analysis of participants in the Health eHeart Study and validated those findings in the longitudinal Cardiovascular Health Study, including a subset of patients undergoing polysomnography. To determine whether the observed relationships readily translated to medical practice, we examined 2005-2009 data from the California Healthcare Cost and Utilization Project. RESULTS: Among 4553 Health eHeart participants, the 526 with AF exhibited more frequent nighttime awakening (odd ratio [OR] 1.47; 95% confidence interval [CI] 1.14-1.89; P = .003). In 5703 Cardiovascular Health Study participants followed for a median 11.6 years, frequent nighttime awakening predicted a 33% greater risk of AF (hazard ratio [HR] 1.33; 95% CI 1.17-1.51; P <.001). In patients with polysomnography (N = 1127), every standard deviation percentage decrease in rapid eye movement (REM) sleep was associated with a 18% higher risk of developing AF (HR 1.18; 95% CI 1.00-1.38; P = .047). Among 14,330,651 California residents followed for a median 3.9 years, an insomnia diagnosis predicted a 36% increased risk of new AF (HR 1.36; 95% CI 1.30-1.42; P <.001). CONCLUSION: Sleep disruption consistently predicted AF before and after adjustment for OSA and other potential confounders across several different populations. Sleep quality itself may be important in the pathogenesis of AF, potentially representing a novel target for prevention.

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.

Sugar-sweetened beverage intake associations with fasting glucose and insulin concentrations are not modified by selected genetic variants in a ChREBP-FGF21 pathway: a meta-analysis. - McKeown, Nicola M; Dashti, Hassan S; Ma, Jiantao; Haslam, Danielle E; Kiefte-de Jong, Jessica C; Smith, Caren E; Tanaka, Toshiko; Graff, Mariaelisa; Lemaitre, Rozenn N; Rybin, Denis; Sonestedt, Emily; Frazier-Wood, Alexis C; et al. (Diabetologia, 2018)
AIMS/HYPOTHESIS: Sugar-sweetened beverages (SSBs) are a major dietary contributor to fructose intake. A molecular pathway involving the carbohydrate responsive element-binding protein (ChREBP) and the metabolic hormone fibroblast growth factor 21 (FGF21) may influence sugar metabolism and, thereby, contribute to fructose-induced metabolic disease. We hypothesise that common variants in 11 genes involved in fructose metabolism and the ChREBP-FGF21 pathway may interact with SSB intake to exacerbate positive associations between higher SSB intake and glycaemic traits. METHODS: Data from 11 cohorts (six discovery and five replication) in the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided association and interaction results from 34,748 adults of European descent. SSB intake (soft drinks, fruit punches, lemonades or other fruit drinks) was derived from food-frequency questionnaires and food diaries. In fixed-effects meta-analyses, we quantified: (1) the associations between SSBs and glycaemic traits (fasting glucose and fasting insulin); and (2) the interactions between SSBs and 18 independent SNPs related to the ChREBP-FGF21 pathway. RESULTS: In our combined meta-analyses of discovery and replication cohorts, after adjustment for age, sex, energy intake, BMI and other dietary covariates, each additional serving of SSB intake was associated with higher fasting glucose (β ± SE 0.014 ± 0.004 [mmol/l], p = 1.5 × 10-3) and higher fasting insulin (0.030 ± 0.005 [log e pmol/l], p = 2.0 × 10-10). No significant interactions on glycaemic traits were observed between SSB intake and selected SNPs. While a suggestive interaction was observed in the discovery cohorts with a SNP (rs1542423) in the β-Klotho (KLB) locus on fasting insulin (0.030 ± 0.011 log e pmol/l, uncorrected p = 0.006), results in the replication cohorts and combined meta-analyses were non-significant. CONCLUSIONS/INTERPRETATION: In this large meta-analysis, we observed that SSB intake was associated with higher fasting glucose and insulin. Although a suggestive interaction with a genetic variant in the ChREBP-FGF21 pathway was observed in the discovery cohorts, this observation was not confirmed in the replication analysis. TRIAL REGISTRATION: Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005121 (Framingham Offspring Study), NCT00005487 (Multi-Ethnic Study of Atherosclerosis) and NCT00005152 (Nurses' Health Study).

Temporal Trends in the Incidence of and Mortality Associated With Heart Failure With Preserved and Reduced Ejection Fraction. - Tsao, Connie W; Lyass, Asya; Enserro, Danielle; Larson, Martin G; Ho, Jennifer E; Kizer, Jorge R; Gottdiener, John S; Psaty, Bruce M; Vasan, Ramachandran S (JACC Heart Fail, 2018)
OBJECTIVES: This study aimed to determine temporal trends in the incidence of and mortality associated with heart failure (HF) and its subtypes (heart failure with reduced ejection fraction [HFrEF] and heart rate with preserved ejection fraction [HFpEF]) in the community. BACKGROUND: Major shifts in cardiovascular disease risk factor prevalence and advances in therapies may have influenced HF incidence and mortality. METHODS: In the FHS (Framingham Heart Study) and CHS (Cardiovascular Health Study), for participants who were ≥60 years of age and free of HF (n = 15,217; 60% women; 2,524 incident HF cases; 115,703 person-years of follow-up), we estimated adjusted incidence rate ratios of HF, HFrEF, and HFpEF from 1990 to 1999 and 2000 to 2009. We compared the cumulative incidence of and mortality associated with HFrEF versus HFpEF within and between decades. RESULTS: Across the 2 decades, HF incidence rate ratio was similar (p = 0.13). The incidence rate ratio of HFrEF declined (p = 0.0029), whereas HFpEF increased (p < 0.001). Although HFrEF incidence declined more in men than in women, men had a higher incidence of HFrEF than women in each decade (p < 0.001). The incidence of HFpEF significantly increased over time in both men and women (p < 0.001 and p = 0.02, respectively). During follow-up after HF, 1,701 individuals died (67.4%; HFrEF, n = 557 [33%]; HFpEF, n = 474 [29%]). There were no significant differences in mortality rates (overall, cardiovascular disease, and noncardiovascular disease) across decades within HF subtypes or between HFrEF and HFpEF within decade. CONCLUSIONS: In several U.S. community-based samples from 1990 to 2009, we observed divergent trends of decreasing HFrEF and increasing HFpEF incidence, with stable overall HF incidence and high risk for mortality. Our findings highlight the need to elucidate factors contributing to these observations.

Trajectories of Nonagenarian Health: Gender, Age, and Period Effects. - Odden, Michelle C; Koh, William Jen Hoe; Arnold, Alice M; Rawlings, Andreea M; Psaty, Bruce M; Newman, Anne B (Am J Epidemiol, 2018)
The US population aged 90 years and older is growing rapidly and there are limited data on their health. The Cardiovascular Health Study is a prospective study of black and white adults ≥65 years recruited in two waves (1989-90 and 1992-93) from Medicare eligibility lists in Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. We created a synthetic cohort of the 1,889 participants who had reached age 90 at baseline or during follow-up through July 16th, 2015. Participants entered the cohort at 90 years and we evaluated their changes in health after age 90 (median [IQR] follow-up: 3 [1.3-5] years). Measures of health included cardiovascular events, cognitive function, depressive symptoms, prescription medications, self-rated health, and measures of functional status. The mortality rate was high: 19.0 (95% CI: 17.8, 20.3) per 100 person-years in women and 20.9 (95% CI: 19.2, 22.8) in men. Cognitive function and all measures of functional status declined with age; these changes were similar by gender. When we isolated period effects, we found that medications use increased over time. These estimates can help inform future research and health care systems to meet the needs of this growing population.

Trans-ethnic Evaluation Identifies Novel Low Frequency Loci Associated with 25-Hydroxyvitamin D Concentrations. - Hong, Jaeyoung; Hatchell, Kathryn E; Bradfield, Jonathan P; Andrew, Bjonnes; Alessandra, Chesi; Chao-Qiang, Lai; Langefeld, Carl D; Lu, Lingyi; Lu, Yingchang; Lutsey, Pamela L; Musani, Solomon K; Nalls, Mike A; et al. (J Clin Endocrinol Metab, 2018)
Context: Vitamin D inadequacy is common in the adult population of the United States. While the genetic determinants underlying vitamin D inadequacy have been studied in people of European ancestry, less is known in Hispanic or African ancestry populations. Objective: The TRANSCEN-D (TRANS-ethniC Evaluation of vitamiN D GWAS) consortium was assembled to replicate genetic associations with 25-hydroxyvitamin D (25(OH)D) concentrations from the meta-analyses of European ancestry (SUNLIGHT) and to identify novel genetic variants related to vitamin D concentrations in African and Hispanic ancestries. Design: Ancestry-specific (Hispanic and African) and trans-ethnic (Hispanic, African and European) meta-analyses were performed using the METAL software. Patients or Other Participants: In total, 8,541 African-American and 3,485 Hispanic-American (from North America) participants from twelve cohorts, and 16,124 European participants from SUNLIGHT were included in the study. Main Outcome Measure(s): Blood concentrations of 25(OH)D were measured for all participants. Results: Ancestry-specific analyses in African and Hispanic Americans replicated SNPs in GC (2 and 4 SNPs, respectively). A potentially novel SNP (rs79666294) near the KIF4B gene was identified in the African-American cohort. Trans-ethnic evaluation replicated GC and DHCR7 region SNPs. Additionally, the trans-ethnic analyses revealed novel SNPs rs719700 and rs1410656 near the ANO6/ARID2 and HTR2A genes, respectively. Conclusions: Ancestry-specific and trans-ethnic GWAS of 25(OH)D confirmed findings in GC and DHCR7 for African and Hispanic American samples and revealed novel findings near KIF4B, ANO6/ARID2, and HTR2A. The biological mechanisms that link these regions with 25(OH)D metabolism require further investigation.

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2018)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.

Assessment of the Relationship Between Genetic Determinants of Thyroid Function and Atrial Fibrillation: A Mendelian Randomization Study. - Ellervik, Christina; Roselli, Carolina; Christophersen, Ingrid E; Alonso, Alvaro; Pietzner, Maik; Sitlani, Collen M; Trompet, Stella; Arking, Dan E; Geelhoed, Bastiaan; Guo, Xiuqing; Kleber, Marcus E; Lin, Henry J; et al. (JAMA Cardiol, 2019)
Importance: Increased free thyroxine (FT4) and decreased thyrotropin are associated with increased risk of atrial fibrillation (AF) in observational studies, but direct involvement is unclear. Objective: To evaluate the potential direct involvement of thyroid traits on AF. Design, Setting, and Participants: Study-level mendelian randomization (MR) included 11 studies, and summary-level MR included 55 114 AF cases and 482 295 referents, all of European ancestry. Exposures: Genomewide significant variants were used as instruments for standardized FT4 and thyrotropin levels within the reference range, standardized triiodothyronine (FT3):FT4 ratio, hypothyroidism, standardized thyroid peroxidase antibody levels, and hyperthyroidism. Mendelian randomization used genetic risk scores in study-level analysis or individual single-nucleotide polymorphisms in 2-sample MR for the summary-level data. Main Outcomes and Measures: Prevalent and incident AF. Results: The study-level analysis included 7679 individuals with AF and 49 233 referents (mean age [standard error], 62 [3] years; 15 859 men [29.7%]). In study-level random-effects meta-analysis, the pooled hazard ratio of FT4 levels (nanograms per deciliter) for incident AF was 1.55 (95% CI, 1.09-2.20; P = .02; I2 = 76%) and the pooled odds ratio (OR) for prevalent AF was 2.80 (95% CI, 1.41-5.54; P = .003; I2 = 64%) in multivariable-adjusted analyses. The FT4 genetic risk score was associated with an increase in FT4 by 0.082 SD (standard error, 0.007; P < .001) but not with incident AF (risk ratio, 0.84; 95% CI, 0.62-1.14; P = .27) or prevalent AF (OR, 1.32; 95% CI, 0.64-2.73; P = .46). Similarly, in summary-level inverse-variance weighted random-effects MR, gene-based FT4 within the reference range was not associated with AF (OR, 1.01; 95% CI, 0.89-1.14; P = .88). However, gene-based increased FT3:FT4 ratio, increased thyrotropin within the reference range, and hypothyroidism were associated with AF with inverse-variance weighted random-effects OR of 1.33 (95% CI, 1.08-1.63; P = .006), 0.88 (95% CI, 0.84-0.92; P < .001), and 0.94 (95% CI, 0.90-0.99; P = .009), respectively, and robust to tests of horizontal pleiotropy. However, the subset of hypothyroidism single-nucleotide polymorphisms involved in autoimmunity and thyroid peroxidase antibodies levels were not associated with AF. Gene-based hyperthyroidism was associated with AF with MR-Egger OR of 1.31 (95% CI, 1.05-1.63; P = .02) with evidence of horizontal pleiotropy (P = .045). Conclusions and Relevance: Genetically increased FT3:FT4 ratio and hyperthyroidism, but not FT4 within the reference range, were associated with increased AF, and increased thyrotropin within the reference range and hypothyroidism were associated with decreased AF, supporting a pathway involving the pituitary-thyroid-cardiac axis.

Association of variants in HTRA1 and NOTCH3 with MRI-defined extremes of cerebral small vessel disease in older subjects. - Mishra, Aniket; Chauhan, Ganesh; Violleau, Marie-Helene; Vojinovic, Dina; Jian, Xueqiu; Bis, Joshua C; Li, Shuo; Saba, Yasaman; Grenier-Boley, Benjamin; Yang, Qiong; Bartz, Traci M; Hofer, Edith; et al. (Brain, 2019)
We report a composite extreme phenotype design using distribution of white matter hyperintensities and brain infarcts in a population-based cohort of older persons for gene-mapping of cerebral small vessel disease. We demonstrate its application in the 3C-Dijon whole exome sequencing (WES) study (n = 1924, nWESextremes = 512), with both single variant and gene-based association tests. We used other population-based cohort studies participating in the CHARGE consortium for replication, using whole exome sequencing (nWES = 2,868, nWESextremes = 956) and genome-wide genotypes (nGW = 9924, nGWextremes = 3308). We restricted our study to candidate genes known to harbour mutations for Mendelian small vessel disease: NOTCH3, HTRA1, COL4A1, COL4A2 and TREX1. We identified significant associations of a common intronic variant in HTRA1, rs2293871 using single variant association testing (Pdiscovery = 8.21 × 10-5, Preplication = 5.25 × 10-3, Pcombined = 4.72 × 10-5) and of NOTCH3 using gene-based tests (Pdiscovery = 1.61 × 10-2, Preplication = 3.99 × 10-2, Pcombined = 5.31 × 10-3). Follow-up analysis identified significant association of rs2293871 with small vessel ischaemic stroke, and two blood expression quantitative trait loci of HTRA1 in linkage disequilibrium. Additionally, we identified two participants in the 3C-Dijon cohort (0.4%) carrying heterozygote genotypes at known pathogenic variants for familial small vessel disease within NOTCH3 and HTRA1. In conclusion, our proof-of-concept study provides strong evidence that using a novel composite MRI-derived phenotype for extremes of small vessel disease can facilitate the identification of genetic variants underlying small vessel disease, both common variants and those with rare and low frequency. The findings demonstrate shared mechanisms and a continuum between genes underlying Mendelian small vessel disease and those contributing to the common, multifactorial form of the disease.

Associations of autozygosity with a broad range of human phenotypes. - Clark, David W; Okada, Yukinori; Moore, Kristjan H S; Mason, Dan; Pirastu, Nicola; Gandin, Ilaria; Mattsson, Hannele; Barnes, Catriona L K; Lin, Kuang; Zhao, Jing Hua; Deelen, Patrick; Rohde, Rebecca; et al. (Nat Commun, 2019)
In many species, the offspring of related parents suffer reduced reproductive success, a phenomenon known as inbreeding depression. In humans, the importance of this effect has remained unclear, partly because reproduction between close relatives is both rare and frequently associated with confounding social factors. Here, using genomic inbreeding coefficients (F) for >1.4 million individuals, we show that F is significantly associated (p < 0.0005) with apparently deleterious changes in 32 out of 100 traits analysed. These changes are associated with runs of homozygosity (ROH), but not with common variant homozygosity, suggesting that genetic variants associated with inbreeding depression are predominantly rare. The effect on fertility is striking: F equivalent to the offspring of first cousins is associated with a 55% decrease [95% CI 44-66%] in the odds of having children. Finally, the effects of F are confirmed within full-sibling pairs, where the variation in F is independent of all environmental confounding.

Biomarkers of Dietary Omega-6 Fatty Acids and Incident Cardiovascular Disease and Mortality. - Marklund, Matti; Wu, Jason H Y; Imamura, Fumiaki; Del Gobbo, Liana C; Fretts, Amanda; de Goede, Janette; Shi, Peilin; Tintle, Nathan; Wennberg, Maria; Aslibekyan, Stella; Chen, Tzu-An; de Oliveira Otto, Marcia C; et al. (Circulation, 2019)
BACKGROUND: Global dietary recommendations for and cardiovascular effects of linoleic acid, the major dietary omega-6 fatty acid, and its major metabolite, arachidonic acid, remain controversial. To address this uncertainty and inform international recommendations, we evaluated how in vivo circulating and tissue levels of linoleic acid (LA) and arachidonic acid (AA) relate to incident cardiovascular disease (CVD) across multiple international studies. METHODS: We performed harmonized, de novo, individual-level analyses in a global consortium of 30 prospective observational studies from 13 countries. Multivariable-adjusted associations of circulating and adipose tissue LA and AA biomarkers with incident total CVD and subtypes (coronary heart disease, ischemic stroke, cardiovascular mortality) were investigated according to a prespecified analytic plan. Levels of LA and AA, measured as the percentage of total fatty acids, were evaluated linearly according to their interquintile range (ie, the range between the midpoint of the first and fifth quintiles), and categorically by quintiles. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Heterogeneity was explored by age, sex, race, diabetes mellitus, statin use, aspirin use, omega-3 levels, and fatty acid desaturase 1 genotype (when available). RESULTS: In 30 prospective studies with medians of follow-up ranging 2.5 to 31.9 years, 15 198 incident cardiovascular events occurred among 68 659 participants. Higher levels of LA were significantly associated with lower risks of total CVD, cardiovascular mortality, and ischemic stroke, with hazard ratios per interquintile range of 0.93 (95% CI, 0.88-0.99), 0.78 (0.70-0.85), and 0.88 (0.79-0.98), respectively, and nonsignificantly with lower coronary heart disease risk (0.94; 0.88-1.00). Relationships were similar for LA evaluated across quintiles. AA levels were not associated with higher risk of cardiovascular outcomes; in a comparison of extreme quintiles, higher levels were associated with lower risk of total CVD (0.92; 0.86-0.99). No consistent heterogeneity by population subgroups was identified in the observed relationships. CONCLUSIONS: In pooled global analyses, higher in vivo circulating and tissue levels of LA and possibly AA were associated with lower risk of major cardiovascular events. These results support a favorable role for LA in CVD prevention.

Blood Leukocyte DNA Methylation Predicts Risk of Future Myocardial Infarction and Coronary Heart Disease. - Agha, Golareh; Mendelson, Michael M; Ward-Caviness, Cavin K; Joehanes, Roby; Huan, Tianxiao; Gondalia, Rahul; Salfati, Elias; Brody, Jennifer A; Fiorito, Giovanni; Bressler, Jan; Chen, Brian H; Ligthart, Symen; et al. (Circulation, 2019)
BACKGROUND: DNA methylation is implicated in coronary heart disease (CHD), but current evidence is based on small, cross-sectional studies. We examined blood DNA methylation in relation to incident CHD across multiple prospective cohorts. METHODS: Nine population-based cohorts from the United States and Europe profiled epigenome-wide blood leukocyte DNA methylation using the Illumina Infinium 450k microarray, and prospectively ascertained CHD events including coronary insufficiency/unstable angina, recognized myocardial infarction, coronary revascularization, and coronary death. Cohorts conducted race-specific analyses adjusted for age, sex, smoking, education, body mass index, blood cell type proportions, and technical variables. We conducted fixed-effect meta-analyses across cohorts. RESULTS: Among 11 461 individuals (mean age 64 years, 67% women, 35% African American) free of CHD at baseline, 1895 developed CHD during a mean follow-up of 11.2 years. Methylation levels at 52 CpG (cytosine-phosphate-guanine) sites were associated with incident CHD or myocardial infarction (false discovery rate<0.05). These CpGs map to genes with key roles in calcium regulation (ATP2B2, CASR, GUCA1B, HPCAL1), and genes identified in genome- and epigenome-wide studies of serum calcium (CASR), serum calcium-related risk of CHD (CASR), coronary artery calcified plaque (PTPRN2), and kidney function (CDH23, HPCAL1), among others. Mendelian randomization analyses supported a causal effect of DNA methylation on incident CHD; these CpGs map to active regulatory regions proximal to long non-coding RNA transcripts. CONCLUSION: Methylation of blood-derived DNA is associated with risk of future CHD across diverse populations and may serve as an informative tool for gaining further insight on the development of CHD.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; CpG Islands; DNA Methylation; Europe; Female; Genome-Wide Association Study; Humans; Incidence; Leukocytes; Male; Middle Aged; Myocardial Infarction; Population Groups; Prognosis; Prospective Studies; Risk; United States

A catalog of genetic loci associated with kidney function from analyses of a million individuals. - Wuttke, Matthias; Li, Yong; Li, Man; Sieber, Karsten B; Feitosa, Mary F; Gorski, Mathias; Tin, Adrienne; Wang, Lihua; Chu, Audrey Y; Hoppmann, Anselm; Kirsten, Holger; Giri, Ayush; et al. (Nat Genet, 2019)
Chronic kidney disease (CKD) is responsible for a public health burden with multi-systemic complications. Through trans-ancestry meta-analysis of genome-wide association studies of estimated glomerular filtration rate (eGFR) and independent replication (n = 1,046,070), we identified 264 associated loci (166 new). Of these, 147 were likely to be relevant for kidney function on the basis of associations with the alternative kidney function marker blood urea nitrogen (n = 416,178). Pathway and enrichment analyses, including mouse models with renal phenotypes, support the kidney as the main target organ. A genetic risk score for lower eGFR was associated with clinically diagnosed CKD in 452,264 independent individuals. Colocalization analyses of associations with eGFR among 783,978 European-ancestry individuals and gene expression across 46 human tissues, including tubulo-interstitial and glomerular kidney compartments, identified 17 genes differentially expressed in kidney. Fine-mapping highlighted missense driver variants in 11 genes and kidney-specific regulatory variants. These results provide a comprehensive priority list of molecular targets for translational research.
Keywords: Chromosome Mapping; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inheritance Patterns; Kidney Function Tests; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Renal Insufficiency, Chronic; Uromodulin

Common Genetic Variation in Relation to Brachial Vascular Dimensions and Flow-Mediated Vasodilation. - Dörr, Marcus; Hamburg, Naomi M; Müller, Christian; Smith, Nicholas L; Gustafsson, Stefan; Lehtimäki, Terho; Teumer, Alexander; Zeller, Tanja; Li, Xiaohui; Lind, Lars; Raitakari, Olli T; Völker, Uwe; et al. (Circ Genom Precis Med, 2019)

Disentangling the genetics of lean mass. - Karasik, David; Zillikens, M Carola; Hsu, Yi-Hsiang; Aghdassi, Ali; Åkesson, Kristina; Amin, Najaf; Barroso, Inês; Bennett, David A; Bertram, Lars; Bochud, Murielle; Borecki, Ingrid B; Broer, Linda; et al. (Am J Clin Nutr, 2019)
Background: Lean body mass (LM) plays an important role in mobility and metabolic function. We previously identified five loci associated with LM adjusted for fat mass in kilograms. Such an adjustment may reduce the power to identify genetic signals having an association with both lean mass and fat mass. Objectives: To determine the impact of different fat mass adjustments on genetic architecture of LM and identify additional LM loci. Methods: We performed genome-wide association analyses for whole-body LM (20 cohorts of European ancestry with n = 38,292) measured using dual-energy X-ray absorptiometry) or bioelectrical impedance analysis, adjusted for sex, age, age2, and height with or without fat mass adjustments (Model 1 no fat adjustment; Model 2 adjustment for fat mass as a percentage of body mass; Model 3 adjustment for fat mass in kilograms). Results: Seven single-nucleotide polymorphisms (SNPs) in separate loci, including one novel LM locus (TNRC6B), were successfully replicated in an additional 47,227 individuals from 29 cohorts. Based on the strengths of the associations in Model 1 vs Model 3, we divided the LM loci into those with an effect on both lean mass and fat mass in the same direction and refer to those as "sumo wrestler" loci (FTO and MC4R). In contrast, loci with an impact specifically on LM were termed "body builder" loci (VCAN and ADAMTSL3). Using existing available genome-wide association study databases, LM increasing alleles of SNPs in sumo wrestler loci were associated with an adverse metabolic profile, whereas LM increasing alleles of SNPs in "body builder" loci were associated with metabolic protection. Conclusions: In conclusion, we identified one novel LM locus (TNRC6B). Our results suggest that a genetically determined increase in lean mass might exert either harmful or protective effects on metabolic traits, depending on its relation to fat mass.

Genetic architecture of subcortical brain structures in 38,851 individuals. - Satizabal, Claudia L; Adams, Hieab H H; Hibar, Derrek P; White, Charles C; Knol, Maria J; Stein, Jason L; Scholz, Markus; Sargurupremraj, Muralidharan; Jahanshad, Neda; Roshchupkin, Gennady V; Smith, Albert V; Bis, Joshua C; et al. (Nat Genet, 2019)
Subcortical brain structures are integral to motion, consciousness, emotions and learning. We identified common genetic variation related to the volumes of the nucleus accumbens, amygdala, brainstem, caudate nucleus, globus pallidus, putamen and thalamus, using genome-wide association analyses in almost 40,000 individuals from CHARGE, ENIGMA and UK Biobank. We show that variability in subcortical volumes is heritable, and identify 48 significantly associated loci (40 novel at the time of analysis). Annotation of these loci by utilizing gene expression, methylation and neuropathological data identified 199 genes putatively implicated in neurodevelopment, synaptic signaling, axonal transport, apoptosis, inflammation/infection and susceptibility to neurological disorders. This set of genes is significantly enriched for Drosophila orthologs associated with neurodevelopmental phenotypes, suggesting evolutionarily conserved mechanisms. Our findings uncover novel biology and potential drug targets underlying brain development and disease.

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.

A genome-wide association study identifies new loci for factor VII and implicates factor VII in ischemic stroke etiology. - de Vries, Paul S; Sabater-Lleal, Maria; Huffman, Jennifer E; Marten, Jonathan; Song, Ci; Pankratz, Nathan; Bartz, Traci M; de Haan, Hugoline G; Delgado, Graciela E; Eicher, John D; Martinez-Perez, Angel; Ward-Caviness, Cavin K; et al. (Blood, 2019)
Factor VII (FVII) is an important component of the coagulation cascade. Few genetic loci regulating FVII activity and/or levels have been discovered to date. We conducted a meta-analysis of 9 genome-wide association studies of plasma FVII levels (7 FVII activity and 2 FVII antigen) among 27 495 participants of European and African ancestry. Each study performed ancestry-specific association analyses. Inverse variance weighted meta-analysis was performed within each ancestry group and then combined for a -ancestry meta-analysis. Our primary analysis included the 7 studies that measured FVII activity, and a secondary analysis included all 9 studies. We provided functional genomic validation for newly identified significant loci by silencing candidate genes in a human liver cell line (HuH7) using small-interfering RNA and then measuring messenger RNA and FVII protein expression. Lastly, we used meta-analysis results to perform Mendelian randomization analysis to estimate the causal effect of FVII activity on coronary artery disease, ischemic stroke (IS), and venous thromboembolism. We identified 2 novel ( and ) and 6 known loci associated with FVII activity, explaining 19.0% of the phenotypic variance. Adding FVII antigen data to the meta-analysis did not result in the discovery of further loci. Silencing in HuH7 cells upregulated FVII, whereas silencing downregulated FVII. Mendelian randomization analyses suggest that FVII activity has a positive causal effect on the risk of IS. Variants at and contribute to FVII activity by regulating expression levels. FVII activity appears to contribute to the etiology of IS in the general population.

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People

Genome-wide association study of breakfast skipping links clock regulation with food timing. - Dashti, Hassan S; Merino, Jordi; Lane, Jacqueline M; Song, Yanwei; Smith, Caren E; Tanaka, Toshiko; McKeown, Nicola M; Tucker, Chandler; Sun, Dianjianyi; Bartz, Traci M; Li-Gao, Ruifang; Nisa, Hoirun; et al. (Am J Clin Nutr, 2019)
BACKGROUND: Little is known about the contribution of genetic variation to food timing, and breakfast has been determined to exhibit the most heritable meal timing. As breakfast timing and skipping are not routinely measured in large cohort studies, alternative approaches include analyses of correlated traits. OBJECTIVES: The aim of this study was to elucidate breakfast skipping genetic variants through a proxy-phenotype genome-wide association study (GWAS) for breakfast cereal skipping, a commonly assessed correlated trait. METHODS: We leveraged the statistical power of the UK Biobank (n = 193,860) to identify genetic variants related to breakfast cereal skipping as a proxy-phenotype for breakfast skipping and applied several in silico approaches to investigate mechanistic functions and links to traits/diseases. Next, we attempted validation of our approach in smaller breakfast skipping GWAS from the TwinUK (n = 2,006) and the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium (n = 11,963). RESULTS: In the UK Biobank, we identified 6 independent GWAS variants, including those implicated for caffeine (ARID3B/CYP1A1), carbohydrate metabolism (FGF21), schizophrenia (ZNF804A), and encoding enzymes important for N6-methyladenosine RNA transmethylation (METTL4, YWHAB, and YTHDF3), which regulates the pace of the circadian clock. Expression of identified genes was enriched in the cerebellum. Genome-wide correlation analyses indicated positive correlations with anthropometric traits. Through Mendelian randomization (MR), we observed causal links between genetically determined breakfast skipping and higher body mass index, more depressive symptoms, and smoking. In bidirectional MR, we demonstrated a causal link between being an evening person and skipping breakfast, but not vice versa. We observed association of our signals in an independent breakfast skipping GWAS in another British cohort (P = 0.032), TwinUK, but not in a meta-analysis of non-British cohorts from the CHARGE consortium (P = 0.095). CONCLUSIONS: Our proxy-phenotype GWAS identified 6 genetic variants for breakfast skipping, linking clock regulation with food timing and suggesting a possible beneficial role of regular breakfast intake as part of a healthy lifestyle.

Genomewide Association Study of Statin-Induced Myopathy in Patients Recruited Using the UK Clinical Practice Research Datalink. - Carr, Daniel F; Francis, Ben; Jorgensen, Andrea L; Zhang, Eunice; Chinoy, Hector; Heckbert, Susan R; Bis, Joshua C; Brody, Jennifer A; Floyd, James S; Psaty, Bruce M; Molokhia, Mariam; Lapeyre-Mestre, Maryse; et al. (Clin Pharmacol Ther, 2019)
Statins can be associated with myopathy. We have undertaken a genomewide association study (GWAS) to discover and validate genetic risk factors for statin-induced myopathy in a "real-world" setting. One hundred thirty-five patients with statin myopathy recruited via the UK Clinical Practice Research Datalink were genotyped using the Illumina OmniExpress Exome version 1.0 Bead Chip and compared with the Wellcome Trust Case-Control Consortium (n = 2,501). Nominally statistically significant single nucleotide polymorphism (SNP) signals in the GWAS (P < 5 × 10 ) were further evaluated in several independent cohorts (comprising 332 cases and 449 drug-tolerant controls). Only one (rs4149056/c.521C>T in the SLCO1B1 gene) SNP was genomewide significant in the severe myopathy (creatine kinase > 10 × upper limit of normal or rhabdomyolysis) group (P = 2.55 × 10 ; odds ratio 5.15; 95% confidence interval 3.13-8.45). The association with SLCO1B1 was present for several statins and replicated in the independent validation cohorts. The data highlight the role of SLCO1B1 c.521C>T SNP as a replicable genetic risk factor for statin myopathy. No other novel genetic risk factors with a similar effect size were identified.
Keywords: Adverse Drug Reaction Reporting Systems; Case-Control Studies; Databases, Factual; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Liver-Specific Organic Anion Transporter 1; Muscular Diseases; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Severity of Illness Index; United Kingdom

Genome-wide meta-analysis of SNP and antihypertensive medication interactions on left ventricular traits in African Americans. - Do, Anh N; Zhao, Wei; Baldridge, Abigail S; Raffield, Laura M; Wiggins, Kerri L; Shah, Sanjiv J; Aslibekyan, Stella; Tiwari, Hemant K; Limdi, Nita; Zhi, Degui; Sitlani, Colleen M; Taylor, Kent D; et al. (Mol Genet Genomic Med, 2019)
BACKGROUND: Left ventricular (LV) hypertrophy affects up to 43% of African Americans (AAs). Antihypertensive treatment reduces LV mass (LVM). However, interindividual variation in LV traits in response to antihypertensive treatments exists. We hypothesized that genetic variants may modify the association of antihypertensive treatment class with LV traits measured by echocardiography. METHODS: We evaluated the main effects of the three most common antihypertensive treatments for AAs as well as the single nucleotide polymorphism (SNP)-by-drug interaction on LVM and relative wall thickness (RWT) in 2,068 participants across five community-based cohorts. Treatments included thiazide diuretics (TDs), angiotensin converting enzyme inhibitors (ACE-Is), and dihydropyridine calcium channel blockers (dCCBs) and were compared in a pairwise manner. We performed fixed effects inverse variance weighted meta-analyses of main effects of drugs and 2.5 million SNP-by-drug interaction estimates. RESULTS: We observed that dCCBs versus TDs were associated with higher LVM after adjusting for covariates (p = 0.001). We report three SNPs at a single locus on chromosome 20 that modified the association between RWT and treatment when comparing dCCBs to ACE-Is with consistent effects across cohorts (smallest p = 4.7 × 10 , minor allele frequency range 0.09-0.12). This locus has been linked to LV hypertrophy in a previous study. A marginally significant locus in BICD1 (rs326641) was validated in an external population. CONCLUSIONS: Our study identified one locus having genome-wide significant SNP-by-drug interaction effect on RWT among dCCB users in comparison to ACE-I users. Upon additional validation in future studies, our findings can enhance the precision of medical approaches in hypertension treatment.
Keywords: African Americans; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Humans; Observational Studies as Topic; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Sodium Chloride Symporter Inhibitors; Ventricular Dysfunction, Left

Genomic and transcriptomic association studies identify 16 novel susceptibility loci for venous thromboembolism. - Lindström, Sara; Wang, Lu; Smith, Erin N; Gordon, William; van Hylckama Vlieg, Astrid; de Andrade, Mariza; Brody, Jennifer A; Pattee, Jack W; Haessler, Jeffrey; Brumpton, Ben M; Chasman, Daniel I; Suchon, Pierre; et al. (Blood, 2019)
Venous thromboembolism (VTE) is a significant contributor to morbidity and mortality. To advance our understanding of the biology contributing to VTE, we conducted a genome-wide association study (GWAS) of VTE and a transcriptome-wide association study (TWAS) based on imputed gene expression from whole blood and liver. We meta-analyzed GWAS data from 18 studies for 30 234 VTE cases and 172 122 controls and assessed the association between 12 923 718 genetic variants and VTE. We generated variant prediction scores of gene expression from whole blood and liver tissue and assessed them for association with VTE. Mendelian randomization analyses were conducted for traits genetically associated with novel VTE loci. We identified 34 independent genetic signals for VTE risk from GWAS meta-analysis, of which 14 are newly reported associations. This included 11 newly associated genetic loci (C1orf198, PLEK, OSMR-AS1, NUGGC/SCARA5, GRK5, MPHOSPH9, ARID4A, PLCG2, SMG6, EIF5A, and STX10) of which 6 replicated, and 3 new independent signals in 3 known genes. Further, TWAS identified 5 additional genetic loci with imputed gene expression levels differing between cases and controls in whole blood (SH2B3, SPSB1, RP11-747H7.3, RP4-737E23.2) and in liver (ERAP1). At some GWAS loci, we found suggestive evidence that the VTE association signal for novel and previously known regions colocalized with expression quantitative trait locus signals. Mendelian randomization analyses suggested that blood traits may contribute to the underlying risk of VTE. To conclude, we identified 16 novel susceptibility loci for VTE; for some loci, the association signals are likely mediated through gene expression of nearby genes.

Heterogeneous Exposure Associations in Observational Cohort Studies: The Example of Blood Pressure in Older Adults. - Odden, Michelle C; Rawlings, Andreea M; Khodadadi, Abtin; Fern, Xiaoli; Shlipak, Michael G; Bibbins-Domingo, Kirsten; Covinsky, Kenneth; Kanaya, Alka M; Lee, Anne; Haan, Mary N; Newman, Anne B; Psaty, Bruce M; et al. (Am J Epidemiol, 2019)
Heterogeneous exposure associations (HEAs) can be defined as differences in the association of a exposure with an outcome among subgroups that differ by a set of characteristics. This manuscript intends to foster discussion of HEAs in the epidemiological literature, and present a variant of the random forest algorithm that can be used to identify HEAs. We demonstrate the use of this algorithm in the setting of the association of systolic blood pressure and death in older adults. The training set included pooled data from the baseline examination of the Cardiovascular Health Study (1989-1993), the Health, Aging, and Body Composition study (1997-1998), and the Sacramento Area Latino Study on Aging (1998-1999). The test set included data from the National Health and Nutrition Examination Survey (1999-2002). The hazard ratios ranged from 1.25 (95% CI: 1.13, 1.37) per 10 mmHg higher systolic blood pressure in men aged ≤67 years with diastolic blood pressure >80 mmHg, to 1.00 (0.96, 1.03) in women with creatinine <0.7 mg/dL and a history of hypertension. HEAs have the potential to improve our understanding of disease mechanisms in diverse populations, and guide the design of randomized controlled trials to control exposures in heterogeneous populations.

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program. - Sarnowski, Chloe; Leong, Aaron; Raffield, Laura M; Wu, Peitao; de Vries, Paul S; DiCorpo, Daniel; Guo, Xiuqing; Xu, Huichun; Liu, Yongmei; Zheng, Xiuwen; Hu, Yao; Brody, Jennifer A; et al. (Am J Hum Genet, 2019)
Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GCK in Europeans and African-Americans, HK1 in Europeans and Hispanics, FN3K and/or FN3KRP in Europeans, and G6PD in African-Americans and Hispanics) and we identified an African-ancestry-specific low-frequency variant (rs1039215 in HBG2 and HBE1, minor allele frequency (MAF) = 0.03). The most associated G6PD variant (rs1050828-T, p.Val98Met, MAF = 12% in African-Americans, MAF = 2% in Hispanics) lowered HbA1c (-0.88% in hemizygous males, -0.34% in heterozygous females) and explained 23% of HbA1c variance in African-Americans and 4% in Hispanics. Additionally, we identified a rare distinct G6PD coding variant (rs76723693, p.Leu353Pro, MAF = 0.5%; -0.98% in hemizygous males, -0.46% in heterozygous females) and detected significant association with HbA1c when aggregating rare missense variants in G6PD. We observed similar magnitude and direction of effects for rs1039215 (HBG2) and rs76723693 (G6PD) in the two largest TOPMed African American cohorts, and we replicated the rs76723693 association in the UK Biobank African-ancestry participants. These variants in G6PD and HBG2 were monomorphic in the European and Asian samples. African or Hispanic ancestry individuals carrying G6PD variants may be underdiagnosed for diabetes when screened with HbA1c. Thus, assessment of these variants should be considered for incorporation into precision medicine approaches for diabetes diagnosis.

A large-scale exome array analysis of venous thromboembolism. - Lindström, Sara; Brody, Jennifer A; Turman, Constance; Germain, Marine; Bartz, Traci M; Smith, Erin N; Chen, Ming-Huei; Puurunen, Marja; Chasman, Daniel; Hassler, Jeffrey; Pankratz, Nathan; Basu, Saonli; et al. (Genet Epidemiol, 2019)
Although recent Genome-Wide Association Studies have identified novel associations for common variants, there has been no comprehensive exome-wide search for low-frequency variants that affect the risk of venous thromboembolism (VTE). We conducted a meta-analysis of 11 studies comprising 8,332 cases and 16,087 controls of European ancestry and 382 cases and 1,476 controls of African American ancestry genotyped with the Illumina HumanExome BeadChip. We used the seqMeta package in R to conduct single variant and gene-based rare variant tests. In the single variant analysis, we limited our analysis to the 64,794 variants with at least 40 minor alleles across studies (minor allele frequency [MAF] ~0.08%). We confirmed associations with previously identified VTE loci, including ABO, F5, F11, and FGA. After adjusting for multiple testing, we observed no novel significant findings in single variant or gene-based analysis. Given our sample size, we had greater than 80% power to detect minimum odds ratios greater than 1.5 and 1.8 for a single variant with MAF of 0.01 and 0.005, respectively. Larger studies and sequence data may be needed to identify novel low-frequency and rare variants associated with VTE risk.

Mendelian randomization evaluation of causal effects of fibrinogen on incident coronary heart disease. - Ward-Caviness, Cavin K; de Vries, Paul S; Wiggins, Kerri L; Huffman, Jennifer E; Yanek, Lisa R; Bielak, Lawrence F; Giulianini, Franco; Guo, Xiuqing; Kleber, Marcus E; Kacprowski, Tim; Groß, Stefan; Petersman, Astrid; et al. (PLoS One, 2019)
BACKGROUND: Fibrinogen is an essential hemostatic factor and cardiovascular disease risk factor. Early attempts at evaluating the causal effect of fibrinogen on coronary heart disease (CHD) and myocardial infraction (MI) using Mendelian randomization (MR) used single variant approaches, and did not take advantage of recent genome-wide association studies (GWAS) or multi-variant, pleiotropy robust MR methodologies. METHODS AND FINDINGS: We evaluated evidence for a causal effect of fibrinogen on both CHD and MI using MR. We used both an allele score approach and pleiotropy robust MR models. The allele score was composed of 38 fibrinogen-associated variants from recent GWAS. Initial analyses using the allele score used a meta-analysis of 11 European-ancestry prospective cohorts, free of CHD and MI at baseline, to examine incidence CHD and MI. We also applied 2 sample MR methods with data from a prevalent CHD and MI GWAS. Results are given in terms of the hazard ratio (HR) or odds ratio (OR), depending on the study design, and associated 95% confidence interval (CI). In single variant analyses no causal effect of fibrinogen on CHD or MI was observed. In multi-variant analyses using incidence CHD cases and the allele score approach, the estimated causal effect (HR) of a 1 g/L higher fibrinogen concentration was 1.62 (CI = 1.12, 2.36) when using incident cases and the allele score approach. In 2 sample MR analyses that accounted for pleiotropy, the causal estimate (OR) was reduced to 1.18 (CI = 0.98, 1.42) and 1.09 (CI = 0.89, 1.33) in the 2 most precise (smallest CI) models, out of 4 models evaluated. In the 2 sample MR analyses for MI, there was only very weak evidence of a causal effect in only 1 out of 4 models. CONCLUSIONS: A small causal effect of fibrinogen on CHD is observed using multi-variant MR approaches which account for pleiotropy, but not single variant MR approaches. Taken together, results indicate that even with large sample sizes and multi-variant approaches MR analyses still cannot exclude the null when estimating the causal effect of fibrinogen on CHD, but that any potential causal effect is likely to be much smaller than observed in epidemiological studies.

Multi-Ancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
An individual's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multi-ancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in Stage 1 (genome-wide discovery) and 66 studies in Stage 2 (focused follow-up), for a total of 394,584 individuals from five ancestry groups. Genetic main and interaction effects were jointly assessed by a 2 degrees of freedom (DF) test, and a 1 DF test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in Stage 1 and were evaluated in Stage 2, followed by combined analyses of Stage 1 and Stage 2. In the combined analysis of Stage 1 and Stage 2, 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2 DF tests, of which 18 were novel. No genome-wide significant associations were found testing the interaction effect alone. The novel loci included several genes (PCSK5, VEGFB, and A1CF) with a putative role in lipid metabolism based on existing evidence from cellular and experimental models.

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.

Multi-ancestry sleep-by-SNP interaction analysis in 126,926 individuals reveals lipid loci stratified by sleep duration. - Noordam, Raymond; Bos, Maxime M; Wang, Heming; Winkler, Thomas W; Bentley, Amy R; Kilpeläinen, Tuomas O; de Vries, Paul S; Sung, Yun Ju; Schwander, Karen; Cade, Brian E; Manning, Alisa; Aschard, Hugues; et al. (Nat Commun, 2019)
Both short and long sleep are associated with an adverse lipid profile, likely through different biological pathways. To elucidate the biology of sleep-associated adverse lipid profile, we conduct multi-ancestry genome-wide sleep-SNP interaction analyses on three lipid traits (HDL-c, LDL-c and triglycerides). In the total study sample (discovery + replication) of 126,926 individuals from 5 different ancestry groups, when considering either long or short total sleep time interactions in joint analyses, we identify 49 previously unreported lipid loci, and 10 additional previously unreported lipid loci in a restricted sample of European-ancestry cohorts. In addition, we identify new gene-sleep interactions for known lipid loci such as LPL and PCSK9. The previously unreported lipid loci have a modest explained variance in lipid levels: most notable, gene-short-sleep interactions explain 4.25% of the variance in triglyceride level. Collectively, these findings contribute to our understanding of the biological mechanisms involved in sleep-associated adverse lipid profiles.

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic Americans; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; Young Adult

NT -pro BNP as a Mediator of the Racial Difference in Incident Atrial Fibrillation and Heart Failure. - Whitman, Isaac R; Vittinghoff, Eric; deFilippi, Christopher R; Gottdiener, John S; Alonso, Alvaro; Psaty, Bruce M; Heckbert, Susan R; Hoogeveen, Ron C; Arking, Dan E; Selvin, Elizabeth; Chen, Lin Y; Dewland, Thomas A; et al. (J Am Heart Assoc, 2019)
Background Blacks harbor more cardiovascular risk factors than whites, but experience less atrial fibrillation ( AF ). Conversely, whites may have a lower risk of heart failure ( CHF ). N-terminal pro-B-type natriuretic peptide ( NT -pro BNP) levels are higher in whites, predict incident AF , and have diuretic effects in the setting of increased ventricular diastolic pressures, potentially providing a unifying explanation for these racial differences. Methods and Results We used data from the CHS (Cardiovascular Health Study) to determine the degree to which baseline NT -pro BNP levels mediate the relationships between race and incident AF and CHF by comparing beta estimates between models with and without NT -pro BNP . The ARIC (Atherosclerosis Risk in Communities) study was used to assess reproducibility. Among 4731 CHS (770 black) and 12 418 ARIC (3091 black) participants, there were 1277 and 1253 incident AF events, respectively. Whites had higher baseline NT -pro BNP ( CHS : 40% higher than blacks; 95% CI , 29-53; ARIC : 39% higher; 95% CI , 33-46) and had a greater risk of incident AF compared with blacks ( CHS : adjusted hazard ratio, 1.60; 95% CI , 1.31-1.93; ARIC : hazard ratio, 1.93; 95% CI , 1.57-2.27). NT -pro BNP levels explained a significant proportion of the racial difference in AF risk ( CHS : 36.2%; 95% CI , 23.2-69.2%; ARIC : 24.6%; 95% CI , 14.8-39.6%). Contrary to our hypothesis, given an increased risk of CHF among whites in CHS (adjusted hazard ratio, 1.20; 95% CI , 1.05-1.47) and the absence of a significant association between race and CHF in ARIC (adjusted hazard ratio, 1.07; 95% CI , 0.94-1.23), CHF -related mediation analyses were not performed. Conclusions A substantial portion of the relationship between race and AF was statistically explained by baseline NT -pro BNP levels. No consistent relationship between race and CHF was observed.

Pharmacogenomics of statin-related myopathy: Meta-analysis of rare variants from whole-exome sequencing. - Floyd, James S; Bloch, Katarzyna M; Brody, Jennifer A; Maroteau, Cyrielle; Siddiqui, Moneeza K; Gregory, Richard; Carr, Daniel F; Molokhia, Mariam; Liu, Xiaoming; Bis, Joshua C; Ahmed, Ammar; Liu, Xuan; et al. (PLoS One, 2019)
AIMS: Statin-related myopathy (SRM), which includes rhabdomyolysis, is an uncommon but important adverse drug reaction because the number of people prescribed statins world-wide is large. Previous association studies of common genetic variants have had limited success in identifying a genetic basis for this adverse drug reaction. We conducted a multi-site whole-exome sequencing study to investigate whether rare coding variants confer an increased risk of SRM. METHODS AND RESULTS: SRM 3-5 cases (N = 505) and statin treatment-tolerant controls (N = 2047) were recruited from multiple sites in North America and Europe. SRM 3-5 was defined as symptoms consistent with muscle injury and an elevated creatine phosphokinase level >4 times upper limit of normal without another likely cause of muscle injury. Whole-exome sequencing and variant calling was coordinated from two analysis centres, and results of single-variant and gene-based burden tests were meta-analysed. No genome-wide significant associations were identified. Given the large number of cases, we had 80% power to identify a variant with minor allele frequency of 0.01 that increases the risk of SRM 6-fold at genome-wide significance. CONCLUSIONS: In this large whole-exome sequencing study of severe statin-related muscle injury conducted to date, we did not find evidence that rare coding variants are responsible for this adverse drug reaction. Larger sample sizes would be required to identify rare variants with small effects, but it is unclear whether such findings would be clinically actionable.

Plasma Ceramides and Sphingomyelins in Relation to Heart Failure Risk. - Lemaitre, Rozenn N; Jensen, Paul N; Hoofnagle, Andrew; McKnight, Barbara; Fretts, Amanda M; King, Irena B; Siscovick, David S; Psaty, Bruce M; Heckbert, Susan R; Mozaffarian, Dariush; Sotoodehnia, Nona (Circ Heart Fail, 2019)
BACKGROUND: Ceramides exhibit multiple biological activities that may influence the pathophysiology of heart failure. These activities may be influenced by the saturated fatty acid carried by the ceramide (Cer). However, the associations of different circulating Cer species, and their sphingomyelin (SM) precursors, with heart failure have received limited attention. METHODS AND RESULTS: We studied the associations of plasma Cer and SM species with incident heart failure in the Cardiovascular Health Study. We examined 8 species: Cer and SM with palmitic acid (Cer-16 and SM-16), species with arachidic acid (Cer-20 and SM-20), species with behenic acid (Cer-22 and SM-22), and species with lignoceric acid (Cer-24 and SM-24). During a median follow-up of 9.4 years, we identified 1179 cases of incident heart failure among 4249 study participants. In Cox regression analyses adjusted for risk factors, higher levels of Cer-16 and SM-16 were associated with higher risk of incident heart failure (hazard ratio for one SD increase:1.25 [95% CI, 1.16-1.36] and 1.28 [1.18-1.40], respectively). In contrast, higher levels of Cer-22 were associated with lower risk of heart failure in multivariable analyses further adjusted for Cer-16 (hazard ratio, 0.85 [0.78-0.92]); and higher levels of SM-20, SM-22 and SM-24 were associated with lower risk of heart failure in analyses further adjusted for SM-16 (hazard ratios, 0.83 [0.77-0.90], 0.81 [0.75-0.88], and 0.83 [0.77-0.90], respectively). No statistically significant interactions with age, sex, black race, body mass index, or baseline coronary heart disease were detected. Similar associations were observed for heart failure with preserved (n=529) or reduced (n=348) ejection fraction. CONCLUSIONS: This study shows associations of higher plasma levels of Cer-16 and SM-16 with increased risk of heart failure and higher levels of Cer-22, SM-20, SM-22, and SM-24 with decreased risk of heart failure. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00005133.

The role of functional status on the relationship between blood pressure and cognitive decline: the Cardiovascular Health Study. - Miller, Lindsay M; Peralta, Carmen A; Fitzpatrick, Annette L; Wu, Chenkai; Psaty, Bruce M; Newman, Anne B; Odden, Michelle C (J Hypertens, 2019)
OBJECTIVE: To examine whether self-reported functional status modified the association between blood pressure (BP) and cognitive decline among older adults. METHODS: The study included 2097 US adults aged 75 years and older from the Cardiovascular Health Study, followed for up to 6 years. Functional status was ascertained by self-reported limitation in activities of daily living (ADL; none vs. any). Cognitive function was assessed by the Modified Mini Mental State Exam (3MSE). We used linear mixed models to examine whether the presence of at least one ADL limitation modified the association between BP and cognitive decline. Potential confounders included demographics, physiologic measures, antihypertensive medication use and apolipoprotein E ε4 allele. We conducted stratified analyses for significant interactions between BP and ADL. RESULTS: The association between BP and change in 3MSE differed by baseline ADL limitation. Among participants without ADL limitation, elevated systolic BP (≥140 mmHg) was associated with a 0.15 decrease (95% CI -0.24 to -0.07); P value for interaction less than 0.001, whereas in those with an ADL limitation, elevated systolic BP was independently associated with a 0.30 increase in 3MSE scores per year (95% CI 0.06-0.55). Elevated diastolic BP (≥80 mmHg) was associated with an increase in cognitive function in both groups, although the increase was greater in those with ADL limitation (0.47 points per year vs. 0.18 points per year, P value for interaction = 0.01). CONCLUSION: Elevated BP appears to be associated with a decrease in cognitive scores among functioning older adults, and modest improvements in cognitive function among poorly functioning elders.

Sequencing Analysis at 8p23 Identifies Multiple Rare Variants in DLC1 Associated with Sleep-Related Oxyhemoglobin Saturation Level. - Liang, Jingjing; Cade, Brian E; He, Karen Y; Wang, Heming; Lee, Jiwon; Sofer, Tamar; Williams, Stephanie; Li, Ruitong; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Hum Genet, 2019)
Average arterial oxyhemoglobin saturation during sleep (AvSpOS) is a clinically relevant measure of physiological stress associated with sleep-disordered breathing, and this measure predicts incident cardiovascular disease and mortality. Using high-depth whole-genome sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) project and focusing on genes with linkage evidence on chromosome 8p23, we observed that six coding and 51 noncoding variants in a gene that encodes the GTPase-activating protein (DLC1) are significantly associated with AvSpOS and replicated in independent subjects. The combined DLC1 association evidence of discovery and replication cohorts reaches genome-wide significance in European Americans (p = 7.9 × 10). A risk score for these variants, built on an independent dataset, explains 0.97% of the AvSpOS variation and contributes to the linkage evidence. The 51 noncoding variants are enriched in regulatory features in a human lung fibroblast cell line and contribute to DLC1 expression variation. Mendelian randomization analysis using these variants indicates a significant causal effect of DLC1 expression in fibroblasts on AvSpOS. Multiple sources of information, including genetic variants, gene expression, and methylation, consistently suggest that DLC1 is a gene associated with AvSpOS.

Serial Plasma Phospholipid Fatty Acids in the De Novo Lipogenesis Pathway and Total Mortality, Cause-Specific Mortality, and Cardiovascular Diseases in the Cardiovascular Health Study. - Lai, Heidi T M; de Oliveira Otto, Marcia C; Lee, Yujin; Wu, Jason H Y; Song, Xiaoling; King, Irena B; Psaty, Bruce M; Lemaitre, Rozenn N; McKnight, Barbara; Siscovick, David S; Mozaffarian, Dariush (J Am Heart Assoc, 2019)
Background Synthesized fatty acids (FAs) from de novo lipogenesis may affect cardiometabolic health, but longitudinal associations between serially measured de novo lipogenesis-related fatty acid biomarkers and mortality or cardiovascular disease (CVD) are not well established. Methods and Results We investigated longitudinal associations between de novo lipogenesis-related fatty acids with all-cause mortality, cause-specific mortality, and incident CVD among 3869 older US adults, mean (SD) age 75 (5) years and free of prevalent CVD at baseline. Levels of plasma phospholipid palmitic (16:0), palmitoleic (16:1n-7), stearic (18:0), oleic acid (18:1n-9), and other risk factors were serially measured at baseline, 6 years, and 13 years. All-cause mortality, cause-specific mortality, and incident fatal and nonfatal CVD were centrally adjudicated. Risk was assessed in multivariable-adjusted Cox models with time-varying FAs and covariates. During 13 years, median follow-up (maximum 22.4 years), participants experienced 3227 deaths (1131 CVD, 2096 non-CVD) and 1753 incident CVD events. After multivariable adjustment, higher cumulative levels of 16:0, 16:1n-7, and 18:1n-9 were associated with higher all-cause mortality, with extreme-quintile hazard ratios (95% CIs) of 1.35 (1.17-1.56), 1.40 (1.21-1.62), and 1.56 (1.35-1.80), respectively, whereas higher levels of 18:0 were associated with lower mortality (hazard ratio=0.76; 95% CI=0.66-0.88). Associations were generally similar for CVD mortality versus non-CVD mortality, as well as total incident CVD. Changes in levels of 16:0 were positively, and 18:0 inversely, associated with all-cause mortality (hazard ratio=1.23, 95% CI=1.08-1.41; and hazard ratio=0.78, 95% CI=0.68-0.90). Conclusions Higher long-term levels of 16:0, 16:1n-7, and 18:1n-9 and changes in 16:0 were positively, whereas long-term levels and changes in 18:0 were inversely, associated with all-cause mortality in older adults.

Statin-induced LDL cholesterol response and type 2 diabetes: a bidirectional two-sample Mendelian randomization study. - Smit, Roelof A J; Trompet, Stella; Leong, Aaron; Goodarzi, Mark O; Postmus, Iris; Warren, Helen; Theusch, Elizabeth; Barnes, Michael R; Arsenault, Benoit J; Li, Xiaohui; Feng, QiPing; Chasman, Daniel I; et al. (Pharmacogenomics J, 2019)
It remains unclear whether the increased risk of new-onset type 2 diabetes (T2D) seen in statin users is due to low LDL-C concentrations, or due to the statin-induced proportional change in LDL-C. In addition, genetic instruments have not been proposed before to examine whether liability to T2D might cause greater proportional statin-induced LDL-C lowering. Using summary-level statistics from the Genomic Investigation of Statin Therapy (GIST, n = 40,914) and DIAGRAM (n = 159,208) consortia, we found a positive genetic correlation between LDL-C statin response and T2D using LD score regression (r = 0.36, s.e. = 0.13). However, mendelian randomization analyses did not provide support for statin response having a causal effect on T2D risk (OR 1.00 (95% CI: 0.97, 1.03) per 10% increase in statin response), nor that liability to T2D has a causal effect on statin-induced LDL-C response (0.20% increase in response (95% CI: -0.40, 0.80) per doubling of odds of liability to T2D). Although we found no evidence to suggest that proportional statin response influences T2D risk, a definitive assessment should be made in populations comprised exclusively of statin users, as the presence of nonstatin users in the DIAGRAM dataset may have substantially diluted our effect estimate.

Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels. - Tin, Adrienne; Marten, Jonathan; Halperin Kuhns, Victoria L; Li, Yong; Wuttke, Matthias; Kirsten, Holger; Sieber, Karsten B; Qiu, Chengxiang; Gorski, Mathias; Yu, Zhi; Giri, Ayush; Sveinbjornsson, Gardar; et al. (Nat Genet, 2019)
Elevated serum urate levels cause gout and correlate with cardiometabolic diseases via poorly understood mechanisms. We performed a trans-ancestry genome-wide association study of serum urate in 457,690 individuals, identifying 183 loci (147 previously unknown) that improve the prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardiometabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analysis, fine-mapping of urate-associated loci and colocalization with gene expression in 47 tissues implicated the kidney and liver as the main target organs and prioritized potentially causal genes and variants, including the transcriptional master regulators in the liver and kidney, HNF1A and HNF4A. Experimental validation showed that HNF4A transactivated the promoter of ABCG2, encoding a major urate transporter, in kidney cells, and that HNF4A p.Thr139Ile is a functional variant. Transcriptional coregulation within and across organs may be a general mechanism underlying the observed pleiotropy between urate and cardiometabolic traits.

Trans-ethnic association study of blood pressure determinants in over 750,000 individuals. - Giri, Ayush; Hellwege, Jacklyn N; Keaton, Jacob M; Park, Jihwan; Qiu, Chengxiang; Warren, Helen R; Torstenson, Eric S; Kovesdy, Csaba P; Sun, Yan V; Wilson, Otis D; Robinson-Cohen, Cassianne; Roumie, Christianne L; et al. (Nat Genet, 2019)
In this trans-ethnic multi-omic study, we reinterpret the genetic architecture of blood pressure to identify genes, tissues, phenomes and medication contexts of blood pressure homeostasis. We discovered 208 novel common blood pressure SNPs and 53 rare variants in genome-wide association studies of systolic, diastolic and pulse pressure in up to 776,078 participants from the Million Veteran Program (MVP) and collaborating studies, with analysis of the blood pressure clinical phenome in MVP. Our transcriptome-wide association study detected 4,043 blood pressure associations with genetically predicted gene expression of 840 genes in 45 tissues, and mouse renal single-cell RNA sequencing identified upregulated blood pressure genes in kidney tubule cells.

Association of CD14 with incident dementia and markers of brain aging and injury. - Pase, Matthew P; Himali, Jayandra J; Beiser, Alexa S; DeCarli, Charles; McGrath, Emer R; Satizabal, Claudia L; Aparicio, Hugo J; Adams, Hieab H H; Reiner, Alexander P; Longstreth, W T; Fornage, Myriam; Tracy, Russell P; et al. (Neurology, 2020)
OBJECTIVE: To test the hypothesis that the inflammatory marker plasma soluble CD14 (sCD14) associates with incident dementia and related endophenotypes in 2 community-based cohorts. METHODS: Our samples included the prospective community-based Framingham Heart Study (FHS) and Cardiovascular Health Study (CHS) cohorts. Plasma sCD14 was measured at baseline and related to the incidence of dementia, domains of cognitive function, and MRI-defined brain volumes. Follow-up for dementia occurred over a mean of 10 years (SD 4) in the FHS and a mean of 6 years (SD 3) in the CHS. RESULTS: We studied 1,588 participants from the FHS (mean age 69 ± 6 years, 47% male, 131 incident events) and 3,129 participants from the CHS (mean age 72 ± 5 years, 41% male, 724 incident events) for the risk of incident dementia. Meta-analysis across the 2 cohorts showed that each SD unit increase in sCD14 was associated with a 12% increase in the risk of incident dementia (95% confidence interval 1.03-1.23; = 0.01) following adjustments for age, sex, ε4 status, and vascular risk factors. Higher levels of sCD14 were associated with various cognitive and MRI markers of accelerated brain aging in both cohorts and with a greater progression of brain atrophy and a decline in executive function in the FHS. CONCLUSION: sCD14 is an inflammatory marker related to brain atrophy, cognitive decline, and incident dementia.

Characterization of cardiac mechanics and incident atrial fibrillation in participants of the Cardiovascular Health Study. - Patel, Ravi B; Delaney, Joseph A; Hu, Mo; Patel, Harnish; Cheng, Jeanette; Gottdiener, John; Kizer, Jorge R; Marcus, Gregory M; Turakhia, Mintu P; Deo, Rajat; Heckbert, Susan R; Psaty, Bruce M; et al. (JCI Insight, 2020)
BACKGROUND: Left atrial (LA) and left ventricular (LV) remodeling are associated with atrial fibrillation (AF). The prospective associations of impairment in cardiac mechanical function, as assessed by speckle-tracking echocardiography, with incident AF are less clear. METHODS: In the Cardiovascular Health Study, a community-based cohort of older adults, participants free of AF with echocardiograms of adequate quality for speckle tracking were included. We evaluated the associations of indices of cardiac mechanics (LA reservoir strain, LV longitudinal strain, and LV early diastolic strain rate) with incident AF. RESULTS: Of 4341 participants with strain imaging, participants with lower LA reservoir strain were older, had more cardiometabolic risk factors, and had lower renal function at baseline. Over a median follow-up of 10 years, 497 (11.4%) participants developed AF. Compared with the highest quartile of LA reservoir strain, the lowest quartile of LA reservoir strain was associated with higher risk of AF after covariate adjustment, including LA volume and LV longitudinal strain (heart rate [HR], 1.80; 95% CI, 1.31-2.45; P < 0.001). The association of LA reservoir strain and AF was stronger in subgroups with higher blood pressure, NT-proBNP, and LA volumes. There were no associations of LV longitudinal strain and LV early diastolic strain rate with incident AF after adjustment for LA reservoir strain. CONCLUSION: Lower LA reservoir strain was associated with incident AF, independent of LV mechanics, and with stronger associations in high-risk subgroups. These findings suggest that LA mechanical dysfunction precedes the development of AF. Therapies targeting LA mechanical dysfunction may prevent progression to AF. FUNDING: This research was supported by contracts HHSN268201200036C, HHSN268200800007C, HHSN268201800001C, N01HC55222, N01HC85079, N01HC85080, N01HC85081, N01HC85082, N01HC85083, and N01HC85086 and grants KL2TR001424, R01HL107577, U01HL080295, and U01HL130114 from the NIH's National Center for Advancing Translational Sciences, and National Heart, Lung, and Blood Institute (NHLBI), with additional contribution from the National Institute of Neurological Disorders and Stroke (NINDS). Additional support was provided by R01AG023629 from the National Institute on Aging (NIA). A full list of principal CHS investigators and institutions can be found at CHS-NHLBI.org.

Cholesterol Variability and Cranial Magnetic Resonance Imaging Findings in Older Adults: The Cardiovascular Health Study. - Kalani, Rizwan; Bartz, Traci M; Suchy-Dicey, Astrid; Elkind, Mitchell S V; Psaty, Bruce M; Leung, Lester Y; Rice, Kenneth; Tirschwell, David; Longstreth, W T (Stroke, 2020)
Background and Purpose- Serum cholesterol variability, independent of mean, has been associated with stroke, white matter hyperintensities on cranial magnetic resonance imaging (MRI), and other cardiovascular events. We sought to assess the relationship between total serum cholesterol (TC) variability and cranial MRI findings of subclinical or covert vascular brain injury in a longitudinal, population-based cohort study of older adults. Methods- In the Cardiovascular Health Study, we assessed associations between intraindividual TC mean, trend, and variability over ≈5 years with covert brain infarction (CBI) and white matter grade (WMG) on cranial MRI. Mean TC was calculated for each study participant from 4 annual TC measurements between 2 MRI scans. TC trend was calculated as the slope of the linear regression of the TC measurements, and TC variability was calculated as the SD of the residuals from the linear regression. We evaluated the association of intraindividual TC variability with incident CBI and worsening WMG between 2 MRI scans in primary analyses and with prevalent CBI number and WMG on the follow-up MRI scan in secondary analyses. Results- Among participants who were eligible for the study and free of clinical stroke before the follow-up MRI, 17.9% of 1098 had incident CBI, and 27.8% of 1351 had worsening WMG on the follow-up MRI. Mean, trend, and variability of TC were not associated with these outcomes. TC variability, independent of mean and trend, was significantly associated with the number of CBI (β=0.009 [95% CI, 0.003-0.016] =0.004; N=1604) and was associated with WMG (β, 0.009 [95% CI, -0.0002 to 0.019] =0.055; N=1602) on the follow-up MRI. Conclusions- Among older adults, TC variability was not associated with incident CBI or worsening WMG but was associated with the number of prevalent CBI on cranial MRI. More work is needed to validate and to clarify the mechanisms underlying such associations.

Chronic obstructive pulmonary disease and related phenotypes: polygenic risk scores in population-based and case-control cohorts. - Moll, Matthew; Sakornsakolpat, Phuwanat; Shrine, Nick; Hobbs, Brian D; DeMeo, Dawn L; John, Catherine; Guyatt, Anna L; McGeachie, Michael J; Gharib, Sina A; Obeidat, Ma'en; Lahousse, Lies; Wijnant, Sara R A; et al. (Lancet Respir Med, 2020)
BACKGROUND: Genetic factors influence chronic obstructive pulmonary disease (COPD) risk, but the individual variants that have been identified have small effects. We hypothesised that a polygenic risk score using additional variants would predict COPD and associated phenotypes. METHODS: We constructed a polygenic risk score using a genome-wide association study of lung function (FEV and FEV/forced vital capacity [FVC]) from the UK Biobank and SpiroMeta. We tested this polygenic risk score in nine cohorts of multiple ethnicities for an association with moderate-to-severe COPD (defined as FEV/FVC <0·7 and FEV <80% of predicted). Associations were tested using logistic regression models, adjusting for age, sex, height, smoking pack-years, and principal components of genetic ancestry. We assessed predictive performance of models by area under the curve. In a subset of studies, we also studied quantitative and qualitative CT imaging phenotypes that reflect parenchymal and airway pathology, and patterns of reduced lung growth. FINDINGS: The polygenic risk score was associated with COPD in European (odds ratio [OR] per SD 1·81 [95% CI 1·74-1·88] and non-European (1·42 [1·34-1·51]) populations. Compared with the first decile, the tenth decile of the polygenic risk score was associated with COPD, with an OR of 7·99 (6·56-9·72) in European ancestry and 4·83 (3·45-6·77) in non-European ancestry cohorts. The polygenic risk score was superior to previously described genetic risk scores and, when combined with clinical risk factors (ie, age, sex, and smoking pack-years), showed improved prediction for COPD compared with a model comprising clinical risk factors alone (AUC 0·80 [0·79-0·81] vs 0·76 [0·75-0·76]). The polygenic risk score was associated with CT imaging phenotypes, including wall area percent, quantitative and qualitative measures of emphysema, local histogram emphysema patterns, and destructive emphysema subtypes. The polygenic risk score was associated with a reduced lung growth pattern. INTERPRETATION: A risk score comprised of genetic variants can identify a small subset of individuals at markedly increased risk for moderate-to-severe COPD, emphysema subtypes associated with cigarette smoking, and patterns of reduced lung growth. FUNDING: US National Institutes of Health, Wellcome Trust.
Keywords: Adult; Case-Control Studies; Cohort Studies; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Phenotype; Pulmonary Disease, Chronic Obstructive; Risk Factors; Vital Capacity

Coagulation factor VIII, white matter hyperintensities and cognitive function: Results from the Cardiovascular Health Study. - Rohmann, Jessica L; Longstreth, W T; Cushman, Mary; Fitzpatrick, Annette L; Heckbert, Susan R; Rice, Kenneth; Rosendaal, Frits R; Sitlani, Colleen M; Psaty, Bruce M; Siegerink, Bob (PLoS One, 2020)
OBJECTIVE: To investigate the relationship between high FVIII clotting activity (FVIII:C), MRI-defined white matter hyperintensities (WMH) and cognitive function over time. METHODS: Data from the population-based Cardiovascular Health Study (n = 5,888, aged ≥65) were used. FVIII:C was measured in blood samples taken at baseline. WMH burden was assessed on two cranial MRI scans taken roughly 5 years apart. Cognitive function was assessed annually using the Modified Mini-Mental State Examination (3MSE) and Digit Symbol Substitution Test (DSST). We used ordinal logistic regression models adjusted for demographic and cardiovascular factors in cross-sectional and longitudinal WMH analyses, and adjusted linear regression and linear mixed models in the analyses of cognitive function. RESULTS: After adjustment for confounding, higher levels of FVIII:C were not strongly associated with the burden of WMH on the initial MRI scan (OR>p75 = 1.20, 95% CI 0.99-1.45; N = 2,735) nor with WMH burden worsening over time (OR>p75 = 1.18, 95% CI 0.87-1.59; N = 1,527). High FVIII:C showed no strong association with cognitive scores cross-sectionally (3MSE>p75 β = -0.06, 95%CI -0.45 to 0.32, N = 4,005; DSST>p75 β = -0.69, 95%CI -1.52 to 0.13, N = 3,954) or over time (3MSE>p75 β = -0.07,95% CI -0.58 to 0.44, N = 2,764; DSST>p75 β = -0.22, 95% CI -0.97 to 0.53, N = 2,306) after confounding adjustment. INTERPRETATION: The results from this cohort study of older adult participants indicate no strong relationships between higher FVIII:C levels and WMH burden or cognitive function in cross-sectional and longitudinal analyses.
Keywords: Aged; Blood Coagulation; Cognition; Cross-Sectional Studies; Factor VIII; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status and Dementia Tests; Up-Regulation; White Matter

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2020)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.

Genetic loci associated with prevalent and incident myocardial infarction and coronary heart disease in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Hahn, Julie; Fu, Yi-Ping; Brown, Michael R; Bis, Joshua C; de Vries, Paul S; Feitosa, Mary F; Yanek, Lisa R; Weiss, Stefan; Giulianini, Franco; Smith, Albert Vernon; Guo, Xiuqing; Bartz, Traci M; et al. (PLoS One, 2020)
BACKGROUND: Genome-wide association studies have identified multiple genomic loci associated with coronary artery disease, but most are common variants in non-coding regions that provide limited information on causal genes and etiology of the disease. To overcome the limited scope that common variants provide, we focused our investigation on low-frequency and rare sequence variations primarily residing in coding regions of the genome. METHODS AND RESULTS: Using samples of individuals of European ancestry from ten cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, both cross-sectional and prospective analyses were conducted to examine associations between genetic variants and myocardial infarction (MI), coronary heart disease (CHD), and all-cause mortality following these events. For prevalent events, a total of 27,349 participants of European ancestry, including 1831 prevalent MI cases and 2518 prevalent CHD cases were used. For incident cases, a total of 55,736 participants of European ancestry were included (3,031 incident MI cases and 5,425 incident CHD cases). There were 1,860 all-cause deaths among the 3,751 MI and CHD cases from six cohorts that contributed to the analysis of all-cause mortality. Single variant and gene-based analyses were performed separately in each cohort and then meta-analyzed for each outcome. A low-frequency intronic variant (rs988583) in PLCL1 was significantly associated with prevalent MI (OR = 1.80, 95% confidence interval: 1.43, 2.27; P = 7.12 × 10-7). We conducted gene-based burden tests for genes with a cumulative minor allele count (cMAC) ≥ 5 and variants with minor allele frequency (MAF) < 5%. TMPRSS5 and LDLRAD1 were significantly associated with prevalent MI and CHD, respectively, and RC3H2 and ANGPTL4 were significantly associated with incident MI and CHD, respectively. No loci were significantly associated with all-cause mortality following a MI or CHD event. CONCLUSION: This study identified one known locus (ANGPTL4) and four new loci (PLCL1, RC3H2, TMPRSS5, and LDLRAD1) associated with cardiovascular disease risk that warrant further investigation.
Keywords: Aging; Coronary Artery Disease; Cross-Sectional Studies; Europe; European Continental Ancestry Group; Genetic Loci; Genome-Wide Association Study; Humans; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

Genetic Studies of Leptin Concentrations Implicate Leptin in the Regulation of Early Adiposity. - Yaghootkar, Hanieh; Zhang, Yiying; Spracklen, Cassandra N; Karaderi, Tugce; Huang, Lam Opal; Bradfield, Jonathan; Schurmann, Claudia; Fine, Rebecca S; Preuss, Michael H; Kutalik, Zoltán; Wittemans, Laura Bl; Lu, Yingchang; et al. (Diabetes, 2020)
Leptin influences food intake by informing the brain about the status of body fat stores. Rare mutations associated with congenital leptin deficiency cause severe early-onset obesity that can be mitigated by administering leptin. However, the role of genetic regulation of leptin in polygenic obesity remains poorly understood. We performed an exome-based analysis in up to 57,232 individuals of diverse ancestries to identify genetic variants that influence adiposity-adjusted leptin concentrations. We identify five novel variants, including four missense variants, in , and , and one intergenic variant near The missense variant Val94Met (rs17151919) in was common in individuals of African ancestry only and its association with lower leptin concentrations was specific to this ancestry (P=2x10, n=3,901). Using analyses, we show that the Met94 allele decreases leptin secretion. We also show that the Met94 allele is associated with higher BMI in young African-ancestry children but not in adults, suggesting leptin regulates early adiposity.

Incorporating sampling weights into robust estimation of Cox proportional hazards regression model, with illustration in the Multi-Ethnic Study of Atherosclerosis. - Sitlani, Colleen M; Lumley, Thomas; McKnight, Barbara; Rice, Kenneth M; Olson, Nels C; Doyle, Margaret F; Huber, Sally A; Tracy, Russell P; Psaty, Bruce M; C Delaney, Joseph A (BMC Med Res Methodol, 2020)
BACKGROUND: Cox proportional hazards regression models are used to evaluate associations between exposures of interest and time-to-event outcomes in observational data. When exposures are measured on only a sample of participants, as they are in a case-cohort design, the sampling weights must be incorporated into the regression model to obtain unbiased estimating equations. METHODS: Robust Cox methods have been developed to better estimate associations when there are influential outliers in the exposure of interest, but these robust methods do not incorporate sampling weights. In this paper, we extend these robust methods, which already incorporate influence weights, so that they also accommodate sampling weights. RESULTS: Simulations illustrate that in the presence of influential outliers, the association estimate from the weighted robust method is closer to the true value than the estimate from traditional weighted Cox regression. As expected, in the absence of outliers, the use of robust methods yields a small loss of efficiency. Using data from a case-cohort study that is nested within the Multi-Ethnic Study of Atherosclerosis (MESA) longitudinal cohort study, we illustrate differences between traditional and robust weighted Cox association estimates for the relationships between immune cell traits and risk of stroke. CONCLUSIONS: Robust weighted Cox regression methods are a new tool to analyze time-to-event data with sampling, e.g. case-cohort data, when exposures of interest contain outliers.

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.

Innate and adaptive immune cell subsets as risk factors for coronary heart disease in two population-based cohorts. - Olson, Nels C; Sitlani, Colleen M; Doyle, Margaret F; Huber, Sally A; Landay, Alan L; Tracy, Russell P; Psaty, Bruce M; Delaney, Joseph A (Atherosclerosis, 2020)
BACKGROUND AND AIMS: Cell-mediated immunity is implicated in atherosclerosis. We evaluated whether innate and adaptive immune cell subsets in peripheral blood are risk factors for coronary heart disease. METHODS: A nested case-cohort study (n = 2155) was performed within the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS). Cases of incident myocardial infarction (MI) and incident angina (n = 880 total cases) were compared with a cohort random sample (n = 1275). Immune cell phenotypes (n = 34, including CD14 monocytes, natural killer cells, γδ T cells, CD4, CD8 and CD19 lymphocyte subsets) were measured from cryopreserved cells by flow cytometry. Cox proportional hazards models with adjustment for cardiovascular disease risk factors were used to evaluate associations of cell phenotypes with incident MI and a composite phenotype of incident MI or incident angina (MI-angina) over a median 9.3 years of follow-up. Th1, Th2, Th17, T regulatory (CD4CD25CD127), naive (CD4CD45RA), memory (CD4CD45RO), and CD4CD28 cells were specified as primary hypotheses. In secondary analyses, 27 additional cell phenotypes were investigated. RESULTS: After correction for multiple testing, there were no statistically significant associations of CD4 naive, memory, CD28, or T helper cell subsets with MI or MI-angina in MESA, CHS, or combined-cohort meta analyses. Null associations were also observed for monocyte subsets, natural killer cells, γδ T cells, CD19 B cell and differentiated CD4 and CD8 cell subsets. CONCLUSIONS: The proportions of peripheral blood monocyte and lymphocyte subsets are not strongly related to the future occurrence of MI or angina in adults free of autoimmune disease.

Level and change in N-terminal pro B-type Natriuretic Peptide and kidney function and survival to age 90. - Häberle, Astrid D; Biggs, Mary L; Cushman, Mary; Psaty, Bruce M; Newman, Anne B; Shlipak, Michael G; Gottdiener, John; Wu, Chenkai; Gardin, Julius M; Bansal, Nisha; Odden, Michelle C (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Many traditional cardiovascular risk factors do not predict survival to very old age. Studies have shown associations of estimated glomerular filtration rate (eGFR) and N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) with cardiovascular disease and mortality in older populations. This study aimed to evaluate the associations of the level and change in eGFR and NT-pro-BNP with longevity to age 90 years. METHODS: The population included participants (n=3,645) in the Cardiovascular Health Study, aged between 67-75 at baseline. The main exposures were eGFR, calculated with the Berlin Initiative Study equation (BIS2), and NT-pro-BNP, and the main outcome was survival to age 90. Mixed models were used to estimate level and change of the main exposures. RESULTS: There was an association between baseline level and change of both eGFR and NT-pro-BNP and survival to 90, and this association persisted after adjustment for covariates. Each 10 ml/min per 1.73 m2 higher eGFR level was associated with an adjusted odds ratio (OR) of 1.23 (95% CI: 1.13, 1.34) of survival to 90, and a 0.5 ml/min/ 1.73 m2 slower decline in eGFR was associated with an OR of 1.51 (95% CI: 1.31, 1.74). A 2-fold higher level of NT-pro-BNP level had an adjusted OR of 0.67 (95% CI: 0.61, 0.73), and a 1.05-fold increase per year in NT-pro-BNP had an OR of 0.53 (95% CI: 0.43, 0.65) for survival to age 90. CONCLUSION: eGFR and NT-pro-BNP appear to be important risk factors for longevity to age 90.

Mendelian randomization analysis does not support causal associations of birth weight with hypertension risk and blood pressure in adulthood. - Zheng, Yan; Huang, Tao; Wang, Tiange; Mei, Zhendong; Sun, Zhonghan; Zhang, Tao; Ellervik, Christina; Chai, Jin-Fang; Sim, Xueling; van Dam, Rob M; Tai, E-Shyong; Koh, Woon-Puay; et al. (Eur J Epidemiol, 2020)
Epidemiology studies suggested that low birthweight was associated with a higher risk of hypertension in later life. However, little is known about the causality of such associations. In our study, we evaluated the causal association of low birthweight with adulthood hypertension following a standard analytic protocol using the study-level data of 183,433 participants from 60 studies (CHARGE-BIG consortium), as well as that with blood pressure using publicly available summary-level genome-wide association data from EGG consortium of 153,781 participants, ICBP consortium and UK Biobank cohort together of 757,601 participants. We used seven SNPs as the instrumental variable in the study-level analysis and 47 SNPs in the summary-level analysis. In the study-level analyses, decreased birthweight was associated with a higher risk of hypertension in adults (the odds ratio per 1 standard deviation (SD) lower birthweight, 1.22; 95% CI 1.16 to 1.28), while no association was found between genetically instrumented birthweight and hypertension risk (instrumental odds ratio for causal effect per 1 SD lower birthweight, 0.97; 95% CI 0.68 to 1.41). Such results were consistent with that from the summary-level analyses, where the genetically determined low birthweight was not associated with blood pressure measurements either. One SD lower genetically determined birthweight was not associated with systolic blood pressure (β = - 0.76, 95% CI - 2.45 to 1.08 mmHg), 0.06 mmHg lower diastolic blood pressure (β = - 0.06, 95% CI - 0.93 to 0.87 mmHg), or pulse pressure (β = - 0.65, 95% CI - 1.38 to 0.69 mmHg, all p > 0.05). Our findings suggest that the inverse association of birthweight with hypertension risk from observational studies was not supported by large Mendelian randomization analyses.

Meta-analysis uncovers genome-wide significant variants for rapid kidney function decline. - Gorski, Mathias; Jung, Bettina; Li, Yong; Matias-Garcia, Pamela R; Wuttke, Matthias; Coassin, Stefan; Thio, Chris H L; Kleber, Marcus E; Winkler, Thomas W; Wanner, Veronika; Chai, Jin-Fang; Chu, Audrey Y; et al. (Kidney Int, 2020)
Rapid decline of glomerular filtration rate estimated from creatinine (eGFRcrea) is associated with severe clinical endpoints. In contrast to cross-sectionally assessed eGFRcrea, the genetic basis for rapid eGFRcrea decline is largely unknown. To help define this, we meta-analyzed 42 genome-wide association studies from the Chronic Kidney Diseases Genetics Consortium and United Kingdom Biobank to identify genetic loci for rapid eGFRcrea decline. Two definitions of eGFRcrea decline were used: 3 mL/min/1.73m/year or more ("Rapid3"; encompassing 34,874 cases, 107,090 controls) and eGFRcrea decline 25% or more and eGFRcrea under 60 mL/min/1.73m at follow-up among those with eGFRcrea 60 mL/min/1.73m or more at baseline ("CKDi25"; encompassing 19,901 cases, 175,244 controls). Seven independent variants were identified across six loci for Rapid3 and/or CKDi25: consisting of five variants at four loci with genome-wide significance (near UMOD-PDILT (2), PRKAG2, WDR72, OR2S2) and two variants among 265 known eGFRcrea variants (near GATM, LARP4B). All these loci were novel for Rapid3 and/or CKDi25 and our bioinformatic follow-up prioritized variants and genes underneath these loci. The OR2S2 locus is novel for any eGFRcrea trait including interesting candidates. For the five genome-wide significant lead variants, we found supporting effects for annual change in blood urea nitrogen or cystatin-based eGFR, but not for GATM or LARP4B. Individuals at high compared to those at low genetic risk (8-14 vs 0-5 adverse alleles) had a 1.20-fold increased risk of acute kidney injury (95% confidence interval 1.08-1.33). Thus, our identified loci for rapid kidney function decline may help prioritize therapeutic targets and identify mechanisms and individuals at risk for sustained deterioration of kidney function.

Multi-ancestry GWAS of the electrocardiographic PR interval identifies 202 loci underlying cardiac conduction. - Ntalla, Ioanna; Weng, Lu-Chen; Cartwright, James H; Hall, Amelia Weber; Sveinbjornsson, Gardar; Tucker, Nathan R; Choi, Seung Hoan; Chaffin, Mark D; Roselli, Carolina; Barnes, Michael R; Mifsud, Borbala; Warren, Helen R; et al. (Nat Commun, 2020)
The electrocardiographic PR interval reflects atrioventricular conduction, and is associated with conduction abnormalities, pacemaker implantation, atrial fibrillation (AF), and cardiovascular mortality. Here we report a multi-ancestry (N = 293,051) genome-wide association meta-analysis for the PR interval, discovering 202 loci of which 141 have not previously been reported. Variants at identified loci increase the percentage of heritability explained, from 33.5% to 62.6%. We observe enrichment for cardiac muscle developmental/contractile and cytoskeletal genes, highlighting key regulation processes for atrioventricular conduction. Additionally, 8 loci not previously reported harbor genes underlying inherited arrhythmic syndromes and/or cardiomyopathies suggesting a role for these genes in cardiovascular pathology in the general population. We show that polygenic predisposition to PR interval duration is an endophenotype for cardiovascular disease, including distal conduction disease, AF, and atrioventricular pre-excitation. These findings advance our understanding of the polygenic basis of cardiac conduction, and the genetic relationship between PR interval duration and cardiovascular disease.

Patterns of Cardiovascular Risk Factors in Old Age and Survival and Health Status at 90. - Odden, Michelle C; Rawlings, Andreea M; Arnold, Alice M; Cushman, Mary; Biggs, Mary L; Psaty, Bruce M; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: The population age 90 years and older is the fastest growing segment of the U.S. population. Only recently is it possible to study the factors that portend survival to this age. METHODS: Among participants of the Cardiovascular Health Study, we studied the association of repeated measures of cardiovascular risk factors measured over 15-23 years of follow-up and not only survival to 90 years of age, but also healthy aging outcomes among the population who reached age 90. We included participants aged 67-75 years at baseline (n = 3,613/5,888) to control for birth cohort effects, and followed participants until death or age 90 (median follow-up = 14.7 years). RESULTS: Higher systolic blood pressure was associated with a lower likelihood of survival to age 90, although this association was attenuated at older ages (p-value for interaction <.001) and crossed the null for measurements taken in participants' 80's. Higher levels of high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, and body mass index (BMI) were associated with greater longevity. Among the survivors to age 90, those with worse cardiovascular profile (high blood pressure, LDL cholesterol, glucose, and BMI; low HDL cholesterol) had lower likelihood of remaining free of cardiovascular disease, cognitive impairment, and disability. CONCLUSION: In summary, we observed paradoxical associations between some cardiovascular risk factors and survival to old age; whereas, among those who survive to very old age, these risk factors were associated with higher risk of adverse health outcomes.

Plasma Ceramides and Sphingomyelins in Relation to Atrial Fibrillation Risk: The Cardiovascular Health Study. - Jensen, Paul N; Fretts, Amanda M; Hoofnagle, Andrew N; Sitlani, Colleen M; McKnight, Barbara; King, Irena B; Siscovick, David S; Psaty, Bruce M; Heckbert, Susan R; Mozaffarian, Dariush; Sotoodehnia, Nona; Lemaitre, Rozenn N (J Am Heart Assoc, 2020)
Background Ceramides exhibit multiple biological activities that may influence the pathophysiological characteristics of atrial fibrillation (AF). Whether the length of the saturated fatty acid carried by the ceramide or their sphingomyelin precursors are associated with AF risk is not known. Methods and Results Among 4206 CHS (Cardiovascular Health Study) participants (mean age, 76 years; 40% men) who were free of prevalent AF at baseline, we identified 1198 incident AF cases over a median 8.7 years of follow-up. We examined 8 sphingolipid species: ceramide and sphingomyelin species with palmitic acid and species with very-long-chain saturated fatty acids: arachidic; behenic; and lignoceric. In adjusted Cox regression analyses, ceramides and sphingomyelins with very-long-chain saturated fatty acids were associated with reduced AF risk (ie, per 2-fold higher ceramide with behenic acid hazard ratio, 0.71; 95% CI, 0.59-0.86; sphingomyelin with behenic acid hazard ratio, 0.60; 95% CI, 0.46-0.77). In contrast, ceramides and sphingomyelins with palmitic acid were associated with increased AF risk (ceramide with palmitic acid hazard ratio, 1.31; 95% CI, 1.03-1.66; sphingomyelin with palmitic acid hazard ratio, 1.73; 95% CI, 1.18-2.55). Associations were attenuated with adjustment for NT-proBNP (N-terminal pro-B-type natriuretic peptide), but did not differ significantly by age, sex, race, body mass index, or history of coronary heart disease. Conclusions Our findings suggest that several ceramide and sphingomyelin species are associated with incident AF, and that these associations differ on the basis of the fatty acid. Ceramides and sphingomyelins with palmitic acid were associated with increased AF risk, whereas ceramides and sphingomyelins with very-long-chain saturated fatty acids were associated with reduced AF risk.

The Polygenic and Monogenic Basis of Blood Traits and Diseases. - Vuckovic, Dragana; Bao, Erik L; Akbari, Parsa; Lareau, Caleb A; Mousas, Abdou; Jiang, Tao; Chen, Ming-Huei; Raffield, Laura M; Tardaguila, Manuel; Huffman, Jennifer E; Ritchie, Scott C; Megy, Karyn; et al. (Cell, 2020)
Blood cells play essential roles in human health, underpinning physiological processes such as immunity, oxygen transport, and clotting, which when perturbed cause a significant global health burden. Here we integrate data from UK Biobank and a large-scale international collaborative effort, including data for 563,085 European ancestry participants, and discover 5,106 new genetic variants independently associated with 29 blood cell phenotypes covering a range of variation impacting hematopoiesis. We holistically characterize the genetic architecture of hematopoiesis, assess the relevance of the omnigenic model to blood cell phenotypes, delineate relevant hematopoietic cell states influenced by regulatory genetic variants and gene networks, identify novel splice-altering variants mediating the associations, and assess the polygenic prediction potential for blood traits and clinical disorders at the interface of complex and Mendelian genetics. These results show the power of large-scale blood cell trait GWAS to interrogate clinically meaningful variants across a wide allelic spectrum of human variation.

Relation of Biomarkers of Cardiac Injury, Stress, and Fibrosis With Cardiac Mechanics in Patients ≥ 65 Years of Age. - Gottdiener, John S; Seliger, Stephen; DeFilippi, Christopher; Christenson, Robert; Baldridge, Abigail S; Kizer, Jorge R; Psaty, Bruce M; Shah, Sanjiv J (Am J Cardiol, 2020)
High sensitivity cardiac troponin T (hscTnT), soluble ST2 (sST2), N-terminal B-type natriuretic peptide (NT-proBNP), and galectin-3 are biomarkers of cardiac injury, stress, myocardial stretch, and fibrosis. Elevated levels are associated with poor outcomes. However, their association with cardiac mechanics in older persons is unknown. Associations between these biomarkers and cardiac mechanics derived from speckle tracking echocardiography, including left ventricular longitudinal strain (LVLS), early diastolic strain, and left atrial reservoir strain (LARS) were evaluated using standardized beta coefficients () in a cross sectional analysis with cardiac biomarkers in older patients without cardiovascular disease, low ejection fraction, or wall motion abnormalities. Biomarker associations with strain were attenuated by demographics and risk factors. In adjusted models, LVLS was associated with continuous measures of hscTnT (β-0.06, p = 0.020), sST2 (β -0.05, p = 0.024) and NT-proBNP (β -0.06, p = 0.007). "High" levels (i.e., greater than prognostic cutpoint) of hscTnT (>13 ng/ml), sST2 (>35 ng/ml), and NT-proBNP (>190 pg/ml) were also associated with worse LVLS. In risk factor adjusted models, LARS was associated with hscTnT (β -0.08, p = 0.003) and NT-proBNP (β-0.18, p <0.0001). High hscTnT (>13 ng/ml) and high NT-proBNP (>190 pg/ml) were also both associated with worse LARS. Gal-3 was not associated with any strain measure. In conclusion, in persons ≥ 65 years of age, without cardiovascular disease, low ejection fraction, or wall motion abnormalities, hscTnT, sST2, and NT-proBNP are associated with worse LVLS. HscTnT and NT-proBNP are associated with worse LARS. In conclusion, these subclinical increases in blood biomarkers, and their associations with subtle diastolic and systolic dysfunction, may represent pre-clinical heart failure.

Role of Rare and Low-Frequency Variants in Gene-Alcohol Interactions on Plasma Lipid Levels. - Wang, Zhe; Chen, Han; Bartz, Traci M; Bielak, Lawrence F; Chasman, Daniel I; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Lim, Elise; Noordam, Raymond; Richard, Melissa A; Wang, Heming; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: Alcohol intake influences plasma lipid levels, and such effects may be moderated by genetic variants. We aimed to characterize the role of aggregated rare and low-frequency protein-coding variants in gene by alcohol consumption interactions associated with fasting plasma lipid levels. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, fasting plasma triglycerides and high- and low-density lipoprotein cholesterol were measured in 34 153 individuals with European ancestry from 5 discovery studies and 32 277 individuals from 6 replication studies. Rare and low-frequency functional protein-coding variants (minor allele frequency, ≤5%) measured by an exome array were aggregated by genes and evaluated by a gene-environment interaction test and a joint test of genetic main and gene-environment interaction effects. Two dichotomous self-reported alcohol consumption variables, current drinker, defined as any recurrent drinking behavior, and regular drinker, defined as the subset of current drinkers who consume at least 2 drinks per week, were considered. RESULTS: We discovered and replicated 21 gene-lipid associations at 13 known lipid loci through the joint test. Eight loci (, , , , , , , and ) remained significant after conditioning on the common index single-nucleotide polymorphism identified by previous genome-wide association studies, suggesting an independent role for rare and low-frequency variants at these loci. One significant gene-alcohol interaction on triglycerides in a novel locus was significantly discovered (=6.65×10 for the interaction test) and replicated at nominal significance level (=0.013) in . CONCLUSIONS: In conclusion, this study applied new gene-based statistical approaches and suggested that rare and low-frequency genetic variants interacted with alcohol consumption on lipid levels.

Sex-Specific Associations of Cardiovascular Risk Factors and Biomarkers With Incident Heart Failure. - Suthahar, Navin; Lau, Emily S; Blaha, Michael J; Paniagua, Samantha M; Larson, Martin G; Psaty, Bruce M; Benjamin, Emelia J; Allison, Matthew A; Bartz, Traci M; Januzzi, James L; Levy, Daniel; Meems, Laura M G; et al. (J Am Coll Cardiol, 2020)
BACKGROUND: Whether cardiovascular (CV) disease risk factors and biomarkers associate differentially with heart failure (HF) risk in men and women is unclear. OBJECTIVES: The purpose of this study was to evaluate sex-specific associations of CV risk factors and biomarkers with incident HF. METHODS: The analysis was performed using data from 4 community-based cohorts with 12.5 years of follow-up. Participants (recruited between 1989 and 2002) were free of HF at baseline. Biomarker measurements included natriuretic peptides, cardiac troponins, plasminogen activator inhibitor-1, D-dimer, fibrinogen, C-reactive protein, sST2, galectin-3, cystatin-C, and urinary albumin-to-creatinine ratio. RESULTS: Among 22,756 participants (mean age 60 ± 13 years, 53% women), HF occurred in 2,095 participants (47% women). Age, smoking, type 2 diabetes mellitus, hypertension, body mass index, atrial fibrillation, myocardial infarction, left ventricular hypertrophy, and left bundle branch block were strongly associated with HF in both sexes (p < 0.001), and the combined clinical model had good discrimination in men (C-statistic = 0.80) and in women (C-statistic = 0.83). The majority of biomarkers were strongly and similarly associated with HF in both sexes. The clinical model improved modestly after adding natriuretic peptides in men (ΔC-statistic = 0.006; likelihood ratio chi-square = 146; p < 0.001), and after adding cardiac troponins in women (ΔC-statistic = 0.003; likelihood ratio chi-square = 73; p < 0.001). CONCLUSIONS: CV risk factors are strongly and similarly associated with incident HF in both sexes, highlighting the similar importance of risk factor control in reducing HF risk in the community. There are subtle sex-related differences in the predictive value of individual biomarkers, but the overall improvement in HF risk estimation when included in a clinical HF risk prediction model is limited in both sexes.

Soluble CD14 and Risk of Heart Failure and Its Subtypes in Older Adults. - Al-Kindi, Sadeer G; Bůzková, Petra; Shitole, Sanyog G; Reiner, Alex P; Garg, Parveen K; Gottdiener, John S; Psaty, Bruce M; Kizer, Jorge R (J Card Fail, 2020)
BACKGROUND: CD14 is a membrane glycoprotein primarily expressed by myeloid cells that plays a key role in inflammation. Soluble CD14 (sCD14) levels carry a poor prognosis in chronic heart failure (HF), but whether elevations in sCD14 precede HF is unknown. We tested the hypothesis that sCD14 is associated with HF incidence and its subtypes independent of major inflammatory biomarkers among older adults. METHODS AND RESULTS: We included participants in the Cardiovascular Health Study without preexisting HF and available baseline sCD14. We evaluated the associations of sCD14, high-sensitivity C-reactive protein (hsCRP), interleukin (IL)-6, and white blood cell count (WBC) with incident HF and subtypes using Cox regression. Among 5217 participants, 1878 had incident HF over 13.6 years (609 classifiable as HF with preserved ejection fraction [HFpEF] and 419 as HF with reduced ejection fraction [HFrEF]). After adjusting for clinical and laboratory covariates, sCD14 was significantly associated with incident HF (hazard ratio [HR]: 1.56 per doubling, 95% confidence interval [CI]: 1.29-1.89), an association that was numerically stronger than for hsCRP (HR per doubling: 1.10, 95% CI: 1.06-1.15), IL-6 (HR: 1.18, 95% CI: 1.10-1.25), and WBC (HR: 1.24, 95% CI: 1.09-1.42), and that remained significant after adjustment for the other markers of inflammation. This association for sCD14 was observed with HFpEF (HR: 1.50, 95% CI: 1.07-2.10) but not HFrEF (HR: 0.99, 95% CI: 0.67-1.49). CONCLUSIONS: Plasma sCD14 was associated with incident HF independently and numerically more strongly than other major inflammatory markers. This association was only observed with HFpEF in the subset with classifiable HF subtypes. Pending replication, these findings have potentially important therapeutic implications.

Trans-ethnic and Ancestry-Specific Blood-Cell Genetics in 746,667 Individuals from 5 Global Populations. - Chen, Ming-Huei; Raffield, Laura M; Mousas, Abdou; Sakaue, Saori; Huffman, Jennifer E; Moscati, Arden; Trivedi, Bhavi; Jiang, Tao; Akbari, Parsa; Vuckovic, Dragana; Bao, Erik L; Zhong, Xue; et al. (Cell, 2020)
Most loci identified by GWASs have been found in populations of European ancestry (EUR). In trans-ethnic meta-analyses for 15 hematological traits in 746,667 participants, including 184,535 non-EUR individuals, we identified 5,552 trait-variant associations at p < 5 × 10, including 71 novel associations not found in EUR populations. We also identified 28 additional novel variants in ancestry-specific, non-EUR meta-analyses, including an IL7 missense variant in South Asians associated with lymphocyte count in vivo and IL-7 secretion levels in vitro. Fine-mapping prioritized variants annotated as functional and generated 95% credible sets that were 30% smaller when using the trans-ethnic as opposed to the EUR-only results. We explored the clinical significance and predictive value of trans-ethnic variants in multiple populations and compared genetic architecture and the effect of natural selection on these blood phenotypes between populations. Altogether, our results for hematological traits highlight the value of a more global representation of populations in genetic studies.

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

Adverse cardiac mechanics and incident coronary heart disease in the Cardiovascular Health Study. - Massera, Daniele; Hu, Mo; Delaney, Joseph A; Bartz, Traci M; Bach, Megan E; Dvorak, Stephen J; deFilippi, Christopher R; Psaty, Bruce M; Gottdiener, John S; Kizer, Jorge R; Shah, Sanjiv J (Heart, 2021)
OBJECTIVES: Speckle-tracking echocardiography enables detection of abnormalities in cardiac mechanics with higher sensitivity than conventional measures of left ventricular (LV) dysfunction and may provide insight into the pathogenesis of coronary heart disease (CHD). We investigated the relationship of LV longitudinal strain, LV early diastolic strain rate (SR) and left atrial (LA) reservoir strain with long-term CHD incidence in community-dwelling older adults. METHODS: The association of all three strain measures with incidence of non-fatal and fatal CHD (primary outcome of revascularisation, non-fatal and fatal myocardial infarction) was examined in the population-based Cardiovascular Health Study using multivariable Cox proportional hazards models. Follow-up was truncated at 10 years. RESULTS: We included 3313 participants (mean (SD) age 72.6 (5.5) years). During a median follow-up of 10.0 (25th-75th percentile 7.7-10.0) years, 439 CHD events occurred. LV longitudinal strain (HR=1.25 per SD decrement, 95% CI 1.09 to 1.43) and LV early diastolic SR (HR=1.31 per SD decrement, 95% CI 1.14 to 1.50) were associated with a significantly greater risk of incident CHD after adjustment for potential confounders. By contrast, LA reservoir strain was not associated with incident CHD (HR=1.06 per SD decrement, 95% CI 0.94 to 1.19). Additional adjustment for biochemical and echocardiographic measures of myocardial stress, dysfunction and remodelling did not meaningfully alter these associations. CONCLUSION: We found an association between echocardiographic measures of subclinically altered LV mechanics and incident CHD. These findings inform the underlying biology of subclinical LV dysfunction and CHD. Early detection of asymptomatic myocardial dysfunction may offer an opportunity for prevention and early intervention.

Association Between Myocardial Strain and Frailty in CHS. - Tan, Annabel X; Shah, Sanjiv J; Sanders, Jason L; Psaty, Bruce M; Wu, Chenkai; Gardin, Julius M; Peralta, Carmen A; Newman, Anne B; Odden, Michelle C (Circ Cardiovasc Imaging, 2021)
BACKGROUND: Myocardial strain, measured by speckle-tracking echocardiography, is a novel measure of subclinical cardiovascular disease and may reflect myocardial aging. We evaluated the association between myocardial strain and frailty-a clinical syndrome of lack of physiological reserve. METHODS: Frailty was defined in participants of the CHS (Cardiovascular Health Study) as having ≥3 of the following clinical criteria: weakness, slowness, weight loss, exhaustion, and inactivity. Using speckle-tracking echocardiography data, we examined the cross-sectional (n=3206) and longitudinal (n=1431) associations with frailty among participants who had at least 1 measure of myocardial strain, left ventricular longitudinal strain (LVLS), left ventricular early diastolic strain rate and left atrial reservoir strain, and no history of cardiovascular disease or heart failure at the time of echocardiography. RESULTS: In cross-sectional analyses, lower (worse) LVLS was associated with prevalent frailty; this association was robust to adjustment for left ventricular ejection fraction (adjusted odds ratio, 1.32 [95% CI, 1.07-1.61] per 1-SD lower strain; =0.007) and left ventricular stroke volume (adjusted OR, 1.32 [95% CI, 1.08-1.61] per 1-SD lower strain; =0.007). In longitudinal analyses, adjusted associations of LVLS and left ventricular early diastolic strain with incident frailty were 1.35 ([95% CI, 0.96-1.89] =0.086) and 1.58 ([95% CI, 1.11-2.27] =0.013, respectively). Participants who were frail and had the worst LVLS had a 2.2-fold increased risk of death (hazard ratio, 2.20 [95% CI, 1.81-2.66]; <0.0001). CONCLUSIONS: In community-dwelling older adults without prevalent cardiovascular disease, worse LVLS by speckle-tracking echocardiography, reflective of subclinical myocardial dysfunction, was associated with frailty. Frailty and LVLS have an additive effect on mortality risk.

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Association of mitochondrial DNA copy number with cardiometabolic diseases. - Liu, Xue; Longchamps, Ryan J; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Blackwell, Thomas W; Yao, Jie; Guo, Xiuqing; Kurniansyah, Nuzulul; Thyagarajan, Bharat; et al. (Cell Genom, 2021)
Mitochondrial DNA (mtDNA) is present in multiple copies in human cells. We evaluated cross-sectional associations of whole blood mtDNA copy number (CN) with several cardiometabolic disease traits in 408,361 participants of multiple ancestries in TOPMed and UK Biobank. Age showed a threshold association with mtDNA CN: among younger participants (<65 years of age), each additional 10 years of age was associated with 0.03 standard deviation (s.d.) higher level of mtDNA CN ( = 0.0014) versus a 0.14 s.d. lower level of mtDNA CN ( = 1.82 × 10) among older participants (≥65 years). At lower mtDNA CN levels, we found age-independent associations with increased odds of obesity ( = 5.6 × 10), hypertension ( = 2.8 × 10), diabetes ( = 3.6 × 10), and hyperlipidemia ( = 6.3 × 10). The observed decline in mtDNA CN after 65 years of age may be a key to understanding age-related diseases.

Association of Trimethylamine N-Oxide and Related Metabolites in Plasma and Incident Type 2 Diabetes: The Cardiovascular Health Study. - Lemaitre, Rozenn N; Jensen, Paul N; Wang, Zeneng; Fretts, Amanda M; McKnight, Barbara; Nemet, Ina; Biggs, Mary L; Sotoodehnia, Nona; de Oliveira Otto, Marcia C; Psaty, Bruce M; Siscovick, David S; Hazen, Stanley L; et al. (JAMA Netw Open, 2021)
Importance: Although rodent studies suggest that trimethylamine N-oxide (TMAO) influences glucose homeostasis and risk of type 2 diabetes, evidence in humans is limited. Objective: To examine the associations of serial measures of plasma TMAO and related metabolite concentrations with incident type 2 diabetes, fasting plasma insulin and glucose levels, and the Gutt insulin sensitivity index (ISI). Design, Setting, and Participants: This prospective cohort design assessed the association of plasma TMAO and related metabolite concentrations with diabetes outcome, whereas a cross-sectional design assessed the association with insulin and glucose levels and Gutt ISI. The participants were a cohort of older US adults from the Cardiovascular Health Study (CHS). Data from June 1989 to May 1990, from November 1992 to June 1993, and from June 1995 to June 1997 were included, with follow-up through June 2010. Levels of TMAO and related metabolites were measured in CHS plasma samples. Data were analyzed from July 2019 to September 2020. Exposures: Plasma concentrations of TMAO, carnitine, betaine, choline, crotonobetaine, and γ-butyrobetaine, measured by high-performance liquid chromatography and mass spectrometry. Main Outcomes and Measures: Linear regression for associations of TMAO and related metabolites with insulin and glucose levels and Gutt ISI, and proportional hazards regression for associations with diabetes. Results: The study included 4442 participants without diabetes at baseline (mean [SD] age, 73 [6] years at entry; 2710 [61%] women). In multivariable analyses, plasma TMAO, carnitine, crotonobetaine, and γ-butyrobetaine concentrations were positively associated with fasting insulin level (insulin mean geometric ratio comparing fifth with first quintiles of metabolite concentration: 1.07 [95% CI, 1.04-1.10] for TMAO; 1.07 [95% CI, 1.03-1.10] for carnitine; 1.05 [95% CI, 1.02-1.08] for crotonobetaine; and 1.06 [95% CI, 1.02-1.09] for γ-butyrobetaine). In contrast, betaine and choline concentrations were associated with greater insulin sensitivity (mean difference in Gutt ISI comparing fifth with first quintiles: 6.46 [95% CI, 4.32-8.60] and 2.27 [95% CI, 0.16-4.38], respectively). Incident diabetes was identified in 661 participants during a median 12.1 (interquartile range, 6.9-17.1) years of follow-up. In multivariable analyses, TMAO and metabolites were not significantly associated with type 2 diabetes risk (hazard ratios of diabetes comparing fifth with first quintile: 1.20 [95% CI, 0.94-1.55] for TMAO; 0.96 [95% CI, 0.74-1.24] for choline; 0.88 [95% CI, 0.67-1.15] for betaine; 1.07 [95% CI, 0.83-1.37] for carnitine; 0.79 [95% CI, 0.60-1.04] for γ-butyrobetaine; and 1.06 [95% CI, 0.83-1.35] for crotonobetaine). Conclusions and Relevance: Plasma TMAO and related metabolites were not significantly associated with type 2 diabetes among older adults. The metabolites TMAO, carnitine, γ-butyrobetaine, and crotonobetaine may be associated with insulin resistance, and betaine and choline may be associated with greater insulin sensitivity, but temporality of the associations was not established.

BinomiRare: A robust test for association of a rare genetic variant with a binary outcome for mixed models and any case-control proportion. - Sofer, Tamar; Lee, Jiwon; Kurniansyah, Nuzulul; Jain, Deepti; Laurie, Cecelia A; Gogarten, Stephanie M; Conomos, Matthew P; Heavner, Ben; Hu, Yao; Kooperberg, Charles; Haessler, Jeffrey; Vasan, Ramachandran S; et al. (HGG Adv, 2021)
Whole-genome sequencing (WGS) and whole-exome sequencing studies have become increasingly available and are being used to identify rare genetic variants associated with health and disease outcomes. Investigators routinely use mixed models to account for genetic relatedness or other clustering variables (e.g., family or household) when testing genetic associations. However, no existing tests of the association of a rare variant with a binary outcome in the presence of correlated data control the type 1 error where there are (1) few individuals harboring the rare allele, (2) a small proportion of cases relative to controls, and (3) covariates to adjust for. Here, we address all three issues in developing a framework for testing rare variant association with a binary trait in individuals harboring at least one risk allele. In this framework, we estimate outcome probabilities under the null hypothesis and then use them, within the individuals with at least one risk allele, to test variant associations. We extend the BinomiRare test, which was previously proposed for independent observations, and develop the Conway-Maxwell-Poisson (CMP) test and study their properties in simulations. We show that the BinomiRare test always controls the type 1 error, while the CMP test sometimes does not. We then use the BinomiRare test to test the association of rare genetic variants in target genes with small-vessel disease (SVD) stroke, short sleep, and venous thromboembolism (VTE), in whole-genome sequence data from the Trans-Omics for Precision Medicine (TOPMed) program.

Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies. - Harris, William S; Tintle, Nathan L; Imamura, Fumiaki; Qian, Frank; Korat, Andres V Ardisson; Marklund, Matti; Djoussé, Luc; Bassett, Julie K; Carmichael, Pierre-Hugues; Chen, Yun-Yu; Hirakawa, Yoichiro; Küpers, Leanne K; et al. (Nat Commun, 2021)
The health effects of omega-3 fatty acids have been controversial. Here we report the results of a de novo pooled analysis conducted with data from 17 prospective cohort studies examining the associations between blood omega-3 fatty acid levels and risk for all-cause mortality. Over a median of 16 years of follow-up, 15,720 deaths occurred among 42,466 individuals. We found that, after multivariable adjustment for relevant risk factors, risk for death from all causes was significantly lower (by 15-18%, at least p < 0.003) in the highest vs the lowest quintile for circulating long chain (20-22 carbon) omega-3 fatty acids (eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids). Similar relationships were seen for death from cardiovascular disease, cancer and other causes. No associations were seen with the 18-carbon omega-3, alpha-linolenic acid. These findings suggest that higher circulating levels of marine n-3 PUFA are associated with a lower risk of premature death.
Keywords: Aged; Aged, 80 and over; Cause of Death; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Male; Middle Aged; Mortality, Premature; Prospective Studies; Protective Factors; Risk Factors

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.

Circulating Ceramides and Sphingomyelins and Risk of Mortality: The Cardiovascular Health Study. - Fretts, Amanda M; Jensen, Paul N; Hoofnagle, Andrew N; McKnight, Barbara; Sitlani, Colleen M; Siscovick, David S; King, Irena B; Psaty, Bruce M; Sotoodehnia, Nona; Lemaitre, Rozenn N (Clin Chem, 2021)
BACKGROUND: Recent studies suggest that associations of ceramides (Cer) and sphingomyelins (SM) with health outcomes differ according to the fatty acid acylated to the sphingoid backbone. The purpose of this study was to assess associations of Cer and SM species with mortality. METHODS: The study population included participants from the Cardiovascular Health Study (CHS), a community-based cohort of adults aged ≥65 years who were followed from 1992-2015 (n = 4612). Associations of plasma Cer and SM species carrying long-chain (i.e., 16:0) and very-long-chain (i.e., 20:0, 22:0, 24:0) saturated fatty acids with mortality were assessed using Cox proportional hazards models. RESULTS: During a median follow-up of 10.2 years, 4099 deaths occurred. High concentrations of Cer and SM carrying fatty acid 16:0 were each associated with an increased risk of mortality. Conversely, high concentrations of several ceramide and sphingomyelin species carrying longer fatty acids were each associated with a decreased risk of mortality. The hazard ratios for total mortality per 2-fold difference in each Cer and SM species were: 1.89 (95% CI), 1.65-2.17 for Cer-16, 0.79 (95% CI, 0.70-0.88) for Cer-22, 0.74 (95% CI, 0.65-0.84) for Cer-24, 2.51 (95% CI, 2.01-3.14) for SM-16, 0.68 (95% CI, 0.58-0.79) for SM-20, 0.57 (95% CI, 0.49-0.67) for SM-22, and 0.66 (0.57-0.75) for SM-24. We found no association of Cer-20 with risk of death. CONCLUSIONS: Associations of Cer and SM with the risk of death differ according to the length of their acylated saturated fatty acid. Future studies are needed to explore mechanisms underlying these relationships.

Cumulative burden of clinically significant aortic stenosis in community-dwelling older adults. - Owens, David S; Bartz, Traci M; Bůzková, Petra; Massera, Daniele; Biggs, Mary L; Carlson, Selma D; Psaty, Bruce M; Sotoodehnia, Nona; Gottdiener, John S; Kizer, Jorge R (Heart, 2021)
OBJECTIVES: Current estimates of aortic stenosis (AS) frequency have mostly relied on cross-sectional echocardiographic or longitudinal administrative data, making understanding of AS burden incomplete. We performed case adjudications to evaluate the frequency of AS and assess differences by age, sex and race in an older cohort with long-term follow-up. METHODS: We developed case-capture methods using study echocardiograms, procedure and diagnosis codes, heart failure events and deaths for targeted review of medical records in the Cardiovascular Health Study to identify moderate or severe AS and related procedures or hospitalisations. The primary outcome was clinically significant AS (severe AS or procedure). Assessment of incident AS burden was based on subdistribution survival methods, while associations with age, sex and race relied on cause-specific survival methods. RESULTS: The cohort comprised 5795 participants (age 73±6, 42.2% male, 14.3% Black). Cumulative frequency of clinically significant AS at maximal 25-year follow-up was 3.69% (probable/definite) to 4.67% (possible/probable/definite), while the corresponding 20-year cumulative incidence was 2.88% to 3.71%. Of incident cases, about 85% had a hospitalisation for severe AS, but roughly half did not undergo valve intervention. The adjusted incidence of clinically significant AS was higher in men (HR 1.62 [95% CI 1.21 to 2.17]) and increased with age (HR 1.08 [95% CI 1.04 to 1.11]), but was lower in Blacks (HR 0.43 [95% CI 0.23 to 0.81]). CONCLUSIONS: In this community-based study, we identified a higher burden of clinically significant AS than reported previously, with differences by age, sex and race. These findings have important implications for public health resource planning, although the lower burden in Blacks merits further study.

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

Discovery and fine-mapping of height loci via high-density imputation of GWASs in individuals of African ancestry. - Graff, Mariaelisa; Justice, Anne E; Young, Kristin L; Marouli, Eirini; Zhang, Xinruo; Fine, Rebecca S; Lim, Elise; Buchanan, Victoria; Rand, Kristin; Feitosa, Mary F; Wojczynski, Mary K; Yanek, Lisa R; et al. (Am J Hum Genet, 2021)
Although many loci have been associated with height in European ancestry populations, very few have been identified in African ancestry individuals. Furthermore, many of the known loci have yet to be generalized to and fine-mapped within a large-scale African ancestry sample. We performed sex-combined and sex-stratified meta-analyses in up to 52,764 individuals with height and genome-wide genotyping data from the African Ancestry Anthropometry Genetics Consortium (AAAGC). We additionally combined our African ancestry meta-analysis results with published European genome-wide association study (GWAS) data. In the African ancestry analyses, we identified three novel loci (SLC4A3, NCOA2, ECD/FAM149B1) in sex-combined results and two loci (CRB1, KLF6) in women only. In the African plus European sex-combined GWAS, we identified an additional three novel loci (RCCD1, G6PC3, CEP95) which were equally driven by AAAGC and European results. Among 39 genome-wide significant signals at known loci, conditioning index SNPs from European studies identified 20 secondary signals. Two of the 20 new secondary signals and none of the 8 novel loci had minor allele frequencies (MAF) < 5%. Of 802 known European height signals, 643 displayed directionally consistent associations with height, of which 205 were nominally significant (p < 0.05) in the African ancestry sex-combined sample. Furthermore, 148 of 241 loci contained ≤20 variants in the credible sets that jointly account for 99% of the posterior probability of driving the associations. In summary, trans-ethnic meta-analyses revealed novel signals and further improved fine-mapping of putative causal variants in loci shared between African and European ancestry populations.

Epigenome-wide association study of serum urate reveals insights into urate co-regulation and the SLC2A9 locus. - Tin, Adrienne; Schlosser, Pascal; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Yu, Zhi; Weihs, Antoine; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Kuhns, Victoria L Halperin; et al. (Nat Commun, 2021)
Elevated serum urate levels, a complex trait and major risk factor for incident gout, are correlated with cardiometabolic traits via incompletely understood mechanisms. DNA methylation in whole blood captures genetic and environmental influences and is assessed in transethnic meta-analysis of epigenome-wide association studies (EWAS) of serum urate (discovery, n = 12,474, replication, n = 5522). The 100 replicated, epigenome-wide significant (p < 1.1E-7) CpGs explain 11.6% of the serum urate variance. At SLC2A9, the serum urate locus with the largest effect in genome-wide association studies (GWAS), five CpGs are associated with SLC2A9 gene expression. Four CpGs at SLC2A9 have significant causal effects on serum urate levels and/or gout, and two of these partly mediate the effects of urate-associated GWAS variants. In other genes, including SLC7A11 and PHGDH, 17 urate-associated CpGs are associated with conditions defining metabolic syndrome, suggesting that these CpGs may represent a blood DNA methylation signature of cardiometabolic risk factors. This study demonstrates that EWAS can provide new insights into GWAS loci and the correlation of serum urate with other complex traits.
Keywords: Amino Acid Transport System y+; Cohort Studies; CpG Islands; DNA Methylation; Epigenome; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Transport Proteins, Facilitative; Gout; Humans; Male; Uric Acid

FGL1 as a modulator of plasma D-dimer levels: Exome-wide marker analysis of plasma tPA, PAI-1, and D-dimer. - Thibord, Florian; Song, Ci; Pattee, Jack; Rodriguez, Benjamin A T; Chen, Ming-Huei; O'Donnell, Christopher J; Kleber, Marcus E; Delgado, Graciela E; Guo, Xiuqing; Yao, Jie; Taylor, Kent D; Ozel, Ayse Bilge; et al. (J Thromb Haemost, 2021)
BACKGROUND: Use of targeted exome-arrays with common, rare variants and functionally enriched variation has led to discovery of new genes contributing to population variation in risk factors. Plasminogen activator-inhibitor 1 (PAI-1), tissue plasminogen activator (tPA), and the plasma product D-dimer are important components of the fibrinolytic system. There have been few large-scale genome-wide or exome-wide studies of PAI-1, tPA, and D-dimer. OBJECTIVES: We sought to discover new genetic loci contributing to variation in these traits using an exome-array approach. METHODS: Cohort-level analyses and fixed effects meta-analyses of PAI-1 (n = 15 603), tPA (n = 6876,) and D-dimer (n = 19 306) from 12 cohorts of European ancestry with diverse study design were conducted, including single-variant analyses and gene-based burden testing. RESULTS: Five variants located in NME7, FGL1, and the fibrinogen locus, all associated with D-dimer levels, achieved genome-wide significance (P < 5 × 10 ). Replication was sought for these 5 variants, as well as 45 well-imputed variants with P < 1 × 10 in the discovery using an independent cohort. Replication was observed for three out of the five significant associations, including a novel and uncommon (0.013 allele frequency) coding variant p.Trp256Leu in FGL1 (fibrinogen-like-1) with increased plasma D-dimer levels. Additionally, a candidate-gene approach revealed a suggestive association for a coding variant (rs143202684-C) in SERPINB2, and suggestive associations with consistent effect in the replication analysis include an intronic variant (rs11057830-A) in SCARB1 associated with increased D-dimer levels. CONCLUSION: This work provides new evidence for a role of FGL1 in hemostasis.

Genetic insights into biological mechanisms governing human ovarian ageing. - Ruth, Katherine S; Day, Felix R; Hussain, Jazib; Martínez-Marchal, Ana; Aiken, Catherine E; Azad, Ajuna; Thompson, Deborah J; Knoblochova, Lucie; Abe, Hironori; Tarry-Adkins, Jane L; Gonzalez, Javier Martin; Fontanillas, Pierre; et al. (Nature, 2021)
Reproductive longevity is essential for fertility and influences healthy ageing in women, but insights into its underlying biological mechanisms and treatments to preserve it are limited. Here we identify 290 genetic determinants of ovarian ageing, assessed using normal variation in age at natural menopause (ANM) in about 200,000 women of European ancestry. These common alleles were associated with clinical extremes of ANM; women in the top 1% of genetic susceptibility have an equivalent risk of premature ovarian insufficiency to those carrying monogenic FMR1 premutations. The identified loci implicate a broad range of DNA damage response (DDR) processes and include loss-of-function variants in key DDR-associated genes. Integration with experimental models demonstrates that these DDR processes act across the life-course to shape the ovarian reserve and its rate of depletion. Furthermore, we demonstrate that experimental manipulation of DDR pathways highlighted by human genetics increases fertility and extends reproductive life in mice. Causal inference analyses using the identified genetic variants indicate that extending reproductive life in women improves bone health and reduces risk of type 2 diabetes, but increases the risk of hormone-sensitive cancers. These findings provide insight into the mechanisms that govern ovarian ageing, when they act, and how they might be targeted by therapeutic approaches to extend fertility and prevent disease.

Identification of Functional Genetic Determinants of Cardiac Troponin T and I in a Multiethnic Population and Causal Associations With Atrial Fibrillation. - Yang, Yunju; Bartz, Traci M; Brown, Michael R; Guo, Xiuqing; Zilhão, Nuno R; Trompet, Stella; Weiss, Stefan; Yao, Jie; Brody, Jennifer A; deFilippi, Christopher R; Hoogeveen, Ron C; Lin, Henry J; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: Elevated cardiac troponin levels in blood are associated with increased risk of cardiovascular diseases and mortality. Cardiac troponin levels are heritable, but their genetic architecture remains elusive. METHODS: We conducted a transethnic genome-wide association analysis on high-sensitivity cTnT (cardiac troponin T; hs-cTnT) and high-sensitivity cTnI (cardiac troponin I; hs-cTnI) levels in 24 617 and 14 336 participants free of coronary heart disease and heart failure from 6 population-based cohorts, followed by a series of bioinformatic analyses to decipher the genetic architecture of hs-cTnT and hs-cTnI. RESULTS: We identified 4 genome-wide significant loci for hs-cTnT including a novel locus rs3737882 in and 3 previously reported loci at , , and . One known locus at was replicated for hs-cTnI. One copy of C allele for rs3737882 was associated with a 6% increase in hs-cTnT levels (minor allele frequency, 0.18; =2.80×10). We observed pleiotropic loci located at and . The proportions of variances explained by single-nucleotide polymorphisms were 10.15% and 7.74% for hs-cTnT and hs-cTnI, respectively. Single-nucleotide polymorphisms were colocalized with expression in heart tissues and hs-cTnT and with expression in artery, heart tissues, and whole blood and both troponins. Mendelian randomization analyses showed that genetically increased hs-cTnT and hs-cTnI levels were associated with higher odds of atrial fibrillation (odds ratio, 1.38 [95% CI, 1.25-1.54] for hs-cTnT and 1.21 [95% CI, 1.06-1.37] for hs-cTnI). CONCLUSIONS: We identified a novel genetic locus associated with hs-cTnT in a multiethnic population and found that genetically regulated troponin levels were associated with atrial fibrillation.

Identification of novel and rare variants associated with handgrip strength using whole genome sequence data from the NHLBI Trans-Omics in Precision Medicine (TOPMed) Program. - Sarnowski, Chloe; Chen, Han; Biggs, Mary L; Wassertheil-Smoller, Sylvia; Bressler, Jan; Irvin, Marguerite R; Ryan, Kathleen A; Karasik, David; Arnett, Donna K; Cupples, L Adrienne; Fardo, David W; Gogarten, Stephanie M; et al. (PLoS One, 2021)
Handgrip strength is a widely used measure of muscle strength and a predictor of a range of morbidities including cardiovascular diseases and all-cause mortality. Previous genome-wide association studies of handgrip strength have focused on common variants primarily in persons of European descent. We aimed to identify rare and ancestry-specific genetic variants associated with handgrip strength by conducting whole-genome sequence association analyses using 13,552 participants from six studies representing diverse population groups from the Trans-Omics in Precision Medicine (TOPMed) Program. By leveraging multiple handgrip strength measures performed in study participants over time, we increased our effective sample size by 7-12%. Single-variant analyses identified ten handgrip strength loci among African-Americans: four rare variants, five low-frequency variants, and one common variant. One significant and four suggestive genes were identified associated with handgrip strength when aggregating rare and functional variants; all associations were ancestry-specific. We additionally leveraged the different ancestries available in the UK Biobank to further explore the ancestry-specific association signals from the single-variant association analyses. In conclusion, our study identified 11 new loci associated with handgrip strength with rare and/or ancestry-specific genetic variations, highlighting the added value of whole-genome sequencing in diverse samples. Several of the associations identified using single-variant or aggregate analyses lie in genes with a function relevant to the brain or muscle or were reported to be associated with muscle or age-related traits. Further studies in samples with sequence data and diverse ancestries are needed to confirm these findings.

Longitudinal Plasma Measures of Trimethylamine N-Oxide and Risk of Atherosclerotic Cardiovascular Disease Events in Community-Based Older Adults. - Lee, Yujin; Nemet, Ina; Wang, Zeneng; Lai, Heidi T M; de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Fretts, Amanda M; Sotoodehnia, Nona; Budoff, Matthew; DiDonato, Joseph A; McKnight, Barbara; Tang, W H Wilson; et al. (J Am Heart Assoc, 2021)
Background Trimethylamine N-oxide (TMAO) is a gut microbiota-dependent metabolite of dietary choline, L-carnitine, and phosphatidylcholine-rich foods. On the basis of experimental studies and patients with prevalent disease, elevated plasma TMAO may increase risk of atherosclerotic cardiovascular disease (ASCVD). TMAO is also renally cleared and may interact with and causally contribute to renal dysfunction. Yet, how serial TMAO levels relate to incident and recurrent ASCVD in community-based populations and the potential mediating or modifying role of renal function are not established. Methods and Results We investigated associations of serial measures of plasma TMAO, assessed at baseline and 7 years, with incident and recurrent ASCVD in a community-based cohort of 4131 (incident) and 1449 (recurrent) older US adults. TMAO was measured using stable isotope dilution liquid chromatography-tandem mass spectrometry (laboratory coefficient of variation, <6%). Incident ASCVD (myocardial infarction, fatal coronary heart disease, stroke, sudden cardiac death, or other atherosclerotic death) was centrally adjudicated using medical records. Risk was assessed by multivariable Cox proportional hazards regression, including time-varying demographics, lifestyle factors, medical history, laboratory measures, and dietary habits. Potential mediating effects and interaction by estimated glomerular filtration rate (eGFR) were assessed. During prospective follow-up, 1766 incident and 897 recurrent ASCVD events occurred. After multivariable adjustment, higher levels of TMAO were associated with a higher risk of incident ASCVD, with extreme quintile hazard ratio (HR) compared with the lowest quintile=1.21 (95% CI, 1.02-1.42; -trend=0.029). This relationship appeared mediated or confounded by eGFR (eGFR-adjusted HR, 1.07; 95% CI, 0.90-1.27), as well as modified by eGFR (-interaction <0.001). High levels of TMAO were associated with higher incidence of ASCVD in the presence of impaired renal function (eGFR <60 mL/min per 1.73 m: HR, 1.56 [95% CI, 1.13-2.14]; -trend=0.007), but not normal or mildly reduced renal function (eGFR ≥60 mL/min per 1.73 m: HR, 1.03 [95% CI, 0.85-1.25]; -trend=0.668). Among individuals with prior ASCVD, TMAO associated with higher risk of recurrent ASCVD (HR, 1.25 [95% CI, 1.01-1.56]; -trend=0.009), without significant modification by eGFR. Conclusions In this large community-based cohort of older US adults, serial measures of TMAO were associated with higher risk of incident ASCVD, with apparent modification by presence of impaired renal function and with higher risk of recurrent ASCVD.

Meta-analyses identify DNA methylation associated with kidney function and damage. - Schlosser, Pascal; Tin, Adrienne; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Weihs, Antoine; Yu, Zhi; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Adeyemo, Adebowale A; et al. (Nat Commun, 2021)
Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated with the respective trait. The majority of these findings showed directionally consistent associations with the respective clinical outcomes chronic kidney disease and moderately increased albuminuria. Associations of DNA methylation with kidney function, such as CpGs at JAZF1, PELI1 and CHD2 were validated in kidney tissue. Methylation at PHRF1, LDB2, CSRNP1 and IRF5 indicated causal effects on kidney function. Enrichment analyses revealed pathways related to hemostasis and blood cell migration for estimated glomerular filtration rate, and immune cell activation and response for urinary albumin-to-creatinineratio-associated CpGs.
Keywords: Adult; Aged; CpG Islands; DNA Methylation; Female; Glomerular Filtration Rate; Humans; Interferon Regulatory Factors; Kidney; Kidney Function Tests; LIM Domain Proteins; Male; Membrane Proteins; Middle Aged; Renal Insufficiency, Chronic; Transcription Factors

Meta-analysis of epigenome-wide association studies of carotid intima-media thickness. - Portilla-Fernández, Eliana; Hwang, Shih-Jen; Wilson, Rory; Maddock, Jane; Hill, W David; Teumer, Alexander; Mishra, Pashupati P; Brody, Jennifer A; Joehanes, Roby; Ligthart, Symen; Ghanbari, Mohsen; Kavousi, Maryam; et al. (Eur J Epidemiol, 2021)
Common carotid intima-media thickness (cIMT) is an index of subclinical atherosclerosis that is associated with ischemic stroke and coronary artery disease (CAD). We undertook a cross-sectional epigenome-wide association study (EWAS) of measures of cIMT in 6400 individuals. Mendelian randomization analysis was applied to investigate the potential causal role of DNA methylation in the link between atherosclerotic cardiovascular risk factors and cIMT or clinical cardiovascular disease. The CpG site cg05575921 was associated with cIMT (beta = -0.0264, p value = 3.5 × 10) in the discovery panel and was replicated in replication panel (beta = -0.07, p value = 0.005). This CpG is located at chr5:81649347 in the intron 3 of the aryl hydrocarbon receptor repressor gene (AHRR). Our results indicate that DNA methylation at cg05575921 might be in the pathway between smoking, cIMT and stroke. Moreover, in a region-based analysis, 34 differentially methylated regions (DMRs) were identified of which a DMR upstream of ALOX12 showed the strongest association with cIMT (p value = 1.4 × 10). In conclusion, our study suggests that DNA methylation may play a role in the link between cardiovascular risk factors, cIMT and clinical cardiovascular disease.

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

Multi-ancestry genome-wide gene-sleep interactions identify novel loci for blood pressure. - Wang, Heming; Noordam, Raymond; Cade, Brian E; Schwander, Karen; Winkler, Thomas W; Lee, Jiwon; Sung, Yun Ju; Bentley, Amy R; Manning, Alisa K; Aschard, Hugues; Kilpeläinen, Tuomas O; Ilkov, Marjan; et al. (Mol Psychiatry, 2021)
Long and short sleep duration are associated with elevated blood pressure (BP), possibly through effects on molecular pathways that influence neuroendocrine and vascular systems. To gain new insights into the genetic basis of sleep-related BP variation, we performed genome-wide gene by short or long sleep duration interaction analyses on four BP traits (systolic BP, diastolic BP, mean arterial pressure, and pulse pressure) across five ancestry groups in two stages using 2 degree of freedom (df) joint test followed by 1df test of interaction effects. Primary multi-ancestry analysis in 62,969 individuals in stage 1 identified three novel gene by sleep interactions that were replicated in an additional 59,296 individuals in stage 2 (stage 1 + 2 P < 5 × 10), including rs7955964 (FIGNL2/ANKRD33) that increases BP among long sleepers, and rs73493041 (SNORA26/C9orf170) and rs10406644 (KCTD15/LSM14A) that increase BP among short sleepers (P < 5 × 10). Secondary ancestry-specific analysis identified another novel gene by long sleep interaction at rs111887471 (TRPC3/KIAA1109) in individuals of African ancestry (P = 2 × 10). Combined stage 1 and 2 analyses additionally identified significant gene by long sleep interactions at 10 loci including MKLN1 and RGL3/ELAVL3 previously associated with BP, and significant gene by short sleep interactions at 10 loci including C2orf43 previously associated with BP (P < 10). 2df test also identified novel loci for BP after modeling sleep that has known functions in sleep-wake regulation, nervous and cardiometabolic systems. This study indicates that sleep and primary mechanisms regulating BP may interact to elevate BP level, suggesting novel insights into sleep-related BP regulation.

Multiethnic Genome-Wide Association Study of Subclinical Atherosclerosis in Individuals With Type 2 Diabetes. - Lu, Yingchang; Dimitrov, Latchezar; Chen, Shyh-Huei; Bielak, Lawrence F; Bis, Joshua C; Feitosa, Mary F; Lu, Lingyi; Kavousi, Maryam; Raffield, Laura M; Smith, Albert V; Wang, Lihua; Weiss, Stefan; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: Coronary artery calcification (CAC) and carotid artery intima-media thickness (cIMT) are measures of subclinical atherosclerosis in asymptomatic individuals and strong risk factors for cardiovascular disease. Type 2 diabetes (T2D) is an independent cardiovascular disease risk factor that accelerates atherosclerosis. METHODS: We performed meta-analyses of genome-wide association studies in up to 2500 T2D individuals of European ancestry (EA) and 1590 T2D individuals of African ancestry with or without exclusion of prevalent cardiovascular disease, for CAC measured by cardiac computed tomography, and 3608 individuals of EA and 838 individuals of African ancestry with T2D for cIMT measured by ultrasonography within the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium. RESULTS: We replicated 2 loci (rs9369640 and rs9349379 near and rs10757278 near ) for CAC and one locus for cIMT (rs7412 and rs445925 near ) that were previously reported in the general EA populations. We identified one novel CAC locus (rs8000449 near at 13q13.3) at =2.0×10 in EA. No additional loci were identified with the meta-analyses of EA and African ancestry. The expression quantitative trait loci analysis with nearby expressed genes derived from arterial wall and metabolic tissues from the Genotype-Tissue Expression project pinpoints , encoding a matricellular protein involved in bone formation and bone matrix organization, as the potential candidate gene at this locus. In addition, we found significant associations (<3.1×10) for 3 previously reported coronary artery disease loci for these subclinical atherosclerotic phenotypes (rs2891168 near and rs11170820 near for CAC, and rs7412 near for cIMT). CONCLUSIONS: Our results provide potential biological mechanisms that could link CAC and cIMT to increased cardiovascular disease risk in individuals with T2D.

is mutated in clonal hematopoiesis and myelodysplastic syndromes and impacts RNA splicing. - Beauchamp, Ellen M; Leventhal, Matthew; Bernard, Elsa; Hoppe, Emma R; Todisco, Gabriele; Creignou, Maria; Gallì, Anna; Castellano, Cecilia A; McConkey, Marie; Tarun, Akansha; Wong, Waihay; Schenone, Monica; et al. (Blood Cancer Discov, 2021)
Clonal hematopoiesis results from somatic mutations in cancer driver genes in hematopoietic stem cells. We sought to identify novel drivers of clonal expansion using an unbiased analysis of sequencing data from 84,683 persons and identified common mutations in the 5-methylcytosine reader, , as well as in , , and . We also identified these mutations at low frequency in myelodysplastic syndrome patients. edited mouse hematopoietic stem and progenitor cells exhibited a competitive advantage and increased genome-wide intron retention. mutations potentially link DNA methylation and RNA splicing, the two most commonly mutated pathways in clonal hematopoiesis and MDS.

Natural killer cells, gamma delta T cells and classical monocytes are associated with systolic blood pressure in the multi-ethnic study of atherosclerosis (MESA). - Delaney, Joseph A C; Olson, Nels C; Sitlani, Colleen M; Fohner, Alison E; Huber, Sally A; Landay, Alan L; Heckbert, Susan R; Tracy, Russell P; Psaty, Bruce M; Feinstein, Matt; Doyle, Margaret F (BMC Cardiovasc Disord, 2021)
BACKGROUND: Hypertension is a major source of cardiovascular morbidity and mortality. Recent evidence from mouse models, genetic, and cross-sectional human studies suggest increased proportions of selected immune cell subsets may be associated with levels of systolic blood pressure (SBP). METHODS: We assayed immune cells from cryopreserved samples collected at the baseline examination (2000-2002) from 1195 participants from the multi-ethnic study of atherosclerosis (MESA). We used linear mixed models, with adjustment for age, sex, race/ethnicity, smoking, exercise, body mass index, education, diabetes, and cytomegalovirus titers, to estimate the associations between 30 immune cell subsets (4 of which were a priori hypotheses) and repeated measures of SBP (baseline and up to four follow-up measures) over 10 years. The analysis provides estimates of the association with blood pressure level. RESULTS: The mean age of the MESA participants at baseline was 64 ± 10 years and 53% were male. A one standard deviation (1-SD) increment in the proportion of γδ T cells was associated with 2.40 mmHg [95% confidence interval (CI) 1.34-3.42] higher average systolic blood pressure; and for natural killer cells, a 1-SD increment was associated with 1.88 mmHg (95% CI 0.82-2.94) higher average level of systolic blood pressure. A 1-SD increment in classical monocytes (CD14CD16) was associated with 2.01 mmHG (95% CI 0.79-3.24) lower average systolic blood pressure. There were no associations of CD4 T helper cell subsets with average systolic blood pressure. CONCLUSION: These findings suggest that the innate immune system plays a role in levels of SBP whereas there were no associations with adaptive immune cells.

The Pharmacogenetics of Statin Therapy on Clinical Events: No Evidence that Genetic Variation Affects Statin Response on Myocardial Infarction. - Trompet, Stella; Postmus, Iris; Warren, Helen R; Noordam, Raymond; Smit, Roelof A J; Theusch, Elizabeth; Li, Xiaohui; Arsenault, Benoit; Chasman, Daniel I; Hitman, Graham A; Munroe, Patricia B; Rotter, Jerome I; et al. (Front Pharmacol, 2021)
The pharmacogenetic effect on cardiovascular disease reduction in response to statin treatment has only been assessed in small studies. In a pharmacogenetic genome wide association study (GWAS) analysis within the Genomic Investigation of Statin Therapy (GIST) consortium, we investigated whether genetic variation was associated with the response of statins on cardiovascular disease risk reduction. The investigated endpoint was incident myocardial infarction (MI) defined as coronary heart disease death and definite and suspect non-fatal MI. For imputed single nucleotide polymorphisms (SNPs), regression analysis was performed on expected allelic dosage and meta-analysed with a fixed-effects model, inverse variance weighted meta-analysis. All SNPs with -values <5.0 × 10 in stage 1 GWAS meta-analysis were selected for further investigation in stage-2. As a secondary analysis, we extracted SNPs from the Stage-1 GWAS meta-analysis results based on predefined hypotheses to possibly modifying the effect of statin therapy on MI. In stage-1 meta-analysis (eight studies, = 10,769, 4,212 cases), we observed no genome-wide significant results ( < 5.0 × 10). A total of 144 genetic variants were followed-up in the second stage (three studies, = 1,525, 180 cases). In the combined meta-analysis, no genome-wide significant hits were identified. Moreover, none of the look-ups of SNPs known to be associated with either CHD or with statin response to cholesterol levels reached Bonferroni level of significance within our stage-1 meta-analysis. This GWAS analysis did not provide evidence that genetic variation affects statin response on cardiovascular risk reduction. It does not appear likely that genetic testing for predicting effects of statins on clinical events will become a useful tool in clinical practice.

Premature ventricular complexes and development of heart failure in a community-based population. - Limpitikul, Worawan B; Dewland, Thomas A; Vittinghoff, Eric; Soliman, Elsayed; Nah, Gregory; Fang, Christina; Siscovick, David S; Psaty, Bruce M; Sotoodehnia, Nona; Heckbert, Susan; Stein, Phyllis K; Gottdiener, John; et al. (Heart, 2021)
OBJECTIVE: A higher premature ventricular complex (PVC) frequency is associated with incident congestive heart failure (CHF) and death. While certain PVC characteristics may contribute to that risk, the current literature stems from patients in medical settings and is therefore prone to referral bias. This study aims to identify PVC characteristics associated with incident CHF in a community-based setting. METHODS: The Cardiovascular Health Study is a cohort of community-dwelling individuals who underwent prospective evaluation and follow-up. We analysed 24-hour Holter data to assess PVC characteristics and used multivariable logistic and Cox proportional hazards models to identify predictors of a left ventricular ejection fraction (LVEF) decline and incident CHF, respectively. RESULTS: Of 871 analysed participants, 316 participants exhibited at least 10 PVCs during the 24-hour recording. For participants with PVCs, the average age was 72±5 years, 41% were women and 93% were white. Over a median follow-up of 11 years, 34% developed CHF. After adjusting for demographics, cardiovascular comorbidities, antiarrhythmic drug use and PVC frequency, a greater heterogeneity of the PVC coupling interval was associated with an increased risk of LVEF decline and incident CHF. Of note, neither PVC duration nor coupling interval duration exhibited a statistically significant relationship with either outcome. CONCLUSIONS: In this first community-based study to identify Holter-based features of PVCs that are associated with LVEF reduction and incident CHF, the fact that coupling interval heterogeneity was an independent risk factor suggests that the mechanism of PVC generation may influence the risk of heart failure.

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.

Silent Myocardial Infarction and Subsequent Ischemic Stroke in the Cardiovascular Health Study. - Merkler, Alexander E; Bartz, Traci M; Kamel, Hooman; Soliman, Elsayed Z; Howard, Virginia; Psaty, Bruce M; Okin, Peter M; Safford, Monika M; Elkind, Mitchell S V; Longstreth, W T (Neurology, 2021)
OBJECTIVE: To test the hypothesis that silent MI is a risk factor for ischemic stroke, we evaluated the association between silent MI and subsequent ischemic stroke in the Cardiovascular Health Study. METHODS: The Cardiovascular Health Study prospectively enrolled community-dwelling individuals ≥65 years of age. We included participants without prevalent stroke or baseline evidence of MI. Our exposures were silent and clinically apparent, overt MI. Silent MI was defined as new evidence of Q-wave MI, without clinical symptoms of MI, on ECGs performed during annual study visits from 1989-1999. The primary outcome was incident ischemic stroke. Secondary outcomes were ischemic stroke subtypes: non-lacunar, lacunar, and other/unknown. Cox proportional hazards analysis was used to model the association between time-varying MI status (silent, overt, or no MI) and stroke after adjustment for baseline demographics and vascular risk factors. RESULTS: Among 4,224 participants, 362 (8.6%) had an incident silent MI, 421 (10.0%) an incident overt MI, and 377 (8.9%) an incident ischemic stroke during a median follow-up of 9.8 years. After adjustment for demographics and comorbidities, silent MI was independently associated with subsequent ischemic stroke (HR, 1.51; 95% CI, 1.03-2.21). Overt MI was associated with ischemic stroke both in the short term (HR, 80; 95% CI, 53-119) and long term (HR, 1.60; 95% CI, 1.04-2.44). In secondary analyses, the association between silent MI and stroke was limited to non-lacunar ischemic stroke (HR 2.40; 95% CI, 1.36-4.22). CONCLUSION: In a community-based sample, we found an association between silent MI and ischemic stroke.

Sugar-Sweetened Beverage Consumption May Modify Associations Between Genetic Variants in the CHREBP (Carbohydrate Responsive Element Binding Protein) Locus and HDL-C (High-Density Lipoprotein Cholesterol) and Triglyceride Concentrations. - Haslam, Danielle E; Peloso, Gina M; Guirette, Melanie; Imamura, Fumiaki; Bartz, Traci M; Pitsillides, Achilleas N; Wang, Carol A; Li-Gao, Ruifang; Westra, Jason M; Pitkänen, Niina; Young, Kristin L; Graff, Mariaelisa; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: ChREBP (carbohydrate responsive element binding protein) is a transcription factor that responds to sugar consumption. Sugar-sweetened beverage (SSB) consumption and genetic variants in the locus have separately been linked to HDL-C (high-density lipoprotein cholesterol) and triglyceride concentrations. We hypothesized that SSB consumption would modify the association between genetic variants in the locus and dyslipidemia. METHODS: Data from 11 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (N=63 599) and the UK Biobank (N=59 220) were used to quantify associations of SSB consumption, genetic variants, and their interaction on HDL-C and triglyceride concentrations using linear regression models. A total of 1606 single nucleotide polymorphisms within or near were considered. SSB consumption was estimated from validated questionnaires, and participants were grouped by their estimated intake. RESULTS: In a meta-analysis, rs71556729 was significantly associated with higher HDL-C concentrations only among the highest SSB consumers (β, 2.12 [95% CI, 1.16-3.07] mg/dL per allele; <0.0001), but not significantly among the lowest SSB consumers (=0.81; <0.0001). Similar results were observed for 2 additional variants (rs35709627 and rs71556736). For triglyceride, rs55673514 was positively associated with triglyceride concentrations only among the highest SSB consumers (β, 0.06 [95% CI, 0.02-0.09] ln-mg/dL per allele, =0.001) but not the lowest SSB consumers (=0.84; =0.0005). CONCLUSIONS: Our results identified genetic variants in the locus that may protect against SSB-associated reductions in HDL-C and other variants that may exacerbate SSB-associated increases in triglyceride concentrations. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT00005133, NCT00005121, NCT00005487, and NCT00000479.

Supplemental Association of Clonal Hematopoiesis With Incident Heart Failure. - Yu, Bing; Roberts, Mary B; Raffield, Laura M; Zekavat, Seyedeh Maryam; Nguyen, Ngoc Quynh H; Biggs, Mary L; Brown, Michael R; Griffin, Gabriel; Desai, Pinkal; Correa, Adolfo; Morrison, Alanna C; Shah, Amil M; et al. (J Am Coll Cardiol, 2021)
BACKGROUND: Age-related clonal hematopoiesis of indeterminate potential (CHIP), defined as clonally expanded leukemogenic sequence variations (particularly in DNMT3A, TET2, ASXL1, and JAK2) in asymptomatic individuals, is associated with cardiovascular events, including recurrent heart failure (HF). OBJECTIVES: This study sought to evaluate whether CHIP is associated with incident HF. METHODS: CHIP status was obtained from whole exome or genome sequencing of blood DNA in participants without prevalent HF or hematological malignancy from 5 cohorts. Cox proportional hazards models were performed within each cohort, adjusting for demographic and clinical risk factors, followed by fixed-effect meta-analyses. Large CHIP clones (defined as variant allele frequency >10%), HF with or without baseline coronary heart disease, and left ventricular ejection fraction were evaluated in secondary analyses. RESULTS: Of 56,597 individuals (59% women, mean age 58 years at baseline), 3,406 (6%) had CHIP, and 4,694 developed HF (8.3%) over up to 20 years of follow-up. CHIP was prospectively associated with a 25% increased risk of HF in meta-analysis (hazard ratio: 1.25; 95% confidence interval: 1.13-1.38) with consistent associations across cohorts. ASXL1, TET2, and JAK2 sequence variations were each associated with an increased risk of HF, whereas DNMT3A sequence variations were not associated with HF. Secondary analyses suggested large CHIP was associated with a greater risk of HF (hazard ratio: 1.29; 95% confidence interval: 1.15-1.44), and the associations for CHIP on HF with and without prior coronary heart disease were homogenous. ASXL1 sequence variations were associated with reduced left ventricular ejection fraction. CONCLUSIONS: CHIP, particularly sequence variations in ASXL1, TET2, and JAK2, represents a new risk factor for HF.
Keywords: Aged; Clonal Hematopoiesis; Correlation of Data; Demography; DNA-Binding Proteins; Female; Heart Failure; Humans; Janus Kinase 2; Male; Middle Aged; Mutation; Proportional Hazards Models; Proto-Oncogene Proteins; Repressor Proteins; Risk Factors; Stroke Volume; Ventricular Dysfunction, Left; Whole Exome Sequencing

A System for Phenotype Harmonization in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. - Stilp, Adrienne M; Emery, Leslie S; Broome, Jai G; Buth, Erin J; Khan, Alyna T; Laurie, Cecelia A; Wang, Fei Fei; Wong, Quenna; Chen, Dongquan; D'Augustine, Catherine M; Heard-Costa, Nancy L; Hohensee, Chancellor R; et al. (Am J Epidemiol, 2021)
Genotype-phenotype association studies often combine phenotype data from multiple studies to increase power. Harmonization of the data usually requires substantial effort due to heterogeneity in phenotype definitions, study design, data collection procedures, and data set organization. Here we describe a centralized system for phenotype harmonization that includes input from phenotype domain and study experts, quality control, documentation, reproducible results, and data sharing mechanisms. This system was developed for the National Heart, Lung and Blood Institute's Trans-Omics for Precision Medicine program, which is generating genomic and other omics data for >80 studies with extensive phenotype data. To date, 63 phenotypes have been harmonized across thousands of participants from up to 17 studies per phenotype (participants recruited 1948-2012). We discuss challenges in this undertaking and how they were addressed. The harmonized phenotype data and associated documentation have been submitted to National Institutes of Health data repositories for controlled-access by the scientific community. We also provide materials to facilitate future harmonization efforts by the community, which include (1) the code used to generate the 63 harmonized phenotypes, enabling others to reproduce, modify or extend these harmonizations to additional studies; and (2) results of labeling thousands of phenotype variables with controlled vocabulary terms.

Whole genome sequence analyses of eGFR in 23,732 people representing multiple ancestries in the NHLBI trans-omics for precision medicine (TOPMed) consortium. - Lin, Bridget M; Grinde, Kelsey E; Brody, Jennifer A; Breeze, Charles E; Raffield, Laura M; Mychaleckyj, Josyf C; Thornton, Timothy A; Perry, James A; Baier, Leslie J; de Las Fuentes, Lisa; Guo, Xiuqing; Heavner, Benjamin D; et al. (EBioMedicine, 2021)
BACKGROUND: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS: We combined whole genome sequencing (WGS) data from 23,732 participants from 10 NHLBI Trans-Omics for Precision Medicine (TOPMed) Program multi-ethnic studies to identify novel loci for estimated glomerular filtration rate (eGFR). Participants included European, African, East Asian, and Hispanic ancestries. We applied linear mixed models using a genetic relationship matrix estimated from the WGS data and adjusted for age, sex, study, and ethnicity. FINDINGS: When testing single variants, we identified three novel loci driven by low frequency variants more commonly observed in non-European ancestry (PRKAA2, rs180996919, minor allele frequency [MAF] 0.04%, P = 6.1 × 10; METTL8, rs116951054, MAF 0.09%, P = 4.5 × 10; and MATK, rs539182790, MAF 0.05%, P = 3.4 × 10). We also replicated two known loci for common variants (rs2461702, MAF=0.49, P = 1.2 × 10, nearest gene GATM, and rs71147340, MAF=0.34, P = 3.3 × 10, CDK12). Testing aggregated variants within a gene identified the MAF gene. A statistical approach based on local ancestry helped to identify replication samples for ancestry-specific variants. INTERPRETATION: This study highlights challenges in studying variants influencing kidney traits that are low frequency in populations and more common in non-European ancestry.

Whole genome sequence analysis of platelet traits in the NHLBI trans-omics for precision medicine initiative. - Little, Amarise; Hu, Yao; Sun, Quan; Jain, Deepti; Broome, Jai; Chen, Ming-Huei; Thibord, Florian; McHugh, Caitlin; Surendran, Praveen; Blackwell, Thomas W; Brody, Jennifer A; Bhan, Arunoday; et al. (Hum Mol Genet, 2021)
Platelets play a key role in thrombosis and hemostasis. Platelet count (PLT) and mean platelet volume (MPV) are highly heritable quantitative traits, with hundreds of genetic signals previously identified, mostly in European ancestry populations. We here utilize whole genome sequencing from NHLBI's Trans-Omics for Precision Medicine Initiative (TOPMed) in a large multi-ethnic sample to further explore common and rare variation contributing to PLT (n = 61 200) and MPV (n = 23 485). We identified and replicated secondary signals at MPL (rs532784633) and PECAM1 (rs73345162), both more common in African ancestry populations. We also observed rare variation in Mendelian platelet related disorder genes influencing variation in platelet traits in TOPMed cohorts (not enriched for blood disorders). For example, association of GP9 with lower PLT and higher MPV was partly driven by a pathogenic Bernard-Soulier syndrome variant (rs5030764, p.Asn61Ser), and the signals at TUBB1 and CD36 were partly driven by loss of function variants not annotated as pathogenic in ClinVar (rs199948010 and rs571975065). However, residual signal remained for these gene-based signals after adjusting for lead variants, suggesting that additional variants in Mendelian genes with impacts in general population cohorts remain to be identified. Gene-based signals were also identified at several GWAS identified loci for genes not annotated for Mendelian platelet disorders (PTPRH, TET2, CHEK2), with somatic variation driving the result at TET2. These results highlight the value of whole genome sequencing in populations of diverse genetic ancestry to identify novel regulatory and coding signals, even for well-studied traits like platelet traits.

Whole-genome association analyses of sleep-disordered breathing phenotypes in the NHLBI TOPMed program. - Cade, Brian E; Lee, Jiwon; Sofer, Tamar; Wang, Heming; Zhang, Man; Chen, Han; Gharib, Sina A; Gottlieb, Daniel J; Guo, Xiuqing; Lane, Jacqueline M; Liang, Jingjing; Lin, Xihong; et al. (Genome Med, 2021)
BACKGROUND: Sleep-disordered breathing is a common disorder associated with significant morbidity. The genetic architecture of sleep-disordered breathing remains poorly understood. Through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program, we performed the first whole-genome sequence analysis of sleep-disordered breathing. METHODS: The study sample was comprised of 7988 individuals of diverse ancestry. Common-variant and pathway analyses included an additional 13,257 individuals. We examined five complementary traits describing different aspects of sleep-disordered breathing: the apnea-hypopnea index, average oxyhemoglobin desaturation per event, average and minimum oxyhemoglobin saturation across the sleep episode, and the percentage of sleep with oxyhemoglobin saturation < 90%. We adjusted for age, sex, BMI, study, and family structure using MMSKAT and EMMAX mixed linear model approaches. Additional bioinformatics analyses were performed with MetaXcan, GIGSEA, and ReMap. RESULTS: We identified a multi-ethnic set-based rare-variant association (p = 3.48 × 10) on chromosome X with ARMCX3. Additional rare-variant associations include ARMCX3-AS1, MRPS33, and C16orf90. Novel common-variant loci were identified in the NRG1 and SLC45A2 regions, and previously associated loci in the IL18RAP and ATP2B4 regions were associated with novel phenotypes. Transcription factor binding site enrichment identified associations with genes implicated with respiratory and craniofacial traits. Additional analyses identified significantly associated pathways. CONCLUSIONS: We have identified the first gene-based rare-variant associations with objectively measured sleep-disordered breathing traits. Our results increase the understanding of the genetic architecture of sleep-disordered breathing and highlight associations in genes that modulate lung development, inflammation, respiratory rhythmogenesis, and HIF1A-mediated hypoxic response.

Whole-genome sequencing association analysis of quantitative red blood cell phenotypes: The NHLBI TOPMed program. - Hu, Yao; Stilp, Adrienne M; McHugh, Caitlin P; Rao, Shuquan; Jain, Deepti; Zheng, Xiuwen; Lane, John; Méric de Bellefon, Sébastian; Raffield, Laura M; Chen, Ming-Huei; Yanek, Lisa R; Wheeler, Marsha; et al. (Am J Hum Genet, 2021)
Whole-genome sequencing (WGS), a powerful tool for detecting novel coding and non-coding disease-causing variants, has largely been applied to clinical diagnosis of inherited disorders. Here we leveraged WGS data in up to 62,653 ethnically diverse participants from the NHLBI Trans-Omics for Precision Medicine (TOPMed) program and assessed statistical association of variants with seven red blood cell (RBC) quantitative traits. We discovered 14 single variant-RBC trait associations at 12 genomic loci, which have not been reported previously. Several of the RBC trait-variant associations (RPN1, ELL2, MIDN, HBB, HBA1, PIEZO1, and G6PD) were replicated in independent GWAS datasets imputed to the TOPMed reference panel. Most of these discovered variants are rare/low frequency, and several are observed disproportionately among non-European Ancestry (African, Hispanic/Latino, or East Asian) populations. We identified a 3 bp indel p.Lys2169del (g.88717175_88717177TCT[4]) (common only in the Ashkenazi Jewish population) of PIEZO1, a gene responsible for the Mendelian red cell disorder hereditary xerocytosis (MIM: 194380), associated with higher mean corpuscular hemoglobin concentration (MCHC). In stepwise conditional analysis and in gene-based rare variant aggregated association analysis, we identified several of the variants in HBB, HBA1, TMPRSS6, and G6PD that represent the carrier state for known coding, promoter, or splice site loss-of-function variants that cause inherited RBC disorders. Finally, we applied base and nuclease editing to demonstrate that the sentinel variant rs112097551 (nearest gene RPN1) acts through a cis-regulatory element that exerts long-range control of the gene RUVBL1 which is essential for hematopoiesis. Together, these results demonstrate the utility of WGS in ethnically diverse population-based samples and gene editing for expanding knowledge of the genetic architecture of quantitative hematologic traits and suggest a continuum between complex trait and Mendelian red cell disorders.
Keywords: Adult; Aged; Chromosomes, Human, Pair 16; Datasets as Topic; Erythrocytes; Female; Gene Editing; Genetic Variation; Genome-Wide Association Study; HEK293 Cells; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Quality Control; Reproducibility of Results; United States

Whole-genome sequencing in diverse subjects identifies genetic correlates of leukocyte traits: The NHLBI TOPMed program. - Mikhaylova, Anna V; McHugh, Caitlin P; Polfus, Linda M; Raffield, Laura M; Boorgula, Meher Preethi; Blackwell, Thomas W; Brody, Jennifer A; Broome, Jai; Chami, Nathalie; Chen, Ming-Huei; Conomos, Matthew P; Cox, Corey; et al. (Am J Hum Genet, 2021)
Many common and rare variants associated with hematologic traits have been discovered through imputation on large-scale reference panels. However, the majority of genome-wide association studies (GWASs) have been conducted in Europeans, and determining causal variants has proved challenging. We performed a GWAS of total leukocyte, neutrophil, lymphocyte, monocyte, eosinophil, and basophil counts generated from 109,563,748 variants in the autosomes and the X chromosome in the Trans-Omics for Precision Medicine (TOPMed) program, which included data from 61,802 individuals of diverse ancestry. We discovered and replicated 7 leukocyte trait associations, including (1) the association between a chromosome X, pseudo-autosomal region (PAR), noncoding variant located between cytokine receptor genes (CSF2RA and CLRF2) and lower eosinophil count; and (2) associations between single variants found predominantly among African Americans at the S1PR3 (9q22.1) and HBB (11p15.4) loci and monocyte and lymphocyte counts, respectively. We further provide evidence indicating that the newly discovered eosinophil-lowering chromosome X PAR variant might be associated with reduced susceptibility to common allergic diseases such as atopic dermatitis and asthma. Additionally, we found a burden of very rare FLT3 (13q12.2) variants associated with monocyte counts. Together, these results emphasize the utility of whole-genome sequencing in diverse samples in identifying associations missed by European-ancestry-driven GWASs.
Keywords: Asthma; Biomarkers; Dermatitis, Atopic; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Leukocytes; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Prognosis; Proteome; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; United Kingdom; United States; Whole Genome Sequencing

Assessing the contribution of rare variants to complex trait heritability from whole-genome sequence data. - Wainschtein, Pierrick; Jain, Deepti; Zheng, Zhili; Cupples, L Adrienne; Shadyab, Aladdin H; McKnight, Barbara; Shoemaker, Benjamin M; Mitchell, Braxton D; Psaty, Bruce M; Kooperberg, Charles; Liu, Ching-Ti; Albert, Christine M; et al. (Nat Genet, 2022)
Analyses of data from genome-wide association studies on unrelated individuals have shown that, for human traits and diseases, approximately one-third to two-thirds of heritability is captured by common SNPs. However, it is not known whether the remaining heritability is due to the imperfect tagging of causal variants by common SNPs, in particular whether the causal variants are rare, or whether it is overestimated due to bias in inference from pedigree data. Here we estimated heritability for height and body mass index (BMI) from whole-genome sequence data on 25,465 unrelated individuals of European ancestry. The estimated heritability was 0.68 (standard error 0.10) for height and 0.30 (standard error 0.10) for body mass index. Low minor allele frequency variants in low linkage disequilibrium (LD) with neighboring variants were enriched for heritability, to a greater extent for protein-altering variants, consistent with negative selection. Our results imply that rare variants, in particular those in regions of low linkage disequilibrium, are a major source of the still missing heritability of complex traits and disease.

The association of aortic valve sclerosis, aortic annulus increased reflectivity, and mitral annular calcification with subsequent aortic stenosis in older individuals. Findings from the Cardiovascular Health Study. - Barasch, Eddy; Gottdiener, John S; Tressel, William; Bartz, Traci M; Bůzková, Petra; Massera, Daniele; DeFilippi, Christopher; Biggs, Mary L; Psaty, Bruce M; Kizer, Jorge R; Owens, David (J Am Soc Echocardiogr, 2022)
BACKGROUND: While aortic valve sclerosis (AVS) is well-described as preceding aortic stenosis (AS), the association of AS with antecedent mitral aortic annular calcification and aortic annulus increased reflectivity (MAC and AAIR, respectively) has not been characterized. In a population-based prospective study, we evaluated whether MAC, AAIR, and AVS are associated with the risk of incident AS. METHODS: Among participants of the Cardiovascular Health Study (CHS) free of AS at the 1994-1995 visit, the presence of MAC, AAIR, AVS, and the combination of all three were evaluated in 3041 participants. Cox proportional hazards regression was used to assess the association between the presence of calcification and the incidence of moderate/severe AS in three nested models adjusting for factors associated with atherosclerosis and inflammation both relevant to the pathogenesis of AS. RESULTS: Over a median follow-up of 11.5 years (IQR 6.7 to 17.0), 110 cases of incident moderate/severe AS were ascertained. Strong positive associations with incident moderate/severe AS were found for all calcification sites after adjustment for the main model covariates: AAIR (HR=2.90, 95% CI=[1.95, 4.32], p<0.0005), AVS (HR=2.20, 95% CI=[1.44, 3.37], p<0.0005), MAC (HR=1.67, 95% CI=[1.14, 2.45], p=0.008), and the combination of MAC, AAIR, and AVS (HR=2.50, 95% CI=[1.65, 3.78], p<0.0005). In a secondary analysis, the risk of AS increased with the number of sites at which calcification was present. CONCLUSIONS: In a large cohort of community-dwelling elderly individuals, there were strong associations between each of AAIR, AVS, MAC, and the combination of MAC, AAIR, and AVS with incident moderate/severe AS. The novel finding that AAIR had a particularly strong association with incident AS, even after adjusting for other calcification sites, suggests its value in identifying individuals at risk for AS, and potential inclusion in the routine assessment by transthoracic echocardiography.

Association of Serum Neurofilament Light Chain Concentration and MRI Findings in Older Adults: The Cardiovascular Health Study. - Fohner, Alison E; Bartz, Traci M; Tracy, Russell P; Adams, Hieab H H; Bis, Joshua C; Djoussé, Luc; Satizabal, Claudia L; Lopez, Oscar L; Seshadri, Sudha; Mukamal, Kenneth J; Kuller, Lewis H; Psaty, Bruce M; et al. (Neurology, 2022)
BACKGROUND AND OBJECTIVES: Neurofilament light chain (NfL) in blood is a sensitive but nonspecific marker of brain injury. This study sought to evaluate associations between NfL concentration and MRI findings of vascular brain injury in older adults. METHODS: A longitudinal cohort study included 2 cranial MRI scans performed about 5 years apart and assessed for white matter hyperintensities (WMH) and infarcts. About 1 year before their second MRI, 1,362 participants (median age 77 years, 61.4% women) without a history of TIA or stroke had measurement of 4 biomarkers: NfL, total tau, glial fibrillary acidic protein (GFAP), and ubiquitin carboxyl-terminal hydrolase L1. Most (n = 1,279) also had the first MRI scan, and some (n = 633) had quantitative measurements of hippocampal and WMH. In primary analyses, we assessed associations of NfL with a 10-point white matter grade (WMG) and prevalent infarcts on second MRI and with worsening WMG and incident infarct comparing the 2 scans. A value <0.0125 (0.05/4) was considered significant for these analyses. We also assessed associations with hippocampal and WMH volume. RESULTS: In fully adjusted models, log(NfL) concentration was associated with WMG (β = 0.27; = 2.3 × 10) and worsening WMG (relative risk [RR] 1.24; = 0.0022), but less strongly with prevalent brain infarcts (RR 1.18; = 0.013) and not with incident brain infarcts (RR 1.18; = 0.18). Associations were also present with WMH volume (β = 2,242.9, = 0.0036). For the other 3 biomarkers, the associations for log (GFAP) concentration with WMG and worsening WMG were significant. DISCUSSION: Among older adults without a history of stroke, higher serum NfL concentration was associated with covert MRI findings of vascular brain injury, especially the burden of WMH and its worsening. Whether these results offer opportunities for the use of NfL as a noninvasive biomarker of WMH or to control vascular risk factors remains to be determined.

Association of Trimethylamine N-Oxide and Metabolites With Mortality in Older Adults. - Fretts, Amanda M; Hazen, Stanley L; Jensen, Paul; Budoff, Matthew; Sitlani, Colleen M; Wang, Meng; de Oliveira Otto, Marcia C; DiDonato, Joseph A; Lee, Yujin; Psaty, Bruce M; Siscovick, David S; Sotoodehnia, Nona; et al. (JAMA Netw Open, 2022)
Importance: Little is known about the association of trimethylamine N-oxide (TMAO), a novel plasma metabolite derived from L-carnitine and phosphatidylcholine, and related metabolites (ie, choline, betaine, carnitine, and butyrobetaine) with risk of death among older adults in the general population. Objective: To investigate the associations of serial measures of plasma TMAO and related metabolites with risk of total and cause-specific death (ie, deaths from cardiovascular diseases [CVDs] and non-CVDs) among older adults in the US. Design, Setting, and Participants: This prospective cohort study involved 5333 participants from the Cardiovascular Health Study-a community-based longitudinal cohort of adults aged 65 years or older-who were followed up from June 1, 1989, to December 31, 2015. Participants were from 4 communities in the US (Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania). Data were analyzed from March 17 to June 23, 2021. Exposures: Plasma TMAO, choline, betaine, carnitine, and butyrobetaine levels were measured using stored samples from baseline (June 1, 1989, to May 31, 1990, or November 1, 1992, to June 31, 1993) and follow-up examination (June 1, 1996, to May 31, 1997). Measurements were performed through stable-isotope dilution liquid chromatography with tandem mass spectrometry using high-performance liquid chromatography with online electrospray ionization tandem mass spectrometry. Main Outcomes and Measures: Deaths (total and cause specific) were adjudicated by a centralized Cardiovascular Health Study events committee based on information from medical records, laboratory and diagnostic reports, death certificates, and/or interviews with next of kin. The associations of each metabolite with mortality were assessed using Cox proportional hazards regression models. Results: Among 5333 participants in the analytic sample, the mean (SD) age was 73 (6) years; 2149 participants (40.3%) were male, 3184 (59.7%) were female, 848 (15.9%) were African American, 4450 (83.4%) were White, and 35 (0.01%) were of other races (12 were American Indian or Alaska Native, 4 were Asian or Pacific Islander, and 19 were of other races or ethnicities). During a median follow-up of 13.2 years (range, 0-26.9 years), 4791 deaths occurred. After adjustment for potential confounders, the hazard ratios for death from any cause (ie, total mortality) comparing extreme quintiles (fifth vs first) of plasma concentrations were 1.30 (95% CI, 1.17-1.44) for TMAO, 1.19 (95% CI, 1.08-1.32) for choline, 1.26 (95% CI, 1.15-1.40) for carnitine, and 1.26 (95% CI, 1.13-1.40) for butyrobetaine. Plasma betaine was not associated with risk of death. The extent of risk estimates was similar for CVD and non-CVD mortality. Conclusions and Relevance: In this cohort study, plasma concentrations of TMAO and related metabolites were positively associated with risk of death. These findings suggest that circulating TMAO is an important novel risk factor associated with death among older adults.
Keywords: Aged; Betaine; Cardiovascular Diseases; Carnitine; Choline; Cohort Studies; Female; Humans; Male; Methylamines; Prospective Studies

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

Circulating Soluble CD163, Associations With Cardiovascular Outcomes and Mortality, and Identification of Genetic Variants in Older Individuals: The Cardiovascular Health Study. - Durda, Peter; Raffield, Laura M; Lange, Ethan M; Olson, Nels C; Jenny, Nancy Swords; Cushman, Mary; Deichgraeber, Pia; Grarup, Niels; Jonsson, Anna; Hansen, Torben; Mychaleckyj, Josyf C; Psaty, Bruce M; et al. (J Am Heart Assoc, 2022)
Background Monocytes/macrophages participate in cardiovascular disease. CD163 (cluster of differentiation 163) is a monocyte/macrophage receptor, and the shed sCD163 (soluble CD163) reflects monocyte/macrophage activation. We examined the association of sCD163 with incident cardiovascular disease events and performed a genome-wide association study to identify sCD163-associated variants. Methods and Results We measured plasma sCD163 in 5214 adults (aged ≥65 years, 58.7% women, 16.2% Black) of the CHS (Cardiovascular Health Study). We used Cox regression models (associations of sCD163 with incident events and mortality); median follow-up was 26 years. Genome-wide association study analyses were stratified on race. Adjusted for age, sex, and race and ethnicity, sCD163 levels were associated with all-cause mortality (hazard ratio [HR], 1.08 [95% CI, 1.04-1.12] per SD increase), cardiovascular disease mortality (HR, 1.15 [95% CI, 1.09-1.21]), incident coronary heart disease (HR, 1.10 [95% CI, 1.04-1.16]), and incident heart failure (HR, 1.18 [95% CI, 1.12-1.25]). When further adjusted (eg, cardiovascular disease risk factors), only incident coronary heart disease lost significance. In European American individuals, genome-wide association studies identified 38 variants on chromosome 2 near (top result rs62165726, =3.3×10),19 variants near chromosome 17 gene (rs55714927, =1.5×10), and 18 variants near chromosome 11 gene . These regions replicated in the European ancestry ADDITION-PRO cohort, a longitudinal cohort study nested in the Danish arm of the Anglo-Danish-Dutch study of Intensive Treatment Intensive Treatment In peOple with screeNdetcted Diabetes in Primary Care. In Black individuals, we identified 9 variants on chromosome 6 (rs3129781 =7.1×10) in the region, and 3 variants (rs115391969 =4.3×10) near the chromosome 16 gene Conclusions Monocyte function, as measured by sCD163, may be predictive of overall and cardiovascular-specific mortality and incident heart failure.
Keywords: Aged; Antigens, CD; Antigens, Differentiation, Myelomonocytic; Asialoglycoprotein Receptor; Biomarkers; Cardiovascular Diseases; Female; Genome-Wide Association Study; Heart Failure; Humans; Longitudinal Studies; Male

Clonal Hematopoiesis Is Associated With Higher Risk of Stroke. - Bhattacharya, Romit; Zekavat, Seyedeh M; Haessler, Jeffrey; Fornage, Myriam; Raffield, Laura; Uddin, Md Mesbah; Bick, Alexander G; Niroula, Abhishek; Yu, Bing; Gibson, Christopher; Griffin, Gabriel; Morrison, Alanna C; et al. (Stroke, 2022)
BACKGROUND AND PURPOSE: Clonal hematopoiesis of indeterminate potential (CHIP) is a novel age-related risk factor for cardiovascular disease-related morbidity and mortality. The association of CHIP with risk of incident ischemic stroke was reported previously in an exploratory analysis including a small number of incident stroke cases without replication and lack of stroke subphenotyping. The purpose of this study was to discover whether CHIP is a risk factor for ischemic or hemorrhagic stroke. METHODS: We utilized plasma genome sequence data of blood DNA to identify CHIP in 78 752 individuals from 8 prospective cohorts and biobanks. We then assessed the association of CHIP and commonly mutated individual CHIP driver genes (, , and ) with any stroke, ischemic stroke, and hemorrhagic stroke. RESULTS: CHIP was associated with an increased risk of total stroke (hazard ratio, 1.14 [95% CI, 1.03-1.27]; =0.01) after adjustment for age, sex, and race. We observed associations with CHIP with risk of hemorrhagic stroke (hazard ratio, 1.24 [95% CI, 1.01-1.51]; =0.04) and with small vessel ischemic stroke subtypes. In gene-specific association results, showed the strongest association with total stroke and ischemic stroke, whereas and were each associated with increased risk of hemorrhagic stroke. CONCLUSIONS: CHIP is associated with an increased risk of stroke, particularly with hemorrhagic and small vessel ischemic stroke. Future studies clarifying the relationship between CHIP and subtypes of stroke are needed.

Clonal Hematopoiesis of Indeterminate Potential and Kidney Function Decline in the General Population. - Kestenbaum, Bryan; Bick, Alexander G; Vlasschaert, Caitlyn; Rauh, Michael J; Lanktree, Matthew B; Franceschini, Nora; Shoemaker, Moore B; Harris, Raymond C; Psaty, Bruce M; Köttgen, Anna; Natarajan, Pradeep; Robinson-Cohen, Cassianne (Am J Kidney Dis, 2022)
RATIONALE & OBJECTIVE: Clonal hematopoiesis of indeterminate potential (CHIP), defined by the age-related ontogenesis of expanded leukemogenic variants indicative of a genetically distinct clonal leukocyte population, is associated with risk of hematologic malignancy and cardiovascular disease. In experimental models, recapitulation of CHIP promotes kidney interstitial fibrosis with direct tissue infiltration of donor macrophages. We tested the hypothesis that CHIP is associated with kidney function decline in the general population. STUDY DESIGN: Cohort study. SETTING & PARTICIPANTS: 12,004 individuals from 3 community-based cohorts in the TOPMed Consortium. EXPOSURE: CHIP status from whole-genome sequences obtained from DNA extracted from peripheral blood. OUTCOME: Risk of 30% decline in estimated glomerular filtration rate (eGFR) and percent eGFR decline per year during the follow-up period. ANALYTICAL APPROACH: Cox proportional hazards models for 30% eGFR decline end point and generalized estimating equations for annualized relative change in eGFR with meta-analysis. Study-specific estimates were combined using fixed-effect meta-analysis. RESULTS: The median baseline eGFR was 84mL/min/1.73m. The prevalence of CHIP was 6.6%, 9.0%, and 12.2% in persons aged 50-60, 60-70, and>70 years, respectively. Over a median follow-up period of 8 years, for the 30% eGFR outcome 205 events occurred among 1,002 CHIP carriers (2.1 events per 100 person-years) and 2,041 events in persons without CHIP (1.7 events per 100 person-years). In meta-analysis, CHIP was associated with greater risk of a 30% eGFR decline (17% [95% CI, 1%-36%] higher; P=0.04). Differences were not observed between those with baseline eGFR above or below 60mL/min/1.73m, of age above or below 60 years, or with or without diabetes. LIMITATIONS: Small number of participants with moderate-to-advanced kidney disease and restricted set of CHIP driver variants. CONCLUSIONS: We report an association between CHIP and eGFR decline in 3 general population cohorts without known kidney disease. Further studies are needed to investigate this novel condition and its potential impact among individuals with overt kidney disease.

Correlations between complex human phenotypes vary by genetic background, gender, and environment. - Elgart, Michael; Goodman, Matthew O; Isasi, Carmen; Chen, Han; Morrison, Alanna C; de Vries, Paul S; Xu, Huichun; Manichaikul, Ani W; Guo, Xiuqing; Franceschini, Nora; Psaty, Bruce M; Rich, Stephen S; et al. (Cell Rep Med, 2022)
We develop a closed-form Haseman-Elston estimator for genetic and environmental correlation coefficients between complex phenotypes, which we term HEc, that is as precise as GCTA yet ∼20× faster. We estimate genetic and environmental correlations between over 7,000 phenotype pairs in subgroups from the Trans-Omics in Precision Medicine (TOPMed) program. We demonstrate substantial differences in both heritabilities and genetic correlations for multiple phenotypes and phenotype pairs between individuals of self-reported Black, Hispanic/Latino, and White backgrounds. We similarly observe differences in many of the genetic and environmental correlations between genders. To estimate the contribution of genetics to the observed phenotypic correlation, we introduce "fractional genetic correlation" as the fraction of phenotypic correlation explained by genetics. Finally, we quantify the enrichment of correlations between phenotypic domains, each of which is comprised of multiple phenotypes. Altogether, we demonstrate that the observed correlations between complex human phenotypes depend on the genetic background of the individuals, their gender, and their environment.
Keywords: Female; Genetic Background; Humans; Male; Phenotype

Cross-Ancestry Investigation of Venous Thromboembolism Genomic Predictors. - Thibord, Florian; Klarin, Derek; Brody, Jennifer A; Chen, Ming-Huei; Levin, Michael G; Chasman, Daniel I; Goode, Ellen L; Hveem, Kristian; Teder-Laving, Maris; Martinez-Perez, Angel; Aïssi, Dylan; Daian-Bacq, Delphine; et al. (Circulation, 2022)
BACKGROUND: Venous thromboembolism (VTE) is a life-threatening vascular event with environmental and genetic determinants. Recent VTE genome-wide association studies (GWAS) meta-analyses involved nearly 30 000 VTE cases and identified up to 40 genetic loci associated with VTE risk, including loci not previously suspected to play a role in hemostasis. The aim of our research was to expand discovery of new genetic loci associated with VTE by using cross-ancestry genomic resources. METHODS: We present new cross-ancestry meta-analyzed GWAS results involving up to 81 669 VTE cases from 30 studies, with replication of novel loci in independent populations and loci characterization through in silico genomic interrogations. RESULTS: In our genetic discovery effort that included 55 330 participants with VTE (47 822 European, 6320 African, and 1188 Hispanic ancestry), we identified 48 novel associations, of which 34 were replicated after correction for multiple testing. In our combined discovery-replication analysis (81 669 VTE participants) and ancestry-stratified meta-analyses (European, African, and Hispanic), we identified another 44 novel associations, which are new candidate VTE-associated loci requiring replication. In total, across all GWAS meta-analyses, we identified 135 independent genomic loci significantly associated with VTE risk. A genetic risk score of the significantly associated loci in Europeans identified a 6-fold increase in risk for those in the top 1% of scores compared with those with average scores. We also identified 31 novel transcript associations in transcriptome-wide association studies and 8 novel candidate genes with protein quantitative-trait locus Mendelian randomization analyses. In silico interrogations of hemostasis and hematology traits and a large phenome-wide association analysis of the 135 GWAS loci provided insights to biological pathways contributing to VTE, with some loci contributing to VTE through well-characterized coagulation pathways and others providing new data on the role of hematology traits, particularly platelet function. Many of the replicated loci are outside of known or currently hypothesized pathways to thrombosis. CONCLUSIONS: Our cross-ancestry GWAS meta-analyses identified new loci associated with VTE. These findings highlight new pathways to thrombosis and provide novel molecules that may be useful in the development of improved antithrombosis treatments.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Thrombosis; Venous Thromboembolism

Dietary Meat, Trimethylamine N-Oxide-Related Metabolites, and Incident Cardiovascular Disease Among Older Adults: The Cardiovascular Health Study. - Wang, Meng; Wang, Zeneng; Lee, Yujin; Lai, Heidi T M; de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Fretts, Amanda; Sotoodehnia, Nona; Budoff, Matthew; DiDonato, Joseph A; McKnight, Barbara; Tang, W H Wilson; et al. (Arterioscler Thromb Vasc Biol, 2022)
BACKGROUND: Effects of animal source foods (ASF) on atherosclerotic cardiovascular disease (ASCVD) and underlying mechanisms remain controversial. We investigated prospective associations of different ASF with incident ASCVD and potential mediation by gut microbiota-generated trimethylamine N-oxide, its L-carnitine-derived intermediates γ-butyrobetaine and crotonobetaine, and traditional ASCVD risk pathways. METHODS: Among 3931 participants from a community-based US cohort aged 65+ years, ASF intakes and trimethylamine N-oxide-related metabolites were measured serially over time. Incident ASCVD (myocardial infarction, fatal coronary heart disease, stroke, other atherosclerotic death) was adjudicated over 12.5 years median follow-up. Cox proportional hazards models with time-varying exposures and covariates examined ASF-ASCVD associations; and additive hazard models, mediation proportions by different risk pathways. RESULTS: After multivariable-adjustment, higher intakes of unprocessed red meat, total meat, and total ASF associated with higher ASCVD risk, with hazard ratios (95% CI) per interquintile range of 1.15 (1.01-1.30), 1.22 (1.07-1.39), and 1.18 (1.03-1.34), respectively. Trimethylamine N-oxide-related metabolites together significantly mediated these associations, with mediation proportions (95% CI) of 10.6% (1.0-114.5), 7.8% (1.0-32.7), and 9.2% (2.2-44.5), respectively. Processed meat intake associated with a nonsignificant trend toward higher ASCVD (1.11 [0.98-1.25]); intakes of fish, poultry, and eggs were not significantly associated. Among other risk pathways, blood glucose, insulin, and C-reactive protein, but not blood pressure or blood cholesterol, each significantly mediated the total meat-ASCVD association. CONCLUSIONS: In this large, community-based cohort, higher meat intake associated with incident ASCVD, partly mediated by microbiota-derived metabolites of L-carnitine, abundant in red meat. These novel findings support biochemical links between dietary meat, gut microbiome pathways, and ASCVD.
Keywords: Animals; Atherosclerosis; Cardiovascular Diseases; Carnitine; Humans; Meat; Methylamines; Risk Factors

Differential and shared genetic effects on kidney function between diabetic and non-diabetic individuals. - Winkler, Thomas W; Rasheed, Humaira; Teumer, Alexander; Gorski, Mathias; Rowan, Bryce X; Stanzick, Kira J; Thomas, Laurent F; Tin, Adrienne; Hoppmann, Anselm; Chu, Audrey Y; Tayo, Bamidele; Thio, Chris H L; et al. (Commun Biol, 2022)
Reduced glomerular filtration rate (GFR) can progress to kidney failure. Risk factors include genetics and diabetes mellitus (DM), but little is known about their interaction. We conducted genome-wide association meta-analyses for estimated GFR based on serum creatinine (eGFR), separately for individuals with or without DM (n = 178,691, n = 1,296,113). Our genome-wide searches identified (i) seven eGFR loci with significant DM/noDM-difference, (ii) four additional novel loci with suggestive difference and (iii) 28 further novel loci (including CUBN) by allowing for potential difference. GWAS on eGFR among DM individuals identified 2 known and 27 potentially responsible loci for diabetic kidney disease. Gene prioritization highlighted 18 genes that may inform reno-protective drug development. We highlight the existence of DM-only and noDM-only effects, which can inform about the target group, if respective genes are advanced as drug targets. Largely shared effects suggest that most drug interventions to alter eGFR should be effective in DM and noDM.
Keywords: Creatinine; Diabetes Mellitus; Diabetic Nephropathies; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney

Endophenotype effect sizes support variant pathogenicity in monogenic disease susceptibility genes. - Halford, Jennifer L; Morrill, Valerie N; Choi, Seung Hoan; Jurgens, Sean J; Melloni, Giorgio; Marston, Nicholas A; Weng, Lu-Chen; Nauffal, Victor; Hall, Amelia W; Gunn, Sophia; Austin-Tse, Christina A; Pirruccello, James P; et al. (Nat Commun, 2022)
Accurate and efficient classification of variant pathogenicity is critical for research and clinical care. Using data from three large studies, we demonstrate that population-based associations between rare variants and quantitative endophenotypes for three monogenic diseases (low-density-lipoprotein cholesterol for familial hypercholesterolemia, electrocardiographic QTc interval for long QT syndrome, and glycosylated hemoglobin for maturity-onset diabetes of the young) provide evidence for variant pathogenicity. Effect sizes are associated with pathogenic ClinVar assertions (P < 0.001 for each trait) and discriminate pathogenic from non-pathogenic variants (area under the curve 0.82-0.84 across endophenotypes). An effect size threshold of ≥ 0.5 times the endophenotype standard deviation nominates up to 35% of rare variants of uncertain significance or not in ClinVar in disease susceptibility genes with pathogenic potential. We propose that variant associations with quantitative endophenotypes for monogenic diseases can provide evidence supporting pathogenicity.
Keywords: Disease Susceptibility; Endophenotypes; Humans; Long QT Syndrome; Virulence

Epigenetic and integrative cross-omics analyses of cerebral white matter hyperintensities on MRI. - Yang, Yunju; Knol, Maria J; Wang, Ruiqi; Mishra, Aniket; Liu, Dan; Luciano, Michelle; Teumer, Alexander; Armstrong, Nicola; Bis, Joshua C; Jhun, Min A; Li, Shuo; Adams, Hieab H H; et al. (Brain, 2022)
Cerebral white matter hyperintensities on MRI are markers of cerebral small vessel disease, a major risk factor for dementia and stroke. Despite the successful identification of multiple genetic variants associated with this highly heritable condition, its genetic architecture remains incompletely understood. More specifically, the role of DNA methylation has received little attention. We investigated the association between white matter hyperintensity burden and DNA methylation in blood at approximately 450,000 CpG sites in 9,732 middle-aged to older adults from 14 community-based studies. Single-CpG and region-based association analyses were carried out. Functional annotation and integrative cross-omics analyses were performed to identify novel genes underlying the relationship between DNA methylation and white matter hyperintensities. We identified 12 single-CpG and 46 region-based DNA methylation associations with white matter hyperintensity burden. Our top discovery single CpG, cg24202936 (P = 7.6 × 10-8), was associated with F2 expression in blood (P = 6.4 × 10-5), and colocalized with FOLH1 expression in brain (posterior probability =0.75). Our top differentially methylated regions were in PRMT1 and in CCDC144NL-AS1, which were also represented in single-CpG associations (cg17417856 and cg06809326, respectively). Through Mendelian randomization analyses cg06809326 was putatively associated with white matter hyperintensity burden (P = 0.03) and expression of CCDC144NL-AS1 possibly mediated this association. Differentially methylated region analysis, joint epigenetic association analysis, and multi-omics colocalization analysis consistently identified a role of DNA methylation near SH3PXD2A, a locus previously identified in genome-wide association studies of white matter hyperintensities. Gene set enrichment analyses revealed functions of the identified DNA methylation loci in the blood-brain barrier and in the immune response. Integrative cross-omics analysis identified 19 key regulatory genes in two networks related to extracellular matrix organization, and lipid and lipoprotein metabolism. A drug repositioning analysis indicated antihyperlipidemic agents, more specifically peroxisome proliferator-activated receptor alpha, as possible target drugs for white matter hyperintensities. Our epigenome-wide association study and integrative cross-omics analyses implicate novel genes influencing white matter hyperintensity burden, which converged on pathways related to the immune response and to a compromised blood brain barrier possibly due to disrupted cell-cell and cell-extracellular matrix interactions. The results also suggest that antihyperlipidemic therapy may contribute to lowering risk for white matter hyperintensities possibly through protection against blood brain barrier disruption.

A framework for detecting noncoding rare-variant associations of large-scale whole-genome sequencing studies. - Li, Zilin; Li, Xihao; Zhou, Hufeng; Gaynor, Sheila M; Selvaraj, Margaret Sunitha; Arapoglou, Theodore; Quick, Corbin; Liu, Yaowu; Chen, Han; Sun, Ryan; Dey, Rounak; Arnett, Donna K; et al. (Nat Methods, 2022)
Large-scale whole-genome sequencing studies have enabled analysis of noncoding rare-variant (RV) associations with complex human diseases and traits. Variant-set analysis is a powerful approach to study RV association. However, existing methods have limited ability in analyzing the noncoding genome. We propose a computationally efficient and robust noncoding RV association detection framework, STAARpipeline, to automatically annotate a whole-genome sequencing study and perform flexible noncoding RV association analysis, including gene-centric analysis and fixed window-based and dynamic window-based non-gene-centric analysis by incorporating variant functional annotations. In gene-centric analysis, STAARpipeline uses STAAR to group noncoding variants based on functional categories of genes and incorporate multiple functional annotations. In non-gene-centric analysis, STAARpipeline uses SCANG-STAAR to incorporate dynamic window sizes and multiple functional annotations. We apply STAARpipeline to identify noncoding RV sets associated with four lipid traits in 21,015 discovery samples from the Trans-Omics for Precision Medicine (TOPMed) program and replicate several of them in an additional 9,123 TOPMed samples. We also analyze five non-lipid TOPMed traits.
Keywords: Genetic Variation; Genome; Genome-Wide Association Study; Humans; Phenotype; Whole Genome Sequencing

Genetic loci and prioritization of genes for kidney function decline derived from a meta-analysis of 62 longitudinal genome-wide association studies. - Gorski, Mathias; Rasheed, Humaira; Teumer, Alexander; Thomas, Laurent F; Graham, Sarah E; Sveinbjornsson, Gardar; Winkler, Thomas W; Günther, Felix; Stark, Klaus J; Chai, Jin-Fang; Tayo, Bamidele O; Wuttke, Matthias; et al. (Kidney Int, 2022)
Estimated glomerular filtration rate (eGFR) reflects kidney function. Progressive eGFR-decline can lead to kidney failure, necessitating dialysis or transplantation. Hundreds of loci from genome-wide association studies (GWAS) for eGFR help explain population cross section variability. Since the contribution of these or other loci to eGFR-decline remains largely unknown, we derived GWAS for annual eGFR-decline and meta-analyzed 62 longitudinal studies with eGFR assessed twice over time in all 343,339 individuals and in high-risk groups. We also explored different covariate adjustment. Twelve genome-wide significant independent variants for eGFR-decline unadjusted or adjusted for eGFR-baseline (11 novel, one known for this phenotype), including nine variants robustly associated across models were identified. All loci for eGFR-decline were known for cross-sectional eGFR and thus distinguished a subgroup of eGFR loci. Seven of the nine variants showed variant-by-age interaction on eGFR cross section (further about 350,000 individuals), which linked genetic associations for eGFR-decline with age-dependency of genetic cross-section associations. Clinically important were two to four-fold greater genetic effects on eGFR-decline in high-risk subgroups. Five variants associated also with chronic kidney disease progression mapped to genes with functional in-silico evidence (UMOD, SPATA7, GALNTL5, TPPP). An unfavorable versus favorable nine-variant genetic profile showed increased risk odds ratios of 1.35 for kidney failure (95% confidence intervals 1.03-1.77) and 1.27 for acute kidney injury (95% confidence intervals 1.08-1.50) in over 2000 cases each, with matched controls). Thus, we provide a large data resource, genetic loci, and prioritized genes for kidney function decline, which help inform drug development pipelines revealing important insights into the age-dependency of kidney function genetics.

Genome Wide Association Studies of Variant-by-Thiazide Interaction on Lipids Identifies a Novel Low-Density Lipoprotein Cholesterol Locus. - Downie, Carolina G; Highland, Heather M; Lee, Moa P; Raffield, Laura M; Preuss, Michael; Whitsel, Eric A; Psaty, Bruce M; Sitlani, Colleen M; Graff, Mariaelisa; Avery, Christy L (Circ Res, 2022)
Keywords: Cholesterol, HDL; Cholesterol, LDL; Diuretics; Genome-Wide Association Study; Sodium Chloride Symporter Inhibitors; Thiazides; Triglycerides

Genome-wide meta-analyses reveal novel loci for verbal short-term memory and learning. - Lahti, Jari; Tuominen, Samuli; Yang, Qiong; Pergola, Giulio; Ahmad, Shahzad; Amin, Najaf; Armstrong, Nicola J; Beiser, Alexa; Bey, Katharina; Bis, Joshua C; Boerwinkle, Eric; Bressler, Jan; et al. (Mol Psychiatry, 2022)
Understanding the genomic basis of memory processes may help in combating neurodegenerative disorders. Hence, we examined the associations of common genetic variants with verbal short-term memory and verbal learning in adults without dementia or stroke (N = 53,637). We identified novel loci in the intronic region of CDH18, and at 13q21 and 3p21.1, as well as an expected signal in the APOE/APOC1/TOMM40 region. These results replicated in an independent sample. Functional and bioinformatic analyses supported many of these loci and further implicated POC1. We showed that polygenic score for verbal learning associated with brain activation in right parieto-occipital region during working memory task. Finally, we showed genetic correlations of these memory traits with several neurocognitive and health outcomes. Our findings suggest a role of several genomic loci in verbal memory processes.

Immune cell subpopulations as risk factors for atrial fibrillation: The Cardiovascular Health Study and Multi-Ethnic Study of Atherosclerosis. - Floyd, James S; Sitlani, Colleen M; Doyle, Margaret F; Feinstein, Matthew J; Olson, Nels C; Heckbert, Susan R; Huber, Sally A; Tracy, Russell P; Psaty, Bruce M; Delaney, Joseph A C (Heart Rhythm, 2022)

Insights From a Large-Scale Whole-Genome Sequencing Study of Systolic Blood Pressure, Diastolic Blood Pressure, and Hypertension. - Kelly, Tanika N; Sun, Xiao; He, Karen Y; Brown, Michael R; Taliun, Sarah A Gagliano; Hellwege, Jacklyn N; Irvin, Marguerite R; Mi, Xuenan; Brody, Jennifer A; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; et al. (Hypertension, 2022)
BACKGROUND: The availability of whole-genome sequencing data in large studies has enabled the assessment of coding and noncoding variants across the allele frequency spectrum for their associations with blood pressure. METHODS: We conducted a multiancestry whole-genome sequencing analysis of blood pressure among 51 456 Trans-Omics for Precision Medicine and Centers for Common Disease Genomics program participants (stage-1). Stage-2 analyses leveraged array data from UK Biobank (N=383 145), Million Veteran Program (N=318 891), and Reasons for Geographic and Racial Differences in Stroke (N=10 643) participants, along with whole-exome sequencing data from UK Biobank (N=199 631) participants. RESULTS: Two blood pressure signals achieved genome-wide significance in meta-analyses of stage-1 and stage-2 single variant findings (<5×10). Among them, a rare intergenic variant at novel locus, , was associated with lower systolic blood pressure in stage-1 (beta [SE]=-32.6 [6.0]; =4.99×10) but not stage-2 analysis (=0.11). Furthermore, a novel common variant at the known locus was suggestively associated with diastolic blood pressure in stage-1 (beta [SE]=-0.36 [0.07]; =4.18×10) and attained genome-wide significance in stage-2 (beta [SE]=-0.29 [0.03]; =7.28×10). Nineteen additional signals suggestively associated with blood pressure in meta-analysis of single and aggregate rare variant findings (<1×10 and <1×10, respectively). DISCUSSION: We report one promising but unconfirmed rare variant for blood pressure and, more importantly, contribute insights for future blood pressure sequencing studies. Our findings suggest promise of aggregate analyses to complement single variant analysis strategies and the need for larger, diverse samples, and family studies to enable robust rare variant identification.

Monocyte subsets, T cell activation profiles, and stroke in men and women: The Multi-Ethnic Study of Atherosclerosis and Cardiovascular Health Study. - Feinstein, Matthew J; Bůzková, Petra; Olson, Nels C; Doyle, Margaret F; Sitlani, Colleen M; Fohner, Alison E; Huber, Sally A; Floyd, James; Sinha, Arjun; Thorp, Edward B; Landay, Alan; Freiberg, Matthew S; et al. (Atherosclerosis, 2022)
BACKGROUND AND AIMS: Despite mechanistic data implicating unresolving inflammation in stroke pathogenesis, data regarding circulating immune cell phenotypes - key determinants of inflammation propagation versus resolution - and incident stroke are lacking. Therefore, we aimed to comprehensively define associations of circulating immune phenotypes and activation profiles with incident stroke. METHODS: We investigated circulating leukocyte phenotypes and activation profiles with incident adjudicated stroke in 2104 diverse adults from the Multi-Ethnic Study of Atherosclerosis (MESA) followed over a median of 16.6 years. Cryopreserved cells from the MESA baseline examination were thawed and myeloid and lymphoid lineage cell subsets were measured using polychromatic flow cytometry and intracellular cytokine activation staining. We analyzed multivariable-adjusted associations of cell phenotypes, as a proportion of parent cell subsets, with incident stroke (overall) and ischemic stroke using Cox regression models. RESULTS: We observed associations of intermediate monocytes, early-activated CD4 T cells, and both CD4 and CD8 T cells producing interleukin-4 after cytokine stimulation (T and T, respectively) with higher risk for incident stroke; effect sizes ranged from 35% to 62% relative increases in risk for stroke. Meanwhile, differentiated and memory T cell phenotypes were associated with lower risk for incident stroke. In sex-stratified analyses, positive and negative associations were especially strong among men but null among women. CONCLUSIONS: Circulating IL-4 producing T cells and intermediate monocytes were significantly associated with incident stroke over nearly two decades of follow-up. These associations were stronger among men and not among women. Further translational studies are warranted to define more precise targets for prognosis and intervention.
Keywords: Atherosclerosis; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cytokines; Female; Follow-Up Studies; Humans; Incidence; Inflammation; Interleukin-4; Ischemic Stroke; Lymphocyte Activation; Male; Monocytes; Stroke; T-Lymphocyte Subsets

Monogenic and Polygenic Contributions to QTc Prolongation in the Population. - Nauffal, Victor; Morrill, Valerie N; Jurgens, Sean J; Choi, Seung Hoan; Hall, Amelia W; Weng, Lu-Chen; Halford, Jennifer L; Austin-Tse, Christina; Haggerty, Christopher M; Harris, Stephanie L; Wong, Eugene K; Alonso, Alvaro; et al. (Circulation, 2022)
Rare sequence variation in genes underlying cardiac repolarization and common polygenic variation influence QT interval duration. However, current clinical genetic testing of individuals with unexplained QT prolongation is restricted to examination of monogenic rare variants. The recent emergence of large-scale biorepositories with sequence data enables examination of the joint contribution of rare and common variation to the QT interval in the population. We performed a genome wide association study (GWAS) of the QTc in 84,630 United Kingdom Biobank (UKB) participants and created a polygenic risk score (PRS). Among 26,976 participants with whole genome sequencing and electrocardiogram data in the Trans-Omics for Precision Medicine (TOPMed) program, we identified 160 carriers of putative pathogenic rare variants in 10 genes known to be associated with the QT interval. We examined QTc associations with the PRS and with rare variants in TOPMed. Fifty-four independent loci were identified by GWAS in the UKB. Twenty-one loci were novel, of which 12 were replicated in TOPMed. The PRS comprising 1,110,494 common variants was significantly associated with the QTc in TOPMed (ΔQTc/ = 1.4 ms, 95% CI 1.3 -1.5; p-value=1.1×10). Carriers of putative pathogenic rare variants had longer QTc than non-carriers (ΔQTc=10.9 ms [7.4-14.4]). 23.7% of individuals with QTc>480 ms carried either a monogenic rare variant or had a PRS in the top decile (3.4% monogenic, 21% top decile of PRS). QTc duration in the population is influenced by both rare variants in genes underlying cardiac repolarization and polygenic risk, with a sizeable contribution from polygenic risk. Comprehensive assessment of the genetic determinants of QTc prolongation includes incorporation of both polygenic and monogenic risk.

Multi-ancestry genetic study of type 2 diabetes highlights the power of diverse populations for discovery and translation. - Mahajan, Anubha; Spracklen, Cassandra N; Zhang, Weihua; Ng, Maggie C Y; Petty, Lauren E; Kitajima, Hidetoshi; Yu, Grace Z; Rüeger, Sina; Speidel, Leo; Kim, Young Jin; Horikoshi, Momoko; Mercader, Josep M; et al. (Nat Genet, 2022)
We assembled an ancestrally diverse collection of genome-wide association studies (GWAS) of type 2 diabetes (T2D) in 180,834 affected individuals and 1,159,055 controls (48.9% non-European descent) through the Diabetes Meta-Analysis of Trans-Ethnic association studies (DIAMANTE) Consortium. Multi-ancestry GWAS meta-analysis identified 237 loci attaining stringent genome-wide significance (P < 5 × 10), which were delineated to 338 distinct association signals. Fine-mapping of these signals was enhanced by the increased sample size and expanded population diversity of the multi-ancestry meta-analysis, which localized 54.4% of T2D associations to a single variant with >50% posterior probability. This improved fine-mapping enabled systematic assessment of candidate causal genes and molecular mechanisms through which T2D associations are mediated, laying the foundations for functional investigations. Multi-ancestry genetic risk scores enhanced transferability of T2D prediction across diverse populations. Our study provides a step toward more effective clinical translation of T2D GWAS to improve global health for all, irrespective of genetic background.
Keywords: Diabetes Mellitus, Type 2; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

A multi-ethnic polygenic risk score is associated with hypertension prevalence and progression throughout adulthood. - Kurniansyah, Nuzulul; Goodman, Matthew O; Kelly, Tanika N; Elfassy, Tali; Wiggins, Kerri L; Bis, Joshua C; Guo, Xiuqing; Palmas, Walter; Taylor, Kent D; Lin, Henry J; Haessler, Jeffrey; Gao, Yan; et al. (Nat Commun, 2022)
In a multi-stage analysis of 52,436 individuals aged 17-90 across diverse cohorts and biobanks, we train, test, and evaluate a polygenic risk score (PRS) for hypertension risk and progression. The PRS is trained using genome-wide association studies (GWAS) for systolic, diastolic blood pressure, and hypertension, respectively. For each trait, PRS is selected by optimizing the coefficient of variation (CV) across estimated effect sizes from multiple potential PRS using the same GWAS, after which the 3 trait-specific PRSs are combined via an unweighted sum called "PRSsum", forming the HTN-PRS. The HTN-PRS is associated with both prevalent and incident hypertension at 4-6 years of follow up. This association is further confirmed in age-stratified analysis. In an independent biobank of 40,201 individuals, the HTN-PRS is confirmed to be predictive of increased risk for coronary artery disease, ischemic stroke, type 2 diabetes, and chronic kidney disease.
Keywords: Adult; Diabetes Mellitus, Type 2; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Multifactorial Inheritance; Prevalence; Risk Factors

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins

Non-linear machine learning models incorporating SNPs and PRS improve polygenic prediction in diverse human populations. - Elgart, Michael; Lyons, Genevieve; Romero-Brufau, Santiago; Kurniansyah, Nuzulul; Brody, Jennifer A; Guo, Xiuqing; Lin, Henry J; Raffield, Laura; Gao, Yan; Chen, Han; de Vries, Paul; Lloyd-Jones, Donald M; et al. (Commun Biol, 2022)
Polygenic risk scores (PRS) are commonly used to quantify the inherited susceptibility for a trait, yet they fail to account for non-linear and interaction effects between single nucleotide polymorphisms (SNPs). We address this via a machine learning approach, validated in nine complex phenotypes in a multi-ancestry population. We use an ensemble method of SNP selection followed by gradient boosted trees (XGBoost) to allow for non-linearities and interaction effects. We compare our results to the standard, linear PRS model developed using PRSice, LDpred2, and lassosum2. Combining a PRS as a feature in an XGBoost model results in a relative increase in the percentage variance explained compared to the standard linear PRS model by 22% for height, 27% for HDL cholesterol, 43% for body mass index, 50% for sleep duration, 58% for systolic blood pressure, 64% for total cholesterol, 66% for triglycerides, 77% for LDL cholesterol, and 100% for diastolic blood pressure. Multi-ancestry trained models perform similarly to specific racial/ethnic group trained models and are consistently superior to the standard linear PRS models. This work demonstrates an effective method to account for non-linearities and interaction effects in genetics-based prediction models.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Machine Learning; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Plasma epoxyeicosatrienoic acids and diabetes-related cardiovascular disease: The cardiovascular health study. - Lemaitre, Rozenn N; Jensen, Paul N; Zeigler, Maxwell; Fretts, Amanda M; Umans, Jason G; Howard, Barbara V; Sitlani, Colleen M; McKnight, Barbara; Gharib, Sina A; King, Irena B; Siscovick, David S; Psaty, Bruce M; et al. (EBioMedicine, 2022)
BACKGROUND: Epoxyeicosatrienoic acids (EETs) are metabolites of arachidonic acid that may impact atherosclerosis, and animal experimental studies suggest EETs protect cardiac function. Plasma EETs are mostly esterified to phospholipids and part of an active pool. To address the limited information about EETs and CVD in humans, we conducted a prospective study of total plasma EETs (free + esterified) and diabetes-related CVD in the Cardiovascular Health Study (CHS). METHODS: We measured 4 EET species and their metabolites, dihydroxyepoxyeicosatrienoic acids (DHETs), in plasma samples from 892 CHS participants with type 2 diabetes. We determined the association of EETs and DHETs with incident myocardial infarction (MI) and ischemic stroke using Cox regression. FINDINGS: During follow-up (median 7.5 years), we identified 150 MI and 134 ischemic strokes. In primary, multivariable analyses, elevated levels of each EET species were associated with non-significant lower risk of incident MI (for example, hazard ratio for 1 SD higher 14,15-EET: 0.86, 95% CI: 0.72-1.02; p=0.08). The EETs-MI associations became significant in analyses further adjusted for DHETs (hazard ratio for 1 SD higher 14,15-EET adjusted for 14,15-DHET: 0.76, 95% CI: 0.63-0.91; p=0.004). Elevated EET levels were associated with higher risk of ischemic stroke in primary but not secondary analyses. Three DHET species were associated with higher risk of ischemic stroke in all analyses. INTERPRETATION: Findings from this prospective study complement the extensive studies in animal models showing EETs protect cardiac function and provide new information in humans. Replication is needed to confirm the associations. FUNDING: US National Institutes of Health.
Keywords: Animals; Arachidonic Acids; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Eicosanoids; Humans; Ischemic Stroke; Prospective Studies

Plasma Levels of Advanced Glycation Endproducts and Risk of Cardiovascular Events: Findings From 2 Prospective Cohorts. - Lamprea-Montealegre, Julio A; Arnold, Alice M; McClelland, Robyn L; Mukamal, Kenneth J; Djoussé, Luc; Biggs, Mary L; Siscovick, David S; Tracy, Russell P; Beisswenger, Paul J; Psaty, Bruce M; Ix, Joachim H; Kizer, Jorge R (J Am Heart Assoc, 2022)
Background Advanced glycation endproducts (AGEs) have been linked to cardiovascular disease (CVD) in cohorts with and without diabetes. Data are lacking on prospective associations of various α-dicarbonyl-derived AGEs and incident CVD in the general population. We tested the hypothesis that major plasma AGEs are associated with new-onset CVD in 2 population-based cohorts of differing age and comorbidities. Methods and Results Analyses involved a random subcohort (n=466) from the Cardiovascular Health Study and a case-cohort sample (n=1631) from the Multi-Ethnic Study of Atherosclerosis. Five AGEs and 2 oxidative products were measured by liquid chromatography tandem mass spectrometry. Associations with CVD (myocardial infarction and stroke) were evaluated with Cox regression. Participants in the Cardiovascular Health Study were older than the Multi-Ethnic Study of Atherosclerosis, and had more comorbidities, along with higher levels of all AGEs. During median follow-up of 11 years, 439 participants in the Multi-Ethnic Study of Atherosclerosis and 200 in the Cardiovascular Health Study developed CVD. After multivariable adjustment, carboxymethyl-lysine, 3-deoxyglucosone hydroimidazolones and a summary variable of all measured AGEs (principal component 1) were significantly associated with incident CVD in the Cardiovascular Health Study (HRs [95% CI]: 1.20 [1.01, 1.42], 1.45 [1.23, 1.72], and 1.29 [1.06, 1.56], respectively), but not the Multi-Ethnic Study of Atherosclerosis. Oxidative products were not associated with CVD in either cohort. Conclusions We found α-dicarbonyl-derived AGEs to be associated with CVD in an older cohort, but not in a healthier middle-aged/older cohort. Our results suggest that AGEs may exert detrimental cardiovascular effects only under conditions of marked dicarbonyl and oxidative stress. Further investigation of α-dicarbonyl derivatives could lead to potential new strategies for CVD prevention in high-risk older populations.
Keywords: Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Glycation End Products, Advanced; Humans; Middle Aged; Risk Factors

Plasma proteomic signature of decline in gait speed and grip strength. - Liu, Xiaojuan; Pan, Stephanie; Xanthakis, Vanessa; Vasan, Ramachandran S; Psaty, Bruce M; Austin, Thomas R; Newman, Anne B; Sanders, Jason L; Wu, Chenkai; Tracy, Russell P; Gerszten, Robert E; Odden, Michelle C (Aging Cell, 2022)
The biological mechanisms underlying decline in physical function with age remain unclear. We examined the plasma proteomic profile associated with longitudinal changes in physical function measured by gait speed and grip strength in community-dwelling adults. We applied an aptamer-based platform to assay 1154 plasma proteins on 2854 participants (60% women, aged 76 years) in the Cardiovascular Health Study (CHS) in 1992-1993 and 1130 participants (55% women, aged 54 years) in the Framingham Offspring Study (FOS) in 1991-1995. Gait speed and grip strength were measured annually for 7 years in CHS and at cycles 7 (1998-2001) and 8 (2005-2008) in FOS. The associations of individual protein levels (log-transformed and standardized) with longitudinal changes in gait speed and grip strength in two populations were examined separately by linear mixed-effects models. Meta-analyses were implemented using random-effects models and corrected for multiple testing. We found that plasma levels of 14 and 18 proteins were associated with changes in gait speed and grip strength, respectively (corrected p < 0.05). The proteins most strongly associated with gait speed decline were GDF-15 (Meta-analytic p = 1.58 × 10 ), pleiotrophin (1.23 × 10 ), and TIMP-1 (5.97 × 10 ). For grip strength decline, the strongest associations were for carbonic anhydrase III (1.09 × 10 ), CDON (2.38 × 10 ), and SMOC1 (7.47 × 10 ). Several statistically significant proteins are involved in the inflammatory responses or antagonism of activin by follistatin pathway. These novel proteomic biomarkers and pathways should be further explored as future mechanisms and targets for age-related functional decline.
Keywords: Adult; Female; Gait; Hand Strength; Humans; Independent Living; Male; Proteomics; Walking Speed

Polygenic transcriptome risk scores for COPD and lung function improve cross-ethnic portability of prediction in the NHLBI TOPMed program. - Hu, Xiaowei; Qiao, Dandi; Kim, Wonji; Moll, Matthew; Balte, Pallavi P; Lange, Leslie A; Bartz, Traci M; Kumar, Rajesh; Li, Xingnan; Yu, Bing; Cade, Brian E; Laurie, Cecelia A; et al. (Am J Hum Genet, 2022)
While polygenic risk scores (PRSs) enable early identification of genetic risk for chronic obstructive pulmonary disease (COPD), predictive performance is limited when the discovery and target populations are not well matched. Hypothesizing that the biological mechanisms of disease are shared across ancestry groups, we introduce a PrediXcan-derived polygenic transcriptome risk score (PTRS) to improve cross-ethnic portability of risk prediction. We constructed the PTRS using summary statistics from application of PrediXcan on large-scale GWASs of lung function (forced expiratory volume in 1 s [FEV] and its ratio to forced vital capacity [FEV/FVC]) in the UK Biobank. We examined prediction performance and cross-ethnic portability of PTRS through smoking-stratified analyses both on 29,381 multi-ethnic participants from TOPMed population/family-based cohorts and on 11,771 multi-ethnic participants from TOPMed COPD-enriched studies. Analyses were carried out for two dichotomous COPD traits (moderate-to-severe and severe COPD) and two quantitative lung function traits (FEV and FEV/FVC). While the proposed PTRS showed weaker associations with disease than PRS for European ancestry, the PTRS showed stronger association with COPD than PRS for African Americans (e.g., odds ratio [OR] = 1.24 [95% confidence interval [CI]: 1.08-1.43] for PTRS versus 1.10 [0.96-1.26] for PRS among heavy smokers with ≥ 40 pack-years of smoking) for moderate-to-severe COPD. Cross-ethnic portability of the PTRS was significantly higher than the PRS (paired t test p < 2.2 × 10 with portability gains ranging from 5% to 28%) for both dichotomous COPD traits and across all smoking strata. Our study demonstrates the value of PTRS for improved cross-ethnic portability compared to PRS in predicting COPD risk.

Proteomics and Population Biology in the Cardiovascular Health Study (CHS): design of a study with mentored access and active data sharing. - Austin, Thomas R; McHugh, Caitlin P; Brody, Jennifer A; Bis, Joshua C; Sitlani, Colleen M; Bartz, Traci M; Biggs, Mary L; Bansal, Nisha; Bůzková, Petra; Carr, Steven A; deFilippi, Christopher R; Elkind, Mitchell S V; et al. (Eur J Epidemiol, 2022)
BACKGROUND: In the last decade, genomic studies have identified and replicated thousands of genetic associations with measures of health and disease and contributed to the understanding of the etiology of a variety of health conditions. Proteins are key biomarkers in clinical medicine and often drug-therapy targets. Like genomics, proteomics can advance our understanding of biology. METHODS AND RESULTS: In the setting of the Cardiovascular Health Study (CHS), a cohort study of older adults, an aptamer-based method that has high sensitivity for low-abundance proteins was used to assay 4979 proteins in frozen, stored plasma from 3188 participants (61% women, mean age 74 years). CHS provides active support, including central analysis, for seven phenotype-specific working groups (WGs). Each CHS WG is led by one or two senior investigators and includes 10 to 20 early or mid-career scientists. In this setting of mentored access, the proteomic data and analytic methods are widely shared with the WGs and investigators so that they may evaluate associations between baseline levels of circulating proteins and the incidence of a variety of health outcomes in prospective cohort analyses. We describe the design of CHS, the CHS Proteomics Study, characteristics of participants, quality control measures, and structural characteristics of the data provided to CHS WGs. We additionally highlight plans for validation and replication of novel proteomic associations. CONCLUSION: The CHS Proteomics Study offers an opportunity for collaborative data sharing to improve our understanding of the etiology of a variety of health conditions in older adults.

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Rare genetic variants explain missing heritability in smoking. - Jang, Seon-Kyeong; Evans, Luke; Fialkowski, Allison; Arnett, Donna K; Ashley-Koch, Allison E; Barnes, Kathleen C; Becker, Diane M; Bis, Joshua C; Blangero, John; Bleecker, Eugene R; Boorgula, Meher Preethi; Bowden, Donald W; et al. (Nat Hum Behav, 2022)
Common genetic variants explain less variation in complex phenotypes than inferred from family-based studies, and there is a debate on the source of this 'missing heritability'. We investigated the contribution of rare genetic variants to tobacco use with whole-genome sequences from up to 26,257 unrelated individuals of European ancestries and 11,743 individuals of African ancestries. Across four smoking traits, single-nucleotide-polymorphism-based heritability ([Formula: see text]) was estimated from 0.13 to 0.28 (s.e., 0.10-0.13) in European ancestries, with 35-74% of it attributable to rare variants with minor allele frequencies between 0.01% and 1%. These heritability estimates are 1.5-4 times higher than past estimates based on common variants alone and accounted for 60% to 100% of our pedigree-based estimates of narrow-sense heritability ([Formula: see text], 0.18-0.34). In the African ancestry samples, [Formula: see text] was estimated from 0.03 to 0.33 (s.e., 0.09-0.14) across the four smoking traits. These results suggest that rare variants are important contributors to the heritability of smoking.

Stroke genetics informs drug discovery and risk prediction across ancestries. - Mishra, Aniket; Malik, Rainer; Hachiya, Tsuyoshi; Jürgenson, Tuuli; Namba, Shinichi; Posner, Daniel C; Kamanu, Frederick K; Koido, Masaru; Le Grand, Quentin; Shi, Mingyang; He, Yunye; Georgakis, Marios K; et al. (Nature, 2022)
Previous genome-wide association studies (GWASs) of stroke - the second leading cause of death worldwide - were conducted predominantly in populations of European ancestry. Here, in cross-ancestry GWAS meta-analyses of 110,182 patients who have had a stroke (five ancestries, 33% non-European) and 1,503,898 control individuals, we identify association signals for stroke and its subtypes at 89 (61 new) independent loci: 60 in primary inverse-variance-weighted analyses and 29 in secondary meta-regression and multitrait analyses. On the basis of internal cross-ancestry validation and an independent follow-up in 89,084 additional cases of stroke (30% non-European) and 1,013,843 control individuals, 87% of the primary stroke risk loci and 60% of the secondary stroke risk loci were replicated (P < 0.05). Effect sizes were highly correlated across ancestries. Cross-ancestry fine-mapping, in silico mutagenesis analysis, and transcriptome-wide and proteome-wide association analyses revealed putative causal genes (such as SH3PXD2A and FURIN) and variants (such as at GRK5 and NOS3). Using a three-pronged approach, we provide genetic evidence for putative drug effects, highlighting F11, KLKB1, PROC, GP1BA, LAMC2 and VCAM1 as possible targets, with drugs already under investigation for stroke for F11 and PROC. A polygenic score integrating cross-ancestry and ancestry-specific stroke GWASs with vascular-risk factor GWASs (integrative polygenic scores) strongly predicted ischaemic stroke in populations of European, East Asian and African ancestry. Stroke genetic risk scores were predictive of ischaemic stroke independent of clinical risk factors in 52,600 clinical-trial participants with cardiometabolic disease. Our results provide insights to inform biology, reveal potential drug targets and derive genetic risk prediction tools across ancestries.

Targeted Genome Sequencing Identifies Multiple Rare Variants in Caveolin-1 Associated with Obstructive Sleep Apnea. - Liang, Jingjing; Wang, Heming; Cade, Brian E; Kurniansyah, Nuzulul; He, Karen Y; Lee, Jiwon; Sands, Scott A; Brody, Jennifer; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Respir Crit Care Med, 2022)
INTRODUCTION: Obstructive sleep apnea (OSA) is a common disorder associated with increased risk for cardiovascular disease, diabetes, and premature mortality. There is strong clinical and epi-demiologic evidence supporting the importance of genetic factors influencing OSA, but limited data implicating specific genes. METHODS: Leveraging high depth genomic sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program and imputed genotype data from multiple population-based studies, we performed linkage analysis in the Cleve-land Family Study (CFS) followed by multi-stage gene-based association analyses in independent cohorts to search for rare variants contributing to OSA severity as assessed by the apnea-hypopnea index (AHI) in a total of 7,708 individuals of European ancestry. RESULTS: Linkage analysis in CFS identified a suggestive linkage peak on chromosome 7q31 (LOD=2.31). Gene-based analysis identified 21 non-coding rare variants in Caveolin-1 (CAV1) associated with lower AHI after accounting for multiple comparisons (p=7.4×10-8). These non-coding variants together significantly contributed to the linkage evidence (p<10-3). Follow-up anal-ysis revealed significant associations between these variants and increased CAV1 expression, and increased CAV1 expression in peripheral monocytes was associated with lower AHI (p=0.024) and higher minimum overnight oxygen saturation (p=0.007). CONCLUSION: Rare variants in CAV1, a membrane scaffolding protein essential in multiple cellular and metabolic functions, are associated with higher CAV1 gene expression and lower OSA severity, suggesting a novel target for modulating OSA severity.

The Value of Rare Genetic Variation in the Prediction of Common Obesity in European Ancestry Populations. - Wang, Zhe; Choi, Shing Wan; Chami, Nathalie; Boerwinkle, Eric; Fornage, Myriam; Redline, Susan; Bis, Joshua C; Brody, Jennifer A; Psaty, Bruce M; Kim, Wonji; McDonald, Merry-Lynn N; Regan, Elizabeth A; et al. (Front Endocrinol (Lausanne), 2022)
Polygenic risk scores (PRSs) aggregate the effects of genetic variants across the genome and are used to predict risk of complex diseases, such as obesity. Current PRSs only include common variants (minor allele frequency (MAF) ≥1%), whereas the contribution of rare variants in PRSs to predict disease remains unknown. Here, we examine whether augmenting the standard common variant PRS (PRS) with a rare variant PRS (PRS) improves prediction of obesity. We used genome-wide genotyped and imputed data on 451,145 European-ancestry participants of the UK Biobank, as well as whole exome sequencing (WES) data on 184,385 participants. We performed single variant analyses (for both common and rare variants) and gene-based analyses (for rare variants) for association with BMI (kg/m), obesity (BMI ≥ 30 kg/m), and extreme obesity (BMI ≥ 40 kg/m). We built PRSs and PRSs using a range of methods (Clumping+Thresholding [C+T], PRS-CS, lassosum, gene-burden test). We selected the best-performing PRSs and assessed their performance in 36,757 European-ancestry unrelated participants with whole genome sequencing (WGS) data from the Trans-Omics for Precision Medicine (TOPMed) program. The best-performing PRS explained 10.1% of variation in BMI, and 18.3% and 22.5% of the susceptibility to obesity and extreme obesity, respectively, whereas the best-performing PRS explained 1.49%, and 2.97% and 3.68%, respectively. The PRS was associated with an increased risk of obesity and extreme obesity (OR = 1.37 per SD, = 1.7x10; OR = 1.55 per SD, = 3.8x10), which was attenuated, after adjusting for PRS (OR = 1.08 per SD, = 9.8x10; OR= 1.09 per SD, = 0.02). When PRS and PRS are combined, the increase in explained variance attributed to PRS was small (incremental Nagelkerke R = 0.24% for obesity and 0.51% for extreme obesity). Consistently, combining PRS to PRS provided little improvement to the prediction of obesity (PRS AUC = 0.591; PRS AUC = 0.708; PRS AUC = 0.710). In summary, while rare variants show convincing association with BMI, obesity and extreme obesity, the PRS provides limited improvement over PRS in the prediction of obesity risk, based on these large populations.
Keywords: Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Obesity; Whole Genome Sequencing

Whole exome sequencing of 14 389 individuals from the ESP and CHARGE consortia identifies novel rare variation associated with hemostatic factors. - Pankratz, Nathan; Wei, Peng; Brody, Jennifer A; Chen, Ming-Huei; Vries, Paul S; Huffman, Jennifer E; Stimson, Mary Rachel; Auer, Paul L; Boerwinkle, Eric; Cushman, Mary; Maat, Moniek P M; Folsom, Aaron R; et al. (Hum Mol Genet, 2022)
Plasma levels of fibrinogen, coagulation factors VII and VIII, and von Willebrand factor (vWF) are four intermediate phenotypes that are heritable and have been associated with the risk of clinical thrombotic events. To identify rare and low-frequency variants associated with these hemostatic factors, we conducted whole exome sequencing in 10 860 individuals of European ancestry (EA) and 3529 African Americans (AAs) from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium and the National Heart, Lung, and Blood Institute's Exome Sequencing Project (ESP). Gene-based tests demonstrated significant associations with rare variation (minor allele frequency < 5%) in FGG (with fibrinogen, p = 9.1x10-13), F7 (with factor VII, p = 1.3x10-72; seven novel variants), and VWF (with factor VIII and vWF; p = 3.2x10-14; one novel variant). These eight novel rare variant associations were independent of the known common variants at these loci and tended to have much larger effect sizes. In addition, one of the rare novel variants in F7 was significantly associated with an increased risk of venous thromboembolism in AAs (Ile200Ser; rs141219108; p = 4.2x10-5). After restricting gene-based analyses to only loss-of-function variants, a novel significant association was detected and replicated between factor VIII levels and a stop-gain mutation exclusive to African Americans (rs3211938) in CD36. This variant has previously been linked to dyslipidemia but not with levels of a hemostatic factor. These efforts represent the largest integration of whole exome sequence data from two national projects to identify genetic variation associated with plasma hemostatic factors.

Whole genome sequence association analysis of fasting glucose and fasting insulin levels in diverse cohorts from the NHLBI TOPMed program. - DiCorpo, Daniel; Gaynor, Sheila M; Russell, Emily M; Westerman, Kenneth E; Raffield, Laura M; Majarian, Timothy D; Wu, Peitao; Sarnowski, Chloe; Highland, Heather M; Jackson, Anne; Hasbani, Natalie R; de Vries, Paul S; et al. (Commun Biol, 2022)
The genetic determinants of fasting glucose (FG) and fasting insulin (FI) have been studied mostly through genome arrays, resulting in over 100 associated variants. We extended this work with high-coverage whole genome sequencing analyses from fifteen cohorts in NHLBI's Trans-Omics for Precision Medicine (TOPMed) program. Over 23,000 non-diabetic individuals from five race-ethnicities/populations (African, Asian, European, Hispanic and Samoan) were included. Eight variants were significantly associated with FG or FI across previously identified regions MTNR1B, G6PC2, GCK, GCKR and FOXA2. We additionally characterize suggestive associations with FG or FI near previously identified SLC30A8, TCF7L2, and ADCY5 regions as well as APOB, PTPRT, and ROBO1. Functional annotation resources including the Diabetes Epigenome Atlas were compiled for each signal (chromatin states, annotation principal components, and others) to elucidate variant-to-function hypotheses. We provide a catalog of nucleotide-resolution genomic variation spanning intergenic and intronic regions creating a foundation for future sequencing-based investigations of glycemic traits.
Keywords: Diabetes Mellitus, Type 2; Fasting; Glucose; Humans; Insulin; National Heart, Lung, and Blood Institute (U.S.); Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Precision Medicine; Receptors, Immunologic; United States

Whole genome sequencing identifies structural variants contributing to hematologic traits in the NHLBI TOPMed program. - Wheeler, Marsha M; Stilp, Adrienne M; Rao, Shuquan; Halldorsson, Bjarni V; Beyter, Doruk; Wen, Jia; Mihkaylova, Anna V; McHugh, Caitlin P; Lane, John; Jiang, Min-Zhi; Raffield, Laura M; Jun, Goo; et al. (Nat Commun, 2022)
Genome-wide association studies have identified thousands of single nucleotide variants and small indels that contribute to variation in hematologic traits. While structural variants are known to cause rare blood or hematopoietic disorders, the genome-wide contribution of structural variants to quantitative blood cell trait variation is unknown. Here we utilized whole genome sequencing data in ancestrally diverse participants of the NHLBI Trans Omics for Precision Medicine program (N = 50,675) to detect structural variants associated with hematologic traits. Using single variant tests, we assessed the association of common and rare structural variants with red cell-, white cell-, and platelet-related quantitative traits and observed 21 independent signals (12 common and 9 rare) reaching genome-wide significance. The majority of these associations (N = 18) replicated in independent datasets. In genome-editing experiments, we provide evidence that a deletion associated with lower monocyte counts leads to disruption of an S1PR3 monocyte enhancer and decreased S1PR3 expression.
Keywords: Blood Cells; Genome-Wide Association Study; Humans; Whole Genome Sequencing

Whole-Exome Sequencing Study Identifies Four Novel Gene Loci Associated with Diabetic Kidney Disease. - Pan, Yang; Sun, Xiao; Mi, Xuenan; Huang, Zhijie; Hsu, Yenchih; Hixson, James E; Munzy, Donna; Metcalf, Ginger; Franceschini, Nora; Tin, Adrienne; Köttgen, Anna; Francis, Michael; et al. (Hum Mol Genet, 2022)
Diabetic kidney disease (DKD) is recognized as an important public health challenge. However, its genomic mechanisms are poorly understood. To identify rare variants for DKD, we conducted a whole-exome sequencing (WES) study leveraging large cohorts well-phenotyped for chronic kidney disease (CKD) and diabetes. Our two-stage whole-exome sequencing study included 4372 European and African ancestry participants from the Chronic Renal Insufficiency Cohort (CRIC) and Atherosclerosis Risk in Communities (ARIC) studies (stage-1) and 11 487 multi-ancestry Trans-Omics for Precision Medicine (TOPMed) participants (stage-2). Generalized linear mixed models, which accounted for genetic relatedness and adjusted for age, sex, and ancestry, were used to test associations between single variants and DKD. Gene-based aggregate rare variant analyses were conducted using an optimized sequence kernel association test (SKAT-O) implemented within our mixed model framework. We identified four novel exome-wide significant DKD-related loci through initiating diabetes. In single variant analyses, participants carrying a rare, in-frame insertion in the DIS3L2 gene (rs141560952) exhibited a 193-fold increased odds (95% confidence interval: 33.6, 1105) of DKD compared with non-carriers (P = 3.59 × 10-9). Likewise, each copy of a low-frequency KRT6B splice-site variant (rs425827) conferred a 5.31-fold higher odds (95% confidence interval: 3.06, 9.21) of DKD (P = 2.72 × 10-9). Aggregate gene-based analyses further identified ERAP2 (P = 4.03 × 10-8) and NPEPPS (P = 1.51 × 10-7), which are both expressed in the kidney and implicated in renin-angiotensin-aldosterone system modulated immune response. In the largest WES study of DKD, we identified novel rare variant loci attaining exome-wide significance. These findings provide new insights into the molecular mechanisms underlying DKD.

Aberrant activation of TCL1A promotes stem cell expansion in clonal haematopoiesis. - Weinstock, Joshua S; Gopakumar, Jayakrishnan; Burugula, Bala Bharathi; Uddin, Md Mesbah; Jahn, Nikolaus; Belk, Julia A; Bouzid, Hind; Daniel, Bence; Miao, Zhuang; Ly, Nghi; Mack, Taralynn M; Luna, Sofia E; et al. (Nature, 2023)
Mutations in a diverse set of driver genes increase the fitness of haematopoietic stem cells (HSCs), leading to clonal haematopoiesis. These lesions are precursors for blood cancers, but the basis of their fitness advantage remains largely unknown, partly owing to a paucity of large cohorts in which the clonal expansion rate has been assessed by longitudinal sampling. Here, to circumvent this limitation, we developed a method to infer the expansion rate from data from a single time point. We applied this method to 5,071 people with clonal haematopoiesis. A genome-wide association study revealed that a common inherited polymorphism in the TCL1A promoter was associated with a slower expansion rate in clonal haematopoiesis overall, but the effect varied by driver gene. Those carrying this protective allele exhibited markedly reduced growth rates or prevalence of clones with driver mutations in TET2, ASXL1, SF3B1 and SRSF2, but this effect was not seen in clones with driver mutations in DNMT3A. TCL1A was not expressed in normal or DNMT3A-mutated HSCs, but the introduction of mutations in TET2 or ASXL1 led to the expression of TCL1A protein and the expansion of HSCs in vitro. The protective allele restricted TCL1A expression and expansion of mutant HSCs, as did experimental knockdown of TCL1A expression. Forced expression of TCL1A promoted the expansion of human HSCs in vitro and mouse HSCs in vivo. Our results indicate that the fitness advantage of several commonly mutated driver genes in clonal haematopoiesis may be mediated by TCL1A activation.
Keywords: Alleles; Animals; Clonal Hematopoiesis; Genome-Wide Association Study; Hematopoiesis; Hematopoietic Stem Cells; Humans; Mice; Mutation; Promoter Regions, Genetic

Association Between Acute Myocardial Infarction and Cognition. - Johansen, Michelle C; Ye, Wen; Gross, Alden; Gottesman, Rebecca F; Han, Dehua; Whitney, Rachael; Briceño, Emily M; Giordani, Bruno J; Shore, Supriya; Elkind, Mitchell S V; Manly, Jennifer J; Sacco, Ralph L; et al. (JAMA Neurol, 2023)
IMPORTANCE: The magnitude of cognitive change after incident myocardial infarction (MI) is unclear. OBJECTIVE: To assess whether incident MI is associated with changes in cognitive function after adjusting for pre-MI cognitive trajectories. DESIGN, SETTING, AND PARTICIPANTS: This cohort study included adults without MI, dementia, or stroke and with complete covariates from the following US population-based cohort studies conducted from 1971 to 2019: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study. Data were analyzed from July 2021 to January 2022. EXPOSURES: Incident MI. MAIN OUTCOMES AND MEASURES: The main outcome was change in global cognition. Secondary outcomes were changes in memory and executive function. Outcomes were standardized as mean (SD) T scores of 50 (10); a 1-point difference represented a 0.1-SD difference in cognition. Linear mixed-effects models estimated changes in cognition at the time of MI (change in the intercept) and the rate of cognitive change over the years after MI (change in the slope), controlling for pre-MI cognitive trajectories and participant factors, with interaction terms for race and sex. RESULTS: The study included 30 465 adults (mean [SD] age, 64 [10] years; 56% female), of whom 1033 had 1 or more MI event, and 29 432 did not have an MI event. Median follow-up was 6.4 years (IQR, 4.9-19.7 years). Overall, incident MI was not associated with an acute decrease in global cognition (-0.18 points; 95% CI, -0.52 to 0.17 points), executive function (-0.17 points; 95% CI, -0.53 to 0.18 points), or memory (0.62 points; 95% CI, -0.07 to 1.31 points). However, individuals with incident MI vs those without MI demonstrated faster declines in global cognition (-0.15 points per year; 95% CI, -0.21 to -0.10 points per year), memory (-0.13 points per year; 95% CI, -0.22 to -0.04 points per year), and executive function (-0.14 points per year; 95% CI, -0.20 to -0.08 points per year) over the years after MI compared with pre-MI slopes. The interaction analysis suggested that race and sex modified the degree of change in the decline in global cognition after MI (race × post-MI slope interaction term, P = .02; sex × post-MI slope interaction term, P = .04), with a smaller change in the decline over the years after MI in Black individuals than in White individuals (difference in slope change, 0.22 points per year; 95% CI, 0.04-0.40 points per year) and in females than in males (difference in slope change, 0.12 points per year; 95% CI, 0.01-0.23 points per year). CONCLUSIONS: This cohort study using pooled data from 6 cohort studies found that incident MI was not associated with a decrease in global cognition, memory, or executive function at the time of the event compared with no MI but was associated with faster declines in global cognition, memory, and executive function over time. These findings suggest that prevention of MI may be important for long-term brain health.

Association Between Whole Blood-Derived Mitochondrial DNA Copy Number, Low-Density Lipoprotein Cholesterol, and Cardiovascular Disease Risk. - Liu, Xue; Sun, Xianbang; Zhang, Yuankai; Jiang, Wenqing; Lai, Meng; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Haessler, Jeffrey; Zheng, Yinan; et al. (J Am Heart Assoc, 2023)
Background The relationship between mitochondrial DNA copy number (mtDNA CN) and cardiovascular disease remains elusive. Methods and Results We performed cross-sectional and prospective association analyses of blood-derived mtDNA CN and cardiovascular disease outcomes in 27 316 participants in 8 cohorts of multiple racial and ethnic groups with whole-genome sequencing. We also performed Mendelian randomization to explore causal relationships of mtDNA CN with coronary heart disease (CHD) and cardiometabolic risk factors (obesity, diabetes, hypertension, and hyperlipidemia). <0.01 was used for significance. We validated most of the previously reported associations between mtDNA CN and cardiovascular disease outcomes. For example, 1-SD unit lower level of mtDNA CN was associated with 1.08 (95% CI, 1.04-1.12; <0.001) times the hazard for developing incident CHD, adjusting for covariates. Mendelian randomization analyses showed no causal effect from a lower level of mtDNA CN to a higher CHD risk (β=0.091; =0.11) or in the reverse direction (β=-0.012; =0.076). Additional bidirectional Mendelian randomization analyses revealed that low-density lipoprotein cholesterol had a causal effect on mtDNA CN (β=-0.084; <0.001), but the reverse direction was not significant (=0.059). No causal associations were observed between mtDNA CN and obesity, diabetes, and hypertension, in either direction. Multivariable Mendelian randomization analyses showed no causal effect of CHD on mtDNA CN, controlling for low-density lipoprotein cholesterol level (=0.52), whereas there was a strong direct causal effect of higher low-density lipoprotein cholesterol on lower mtDNA CN, adjusting for CHD status (β=-0.092; <0.001). Conclusions Our findings indicate that high low-density lipoprotein cholesterol may underlie the complex relationships between mtDNA CN and vascular atherosclerosis.

Association of Immune Cell Subsets with Incident Hip Fracture: The Cardiovascular Health Study. - Elam, Rachel E; Bůzková, Petra; Delaney, Joseph A C; Fink, Howard A; Barzilay, Joshua I; Carbone, Laura D; Saha, Rick; Robbins, John A; Mukamal, Kenneth J; Valderrábano, Rodrigo J; Psaty, Bruce M; Tracy, Russell P; et al. (Calcif Tissue Int, 2023)
In this study, we aimed to evaluate the association of innate and adaptive immune cell subsets in peripheral blood mononuclear cells (PBMCs) with hip fracture. To conduct this study, we used data from the Cardiovascular Health Study (CHS), a U.S. multicenter observational cohort of community-dwelling men and women aged ≥ 65 years. Twenty-five immune cell phenotypes were measured by flow cytometry from cryopreserved PBMCs of CHS participants collected in 1998-1999. The natural killer (NK), γδ T, T helper 17 (Th17), and differentiated/senescent CD4CD28 T cell subsets were pre-specified as primary subsets of interest. Hip fracture incidence was assessed prospectively by review of hospitalization records. Multivariable Cox hazard models evaluated associations of immune cell phenotypes with incident hip fracture in sex-stratified and combined analyses. Among 1928 persons, 259 hip fractures occurred over a median 9.7 years of follow-up. In women, NK cells were inversely associated with hip fracture [hazard ratio (HR) 0.77, 95% confidence interval (CI) 0.60-0.99 per one standard deviation higher value] and Th17 cells were positively associated with hip fracture [HR 1.18, 95% CI 1.01-1.39]. In men, γδ T cells were inversely associated with hip fracture [HR 0.60, 95% CI 0.37-0.98]. None of the measured immune cell phenotypes were significantly associated with hip fracture incidence in combined analyses. In this large prospective cohort of older adults, potentially important sex differences in the associations of immune cell phenotypes and hip fracture were identified. However, immune cell phenotypes had no association with hip fracture in analyses combining men and women.

Association of Mitochondrial DNA Copy Number With Brain MRI Markers and Cognitive Function: A Meta-analysis of Community-Based Cohorts. - Zhang, Yuankai; Liu, Xue; Wiggins, Kerri L; Kurniansyah, Nuzulul; Guo, Xiuqing; Rodrigue, Amanda L; Zhao, Wei; Yanek, Lisa R; Ratliff, Scott M; Pitsillides, Achilleas; Aguirre Patiño, Juan Sebastian; Sofer, Tamar; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: Previous studies suggest lower mitochondrial DNA (mtDNA) copy number (CN) is associated with neurodegenerative diseases. However, whether mtDNA CN in whole blood is related to endophenotypes of Alzheimer's disease (AD) and AD related dementia (AD/ADRD) needs further investigation. We assessed the association of mtDNA CN with cognitive function and MRI measures in community-based samples of middle-aged to older adults. METHODS: We included dementia-free participants from nine diverse community-based cohorts with whole-genome sequencing in the Trans-Omics for Precision Medicine (TOPMed) program. Circulating mtDNA CN was estimated as twice the ratio of the average coverage of mtDNA to nuclear DNA. Brain MRI markers included total brain, hippocampal, and white matter hyperintensity volumes. General cognitive function was derived from distinct cognitive domains. We performed cohort-specific association analyses of mtDNA CN with AD/ADRD endophenotypes assessed within ±5 years (i.e., cross-sectional analyses) or 5 to 20 years after blood draw (i.e., prospective analyses) adjusting for potential confounders. We further explored associations stratified by sex and age (<60 vs. ≥60 years). Fixed-effects or sample size-weighted meta-analyses were performed to combine results. Finally, we performed Mendelian randomization (MR) analyses to assess causality. RESULTS: We included up to 19,152 participants (mean age 59 years, 57% women). Higher mtDNA CN was cross-sectionally associated with better general cognitive function (Beta=0.04; 95% CI 0.02, 0.06) independent of age, sex, batch effects, race/ethnicity, time between blood draw and cognitive evaluation, cohort-specific variables, and education. Additional adjustment for blood cell counts or cardiometabolic traits led to slightly attenuated results. We observed similar significant associations with cognition in prospective analyses, although of reduced magnitude. We found no significant associations between mtDNA CN and brain MRI measures in meta-analyses. MR analyses did not reveal a causal relation between mtDNA CN in blood and cognition. DISCUSSION: Higher mtDNA CN in blood is associated with better current and future general cognitive function in large and diverse communities across the US. Although MR analyses did not support a causal role, additional research is needed to assess causality. Circulating mtDNA CN could serve nevertheless as a biomarker of current and future cognitive function in the community.

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Boerwinkle, Eric; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.

Association of Severe Hypercholesterolemia and Familial Hypercholesterolemia Genotype With Risk of Coronary Heart Disease. - Zhang, Yiyi; Dron, Jacqueline S; Bellows, Brandon K; Khera, Amit V; Liu, Junxiu; Balte, Pallavi P; Oelsner, Elizabeth C; Amr, Sami Samir; Lebo, Matthew S; Nagy, Anna; Peloso, Gina M; Natarajan, Pradeep; et al. (Circulation, 2023)
Keywords: Coronary Disease; Genotype; Humans; Hypercholesterolemia; Hyperlipoproteinemia Type II

Carriers of rare damaging genetic variants are at lower risk of atherosclerotic disease. - Georgakis, Marios K; Malik, Rainer; Hasbani, Natalie R; Shakt, Gabrielle; Morrison, Alanna C; Tsao, Noah L; Judy, Renae; Mitchell, Braxton D; Xu, Huichun; Montasser, May E; Do, Ron; Kenny, Eimear E; et al. (medRxiv, 2023)
BACKGROUND: The CCL2/CCR2 axis governs monocyte trafficking and recruitment to atherosclerotic lesions. Human genetic analyses and population-based studies support an association between circulating CCL2 levels and atherosclerosis. Still, it remains unknown whether pharmacological targeting of CCR2, the main CCL2 receptor, would provide protection against human atherosclerotic disease. METHODS: In whole-exome sequencing data from 454,775 UK Biobank participants (40-69 years), we identified predicted loss-of-function (LoF) or damaging missense (REVEL score >0.5) variants within the gene. We prioritized variants associated with lower monocyte count (p<0.05) and tested associations with vascular risk factors and risk of atherosclerotic disease over a mean follow-up of 14 years. The results were replicated in a pooled cohort of three independent datasets (TOPMed, deCODE and Penn Medicine BioBank; total n=441,445) and the effect of the most frequent damaging variant was experimentally validated. RESULTS: A total of 45 predicted LoF or damaging missense variants were identified in the gene, 4 of which were also significantly associated with lower monocyte count, but not with other white blood cell counts. Heterozygous carriers of these variants were at a lower risk of a combined atherosclerosis outcome, showed a lower burden of atherosclerosis across four vascular beds, and were at a lower lifetime risk of coronary artery disease and myocardial infarction. There was no evidence of association with vascular risk factors including LDL-cholesterol, blood pressure, glycemic status, or C-reactive protein. Using a cAMP assay, we found that cells transfected with the most frequent damaging variant (3:46358273:T:A, M249K, 547 carriers, frequency: 0.14%) show a decrease in signaling in response to CCL2. The associations of the M249K variant with myocardial infarction were consistent across cohorts (OR : 0.62 95%CI: 0.39-0.96; OR : 0.64 95%CI: 0.34-1.19; OR : 0.64 95%CI: 0.45-0.90). In a phenome-wide association study, we found no evidence for higher risk of common infections or mortality among carriers of damaging variants. CONCLUSIONS: Heterozygous carriers of damaging variants have a lower burden of atherosclerosis and lower lifetime risk of myocardial infarction. In conjunction with previous evidence from experimental and epidemiological studies, our findings highlight the translational potential of CCR2-targeting as an atheroprotective approach.

Circulating differentiated and senescent lymphocyte subsets and incident diabetes risk in older adults: The Cardiovascular Health Study. - Olson, Nels C; Doyle, Margaret F; Bůzková, Petra; Huber, Sally A; de Boer, Ian H; Sitlani, Colleen M; Tracy, Russell P; Psaty, Bruce M; Mukamal, Kenneth J; Delaney, Joseph A (Endocrinol Diabetes Metab, 2023)
INTRODUCTION: Cellular senescence is a feature of aging implicated in the pathophysiology of diabetes mellitus (DM). Whether senescent lymphocytes are associated with the future occurrence of DM is uncertain. METHODS: We used cryopreserved peripheral blood mononuclear cells collected from 1860 Cardiovascular Health Study participants (average age 80.2 years) and flow cytometry immunophenotyping to evaluate the longitudinal relationships of naive (CD45RA ), memory (CD45RO ), senescent (CD28 ), and T effector memory RA (TEMRA) (CD28 CD57 CD45RA ) CD4 and CD8 T cells, and memory B cells (CD19 CD27 ), with the risk of incident DM. In exploratory analyses we evaluated the relationships of 13 additional innate lymphocyte and CD4 and CD8 subsets with incident DM risk. RESULTS: Over a median follow-up time of 8.9 years, 155 cases of incident DM occurred. In Cox models adjusted for demographic variables (age, sex, race, study site and flow cytometry analytical batch) or diabetes risk factors (demographic variables plus education, body mass index, smoking status, alcohol use, systolic blood pressure, hypertension medication use and physical activity), no significant associations were observed for any CD4 , CD8 or CD19 cell phenotypes with incident DM. CONCLUSIONS: These results suggest the frequencies of naive, memory and senescent T cells and memory B cells are not strongly associated with incident DM risk in older adults.
Keywords: CD28 Antigens; CD8-Positive T-Lymphocytes; Cellular Senescence; Diabetes Mellitus; Leukocytes, Mononuclear; Lymphocyte Subsets

Circulating Growth Differentiation Factors 11 and 8, Their Antagonists Follistatin and Follistatin-like-3, and Risk of Heart Failure in Elders. - Kizer, Jorge R; Patel, Sheena; Ganz, Peter; Newman, Anne B; Bhasin, Shalender; Lee, Se-Jin; Cawthon, Peggy M; LeBrasseur, Nathan; Shah, Sanjiv J; Psaty, Bruce M; Tracy, Russell P; Cummings, Steven R (J Gerontol A Biol Sci Med Sci, 2023)
BACKGROUND: Heterochronic parabiosis has identified growth differentiation factor (GDF)-11 as a potential means of cardiac rejuvenation, but findings have been inconsistent. A major barrier has been lack of assay specificity for GDF-11 and its homolog GDF-8. METHODS: We tested the hypothesis that GDF-11 and GDF-8, and their major antagonists follistatin and follistatin-like (FSTL)-3, are associated with incident heart failure (HF) and its subtypes in elders. Based on validation experiments, we used liquid chromatography tandem mass spectrometry to measure total serum GDF-11 and GDF-8, along with follistatin and follistatin-like (FSTL)-3 by immunoassay, in two longitudinal cohorts of older adults. RESULTS: In 2,599 participants (age 75.2±4.3) followed for 10.8±5.6 years, 721 HF events occurred. After adjustment, neither GDF-11 (HR per doubling: 0.93 [0.67, 1.30]) nor GDF-8 (HR: 1.02 per doubling [0.83, 1.27]) was associated with incident HF or its subtypes. Positive associations with HF were detected for follistatin (HR: 1.15 [1.00, 1.32]) and FLST-3 (HR: 1.38 [1.03, 1.85]), and with HF with preserved ejection fraction for FSTL-3 (HR: 1.77 [1.03, 3.02]). (All HRs per doubling of biomarker.) FSTL-3 associations with HF appeared stronger at higher follistatin levels and vice versa, and also for men, Blacks and lower kidney function. CONCLUSIONS: Among older adults, serum follistatin and FSTL-3, but not GDF-11 or GDF-8, were associated with incident HF. These findings do not support the concept that low serum levels of total GDF-11 or GDF-8 contribute to HF late in life, but do implicate transforming growth factor-βsuperfamily pathways as potential therapeutic targets.

Clonal hematopoiesis is associated with protection from Alzheimer's disease. - Bouzid, Hind; Belk, Julia A; Jan, Max; Qi, Yanyan; Sarnowski, Chloe; Wirth, Sara; Ma, Lisa; Chrostek, Matthew R; Ahmad, Herra; Nachun, Daniel; Yao, Winnie; Beiser, Alexa; et al. (Nat Med, 2023)
Clonal hematopoiesis of indeterminate potential (CHIP) is a premalignant expansion of mutated hematopoietic stem cells. As CHIP-associated mutations are known to alter the development and function of myeloid cells, we hypothesized that CHIP may also be associated with the risk of Alzheimer's disease (AD), a disease in which brain-resident myeloid cells are thought to have a major role. To perform association tests between CHIP and AD dementia, we analyzed blood DNA sequencing data from 1,362 individuals with AD and 4,368 individuals without AD. Individuals with CHIP had a lower risk of AD dementia (meta-analysis odds ratio (OR) = 0.64, P = 3.8 × 10), and Mendelian randomization analyses supported a potential causal association. We observed that the same mutations found in blood were also detected in microglia-enriched fraction of the brain in seven of eight CHIP carriers. Single-nucleus chromatin accessibility profiling of brain-derived nuclei in six CHIP carriers revealed that the mutated cells comprised a large proportion of the microglial pool in the samples examined. While additional studies are required to validate the mechanistic findings, these results suggest that CHIP may have a role in attenuating the risk of AD.

Clonal Hematopoiesis of Indeterminate Potential (CHIP) and Incident Type 2 Diabetes Risk. - Tobias, Deirdre K; Manning, Alisa K; Wessel, Jennifer; Raghavan, Sridharan; Westerman, Kenneth E; Bick, Alexander G; DiCorpo, Daniel; Whitsel, Eric A; Collins, Jason; Correa, Adolfo; Cupples, L Adrienne; Dupuis, Josée; et al. (Diabetes Care, 2023)
OBJECTIVE: Clonal hematopoiesis of indeterminate potential (CHIP) is an aging-related accumulation of somatic mutations in hematopoietic stem cells, leading to clonal expansion. CHIP presence has been implicated in atherosclerotic coronary heart disease (CHD) and all-cause mortality, but its association with incident type 2 diabetes (T2D) is unknown. We hypothesized that CHIP is associated with elevated risk of T2D. RESEARCH DESIGN AND METHODS: CHIP was derived from whole-genome sequencing of blood DNA in the National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine (TOPMed) prospective cohorts. We performed analysis for 17,637 participants from six cohorts, without prior T2D, cardiovascular disease, or cancer. We evaluated baseline CHIP versus no CHIP prevalence with incident T2D, including associations with DNMT3A, TET2, ASXL1, JAK2, and TP53 variants. We estimated multivariable-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) with adjustment for age, sex, BMI, smoking, alcohol, education, self-reported race/ethnicity, and combined cohorts' estimates via fixed-effects meta-analysis. RESULTS: Mean (SD) age was 63.4 (11.5) years, 76% were female, and CHIP prevalence was 6.0% (n = 1,055) at baseline. T2D was diagnosed in n = 2,467 over mean follow-up of 9.8 years. Participants with CHIP had 23% (CI = 1.04, 1.45) higher risk of T2D than those with no CHIP. Specifically, higher risk was for TET2 (HR 1.48; CI = 1.05, 2.08) and ASXL1 (HR 1.76; CI = 1.03, 2.99) mutations; DNMT3A was nonsignificant (HR 1.15; CI = 0.93, 1.43). Statistical power was limited for JAK2 and TP53 analyses. CONCLUSIONS: CHIP was associated with higher incidence of T2D. CHIP mutations located on genes implicated in CHD and mortality were also related to T2D, suggesting shared aging-related pathology.

Clonal Hematopoiesis of Indeterminate Potential is Associated with Acute Kidney Injury. - Vlasschaert, Caitlyn; Robinson-Cohen, Cassianne; Kestenbaum, Bryan; Silver, Samuel A; Chen, Jian-Chun; Akwo, Elvis; Bhatraju, Pavan K; Zhang, Ming-Zhi; Cao, Shirong; Jiang, Ming; Wang, Yinqiu; Niu, Aolei; et al. (medRxiv, 2023)
Age is a predominant risk factor for acute kidney injury (AKI), yet the biological mechanisms underlying this risk are largely unknown and to date no genetic mechanisms for AKI have been established. Clonal hematopoiesis of indeterminate potential (CHIP) is a recently recognized biological mechanism conferring risk of several chronic aging diseases including cardiovascular disease, pulmonary disease and liver disease. In CHIP, blood stem cells acquire mutations in myeloid cancer driver genes such as and and the myeloid progeny of these mutated cells contribute to end-organ damage through inflammatory dysregulation. We sought to establish whether CHIP causes acute kidney injury (AKI). To address this question, we first evaluated associations with incident AKI events in three population-based epidemiology cohorts (N = 442,153). We found that CHIP was associated with a greater risk of AKI (adjusted HR 1.26, 95% CI: 1.19-1.34, p<0.0001), which was more pronounced in patients with AKI requiring dialysis (adjusted HR 1.65, 95% CI: 1.24-2.20, p=0.001). The risk was particularly high in the subset of individuals where CHIP was driven by mutations in genes other than (HR: 1.49, 95% CI: 1.37-1.61, p<0.0001). We then examined the association between CHIP and recovery from AKI in the ASSESS-AKI cohort and identified that non- CHIP was more common among those with a non-resolving pattern of injury (HR 2.3, 95% CI: 1.14-4.64, p = 0.03). To gain mechanistic insight, we evaluated the role of -CHIP to AKI in ischemia-reperfusion injury (IRI) and unilateral ureteral obstruction (UUO) mouse models. In both models, we observed more severe AKI and greater post-AKI kidney fibrosis in -CHIP mice. Kidney macrophage infiltration was markedly increased in -CHIP mice and -CHIP mutant renal macrophages displayed greater pro-inflammatory responses. In summary, this work establishes CHIP as a genetic mechanism conferring risk of AKI and impaired kidney function recovery following AKI via an aberrant inflammatory response in CHIP derived renal macrophages.

Complexities of cerebral small vessel disease, blood pressure, and dementia relationship: new insights from genetics. - Sargurupremraj, Muralidharan; Soumaré, Aïcha; Bis, Joshua C; Surakka, Ida; Jürgenson, Tuuli; Joly, Pierre; Knol, Maria J; Wang, Ruiqi; Yang, Qiong; Satizabal, Claudia L; Gudjonsson, Alexander; Mishra, Aniket; et al. (medRxiv, 2023)
IMPORTANCE: There is increasing recognition that vascular disease, which can be treated, is a key contributor to dementia risk. However, the contribution of specific markers of vascular disease is unclear and, as a consequence, optimal prevention strategies remain unclear. OBJECTIVE: To disentangle the causal relation of several key vascular traits to dementia risk: (i) white matter hyperintensity (WMH) burden, a highly prevalent imaging marker of covert cerebral small vessel disease (cSVD); (ii) clinical stroke; and (iii) blood pressure (BP), the leading risk factor for cSVD and stroke, for which efficient therapies exist. To account for potential epidemiological biases inherent to late-onset conditions like dementia. DESIGN SETTING AND PARTICIPANTS: This study first explored the association of genetically determined WMH, BP levels and stroke risk with AD using summary-level data from large genome-wide association studies (GWASs) in a two-sample Mendelian randomization (MR) framework. Second, leveraging individual-level data from large longitudinal population-based cohorts and biobanks with prospective dementia surveillance, the association of weighted genetic risk scores (wGRSs) for WMH, BP, and stroke with incident all-cause-dementia was explored using Cox-proportional hazard and multi-state models. The data analysis was performed from July 26, 2020, through July 24, 2022. EXPOSURES: Genetically determined levels of WMH volume and BP (systolic, diastolic and pulse blood pressures) and genetic liability to stroke. MAIN OUTCOMES AND MEASURES: The summary-level MR analyses focused on the outcomes from GWAS of clinically diagnosed AD (n-cases=21,982) and GWAS additionally including self-reported parental history of dementia as a proxy for AD diagnosis (AD , n-cases=53,042). For the longitudinal analyses, individual-level data of 157,698 participants with 10,699 incident all-cause-dementia were studied, exploring AD, vascular or mixed dementia in secondary analyses. RESULTS: In the two-sample MR analyses, WMH showed strong evidence for a causal association with increased risk of AD (OR, 1.16; 95%CI:1.05-1.28; P=.003) and AD (OR, 1.28; 95%CI:1.07-1.53; P=.008), after accounting for genetically determined pulse pressure for the latter. Genetically predicted BP traits showed evidence for a protective association with both clinically defined AD and AD , with evidence for confounding by shared genetic instruments. In longitudinal analyses the wGRSs for WMH, but not BP or stroke, showed suggestive association with incident all-cause-dementia (HR, 1.02; 95%CI:1.00-1.04; P=.06). BP and stroke wGRSs were strongly associated with mortality but there was no evidence for selective survival bias during follow-up. In secondary analyses, polygenic scores with more liberal instrument definition showed association of both WMH and stroke with all-cause-dementia, AD, and vascular or mixed dementia; associations of stroke, but not WMH, with dementia outcomes were markedly attenuated after adjusting for interim stroke. CONCLUSION: These findings provide converging evidence that WMH is a leading vascular contributor to dementia risk, which may better capture the brain damage caused by BP (and other etiologies) than BP itself and should be targeted in priority for dementia prevention in the population. KEY POINTS: Do instrumental variable analyses leveraging genetic information provide evidence for a causal association of various vascular traits with Alzheimer's disease (AD) and all-cause-dementia? How do these associations compare for white matter hyperintensity (WMH) burden, a highly prevalent marker of covert cerebral small vessel disease (cSVD), stroke, and blood pressure traits, the strongest known risk factor for cSVD and stroke? Using Mendelian randomization (MR) leveraging large, published genome-wide association studies, this study showed a putative causal association of larger WMH burden with increased AD risk after accounting for pulse pressure effects, and some evidence for association of lower BP with AD risk with possible confounding by shared genetic instruments. Longitudinal analyses on individual-level data also supported association of genetically determined WMH with incident all-cause-dementia and AD, independently of interim stroke. This study using complementary genetic epidemiology approaches, identified increasing WMH burden to be associated with dementia and AD risk, suggesting the association as specific for cSVD and independent of BP and stroke.

Determinants of mosaic chromosomal alteration fitness. - Pershad, Yash; Mack, Taralynn; Poisner, Hannah; Jakubek, Yasminka A; Stilp, Adrienne M; Mitchell, Braxton D; Lewis, Joshua P; Boerwinkle, Eric; Loos, Ruth J; Chami, Nathalie; Wang, Zhe; Barnes, Kathleen; et al. (medRxiv, 2023)
Clonal hematopoiesis (CH) is characterized by the acquisition of a somatic mutation in a hematopoietic stem cell that results in a clonal expansion. These driver mutations can be single nucleotide variants in cancer driver genes or larger structural rearrangements called mosaic chromosomal alterations (mCAs). The factors that influence the variations in mCA fitness and ultimately result in different clonal expansion rates are not well-understood. We used the Passenger-Approximated Clonal Expansion Rate (PACER) method to estimate clonal expansion rate for 6,381 individuals in the NHLBI TOPMed cohort with gain, loss, and copy-neutral loss of heterozygosity mCAs. Our estimates of mCA fitness were correlated (R = 0.49) with an alternative approach that estimated fitness of mCAs in the UK Biobank using a theoretical probability distribution. Individuals with lymphoid-associated mCAs had a significantly higher white blood cell count and faster clonal expansion rate. In a cross-sectional analysis, genome-wide association study of estimates of mCA expansion rate identified , , and locus variants as modulators of mCA clonal expansion rate.

Effect of 2022 ACC/AHA/HFSA Criteria on Stages of Heart Failure in a Pooled Community Cohort. - Mohebi, Reza; Wang, Dongyu; Lau, Emily S; Parekh, Juhi K; Allen, Norrina; Psaty, Bruce M; Benjamin, Emelia J; Levy, Daniel; Wang, Thomas J; Shah, Sanjiv J; Gottdiener, John S; Januzzi, James L; et al. (J Am Coll Cardiol, 2023)
BACKGROUND: The 2022 American College of Cardiology (ACC)/American Heart Association (AHA)/Heart Failure Society of America (HFSA) clinical practice guideline proposed an updated definition for heart failure (HF) stages. OBJECTIVES: This study aimed to compare prevalence and prognosis of HF stages according to classification/definition originally described in 2013 and 2022 ACC/AHA/HFSA definitions. METHODS: Study participants from 3 longitudinal cohorts (the MESA [Multi-Ethnic Study of Atherosclerosis], CHS [Cardiovascular Health Study], and the FHS [Framingham Heart Study]), were categorized into 4 HF stages according to the 2013 and 2022 criteria. Cox proportional hazards regression was used to assess predictors of progression to symptomatic HF and adverse clinical outcomes associated with each HF stage. RESULTS: Among 11,618 study participants, according to the 2022 staging, 1,943 (16.7%) were healthy, 4,348 (37.4%) were in stage A (at risk), 5,019 (43.2%) were in stage B (pre-HF), and 308 (2.7%) were in stage C/D (symptomatic HF). Compared to the classification/definition originally described in 2013, the 2022 ACC/AHA/HFSA approach resulted in a higher proportion of individuals with stage B HF (increase from 15.9% to 43.2%); this shift disproportionately involved women as well as Hispanic and Black individuals. Despite the 2022 criteria designating a greater proportion of individuals as stage B, the relative risk of progression to symptomatic HF remained similar (HR: 10.61; 95% CI: 9.00-12.51; P < 0.001). CONCLUSIONS: New standards for HF staging resulted in a substantial shift of community-based individuals from stage A to stage B. Those with stage B HF in the new system were at high risk for progression to symptomatic HF.
Keywords: American Heart Association; Atherosclerosis; Cardiology; Female; Heart Failure; Humans; Longitudinal Studies; Prognosis; United States

Evaluating the use of blood pressure polygenic risk scores across race/ethnic background groups. - Kurniansyah, Nuzulul; Goodman, Matthew O; Khan, Alyna T; Wang, Jiongming; Feofanova, Elena; Bis, Joshua C; Wiggins, Kerri L; Huffman, Jennifer E; Kelly, Tanika; Elfassy, Tali; Guo, Xiuqing; Palmas, Walter; et al. (Nat Commun, 2023)
We assess performance and limitations of polygenic risk scores (PRSs) for multiple blood pressure (BP) phenotypes in diverse population groups. We compare "clumping-and-thresholding" (PRSice2) and LD-based (LDPred2) methods to construct PRSs from each of multiple GWAS, as well as multi-PRS approaches that sum PRSs with and without weights, including PRS-CSx. We use datasets from the MGB Biobank, TOPMed study, UK biobank, and from All of Us to train, assess, and validate PRSs in groups defined by self-reported race/ethnic background (Asian, Black, Hispanic/Latino, and White). For both SBP and DBP, the PRS-CSx based PRS, constructed as a weighted sum of PRSs developed from multiple independent GWAS, perform best across all race/ethnic backgrounds. Stratified analysis in All of Us shows that PRSs are better predictive of BP in females compared to males, individuals without obesity, and middle-aged (40-60 years) compared to older and younger individuals.
Keywords: Blood Pressure; Ethnicity; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Multifactorial Inheritance; Population Health; Risk Factors

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Genetic architecture of spatial electrical biomarkers for cardiac arrhythmia and relationship with cardiovascular disease. - Young, William J; Haessler, Jeffrey; Benjamins, Jan-Walter; Repetto, Linda; Yao, Jie; Isaacs, Aaron; Harper, Andrew R; Ramirez, Julia; Garnier, Sophie; Van Duijvenboden, Stefan; Baldassari, Antoine R; Concas, Maria Pina; et al. (Nat Commun, 2023)
The 3-dimensional spatial and 2-dimensional frontal QRS-T angles are measures derived from the vectorcardiogram. They are independent risk predictors for arrhythmia, but the underlying biology is unknown. Using multi-ancestry genome-wide association studies we identify 61 (58 previously unreported) loci for the spatial QRS-T angle (N = 118,780) and 11 for the frontal QRS-T angle (N = 159,715). Seven out of the 61 spatial QRS-T angle loci have not been reported for other electrocardiographic measures. Enrichments are observed in pathways related to cardiac and vascular development, muscle contraction, and hypertrophy. Pairwise genome-wide association studies with classical ECG traits identify shared genetic influences with PR interval and QRS duration. Phenome-wide scanning indicate associations with atrial fibrillation, atrioventricular block and arterial embolism and genetically determined QRS-T angle measures are associated with fascicular and bundle branch block (and also atrioventricular block for the frontal QRS-T angle). We identify potential biology involved in the QRS-T angle and their genetic relationships with cardiovascular traits and diseases, may inform future research and risk prediction.
Keywords: Arrhythmias, Cardiac; Atrioventricular Block; Biomarkers; Cardiovascular Diseases; Electrocardiography; Genome-Wide Association Study; Humans; Risk Factors

The genetic determinants of recurrent somatic mutations in 43,693 blood genomes. - Weinstock, Joshua S; Laurie, Cecelia A; Broome, Jai G; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Lewis, Joshua P; Boerwinkle, Eric; Barnes, Kathleen C; Chami, Nathalie; Kenny, Eimear E; et al. (Sci Adv, 2023)
Nononcogenic somatic mutations are thought to be uncommon and inconsequential. To test this, we analyzed 43,693 National Heart, Lung and Blood Institute Trans-Omics for Precision Medicine blood whole genomes from 37 cohorts and identified 7131 non-missense somatic mutations that are recurrently mutated in at least 50 individuals. These recurrent non-missense somatic mutations (RNMSMs) are not clearly explained by other clonal phenomena such as clonal hematopoiesis. RNMSM prevalence increased with age, with an average 50-year-old having 27 RNMSMs. Inherited germline variation associated with RNMSM acquisition. These variants were found in genes involved in adaptive immune function, proinflammatory cytokine production, and lymphoid lineage commitment. In addition, the presence of eight specific RNMSMs associated with blood cell traits at effect sizes comparable to Mendelian genetic mutations. Overall, we found that somatic mutations in blood are an unexpectedly common phenomenon with ancestry-specific determinants and human health consequences.
Keywords: Germ-Line Mutation; Hematopoiesis; Humans; Middle Aged; Mutation; Mutation, Missense; Phenotype

Inflammation and Incident Conduction Disease. - Frimodt-Møller, Emilie K; Gottdiener, John S; Soliman, Elsayed Z; Kizer, Jorge R; Vittinghoff, Eric; Psaty, Bruce M; Biering-Sørensen, Tor; Marcus, Gregory M (J Am Heart Assoc, 2023)
Keywords: Cardiac Conduction System Disease; Electrocardiography; Heart Block; Humans; Inflammation

Late-life plasma proteins associated with prevalent and incident frailty: A proteomic analysis. - Liu, Fangyu; Austin, Thomas R; Schrack, Jennifer A; Chen, Jingsha; Walston, Jeremy; Mathias, Rasika A; Grams, Morgan; Odden, Michelle C; Newman, Anne; Psaty, Bruce M; Ramonfaur, Diego; Shah, Amil M; et al. (Aging Cell, 2023)
Proteomic approaches have unique advantages in the identification of biological pathways that influence physical frailty, a multifactorial geriatric syndrome predictive of adverse health outcomes in older adults. To date, proteomic studies of frailty are scarce, and few evaluated prefrailty as a separate state or examined predictors of incident frailty. Using plasma proteins measured by 4955 SOMAmers in the Atherosclerosis Risk in Community study, we identified 134 and 179 proteins cross-sectionally associated with prefrailty and frailty, respectively, after Bonferroni correction (p < 1 × 10 ) among 3838 older adults aged ≥65 years, adjusting for demographic and physiologic factors and chronic diseases. Among them, 23 (17%) and 82 (46%) were replicated in the Cardiovascular Health Study using the same models (FDR p < 0.05). Notably, higher odds of prefrailty and frailty were observed with higher levels of growth differentiation factor 15 (GDF15; p  = 1 × 10 , p  = 2 × 10 ), transgelin (TAGLN; p  = 2 × 10 , p  = 6 × 10 ), and insulin-like growth factor-binding protein 2 (IGFBP2; p  = 5 × 10 , p  = 1 × 10 ) and with a lower level of growth hormone receptor (GHR, p  = 3 × 10 , p  = 2 × 10 ). Longitudinally, we identified 4 proteins associated with incident frailty (p < 1 × 10 ). Higher levels of triggering receptor expressed on myeloid cells 1 (TREM1), TAGLN, and heart and adipocyte fatty-acid binding proteins predicted incident frailty. Differentially regulated proteins were enriched in pathways and upstream regulators related to lipid metabolism, angiogenesis, inflammation, and cell senescence. Our findings provide a set of plasma proteins and biological mechanisms that were dysregulated in both the prodromal and the clinical stage of frailty, offering new insights into frailty etiology and targets for intervention.

Lifestyle habits associated with cardiac conduction disease. - Frimodt-Møller, Emilie K; Soliman, Elsayed Z; Kizer, Jorge R; Vittinghoff, Eric; Psaty, Bruce M; Biering-Sørensen, Tor; Gottdiener, John S; Marcus, Gregory M (Eur Heart J, 2023)
AIMS: Cardiac conduction disease can lead to syncope, heart failure, and death. The only available therapy is pacemaker implantation, with no established prevention strategies. Research to identify modifiable risk factors has been scant. METHODS AND RESULTS: Data from the Cardiovascular Health Study, a population-based cohort study of adults ≥ 65 years with annual 12-lead electrocardiograms obtained over 10 years, were utilized to examine relationships between baseline characteristics, including lifestyle habits, and conduction disease. Of 5050 participants (mean age 73 ± 6 years; 52% women), prevalent conduction disease included 257 with first-degree atrioventricular block, 99 with left anterior fascicular block, 9 with left posterior fascicular block, 193 with right bundle branch block (BBB), 76 with left BBB, and 102 with intraventricular block at baseline. After multivariable adjustment, older age, male sex, a larger body mass index, hypertension, and coronary heart disease were associated with a higher prevalence of conduction disease, whereas White race and more physical activity were associated with a lower prevalence. Over a median follow-up on 7 (interquartile range 1-9) years, 1036 developed incident conduction disease. Older age, male sex, a larger BMI, and diabetes were each associated with incident conduction disease. Of lifestyle habits, more physical activity (hazard ratio 0.91, 95% confidence interval 0.84-0.98, P = 0.017) was associated with a reduced risk, while smoking and alcohol did not exhibit a significant association. CONCLUSION: While some difficult to control comorbidities were associated with conduction disease as expected, a readily modifiable lifestyle factor, physical activity, was associated with a lower risk.

Machine learning models for blood pressure phenotypes combining multiple polygenic risk scores. - Hrytsenko, Yana; Shea, Benjamin; Elgart, Michael; Kurniansyah, Nuzulul; Lyons, Genevieve; Morrison, Alanna C; Carson, April P; Haring, Bernhard; Mitchel, Braxton D; Psaty, Bruce M; Jaeger, Byron C; Gu, C Charles; et al. (medRxiv, 2023)
We construct non-linear machine learning (ML) prediction models for systolic and diastolic blood pressure (SBP, DBP) using demographic and clinical variables and polygenic risk scores (PRSs). We developed a two-model ensemble, consisting of a baseline model, where prediction is based on demographic and clinical variables only, and a genetic model, where we also include PRSs. We evaluate the use of a linear versus a non-linear model at both the baseline and the genetic model levels and assess the improvement in performance when incorporating multiple PRSs. We report the ensemble model's performance as percentage variance explained (PVE) on a held-out test dataset. A non-linear baseline model improved the PVEs from 28.1% to 30.1% (SBP) and 14.3% to 17.4% (DBP) compared with a linear baseline model. Including seven PRSs in the genetic model computed based on the largest available GWAS of SBP/DBP improved the genetic model PVE from 4.8% to 5.1% (SBP) and 4.7% to 5% (DBP) compared to using a single PRS. Adding additional 14 PRSs computed based on two independent GWASs further increased the genetic model PVE to 6.3% (SBP) and 5.7% (DBP). PVE differed across self-reported race/ethnicity groups, with primarily all non-White groups benefitting from the inclusion of additional PRSs.

Multi-ancestry genome-wide study identifies effector genes and druggable pathways for coronary artery calcification. - Kavousi, Maryam; Bos, Maxime M; Barnes, Hanna J; Lino Cardenas, Christian L; Wong, Doris; Lu, Haojie; Hodonsky, Chani J; Landsmeer, Lennart P L; Turner, Adam W; Kho, Minjung; Hasbani, Natalie R; de Vries, Paul S; et al. (Nat Genet, 2023)
Coronary artery calcification (CAC), a measure of subclinical atherosclerosis, predicts future symptomatic coronary artery disease (CAD). Identifying genetic risk factors for CAC may point to new therapeutic avenues for prevention. Currently, there are only four known risk loci for CAC identified from genome-wide association studies (GWAS) in the general population. Here we conducted the largest multi-ancestry GWAS meta-analysis of CAC to date, which comprised 26,909 individuals of European ancestry and 8,867 individuals of African ancestry. We identified 11 independent risk loci, of which eight were new for CAC and five had not been reported for CAD. These new CAC loci are related to bone mineralization, phosphate catabolism and hormone metabolic pathways. Several new loci harbor candidate causal genes supported by multiple lines of functional evidence and are regulators of smooth muscle cell-mediated calcification ex vivo and in vitro. Together, these findings help refine the genetic architecture of CAC and extend our understanding of the biological and potential druggable pathways underlying CAC.

Multi-ancestry genome-wide study in >2.5 million individuals reveals heterogeneity in mechanistic pathways of type 2 diabetes and complications. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Rayner, Nigel W; Bocher, Ozvan; Ana Luiza de, S V Arruda; Sonehara, Kyuto; et al. (medRxiv, 2023)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes. To characterise the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study (GWAS) data from 2,535,601 individuals (39.7% non-European ancestry), including 428,452 T2D cases. We identify 1,289 independent association signals at genome-wide significance (P<5×10 ) that map to 611 loci, of which 145 loci are previously unreported. We define eight non-overlapping clusters of T2D signals characterised by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial, and enteroendocrine cells. We build cluster-specific partitioned genetic risk scores (GRS) in an additional 137,559 individuals of diverse ancestry, including 10,159 T2D cases, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned GRS are more strongly associated with coronary artery disease and end-stage diabetic nephropathy than an overall T2D GRS across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings demonstrate the value of integrating multi-ancestry GWAS with single-cell epigenomics to disentangle the aetiological heterogeneity driving the development and progression of T2D, which may offer a route to optimise global access to genetically-informed diabetes care.

Multi-ancestry transcriptome-wide association analyses yield insights into tobacco use biology and drug repurposing. - Chen, Fang; Wang, Xingyan; Jang, Seon-Kyeong; Quach, Bryan C; Weissenkampen, J Dylan; Khunsriraksakul, Chachrit; Yang, Lina; Sauteraud, Renan; Albert, Christine M; Allred, Nicholette D D; Arnett, Donna K; Ashley-Koch, Allison E; et al. (Nat Genet, 2023)
Most transcriptome-wide association studies (TWASs) so far focus on European ancestry and lack diversity. To overcome this limitation, we aggregated genome-wide association study (GWAS) summary statistics, whole-genome sequences and expression quantitative trait locus (eQTL) data from diverse ancestries. We developed a new approach, TESLA (multi-ancestry integrative study using an optimal linear combination of association statistics), to integrate an eQTL dataset with a multi-ancestry GWAS. By exploiting shared phenotypic effects between ancestries and accommodating potential effect heterogeneities, TESLA improves power over other TWAS methods. When applied to tobacco use phenotypes, TESLA identified 273 new genes, up to 55% more compared with alternative TWAS methods. These hits and subsequent fine mapping using TESLA point to target genes with biological relevance. In silico drug-repurposing analyses highlight several drugs with known efficacy, including dextromethorphan and galantamine, and new drugs such as muscle relaxants that may be repurposed for treating nicotine addiction.
Keywords: Biology; Drug Repositioning; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Tobacco Use; Transcriptome

Multiple Prior Live Births are Associated with Cardiac Remodeling and Heart Failure Risk in Women. - Sarma, Amy A; Paniagua, Samantha M; Lau, Emily S; Wang, Dongyu; Liu, Elizabeth E; Larson, Martin G; Hamburg, Naomi M; Mitchell, Gary F; Kizer, Jorge; Psaty, Bruce M; Allen, Norrina B; Lely, A Titia; et al. (J Card Fail, 2023)
INTRODUCTION: Greater parity has been associated with cardiovascular disease risk, though effects on cardiac remodeling and heart failure risk remain unclear. METHODS: We examined the association of number of live births and echocardiographic measures of cardiac structure and function in participants of the Framingham Heart Study (FHS) using multivariable linear regression. We next examined the association of parity with incident heart failure with preserved (HFpEF) or reduced (HFrEF) ejection fraction using a Fine-Gray subdistribution hazards model in a pooled analysis of n=12,635 participants of FHS, the Cardiovascular Health Study, the Multi-Ethnic Study of Atherosclerosis, and Prevention of Renal and Vascular Endstage Disease. Secondary analyses included major CVD, MI, and stroke. RESULTS: Among n=3931 FHS participants (mean age 48 ± 13 years), higher number of live births was associated with worse LV fractional shortening (multivariable β -1.11 (0.31), p= 0.0005 in ≥ 5 live births vs nulliparous women) and worse cardiac mechanics including global circumferential strain and longitudinal and radial dyssynchrony (p< 0.01 for all comparing ≥ 5 live births vs nulliparity). When examining HF subtypes, women with ≥5 live births were at higher risk of developing future HFrEF compared with nulliparous women (HR 1.93, 95% CI 1.19-3.12, p=0.008); by contrast, a lower risk of HFpEF was observed (HR 0.58, 95% CI 0.37-0.91, p=0.02). CONCLUSIONS: Greater number of live births are associated with worse cardiac structure and function. While there was no association with overall HF, a higher number of live births was associated with greater risk for incident HFrEF.

Plasma Ceramides and Sphingomyelins and Sudden Cardiac Death in the Cardiovascular Health Study. - Bockus, Lee B; Jensen, Paul N; Fretts, Amanda M; Hoofnagle, Andrew N; McKnight, Barbara; Sitlani, Colleen M; Siscovick, David S; King, Irena B; Psaty, Bruce M; Sotoodehnia, Nona; Lemaitre, Rozenn N (JAMA Netw Open, 2023)
IMPORTANCE: Sphingolipids, including ceramides and sphingomyelins, may influence the pathophysiology and risk of sudden cardiac death (SCD) through multiple biological activities. Whether the length of the fatty acid acylated to plasma sphingolipid species is associated with SCD risk is not known. OBJECTIVE: To determine whether the saturated fatty acid length of plasma ceramides and sphingomyelins influences the association with SCD risk. DESIGN, SETTING, AND PARTICIPANTS: In this cohort study, multivariable Cox proportional hazards regression models were used to examine the association of sphingolipid species with SCD risk. The study population included 4612 participants in the Cardiovascular Health Study followed up prospectively for a median of 10.2 (IQR, 5.5-11.6) years. Baseline data were collected from January 1992 to December 1995 during annual examinations. Data were analyzed from February 11, 2020, to September 9, 2023. EXPOSURES: Eight plasma sphingolipid species (4 ceramides and 4 sphingomyelins) with saturated fatty acids of 16, 20, 22, and 24 carbons. MAIN OUTCOME AND MEASURE: Association of plasma ceramides and sphingomyelins with saturated fatty acids of different lengths with SCD risk. RESULTS: Among the 4612 CHS participants included in the analysis (mean [SD] age, 77 [5] years; 2724 [59.1%] women; 6 [0.1%] American Indian; 4 [0.1%] Asian; 718 [15.6%] Black; 3869 [83.9%] White, and 15 [0.3%] Other), 215 SCD cases were identified. In adjusted Cox proportional hazards regression analyses, plasma ceramides and sphingomyelins with palmitic acid (Cer-16 and SM-16) were associated with higher SCD risk per higher SD of log sphingolipid levels (hazard ratio [HR] for Cer-16, 1.34 [95% CI, 1.12-1.59]; HR for SM-16, 1.37 [95% CI, 1.12-1.67]). Associations did not differ by baseline age, sex, race, or body mass index. No significant association of SCD with sphingolipids with very-long-chain saturated fatty acids was observed after correction for multiple testing (HR for ceramide with arachidic acid, 1.06 [95% CI, 0.90-1.24]; HR for ceramide with behenic acid, 0.92 [95% CI, 0.77-1.10]; HR for ceramide with lignoceric acid, 0.92 [95% CI, 0.77-1.09]; HR for sphingomyelin with arachidic acid, 0.83 [95% CI, 0.71-0.98]; HR for sphingomyelin with behenic acid, 0.84 [95% CI, 0.70-1.00]; HR for sphingomyelin with lignoceric acid, 0.86 [95% CI, 0.72-1.03]). CONCLUSIONS AND RELEVANCE: The findings of this large, population-based cohort study of SCD identified that higher plasma levels of Cer-16 and SM-16 were associated with higher risk of SCD. Future studies are needed to examine the underlying mechanism of these associations.
Keywords: Aged; Ceramides; Cohort Studies; Death, Sudden, Cardiac; Eicosanoic Acids; Fatty Acids; Female; Humans; Male; Sphingolipids; Sphingomyelins

Plasma Proteomic Associations With Incident Ischemic Stroke in Older Adults: The Cardiovascular Health Study. - Kalani, Rizwan; Bartz, Traci M; Psaty, Bruce M; Elkind, Mitchell S V; Floyd, James S; Gerszten, Robert E; Shojaie, Ali; Heckbert, Susan R; Bis, Joshua C; Austin, Thomas R; Tirschwell, David L; Delaney, Joseph A C; et al. (Neurology, 2023)
BACKGROUND: Plasma proteomics may elucidate novel insights into the pathophysiology of ischemic stroke (IS), identify biomarkers of IS risk, and guide development of nascent prevention strategies. We evaluated the relationship between the plasma proteome and IS risk in the population-based Cardiovascular Health Study (CHS). METHODS: Eligible CHS participants were free of prevalent stroke and underwent quantification of 1298 plasma proteins using the aptamer-based SOMAScan assay platform from the 1992-1993 study visit. Multivariable Cox proportional hazards regression was used to evaluate associations between a 1-standard deviation increase in the log-2 transformed estimated plasma protein concentrations and incident IS, adjusting for demographics, IS risk factors, and estimated glomerular filtration rate. For proteins independently associated with incident IS, a secondary stratified analysis evaluated associations in subgroups defined by sex and race. Exploratory analyses evaluated plasma proteomic associations with cardioembolic and non-cardioembolic IS as well as proteins associated with IS risk in participants with left atrial dysfunction but without atrial fibrillation. RESULTS: Of 2983 eligible participants, the mean age was 74.3 (± 4.8) years, 61.2% were women, and 15.4% were Black. Over a median follow-up of 12.6 years, 450 participants experienced an incident IS. N-terminal pro-brain natriuretic peptide (NTproBNP, adjusted HR 1.37, 95% CI 1.23-1.53, P=2.08x10) and macrophage metalloelastase (MMP12, adjusted HR 1.30, 95% CI 1.16-1.45, P=4.55x10) were independently associated with IS risk. These two associations were similar in men and women and in Black and non-Black participants. In exploratory analyses, NTproBNP was independently associated with incident cardioembolic IS, E-selectin with incident non-cardioembolic IS, and secreted frizzled-related protein 1 with IS risk in participants with left atrial dysfunction. CONCLUSIONS: In a cohort of older adults, NTproBNP and MMP12 were independently associated with IS risk. We identified plasma proteomic determinants of incident cardioembolic and non-cardioembolic IS and found a novel protein associated with IS risk in those with left atrial dysfunction.

Plasma sphingolipids, lung function and COPD: the Cardiovascular Health Study. - Gharib, Arya R; Jensen, Paul N; Psaty, Bruce M; Hoofnagle, Andrew N; Siscovick, David; Gharib, Sina A; Sitlani, Colleen M; Sotoodehnia, Nona; Lemaitre, Rozenn N (ERJ Open Res, 2023)
RATIONALE: COPD is the third leading cause of death in the United States. Sphingolipids, structural membrane constituents that play a role in cellular stress and apoptosis signalling, may be involved in lung function. METHODS: In the Cardiovascular Health Study, a prospective cohort of older adults, we cross-sectionally examined the association of plasma levels of 17 sphingolipid species with lung function and COPD. Multivariable linear regression and logistic regression were used to evaluate associations of sphingolipid concentrations with forced expiratory volume in 1 s (FEV) and odds of COPD, respectively. RESULTS: Of the 17 sphingolipids evaluated, ceramide-18 (Cer-18) and sphingomyelin-18 (SM-18) were associated with lower FEV values (-0.061 L per two-fold higher Cer-18, p=0.001; -0.092 L per two-fold higher SM-18, p=0.002) after correction for multiple testing. Several other associations were significant at a 0.05 level, but did not reach statistical significance after correction for multiple testing. Specifically, Cer-18 and SM-18 were associated with higher odds of COPD (odds ratio per two-fold higher Cer-18 1.29, p=0.03 and SM-18 1.73, p=0.008). Additionally, Cer-16 and SM-16 were associated with lower FEV values, and Cer-14, SM-14 and SM-16 with a higher odds of COPD. CONCLUSION: In this large cross-sectional study, specific ceramides and sphingomyelins were associated with reduced lung function in a population-based study. Future studies are needed to examine whether these biomarkers are associated with longitudinal change in FEV within individuals or with incident COPD.

Plasma Trimethylamine--Oxide and Incident Ischemic Stroke: The Cardiovascular Health Study and the Multi-Ethnic Study of Atherosclerosis. - Lemaitre, Rozenn N; Jensen, Paul N; Wang, Zeneng; Fretts, Amanda M; Sitlani, Colleen M; Nemet, Ina; Sotoodehnia, Nona; de Oliveira Otto, Marcia C; Zhu, Weifei; Budoff, Matt; Longstreth, W T; Psaty, Bruce M; et al. (J Am Heart Assoc, 2023)
Background The association of circulating trimethylamine--oxide (TMAO) with stroke has received limited attention. To address this gap, we examined the associations of serial measures of plasma TMAO with incident ischemic stroke. Methods and Results We used a prospective cohort design with data pooled from 2 cohorts. The settings were the CHS (Cardiovascular Health Study), a cohort of older adults, and the MESA (Multi-Ethnic Study of Atherosclerosis), both in the United States. We measured plasma concentrations of TMAO at baseline and again during the follow-up using high-performance liquid chromatography and mass spectrometry. We assessed the association of plasma TMAO with incident ischemic stroke using proportional hazards regression adjusted for risk factors. The combined cohorts included 11 785 participants without a history of stroke, on average 73 (CHS) and 62 (MESA) years old at baseline, including 60% (CHS) and 53% (MESA) women. We identified 1031 total incident ischemic strokes during a median 15-year follow-up in the combined cohorts. In multivariable analyses, TMAO was significantly associated with incident ischemic stroke risk (hazard ratios comparing a doubling of TMAO: 1.11 [1.03-1.18], =0.004). The association was linear over the range of TMAO concentrations and appeared restricted to those without diagnosed coronary heart disease. An association with hemorrhagic stroke was not found. Conclusions Plasma TMAO levels are associated with incident ischemic stroke in a diverse population. Registration URL: https://www.clinicaltrials.gov. Unique identifier: NCT00005133.
Keywords: Aged; Atherosclerosis; Female; Humans; Ischemic Stroke; Methylamines; Oxides; Prospective Studies; Risk Factors; Stroke; United States

Powerful, scalable and resource-efficient meta-analysis of rare variant associations in large whole genome sequencing studies. - Li, Xihao; Quick, Corbin; Zhou, Hufeng; Gaynor, Sheila M; Liu, Yaowu; Chen, Han; Selvaraj, Margaret Sunitha; Sun, Ryan; Dey, Rounak; Arnett, Donna K; Bielak, Lawrence F; Bis, Joshua C; et al. (Nat Genet, 2023)
Meta-analysis of whole genome sequencing/whole exome sequencing (WGS/WES) studies provides an attractive solution to the problem of collecting large sample sizes for discovering rare variants associated with complex phenotypes. Existing rare variant meta-analysis approaches are not scalable to biobank-scale WGS data. Here we present MetaSTAAR, a powerful and resource-efficient rare variant meta-analysis framework for large-scale WGS/WES studies. MetaSTAAR accounts for relatedness and population structure, can analyze both quantitative and dichotomous traits and boosts the power of rare variant tests by incorporating multiple variant functional annotations. Through meta-analysis of four lipid traits in 30,138 ancestrally diverse samples from 14 studies of the Trans Omics for Precision Medicine (TOPMed) Program, we show that MetaSTAAR performs rare variant meta-analysis at scale and produces results comparable to using pooled data. Additionally, we identified several conditionally significant rare variant associations with lipid traits. We further demonstrate that MetaSTAAR is scalable to biobank-scale cohorts through meta-analysis of TOPMed WGS data and UK Biobank WES data of ~200,000 samples.
Keywords: Exome Sequencing; Genome-Wide Association Study; Lipids; Phenotype; Whole Genome Sequencing

Prediction of Multiple Individual Primary Cardiovascular Events Using Pooled Cohorts. - Sussman, Jeremy B; Whitney, Rachael T; Burke, James F; Hayward, Rodney A; Galecki, Andrzej; Sidney, Stephen; Allen, Norrina Bai; Gottesman, Rebecca F; Heckbert, Susan R; Longstreth, William T; Psaty, Bruce M; Elkind, Mitchell S V; et al. (medRxiv, 2023)
INTRODUCTION: Most current clinical risk prediction scores for cardiovascular disease prevention use a composite outcome. Risk prediction scores for specific cardiovascular events could identify people who are at higher risk for some events than others informing personalized care and trial recruitment. We sought to predict risk for multiple different events, describe how those risks differ, and examine if these differences could improve treatment priorities. METHODS: We used participant-level data from five cohort studies. We included participants between 40 and 79 years old who had no history of myocardial infarction (MI), stroke, or heart failure (HF). We made separate models to predict 10-year rates of first atherosclerotic cardiovascular disease (ASCVD), first fatal or nonfatal MI, first fatal or nonfatal stroke, new-onset HF, fatal ASCVD, fatal MI, fatal stroke, and all-cause mortality using established ASCVD risk factors. To limit overfitting, we used elastic net regularization with alpha = 0.75. We assessed the models for calibration, discrimination, and for correlations between predicted risks for different events. We also estimated the potential impact of varying treatment based on patients who are high risk for some ASCVD events, but not others. RESULTS: Our study included 24,505 people; 55.6% were women, and 20.7% were non-Hispanic Black. Our models had C-statistics between 0.75 for MI and 0.85 for HF, good calibration, and minimal overfitting. The models were least similar for fatal stroke and all MI (0.58). In 1,840 participants whose risk of MI but not stroke or all-cause mortality was in the top quartile, we estimate one blood pressure-lowering medication would have a 2.4% chance of preventing any ASCVD event per 10 years. A moderate-strength statin would have a 2.1% chance. In 1,039 participants who had top quartile risk of stroke but not MI or mortality, a blood pressure-lowering medication would have a 2.5% chance of preventing an event, but a moderate-strength statin, 1.6%. CONCLUSION: We developed risk scores for eight key clinical events and found that cardiovascular risk varies somewhat for different clinical events. Future work could determine if tailoring decisions by risk of separate events can improve care.

A proteomic analysis of atrial fibrillation in a prospective longitudinal cohort (AGES-Reykjavik study). - Jonmundsson, Thorarinn; Steindorsdottir, Anna E; Austin, Thomas R; Frick, Elisabet A; Axelsson, Gisli T; Launer, Lenore; Psaty, Bruce M; Loureiro, Joseph; Orth, Anthony P; Aspelund, Thor; Emilsson, Valur; Floyd, James S; et al. (Europace, 2023)
AIMS: Atrial fibrillation (AF) is associated with high risk of comorbidities and mortality. Our aim was to examine causal and predictive relationships between 4137 serum proteins and incident AF in the prospective population-based Age, Gene/Environment Susceptibility-Reykjavik (AGES-Reykjavik) study. METHODS AND RESULTS: The study included 4765 participants, of whom 1172 developed AF. Cox proportional hazards regression models were fitted for 4137 baseline protein measurements adjusting for known risk factors. Protein associations were tested for replication in the Cardiovascular Health Study (CHS). Causal relationships were examined in a bidirectional, two-sample Mendelian randomization analysis. The time-dependent area under the receiver operating characteristic curve (AUC)-statistic was examined as protein levels and an AF-polygenic risk score (PRS) were added to clinical risk models. The proteomic signature of incident AF consisted of 76 proteins, of which 63 (83%) were novel and 29 (38%) were replicated in CHS. The signature included both N-terminal prohormone of brain natriuretic peptide (NT-proBNP)-dependent (e.g. CHST15, ATP1B1, and SVEP1) and independent components (e.g. ASPN, AKR1B, and LAMA1/LAMB1/LAMC1). Nine causal candidates were identified (TAGLN, WARS, CHST15, CHMP3, COL15A1, DUSP13, MANBA, QSOX2, and SRL). The reverse causal analysis suggested that most AF-associated proteins were affected by the genetic liability to AF. N-terminal prohormone of brain natriuretic peptide improved the prediction of incident AF events close to baseline with further improvements gained by the AF-PRS at all time points. CONCLUSION: The AF proteomic signature includes biologically relevant proteins, some of which may be causal. It mainly reflects an NT-proBNP-dependent consequence of the genetic liability to AF. N-terminal prohormone of brain natriuretic peptide is a promising marker for incident AF in the short term, but risk assessment incorporating a PRS may improve long-term risk assessment.
Keywords: Atrial Fibrillation; Biomarkers; Endosomal Sorting Complexes Required for Transport; Humans; Natriuretic Peptide, Brain; Oxidoreductases Acting on Sulfur Group Donors; Peptide Fragments; Prognosis; Prospective Studies; Proteomics; Risk Factors

Proteomic prediction of incident heart failure and its main subtypes. - Emilsson, Valur; Jonsson, Brynjolfur G; Austin, Thomas R; Gudmundsdottir, Valborg; Axelsson, Gisli T; Frick, Elisabet A; Jonmundsson, Thorarinn; Steindorsdottir, Anna E; Loureiro, Joseph; Brody, Jennifer A; Aspelund, Thor; Launer, Lenore J; et al. (Eur J Heart Fail, 2023)
AIM: To examine the ability of serum proteins in predicting future heart failure (HF) events, including HF with reduced or preserved ejection fraction (HFrEF or HFpEF), in relation to event time, and with or without considering established HF-associated clinical variables. METHODS AND RESULTS: In the prospective population-based Age, Gene/Environment Susceptibility Reykjavik Study (AGES-RS), 440 individuals developed HF after their first visit with a median follow-up of 5.45 years. Among them, 167 were diagnosed with HFrEF and 188 with HFpEF. A least absolute shrinkage and selection operator regression model with nonparametric bootstrap were used to select predictors from an analysis of 4782 serum proteins, and several pre-established clinical parameters linked to HF. A subset of 8-10 distinct or overlapping serum proteins predicted different future HF outcomes, and C-statistics were used to assess discrimination, revealing proteins combined with a C-index of 0.80 for all incident HF, 0.78 and 0.80 for incident HFpEF or HFrEF, respectively. In the AGES-RS, protein panels alone encompassed the risk contained in the clinical information and improved the performance characteristics of prediction models based on NT-proBNP and clinical risk factors. Finally, the protein predictors performed particularly well close to the time of an HF event, an outcome that was replicated in the Cardiovascular Health Study (CHS). CONCLUSION: A small number of circulating proteins accurately predicted future HF in the AGES-RS cohort of older adults, and they alone encompass the risk information found in a collection of clinical data. Incident HF events were predicted up to eight years, with predictor performance significantly improving for events occurring less than one year ahead, a finding replicated in an external cohort study. This article is protected by copyright. All rights reserved.

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Boerwinkle, Eric; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

A statistical framework for powerful multi-trait rare variant analysis in large-scale whole-genome sequencing studies. - Li, Xihao; Chen, Han; Selvaraj, Margaret Sunitha; Van Buren, Eric; Zhou, Hufeng; Wang, Yuxuan; Sun, Ryan; McCaw, Zachary R; Yu, Zhi; Arnett, Donna K; Bis, Joshua C; Blangero, John; et al. (bioRxiv, 2023)
Large-scale whole-genome sequencing (WGS) studies have improved our understanding of the contributions of coding and noncoding rare variants to complex human traits. Leveraging association effect sizes across multiple traits in WGS rare variant association analysis can improve statistical power over single-trait analysis, and also detect pleiotropic genes and regions. Existing multi-trait methods have limited ability to perform rare variant analysis of large-scale WGS data. We propose MultiSTAAR, a statistical framework and computationally-scalable analytical pipeline for functionally-informed multi-trait rare variant analysis in large-scale WGS studies. MultiSTAAR accounts for relatedness, population structure and correlation among phenotypes by jointly analyzing multiple traits, and further empowers rare variant association analysis by incorporating multiple functional annotations. We applied MultiSTAAR to jointly analyze three lipid traits (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides) in 61,861 multi-ethnic samples from the Trans-Omics for Precision Medicine (TOPMed) Program. We discovered new associations with lipid traits missed by single-trait analysis, including rare variants within an enhancer of and an intergenic region on chromosome 1.

Time-to-Event Genome-Wide Association Study for Incident Cardiovascular Disease in People with Type 2 Diabetes Mellitus. - Kwak, Soo Heon; Hernandez-Cancela, Ryan B; DiCorpo, Daniel A; Condon, David E; Merino, Jordi; Wu, Peitao; Brody, Jennifer A; Yao, Jie; Guo, Xiuqing; Ahmadizar, Fariba; Meyer, Mariah; Sincan, Murat; et al. (medRxiv, 2023)
BACKGROUND: Type 2 diabetes mellitus (T2D) confers a two- to three-fold increased risk of cardiovascular disease (CVD). However, the mechanisms underlying increased CVD risk among people with T2D are only partially understood. We hypothesized that a genetic association study among people with T2D at risk for developing incident cardiovascular complications could provide insights into molecular genetic aspects underlying CVD. METHODS: From 16 studies of the Cohorts for Heart & Aging Research in Genomic Epidemiology (CHARGE) Consortium, we conducted a multi-ancestry time-to-event genome-wide association study (GWAS) for incident CVD among people with T2D using Cox proportional hazards models. Incident CVD was defined based on a composite of coronary artery disease (CAD), stroke, and cardiovascular death that occurred at least one year after the diagnosis of T2D. Cohort-level estimated effect sizes were combined using inverse variance weighted fixed effects meta-analysis. We also tested 204 known CAD variants for association with incident CVD among patients with T2D. RESULTS: A total of 49,230 participants with T2D were included in the analyses (31,118 European ancestries and 18,112 non-European ancestries) which consisted of 8,956 incident CVD cases over a range of mean follow-up duration between 3.2 and 33.7 years (event rate 18.2%). We identified three novel, distinct genetic loci for incident CVD among individuals with T2D that reached the threshold for genome-wide significance ( <5.0×10 ): rs147138607 (intergenic variant between and ) with a hazard ratio (HR) 1.23, 95% confidence interval (CI) 1.15 - 1.32, =3.6×10 , rs11444867 (intergenic variant near ) with HR 1.89, 95% CI 1.52 - 2.35, =9.9×10 , and rs335407 (intergenic variant between and ) HR 1.25, 95% CI 1.16 - 1.35, =1.5×10 . Among 204 known CAD loci, 32 were associated with incident CVD in people with T2D with <0.05, and 5 were significant after Bonferroni correction ( <0.00024, 0.05/204). A polygenic score of these 204 variants was significantly associated with incident CVD with HR 1.14 (95% CI 1.12 - 1.16) per 1 standard deviation increase ( =1.0×10 ). CONCLUSIONS: The data point to novel and known genomic regions associated with incident CVD among individuals with T2D. CLINICAL PERSPECTIVE: We conducted a large-scale multi-ancestry time-to-event GWAS to identify genetic variants associated with CVD among people with T2D. Three variants were significantly associated with incident CVD in people with T2D: rs147138607 (intergenic variant between and ), rs11444867 (intergenic variant near ), and rs335407 (intergenic variant between and ). A polygenic score composed of known CAD variants identified in the general population was significantly associated with the risk of CVD in people with T2D. There are genetic risk factors specific to T2D that could at least partially explain the excess risk of CVD in people with T2D.In addition, we show that people with T2D have enrichment of known CAD association signals which could also explain the excess risk of CVD.

Traditional and novel risk factors for incident aortic stenosis in community-dwelling older adults. - Massera, Daniele; Bartz, Traci M; Biggs, Mary L; Sotoodehnia, Nona; Reiner, Alexander P; Semba, Richard D; Gottdiener, John S; Psaty, Bruce M; Owens, David S; Kizer, Jorge R (Heart, 2023)
OBJECTIVES: Calcific aortic stenosis (AS) is the most common valvular disease in older adults, yet its risk factors remain insufficiently studied in this population. Such studies are necessary to enhance understanding of mechanisms, disease management and therapeutics. METHODS: The Cardiovascular Health Study is a population-based investigation of older adults that completed adjudication of incident AS over long-term follow-up. We evaluated traditional cardiovascular risk factors or disease, as well as novel risk factors from lipid, inflammatory and mineral metabolism pathways, in relation to incident moderate or severe AS (including AS procedures) and clinically significant AS (severe AS, including procedures). RESULTS: Of 5390 participants (age 72.9±5.6 years, 57.6% female, 12.5% black), 287 developed moderate or severe AS, and 175 clinically significant AS, during median follow-up of 13.1 years. After full adjustment, age (HR=1.66 per SD (95% CI=1.45, 1.91)), male sex (HR=1.41 (1.06, 1.87)), diabetes (HR=1.53 (1.10, 2.13)), coronary heart disease (CHD, HR=1.36 (1.01, 1.84)), lipoprotein-associated phospholipase-A (LpPLA) activity (HR=1.21 per SD (1.07, 1.37)) and sCD14 (HR=1.16 per SD (1.01, 1.34)) were associated with incident moderate/severe AS, while black race demonstrated an inverse association (HR=0.40 (0.24, 0.65)), and creatinine-based estimated glomerular filtration rate (eGFR) showed a U-shaped relationship. Findings were similar for clinically significant AS, although CHD and sCD14 fell short of significance, but interleukin-(IL) 6 showed a positive association. CONCLUSION: This comprehensive evaluation of risk factors for long-term incidence of AS identified associations for diabetes and prevalent CHD, LpPLA activity, sCD14 and IL-6, and eGFR. These factors may hold clues to biology, preventive efforts and potential therapeutics for those at highest risk.

Type 2 Diabetes Modifies the Association of CAD Genomic Risk Variants With Subclinical Atherosclerosis. - Hasbani, Natalie R; Westerman, Kenneth E; Heon Kwak, Soo; Chen, Han; Li, Xihao; DiCorpo, Daniel; Wessel, Jennifer; Bis, Joshua C; Sarnowski, Chloe; Wu, Peitao; Bielak, Lawrence F; Guo, Xiuqing; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of coronary artery disease (CAD), but questions remain about the underlying pathology. Identifying which CAD loci are modified by T2D in the development of subclinical atherosclerosis (coronary artery calcification [CAC], carotid intima-media thickness, or carotid plaque) may improve our understanding of the mechanisms leading to the increased CAD in T2D. METHODS: We compared the common and rare variant associations of known CAD loci from the literature on CAC, carotid intima-media thickness, and carotid plaque in up to 29 670 participants, including up to 24 157 normoglycemic controls and 5513 T2D cases leveraging whole-genome sequencing data from the Trans-Omics for Precision Medicine program. We included first-order T2D interaction terms in each model to determine whether CAD loci were modified by T2D. The genetic main and interaction effects were assessed using a joint test to determine whether a CAD variant, or gene-based rare variant set, was associated with the respective subclinical atherosclerosis measures and then further determined whether these loci had a significant interaction test. RESULTS: Using a Bonferroni-corrected significance threshold of <1.6×10, we identified 3 genes (, , and ) associated with CAC and 2 genes ( and ) associated with carotid intima-media thickness and carotid plaque, respectively, through gene-based rare variant set analysis. Both and also had significantly different associations for CAC in T2D cases versus controls. No significant interaction tests were identified through the candidate single-variant analysis. CONCLUSIONS: These results highlight T2D as an important modifier of rare variant associations in CAD loci with CAC.

Whole genome analysis of plasma fibrinogen reveals population-differentiated genetic regulators with putative liver roles. - Huffman, Jennifer E; Nicolas, Jayna; Hahn, Julie; Heath, Adam S; Raffield, Laura M; Yanek, Lisa R; Brody, Jennifer A; Thibord, Florian; Almasy, Laura; Bartz, Traci M; Bielak, Lawrence F; Bowler, Russell P; et al. (medRxiv, 2023)
UNLABELLED: Genetic studies have identified numerous regions associated with plasma fibrinogen levels in Europeans, yet missing heritability and limited inclusion of non-Europeans necessitates further studies with improved power and sensitivity. Compared with array-based genotyping, whole genome sequencing (WGS) data provides better coverage of the genome and better representation of non-European variants. To better understand the genetic landscape regulating plasma fibrinogen levels, we meta-analyzed WGS data from the NHLBI's Trans-Omics for Precision Medicine (TOPMed) program (n=32,572), with array-based genotype data from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium (n=131,340) imputed to the TOPMed or Haplotype Reference Consortium panel. We identified 18 loci that have not been identified in prior genetic studies of fibrinogen. Of these, four are driven by common variants of small effect with reported MAF at least 10% higher in African populations. Three ( , and signals contain predicted deleterious missense variants. Two loci, and , each harbor two conditionally distinct, non-coding variants. The gene region encoding the protein chain subunits ( ), contains 7 distinct signals, including one novel signal driven by rs28577061, a variant common (MAF=0.180) in African reference panels but extremely rare (MAF=0.008) in Europeans. Through phenome-wide association studies in the VA Million Veteran Program, we found associations between fibrinogen polygenic risk scores and thrombotic and inflammatory disease phenotypes, including an association with gout. Our findings demonstrate the utility of WGS to augment genetic discovery in diverse populations and offer new insights for putative mechanisms of fibrinogen regulation. KEY POINTS: Largest and most diverse genetic study of plasma fibrinogen identifies 54 regions (18 novel), housing 69 conditionally distinct variants (20 novel).Sufficient power achieved to identify signal driven by African population variant.Links to (1) liver enzyme, blood cell and lipid genetic signals, (2) liver regulatory elements, and (3) thrombotic and inflammatory disease.

Whole Genome Analysis of Venous Thromboembolism: the Trans-Omics for Precision Medicine Program. - Seyerle, Amanda A; Laurie, Cecelia A; Coombes, Brandon J; Jain, Deepti; Conomos, Matthew P; Brody, Jennifer; Chen, Ming-Huei; Gogarten, Stephanie M; Beutel, Kathleen M; Gupta, Namrata; Heckbert, Susan R; Jackson, Rebecca D; et al. (Circ Genom Precis Med, 2023)
Background Risk for venous thromboembolism has a strong genetic component. Whole genome sequencingfrom the Trans-Omics for Precision Medicine program allowed us to look for new associations, particularly rare variants missed by standard genome-wide association studies. Methods The 3793 cases and 7834 controls (11.6% of cases were Black, Hispanic/Latino, or Asian American) were analyzed using a single variant approach and an aggregate gene-based approach using our primary filter (included only loss-of-function and missense variants predicted to be deleterious) and our secondary filter (included all missense variants). Results Single variant analyses identified associations at 5 known loci. Aggregate gene-based analyses identified only (odds ratio, 6.2 for carriers of rare variants; =7.4×10) when using our primary filter. Employing our secondary variant filter led to a smaller effect size at (odds ratio, 3.8; =1.6×10), while excluding variants found only in rare isoforms led to a larger one (odds ratio, 7.5). Different filtering strategies improved the signal for 2 other known genes: became significant (minimum =1.8×10 with the secondary filter), while did not (minimum =4.4×10 with minor allele frequency <0.0005). Results were largely the same when restricting the analyses to include only unprovoked cases; however, one novel gene, , became significant (=4.4×10 using all missense variants with minor allele frequency <0.0005). Conclusions Here, we have demonstrated the importance of using multiple variant filtering strategies, as we detected additional genes when filtering variants based on their predicted deleteriousness, frequency, and presence on the most expressed isoforms. Our primary analyses did not identify new candidate loci; thus larger follow-up studies are needed to replicate the novel locus and to identify additional rare variation associated with venous thromboembolism.

Whole genome sequence analysis of apparent treatment resistant hypertension status in participants from the Trans-Omics for Precision Medicine program. - Armstrong, Nicole D; Srinivasasainagendra, Vinodh; Ammous, Farah; Assimes, Themistocles L; Beitelshees, Amber L; Brody, Jennifer; Cade, Brian E; Ida Chen, Yii-Der; Chen, Han; de Vries, Paul S; Floyd, James S; Franceschini, Nora; et al. (Front Genet, 2023)
Apparent treatment-resistant hypertension (aTRH) is characterized by the use of four or more antihypertensive (AHT) classes to achieve blood pressure (BP) control. In the current study, we conducted single-variant and gene-based analyses of aTRH among individuals from 12 Trans-Omics for Precision Medicine cohorts with whole-genome sequencing data. Cases were defined as individuals treated for hypertension (HTN) taking three different AHT classes, with average systolic BP ≥ 140 or diastolic BP ≥ 90 mmHg, or four or more medications regardless of BP ( = 1,705). A normotensive control group was defined as individuals with BP < 140/90 mmHg ( = 22,079), not on AHT medication. A second control group comprised individuals who were treatment responsive on one AHT medication with BP < 140/ 90 mmHg ( = 5,424). Logistic regression with kinship adjustment using the Scalable and Accurate Implementation of Generalized mixed models (SAIGE) was performed, adjusting for age, sex, and genetic ancestry. We assessed variants using SKAT-O in rare-variant analyses. Single-variant and gene-based tests were conducted in a pooled multi-ethnicity stratum, as well as self-reported ethnic/racial strata (European and African American). One variant in the known HTN locus, , was a top finding in the multi-ethnic analysis ( = 8.23E-07) for the normotensive control group [rs12476527, odds ratio (95% confidence interval) = 0.80 (0.74-0.88)]. This variant was replicated in the Vanderbilt University Medical Center's DNA repository data. Aggregate gene-based signals included the genes and . Additional work validating these loci in larger, more diverse populations, is warranted to determine whether these regions influence the pathobiology of aTRH.

WHOLE GENOME SEQUENCING ANALYSIS OF BODY MASS INDEX IDENTIFIES NOVEL AFRICAN ANCESTRY-SPECIFIC RISK ALLELE. - Zhang, Xinruo; Brody, Jennifer A; Graff, Mariaelisa; Highland, Heather M; Chami, Nathalie; Xu, Hanfei; Wang, Zhe; Ferrier, Kendra; Chittoor, Geetha; Josyula, Navya S; Li, Xihao; Li, Zilin; et al. (medRxiv, 2023)
Obesity is a major public health crisis associated with high mortality rates. Previous genome-wide association studies (GWAS) investigating body mass index (BMI) have largely relied on imputed data from European individuals. This study leveraged whole-genome sequencing (WGS) data from 88,873 participants from the Trans-Omics for Precision Medicine (TOPMed) Program, of which 51% were of non-European population groups. We discovered 18 BMI-associated signals ( < 5 × 10 ). Notably, we identified and replicated a novel low frequency single nucleotide polymorphism (SNP) in that was common in individuals of African descent. Using a diverse study population, we further identified two novel secondary signals in known BMI loci and pinpointed two likely causal variants in the and loci. Our work demonstrates the benefits of combining WGS and diverse cohorts in expanding current catalog of variants and genes confer risk for obesity, bringing us one step closer to personalized medicine.

Whole Genome Sequencing Based Analysis of Inflammation Biomarkers in the Trans-Omics for Precision Medicine (TOPMed) Consortium. - Jiang, Min-Zhi; Gaynor, Sheila M; Li, Xihao; Van Buren, Eric; Stilp, Adrienne; Buth, Erin; Wang, Fei Fei; Manansala, Regina; Gogarten, Stephanie M; Li, Zilin; Polfus, Linda M; Salimi, Shabnam; et al. (bioRxiv, 2023)
Inflammation biomarkers can provide valuable insight into the role of inflammatory processes in many diseases and conditions. Sequencing based analyses of such biomarkers can also serve as an exemplar of the genetic architecture of quantitative traits. To evaluate the biological insight, which can be provided by a multi-ancestry, whole-genome based association study, we performed a comprehensive analysis of 21 inflammation biomarkers from up to 38,465 individuals with whole-genome sequencing from the Trans-Omics for Precision Medicine (TOPMed) program. We identified 22 distinct single-variant associations across 6 traits - E-selectin, intercellular adhesion molecule 1, interleukin-6, lipoprotein-associated phospholipase A2 activity and mass, and P-selectin - that remained significant after conditioning on previously identified associations for these inflammatory biomarkers. We further expanded upon known biomarker associations by pairing the single-variant analysis with a rare variant set-based analysis that further identified 19 significant rare variant set-based associations with 5 traits. These signals were distinct from both significant single variant association signals within TOPMed and genetic signals observed in prior studies, demonstrating the complementary value of performing both single and rare variant analyses when analyzing quantitative traits. We also confirm several previously reported signals from semi-quantitative proteomics platforms. Many of these signals demonstrate the extensive allelic heterogeneity and ancestry-differentiated variant-trait associations common for inflammation biomarkers, a characteristic we hypothesize will be increasingly observed with well-powered, large-scale analyses of complex traits.

Association analysis of mitochondrial DNA heteroplasmic variants: methods and application. - Sun, Xianbang; Bulekova, Katia; Yang, Jian; Lai, Meng; Pitsillides, Achilleas N; Liu, Xue; Zhang, Yuankai; Guo, Xiuqing; Yong, Qian; Raffield, Laura M; Rotter, Jerome I; Rich, Stephen S; et al. (medRxiv, 2024)
We rigorously assessed a comprehensive association testing framework for heteroplasmy, employing both simulated and real-world data. This framework employed a variant allele fraction (VAF) threshold and harnessed multiple gene-based tests for robust identification and association testing of heteroplasmy. Our simulation studies demonstrated that gene-based tests maintained an appropriate type I error rate at α=0.001. Notably, when 5% or more heteroplasmic variants within a target region were linked to an outcome, burden-extension tests (including the adaptive burden test, variable threshold burden test, and z-score weighting burden test) outperformed the sequence kernel association test (SKAT) and the original burden test. Applying this framework, we conducted association analyses on whole-blood derived heteroplasmy in 17,507 individuals of African and European ancestries (31% of African Ancestry, mean age of 62, with 58% women) with whole genome sequencing data. We performed both cohort- and ancestry-specific association analyses, followed by meta-analysis on bothpooled samples and within each ancestry group. Our results suggest that mtDNA-Enco ded genes/regions are likely to exhibit varying rates in somatic aging, with the notably strong associations observed between heteroplasmy in the and genes ( <0.001) and advance aging by the Original Burden test. In contrast, SKAT identified significant associations ( <0.001) between diabetes and the aggregated effects of heteroplasmy in several protein-coding genes. Further research is warranted to validate these findings. In summary, our proposed statistical framework represents a valuable tool for facilitating association testing of heteroplasmy with disease traits in large human populations.

Familial Hypercholesterolemia Variant and Cardiovascular Risk in Individuals With Elevated Cholesterol. - Zhang, Yiyi; Dron, Jacqueline S; Bellows, Brandon K; Khera, Amit V; Liu, Junxiu; Balte, Pallavi P; Oelsner, Elizabeth C; Amr, Sami Samir; Lebo, Matthew S; Nagy, Anna; Peloso, Gina M; Natarajan, Pradeep; et al. (JAMA Cardiol, 2024)
IMPORTANCE: Familial hypercholesterolemia (FH) is a genetic disorder that often results in severely high low-density lipoprotein cholesterol (LDL-C) and high risk of premature coronary heart disease (CHD). However, the impact of FH variants on CHD risk among individuals with moderately elevated LDL-C is not well quantified. OBJECTIVE: To assess CHD risk associated with FH variants among individuals with moderately (130-189 mg/dL) and severely (≥190 mg/dL) elevated LDL-C and to quantify excess CHD deaths attributable to FH variants in US adults. DESIGN, SETTING, AND PARTICIPANTS: A total of 21 426 individuals without preexisting CHD from 6 US cohort studies (Atherosclerosis Risk in Communities study, Coronary Artery Risk Development in Young Adults study, Cardiovascular Health Study, Framingham Heart Study Offspring cohort, Jackson Heart Study, and Multi-Ethnic Study of Atherosclerosis) were included, 63 of whom had an FH variant. Data were collected from 1971 to 2018, and the median (IQR) follow-up was 18 (13-28) years. Data were analyzed from March to May 2023. EXPOSURES: LDL-C, cumulative past LDL-C, FH variant status. MAIN OUTCOMES AND MEASURES: Cox proportional hazards models estimated associations between FH variants and incident CHD. The Cardiovascular Disease Policy Model projected excess CHD deaths associated with FH variants in US adults. RESULTS: Of the 21 426 individuals without preexisting CHD (mean [SD] age 52.1 [15.5] years; 12 041 [56.2%] female), an FH variant was found in 22 individuals with moderately elevated LDL-C (0.3%) and in 33 individuals with severely elevated LDL-C (2.5%). The adjusted hazard ratios for incident CHD comparing those with and without FH variants were 2.9 (95% CI, 1.4-6.0) and 2.6 (95% CI, 1.4-4.9) among individuals with moderately and severely elevated LDL-C, respectively. The association between FH variants and CHD was slightly attenuated when further adjusting for baseline LDL-C level, whereas the association was no longer statistically significant after adjusting for cumulative past LDL-C exposure. Among US adults 20 years and older with no history of CHD and LDL-C 130 mg/dL or higher, more than 417 000 carry an FH variant and were projected to experience more than 12 000 excess CHD deaths in those with moderately elevated LDL-C and 15 000 in those with severely elevated LDL-C compared with individuals without an FH variant. CONCLUSIONS AND RELEVANCE: In this pooled cohort study, the presence of FH variants was associated with a 2-fold higher CHD risk, even when LDL-C was only moderately elevated. The increased CHD risk appeared to be largely explained by the higher cumulative LDL-C exposure in individuals with an FH variant compared to those without. Further research is needed to assess the value of adding genetic testing to traditional phenotypic FH screening.

Genetic drivers of heterogeneity in type 2 diabetes pathophysiology. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Melloni, Giorgio E M; Kanoni, Stavroula; Rayner, Nigel W; Bocher, Ozvan; et al. (Nature, 2024)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes and molecular mechanisms that are often specific to cell type. Here, to characterize the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study data from 2,535,601 individuals (39.7% not of European ancestry), including 428,452 cases of T2D. We identify 1,289 independent association signals at genome-wide significance (P < 5 × 10) that map to 611 loci, of which 145 loci are, to our knowledge, previously unreported. We define eight non-overlapping clusters of T2D signals that are characterized by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type-specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial cells and enteroendocrine cells. We build cluster-specific partitioned polygenic scores in a further 279,552 individuals of diverse ancestry, including 30,288 cases of T2D, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned polygenic scores are associated with coronary artery disease, peripheral artery disease and end-stage diabetic nephropathy across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings show the value of integrating multi-ancestry genome-wide association study data with single-cell epigenomics to disentangle the aetiological heterogeneity that drives the development and progression of T2D. This might offer a route to optimize global access to genetically informed diabetes care.

Genome-wide analysis in over 1 million individuals of European ancestry yields improved polygenic risk scores for blood pressure traits. - Keaton, Jacob M; Kamali, Zoha; Xie, Tian; Vaez, Ahmad; Williams, Ariel; Goleva, Slavina B; Ani, Alireza; Evangelou, Evangelos; Hellwege, Jacklyn N; Yengo, Loic; Young, William J; Traylor, Matthew; et al. (Nat Genet, 2024)
Hypertension affects more than one billion people worldwide. Here we identify 113 novel loci, reporting a total of 2,103 independent genetic signals (P < 5 × 10) from the largest single-stage blood pressure (BP) genome-wide association study to date (n = 1,028,980 European individuals). These associations explain more than 60% of single nucleotide polymorphism-based BP heritability. Comparing top versus bottom deciles of polygenic risk scores (PRSs) reveals clinically meaningful differences in BP (16.9 mmHg systolic BP, 95% CI, 15.5-18.2 mmHg, P = 2.22 × 10) and more than a sevenfold higher odds of hypertension risk (odds ratio, 7.33; 95% CI, 5.54-9.70; P = 4.13 × 10) in an independent dataset. Adding PRS into hypertension-prediction models increased the area under the receiver operating characteristic curve (AUROC) from 0.791 (95% CI, 0.781-0.801) to 0.826 (95% CI, 0.817-0.836, ∆AUROC, 0.035, P = 1.98 × 10). We compare the 2,103 loci results in non-European ancestries and show significant PRS associations in a large African-American sample. Secondary analyses implicate 500 genes previously unreported for BP. Our study highlights the role of increasingly large genomic studies for precision health research.

Genomic and phenotypic correlates of mosaic loss of chromosome Y in blood. - Jakubek, Yasminka A; Ma, Xiaolong; Stilp, Adrienne M; Yu, Fulong; Bacon, Jason; Wong, Justin W; Aguet, Francois; Ardlie, Kristin; Arnett, Donna; Barnes, Kathleen; Bis, Joshua C; Blackwell, Tom; et al. (medRxiv, 2024)
Mosaic loss of Y (mLOY) is the most common somatic chromosomal alteration detected in human blood. The presence of mLOY is associated with altered blood cell counts and increased risk of Alzheimer's disease, solid tumors, and other age-related diseases. We sought to gain a better understanding of genetic drivers and associated phenotypes of mLOY through analyses of whole genome sequencing of a large set of genetically diverse males from the Trans-Omics for Precision Medicine (TOPMed) program. This approach enabled us to identify differences in mLOY frequencies across populations defined by genetic similarity, revealing a higher frequency of mLOY in the European American (EA) ancestry group compared to those of Hispanic American (HA), African American (AA), and East Asian (EAS) ancestry. Further, we identified two genes ( and ) that harbor multiple rare, putatively deleterious variants associated with mLOY susceptibility, show that subsets of human hematopoietic stem cells are enriched for activity of mLOY susceptibility variants, and that certain alleles on chromosome Y are more likely to be lost than others.

The Gut Microbial Metabolite Trimethylamine N-oxide, Incident CKD, and Kidney Function Decline. - Wang, Meng; Tang, W H Wilson; Li, Xinmin S; de Oliveira Otto, Marcia C; Lee, Yujin; Lemaitre, Rozenn N; Fretts, Amanda; Nemet, Ina; Sotoodehnia, Nona; Sitlani, Colleen M; Budoff, Matthew; DiDonato, Joseph A; et al. (J Am Soc Nephrol, 2024)
BACKGROUND: Trimethylamine N-oxide (TMAO) is a gut microbiota-derived metabolite of dietary phosphatidylcholine and carnitine. Experimentally, TMAO causes kidney injury and tubulointerstitial fibrosis. Little is known about prospective associations between TMAO and kidney outcomes, especially incident CKD. We hypothesized that higher plasma TMAO levels would be associated with higher risk of incident CKD and greater rate of kidney function decline. METHODS: We included 10,564 participants from two community-based, prospective cohorts with estimated glomerular filtration rate (eGFR) ≥ 60 mL/min/1.73m2 to assess incident CKD. TMAO was measured using targeted mass spectrometry at baseline and one follow-up visit. Creatinine and Cystatin C were measured up to 4 times during follow-up and used to compute eGFR. Incident CKD was defined as an eGFR decline ≥ 30% from baseline and a resulting eGFR<60 ml/min/1.73 m2. Time-varying Cox models assessed the association of serial TMAO measures with incident CKD, adjusting for sociodemographic, lifestyle, diet, and cardiovascular disease risk factors. Linear mixed models assessed the association with annualized eGFR change in 10,009 participants with at least one follow-up eGFR measure without exclusions for baseline eGFR levels. RESULTS: During a median follow-up of 9.4 years (interquartile range: 9.1-11.6 years), 979 incident CKD events occurred. Higher TMAO levels associated with higher risk of incident CKD (2nd to 5th vs. 1st quintile HR[95%CI]= 1.65 [1.22-2.23], 1.68 [1.26-2.25], 2.28 [1.72-3.02], and 2.24[1.68-2.98], respectively) and greater annualized eGFR decline ( 2nd to 5th vs. 1st quintile annualized eGFR change= -0.21 [-0.32, -0.09], -0.17 [-0.29, -0.05], -0.35 [-0.47, -0.22], and -0.43[-0.56, -0.30], respectively) with monotonic dose-response relationships. These associations were consistent across different racial/ethnic groups examined. The association with eGFR decline was similar to or larger than that seen for established CKD risk factors including diabetes, per 10 mmHg of higher systolic blood pressure, per 10 years of older age, and Black race. CONCLUSIONS: In community-based US adults, higher serial measures of plasma TMAO were associated with higher risk of incident CKD and greater annualized kidney function decline.

Large-scale circulating proteome association study (CPAS) meta-analysis identifies circulating proteins and pathways predicting incident hip fractures. - Austin, Thomas R; Fink, Howard A; Jalal, Diana I; Törnqvist, Anna E; Bůzková, Petra; Barzilay, Joshua I; Lu, Tianyuan; Carbone, Laura; Gabrielsen, Maiken E; Grahnemo, Louise; Hveem, Kristian; Jonasson, Christian; et al. (J Bone Miner Res, 2024)
Hip fractures are associated with significant disability, high cost, and mortality. However, the exact biological mechanisms underlying susceptibility to hip fractures remain incompletely understood. In an exploratory search of the underlying biology as reflected through the circulating proteome, we performed a comprehensive Circulating Proteome Association Study (CPAS) meta-analysis for incident hip fractures. Analyses included 6430 subjects from two prospective cohort studies (Cardiovascular Health Study and Trøndelag Health Study) with circulating proteomics data (aptamer-based 5 K SomaScan version 4.0 assay; 4979 aptamers). Associations between circulating protein levels and incident hip fractures were estimated for each cohort using age and sex-adjusted Cox regression models. Participants experienced 643 incident hip fractures. Compared with the individual studies, inverse-variance weighted meta-analyses yielded more statistically significant associations, identifying 23 aptamers associated with incident hip fractures (conservative Bonferroni correction 0.05/4979, P < 1.0 × 10-5). The aptamers most strongly associated with hip fracture risk corresponded to two proteins of the growth hormone/insulin growth factor system (GHR and IGFBP2), as well as GDF15 and EGFR. High levels of several inflammation-related proteins (CD14, CXCL12, MMP12, ITIH3) were also associated with increased hip fracture risk. Ingenuity pathway analysis identified reduced LXR/RXR activation and increased acute phase response signaling to be overrepresented among those proteins associated with increased hip fracture risk. These analyses identified several circulating proteins and pathways consistently associated with incident hip fractures. These findings underscore the usefulness of the meta-analytic approach for comprehensive CPAS in a similar manner as has previously been observed for large-scale human genetic studies. Future studies should investigate the underlying biology of these potential novel drug targets.

A Large-Scale Genome-Wide Study of Gene-Sleep Duration Interactions for Blood Pressure in 811,405 Individuals from Diverse Populations. - Nagarajan, Pavithra; Winkler, Thomas W; Bentley, Amy R; Miller, Clint L; Kraja, Aldi T; Schwander, Karen; Lee, Songmi; Wang, Wenyi; Brown, Michael R; Morrison, John L; Giri, Ayush; O'Connell, Jeffrey R; et al. (medRxiv, 2024)
Although both short and long sleep duration are associated with elevated hypertension risk, our understanding of their interplay with biological pathways governing blood pressure remains limited. To address this, we carried out genome-wide cross-population gene-by-short-sleep and long-sleep duration interaction analyses for three blood pressure traits (systolic, diastolic, and pulse pressure) in 811,405 individuals from diverse population groups. We discover 22 novel gene-sleep duration interaction loci for blood pressure, mapped to genes involved in neurological, thyroidal, bone metabolism, and hematopoietic pathways. Non-overlap between short sleep (12) and long sleep (10) interactions underscores the plausibility of distinct influences of both sleep duration extremes in cardiovascular health. With several of our loci reflecting specificity towards population background or sex, our discovery sheds light on the importance of embracing granularity when addressing heterogeneity entangled in gene-environment interactions, and in therapeutic design approaches for blood pressure management.

Multi-omics and pathway analyses of genome-wide associations implicate regulation and immunity in verbal declarative memory performance. - Mei, Hao; Simino, Jeannette; Li, Lianna; Jiang, Fan; Bis, Joshua C; Davies, Gail; Hill, W David; Xia, Charley; Gudnason, Vilmundur; Yang, Qiong; Lahti, Jari; Smith, Jennifer A; et al. (Alzheimers Res Ther, 2024)
BACKGROUND: Uncovering the functional relevance underlying verbal declarative memory (VDM) genome-wide association study (GWAS) results may facilitate the development of interventions to reduce age-related memory decline and dementia. METHODS: We performed multi-omics and pathway enrichment analyses of paragraph (PAR-dr) and word list (WL-dr) delayed recall GWAS from 29,076 older non-demented individuals of European descent. We assessed the relationship between single-variant associations and expression quantitative trait loci (eQTLs) in 44 tissues and methylation quantitative trait loci (meQTLs) in the hippocampus. We determined the relationship between gene associations and transcript levels in 53 tissues, annotation as immune genes, and regulation by transcription factors (TFs) and microRNAs. To identify significant pathways, gene set enrichment was tested in each cohort and meta-analyzed across cohorts. Analyses of differential expression in brain tissues were conducted for pathway component genes. RESULTS: The single-variant associations of VDM showed significant linkage disequilibrium (LD) with eQTLs across all tissues and meQTLs within the hippocampus. Stronger WL-dr gene associations correlated with reduced expression in four brain tissues, including the hippocampus. More robust PAR-dr and/or WL-dr gene associations were intricately linked with immunity and were influenced by 31 TFs and 2 microRNAs. Six pathways, including type I diabetes, exhibited significant associations with both PAR-dr and WL-dr. These pathways included fifteen MHC genes intricately linked to VDM performance, showing diverse expression patterns based on cognitive status in brain tissues. CONCLUSIONS: VDM genetic associations influence expression regulation via eQTLs and meQTLs. The involvement of TFs, microRNAs, MHC genes, and immune-related pathways contributes to VDM performance in older individuals.
Keywords: Aged; Cognition; Genome-Wide Association Study; Humans; Memory; MicroRNAs; Multiomics; Polymorphism, Single Nucleotide

Plasma proteomic signature of human longevity. - Liu, Xiaojuan; Axelsson, Gisli Thor; Newman, Anne B; Psaty, Bruce M; Boudreau, Robert M; Wu, Chenkai; Arnold, Alice M; Aspelund, Thor; Austin, Thomas R; Gardin, Julius M; Siggeirsdottir, Kristin; Tracy, Russell P; et al. (Aging Cell, 2024)
The identification of protein targets that exhibit anti-aging clinical potential could inform interventions to lengthen the human health span. Most previous proteomics research has been focused on chronological age instead of longevity. We leveraged two large population-based prospective cohorts with long follow-ups to evaluate the proteomic signature of longevity defined by survival to 90 years of age. Plasma proteomics was measured using a SOMAscan assay in 3067 participants from the Cardiovascular Health Study (discovery cohort) and 4690 participants from the Age Gene/Environment Susceptibility-Reykjavik Study (replication cohort). Logistic regression identified 211 significant proteins in the CHS cohort using a Bonferroni-adjusted threshold, of which 168 were available in the replication cohort and 105 were replicated (corrected p value <0.05). The most significant proteins were GDF-15 and N-terminal pro-BNP in both cohorts. A parsimonious protein-based prediction model was built using 33 proteins selected by LASSO with 10-fold cross-validation and validated using 27 available proteins in the validation cohort. This protein model outperformed a basic model using traditional factors (demographics, height, weight, and smoking) by improving the AUC from 0.658 to 0.748 in the discovery cohort and from 0.755 to 0.802 in the validation cohort. We also found that the associations of 169 out of 211 proteins were partially mediated by physical and/or cognitive function. These findings could contribute to the identification of biomarkers and pathways of aging and potential therapeutic targets to delay aging and age-related diseases.

A polygenic risk score of atrial fibrillation improves prediction of lifetime risk for heart failure. - Alkis, Taryn; Luo, Xi; Wall, Katherine; Brody, Jennifer; Bartz, Traci; Chang, Patricia P; Norby, Faye L; Hoogeveen, Ron C; Morrison, Alanna C; Ballantyne, Christie M; Coresh, Josef; Boerwinkle, Eric; et al. (ESC Heart Fail, 2024)
AIMS: Heart failure (HF) has shared genetic architecture with its risk factors: atrial fibrillation (AF), body mass index (BMI), coronary heart disease (CHD), systolic blood pressure (SBP), and type 2 diabetes (T2D). We aim to assess the association and risk prediction performance of risk-factor polygenic risk scores (PRSs) for incident HF and its subtypes in bi-racial populations. METHODS AND RESULTS: Five PRSs were constructed for AF, BMI, CHD, SBP, and T2D in White participants of the Atherosclerosis Risk in Communities (ARIC) study. The associations between PRSs and incident HF and its subtypes were assessed using Cox models, and the risk prediction performance of PRSs was assessed using C statistics. Replication was performed in the ARIC study Black and Cardiovascular Health Study (CHS) White participants. In 8624 ARIC study Whites, 1922 (31% cumulative incidence) HF cases developed over 30 years of follow-up. PRSs of AF, BMI, and CHD were associated with incident HF (P < 0.001), where PRS showed the strongest association [hazard ratio (HR): 1.47, 95% confidence interval (CI): 1.41-1.53]. Only the addition of PRS to the ARIC study HF risk equation improved C statistics for 10 year risk prediction from 0.812 to 0.829 (∆C: 0.017, 95% CI: 0.009-0.026). The PRS was associated with both incident HF with reduced ejection fraction (HR: 1.43, 95% CI: 1.27-1.60) and incident HF with preserved ejection fraction (HR: 1.46, 95% CI: 1.33-1.62). The associations between PRS and incident HF and its subtypes, as well as the improved risk prediction, were replicated in the ARIC study Blacks and the CHS Whites (P < 0.050). Protein analyses revealed that N-terminal pro-brain natriuretic peptide and other 98 proteins were associated with PRS . CONCLUSIONS: The PRS was associated with incident HF and its subtypes and had significant incremental value over an established HF risk prediction equation.

Role of Polyunsaturated Fat in Modifying Cardiovascular Risk Associated With Family History of Cardiovascular Disease: Pooled De Novo Results From 15 Observational Studies. - Laguzzi, Federica; Åkesson, Agneta; Marklund, Matti; Qian, Frank; Gigante, Bruna; Bartz, Traci M; Bassett, Julie K; Birukov, Anna; Campos, Hannia; Hirakawa, Yoichiro; Imamura, Fumiaki; Jäger, Susanne; et al. (Circulation, 2024)
BACKGROUND: It is unknown whether dietary intake of polyunsaturated fatty acids (PUFA) modifies the cardiovascular disease (CVD) risk associated with a family history of CVD. We assessed interactions between biomarkers of low PUFA intake and a family history in relation to long-term CVD risk in a large consortium. METHODS: Blood and tissue PUFA data from 40 885 CVD-free adults were assessed. PUFA levels ≤25th percentile were considered to reflect low intake of linoleic, alpha-linolenic, and eicosapentaenoic/docosahexaenoic acids (EPA/DHA). Family history was defined as having ≥1 first-degree relative who experienced a CVD event. Relative risks with 95% CI of CVD were estimated using Cox regression and meta-analyzed. Interactions were assessed by analyzing product terms and calculating relative excess risk due to interaction. RESULTS: After multivariable adjustments, a significant interaction between low EPA/DHA and family history was observed (product term pooled RR, 1.09 [95% CI, 1.02-1.16]; =0.01). The pooled relative risk of CVD associated with the combined exposure to low EPA/DHA, and family history was 1.41 (95% CI, 1.30-1.54), whereas it was 1.25 (95% CI, 1.16-1.33) for family history alone and 1.06 (95% CI, 0.98-1.14) for EPA/DHA alone, compared with those with neither exposure. The relative excess risk due to interaction results indicated no interactions. CONCLUSIONS: A significant interaction between biomarkers of low EPA/DHA intake, but not the other PUFA, and a family history was observed. This novel finding might suggest a need to emphasize the benefit of consuming oily fish for individuals with a family history of CVD.
Keywords: Animals; Biomarkers; Cardiovascular Diseases; Docosahexaenoic Acids; Fatty Acids, Omega-3; Risk Factors

Time-to-Event Genome-Wide Association Study for Incident Cardiovascular Disease in People With Type 2 Diabetes. - Kwak, Soo Heon; Hernandez-Cancela, Ryan B; DiCorpo, Daniel A; Condon, David E; Merino, Jordi; Wu, Peitao; Brody, Jennifer A; Yao, Jie; Guo, Xiuqing; Ahmadizar, Fariba; Meyer, Mariah; Sincan, Murat; et al. (Diabetes Care, 2024)
OBJECTIVE: To identify genetic risk factors for incident cardiovascular disease (CVD) among people with type 2 diabetes (T2D). RESEARCH DESIGN AND METHODS: We conducted a multiancestry time-to-event genome-wide association study for incident CVD among people with T2D. We also tested 204 known coronary artery disease (CAD) variants for association with incident CVD. RESULTS: Among 49,230 participants with T2D, 8,956 had incident CVD events (event rate 18.2%). We identified three novel genetic loci for incident CVD: rs147138607 (near CACNA1E/ZNF648, hazard ratio [HR] 1.23, P = 3.6 × 10-9), rs11444867 (near HS3ST1, HR 1.89, P = 9.9 × 10-9), and rs335407 (near TFB1M/NOX3, HR 1.25, P = 1.5 × 10-8). Among 204 known CAD loci, 5 were associated with incident CVD in T2D (multiple comparison-adjusted P < 0.00024, 0.05/204). A standardized polygenic score of these 204 variants was associated with incident CVD with HR 1.14 (P = 1.0 × 10-16). CONCLUSIONS: The data point to novel and known genomic regions associated with incident CVD among individuals with T2D.

X-chromosome and kidney function: evidence from a multi-trait genetic analysis of 908,697 individuals reveals sex-specific and sex-differential findings in genes regulated by androgen response elements. - Scholz, Markus; Horn, Katrin; Pott, Janne; Wuttke, Matthias; Kühnapfel, Andreas; Nasr, M Kamal; Kirsten, Holger; Li, Yong; Hoppmann, Anselm; Gorski, Mathias; Ghasemi, Sahar; Li, Man; et al. (Nat Commun, 2024)
X-chromosomal genetic variants are understudied but can yield valuable insights into sexually dimorphic human traits and diseases. We performed a sex-stratified cross-ancestry X-chromosome-wide association meta-analysis of seven kidney-related traits (n = 908,697), identifying 23 loci genome-wide significantly associated with two of the traits: 7 for uric acid and 16 for estimated glomerular filtration rate (eGFR), including four novel eGFR loci containing the functionally plausible prioritized genes ACSL4, CLDN2, TSPAN6 and the female-specific DRP2. Further, we identified five novel sex-interactions, comprising male-specific effects at FAM9B and AR/EDA2R, and three sex-differential findings with larger genetic effect sizes in males at DCAF12L1 and MST4 and larger effect sizes in females at HPRT1. All prioritized genes in loci showing significant sex-interactions were located next to androgen response elements (ARE). Five ARE genes showed sex-differential expressions. This study contributes new insights into sex-dimorphisms of kidney traits along with new prioritized gene targets for further molecular research.
Keywords: Androgens; Chromosomes, Human, X; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kidney; Male; Polymorphism, Single Nucleotide; Response Elements; Tetraspanins